Longitudinal study of anthropometry in Fontan survivors: Pediatric Heart Network Fontan study - Lambert, L.M.; McCrindle, B.W.; Pemberton, V.L.; Hollenbeck-Pringle, D.; Atz, A.M.; Ravishankar, C.; Campbell, M.J.; Dunbar-Masterson, C.; Uzark, K.; Rolland, M.; Trachtenberg, F.L.; Menon, S.C.; et al. (American Heart Journal, 2020)
Background: Growth abnormalities in single-ventricle survivors may reduce quality of life (QoL) and exercise capacity. Methods: This multicenter, longitudinal analysis evaluated changes in height and body mass index (BMI) compared to population norms and their relationship to mortality, ventricular morphology, QoL, and exercise capacity in the Pediatric Heart Network Fontan studies. Results: Fontan 1 (F1) included 546 participants (12 ± 3.4 years); Fontan 2 (F2), 427 (19 ± 3.4 years); and Fontan 3 (F3), 362 (21 ± 3.5 years), with ~60% male at each time point. Height z-score was −0.67 ± −1.27, −0.60 ± 1.34, and− 0.43 ± 1.14 at F1-F3, lower compared to norms at all time points (P ≤ .001). BMI z-score was similar to population norms. Compared to survivors, participants who died had lower height z-score (P ≤ .001). Participants with dominant right ventricle (n = 112) had lower height z-score (P ≤ .004) compared to dominant left (n = 186) or mixed (n = 64) ventricular morphologies. Higher height z-score was associated with higher Pediatric Quality of Life Inventory for the total score (slope = 2.82 ± 0.52; P ≤ .001). Increase in height z-score (F1 to F3) was associated with increased oxygen consumption (slope = 2.61 ± 1.08; P = .02), whereas, for participants >20 years old, an increase in BMI (F1 to F3) was associated with a decrease in oxygen consumption (slope = −1.25 ± 0.33; P ≤ .001). Conclusions: Fontan survivors, especially those with right ventricular morphology, are shorter when compared to the normal population but have similar BMI. Shorter stature was associated with worse survival. An increase in height z-score over the course of the study was associated with better QoL and exercise capacity; an increase in BMI was associated with worse exercise capacity. © 2020 Elsevier Inc.

Reduction of Inflammation by High-Dose Methylprednisolone Does not Attenuate Oxidative Stress in Children Undergoing Bidirectional Glenn Procedure With or Without Aortic Arch or Pulmonary Arterial Repair - Keski-Nisula, J.; Arvola, O.; Jahnukainen, T.; Andersson, S.; Pesonen, E. (Journal of Cardiothoracic and Vascular Anesthesia, 2020)
Objective: Corticosteroids attenuate an inflammatory reaction in pediatric heart surgery. Inflammation is a source of free oxygen radicals. Children with a cyanotic heart defect are prone to increased radical stress during heart surgery. The authors hypothesized that high-dose methylprednisolone reduces inflammatory reaction and thereby also oxidative stress in infants with a univentricular heart defect undergoing the bidirectional Glenn procedure. Design: A double-blind, placebo-controlled, randomized clinical trial. Setting: Operating room and pediatric intensive care unit of a university hospital. Participants: The study comprised 29 infants undergoing the bidirectional Glenn procedure with or without aortic arch or pulmonary arterial repair. Interventions: After anesthesia induction, the patients received intravenously either 30 mg/kg of methylprednisolone (n = 15) or the same volume of saline as placebo (n = 14). Measurements and Main Results: Plasma interleukin-6, interleukin-8, interleukin-10 (biomarkers of inflammation), and 8-hydroxydeoxyguanosine concentrations (a biomarker of oxidative stress) were measured at the following 4 time points: preoperatively, during cardiopulmonary bypass, after protamine administration, and 6 hours postoperatively. The study parameters did not differ between the study groups preoperatively. Methylprednisolone reduced the proinflammatory cytokines interleukin-6 and interleukin-8 and increased the anti-inflammatory cytokine interleukin-10 postoperatively. Despite reduced inflammation, there were no differences in 8-hydroxydeoxyguanosine between the methylprednisolone and placebo groups. Conclusions: The proinflammatory reaction and increase in free radical stress were not interrelated during congenital heart surgery in cyanotic infants with a univentricular heart defect undergoing the bidirectional Glenn procedure. High-dose methylprednisolone was ineffective in attenuating free radical stress. © 2019 Elsevier Inc.
Keywords: bidirectional Glenn procedure; congenital heart defect; infant; inflammation; methylprednisolone; radical stress

Health related quality of life in children with congenital heart disease that undergo cardiac surgery during their first year of life - Saavedra, M.J.; Eymann, A.; Pérez, L.; Busaniche, J.; Nápoli, N.; Marantz, P.; Llera, J. (Archivos argentinos de pediatria, 2020)
INTRODUCTION: Advances in diagnostic methods, surgical techniques and postoperative intensive care have significantly increased the survival rates for children with congenital heart disease. In this context, long term sequelae acquired greater relevance. Health-related quality of life (HRQOL) is a concept that helps to measure the impact of chronic diseases. The purpose of the current study was to describe HRQOL in children with congenital heart disease that undergo cardiac surgery during their first year of life. METHODS: A cross-sectional observational study was conducted between August 2017 and December 2018 at a University General Hospital. PedsQL 4.0 Generic Core Scales were used. Children with congenital heart disease between 2 and 4 years old who had cardiac surgery during their first year of life and healthy children were included. Scores were compared with T-test or Wilcoxon according to the observed distribution. p value < 0.05 was considered significant. RESULTS: A total of 31 children with congenital heart disease (26 % with a single ventricle) and 62 healthy children were enrolled. The first surgery was in the neonatal period in 61.3 %. Our study showed no statistical differences (p = 0.10) between HRQOL Total Scale Score of children with congenital heart disease compared to healthy children. However, lower scores were observed with statistically significant differences in social (p = 0.0092) and school (p = 0.0001) scales. CONCLUSIONS: Our cohort of children diagnosed with congenital heart disease has a global quality of life comparable with healthy children except in social and school functioning scales. Sociedad Argentina de Pediatría. Introducción. En las últimas décadas, el desarrollo de métodos diagnósticos, técnicas quirúrgicas y cuidados intensivos, aumentó la sobrevida de los niños con cardiopatía congénita. En este contexto, las secuelas a largo plazo adquirieron mayor relevancia. La calidad de vida relacionada con la salud mide el impacto de las enfermedades crónicas. Nuestro objetivo fue describir la calidad de vida relacionada con la salud en pacientes con cardiopatía congénita operados durante el primer año de vida. Población y métodos. Estudio observacional, transversal, realizado entre agosto de 2017 y diciembre de 2018 en un hospital general universitario. Se utilizó el cuestionario PedsQL 4.0, versión genérica. Se incluyeron pacientes de entre 2 y 4 años con cardiopatía congénita operados durante el primer año de vida y niños sanos. Se compararon los resultados con T-Test o Wilcoxon según la distribución observada. Se consideró significativo el valor de p < 0,05. Resultados. Se incluyeron 31 pacientes. El 26 % tenían ventrículo único. La primera cirugía fue, en un 61,3 %, en el período neonatal. No hubo diferencia (p = 0,10) entre la calidad de vida relacionada con la salud global de la población con cardiopatía congénita y de los niños sanos. Sin embargo, se observaron puntajes más bajos con diferencia estadísticamente significativa en las esferas social (p = 0,0092) y escolar (p = 0,0001). Conclusiones. Nuestra cohorte de niños con cardiopatía congénita tiene una calidad de vida global comparable con la de los niños sanos, excepto en las escalas correspondientes a funcionamiento social y escolar.
Keywords: cardiac surgery; chronic disease; congenital heart disease; health related quality of life

Impaired histomorphology might provoke cell cycle regulators alteration in thymus of children with various congenital heart defects - Mestanova, V.; Varga, I.; Adamkov, M. (Medical Hypotheses, 2020)
Thymus, as a primary site of appropriate adaptive immunity formation, is an essential organ in face of a self-tolerance as well as a potential menace from impairment of body integrity. Due to vital selection processes during differentiation and maturation of T lymphocytes, control over cell survival and programmed cell death must be orchestrated in detail. Indeed, thymus is highly sensitive to wide spectrum of stressors that initiate acute structural changes. Hypoxia, one of the most common complications in congenital heart defects (CHDs) patients, provokes stress-induced thymus involution. Disrupted embryolonic development of thymus in association with congenital heart defects, may negatively affect physiological immune mechanisms. We propose that detailed analysis of thymic morphology could critically contribute to unveil the pathophysiology of diseases associated with disrupted adaptive immunity in children with heterogeneous congenital heart diseases. © 2020 Elsevier Ltd
Keywords: Apoptosis; Congenital heart defects; Histomorphology; Immunohistochemistry; Proliferation; Thymus

Brief version of the coping health inventory for parents (CHIP) among family caregivers of children with chronic diseases - Toledano-Toledano, F.; Moral De La Rubia, J.; McCubbin, L.D.; Cauley, B.; Luna, D. (Health and Quality of Life Outcomes, 2020)
Background: The Coping Health Inventory for Parents (CHIP) has demonstrated good psychometric properties in several language forms and has been used to assess the coping behaviors of families facing disease. However, the CHIP has not been validated in Mexico among families of children with chronic conditions, where it could be useful for research and intervention. The objectives of this instrumental study were to obtain a version of the CHIP for the Spanish language in Mexico, establish the factor structure of the Mexican version of the CHIP, probe its internal consistency reliability, and assess its concurrent construct validity. Methods: A nonprobability sample of 405 family caregivers of children with chronic diseases responded to a battery of measurement instruments that included the CHIP, the Beck Anxiety Inventory, and the Beck Depression Inventory. The sample was randomly divided into two parts. In one subsample (190 participants), an exploratory factor analysis was performed using a principal component analysis and oblique rotation. In the second subsample (215 participants), a confirmatory factor analysis was performed using maximum likelihood estimation. Results: The scale was reduced to 16 items (CHIP-16) with factorial loads greater than.50. The empirical criteria used to determine the number of factors converged on the following five factors: belief and trust (McDonald ω =.85), spouse/partner relationship (ω =.79), home care (ω =.77), family involvement (ω =.75), and security/stability (ω =.79). The overall internal consistency was good (ω =.88). The five-factor model showed acceptable fit indices and high parsimony. The mean CHIP-16 scores and the Spouse/partner relationship scores among the caregivers with anxiety were greater than those among the caregivers without anxiety. The mean home-care scores among the women were greater than those among men. Conclusions: The 16-item version of the CHIP showed good internal consistency and construct validity; thus, the CHIP-16 is a useful instrument for measuring and assessing coping in family caregivers of children with chronic diseases. © 2020 The Author(s).
Keywords: Anxiety; Coping; Depression; Family caregivers; Mexico; Psychometrics

Surgical palliation or primary transplantation for aortic valve atresia - Stackhouse, K.A.; McCrindle, B.W.; Blackstone, E.H.; Rajeswaran, J.; Kirklin, J.K.; Bailey, L.L.; Jacobs, M.L.; Tchervenkov, C.I.; Jacobs, J.P.; Pettersson, G.B.; Congenital Heart Surgeons' Society (Journal of Thoracic and Cardiovascular Surgery, 2020)
Objective: The study objective was to describe the surgical pathway progression through adolescence of an inception cohort of neonates with aortic valve atresia managed initially with surgical palliation or primary transplantation, comparing survival and self-reported health-related quality of life. Methods: From 1994 to 2000, 565 neonates with aortic atresia were admitted to 26 Congenital Heart Surgeons' Society hospitals and followed annually for vital status. Initial management included surgical palliation (n = 453) and primary cardiac transplantation (n = 68). PedsQL health-related quality of life questionnaires were sent cross-sectionally to a subgroup of 198 patients alive at previous follow-up, with 80 responses. Results: Risk of death was initially high for both treatment strategies. However, compared with initial surgical palliation, survival with primary transplantation, including wait-list mortality, was greater and persisted long-term (65% vs 40% at 15 years; P =.002). Survival after secondary transplantation (48% at 9 years) was lower than after primary transplantation (74%). Health-related quality of life total score was lower overall than that of the general adolescent population (71 ± 16 vs 84 ± 13; P =.0001; normal = 100), but similar to that of adolescents with chronic diseases. It was similar in the surgical palliation and primary transplantation groups (70 ± 16 vs 75 ± 15; P =.3). Patients who received surgical palliation reported more symptoms (76 ± 15 vs 63 ± 18; P =.02). Conclusions: Patients receiving primary heart transplantation for aortic atresia in 1994 to 2000 experienced better survival, fewer symptoms, and equivalent quality of life compared with those undergoing initial surgical palliation. Notwithstanding the limited availability of neonatal and infant donor hearts, primary transplantation may be considered for those neonates with risk factors predictive of exceptionally poor survival after surgical palliation. © 2019 The American Association for Thoracic Surgery
Keywords: aortic atresia; Fontan; neonatal; quality of life; surgical palliation; survival; transplantation

Efficacy of phosphodiesterase type 5 inhibitors in univentricular congenital heart disease: the SV-INHIBITION study design - Amedro, P.; Gavotto, A.; Abassi, H.; Picot, M.-C.; Matecki, S.; Malekzadeh-Milani, S.; Levy, M.; Ladouceur, M.; Ovaert, C.; Aldebert, P.; Thambo, J.-B.; Fraisse, A.; et al. (ESC Heart Failure, 2020)
Aims: In univentricular hearts, selective lung vasodilators such as phosphodiesterase type 5 (PDE5) inhibitors would decrease pulmonary resistance and improve exercise tolerance. However, the level of evidence for the use of PDE5 inhibitors in patients with a single ventricle (SV) remains limited. We present the SV-INHIBITION study rationale, design, and methods. Methods and results: The SV-INHIBITION trial is a nationwide multicentre, randomized, double blind, placebo-controlled, Phase III study, aiming to evaluate the efficacy of sildenafil on the ventilatory efficiency during exercise, in teenagers and adult patients (>15 years old) with an SV. Patients with a mean pulmonary arterial pressure >15 mmHg and a trans-pulmonary gradient >5 mmHg, measured by cardiac catheterization, will be eligible. The primary outcome is the variation of the VE/VCO2 slope, measured by a cardiopulmonary exercise test, between baseline and 6 months of treatment. A total of 50 patients are required to observe a decrease of 5 ± 5 points in the VE/VCO2 slope, with a power of 90% and an alpha risk of 5%. The secondary outcomes are clinical outcomes, oxygen saturation, 6 min walk test, SV function, NT-proBNP, peak VO2, stroke volume, mean pulmonary arterial pressure, trans-pulmonary gradient, SF36 quality of life score, safety, and acceptability. Conclusions: The SV-INHIBITION study aims to answer the question whether PDE5 inhibitors should be prescribed in patients with an SV. This trial has been built focusing on the three levels of research defined by the World Health Organization: disability (exercise tolerance), deficit (SV function), and handicap (quality of life). © 2020 The Authors. ESC Heart Failure published by John Wiley & Sons Ltd on behalf of European Society of Cardiology
Keywords: Congenital heart defect; Exercise capacity; Pulmonary hypertension; Pulmonary vasodilator; Sildenafil; Single ventricle

Qualitative Exploration of the Pediatric Heart Failure Experience for Development of a Patient-Reported Outcome Measure - Chen, C.; Ridgeway, J.L.; Bocell, F.D.; Tanenbaum, M.L.; Hood, K.K.; Behnken, E.; Schmidt, J.; Hanes, S.J.; Saha, A.; Caldwell, B.; Tarver, M.; Peiris, V.; et al. (The Journal of heart and lung transplantation : the official publication of the International Society for Heart Transplantation, 2020)
PURPOSE: No valid, reliable, and publicly available patient-reported outcome measure (PROM) exists to assess the pediatric heart failure (HF) experience. We sought to understand this experience in order to develop a PROM that can reliably capture and track outcomes for adolescent patients. METHODS: Semi-structured individual or group interviews were conducted at two pediatric HF and transplant centers in the US. Patient ages 12-21 who had a record of symptomatic HF in the past 2 years were eligible to participate. Caregivers of participants were also eligible. Symptom experiences and their impact on daily activities were explored. Transcripts were analyzed by members of a multidisciplinary team using thematic analysis. RESULTS: 16 patients and 9 caregivers participated. 22 completed individual interviews in-person or by phone, and 3 participated in a web-based focus group. Patient participants were 31% male, and median age was 16.5 years. 31% (n=5) had HF from cardiomyopathy and 69% (n=11) had HF due to congenital heart disease, with 7 having single ventricle physiology. 5 participants were interviewed post-transplant. Preliminary analysis revealed consistent themes across interviews. Common symptoms included fatigue, shortness of breath, and chest discomfort. Symptoms limited ability to perform daily tasks (e.g. climbing stairs at school), participate in certain extracurricular activities (e.g. sports, dance) and keep up with peers. Participants described social and emotional impacts from being treated differently by others due to surgical scars, medical devices, or functional limitations. They also reported burden of frequent medical visits and treatments, and expressed worry and uncertainty about the need for future medical interventions. Caregivers reported similar impacts on patient function and wellbeing, and they further described social exclusion by peers and anxiety about the future (e.g. limited life expectancy or career limitations). CONCLUSION: The unique personal and social impacts of HF symptoms on adolescents and young adults may necessitate development of unique items for PRO measurement in this population. These findings will be used to draft a developmentally-relevant PROM that will subsequently be tested in this population and validated for use in clinical care and regulatory evaluation of new medical products. Copyright © 2020. Published by Elsevier Inc.

Heart rate variability is depressed in the early transitional period for newborns with complex congenital heart disease - Mulkey, S.B.; Govindan, R.; Metzler, M.; Swisher, C.B.; Hitchings, L.; Wang, Y.; Baker, R.; Larry Maxwell, G.; Krishnan, A.; du Plessis, A.J. (Clinical Autonomic Research, 2020)
Purpose: To compare early changes in autonomic nervous system (ANS) tone between newborns with complex congenital heart disease (CHD) and newborns without CHD. Methods: We performed a case–control study of heart rate variability (HRV) in newborns with complex CHD [transposition of the great arteries (TGA) or hypoplastic left heart syndrome (HLHS)] and low-risk control newborns without CHD. Cases with CHD were admitted following birth to a pediatric cardiac intensive care unit and had archived continuous ECG data. Control infants were prospectively enrolled at birth. ECG data in cases and controls were analyzed for HRV in the time and frequency domains at 24 h of age. We analyzed the following HRV metrics: alpha short (αs), alpha long (αL), root mean square short and long (RMSs and RMSL), low-frequency (LF) power, normalized LF (nLF), high-frequency (HF) power, and normalized HF (nHF). We used ANOVA to compare HRV metrics between groups and to control for medication exposures. Results: HRV data from 57 infants with CHD (TGA, n = 33 and HLHS, n = 24) and from 29 controls were analyzed. The HRV metrics αS, RMSL, LF, and nLF were significantly lower in infants with CHD than in the controls. Due to the effect of normalization, nHF was higher in CHD infants (P < 0.0001), although absolute HF was lower (P = 0.0461). After adjusting for medications, αS and nLF remained lower and nHF higher in newborns with CHD (P < 0.0005). Conclusions: Infants with complex CHD have depressed autonomic balance in the early postnatal period, which may complicate the fetal–neonatal transition. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Autonomic nervous system; Congenital heart disease; Heart rate variability; Newborn

Congenital absence of the left atrial appendage - Vaideeswar, P.; Karande, S. (Journal of Postgraduate Medicine, 2020)

Health-Related Quality of Life in Children, Adolescents, and Adults With a Fontan Circulation: A Meta-Analysis - Marshall, K.H.; D'Udekem, Y.; Sholler, G.F.; Opotowsky, A.R.; Costa, D.S.J.; Sharpe, L.; Celermajer, D.S.; Winlaw, D.S.; Newburger, J.W.; Kasparian, N.A. (Journal of the American Heart Association, 2020)
Background People with a Fontan circulation experience a range of physical, psychosocial and neurodevelopmental challenges alongside, or caused by, their cardiac condition, with significant consequences for health-related quality of life (HRQOL). We meta-analyzed HRQOL outcomes reported by people with a Fontan circulation or their proxies and evaluated predictors of poorer HRQOL. Methods and Results Six electronic databases were searched for peer-reviewed, English-language articles published before March 2019. Standardized mean differences (SMD) were calculated using fixed and random-effects models. Fifty articles reporting on 29 unique studies capturing HRQOL outcomes for 2793 people with a Fontan circulation and 1437 parent-proxies were analyzed. HRQOL was lower in individuals with a Fontan circulation compared with healthy referents or normative samples (SMD, -0.92; 95% CI, -1.36 to -0.48; P<0.001). Lower scores were reported across all HRQOL domains, with the largest differences found for physical (SMD, -0.90; 95% CI, -1.13 to -0.67; P<0.001) and school/work functioning (SMD, -0.71; 95% CI, -0.90 to -0.52; P<0.001). Meta-regression analyses found no significant predictors of self-reported physical functioning, but older age at Fontan operation was associated with poorer emotional functioning (β=-0.124; P=0.004), and diagnosis of hypoplastic left heart was associated with poorer social functioning (β=-0.007; P=0.048). Sensitivity analyses showed use of the PedsQL Core Module was associated with lower HRQOL scores compared with the Short-Form Health Survey-36. Conclusions HRQOL outcomes for people with a Fontan circulation are lower than the general population. Optimal care acknowledges the lifelong impact of the Fontan circulation on HRQOL and offers targeted strategies to improve outcomes for this growing population.
Keywords: chronic illness; congenital heart disease; Fontan circulation; health‐related quality of life; mental health; psychological stress

Association of Maternal Psychological Distress with in Utero Brain Development in Fetuses with Congenital Heart Disease - Wu, Y.; Kapse, K.; Jacobs, M.; Niforatos-Andescavage, N.; Donofrio, M.T.; Krishnan, A.; Vezina, G.; Wessel, D.; Du Plessis, A.; Limperopoulos, C. (JAMA Pediatrics, 2020)
Importance: Prenatal maternal psychological distress can result in detrimental mother and child outcomes. Maternal stress increases with receipt of a prenatal diagnosis of fetal congenital heart disease (CHD); however, the association between maternal stress and the developing brain in fetuses with CHD is unknown. Objective: To determine the association of maternal psychological distress with brain development in fetuses with CHD. Design, Setting, and Participants: This longitudinal, prospective, case-control study consecutively recruited 48 pregnant women carrying fetuses with CHD and 92 healthy volunteers with low-risk pregnancies from the Children's National Health System between January 2016 and September 2018. Data were analyzed between January 2016 and June 2019. Exposures: Fetal CHD and maternal stress, anxiety, and depression. Main Outcomes and Measures: Maternal stress, anxiety, and depression were measured using the Perceived Stress Scale, Spielberger State-Trait Anxiety Inventory, and Edinburgh Postnatal Depression Scale, respectively. Volumes of fetal total brain, cerebrum, left and right hippocampus, cerebellum, and brainstem were determined from 3-dimensionally reconstructed T2-weighted magnetic resonance imaging (MRI) scans. Results: This study included 223 MRI scans from 140 fetuses (74 MRIs from 48 fetuses with CHD and 149 MRIs from 92 healthy fetuses) between 21 and 40 weeks' gestation. Among 48 women carrying fetuses with CHD, 31 (65%) tested positive for stress, 21 (44%) for anxiety, and 14 (29%) for depression. Among 92 pregnant women carrying healthy fetuses, 25 (27%) tested positive for stress, 24 (26%) for anxiety, and 8 (9%) for depression. Depression scores were higher among 17 women carrying fetuses with single-ventricle CHD vs 31 women carrying fetuses with 2-ventricle CHD (3.8; 95% CI, 0.3 to 7.3). Maternal stress and anxiety were associated with smaller left hippocampal (stress: -0.003 cm3; 95% CI, -0.005 to -0.001 cm3), right hippocampal (stress: -0.004; 95% CI, -0.007 to -0.002; trait anxiety: -0.003; 95% CI, -0.005 to -0.001), and cerebellar (stress: -0.06; 95% CI, -0.09 to -0.02) volumes only among women with fetal CHD. Impaired hippocampal regions were noted in the medial aspect of left hippocampal head and inferior aspect of right hippocampal head and body. Impaired cerebellar regions were noted in the anterior superior aspect of vermal and paravermal regions and the left cerebellar lobe. Conclusions and Relevance: These findings suggested that psychological distress among women carrying fetuses with CHD is prevalent and is associated with impaired fetal cerebellar and hippocampal development. These data underscore the importance of universal screening for maternal psychological distress, integrated prenatal mental health support, and targeted early cognitive-behavioral interventions given that stress is a potentially modifiable risk factor in this high-risk population.. © 2020 American Medical Association. All rights reserved.

Assessment of antiplatelet therapy response in pediatric patients following cardiac surgery by microfluidic assay - Kapileshwarkar, Y.; Gelmini, L.; Tseng, Y.-S.; Jackson, T.; Gao, X.; Richards, K.; Dokas, M.; Walters, H., III; Hines, P.C. (Progress in Pediatric Cardiology, 2020)
Introduction: Anti-platelet therapies, like aspirin, are routinely used following many surgical repairs for congenital heart disease to prevent life-threatening thrombotic complications. Optimal dosing is not well studied and determination of real-time dose response to prophylactic aspirin is not routinely performed due to blood volume requirements and poor predictive value of existing platelet function assays (PFAs). Our objective was to study platelet function and thrombosis in post-operative cardiac patients under physiologic shear conditions using a novel collagen-coated microfluidic thrombosis assay (MTA) compared to a standard whole blood aggregometry (WBA) assay before and after clinically and experimentally administered aspirin therapy. Methods: We recruited congenital heart surgical patients with post-operative indications for aspirin therapy at the Children's Hospital of Michigan. Samples of 1.8 mL blood were drawn within 24 h of initiating aspirin (D0) and 24 to 48 h after initiating aspirin (D1). Blood samples were split for use in the MTA and the WBA. The MTA sample was run through collagen coated microfluidic channels at shear stress of 10 dyne/cm2 and pulse frequency of 1.67 Hz to simulate physiologic flow conditions. Each sample was run under untreated conditions (reflects the study subject's endogenous platelet function, D0, D1) and following exogenous aspirin administration (reflects maximum theoretical platelet response to aspirin, +eASA). The kinetics of thrombus formation was assessed as area percent of signal intensity (total fluorescent intensity, TFI) of thrombosis at 6 &10 min and as area under curve (AUC) for MTA and as AUC and impedance at 6 min for WBA. Results: Results from MTA and WBA on pre- and post-aspirin blood samples collected from 18 subjects, with and without exogenously added aspirin, were analyzed in this study. Fold changes for AUC were calculated for each test and were compared using Wilcoxon signed rank test; this showed no statistically significant difference. Three of the patients were found to have no response to endogenous or exogenous aspirin. Conclusions: We observed that measured platelet function is variable and potential sources of variability could be sample source, timing of sample from bypass, platelet count, transfusions and others. Standard aspirin doses might not be adequate for patients who are at high risk of thrombosis. In this study, we demonstrate the feasibility of employing microfluidic thrombosis assay to assess real time clinical platelet function in the cardiac ICU setting. Microfluidic assays provide real time assessment of platelet function under physiologic flow conditions and might be helpful with optimizing aspirin doses. Further studies on larger cohorts are required to validate this possibility. © 2020 Elsevier B.V.

Global, regional, and national burden of congenital heart disease, 1990–2017: a systematic analysis for the Global Burden of Disease Study 2017 - Zimmerman, M.S.; Smith, A.G.C.; Sable, C.A.; Echko, M.M.; Wilner, L.B.; Olsen, H.E.; Atalay, H.T.; Awasthi, A.; Bhutta, Z.A.; Boucher, J.L.; Castro, F.; Cortesi, P.A.; et al. (The Lancet Child and Adolescent Health, 2020)
Background: Previous congenital heart disease estimates came from few data sources, were geographically narrow, and did not evaluate congenital heart disease throughout the life course. Completed as part of the Global Burden of Diseases, Injuries, and Risk Factors Study 2017, this study aimed to provide comprehensive estimates of congenital heart disease mortality, prevalence, and disability by age for 195 countries and territories from 1990 to 2017. Methods: Mortality estimates were generated for aggregate congenital heart disease and non-fatal estimates for five subcategories (single ventricle and single ventricle pathway congenital heart anomalies; severe congenital heart anomalies excluding single ventricle heart defects; critical malformations of great vessels, congenital valvular heart disease, and patent ductus arteriosus; ventricular septal defect and atrial septal defect; and other congenital heart anomalies), for 1990 through to 2017. All available global data were systematically analysed to generate congenital heart disease mortality estimates (using Cause of Death Ensemble modelling) and prevalence estimates (DisMod-MR 2·1). Systematic literature reviews of all types of congenital anomalies to capture information on prevalence, associated mortality, and long-term health outcomes on congenital heart disease informed subsequent disability estimates. Findings: Congenital heart disease caused 261 247 deaths (95% uncertainty interval 216 567–308 159) globally in 2017, a 34·5% decline from 1990, with 180 624 deaths (146 825–214 178) being among infants (aged <1 years). Congenital heart disease mortality rates declined with increasing Socio-demographic Index (SDI); most deaths occurred in countries in the low and low-middle SDI quintiles. The prevalence rates of congenital heart disease at birth changed little temporally or by SDI, resulting in 11 998 283 (10 958 658–13 123 888) people living with congenital heart disease globally, an 18·7% increase from 1990 to 2017, and causing a total of 589 479 (287 200–973 359) years lived with disability. Interpretation: Congenital heart disease is a large, rapidly emerging global problem in child health. Without the ability to substantially alter the prevalence of congenital heart disease, interventions and resources must be used to improve survival and quality of life. Our findings highlight the large global inequities in congenital heart disease and can serve as a starting point for policy changes to improve screening, treatment, and data collection. Funding: Bill & Melinda Gates Foundation. © 2020 The Author(s). Published by Elsevier Ltd. This is an Open Access article under the CC BY 4.0 license

Evidence of Systemic Absorption of Enteral Budesonide in Patients with Fontan-Associated Protein-Losing Enteropathy - Roberts, R.O., III; Di Maria, M.V.; Brigham, D.; Hsu, S. (Pediatric Cardiology, 2020)
To evaluate for evidence of systemic glucocorticoid absorption in cases of Fontan-associated protein-losing enteropathy (PLE) treated with enteral budesonide, we reviewed the charts of 27 patients with Fontan-associated PLE followed at Children’s Hospital Colorado from 2005 to 2018. Cases were excluded for lack of budesonide thserapy or a treatment duration of less than 6 months. Charts were examined by two endocrinologists for review of prior biochemical endocrine evaluations, alterations in linear growth, and physical exam findings consistent with steroid excess. Twelve patients met inclusion criteria. Eight had prior documented cortisol screening. Three patients were tested while on treatment with a median fasting AM cortisol of 0.9 mcg/dL; two of these had a concomitantly measured ACTH, both below the detectable limit. Five patients were tested while weaning or having discontinued budesonide, with a median fasting AM cortisol of 9.1 mcg/dL. Eleven patients had decreases in height velocity associated with starting budesonide. Six patients had documentation of cushingoid features by an endocrinologist. In this cohort of children treated with budesonide for PLE following Fontan, clinical signs of systemic glucocorticoid absorption were frequent. Cortisol secretion was suppressed while on therapy, with adrenal recovery noted once budesonide was discontinued. Growth failure and cushingoid features were common findings. While these findings should be confirmed in larger cohorts, we recommend that the evaluation for systemic absorption of exogenous steroids be considered in patients treated with long-term enteral budesonide given the potential risk for adrenal crisis in times of physiologic stressors. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Adrenal suppression; Budesonide; Fontan; Protein-losing enteropathy

Health-related quality of life for children and adolescents in school age with hypoplastic left heart syndrome: A single-centre study - Oberhuber, R.D.; Huemer, S.; Mair, R.; Sames-Dolzer, E.; Kreuzer, M.; Tulzer, G. (Cardiology in the Young, 2020)
Data from neurological and radiological research show an abnormal neurological development in patients treated for hypoplastic left heart syndrome. Thus, the aim of this study was to survey the quality of life scores in comparison with healthy children and children with other heart diseases (mild, moderate, and severe heart defects, heart defects in total). Children with hypoplastic left heart syndrome (aged 6.3-16.9 years) under compulsory education requirements, who were treated at the Children's Heart Center Linz between 1997 and 2009 (n = 74), were surveyed. Totally, 41 children and 44 parents were examined prospectively by psychologists according to Pediatric Quality of Life Inventory, a health-related quality of life measurement. The results of the self-assessments of health-related quality of life on a scale of 1-100 showed a wide range, from a minimum of 5.00 (social functioning) to a maximum of 100 (physical health-related summary scores, emotional functioning, school functioning), with a total score of 98.44. The parents' assessments (proxy) were quite similar, showing a range from 10 (social functioning) up to 100. Adolescent hypoplastic left heart syndrome patients rated themselves on the same level as healthy youths and youths with different heart diseases. The results show that patients with hypoplastic left heart syndrome aged 6-16 years can be successfully supported and assisted in their psychosocial development even if they show low varying physical and psychosocial parameters. The finding that adolescent hypoplastic left heart syndrome patients estimated themselves similar to healthy individuals suggests that they learnt to cope with a severe heart defect. © The Author(s) 2020. Published by Cambridge University Press.
Keywords: Adolescence; children; health-related quality of life; hypoplastic left heart syndrome; long-term follow-up

Covid19: Potential cardiovascular issues in pediatric patients - Bertoncelli, D.; Guidarini, M.; Della Greca, A.; Ratti, C.; Falcinella, F.; Iovane, B.; Luigi Dutto, M.; Caffarelli, C.; Tchana, B. (Acta Biomedica, 2020)
Summary. The novel severe acute respiratory syndrome coronavirus 2 (SARS-COV 2) has rapidly spread worldwide with increasing hospitalization and mortality rate. Ongoing studies and accumulated data are detailing the features and the effects of the new coronavirus disease 19 (COVID 19) in the adult population, and cardiovascular involvement is emerging as the most significant and life-threatening complication, with an increased risk of morbidity and mortality in patients with underlying cardiovascular disease. At present, though the limited data on the effects of COVID 19 in pediatric patients, children seem to count for a little proportion of SARS-COV 2 infection, and present with less severe disease and effects However infants and toddlers are at risk of developing critical course. The disease has a range of clinical presentations in children, for which the potential need for further investigation of myocardial injury and cardiovascular issues should be kept in mind to avoid misdiagnosing severe clinical entities. Overlapping with Kawasaki disease is a concern, particularly the incomplete and atypical form. We aim to summarize the initial considerations and potential cardiovascular implications of COVID-19 for children and patients with congenital heart disease. (www.actabiomedica.it). © Mattioli 1885.
Keywords: Cardiovascular; Children; Congenital heart diseases; COVID-19; Kawasaki disease; Myocarditis

Early Integration of Palliative Care in Families of Children with Single Ventricle Congenital Heart Defects: A Quality Improvement Project to Enhance Family Support - Davis, J.A.M.; Bass, A.; Humphrey, L.; Texter, K.; Garee, A. (Pediatric Cardiology, 2020)
Children with single ventricle congenital heart defects (SVCHD) experience a significant risk of early mortality throughout their lifespan, particularly during their first year of life. Due to the intense care needed for these children and families, pediatric palliative care (PPC) team consults should be routine; however, medical staff are often reluctant to broach the idea of PPC to families. The involvement of PPC for many carries with it an association to end-of-life (EOL) care. Setting the standard of PPC involvement from the time of admission for the first palliative surgery led to increased family support, decreased days to consult, improved acceptance and communication. The purpose of this article is to describe a quality improvement project of early integration of PPC with families of children with SVCHD. Lessons learned will be presented, including the resources needed and the barriers encountered in assimilating PPC into the standard of care for all patients with SVCHD. The single ventricle (SV) and PPC teams collaborated to enhance the support given to SV families. Education was initiated with cardiology and PPC providers to understand the goal of consistent PPC consults beginning after birth for patients with SVCHD. Parents were educated during fetal consultation regarding the involvement of the PPC team. The SV team ensured compliance with the PPC initiative by identifying eligible patients and requesting consult orders from the primary providers. PPC consultation increased significantly over the 40 month study period to nearly 100% compliance for children with SVCHD who are undergoing pre-Fontan surgery. In addition, mean days to consult decreased dramatically during the study to a current average of 3 days into the patient’s hospitalization; the data likely suggest that more PPC consults were routinely ordered versus urgently placed for unexpected complications. Data indicate that patients are being followed by the PPC team at an earlier age and stage in their SV journey which allows for more opportunity to provide meaningful support to these patients and families. The early involvement of the PPC team for children with SV physiology was operationally feasible and was accepted by families, thus allowing PPC providers to establish a therapeutic relationship early in the disease trajectory with the family. It allowed more continuity throughout the SV journey in a proactive fashion rather than a reactive manner. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Cardiac; Collaboration; End-of-life; Palliative; Pediatric; Single ventricle

Translation of the Frailty Paradigm from Older Adults to Children with Cardiac Disease - Panchangam, C.; White, D.A.; Goudar, S.; Birnbaum, B.; Malloy-Walton, L.; Gross-Toalson, J.; Reid, K.J.; Shirali, G.; Parthiban, A. (Pediatric Cardiology, 2020)
Children and adolescents with cardiac disease (CCD) have significant morbidity and lower quality of life. However, there are no broadly applicable tools similar to the frailty score as described in the elderly, to define functional phenotype in terms of physical capability and psychosocial wellbeing in CCD. The purpose of this study is to investigate the domains of the frailty in CCD. We prospectively recruited CCD (8–17.5 years old, 70% single ventricle, 27% heart failure, 12% pulmonary hypertension; NYHA classes I, II and III) and age and gender matched healthy controls (total n = 56; CCD n = 34, controls n = 22; age 12.6 ± 2.6 years; 39.3% female). We measured the five domains of frailty: slowness, weakness, exhaustion, body composition and physical activity using developmentally appropriate methods. Age and gender-based population norms were used to obtain Z scores and percentiles for each measurement. Two-tailed t-tests were used to compare the two groups. The CCD group performed significantly worse in all five domains of frailty compared to healthy controls. Slowness: 6-min walk test with Z score −3.9 ± 1.3 vs −1.4 ± 1.3, p < 0.001; weakness: handgrip strength percentile 18.9 ± 20.9 vs 57.9 ± 26.0, p < 0.001; exhaustion: multidimensional fatigue scale percentile 63.7 ± 13.5 vs 83.3 ± 14.4, p < 0.001; body composition: height percentile 43.4 ± 29.5 vs 71.4 ± 25.2, p < 0.001, weight percentile 46.0 ± 36.0 vs 70.9 ± 24.3, p = 0.006, BMI percentile 48.4 ± 35.5 vs 66.9 ± 24.2, p = 0.04, triceps skinfold thickness 41.0 ± 24.0 vs 54.4 ± 22.1, p = 0.04; physical activity: pediatric activity questionnaire score 2 ± 0.6 vs 2.7 ± 0.6, p < 0.001. The domains of frailty can be quantified in children using developmentally appropriate methods. CCD differ significantly from controls in all five domains, supporting the concept of quantifying the domains of frailty. Larger longitudinal studies are needed to study frailty in CCD and examine if it predicts adverse health outcomes. Clinical Trial Registration: The ClinicalTrials.gov identification number is NCT02999438. https://clinicaltrials.gov/ct2/show/NCT02999438. © 2020, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Cardiomyopathy; Children with heart disease; Congenital heart disease; Fontan; Frailty; Heart failure; Pulmonary hypertension; Quality and outcomes

Dobutamine stress testing in patients with Fontan circulation augmented by biomechanical modeling - Ruijsink, B.; Zugaj, K.; Wong, J.; Pushparajah, K.; Hussain, T.; Moireau, P.; Razavi, R.; Chapelle, D.; Chabiniok, R. (PLoS ONE, 2020)
Understanding (patho)physiological phenomena and mechanisms of failure in patients with Fontan circulation—a surgically established circulation for patients born with a functionally single ventricle—remains challenging due to the complex hemodynamics and high inter-patient variations in anatomy and function. In this work, we present a biomechanical model of the heart and circulation to augment the diagnostic evaluation of Fontan patients with early-stage heart failure. The proposed framework employs a reduced-order model of heart coupled with a simplified circulation including venous return, creating a closed-loop system. We deploy this framework to augment the information from data obtained during combined cardiac catheterization and magnetic resonance exams (XMR), performed at rest and during dobutamine stress in 9 children with Fontan circulation and 2 biventricular controls. We demonstrate that our modeling framework enables patient-specific investigation of myocardial stiffness, contractility at rest, contractile reserve during stress and changes in vascular resistance. Hereby, the model allows to identify key factors underlying the pathophysiological response to stress in these patients. In addition, the rapid personalization of the model to patient data and fast simulation of cardiac cycles make our framework directly applicable in a clinical workflow. We conclude that the proposed modeling framework is a valuable addition to the current clinical diagnostic XMR exam that helps to explain patient-specific stress hemodynamics and can identify potential mechanisms of failure in patients with Fontan circulation. © 2020 Ruijsink et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Influence of Offset on Hemodynamics of Intra-atrial Conduit Fontan's Procedure and Its Clinical Implications - Hu, J.; Wang, Q.; Tong, Z.; Shen, J.; Liu, J.; Sun, Y.; Zhang, H. (Thoracic and Cardiovascular Surgeon, 2020)
Background The desirable distance, defined as offset, between the central line of the superior vena cava (SVC) and the intra-atrial conduit after an intra-atrial conduit (IAC) Fontan's procedure remained unclear. We compared the hemodynamic features using virtual surgery with different offset designs in our study. Methods Three-dimensional models of IAC Fontan's procedure were reconstructed according to the magnetic resonance imagings (MRIs) of three patients, then four models for each patient with different offsets equaling 100, 67, 33, and 0% of the diameter of the IVC were reconstructed. Computational fluid dynamics (CFD) were performed in each model to predict the best hemodynamic features, including streamlines of blood flow, wall shear stress (WSS), energy loss (EL), and the hepatic flow distribution (HFD) ratio. Results Comprehensive evaluation of WSS, EL, and HFD revealed than an offset of 33% presents the best hemodynamic performance among the three patients modeled. In patient A, an offset of 33% resulted in the best HFD (left pulmonary artery/right pulmonary artery [LPA/RPA] = 35/65%). In patient B, the best trade-off between HFD (35/65%), and WSS was achieved with an offset of 33%. In patient C, EL peaked at an offset of 0% and significantly dropped at an offset of 33% with a desirable HFD (60/40%). Conclusions We verified that the offset distance influences hemodynamic performance in IAC Fontan's procedure. Considering several hemodynamic parameters, the best trade-offs between hemorheology, pulmonary perfusion, and energy efficiency were achieved at an offset of 33%. This distance should be taken into consideration and optimized during the surgical planning for the IAC Fontan's procedure. © 2020 Georg Thieme Verlag KG Stuttgart New York.
Keywords: bioengineering; cardiac; CHD; congenital heart disease; pulmonary arteries/veins

Clinical outcome of prenatally suspected cardiac rhabdomyomas of the fetus - Altmann, J.; Kiver, V.; Henrich, W.; Weichert, A. (Journal of perinatal medicine, 2019)
Background The main objective of this retrospective analysis in a large tertiary center was the clinical outcome of prenatally diagnosed cardiac rhabdomyomas as well as the identification of factors influencing fetal prognosis. Methods A total of 45 cases of fetuses with prenatally suspected rhabdomyoma and their clinical outcome were analyzed retrospectively. A review of the literature was also performed. Results In five cases, after a tuberous sclerosis complex (TSC) mutation had been confirmed, termination of pregnancy was chosen. In 30 cases postnatal data were available. In 93% TSC was confirmed clinically or by mutational analysis. Two thirds of fetuses presented with multiple tumor while one third presented with a solitary tumor. In two fetuses mild pericardial effusions were observed. Another three fetuses presented with extrasystoles prenatally. No hydrops fetalis or fetal perinatal demise were observed. After birth 41% of the children suffered from arrhythmia including supra- and ventricular tachycardia, Wolff-Parkinson-White syndrome and atrioventricular block. One child received a Fontan procedure with Glenn anastomosis. Another child with a dilatative cardiomyopathy and a left ventricular ejection fraction of 15% died. Fifty-two percent of the children with TSC suffered from epilepsy ranging from absence epilepsy and West syndrome to generalized seizures with a frequency of up to 40 per day. Two children underwent neurosurgery to remove the epileptogenic focus. One child suffered from TSC and Lesch-Nyhan disease. In another case Beckwith-Wiedemann syndrome was identified as the causative disorder. Conclusion Rhabdomyoma are rare, benign tumors. There is an association with TSC. In the majority of cases rhabdomyoma are not hemodynamically relevant and do not increase in size. The quality of life of affected patients is impaired particularly due to epilepsy and psychomotor retardation.
Keywords: Beckwith-Wiedemann syndrome; cardiac rhabdomyoma; cranial tuber; Lesch-Nyhan disease; tuberous sclerosis complex

Early Neurodevelopmental Outcomes in Children with Hypoplastic Left Heart Syndrome and Related Anomalies After Hybrid Procedure - Khalid, O.M.; Harrison, T.M. (Pediatric Cardiology, 2019)
The hybrid strategy is one approach to single ventricle palliation. In this study, we reported neurodevelopment at 12 months for two cohorts of children managed with the hybrid and clinical factors associated with neurodevelopment in the entire sample. We performed a retrospective study of children with single ventricle who had undergone a neonatal hybrid procedure. One group included infants with hypoplastic left heart syndrome (HLHS); another group included infants with non-HLHS single ventricle. Neurodevelopment was assessed with 12-month Bayley III. Parametric and non-parametric statistics were used for analysis. Nine infants with HLHS and 15 with non-HLHS were identified. Abnormal neurodevelopment was identified in 11 of 24 (46%), primarily motor (46%). Development did not differ between groups. In the whole sample, higher lactate levels were associated with lower cognitive scores (p = 0.04). Fewer mechanical ventilation days were associated with higher cognitive scores (p = 0.05) after Stage 1 and higher motor scores after Stage 2. Shorter ICU length of stay (p = 0.01), shorter hospital length of stay (p = 0.01), and fewer complications (p = 0.01) after stage 2 were associated with higher motor scores. Higher cognitive (p = 0.02) and language (p = 0.002) scores were associated with higher weight at 12 months. In the largest cohort of single ventricle children treated with neonatal hybrid palliation yet reported, significant neurodevelopmental impairment was identified. No differences in neurodevelopment were found between children with HLHS and those with non-HLHS variants. A multicenter trial is needed to test differences in neurodevelopment between hybrid and Norwood approaches. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Congenital heart disease; Hybrid procedure; Hypoplastic left heart syndrome; Neurodevelopmental outcome

Percutaneous embolization of lymphatic fistulae as treatment for protein-losing enteropathy and plastic bronchitis in patients with failing Fontan circulation - Maleux, G.; Storme, E.; Cools, B.; Heying, R.; Boshoff, D.; Louw, J.J.; Frerich, S.; Malekzadeh-Milanii, S.; Hubrechts, J.; Brown, S.C.; Gewillig, M. (Catheterization and Cardiovascular Interventions, 2019)
Background: To determine the feasibility and clinical result of selective embolization of hepatoduodenal or paratracheal lymphatics in Fontan patients with protein-losing enteropathy (PLE) or plastic bronchitis (PB). Methods: Dilated lymph vessels in periportal (PLE) or paratracheal (PB) position were percutaneously punctured with a 22G Chiba needle. Intralymphatic position was confirmed by water soluble contrast injection with drainage to hepatoduodenal or tracheal fistulae. After flushing with 10% glucose solution, occlusion of hepatoduodenal or paratreacheal lymphatics was effected by injection of 1–4 cc mixture 4/1 of Lipiodol/n-butyl cyanoacrylate (n-BCA; Histoacryl). Results: Seven patients with proven PLE were treated with periportal lymphatic embolization 10.7 (range: 6.6–13.5) years after the Fontan operation. The Fontan operation was performed at a median age of 3.7 (range: 2.9–5.7) years and PLE started a median of 3.1 (range: 0.9–4.7) years later. Five patients required a second procedure 2–8 months later. Complications were limited (spillage of glue in portal branch, transient cholangitis, and caustic duodenal bleeding). Six of seven patients reported significant improvement in quality of life and normalization of albumin levels after limited follow-up (p <.01). One patient (Fontan at 2.9 years; age 16.4 years) had PB for 2 years. Selective transthoracic cone-beam-directed puncture of left and right paratracheal lymphatics with n-BCA embolization of distal lymphatic fistulae resulted in lasting absence of tracheal casts (11 months). Conclusions: Embolization of periportal/peritracheal lymphatics is a promising technique in Fontan patients with PLE/PB. Larger series are required to determine incidence and reasons of success/failure, with long-term results and effects on liver function. © 2019 Wiley Periodicals, Inc.
Keywords: congenital heart disease; lymphangiography; lymphatic embolization; n-butyl cyanoacrylate; plastic bronchitis; protein losing enteropathy

Outcome of patients with functional single ventricular heart after pacemaker implantation: What makes it poor, and what can we do? - Kodama, Y.; Kuraoka, A.; Ishikawa, Y.; Nakamura, M.; Ushinohama, H.; Sagawa, K.; Umemoto, S.; Hashimoto, T.; Sakamoto, I.; Ohtani, K.; Ide, T.; Tsutsui, H.; et al. (Heart Rhythm, 2019)
Background: Pacemaker implantation in patients with single ventricle is associated with poor outcomes. Objective: The purpose of this study was to determine the reasons for the poor outcomes of pacemaker implantation. Methods: We performed a retrospective chart review of patients with single ventricle who had undergone permanent pacemaker implantation. Patients were categorized into 3 groups based on the site of pacing and the proportion of ventricular pacing (VP) as follows: (1) atrial pacing group with atrial pacing only (n = 11); (2) low VP group with low daily VP proportion (<50%; n = 12); and (3) high VP group with high daily VP proportion (≥50%; n = 15). Pacing leads were placed at the epicardium in all patients. Results: No patients in the atrial pacing or low VP groups died, whereas the survival rate in the high VP group was 58.9% and 39.3% at 10 and 20 years, respectively, after pacemaker implantation. Among the post-Fontan patients, plasma brain natriuretic peptide (BNP) levels significantly increased with the proportion of VP: 11.7, 20.3, and 28.4 pg/mL in the atrial pacing, low VP, and high VP groups, respectively (P = 0.04). In the high VP group, the plasma BNP level was significantly lower in patients with an apical pacing lead than in those with a nonapical pacing lead (27.0 pg/mL vs 82.8 pg/mL, respectively; P = .03). Conclusion: A higher proportion of VP was associated with poor outcome and higher plasma BNP levels, probably due to ventricular dyssynchrony. In epicardial ventricular pacing, apical pacing is better to avoid the increase in ventricular stress and plasma BNP level. © 2019 Heart Rhythm Society
Keywords: Apical pacing; Epicardial lead; Fontan procedure; Functional single ventricle; Pacemaker implantation

Risk factors for chylothorax and persistent serous effusions after congenital heart surgery - Raatz, A.; Schöber, M.; Zant, R.; Cesnjevar, R.; Rüffer, A.; Purbojo, A.; Dittrich, S.; Alkassar, M. (European Journal of Cardio-thoracic Surgery, 2019)
OBJECTIVES: This study evaluated the various risk factors for chylothorax and persistent serous effusions (>7 days) after congenital heart surgery and developed equations to calculate the probability of their occurrence. METHODS: We performed a retrospective review of different medical databases at the University Hospital of Erlangen between January 2014 and December 2016. Full model regression analysis was used to identify risk factors, and prediction algorithms were set up to calculate probabilities. Discriminative power of the models was checked with the help of C-statistics. RESULTS: Of 745 operations on 667 patients, 68 chylothoraxes (9.1%) and 125 persistent pleural effusions (16.8%) were diagnosed. Lowest temperature [P = 0.043; odds ratio (OR) 0.899], trisomy 21 (P = 0.001; OR 5.548), a higher vasoactive inotropic score on the day of surgery (P = 0.001; OR 1.070) and use of an assist device (P = 0.001; OR 5.779) were significantly associated with chylothorax. Risk factors for persistent serous effusions were a given or possible involvement of the aortic arch during the operation (P = 0.000; OR 3.982 and 2.905), univentricular hearts (P = 0.019; OR 2.644), a higher number of previous heart operations (P = 0.014; OR 1.436), a higher vasoactive inotropic score 72 h after surgery (P = 0.019; OR 1.091), a higher central venous pressure directly after surgery (P = 0.046; OR 1.076) and an aortic cross-clamp time >86 min (P = 0.023; OR 2.223), as well as use of an assist device (P = 0.002; OR 10.281). The prediction models for both types of effusions proved to have excellent discriminative power. CONCLUSIONS: Persistent serous effusion is associated with a higher vasoactive inotropic score 72 h after surgery, an aortic cross-clamp time >86 min and elevated central venous pressure directly after surgery, which, in combination, potentially indicate cardiac stress. The developed logistic algorithm helps to estimate future likelihood. © 2019 The Author(s). Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Cardiac insufficiency; Cardiac surgery; Chylothorax; Congenital heart disease; Persistent effusions; Risk factor

Altered Hemorheology in Fontan Patients in Normoxia and After Acute Hypoxic Exercise - Härtel, J.A.; Müller, N.; Herberg, U.; Breuer, J.; Bizjak, D.A.; Bloch, W.; Grau, M. (Frontiers in Physiology, 2019)
Background: The Fontan circulation is a unique palliation procedure for several congenital heart defects. Impaired exercise capacity has previously been demonstrated in these patients and also a higher risk for cardiopulmonary mortality. Hemorheology was shown to affect cardiopulmonary capacity and in turn to be affected by regular exercise and hypoxia but none of these have been investigated in Fontan patients so far. The aim of this study was to detect general differences in hemorheology in normoxia as well as possible altered hemorheological responses to hypoxia exposure and hypoxic exercise between Fontan patients and healthy controls. Methods and Findings: 26 Fontan patients and 20 healthy controls performed an acute exercise test (AET) on a bicycle ergometer under hypoxia with ambient 15.2% oxygen saturation (sO2). Blood samples were taken at rest in normoxia (T0), at rest in hypoxia (T1), after maximum exhaustion in hypoxia (T2), and after 50 min recovery in normoxia (T3). Hemorheological and blood parameters were investigated. Additionally, arterial stiffness was tested at T0. Red blood cell (RBC) deformability, NOx, erythropoietin (EPO) concentration, RBC count, hemoglobin (Hb) concentration and hematocrit (hct) were significantly increased in Fontan patients compared to controls. Same was observed for arterial stiffness. No changes were observed for RBC aggregation, fibrinogen concentration, free radical levels and vascular endothelial growth factor (VEGF). Hypoxia exposure did not change parameters, whereas exercise in hypoxia increased aggregation and hct significantly in both groups. Fontan patients showed significantly increased aggregation-disaggregation balance compared to controls. Conclusion: Acute hypoxia exposure and exercise under hypoxia might have similar impact on hemorheology in Fontan patients and controls and was clinically well tolerated. Nevertheless, exercise alters aggregation and possibly hemodynamics which requires special attention in Fontan patients. © Copyright © 2019 Härtel, Müller, Herberg, Breuer, Bizjak, Bloch and Grau.
Keywords: exercise; Fontan circulation; hypoxia; red blood cells; rheology

Behavior and quality of life at 6 years for children with hypoplastic left heart syndrome - Goldberg, C.S.; Hu, C.; Brosig, C.; Gaynor, J.W.; Mahle, W.T.; Miller, T.; Mussatto, K.A.; Sananes, R.; Uzark, K.; Trachtenberg, F.; Pizarro, C.; Pemberton, V.L.; et al. (Pediatrics, 2019)
OBJECTIVES:We measured behavioral, quality of life (QoL), and functional status outcomes for 6- year-old children with hypoplastic left heart syndrome enrolled in the Single Ventricle Reconstruction Trial. We sought to compare these outcomes with those in the normative population and to analyze risk factors for worse outcomes within the single-ventricle group. METHODS: Parent-response instruments included the Vineland Adaptive Behavior Scales, Second Edition (Vineland-II) (primary outcome), Behavior Assessment System for Children 2, Pediatric Quality of Life Inventory 4.0, and other measures of QoL and functional status. We compared subjects with those in the normative sample using 1-sample Wilcoxon rank tests and assessed outcome predictors using multivariable regression. RESULTS: Of 325 eligible patients, 250 (77%) participated. Compared with population norms, participants had lower scores on the Vineland-II motor skills domain (90 6 17 vs 100 6 15; P <001), with 11% scoring .2 SDs below the normative mean. On nearly all major domains, more study subjects (3.3%-19.7%) scored outside the normal range than anticipated for the general population. Independent risk factors for lower Vineland-II scores included perioperative extracorporeal membrane oxygenation, male sex, use of regional cerebral perfusion, catheterization after stage 2 operation, visual problems, seizure history, and more complications after 2 years (R2 = 0.32). Independent predictors of worse Behavior Assessment System for Children 2 (R2 = 0.07-0.20) and Pediatric Quality of Life Inventory 4.0 (R2 = 0.17-0.25) domain scores also included sociodemographic factors and measures of morbidity and/or greater course complexity. CONCLUSIONS: At 6 years, children with hypoplastic left heart syndrome had difficulty in areas of adaptive behavior, behavioral symptoms, QoL, and functional status. Principal risks for adverse outcomes include sociodemographic factors and measures of greater course complexity. However, models reveal less than one-third of outcome variance. © 2019 by the American Academy of Pediatrics.

Parenting stress trajectories during infancy in infants with congenital heart disease: Comparison of single-ventricle and biventricular heart physiology - Golfenshtein, N.; Hanlon, A.L.; Deatrick, J.A.; Medoff-Cooper, B. (Congenital Heart Disease, 2019)
Objective: Parents of infants with congenital heart disease (CHD) experience increased parenting stress levels, potentially interfering with parenting practices and bear adverse family outcomes. Condition severity has been linked to parenting stress. The current study aimed to explore parenting stress trajectories over infancy in parents of infants with complex CHD, and to compare them by post-operative cardiac physiology. Design: Data from a larger prospective cohort study was analyzed using longitudinal mixed-effects regression modeling. Setting: Cardiac intensive care unit and outpatient clinic of a 480-bed children's hospital in the American North-Atlantic region. Participants: Parents of infants with complex CHD (n = 90). Measures: Parenting stress was measured via the parenting stress index-long form over four time points during infancy. Results: Parents of infants with a single-ventricle heart experienced a decrease in total stress over time. Parents of infants with a biventricular heart experienced a decrease in attachment-related stress, and an increase in stress related to infant temperament over time. Parenting stress trajectories over time significantly differed between groups on infant temperamental subscales. Conclusions: Findings highlight stressful and potentially risky periods for parents of infants with complex CHD, and introduce additional illness-related and psychosocial/familial aspects to the parenting stress concept. Early intervention may promote parental adaptive coping and productive parenting practices in this population. © 2019 Wiley Periodicals, Inc.
Keywords: congenital heart disease; infancy; longitudinal design; parenting stress; uni-ventricular heart

Surveillance and screening practices of New England congenital cardiologists for patients after the Fontan operation - Davey, B.T.; Toro-Salazar, O.H.; Gauthier, N.; Valente, A.M.; Elder, R.W.; Wu, F.M.; Berman, N.; Pollack, P.; Lee, J.H.; Rathod, R.H. (Congenital Heart Disease, 2019)
Introduction: Surveillance and management guidelines for Fontan patients are lacking due to the paucity of evidence in the literature of screening efficacy on outcome measures. Methods: The Fontan Working Group within the New England Congenital Cardiology Association designed an electronic survey to assess surveillance practices for patients with Fontan procedures among New England congenital cardiologists and to explore variability in screening low-risk vs high-risk Fontan patients across regional programs. Results: Fifty-six cardiologists representing 12 regional programs responded to the survey, comprising ~40% of the total New England congenital cardiac physicians. The majority of desired testing and consultation was available within 50 miles of the patient's home institution with some limitations of cardiac catheterization and cardiac magnetic resonance imaging availability. Surveillance and screening were less frequent in low-risk Fontan patients compared to high-risk Fontan patients. Counseling practices were similar for both low-risk and high-risk Fontan patients. Aspirin monotherapy was recommended by 82% of providers for low-risk Fontan patients, while anticoagulation regimens were more varied for the high-risk population. Practitioners with ≤15 years of experience were more likely to provide quality of life testing in both low-risk and high-risk Fontan patients. There were no other major differences in testing frequencies by years of practice, quaternary vs nonquaternary care facility, or the number of Fontan patients in a practice. Conclusion: This survey provides insight into regional practices of screening and surveillance of Fontan patients. These data may be used to design future research studies and evidence-based guidelines to streamline the approach to manage these complex patients. © 2019 Wiley Periodicals, Inc.
Keywords: congenital heart disease; Fontan; screening; single ventricle; survey

Analysis of Inlet Velocity Profiles in Numerical Assessment of Fontan Hemodynamics - Wei, Z.A.; Huddleston, C.; Trusty, P.M.; Singh-Gryzbon, S.; Fogel, M.A.; Veneziani, A.; Yoganathan, A.P. (Annals of Biomedical Engineering, 2019)
Computational fluid dynamic (CFD) simulations are widely utilized to assess Fontan hemodynamics that are related to long-term complications. No previous studies have systemically investigated the effects of using different inlet velocity profiles in Fontan simulations. This study implements real, patient-specific velocity profiles for numerical assessment of Fontan hemodynamics using CFD simulations. Four additional, artificial velocity profiles were used for comparison: (1) flat, (2) parabolic, (3) Womersley, and (4) parabolic with inlet extensions [to develop flow before entering the total cavopulmonary connection (TCPC)]. The differences arising from the five velocity profiles, as well as discrepancies between the real and each of the artificial velocity profiles, were quantified by examining clinically important metrics in TCPC hemodynamics: power loss (PL), viscous dissipation rate (VDR), hepatic flow distribution, and regions of low wall shear stress. Statistically significant differences were observed in PL and VDR between simulations using real and flat velocity profiles, but differences between those using real velocity profiles and the other three artificial profiles did not reach statistical significance. These conclusions suggest that the artificial velocity profiles (2)–(4) are acceptable surrogates for real velocity profiles in Fontan simulations, but parabolic profiles are recommended because of their low computational demands and prevalent applicability. © 2019, Biomedical Engineering Society.
Keywords: Computational fluid dynamics; Fontan hemodynamics; Inlet velocity profiles

Computational fluid dynamic simulations of a cavopulmonary assist device for failing Fontan circulation - Lin, W.C.P.; Doyle, M.G.; Roche, S.L.; Honjo, O.; Forbes, T.L.; Amon, C.H. (Journal of Thoracic and Cardiovascular Surgery, 2019)
Objectives: Adult patients who have undergone the Fontan procedure are highly vulnerable to gradual, progressive circulatory failure, and options to reverse this situation are few. A cavopulmonary assist device could decongest the venous and lymphatic systems, overcome elevated pulmonary vascular resistance, increase cardiac output, and support some of these patients to heart transplant. This study characterizes the performance and challenges of a novel multilumen cannula coupled to an external blood pump proposed as a potential Fontan cavopulmonary assist strategy. Methods: Computational fluid dynamic simulations were conducted for 3 extracardiac Fontan geometries consisting of 1 idealized model and 2 patient-specific models. A range of physiologic flow rates and pump assist levels were simulated to calculate the pressure gain provided by the multilumen cannula. Hemolysis index was estimated for the idealized model with Lagrangian particle tracking and 2 variations of the power-law. Wall shear stresses were also examined. Results: Pressure gains up to 4 and 9 mm Hg were achieved for the idealized and patient-specific models, respectively. Pressure gains increased with both higher cardiac output and larger pump intake through the external pump. Flow-weighted hemolysis show hemoglobin damage levels to be several times lower than the 2% threshold at the highest pump intake flow cases. Wall shear stress predictions depict elevated areas in the pulmonary vessels and regions of the cannula device. Conclusions: The cannula tested in this study shows promise as a percutaneous option to bridge support in some patients with a failing extracardiac Fontan. Limitations identified will be addressed in future design iterations and in ongoing experimental tests. © 2019 The American Association for Thoracic Surgery
Keywords: cavopulmonary assist; computational fluid dynamics; Fontan circulation; hemolysis; multilumen cannula

Standardized outcomes in reproductive cardiovascular care: The STORCC initiative - Valente, A.M.; Landzberg, M.J.; Gauvreau, K.; Egidy-Assenza, G.; Barker, N.; Partington, S.; Morgan, R.B.; Harmon, A.J.; Hickey, K.; Mullen, M.P.; Carabuena, J.M.; O'Gara, P.; et al. (American Heart Journal, 2019)
Background: Validated protocols for diagnostic testing and management of pregnant women with cardiovascular disease (CVD) do not exist. Our objective was to establish a prospective standardized protocol for the clinical evaluation of pregnant women with CVD. Methods: The Standardized Outcomes in Reproductive Cardiovascular Care (STORCC) initiative prospectively enrolled pregnant women with CVD into a standardized diagnostic testing and assessment protocol. Detailed cardiac and obstetric data were collected during the antepartum, intrapartum, and postpartum periods. Each woman was assigned a STORCC color code of perceived risk at a monthly multidisciplinary conference. Results: In 250 pregnancies of 207 women with CVD, the standardized care protocol was followed in 136 and routine care in 114. The median age of the subjects was 32 years, and the most common form of heart disease was congenital heart disease (77%). Women enrolled in standardized care protocol had high compliance with second- and third-trimester visits (93%) and postpartum visits (76%). Maternal cardiac complications occurred in 10%. The STORCC cardiac and obstetric color codes predicted adverse outcomes within each respective category (P = .02, .01). Conclusions: The STORCC protocol for prospective diagnostic testing and follow-up of pregnant women with CVD was successfully established, and compliance was high. The strength of a standardized testing and care protocol as well as detailed classification of labor and delivery characteristics allows for robust analyses into specific questions regarding testing protocols, and mode and timing of delivery. © 2019

Knowledge of Life-Long Cardiac Care by Adolescents and Young Adults with Congenital Heart Disease - Fernandes, S.M.; Verstappen, A.; Clair, M.; Rummell, M.; Barber, D.; Ackerman, K.; Dummer, K.; Mares, J.C.; Cannobio, M.M.; Reardon, L.C.; Long, J.; Crumb, S.; et al. (Pediatric Cardiology, 2019)
National management guidelines recommend that patients with moderate and complex congenital heart disease (CHD) receive life-long cardiac care (LLCC), guided in adulthood by an adult congenital heart disease (ACHD) specialist. However, the percentage of adult CHD patients who receive such care is quite low. Inadequate knowledge regarding LLCC may contribute to care interruption. We, therefore, sought to determine the knowledge of adolescents and young adults regarding LLCC. In this multi-center study, we administered a survey to patients 13–20 years of age with surgically repaired congenital heart disease. We assessed the understanding of both their need for LLCC and awareness of the type of recommended care providers. A total of 290/302 (96%) patients approached in the outpatient clinic setting (10 centers) agreed to study participation; mean age was 16.3 ± 2.3 years; patients were 62% male. While the need for LLCC was recognized by 78% of subjects, only 37% understood that an ACHD specialist in adulthood should guide this care. Only 37% of respondents stated that their current cardiology team had spoken to them about LLCC, but 90% wished to learn more. A substantial number of adolescents and young adults with moderate and complex CHD lack adequate knowledge about LLCC, but most have a desire to learn more about the type of care they will require in adulthood. Transition education/assessment ensuring successful transfer to adult-oriented care for this population should emphasize the importance of LLCC. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Adult congenital heart disease; Congenital heart disease; Health care transition; Pediatric cardiology

Adverse Perioperative Events in Children with Complex Congenital Heart Disease Undergoing Operative Scoliosis Repair in the Contemporary Era - Przybylski, R.; Hedequist, D.J.; Nasr, V.G.; McCann, M.E.; Brustowicz, R.M.; Emans, J.B.; Marshall, A.C.; Brown, D.W. (Pediatric Cardiology, 2019)
Scoliosis is common in children with congenital heart disease (CHD) and may have deleterious effects on quality of life and hemodynamics. Relatively little is known about the outcomes of spinal fusion for scoliosis repair in children with complex CHD. We reviewed all cases of children with CHD undergoing first time spinal fusion excluding those with minor CHD between 1995 and 2015. Seventy-eight patients were identified and included in the study. 97.4% of patients included had undergone prior cardiac surgery and sixteen patients had single ventricle circulations. 17.9% of patients experienced a significant perioperative event defined as an aggregate of the presence of any of the following: need for early unanticipated reoperation, neurologic deficit, postoperative bleeding requiring intervention, end organ dysfunction, or death. There were no deaths in our cohort. 38.5% of patients experienced any adverse event, the majority of which were related to perioperative fluid shifts. Larger preoperative Cobb angle and longer length of spinal fusion were associated with increased risk of significant perioperative event while larger preoperative Cobb angle and longer length of spinal fusion, older age at time of surgery, single ventricle circulation, cyanosis and patients taking cardiac medications at the time of surgery were more likely to experience any adverse event. Operative repair of scoliosis in children with complex CHD has been performed without mortality over a 20-year period in a single institution, albeit with a higher rate of perioperative complication than is seen in the general pediatric population. Patients with large preoperative Cobb angles and cyanotic single ventricle circulations appear to be at the highest risk for perioperative complications. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Congenital heart disease; Scoliosis; Spinal fusion

Optimization of Tissue-Engineered Vascular Graft Design Using Computational Modeling - Szafron, J.M.; Ramachandra, A.B.; Breuer, C.K.; Marsden, A.L.; Humphrey, J.D. (Tissue Engineering - Part C: Methods, 2019)
Tissue-engineered vascular grafts hold great promise in many clinical applications, especially in pediatrics wherein growth potential is critical. A continuing challenge, however, is identification of optimal scaffold parameters for promoting favorable neovessel development. In particular, given the countless design parameters available, including those related to polymeric microstructure, material behavior, and degradation kinetics, the number of possible scaffold designs is almost limitless. Advances in computationally modeling the growth and remodeling of native blood vessels suggest that similar simulations could help reduce the search space for candidate scaffold designs in tissue engineering. In this study, we meld a computational model of in vivo neovessel formation with a surrogate management framework to identify optimal scaffold designs for use in the extracardiac Fontan circulation while comparing the utility of different objective functions. We show that evolving luminal radius and graft compliance can be matched to that of the native vein by the end of the simulation period with judicious combinations of scaffold parameters, although the inability to match these metrics at all times reveals constraints engendered by current materials. We emphasize further that there is yet a need to examine additional metrics, and combinations thereof, when seeking to optimize functionality and reduce the potential for adverse outcomes. Tissue-engineered vascular grafts have considerable promise for treating myriad conditions, and multiple designs are now in FDA-approved trials. Nevertheless, the search continues for the optimal design of the underlying polymeric scaffold. We present a novel melding of a computational model of vascular adaptation and a formal method of optimization that can aid in identifying optimal design parameters, with potential to save development time and costs while improving clinical outcomes. © Copyright 2019, Mary Ann Liebert, Inc., publishers.
Keywords: computational modeling; inflammation; mechanobiology; optimization; scaffold

What are the important morbidities associated with paediatric cardiac surgery? A mixed methods study - Brown, K.L.; Pagel, C.; Ridout, D.; Wray, J.; Anderson, D.; Barron, D.J.; Cassidy, J.; Davis, P.; Hudson, E.; Jones, A.; McLean, A.; Morris, S.; et al. (BMJ Open, 2019)
Given the current excellent early mortality rates for paediatric cardiac surgery, stakeholders believe that this important safety outcome should be supplemented by a wider range of measures. Our objectives were to prospectively measure the incidence of morbidities following paediatric cardiac surgery and to evaluate their clinical and health-economic impact over 6 months. Design The design was a prospective, multicentre, multidisciplinary mixed methods study. Setting The setting was 5 of the 10 paediatric cardiac surgery centres in the UK with 21 months recruitment. Participants Included were 3090 paediatric cardiac surgeries, of which 666 patients were recruited to an impact substudy. Results Families and clinicians prioritised: Acute neurological event, unplanned re-intervention, feeding problems, renal replacement therapy, major adverse events, extracorporeal life support, necrotising enterocolitis, postsurgical infection and prolonged pleural effusion or chylothorax. Among 3090 consecutive surgeries, there were 675 (21.8%) with at least one of these morbidities. Independent risk factors for morbidity included neonatal age, complex heart disease and prolonged cardiopulmonary bypass (p<0.001). Among patients with morbidity, 6-month survival was 88.2% (95% CI 85.4 to 90.6) compared with 99.3% (95% CI 98.9 to 99.6) with none of the morbidities (p<0.001). The impact substudy in 340 children with morbidity and 326 control children with no morbidity indicated that morbidity-related impairment in quality of life improved between 6 weeks and 6 months. When compared with children with no morbidities, those with morbidity experienced a median of 13 (95% CI 10.2 to 15.8, p<0.001) fewer days at home by 6 months, and an adjusted incremental cost of £21 292 (95% CI £17 694 to £32 423, p<0.001). Conclusions Evaluation of postoperative morbidity is more complicated than measuring early mortality. However, tracking morbidity after paediatric cardiac surgery over 6 months offers stakeholders important data that are of value to parents and will be useful in driving future quality improvement. © Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY. Published by BMJ.
Keywords: cardiac surgery; complications; morbidity; outcome; paediatrics; quality of life

Transition Readiness in Adolescents and Young Adults with Heart Disease: Can We Improve Quality of Life? - Uzark, K.; Afton, K.; Yu, S.; Lowery, R.; Smith, C.; Norris, M.D. (Journal of Pediatrics, 2019)
Objectives: We previously reported common knowledge deficits and lack of transition readiness in 13- 25-year-olds with congenital or acquired heart disease. The aims of this study were to re-evaluate transition readiness in this cohort at follow-up and to examine the relationship between changes in transition readiness and quality of life (QOL). Study design: In this prospective cohort study, patients completed the Transition Readiness Assessment and the Pediatric Quality of Life Inventory using an e-tablet, web-based format at a routine follow-up visit. Changes from initial to follow-up scores were evaluated. Results: Sixty-five percent of patients (106 of 164) completed follow-up assessments at a median age of 18.7 years (IQR, 16.5-21.2 years) at a median follow-up of 1 year. The average perceived knowledge deficit score (percent of items with no knowledge) at follow-up was 18.0 ± 15.2%, which decreased from 24.7 ± 16.5% (P < .0001). On a 100-point scale, the mean score for self-efficacy increased from 71.4 ± 17.0 to 76.7 ± 18.2 (P = .0004) and for self-management increased from 47.9 ± 18.4 to 52.0 ± 20.7 (P = .004). Although physical QOL did not change, the mean psychosocial QOL score increased significantly (P = .02). A decrease in the knowledge deficit score at follow-up was significantly associated with an increased psychosocial QOL score (P = .03). An increase in the self-efficacy score was associated with an increase in psychosocial QOL score (P = .04), especially social QOL (P = .02). Conclusions: Although deficits in knowledge and self-management skills persist, transition readiness assessment and recognition of deficits can improve transition readiness with improved psychosocial QOL. © 2019 Elsevier Inc.
Keywords: adult congenital heart disease; healthcare transition; patient education; quality of life; self-management

Hand-held echocardiography in children with hypoplastic left heart syndrome - Riley, A.F.; Ocampo, E.C.; Hagan, J.; Lantin-Hermoso, M.R. (Congenital Heart Disease, 2019)
Background: When performed by cardiologists, hand-held echocardiography (HHE) can assess ventricular systolic function and valve disease in adults, but its accuracy and utility in congenital heart disease is unknown. In hypoplastic left heart syndrome (HLHS), the echocardiographic detection of depressed right ventricular (RV) systolic function and higher grade tricuspid regurgitation (TR) can identify patients who are at increased risk of morbidity and mortality and who may benefit from additional imaging or medical therapies. Methods: Children with HLHS after Stage I or II surgical palliation (Norwood or Glenn procedures) were prospectively enrolled. Subjects underwent HHE by a pediatric cardiologist on the same day as standard echocardiography (SE). Using 4-point scales, bedside HHE assessment of RV systolic function and TR were compared with blinded assessment of offline SE images. Concordance correlation coefficient (CCC) was used to evaluate agreement. Results: Thirty-two HHEs were performed on 15 subjects (Stage I: n = 17 and Stage II: n = 15). Median subject age was 3.4 months (14 days-4.2 years). Median weight was 5.9 kg (2.6-15.4 kg). Bedside HHE assessment of RV systolic function and TR severity had substantial agreement with SE (CCC = 0.80, CCC = 0.74, respectively; P <.001). HHE sensitivity and specificity for any grade of depressed RV systolic function were 100% and 92%, respectively, and were 94% and 88% for moderate or greater TR, respectively. Average HHE scan time was 238 seconds. Conclusions: HHE offers a rapid, bedside tool for pediatric cardiologists to detect RV systolic dysfunction and hemodynamically significant TR in HLHS. © 2019 Wiley Periodicals, Inc.
Keywords: congenital heart disease; focused cardiac ultrasound; hypoplastic left heart syndrome

More than the heart: Hepatic, renal, and cardiac dysfunction in adult Fontan patients - Byrne, R.D.; Weingarten, A.J.; Clark, D.E.; Huang, S.; Perri, R.E.; Scanga, A.E.; Menachem, J.N.; Markham, L.W.; Frischhertz, B.P. (Congenital Heart Disease, 2019)
Setting: Fontan-associated liver disease universally affects adults with single ventricle heart disease. Chronic kidney disease is also highly prevalent in adult Fontan patients. In this study, we evaluate the relationship of Fontan hemodynamics invasively and noninvasively with extra-cardiac dysfunction as measured by MELD and MELD-XI. Objective: We hypothesize that invasive and noninvasive measures of Fontan circuit congestion and ventricular dysfunction are associated with increased MELD and MELD-XI scores. Design: Single-center data from adults with Fontan palliation who had ongoing care, including cardiac catheterization, were retrospectively collected. Hemodynamic data from cardiac catheterization and echocardiographic assessment of ventricular and atrioventricular valve function were tested for association with serum creatinine, MELD, and MELD-XI. Linear regression was used to perform multivariable analysis in the echocardiogram cohort. Results: Fifty-seven patients had congruent lab and catheterization data for analysis. Sixty-three and sixty-nine patients had congruent lab and echocardiogram data for MELD and MELD-XI, respectively. Of the hemodynamic variables analyzed, only decreased systemic oxygen saturation had significant correlation with elevated MELD and MELD-XI (P =.045). Patients with moderately or severely reduced ejection fraction by echocardiogram had significantly higher MELD and MELD-XI scores compared to those with normal or mildly depressed systolic ventricular function (P =.008 and P <.001 for MELD and MELD-XI, respectively). Significant differences in creatinine were also found among the ventricular dysfunction groups (P =.02). Conclusions: In adults following Fontan palliation, systolic ventricular dysfunction and decreased oxygen saturation were associated with hepatic and renal dysfunction as assessed by elevated serum creatinine, MELD, and MELD-XI scores. © 2019 Wiley Periodicals, Inc.
Keywords: extra-cardiac; Fontan; liver; MELD; renal

Relationship of Aortic Stiffness to Exercise and Ventricular Volumes in Single Ventricles - Biko, D.M.; Gaynor, J.W.; Partington, S.L.; Harris, M.A.; Whitehead, K.K.; Trusty, P.; Yoganathan, A.P.; Fogel, M.A. (Annals of Thoracic Surgery, 2019)
Background: Patients with single ventricle (SV) may often undergo aortic reconstruction that creates a stiff large vessel, increasing afterload and affecting exercise performance. The objective of this study was to determine the relationship of pulse wave velocity (PWV) and distensibility in reconstructed and normal aortic arches after Fontan with exercise variables. Methods: PWV and distensibility of the descending aorta at the level of the diaphragm (DAo) were calculated with real-time exercise cardiac magnetic resonance in 48 patients with SV after Fontan (18 after aortic reconstruction; 30 without aortic reconstruction) and compared with metabolic exercise stress test variables. Results: PWV was greater in the reconstructed group than in the non-reconstructed group (median 4.4 m/s [range: 2.3 to 9.8 m/s] versus 3.6 [range: 2.6 to 6.3 m/s], respectively, p = 0.003). Statistically significant inverse correlations were found between PWV and end-diastolic, end-systolic, and stroke volumes at rest and at exercise in the reconstructed group. In addition, inverse correlations also existed in the reconstructed group between distensibility of the DAo and the exercise variables such as peak oxygen pulse (R = 0.56, p = 0.02), peak oxygen consumption (R = 0.63, p = 0.008), oxygen consumption at ventilatory anaerobic threshold (R = 0.48, p = 0.04), and peak work (R = 0.54, p = 0.02). Similar correlations were not seen in patients with non-reconstructed aortas. Conclusions: Patients with SV with reconstructed aortas have increased aortic stiffness, increasing afterload on the ventricle. Native DAo stiffness distal to the reconstruction is inversely correlated with exercise performance, presumably to decrease impedance mismatch to maintain homogeneity of the aortic wall. This information suggests a possible mechanism for decreased exercise performance in patients with SV with aortic reconstructions. © 2019 The Society of Thoracic Surgeons

Maternal voluntary exercise mitigates oxidative stress and incidence of congenital heart defects in pre-gestational diabetes - Saiyin, T.; Engineer, A.; Greco, E.R.; Kim, M.Y.; Lu, X.; Jones, D.L.; Feng, Q. (Journal of Cellular and Molecular Medicine, 2019)
Women with pre-gestational diabetes have a higher risk of producing children with congenital heart defects (CHDs), caused predominantly by hyperglycemia-induced oxidative stress. In this study, we evaluated if exercise during pregnancy could mitigate oxidative stress and reduce the incidence of CHDs in the offspring of diabetic mice. Female mice were treated with streptozotocin to induce pre-gestational diabetes, then mated with healthy males to produce offspring. They were also given access to running wheels 1 week before mating and allowed to exercise voluntarily until E18.5. Heart morphology, gene expression, and oxidative stress were assessed in foetal hearts. Maternal voluntary exercise results in a significantly lower incidence of CHDs from 59.5% to 25%. Additionally, diabetes-induced defects in coronary artery and capillary morphogenesis were also lower with exercise. Myocardial cell proliferation and epithelial-mesenchymal transition at E12.5 was significantly lower with pre-gestational diabetes which was mitigated with maternal exercise. Cardiac gene expression of Notch1, Snail1, Gata4 and Cyclin D1 was significantly higher in the embryos of diabetic mice that exercised compared to the non-exercised group. Furthermore, maternal exercise produced lower reactive oxygen species (ROS) and oxidative stress in the foetal heart. In conclusion, maternal exercise mitigates ROS and oxidative damage in the foetal heart, and results in a lower incidence of CHDs in the offspring of pre-gestational diabetes. Exercise may be an effective intervention to compliment clinical management and further minimize CHD risk in mothers with diabetes. © 2019 The Authors. Journal of Cellular and Molecular Medicine published by John Wiley & Sons Ltd and Foundation for Cellular and Molecular Medicine.
Keywords: congenital heart defects; exercise; heart development; oxidative stress; pre-gestational diabetes

Stress increases intracardiac 4D flow cardiovascular magnetic resonance -derived energetics and vorticity and relates to VO2max in Fontan patients - Kamphuis, V.P.; Elbaz, M.S.M.; van den Boogaard, P.J.; Kroft, L.J.M.; Lamb, H.J.; Hazekamp, M.G.; Jongbloed, M.R.M.; Blom, N.A.; Helbing, W.A.; Roest, A.A.W.; Westenberg, J.J.M. (Journal of cardiovascular magnetic resonance : official journal of the Society for Cardiovascular Magnetic Resonance, 2019)
BACKGROUND: We hypothesize that dobutamine-induced stress impacts intracardiac hemodynamic parameters and that this may be linked to decreased exercise capacity in Fontan patients. Therefore, the purpose of this study was to assess the effect of pharmacologic stress on intraventricular kinetic energy (KE), viscous energy loss (EL) and vorticity from four-dimensional (4D) Flow cardiovascular magnetic resonance (CMR) imaging in Fontan patients and to study the association between stress response and exercise capacity. METHODS: Ten Fontan patients underwent whole-heart 4D flow CMR before and during 7.5 μg/kg/min dobutamine infusion and cardiopulmonary exercise testing (CPET) on the same day. Average ventricular KE, EL and vorticity were computed over systole, diastole and the total cardiac cycle (vorticity_volavg cycle, KEavg cycle, ELavg cycle). The relation to maximum oxygen uptake (VO2 max) from CPET was tested by Pearson's correlation or Spearman's rank correlation in case of non-normality of the data. RESULTS: Dobutamine stress caused a significant 88 ± 52% increase in KE (KEavg cycle: 1.8 ± 0.5 vs 3.3 ± 0.9 mJ, P < 0.001), a significant 108 ± 49% increase in EL (ELavg cycle: 0.9 ± 0.4 vs 1.9 ± 0.9 mW, P < 0.001) and a significant 27 ± 19% increase in vorticity (vorticity_volavg cycle: 3441 ± 899 vs 4394 ± 1322 mL/s, P = 0.002). All rest-stress differences (%) were negatively correlated to VO2 max (KEavg cycle: r = - 0.83, P = 0.003; ELavg cycle: r = - 0.80, P = 0.006; vorticity_volavg cycle: r = - 0.64, P = 0.047). CONCLUSIONS: 4D flow CMR-derived intraventricular kinetic energy, viscous energy loss and vorticity in Fontan patients increase during pharmacologic stress and show a negative correlation with exercise capacity measured by VO2 max.
Keywords: 4D flow CMR; Flow; Fontan; Kinetic energy: energy loss; Vorticity

Altered brain diffusion tensor imaging indices in adolescents with the Fontan palliation - Singh, S.; Roy, B.; Pike, N.; Daniel, E.; Ehlert, L.; Lewis, A.B.; Halnon, N.; Woo, M.A.; Kumar, R. (Neuroradiology, 2019)
Purpose: Single ventricle heart disease (SVHD) patients show injury in brain sites that regulate autonomic, mood, and cognitive functions. However, the nature (acute or chronic changes) and extent of brain injury in SVHD are unclear. Our aim was to examine regional brain tissue damage in SVHD over controls using DTI-based mean diffusivity (MD), axial diffusivity (AD), radial diffusivity (RD), and fractional anisotropy (FA) procedures. Methods: We collected two DTI series (3.0-T MRI), mood and cognitive data, from 27 SVHD and 35 control adolescents. Whole-brain MD, AD, RD, and FA maps were calculated from each series, realigned and averaged, normalized to a common space, smoothed, and compared between groups using ANCOVA (covariates, age and sex; false discovery rate, p < 0.05). Region-of-interest analyses were performed to calculate MD, AD, RD, and FA values for magnitude assessment between groups. Results: SVHD patients showed impaired mood and cognitive functions over healthy adolescents. Multiple brain sites in SVHD showed increased MD values, including the insula, caudate, cingulate, hypothalamus, thalamus, medial prefrontal and frontal cortices, parahippocampal gyrus, hippocampus, precentral gyrus, amygdala, cerebellum, corpus callosum, basal forebrain, mammillary bodies, internal capsule, midbrain, fornix, and occipital, parietal, and temporal cortices, indicating chronic tissue changes. Similar areas showed either increased AD or RD values, with RD changes more enhanced over AD in SVHD compared to controls. Few brain regions emerged with increased or decreased FA values in SVHD patients over controls. Conclusion: SVHD adolescents, more than a decade from their last surgical procedure, show widespread brain abnormalities in autonomic, mood, and cognitive regulatory areas. These findings indicate that brain injury is in a chronic stage in SVHD with predominantly myelin changes that may result from previous hypoxia/ischemia- or developmental-induced processes. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Brain injury; Cognition; Diffusion tensor imaging; Single ventricle heart disease

Risk factors associated with the development of double-inlet ventricle congenital heart disease - Paige, S.L.; Yang, W.; Priest, J.R.; Botto, L.D.; Shaw, G.M.; Collins, R.T., II; the National Birth Defects Prevention Study (Birth Defects Research, 2019)
Background: Congenital heart disease (CHD) is the most common birth defect group and a significant contributor to neonatal and infant death. CHD with single ventricle anatomy, including hypoplastic left heart syndrome (HLHS), tricuspid atresia (TA), and various double-inlet ventricle (DIV) malformations, is the most complex with the highest mortality. Prenatal risk factors associated with HLHS have been studied, but such data for DIV are lacking. Methods: We analyzed DIV cases and nonmalformed controls in the National Birth Defects Prevention Study, a case-control, multicenter population-based study of birth defects. Random forest analysis identified potential predictor variables for DIV, which were included in multivariable models to estimate effect magnitude and directionality. Results: Random forest analysis identified pre-pregnancy diabetes, history of maternal insulin use, maternal total lipid intake, paternal race, and intake of several foods and nutrients as potential predictors of DIV. Logistic regression confirmed pre-pregnancy diabetes, maternal insulin use, and paternal race as risk factors for having a child with DIV. Additionally, higher maternal total fat intake was associated with a reduced risk. Conclusions: Maternal pre-pregnancy diabetes and history of insulin use were associated with an increased risk of having an infant with DIV, while maternal lipid intake had an inverse association. These novel data provide multiple metabolic pathways for investigation to identify better the developmental etiologies of DIV and suggest that public health interventions targeting diabetes prevention and management in women of childbearing age could reduce CHD risk. © 2019 Wiley Periodicals, Inc.
Keywords: case-control studies; congenital heart disease; double-inlet ventricle

Elective Extracorporeal Membrane Oxygenation Support for High-Risk Pediatric Cardiac Catheterization - Zaleski, K.L.; Scholl, R.L.; Thiagarajan, R.R.; Porras, D.; Mah, D.; DiNardo, J.A.; Nasr, V.G. (Journal of Cardiothoracic and Vascular Anesthesia, 2019)
Objective: The utility of extracorporeal membrane oxygenation (ECMO) as an elective support modality for high-risk cardiac procedures is extensively described in adults, but its use in children is limited to isolated reports. The objective of this study was to analyze the outcomes of patients who underwent elective cannulation to ECMO for this purpose. Design: Single-center, retrospective chart review. Setting: Free-standing pediatric tertiary care center. Participants: Patients who underwent elective cannulation to ECMO for cardiorespiratory support during a high-risk cardiac catheterization procedure. Interventions: Elective ECMO cannulation for high-risk percutaneous cardiac interventions or electrophysiology procedures. Measurements and Main Results: Survival to discharge was 71.4% compared with 30% for patients who required extracorporeal cardiopulmonary resuscitation in the cardiac catheterization laboratory. The mean duration of cannulation was 137.43 hours (range 27-615 h, median 55 h). There were no major neurologic sequelae, but ECMO circuit thrombosis (57%) was relatively common. Conclusion: The use of elective ECMO support for high-risk pediatric cardiac catheterizations can be accomplished safely and may allow for an improved rate of survival with lower rates of severe adverse events compared with extracorporeal cardiopulmonary resuscitation as rescue therapy. © 2019 Elsevier Inc.
Keywords: cardiac catheterization; cardiopulmonary resuscitation; extracorporeal membrane oxygenation; pediatric; retrospective study; treatment outcome

The first Fetal Echocardiography experience for Prenatal diagnosis of Congenital Heart Disease in Lebanon: Successes and challenges - Charafeddine, F.; Hachem, A.; Kibbi, N.; Abutaqa, M.; Bitar, F.; Bulbul, Z.; El-Rassi, I.; Arabi, M. (Journal of the Saudi Heart Association, 2019)
Objectives: To describe the first Lebanese fetal echocardiography experience for prenatal diagnosis of congenital heart diseases (CHD), showcase successes, and hurdles. Methods: This was a retrospective study from January 2014 to December 2017. A total of 350 fetal echocardiograms for 299 fetuses were performed at the Children's Heart Center at the American University of Beirut, the only fetal center in Lebanon. Data were collected regarding diagnosis, reasons for referral, and timing of referral. Results: The mean gestational age at presentation was 25.3 weeks (standard deviation 4.9 weeks). The primary reasons for referral were abnormal anomaly scan (81 27%), history of previous child with CHD (48 16%), and pre-existing maternal congenital heart disease (15 5%). A total of 144 fetal echocardiograms were normal and 155 patients were diagnosed prenatally with CHD giving a detection rate of 44%. The most identified cardiac lesions were ventricular septal defects (31, 20%), atrial septal defects (15, 9.7%). Significant CHD defined as major abnormalities which would impact pregnancy and future quality of life of the baby were identified in 78 fetuses, with a detection rate of 22%. Conclusion: High rates of detection are mainly due to low rates of referral when indicated and possibly parental anxiety regarding CHD diagnosis. © 2019 The Authors
Keywords: Congenital heart disease; Fetal echocardiography; Prenatal diagnosis

Perceived Health Mediates Effects of Physical Activity on Quality of Life in Patients With a Fontan Circulation - Holbein, C.E.; Veldtman, G.R.; Moons, P.; Kovacs, A.H.; Luyckx, K.; Apers, S.; Chidambarathanu, S.; Soufi, A.; Eriksen, K.; Jackson, J.L.; Enomoto, J.; Fernandes, S.M.; et al. (American Journal of Cardiology, 2019)
Patients with a Fontan circulation are at risk of a sedentary lifestyle. Given the direct relationship between physical activity and health, promotion of physical activity has the potential to improve outcomes, including quality of life (QOL). This study aimed to describe self-reported physical activity levels in adult Fontan patients and examine associations between physical activity, perceived health status and QOL. The sample consisted of 177 Fontan patients (Mage = 27.5 ± 7.6 years, 52% male)who reported their physical activity, perceived health status, and QOL as part of the cross-sectional Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease – International Study. Descriptive statistics and univariate analyses of variance with planned contrasts were computed to describe physical activity characteristics. Mediation analyses tested whether perceived health status variables mediated the association between physical activity and QOL. Forty-six percent of patients were sedentary while only 40% met international physical activity guidelines. Higher physical activity was associated with younger age, lower NYHA class, higher perceived general health, and greater QOL. Patients who commuted by walking and engaged in sports reported better perceived health and QOL. Mediation analyses revealed that perceived general health but not NYHA functional class mediated the association between physical activity and QOL (αβ = 0.22, 95% confidence interval = 0.04 to 0.49). In conclusion, Fontan patients likely benefit from regular physical activity, having both higher perceived general health and functional capacity; greater perceived health status may contribute to enhanced QOL. In conclusion, these data support the pivotal role of regular physical activity for Fontan patients. © 2019 Elsevier Inc.

Impaired pulmonary function and its association with clinical outcomes, exercise capacity and quality of life in children with congenital heart disease - Abassi, H.; Gavotto, A.; Picot, M.C.; Bertet, H.; Matecki, S.; Guillaumont, S.; Moniotte, S.; Auquier, P.; Moreau, J.; Amedro, P. (International Journal of Cardiology, 2019)
Background: Impaired pulmonary function is an independent predictor of mortality in adult congenital heart disease (CHD), but has been scarcely studied in the paediatric CHD population. Aims: To compare the pulmonary function of children with CHD to healthy controls, and evaluate its association with clinical outcomes, exercise capacity, and quality of life. Methods: Cross-sectional multicentre study among 834 children (555 CHD and 279 control subjects) who underwent a complete spirometry and a cardiopulmonary exercise test (CPET). The 5th centile (Z-score = −1.64) was used to define the lower limit of normal. The association of clinical and CPET variables with spirometry was studied using a multivariate analysis. Children and their parents filled in the Kidscreen health-related quality of life questionnaire. Results: Forced vital capacity (FVC) and forced expiratory volume in 1 s (FEV1) Z-scores values were lower in children with CHD than controls (−0.4 ± 1.5 vs. 0.4 ± 1.3, P < 0.001 and −0.5 ± 1.4 vs. 0.4 ± 1.2, P < 0.001, respectively), without any obstructive airway disorder. Restrictive pattern was more frequent in CHD patients than in controls (20% vs. 4%, P < 0.0001). FVC Z-scores were predominantly impaired in complex CHD, such as heterotaxy (−1.1 ± 0.6), single ventricle (−1.0 ± 0.2), and complex anomalies of the ventricular outflow tracts (−0.9 ± 0.1). In multivariate analysis, FVC was associated with age, body mass index, peak oxygen uptake, genetic anomalies, the number of cardiac surgery and cardiac catheter procedures. FVC and FEV1 correlated with self and proxy-related quality of life scores. Conclusion: These results suggest that pulmonary function should be monitored early in life, from childhood, in the CHD population. Trial registration number: NCT01202916, post-results. © 2019 Elsevier B.V.
Keywords: Children; Congenital heart disease; Lung; Pulmonary function; Spirometry

Usefulness of 4D-Flow MRI in Mapping Flow Distribution Through Failing Fontan Circulation Prior to Cardiac Intervention - McLennan, D.; Schäfer, M.; Mitchell, M.B.; Morgan, G.J.; Ivy, D.; Barker, A.J.; Jacobsen, R. (Pediatric Cardiology, 2019)
We report a case of a 23-year-old male with failing Fontan circulation who was taken to the catheterization lab to better evaluate the Fontan circulation and hemodynamics. Catheterization revealed arteriovenous malformations exclusively present in the right lung leading to the consideration of placing stents to direct the inferior vena cava flow through the Fontan circuit to the right pulmonary artery (RPA), thus increasing the RPA concentration of the hepatic factor. However, comprehensive 4D-Flow MRI analyses indicated sufficient distribution of the hepatic flow between branch pulmonary arteries, and consequently no further invasive intervention to redirect hepatic flow was performed. © 2019, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Flow; Fontan circulation; MRI

Visual-spatial processing style is associated with psychopathology in adolescents with critical congenital heart disease - Cassidy, A.R.; Bernstein, J.H.; Bellinger, D.C.; Newburger, J.W.; DeMaso, D.R. (Clinical Neuropsychologist, 2019)
Objective: To determine whether visual-spatial processing style is associated with psychopathology in a large sample of adolescents with critical congenital heart disease (CHD). Local (part-oriented) style was hypothesized to increase risk for internalizing (but not externalizing) forms of psychopathology. Method: Participants included 278 adolescents with critical CHD (dextro-transposition of the great arteries = 134, tetralogy of Fallot = 58, single-ventricle cardiac anatomy requiring the Fontan procedure = 86). Visual-spatial processing style was indexed using Copy Style Ratings from the Rey-Osterrieth Complex Figure-Developmental Scoring System. The Schedule for Affective Disorders and Schizophrenia for School-Aged Children–Present & Lifetime Version was used to determine presence/absence of diagnosable DSM-IV psychiatric disorder(s). Processing style and psychopathology were assessed concurrently. Results: Thirty-three percent of the sample had a part-oriented processing style. In multivariable binary logistic regression models, part-orientation was associated with more than twice the odds of having an anxiety disorder (lifetime: OR = 2.2, p =.02, 95% CI = 1.1–4.1; current: OR = 2.7, p =.03, 95% CI = 1.1–6.5) but was not associated with an increased risk for ADHD, disruptive behavior, or mood disorders (ps >.05). Conclusions: Adolescents with critical CHD who approach complex visual-spatial materials in a local, part-oriented fashion are more likely to meet criteria for an anxiety disorder than those who approach complexity more holistically. Part-orientation may make it more difficult for individuals to judge the relative importance of isolated details and engage in more adaptive perspective-taking. © 2018, © 2018 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: ADHD; anxiety; cardiac; cognitive style; pediatric

Infant with trisomy 18 and hypoplastic left heart syndrome - Kukora, S.; Firn, J.; Laventhal, N.; Vercler, C.; Moore, B.; Lantos, J.D. (Pediatrics, 2019)
We present a case in which a fetal diagnosis of complex congenital heart disease and trisomy 18 led to a series of decisions for an infant who was critically ill. The parents wanted everything done. The surgeons believed that surgery would be futile. The parents publicized the case on social media, which led to publicity and pressure on the hospital. The case reveals the intersection of parental values, clinical judgments, ethics consultation, insurance company decisions about reimbursement, and social media publicity. Together, these factors complicate the already delicate ethical deliberations and decisions. Copyright © 2019 by the American Academy of Pediatrics.

Gestational age, birth weight, and outcomes six years after the norwood procedure - Miller, T.A.; Ghanayem, N.S.; Newburger, J.W.; McCrindle, B.W.; Hu, C.; DeWitt, A.G.; Cnota, J.F.; Tractenberg, F.L.; Pemberton, V.L.; Wolf, M.J.; Votava-Smith, J.K.; Fifer, C.G.; et al. (Pediatrics, 2019)
BACKGROUND: Preterm delivery and low birth weight (LBW) are generally associated with worse outcomes in hypoplastic left heart syndrome (HLHS), but an individual preterm or small neonate may do well. We sought to explore the interactions between gestational age, birth weight, and birth weight for gestational age with intermediate outcomes in HLHS. METHODS: We analyzed survival, growth, neurodevelopment, length of stay, and complications to age 6 years in subjects with HLHS from the Single Ventricle Reconstruction trial. Univariate and multivariable survival and regression analyses examined the effects and interactions of LBW (,2500 g), weight for gestational age, and gestational age category. RESULTS: Early-term delivery (n = 234) was more common than term (n = 219) delivery. Small for gestational age (SGA) was present in 41% of subjects, but only 14% had LBW. Preterm, compared with term, delivery was associated with an increased risk of death or transplant at age 6 years (all: hazard ratio = 2.58, confidence interval = 1.43–4.67; Norwood survivors: hazard ratio = 1.96, confidence interval = 1.10–3.49) independent of LBW and weight for gestational age. Preterm delivery, early-term delivery, LBW, and SGA were each associated with lower weight at 6 years. Neurodevelopmental outcomes were worst in the LBW cohort. CONCLUSIONS: Preterm delivery in HLHS was associated with worse survival, even beyond Norwood hospitalization. LBW, SGA, and early-term delivery were associated with worse growth but not survival. LBW was associated with worse neurodevelopment, despite similar length of stay and complications. These data suggest that preterm birth and LBW (although often concomitant) are not equivalent, impacting clinical outcomes through mechanisms independent of perioperative course complexity. Copyright © 2019 by the American Academy of Pediatrics.

Colchicine: An impressive effect on posttransplant capillary leak syndrome and renal failure - Cocchi, E.; Chiale, F.; Gianoglio, B.; Deorsola, L.; Napoleone, C.P.; Fagioli, F.; Peruzzi, L. (Pediatrics, 2019)
Capillary leak syndrome is a critical condition occasionally occurring posttransplant and is characterized by acute endothelial hyperpermeability leading to systemic protein-rich fluid extravasation and consequent hypovolemia, hypoperfusion, and acute kidney injury. Treatment is merely supportive and is based on osmotic drugs, diuretics, continuous renal replacement therapy, and surgical drainage. However, removal of the underlying inflammatory cause is mandatory to achieve stable resolution. Herein, we report the first successful treatment with colchicine in 2 life-threatening pediatric cases of capillary leak syndrome with renal failure occurring after transplant (heart and bone marrow) and unresponsive to any other line of therapy. Both cases were only palliated by supportive therapy and revealed an impressively rapid response to colchicine both in terms of diuresis and clinical condition recovery, allowing for the cessation of renal replacement therapy in a few hours. In both patients, colchicine was temporarily discontinued for transient leukopenia (attributed to an additive effect with mycophenolate mofetil), resulting in extravasation, and renal failure recurrence was restored only after colchicine reintroduction. Although the association of colchicine with an immunosuppressive drug was formerly contraindicated, no other adverse events were noted when using a minimized dose. Both patients are now maintaining a good renal function without recurrence of extravasation after 6 months of follow-up. In conclusion, this strikingly positive experience forces physicians to consider this old and cost-effective drug as a new, powerful rescue tool in such critical cases. Copyright © 2019 by the American Academy of Pediatrics.

2018 AHA/ACC guideline for the management of adults with congenital heart disease: Executive summary: A report of the American College of Cardiology/American Heart Association Task Force on clinical practice guidelines - Stout, K.K.; Daniels, C.J.; Aboulhosn, J.A.; Bozkurt, B.; Broberg, C.S.; Colman, J.M.; Crumb, S.R.; Dearani, J.A.; Fuller, S.; Gurvitz, M.; Khairy, P.; Landzberg, M.J.; et al. (Circulation, 2019)
Keywords: AHA scientific statements; Arrhythmias; Cardiac catheterization; Cardiac defects; Congenital heart disease; Congenital heart surgery; Unoperated/repaired heart defect

Neurodevelopmental outcome in hypoplastic left heart syndrome after hybrid procedure - Reich, B.; Heye, K.N.; Wetterling, K.; Logeswaran, T.; Hahn, A.; Akintürk, H.; Jux, C.; Schranz, D. (Translational Pediatrics, 2019)
Background: Little is known about the mid-term outcome and brain development in patients following the hybrid approach for hypoplastic left heart syndrome (HLHS). This study investigates neurodevelopmental outcome, quality of life (QoL) and brain MRI findings in HLHS preschoolers treated with the hybrid approach. Methods: Twenty HLHS patients (60% males) have been examined after neonatal hybrid Stage I and comprehensive stage II operation at the Pediatric Heart Center Giessen, Germany, between 2012 and 2016. Patients were evaluated with the Bayley Scales of Infant and Toddler Development III (Bayley-III), neurological examination, the Preschool Children Quality of Life Questionnaire (TAPQOL) at age 26.5±3.6 months, and again at 39.7±3.9 months with the Pediatric Cardiac Quality of Life Inventory (PCQLI). Furthermore, brain volumetric measurements and conventional brain MRI findings (27.3±4.5 months) were analyzed and compared with six healthy controls (29.2±11.1 months, P=0.53). Children with verified genetic comorbidities were excluded. Results: Mean cognitive, language, and motor composite scores on the Bayley-III were not different from healthy norms (100±15), and were 101±9.3 (P=0.48), 100±13 (P=0.93), and 98±11.7 (P=0.45), respectively. Status post stroke was the most common brain MRI abnormality, and was found in 3/19 (16%) patients, most common affecting the middle cerebral artery territory. In comparison to controls, total white matter volumes were reduced (P=0.014), and cerebrospinal fluid (CSF) volumes were increased (P=0.042) in patients. Overall health-related QoL in 2 to 3 years aged children HLHS was good, but inferior scores in the motor subscale were noted compared to healthy norms (P=0.007). However, at 3 to 4 years, parents reported comparable QoL for their children in the PCQLI to children with biventricular heart lesion. Conclusions: HLHS patients followed by hybrid approach without major complications show a favorable neurodevelopment at 2–3 years of age. Despite extensive health-related burden, the vast majority of Fontan preschoolers with HLHS showed a good health-related QoL. Nevertheless, comprehensive care and establishing routine follow-up examinations are important to recognize long-term challenges and further improve neurodevelopmental outcome of this high-risk patient population. © Translational Pediatrics. All rights reserved.
Keywords: Brain development; Congenital heart disease (CHD); Hybrid procedure; Hypoplastic left heart syndrome (HLHS); Neurodevelopmental outcome

149 Fontan Conversions - Backer, C.L.; Mavroudis, C. (Methodist DeBakey cardiovascular journal, 2019)
Patients with a functionally univentricular heart who have had an atriopulmonary Fontan are at risk for atrial dilatation, atrial arrhythmias, and progressive circulatory failure. Between 1994 and 2018, we performed 149 Fontan conversions with arrhythmia surgery and epicardial pacemaker placement at Ann & Robert H. Lurie Children's Hospital of Chicago. This operation converts the atriopulmonary Fontan to an extracardiac Fontan that improves hemodynamics and controls the atrial arrhythmias. Operative mortality during that time was 2%, and freedom from death or heart transplant at 10 years is 84%. For properly selected patients, Fontan conversion improves both survival and quality of life. Patients with an atriopulmonary Fontan constitute an eroding population, as they face many comorbidities and have a decreased life expectancy without treatment; therefore, all patients with an atriopulmonary Fontan should be evaluated for this procedure.
Keywords: arrhythmia; atrial fibrillation; atriopulmonary Fontan; congenital heart surgery; cryoablation; epicardial pacemaker; Fontan conversion; protein-losing enteropathy; tricuspid atresia

Third Annual Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs) Report: Preimplant Characteristics and Outcomes - Morales, D.L.S.; Rossano, J.W.; VanderPluym, C.; Lorts, A.; Cantor, R.; St. Louis, J.D.; Koeh, D.; Sutcliffe, D.L.; Adachi, I.; Kirklin, J.K.; Rosenthal, D.N.; Blume, E.D.; et al. (Annals of Thoracic Surgery, 2019)
Background: The influence of ventricular assist device (VAD) use in the care of children with end-stage heart failure is growing rapidly through increasing numbers, new devices, expanding indications, and improving outcomes. Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs), a National Institutes of Health–sponsored United States database, provides a platform to understand this emerging population. Methods: Between September 19, 2012, and December 31, 2017, 30 hospitals implanted 508 devices in 423 patients aged younger than 19 years. This past year was one of evolution for the database as its management was transitioned to The Society of Thoracic Surgery; therefore, this report does not include data from institutions not under contract by August 1, 2018. Results: Of the 423 patients, the diagnosis was cardiomyopathy in 261 (62%), myocarditis in 48 (11%), other in 28 (7%), and congenital heart disease (CHD) in 86 (20%), with 52 of these patients having single-ventricle physiology. The two most common support strategies included left VAD in 342 (81%) and biventricular assist device in 64 (15%). Positive outcome (alive on device or bridge to transplantation/recovery) was 80% at 6 months (overall mortality of 20%). The patient cohort for implantable continuous-flow (IC) pumps (n = 197; age at implant, 13.4 ± 3.8 years; 19% Interagency Registry for Mechanically Assisted Circulatory Support [Intermacs] profile 1, 21% intubated at implant, and 12% with CHD) was significantly different from the paracorporeal continuous-flow (PC) pump cohort (n = 79; age, 3.9 ± 5.2 years; 49% Intermacs profile 1, 86% intubated at implant, and 38% with CHD) and the paracorporeal pulsatile (PP) pump cohort (n = 121; age, 3.3 ± 3.9 years; 41% Intermacs profile 1, 77% intubated at implant, and 21% with CHD). Consistent with their cohort composition, device type positive outcomes at 6 months were PC, 63%; PP, 77%; and IC, 92%. Parametric hazard modeling showed an early hazard for death was associated with Intermacs profile 1, biventricular assist device, percutaneous devices, PC devices, small-volume institutions, low age, and low weight, whereas a constant hazard was associated with intubation and liver dysfunction at time of implant. Conclusions: IC VADs are the most common VAD type placed in children. The positive outcomes for the IC VADs exceed 90% at 6 months, which may represent our field's maturation in both patient selection and timing of implantation. The PP/PC devices are currently limited to supporting our most challenging patients, those weighing less than 20 kg and those with CHD. The introduction of new devices and our communities’ commitment to shared learning and improvement will lead to more pediatric lives saved by VAD support and will also focus on improving the quality of life of children supported with VADs. © 2019 The Society of Thoracic Surgeons

Outcomes and associated ethical considerations of long-run pediatric ECMO at a single center institution - Ares, G.J.; Buonpane, C.; Helenowski, I.; Reynolds, M.; Hunter, C.J. (Pediatric Surgery International, 2019)
Purpose: Survival of neonatal and pediatric patients undergoing extracorporeal membrane oxygenation (ECMO) ≥ 21 days has not been well described. We hypothesized that patients would have poor survival and increased long-term complications. Methods: Retrospective, single center, review and case analysis. Tertiary-care university children’s hospital including neonatal, pediatric and cardiac intensive care units. After institutional review board approval, the charts of all patients < 18 years of age undergoing ECMO for ≥ 21 continuous days were performed, and they were compared to comparative patients undergoing shorter runs. Overall survival, incidence of complications, and post-discharge recovery were recorded. Results: Overall survival was 36% in patients undergoing ≥ 21 days of ECMO (N = 14). 5/8 patients with cardiopulmonary failure from acquired etiologies survived versus 0/6 patients with congenital anomalies. 1/5 survivors achieved complete recovery with no neurologic deficits. The remaining survivors suffer from multiple medical and neurodevelopmental morbidities. Conclusion: ECMO support for ≥ 21 days is associated with poor survival, particularly in neonates with congenital anomalies. Long-term outcomes for survivors ought to be carefully weighed and discussed with parents given the high incidence of neurologic morbidities in this population. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Long-run; Moral distress, Ethics; Neonatal ECMO; Neurodevelopmental outcome; Pediatric ECMO

Amiodarone toxicity in two post-operative congenital heart disease patients - Covi, S.; Clark, J.; Delius, R.; Chauhan, M. (Progress in Pediatric Cardiology, 2019)
Amiodarone is a class III antiarrhythmic medication known for its efficacy in treating tachyarrhythmias. The pulmonary complications including acute lung toxicity are well documented in the adult population, however much less so in pediatrics. We describe two pediatric congenital heart disease patients with suspected amiodarone induced pulmonary toxicity in the post-operative period. Case 1 presented with acute respiratory distress syndrome accompanied by periods of pulmonary hemorrhage post-operatively; after multiple courses of methylprednisolone and discontinuation of amiodarone, she showed significant clinical improvement with normalization of her CXR. Case 2 presented as hypoxemic with acute respiratory distress syndrome, and had notable clinical improvement after cessation of amiodarone with pulse dose methylprednisolone and inhaled budesonide. © 2018 Elsevier B.V.
Keywords: Acute respiratory distress syndrome; Amiodarone; Congenital heart disease; Pediatrics; Toxicity

Cardiac magnetic resonance imaging of mechanical cavopulmonary assistance - Chopski, S.G.; Whitehead, K.; Englehardt, G.J.; Throckmorton, A. (Journal of Medical Devices, Transactions of the ASME, 2019)
Mechanical circulatory support (MCS) options are limited for patients with dysfunctional single ventricle physiology. To address this unmet clinical need, we are developing an axial-flow blood pump to provide mechanical assistance to the cavopulmonary circulation. In this study, we investigate the use of high-resolution cardiac magnetic resonance imaging (MRI) to visualize the complex fluid flow conditions of mechanical circulatory assist in two patient-specific Fontan anatomies. A three-bladed axial-flow impeller coupled to a supportive cage with a four-bladed diffuser was positioned in the inferior vena cava (IVC) of each Fontan anatomy. Cardiac magnetic resonance (CMR) imaging and power efficiency studies were conducted at physiologic relevant parameters with cardiac outputs of 2, 3, and 4 L/min with impeller rotational speeds of 2000 and 4000 rpm. The axial-flow impeller was able to generate improved flow in the total cavopulmonary connection (TCPC). The higher rotational speed was able to redistribute flow in the TCPC anastomosis aiding in removing stagnant blood. No retrograde flow was observed or measured in the superior vena cava (SVC). As an extension of the CMR data, a scalar stress analysis was performed on both models and found a maximum scalar stress of approximately 42 Pa for both patient anatomies. The power efficiency experiments demonstrated a maximum energy gain of 8.6 mW for TCPC Anatomy 1 and 12.58 mW for TCPC Anatomy 2 for a flow rate of 4 L/min and at 4000 rpm. These findings support the continued development of axial blood pumps for mechanical cavopulmonary assist. © 2019 by ASME.
Keywords: cardiac magnetic resonance; CMR; mechanical circulatory assistance; PC-MRI; pediatric circulatory support; rotary blood pump

Neurodevelopmental assessment of infants with congenital heart disease in the early postoperative period - Butler, S.C.; Sadhwani, A.; Stopp, C.; Singer, J.; Wypij, D.; Dunbar-Masterson, C.; Ware, J.; Newburger, J.W. (Congenital Heart Disease, 2019)
Objective: Mortality rates for children with congenital heart disease (CHD) have significantly declined, resulting in a growing population with associated neurodevelopmental disabilities. American Heart Association guidelines recommend systematic developmental screening for children with CHD. The present study describes results of inpatient newborn neurodevelopmental assessment of infants after open heart surgery. Outcome measures: We evaluated the neurodevelopment of a convenience sample of high-risk infants following cardiac surgery but before hospital discharge using an adaptation of the Newborn Behavioral Observation. Factor analysis examined relationships among assessment items and consolidated them into domains of development. Results: We assessed 237 infants at a median of 11 days (interquartile range [IQR]: 7-19 days) after cardiac surgery and median corrected age of 21 days (IQR: 13-33 days). Autonomic regulation was minimally stressed or well organized in 14% of infants. Upper and lower muscle tone was appropriate in 33% and 35%, respectively. Appropriate response to social stimulation ranged between 7% and 12% depending on task, and state regulation was well organized in 14%. The vast majority (87%) required enhanced examiner facilitation for participation. Factor analyses of assessment items aligned into four domains of development (autonomic, motor, oral motor, and attention organization). Conclusion: At discharge, postoperative infants with CHD had impairments in autonomic, motor, attention, and state regulation following cardiac surgery. Findings highlight the challenges faced by children with CHD relative to healthy peers, suggesting that neurodevelopmental follow-up and intervention should begin early in infancy. © 2018 Wiley Periodicals, Inc.
Keywords: assessment; cardiac; developmental impairments; infancy; neurodevelopment

The Case for Cardiac Xenotransplantation in Neonates: Is Now the Time to Reconsider Xenotransplantation for Hypoplastic Left Heart Syndrome? - Cleveland, D.; Adam Banks, C.; Hara, H.; Carlo, W.F.; Mauchley, D.C.; Cooper, D.K.C. (Pediatric Cardiology, 2019)
Neonatal cardiac transplantation for hypoplastic left heart syndrome (HLHS) is associated with excellent long-term survival compared to older recipients. However, heart transplantation for neonates is greatly limited by the critical shortage of donor hearts, and by the associated mortality of the long pre-transplant waiting period. This led to the development of staged surgical palliation as the first-line surgical therapy for HLHS. Recent advances in genetic engineering and xenotransplantation have provided the potential to replicate the excellent results of neonatal cardiac allotransplantation while eliminating wait-list-associated mortality through genetically modified pig-to-human neonatal cardiac xenotransplantation. The elimination of the major pig antigens in addition to the immature B-cell response in neonates allows for the potential to induce B-cell tolerance. Additionally, the relatively mature neonatal T-cell response could be reduced by thymectomy at the time of operation combined with donor-specific pig thymus transplantation to “reprogram” the host’s T-cells to recognize the xenograft as host tissue. In light of the recent significantly increased graft survival of genetically-engineered pig-to-baboon cardiac xenotransplantation, we propose that now is the time to consider devoting research to advance the potential clinical application of cardiac xenotransplantation as a treatment option for patients with HLHS. Employing cardiac xenotransplantation could revolutionize therapy for complex congenital heart defects and open a new chapter in the field of pediatric cardiac transplantation. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Congenital heart disease; Genetically-engineered; Immunological tolerance; Pig; Staged surgical palliation; Xenotransplantation

Need for Routine Screening of Health-Related Quality of Life in Families of Young Children with Complex Congenital Heart Disease - Denniss, D.L.; Sholler, G.F.; Costa, D.S.J.; Winlaw, D.S.; Kasparian, N.A. (Journal of Pediatrics, 2019)
Objectives: To assess health-related quality of life (HRQOL) in families of young children with complex congenital heart disease (CHD), and identify the demographic, clinical, and psychosocial factors that place these children and their mothers at greater risk of vulnerability. Study design: This cross-sectional study took place from June 2015 to October 2016 at The Sydney Children's Hospitals Network Cardiac Service, Australia. Mothers of a child aged 1-5 years with either single ventricle CHD or CHD requiring neonatal biventricular repair were invited to participate. Eighty-seven mothers completed a suite of validated measures, including the Pediatric Quality of Life Inventory, which assessed the outcomes of child and maternal HRQOL. Results: Sixty percent of children with single ventricle CHD and 25% of children with biventricular repair had total Pediatric Quality of Life Inventory scores within the at-risk range. Lower child HRQOL was strongly associated with single ventricle CHD (β = −0.38; P <.001), physical comorbidity (β = −0.32; P =.001), feeding difficulties (β = −0.26; P =.008), and greater maternal psychological stress (β = −0.18; P =.045), accounting for 52% of the variance in child HRQOL. Lower maternal HRQOL was strongly associated with poorer family functioning (β = 0.61; P <.001), greater maternal psychological stress (β = −0.23; P =.004), child physical comorbidity (β = −0.17; P =.01), and a ‘difficult’ child temperament (β = −0.14; P =.01), accounting for 73% of the variance in maternal HRQOL. Conclusions: Lower HRQOL is common in young children with complex CHD, particularly single ventricle CHD. Several predictors of HRQOL are potentially modifiable, offering possible pathways for prevention and early intervention. Routine screening is a necessary first step toward developing models of care to improve HRQOL in this population. © 2018 Elsevier Inc.
Keywords: child development; congenital heart disease; integrated care; mental health; psychological stress; psychosocial screening; quality of life

Health-related quality of life in pre-school age children with single-ventricle CHD - Heye, K.N.; Knirsch, W.; Scheer, I.; Beck, I.; Wetterling, K.; Hahn, A.; Hofmann, K.; Latal, B.; Reich, B.; Landolt, M.A. (Cardiology in the Young, 2019)
Background: Little is known about health-related quality of life in young children undergoing staged palliation for single-ventricle CHD. The aim of this study was to assess the impact of CHD on daily life in pre-schoolers with single-ventricle CHD and to identify determinants of health-related quality of life. Method: Prospective two-centre cohort study assessing health-related quality of life using the Preschool Paediatric Cardiac Quality of Life Inventory in 46 children at a mean age of 38 months and 3 weeks. Children with genetic anomalies were excluded. Scores were compared with reference data of children with biventricular CHD. Multiple linear regression analysis was used to identify determinants of health-related quality of life. Results: Health-related quality of life in pre-schoolers with single-ventricle CHD was comparable to children with biventricular CHD. Preterm birth and perioperative variables were significant predictors of low health-related quality of life. Notably, pre-Fontan brain MRI findings and neurodevelopmental status were not associated with health-related quality of life. Overall, perioperative variables explained 24% of the variability of the total health-related quality of life score. Interpretation: Despite substantial health-related burden, pre-schoolers with single-ventricle CHD showed good health-related quality of life. Less-modifiable treatment-related risk factors and preterm birth had the highest impact on health-related quality of life. Long-term follow-up assessment of self-reported health-related quality of life is needed to identify patients with poorer health-related quality of life and to initiate supportive care. © 2018 Cambridge University Press.
Keywords: CHD; Health-related quality of life; risk factors; single-ventricle

Atrioventricular reentrant tachycardia in a child with tricuspid atresia: A case report of catheter ablation - Wang, Y.; Liu, Q.; Deng, X.; Xiao, Y.; Chen, Z. (Medicine (United States), 2019)
Rationale:Atrioventricular reentrant tachycardia (AVRT) is the most common supraventricular tachycardia occurring in children. However, in complex congenital heart disease patients with a different heart anatomy and conduction system morphology, accessory pathway modification may be particularly challenging because of distortion of typical anatomic landmarks.Patient concerns:A 10-year-old boy with tricuspid atresia and history of bidirectional Glenn operation had recurrent chest distress and palpitation for 3 months. He had multiple hospitalizations for narrow-QRS tachycardia with poor hemodynamic tolerance, despite the use of adenosine and amiodarone.Diagnoses:AVRT. Tricuspid atresia with secundum atrial septal defect, large ventricular septal defect, and right ventricular outflow tract stenosis.Interventions:Cardiac catheterization, electrophysiological examination, and ablation.Outcomes:The child has not had a recurrent AVRT during 6 months of follow-up and is waiting for Fontan operation.Lessons:Since there is an increased risk of accessory pathways in patients with tricuspid atresia, all these patients should be checked before the Fontan operation to exclude congenital accessory pathways. © 2019 the Author(s). Published by Wolters Kluwer Health, Inc..
Keywords: Atrioventricular reentrant tachycardia; catheter ablation; children; tricuspid atresia

Quality of life in young people with congenital heart disease is better than expected - Reiner, B.; Oberhoffer, R.; Ewert, P.; Müller, J. (Archives of Disease in Childhood, 2019)
Objectives Improved treatments for patients with congenital heart disease (CHD) have led to a growing interest in long-term functional outcomes such as health-related quality of life (HRQoL). Studies on HRQoL in children with CHD have contradicting results. Therefore, we compared HRQoL of children with CHD with that of current healthy peers and stratify CHD cases by severity and diagnostic subgroups. Methods We included 514 patients (191 girls) aged 7-17 (12.9±3.1) years who were recruited at our institution between July 2014 and May 2017. The self-reported and age-adapted KINDL questionnaire was used to assess HRQoL. Patient data were compared with that of a recent control group of 734 healthy children (346 girls, 13.4±2.1 years). Results Patients with CHD scored at least as high as healthy peers in HRQoL (CHD: 78.6±9.8; healthy: 75.6±10.1; P<0.001). After correction for sex and age, patients with CHD presented a 2.3-point higher HRQoL (P<0.001). The sex-specific and age-specific analyses showed that there were no differences between boys with and without CHD in childhood (P=0.255), but in adolescence, boys with CHD had on average 3.9-point higher scores (P=0.001), whereas girls with CHD had statistically higher HRQoL perception than healthy girls in childhood (4.2 points; P=0.003) and adolescence (4.2 points; P=0.005). There were no differences between the severity classes or diagnostic subgroups in the total HRQoL score or in the six subdomains. Conclusion The high HRQoL in young patients with CHD suggests that they can cope well with their disease burden. This holds true for all severity classes and diagnostic subgroups. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2019. All rights reserved. No commercial use is permitted unless otherwise expressly granted.
Keywords: Health-related quality of life; severity of heart defects

Outcomes of the conversion of the fontan-kreutzer operation to a total cavopulmonary connection for the failing univentricular circulation - Fernandes, G.C.; da Silva, G.V.R.; Caneo, L.F.; Tanamati, C.; Turquetto, A.L.R.; Jatene, M.B. (Arquivos Brasileiros de Cardiologia, 2019)
Background: The Fontan-Kreutzer procedure (FK) was widely performed in the past, but in the long-term generated many complications resulting in univentricular circulation failure. The conversion to total cavopulmonary connection (TCPC) is one of the options for treatment. Objective: To evaluate the results of conversion from FK to TCPC. Methods: A retrospective review of medical records for patients who underwent the conversion of FK to TCPC in the period of 1985 to 2016. Significance p < 0,05. Results: Fontan-type operations were performed in 420 patients during this period: TCPC was performed in 320, lateral tunnel technique in 82, and FK in 18. Ten cases from the FK group were elected to conversion to TCPC. All patients submitted to Fontan Conversion were included in this study. In nine patients the indication was due to uncontrolled arrhythmia and in one, due to protein-losing enteropathy. Death was observed in the first two cases. The average intensive care unit (ICU) length of stay (LOS) was 13 days, and the average hospital LOS was 37 days. A functional class by New York Heart Association (NYHA) improvement was observed in 80% of the patients in NYHA I or II. Fifty-seven percent of conversions due to arrhythmias had improvement of arrhythmias; four cases are cured. Conclusions: The conversion is a complex procedure and requires an experienced tertiary hospital to be performed. The conversion has improved the NYHA functional class despite an unsatisfactory resolution of the arrhythmia. © 2019, Arquivos Brasileiros de Cardiologia. All rights reserved.
Keywords: Arrihythmias; Cardiac/surgery; Fontan procedure; Fontan-Kreutzer prodedure; Heart defects congenital/surgery; Mortality

Innovative 2-Step Management Strategy Utilizing EXIT Procedure for a Fetus With Hypoplastic Left Heart Syndrome and Intact Atrial Septum - Said, S.M.; Qureshi, M.Y.; Taggart, N.W.; Anderson, H.N.; O'Leary, P.W.; Cetta, F.; Alrahmani, L.; Cofer, S.A.; Segura, L.G.; Pike, R.B.; Sharpe, E.E.; Derleth, D.P.; et al. (Mayo Clinic Proceedings, 2019)
Hypoplastic left heart syndrome (HLHS) with intact atrial septum (HLHS-IAS) carries a high risk of mortality and affects about 6% of all patients with HLHS. Fetal interventions, postnatal transcatheter interventions, and postnatal surgical resection have all been used, but the mortality risk continues to be high in this subgroup of patients. We describe a novel, sequential approach to manage HLHS-IAS and progressive fetal hydrops. A 28-year-old, gravida 4 para 2 mother was referred to Mayo Clinic for fetal HLHS. Fetal echocardiography at 28 weeks of gestation demonstrated HLHS-IAS with progressive fetal hydrops. The atrial septum was thick and muscular with no interatrial communication. Ultrasound-guided fetal atrial septostomy was performed with successful creation of a small atrial communication. However, fetal echocardiogram at 33 weeks of gestation showed recurrence of a pleural effusion and restriction of the atrial septum. We proceeded with an Ex utero Intrapartum Treatment (EXIT) delivery and open atrial septectomy. This was performed successfully, and the infant was stabilized in the intensive care unit. The infant required venoarterial extracorporeal membrane oxygenator support on day of life 1. The patient later developed hemorrhagic complications, leading to his demise on day of life 9. This is the first reported case of an EXIT procedure and open atrial septectomy performed without cardiopulmonary bypass for an open-heart operation and provides a promising alternative strategy for the management of HLHS-IAS in select cases. © 2018 Mayo Foundation for Medical Education and Research

Variations in Criteria and Practices for Heart Transplantation Listing Among Pediatric Transplant Cardiologists - Patel, A.; Michelson, K.; Andrei, A.-C.; Pahl, E.; Gossett, J.G. (Pediatric Cardiology, 2019)
Ethical issues in pediatric heart transplantation (Htx) include resource allocation, benefit, and burden assessment in high-risk recipients, and informed consent. Practice patterns and decision-making was investigated using an internet survey with 47-multiple choice items and vignette-based questions. Of 43 pediatric Htx cardiologists contacted, 28 (65%) responded. Respondents reported that an overall median 1-month survival of 73% (range 50–100%), 1-year survival of 70% (range 50–85%), 5-year survival of 50% (range 40–85%), and 10-year survival of 50% (range 25–85%) was adequate to offer Htx. Based on vignettes presented, 100% of those surveyed would offer Htx to a straightforward 12-year old with end-stage dilated cardiomyopathy and a 7-year old with hypoplastic left heart syndrome with protein losing enteropathy. Thirty percent of physicians would offer Htx to a patient status post a Fontan procedure with mutliple co-morbidities. Seventy-five percent of physicians would offer Htx despite proven non-adherence. Considerable variability exists in the practice patterns of pediatric heart transplant cardiologists with regards to decision-making while evaluating patients for listing. Disagreements among pediatric Htx cardiologists exist when there are concerns for non-adherence and associated multiple co-morbidities. Further work is needed to understand these variations and develop consensus for pediatric Htx organ allocation. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Ethics; Heart transplantation; Pediatric

Paediatric donation after circulatory determined death heart transplantation using donor normothermic regional perfusion and ex situ heart perfusion: A case report - Khushnood, A.; Butt, T.A.; Jungschleger, J.; Henderson, P.; Smith, J.H.; De Rita, F.; Nassar, M.; Page, A.; Messer, S.; Large, S.; Dark, J.H.; Parry, G.; et al. (Pediatric Transplantation, 2019)
This is a report of a unique DCD paediatric heart transplant whereby normothermic regional perfusion was used to assess DCD heart function after death followed by ex situ heart perfusion of the graft during transportation from donor to recipient hospitals. The DCD donor was a 9-year-old boy weighing 84 kg. The recipient was 7-year-old boy with failing Fontan circulation and weighed 23 kg. It was an ABO-compatible heart transplantation. The DCD heart was reperfused and assessed using normothermic regional perfusion followed by portable ex situ heart perfusion during transportation. The orthotopic heart transplantation was successful with good graft function and no evidence of rejection on endomyocardial biopsy at 30 days post-transplant. At 1-year follow-up, excellent graft function is maintained, and he is attending school with a good quality of life. DCD heart transplantation in children is a promising solution to reducing paediatric waiting times. The case demonstrates the feasibility of using normothermic regional perfusion in the donor and ex situ heart perfusion during graft transportation. This combination allowed a functional assessment whilst minimizing warm ischaemia resulting in a successful outcome. More research and long-term follow-up are needed in order to benefit from the huge potential that paediatric DCD heart transplantation has to offer. © 2019 Wiley Periodicals, Inc.
Keywords: donation after circulatory determined death; heart transplantation; normothermic regional perfusion; paediatric

Conjoined Twins Separation Leading to the Death of One Twin: An Expanded Ethical Analysis of Issues Facing the ICU Team - Cummings, B.M.; Paris, J.J. (Journal of Intensive Care Medicine, 2019)
A recent case of conjoined twins required multiple hospitalizations in the pediatric intensive care unit and led to a difficult situation confronting staff regarding the potential separation where surgery would result in the death of one twin. The hospital ethics committee was consulted. A systematic approach was utilized to examine medical standards, historical precedents, and various ethical and legal frameworks. The ethics committee believed that either proceeding with or forgoing attempted separation surgery would be ethically acceptable. We share our reasoning and lessons learned for others facing this situation in the future. © The Author(s) 2018.
Keywords: decision-making; disagreement; end-of-life care; ethics consultations; pediatric intensive care

Positive pediatric exercise capacity trajectory predicts better adult Fontan physiology rationale for early establishment of exercise habits - Ohuchi, H.; Negishi, J.; Miike, H.; Toyoshima, Y.; Morimoto, H.; Fukuyama, M.; Iwasa, T.; Sakaguchi, H.; Miyazaki, A.; Shiraishi, I.; Kurosaki, K.; Nakai, M. (International Journal of Cardiology, 2019)
Objective: Exercise training is recommended for its possible favorable effects on Fontan pathophysiology. This study aimed to elucidate the impact of pediatric exercise capacity trajectory, which may mimic the effect of exercise training, on late adult Fontan pathophysiology. Methods: Since 1990, 97 Fontan patients had consecutively undergone two serial cardiopulmonary exercise tests (CPX1 and CPX2) during childhood (ages 8 ± 2 and 14 ± 2 years) and one during adulthood (CPX3; age 23 ± 5 years). The changes in peak oxygen uptake (PVO2: % of normal value) from CPX1 to CPX2 (1-dPVO2) and from CPX2 to CPX3 (2-dPVO2) were calculated, and then the patients were divided into four subgroups according the 1-dPVO2 and 2-dPVO2. Results: In their adulthood, when compared with groups with negative 1-dPVO2, the central venous pressure, plasma brain natriuretic peptide level, and renal resistive index were lower, whereas liver synthetic function, body fat-free percentage, and PVO2 were higher in those with positive 1-dPVO2 (p < 0.05–0.0001). However, these favorable associations of 2-d-PVO2 with adult Fontan pathophysiology were not observed, except for the PVO2. After CPX3, 13 unexpected events occurred, and the risk was 76% lower in the groups having positive 1-dPVO2 than in those with negative 1-dPVO2 (hazard ratio, 0.24; 95% confidence interval, 0.09–0.62; p = 0.0035). Conclusions: A positive exercise capacity trajectory during childhood predicts better adult Fontan pathophysiology, including better prognosis. Thus, prescription of exercise could be a promising strategy in the management of pediatric Fontan patients. © 2018 Elsevier B.V.
Keywords: Adulthood; Childhood; Exercise capacity; Fontan operation; Morbidity

Oxygen availability in respiratory muscles during exercise in children following fontan operation - Stöcker, F.; Neidenbach, R.; Fritz, C.; Oberhoffer, R.M.; Ewert, P.; Hager, A.; Nagdyman, N. (Frontiers in Pediatrics, 2019)
Introduction: As survival of previously considered as lethal congenital heart disease forms is the case in our days, issues regarding quality of life including sport and daily activities emerge. In patients with Fontan circulation, there is no pump to propel blood into the pulmonary arteries since the systemic veins are directly connected to the pulmonary arteries. The complex hemodynamics of Fontan circulation include atrial function, peripheral muscle pump, integrity of the atrioventricular valve, absence of restrictive, or obstructive pulmonary lung function. Therefore, thoracic mechanics are of particular importance within the complex hemodynamics of Fontan circulation. Methods: To understand the physiology of respiratory muscles, the aim of this study was to examine the matching of auxiliary respiratory muscle oxygen delivery and utilization during incremental exercise in young male Fontan patients (n = 22, age = 12.04 ± 2.51) and healthy Controls (n = 10, age = 14.90 ± 2.23). All subjects underwent a cardiopulmonary exercise test (CPET) to exhaustion whereas respiratory muscle oxygenation was measured non-invasively using a near-infrared spectrometer (NIRS). Results: CPET revealed significantly lower peak power output, oxygen uptake and breath activity in Fontan patients. The onset of respiratory muscle deoxygenation was significantly earlier. The matching of local muscle perfusion to oxygen demand was significantly worse in Fontans between 50 and 90% V.O2peak. Findings: The results indicate that (a) there is high strain on respiratory muscles during incremental cycling exercise and (b) auxiliary respiratory muscles are worse perfused in patients who underwent a Fontan procedure compared to healthy Controls. This might be indicative of a more general skeletal muscle strain and worse perfusion in Fontan patients rather than a localized-limited to thoracic muscles phenomenon. © 2019 Stöcker, Neidenbach, Fritz, Oberhoffer, Ewert, Hager and Nagdyman.
Keywords: CHD; Fontan; Muscle oxygenation; NIRS; Pediatrics; Respiratory muscles

Evaluation of Fontan liver disease: Correlation of transjugular liver biopsy with magnetic resonance and hemodynamics - Silva-Sepulveda, J.A.; Fonseca, Y.; Vodkin, I.; Vaughn, G.; Newbury, R.; Vavinskaya, V.; Dwek, J.; Perry, J.C.; Reshamwala, P.; Baehling, C.; Lyon, J.; Davis, C.; et al. (Congenital Heart Disease, 2019)
Introduction: Liver fibrosis and cirrhosis are late complications in Fontan palliation. Liver biopsy is the gold standard. The goal of this study is to correlate transjugular liver biopsy (TJLB) in the setting of Fontan palliation with noninvasive testing and hemodynamics. Methods: Between August 2014 and July 2017, 49 Fontan patients underwent TJLB. All the patients had hemodynamic evaluation, 28 patients had MRE (magnetic resonance elastography) and 40 patients had cardiopulmonary exercise test. Histologic liver fibrosis was quantitated using traditional histologic scoring systems and a modified Ishak congestive hepatic fibrosis score. Results: Median age 17.8 years, median time since Fontan 15.2 years. Primary diagnosis and Fontan type were variables, but predominantly LV morphology (30/49), lateral tunnel Fontan (29/49), originally fenestrated (37/49), and 11/49 had a pacemaker. Histologic fibrosis correlated with MRE (R = 0.62, P ≤.001). Histologic fibrosis and MRE correlated with Fontan pressure (R = 0.38, P =.008 & R = 0.59, P ≤.001). Morphology of the single ventricle did not correlate with liver fibrosis. The presence of a fenestration resulted in a higher cardiac index (P =.026) but did not resulted in lower liver fibrosis (P =.64). Conclusion: Noninvasive tests, such as MRE, may be suitable for longitudinal follow-up in patients with single ventricle physiology. Our data suggest that there is reasonable correlation of MRE liver stiffness with biopsy scoring systems and Fontan pressures. We demonstrated the feasibility of TJLB in the setting of Fontan palliation and demonstrated its correlation with noninvasive measures particularly MRE. We recommend selective use of TJLB when MRE score is >5 KPa or when there are other clinical signs of cirrhosis. © 2019 Wiley Periodicals, Inc.
Keywords: cirrhosis; exercise stress test; fontan; liver biopsy; magnetic resonance elastography; transient elastography

IMPACT Registry and National Pediatric Cardiology Quality Improvement Collaborative: Contributions to Quality in Congenital Heart Disease - Martin, G.R.; Anderson, J.B.; Vincent, R.N. (World journal for pediatric & congenital heart surgery, 2019)
The IMproving Pediatric and Adult Congenital Treatments (IMPACT) Registry and the National Pediatric Cardiology Quality Improvement Collaborative (NPC-QIC) are two efforts initiated to improve outcomes in the congenital heart disease field. The IMPACT Registry is focused on evaluating the use, risks, adverse events (AEs), and outcomes associated with diagnostic and common interventional catheterization procedures in all children and adults with congenital heart disease. Utilizing a modular approach, the common procedures include diagnostic cardiac catheterization, atrial septal defect device closure, patent ductus arteriosus device closure, pulmonary valvuloplasty, aortic valvuloplasty, balloon and stent angioplasty of coarctation of the aorta, pulmonary artery balloon stent angioplasty, transcatheter pulmonary valve replacement, and electrophysiology procedures including radiofrequency ablation. To date, important observations on the common procedures have been made and a risk stratification methodology has been created to allow comparisons between centers in AEs and quality improvement activity. The registry is open to international participation. The NPC-QIC was developed to reduce mortality and improve the quality of life of infants with Hypoplastic Left Heart Syndrome (HLHS) during the interstage period between discharge from the Norwood operation and admission for the bidirectional Glenn procedure. Mortality in the interstage has been reduced by 44%. The IMPACT Registry and the NPC-QIC have demonstrated value to the congenital heart disease community. The IMPACT Registry, however, has not yet demonstrated an impact on patient outcomes. The NPC-QIC, which combines both a registry with a learning collaborative with specific aims, key drivers, and change strategies, has made more significant gains with reductions in variation, growth failures, and mortality.
Keywords: cardiac catheterization/intervention; congenital heart disease; databases; outcomes

Functional capacity in children and adolescents with congenital heart disease - Schaan, C.W.; Feltez, G.; D’Agord Schaan, B.; Pellanda, L.C. (Revista Paulista de Pediatria, 2019)
Objective: To evaluate the physical activity level and functional capacity of children and adolescents with congenital heart disease and to describe correlations between functionality, surgical and echocardiographic findings, metabolic and inflammatory profile and differences between acyanotic and cyanotic heart defects. Methods: A cross-sectional study including children and adolescents with congenital heart disease between six and 18 years old that were evaluated with the 6-minute walk test (6MWT) to assess functional capacity. The short version form of the International Physical Activity Questionnaire (IPAQ) was performed to evaluate physical activity levels. Also, echocardiography and blood collection, to evaluate the metabolic (blood glucose, lipids, insulin) and inflammatory markers (C-reactive protein), were assessed. Results: Twenty-five individuals were evaluated. Of them, 14 had acyanotic heart defects and 11 cyanotic heart defects. Mean age was 12.0±3.7 years, and 20 (80%) were male. IPAQ showed that six (24%) individuals were very active, eight (32%) were active, nine (36%) had irregular physical activity, and two (8%) were sedentary. The mean distance walked in the 6MWT, considering all studied individuals, was 464.7±100.4 m, which was 181.4±42.0 m less than the predicted (p=0.005). There was a positive correlation between Z score 6MWT and the number of surgical procedures (r=-0.455; p=0.022). Conclusions: Children and adolescents with congenital heart disease have low functional capacity, but they are not completely sedentary. © 2019 Sociedade de Pediatria de São Paulo. Published by Zeppelini Publishers.
Keywords: Adolescent; Child; Congenital; Exercise tolerance; Heart defects

Plastic bronchitis: A case report - Grizales, C.L.; González, L.M.; Castrillon, M.A.; Sua, L.F.; Lores, J.; Aguirre, M.; Fernández-Trujillo, L. (Respiratory Medicine Case Reports, 2019)
Plastic bronchitis is a rare and underdiagnosed disease characterized by the formation and expectoration of bronchial casts of amorphous material, which can be potentially fatal. It is more frequent in pediatric population. Symptoms can range from chronic cough and dyspnea to respiratory failure depending on the area of the compromised airway. Casts are classified as type I when constituted by inflammatory cells and accompany diseases such as asthma and pneumonias; and type II when acellular and are associated with congenital heart diseases following procedures such as Fontan. We report the case of a male schoolchild with a history of complex congenital heart disease, treated with palliative surgery, evaluated in the emergency department for cough and respiratory distress. The mother referred expulsion of gelatinous material after coughing. During clinical evaluation, expulsion of bronchial casts was evidenced, suggesting a plastic bronchitis. He underwent a diagnostic and therapeutic bronchoscopy and received initial treatment with respiratory therapy, nebulized hypertonic saline solution, mucolytics, dornase alpha and nebulized heparin. The hospitalization revealed a stenosis of the right pulmonary artery, which was corrected with stent. The patient progressed satisfactorily with improvement of cough and expectoration. He was discharged with combined treatment, nebulized medications and those concerning his underlying disease. © 2019
Keywords: Bronchial casts; Congenital heart disease; Fontan; Plastic bronchitis

Outcomes and factors associated with early mortality in pediatric and neonatal patients requiring extracorporeal membrane oxygenation for heart and lung failure - Azizov, F.; Merkle, J.; Fatullayev, J.; Eghbalzadeh, K.; Djordjevic, I.; Weber, C.; Saenko, S.; Kroener, A.; Zeriouh, M.; Sabashnikov, A.; Bennink, G.; Wahlers, T. (Journal of Thoracic Disease, 2019)
Background: Mortality and morbidity after surgical repair for complex congenital heart defects and severe cardiopulmonary failure on extracorporeal membrane oxygenation (ECMO) support remain high despite significant advances in medical management and technological improvements. We report on outcomes and factors after using ECMO in our surgical pediatric population including short- and long-term survival. Methods: A total of 45 neonatal and pediatric patients were identified who needed ECMO in our department between January 2008 and December 2016. In 41 cases (91%) a vaECMO (ECLS) was implemented, whereas 4 patients (9%) received vvECMO treatment for respiratory failure. In 33 cases vaECMO was implanted following cardiac surgery for congenital heart disease (CHD), whereas in 8 patients ECMO was utilized by means of extracorporeal cardiopulmonary resuscitation (eCPR) following refractory cardiac arrest. The primary endpoint of the present study was survival to discharge and long-term survival free from neurological impairments. Univariate and bivariate analysis was performed to address predictors for outcome. Kaplan-Meier survival analysis was used to address mid- and long-term survival. Results: Median [IQR] duration of ECMO support was 3 [2, 5] days (range, 1–17 days). Median age at ECMO implantation was 128 [14, 1,813] days, median weight of patients was 5.4 [3.3, 12] kg. Totally 10 patients included in this study were diagnosed with concomitant genetic conditions. A total of 20 (44%) patients were successfully weaned off ECMO (survived >24 h after ECMO explantation), whereas 15 (33%) of them survived to discharge. Single ventricle (SV) repair was performed in 14, biventricular repair in 19 patients. Neonates (<30 days of age), female patients, patients with genetic conditions, SV repair patients, and eCPR patient cohort showed lower odds of survival on ECMO. Failed myocardial recovery (P=0.001), profound circulatory failure despite a high dose of catecholamines (P<0.001), neurological impairment pre-ECMO and post-ECMO (P=0.04 and P<0.001, respectively), and severe pulmonary failure despite high respiratory pressure settings were most common mortality reasons. Conclusions: ECMO provides efficient therapy opportunities for life-threatening conditions. Nevertheless, neonates and pediatric patients who underwent ECMO were at high risk for cerebrovascular events and poor survival. Appropriate patient selection using predictors of outcome reducing complications might improve outcomes of this patient cohort. © Journal of Thoracic Disease. All rights reserved.
Keywords: Congenital cardiac surgery (CCS); Extracorporeal membrane oxygenation (ECMO); Neonatal; Pediatric and neonatal patients; Pediatric intensive care unit; Resuscitation

Exploring associations of maternal sleep during periconceptional period with congenital heart disease in offspring - Zhao, A.; Zhao, K.; Xia, Y.; Yin, Y.; Zhu, J.; Hong, H.; Li, S. (Birth Defects Research, 2019)
Background: In general, the existing evidence points to a role for maternal sleep in pregnancy complications and fetal growth, however, little has been focused on birth defects. We aimed to explore the association between periconceptional poor sleep and the risk of congenital heart disease (CHD), and to examine if daytime napping could to some extent change the association. Methods: A case–control study was conducted in Shanghai Children's Medical Center, in which, a total of 524 cases (262 simple CHD vs. 262 severe CHD), along with 262 controls. Results: In the multivariable logistic analysis, poor sleep could increase the risk of both simple CHD (OR = 2.486, 95% CI = 1.619–3.818) and severe CHD (OR = 1.950, 95% CI = 1.269–2.997), while routine daytime nap could decrease risk of simple CHD (OR = 0.634, 95% CI = 0.435–0.923). In the stratified analysis, the concurrence with routine daytime nap could weaken the risk of simple CHD caused by poor sleep (OR = 3.183, 95% CI: 1.830–5.537 decreased to OR = 2.236, 95% CI: 1.200–4.165). The examinations were repeated in ventricular septal defect and tetralogy of Fallot, and the established associations can be verified. Moreover, all these findings were also similarly observed in both propensity-score-adjusted and propensity-score-matched analyses. Conclusions: Poor maternal sleep around periconceptional period seems to be an independent risk factor for CHD. The concurrence with daytime nap could to some extent reduce the risk in simple CHD. The results individually and collectively put forward the importance of maternal sleep in embryonic heart development. © 2019 The Authors. Birth Defects Research published by Wiley Periodicals, Inc.
Keywords: case–control study; congenital heart disease; daytime nap; maternal sleep; pregnancy

Psychosocial functioning of parents of children with heart disease—describing the landscape - Wray, J.; Cassedy, A.; Ernst, M.M.; Franklin, R.C.; Brown, K.; Marino, B.S. (European Journal of Pediatrics, 2018)
The aim was to describe the psychological functioning of parents of school-age children with heart disease (HD) in a large-scale, transnational evaluation of parent dyads across the spectrum of cardiac diagnoses and a range of psychosocial domains. Parents of children with HD attending routine out-patient cardiology follow-up visits completed questionnaires assessing their mental health, coping, and family functioning. Parents (1197 mothers and 1053 fathers) of 1214 children (mean age: 12.6 years; S.D. 3.0 years; median time since last surgery: 8.9 years) with congenital or acquired HD from three centers each in the UK and the USA participated (80% response rate). Parents of children with milder HD demonstrated few differences from healthy norms and had significantly lower scores on measures of illness-related stress and post-traumatic stress than parents of children with single ventricle conditions or cardiomyopathy. Parents in these latter two diagnostic sub-groups had significantly higher levels of anxiety and depression than healthy norms but did not differ on other measures of family functioning and coping skills. There were few differences between parents from the UK and the USA. Agreement between mothers and fathers within a dyad was highest for the measure of frequency of illness-related stressors (ICC = 0.67) and lowest for anxiety (ICC = 0.12). Conclusion: Our results suggest two different pathways for the long-term psychological well-being of parents of children with HD: on the one hand, more complex HD is associated with poorer long-term psychosocial outcomes; in contrast, there are also grounds for optimism, particularly for parents of children with less complex conditions, with better psychological outcomes noted for some groups of parents compared to previously reported early psychosocial outcomes. Future work needs to identify factors other than disease severity which might explain poorer (or better) functioning in some parents of children with more complex HD.What is Known:• Parents of children with congenital heart disease report elevated levels of anxiety, depression, and stress after cardiac surgery in infancy.• Maternal mental health problems can have an adverse impact on the psychological adjustment of the child with congenital heart disease.What is New:• Parents of children with milder forms of heart disease do not differ from healthy norms in the longer term and psychological outcomes are better than might be expected from early findings.• More complex diagnoses, particularly functional single ventricle conditions and cardiomyopathy, are associated with poorer long-term psychosocial outcomes for parents. © 2018, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Heart disease; Parents; Psychological functioning

Perioperative Cerebral Oxygenation Metabolism in Neonates with Hypoplastic Left Heart Syndrome or Transposition of the Great Arteries - Neunhoeffer, F.; Hofbeck, M.; Schlensak, C.; Schuhmann, M.U.; Michel, J. (Pediatric Cardiology, 2018)
Optimizing oxygen delivery to the brain is one of the main goals in children with congenital heart defects after surgery. It has been shown that cerebral oxygen saturation (cSO2) is depressed within the first day after neonatal cardiopulmonary bypass surgery. However, peri-operative cerebral oxygen metabolism has not yet been assessed in previous studies. The aim of this study was to describe the peri-operative changes in cerebral oxygen metabolism in neonates with congenital heart defects following cardiopulmonary bypass surgery. Prospective observational cohort study. PICU of a tertiary referral center. Fourteen neonates with hypoplastic left heart syndrome (HLHS) undergoing Norwood procedure and 14 neonates with transposition of great arteries (TGA) undergoing arterial switch operation (ASO) were enrolled. Pediatric heart surgery. We measured non-invasively regional cSO2 and microperfusion (rcFlow) using tissue spectrometry and laser Doppler flowmetry before and after surgery. Cerebral fractional tissue oxygen extraction (cFTOE), the arterio–cerebral difference in oxygen content (acDO2) and approximated cerebral metabolic rate of oxygen (aCMRO2) were calculated. According to the postsurgical hemodynamics, arterial saturation (aSO2) normalized immediately after surgery in the TGA group, whereas HLHS patients still were cyanotic. cSO2 significantly increased in TGA group over 48 h after ASO (p = 0.004) and was significantly higher compared to HLHS group after Norwood procedure. cFTOE as a risk marker for brain injury was elevated before surgery (TGA group 0.37 ± 0.10, HLHS group 0.42 ± 0.12) and showed a slight decrease after ASO (p = 0.35) but significantly decreased in patients after Norwood procedure (p = 0.02). Preo-peratively, acDO2 was significantly higher in patients with HLHS compared to patients with TGA (7.7 ± 2.5 vs. 5.2 ± 1.6 ml/dl, p = 0.005), but normalized in the posto-perative course. Before surgery, the aCMRO2 was slightly higher in the HLHS group (5.1 ± 1.5 vs. 3.9 ± 2.5 AU, p = 0.14), but significantly decreased after Norwood procedure (− 1.6 AU, p = 0.009). There was no difference in rcFlow between both groups and between the points in time prior and after surgery. Neonates undergoing cardiac surgery suffer from peri-operative changes in hemodynamics and cerebral hypoxemic stress. The cerebral oxygen metabolism seems to be more affected in cyanotic children with functionally univentricular hearts compared to post-operative acyanotic patients. Additional stress factors must be avoided to achieve the best possible neurological outcome. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Arterial switch operation; Cerebral autoregulation; Congenital heart defect; Norwood

Ventricular mechanics in adolescent and adult patients with a Fontan circulation: Relation to geometry and wall stress - Rösner, A.; Khalapyan, T.; Pedrosa, J.; Dalen, H.; McElhinney, D.B.; Friedberg, M.K.; Lui, G.K. (Echocardiography, 2018)
Background: Patients with single ventricle physiology and Fontan circulation are at increased risk for late complications and reduced survival. The aim of the study was to investigate the correlation between ventricular geometry and systolic regional function in different underlying anatomic conditions in adolescent and adult Fontan-palliated patients. Method: In a retrospective cross-sectional study, we measured 2D strain, ventricular diameters, ventricular volumes, ejection fraction (EF), global and segmental wall stress, and sphericity index. The same analyses were performed in 99 age- and gender-matched healthy individuals. Results: One hundred and one patients were included at a mean age of 21 (range 14–59) years. In comparison with healthy subjects, patients with Fontan circulation displayed larger ventricular volumes (153 ± 78 mL vs 116 ± 38 mL P < 0.05), reduced EF (43% ± 15% vs 55% ± 8% P < 0.05), reduced longitudinal (−13% ± 6% vs −21% ± 4% P < 0.05) and circumferential strain values (−15% ± 7% vs −22% ± 4% P < 0.05). Functionally single ventricles were more spherical (ratio of longitudinal to short-axis diameters 1.3 ± 0.3 vs 1.7 ± 0.2 P < 0.05). Circumferential strain correlated well with global wall stress and the degree of sphericity (R 2  = 0.320), while segmental strain did not correlate with segmental wall stress. The percentage of segments with akinesia was relatively high (16 ± 16% vs 0 ± 0% P < 0.05) indicating reduced segmental contractile function. Conclusion: Functionally single ventricles after Fontan palliation have significantly reduced systolic regional and global function with a high intersegmental inhomogeneity. The underlying pathological mechanisms might be multifactorial, including ventricular geometry, sphericity, and regional contractile properties. Future studies are needed to investigate the role of ventricular geometry for clinical performance and outcome. © 2018 Wiley Periodicals, Inc.
Keywords: Fontan circulation; strain rate echocardiography; ventricular function; ventricular geometry

Safety of outpatient cardiac catheterisation in infants with single-ventricle or shunt-dependent biventricular congenital heart disease - Colombo, J.N.; Spaeder, M.C.; Hainstock, M.R. (Cardiology in the Young, 2018)
Objective: We aimed to investigate the incidence and causes of readmission of infants with single-ventricle and shunt-dependent biventricular CHD following routine, outpatient cardiac catheterisation.Background Cardiac catheterisation is commonly performed in patients with single-ventricle and shunt-dependent biventricular CHD for haemodynamic assessment and surgical planning. Best practices for post-procedural care in this population are unknown, and substantial variation exists between centres. Outpatient catheterisation reduces parental anxiety and decreases cost. Our institutional strategy is to discharge patients following a 4- to 6-hour post-procedure observation period. Methods: Retrospective cohort study using the Society of Thoracic Surgeons Database identified patients <1 year of age with pre-stage II single-ventricle CHD or shunt-dependent biventricular CHD who underwent cardiac catheterisation between 2007 and 2015. Readmission was defined as admission to the hospital within 48 hours after discharge after catheterisation. Results: A total of 92 patients were included in the analysis. Among them, 62 patients (67%) were discharged after a 4- to 6-hour observation period with only 3% readmission, 18 patients (20%) stayed for a 23-hour observation period, and 12 patients (13%) were admitted for >23 hours. There were no differences in baseline characteristics between discharged and admitted patients. Patients who underwent intervention were more likely to be admitted. Patients with hypoplastic left heart syndrome did not have major adverse events or readmissions. No intra- or peri-procedural deaths occurred. Conclusions: Outpatient cardiac catheterisation may be a safe option for infants with single-ventricle and shunt-dependent biventricular CHD, with low readmission rates and minimal morbidity. © 2018 Cambridge University Press.
Keywords: cardiac catheterisation; CHD; hypoplastic left heart syndrome; single ventricle

Single-centre experience in stenting arterial shunts for adult CHD patients with single-ventricle physiology and pulmonary blood flow dependent on arterial shunts - Kasem, M.; Bentham, J.; Thomson, J. (Cardiology in the Young, 2018)
Objectives The objectives of this study were to describe the approach to stenting arterial shunts in adult congenital patients with single-ventricle physiology and to assess the medium-term clinical and haemodynamic outcomes following stent insertion. Background Adult patients with single-ventricle physiology and pulmonary blood flow dependent on a surgically placed arterial shunt who did not progress to venous palliation are extremely challenging to manage. Progressive cyanosis secondary to narrowing of the shunt has a marked impact on exercise tolerance and results in intolerable well-being for these patients. Stenting arterial shunts in adult patients is one method that can help improve pulmonary blood flow. There is very limited information in the literature about this patient. Methods: This is a retrospective study for arterial shunts stenting conducted between 2008 and 2016. The peripheral oxygen saturations, the NYHA status, the haemoglobin, and the degree of atrio-ventricular valve regurgitation as assessed on transthoracic echo were compared before and 6-12 months after procedures. Results: There was a short-term improvement in oxygen saturations; the pre-procedure mean was 75.8 (SD 2.55)% (range 70-85%) and post-procedure mean was 83 (SD 2.52)% (range 78-87%), with a p value of 0.04. Haemoglobin level decreased from a pre-procedure mean of 22.06-20.28 g/L 6 months post procedure (range 18.1-24.4 to 13-23.3 g/L), with a p value of 0.44. NYHA class decreased from a mean of 3.2-2.2 post procedure. Left atrial volume for four of the cases did not change (22.6-76.6 ml [mean 48.4 ml] to 29.6-72.9 ml [mean 52 ml], p value: 0.83). Conclusions: Stenting stenotic arterial shunts is a useful method to gain a medium-term improvement on the oxygen saturation and clinical symptoms, and may act as a useful intermediate step for further management plans. © 2018 Cambridge University Press.
Keywords: Arterial shunt; Blalock-Taussig shunt; central shunt; stenting

Parents' experiences of receiving an antenatal versus postnatal diagnosis of complex congenital heart disease - Reid, A.; Gaskin, K. (Nursing children and young people, 2018)
BACKGROUND: The time point at which parents receive a diagnosis of congenital heart disease (CHD) has changed over the years due in part to advances in fetal ultrasound. However, CHD remains undiscovered until after birth in some cases. The psychological effect of time of diagnosis on parents' experiences has not been well researched. AIM: To explore parents' experiences at the time of diagnosis of complex CHD and to compare if experiences differ when receiving an antenatal versus postnatal diagnosis. METHOD: Descriptive and thematic analysis of primary mixed qualitative and quantitative data, collected in 2012-2013, from an online survey of parents ( n =22) whose infants had undergone stage one surgery for a functionally univentricular heart. FINDINGS: Four themes emerged: parents' understanding of the condition at the time of diagnosis; parents' emotions at the time of diagnosis; sources of support at the time of diagnosis; and additional sources of information after the diagnosis. CONCLUSION: There are implications for practice in terms of who provides the diagnosis and, more importantly, how well it is explained. Professionals need to assess parents' emotional status, information needs and level of understanding irrespective of time of diagnosis, so that support is individualised, sensitive and time appropriate. ©2018 RCN Publishing Company Ltd. All rights reserved. Not to be copied, transmitted or recorded in any way, in whole or part, without prior permission of the publishers.
Keywords: child health; congenital abnormalities; heart diseases; research

Executive Function and Psychosocial Quality of Life in School Age Children with Congenital Heart Disease - Sanz, J.H.; Wang, J.; Berl, M.M.; Armour, A.C.; Cheng, Y.I.; Donofrio, M.T. (Journal of Pediatrics, 2018)
Objective: To test a model to predict psychosocial quality of life (QOL) in children with congenital heart disease (CHD) via executive dysfunction. Study design: Parents of 91 children with CHD requiring surgery in the first year of life completed questionnaires by mail or as part of their cardiology clinic visit. Latent class analysis identified 2 groups of patients with different likelihoods of executive dysfunction. Select medical and demographic characteristics and executive dysfunction group membership were evaluated as predictors of QOL using structural equation modeling. Results: In children with CHD, aortic obstruction, male sex, and premature birth predicted worse executive function, explaining 59% of the variance. Structural equation modeling results indicated that executive dysfunction plays an important mediating role, through which CHD with aortic obstruction, male sex, and premature birth indirectly affect psychosocial QOL. Neurologic abnormalities and single-ventricle CHD did not significantly predict executive dysfunction or QOL. Conclusions: Executive dysfunction is a strong predictor of psychosocial QOL at school age. Select medical and demographic risk factors did not directly predict QOL at school age in CHD; however, aortic obstruction, premature birth, and male sex impacted QOL indirectly by contributing to executive dysfunction. These findings suggest important risk factors for executive dysfunction that can be monitored, allowing for provision of early supports for executive skills development in an effort to improve long term psychosocial QOL in at-risk children with CHD. © 2018 Elsevier Inc.
Keywords: congenital heart defects; executive function; neurodevelopmental outcome; quality of life

Home- and hospital-based exercise training programme after Fontan surgery - Sutherland, N.; Jones, B.; Westcamp Aguero, S.; Melchiori, T.; Du Plessis, K.; Konstantinov, I.E.; Cheung, M.M.H.; D'Udekem, Y. (Cardiology in the Young, 2018)
Background Exercise training has been shown to increase exercise capacity in survivors of Fontan surgery. The geographic distribution of the Fontan population has been a barrier to hospital-based exercise training programmes. The objective of this study was to establish whether a home exercise training programme could achieve similar improvements to a hospital programme.Methods Adolescents with a Fontan circulation aged 12-19 years were prospectively recruited in a hospital or home exercise training programme. Patients underwent cardiopulmonary exercise testing and completed the Paediatric Quality of Life Inventory at initial assessment and after completion of an 8-week programme. Both groups performed two 1-hour training sessions per week. Patients in the home training programme had their first session in the hospital, and then progressed independently with one phone consult per week and one home visit by a physiotherapist.Results In total, 17 patients, with a mean age of 15±3 years, completed the training programme (six hospital). Characteristics and baseline performance of patients were similar in both groups. Oxygen consumption at anaerobic threshold increased from 19.3±3.8 to 21.6±6.0 ml/kg/minute (p=0.02) and peak oxygen pulse increased from 8.8±2.5 to 9.5±2.7 ml/beat (p=0.049). Total quality of life scale improved from 68 to 74% (p=0.01) and psychosocial health improved from 67 to 74% (p=0.02). No patient experienced training-related complications.Conclusions Exercise training is beneficial and most likely safe after Fontan, resulting in improved exercise capacity and self-reported quality of life. Home exercise training programmes are probably as effective as hospital programmes. Home exercise training programmes should be integrated in the follow-up care of patients undergoing Fontan surgery. © Cambridge University Press 2018.
Keywords: CHD; exercise therapy; Fontan procedure; rehabilitation; resistance training

Grief and coping of parents whose child has a constant life-threatening disability, hypoplastic left heart syndrome with reference to the Dual-Process Model - Cantwell-Bartl, A. (Death Studies, 2018)
This paper reports on a study that examined the grief and coping of 29 parents whose child has hypoplastic left heart syndrome using the Dual Process Model. The study employed a secondary thematic analysis of interviews at key times of treatment and recovery for the child. After the diagnosis, parents experienced intense loss (LO), but focused upon restoration-orientated tasks (RO) to support their child. Over time, most parents employed a healthy oscillation between LO coping and RO coping, with waves of grief and with some grieving suppressed. There are some specific grief and coping and gender patterns employed by parents. © 2018 Taylor & Francis.

Altered White Matter Microstructure Correlates with IQ and Processing Speed in Children and Adolescents Post-Fontan - Watson, C.G.; Stopp, C.; Wypij, D.; Bellinger, D.C.; Newburger, J.W.; Rivkin, M.J. (Journal of Pediatrics, 2018)
Objective: To compare white matter microstructure in children and adolescents with single ventricle who underwent the Fontan procedure with healthy controls, and to explore the association of white matter injury with cognitive performance as well as patient and medical factors. Study design: Fontan (n = 102) and control subjects (n = 47) underwent diffusion tensor imaging (DTI) at ages 10-19 years. Mean DTI measures (fractional anisotropy, radial diffusivity, axial diffusivity, and mean diffusivity) were calculated for 33 fiber tracts from standard white matter atlases. Voxel-wise group differences in DTI measures were assessed using Tract-Based Spatial Statistics. Associations of regional fractional anisotropy with IQ and processing speed as well as medical characteristics were examined. Results: Subjects with Fontan, compared with controls, had reduced bilateral regional and voxel-wise fractional anisotropy in multiple white matter tracts along with increased regional radial diffusivity in several overlapping tracts; regional mean diffusivity differed in 2 tracts. The groups did not differ in voxel-wise radial diffusivity or mean diffusivity. Among subjects with Fontan, fractional anisotropy in many tracts correlated positively with Full-Scale Intelligence Quotient and processing speed, although similar findings were absent in controls. Lower mean fractional anisotropy in various tracts was associated with more complications in the first operation, a greater number of total operations, and history of neurologic event. Conclusions: Children and adolescents who have undergone the Fontan procedure have widespread abnormalities in white matter microstructure. Furthermore, white matter microstructure in several tracts is associated with cognitive performance and operative and medical history characteristics. © 2018
Keywords: brain; cognition; congenital heart disease; DTI; Fontan; MRI; single ventricle

Can a home-based cardiac physical activity program improve and sustain quality of life and exercise capacity in children with Fontan circulation? - Jacobsen, R.; Danduran, M.; Mussatto, K.; Hill, G.D.; Ginde, S. (Progress in Pediatric Cardiology, 2018)
Objective: Fontan survivors report reduced health-related quality of life (HRQOL) and have decreased exercise tolerance compared to healthy peers. We recently demonstrated that a 12-week home-based physical activity program was safe, feasible, and improved parent proxy-reported HRQOL and objective measures of exercise capacity in patients with Fontan circulation. We sought to determine if these improvements in HRQOL and exercise capacity are sustained at 6-month follow-up. Design: Patients, 8–12 years old, with Fontan circulation that completed a 12-week moderate-to-vigorous intensity home-based physical activity program were invited to attend a 6-month follow-up session to complete objective assessments of HRQOL and exercise capacity. HRQOL was measured with validated questionnaires. The 20-meter Shuttle Run (PACER Test) was used to measure exercise capacity. Results: Of the 13 patients who completed the original 12-week physical activity program, 11 (85%) attended the 6-month follow-up. There were no adverse events during the follow-up period. Improvements in parent proxy-report for HRQOL at completion of the 12-week program were sustained at 6-month follow-up. Patients reported a significant decrease in HRQOL assessed by PedsQL at 6-month follow-up. However, there was a non-significant trend of improvement in patient PCQLI total and psychosocial impact scores at completion of the 12-week program, which was sustained at 6-month follow-up. The significant improvements in objective measures of exercise capacity seen from baseline to completion of the 12-week program were sustained at 6-month follow-up. Conclusion: Improvements in parent-proxy report HRQOL and objective measures of exercise capacity after completion of a home-based 12-week physical activity program were sustained at 6-month follow-up. Despite improvements in exercise capacity, patients did not report improved HRQOL. A larger, controlled study of this home-based physical activity program is needed to assess the impact of physical activity and improved exercise capacity on HRQOL in children with Fontan circulation. © 2018 Elsevier B.V.
Keywords: Congenital Heart Disease, CHD; Exercise; Fontan; Physical activity; Quality of life; Rehabilitation

A survey of health professionals’ views on acceptable gestational age and termination of pregnancy for fetal anomaly - Crowe, L.; Graham, R.H.; Robson, S.C.; Rankin, J. (European Journal of Medical Genetics, 2018)
Termination of pregnancy for fetal anomaly is legal in the UK with no upper limit, if two doctors, in good faith, agree “there is a substantial risk that if the child were born it would suffer from such physical or mental abnormalities as to be seriously handicapped”. This is Clause E of the Human Fertlisation and Embryology Act. The most commonly sighted Clause is C, which states “the pregnancy has not exceeded its twenty-fourth week and that the continuance of the pregnancy would involve risk, greater than if the pregnancy were terminated, of injury to the physical or mental health of the pregnant woman”. This study aimed to investigate health professionals’ views on gestational age and acceptable termination of pregnancy for fetal anomaly (TOPFA). We undertook a questionnaire survey of UK health professionals working in fetal medicine, obstetrics and gynaecology and neonatology. A study pack consisting of a self-completion questionnaire, an invitation letter, participant information sheet, and a stamped addressed return envelope, were sent to health professionals. We used four fetal anomalies as case study examples in the questionnaire: isolated cleft lip, hypoplastic left heart, spina bifida and trisomy 21. These anomalies were chosen as they differed in terms of the type of anomaly, the type of impairment, and the perceived severity. Forty-one study packs were returned. For anomalies deemed less serious, later gestational ages were an important consideration when deciding acceptable TOPFA. The prognosis of an anomaly was considered an important factor in deciding whether a TOPFA was acceptable alongside gestational age. Clause C of the current UK legislation, which allows a legal termination prior to 24 weeks gestational age if continuing with the pregnancy would impact the mental health of the mother, was deemed a reasonable option for termination when parents are requesting a TOPFA. For each case study example, health professionals responded that TOPFA at ‘25 weeks and over’ was acceptable (cleft lip n = 1; hypoplastic left heart n = 19; spina bifida n = 13 and Trisomy 21 n = 10). Professionals also distinguished between their personal and professional views. These findings offer new insight into how gestational age considerations influence professionals’ conceptualisation of acceptable TOPFA. © 2018 Elsevier Masson SAS
Keywords: Gestational age; Health professionals; Termination of pregnancy; Termination of pregnancy for fetal anomaly

Cerebral autoregulation in neonates with and without congenital heart disease - Tran, N.N.; Ram Kumar, S.; Hodge, F.S.; Macey, P.M. (American Journal of Critical Care, 2018)
Background Congenital heart disease (CHD) is a leading birth defect in the United States, affecting about 40 000 neonates each year. Despite efforts to prevent developmental delays, many children with CHD have neurological deficits that last into adulthood, influencing employability, self-care, and quality of life. Objective To determine if neonates with CHD have impaired cerebral autoregulation and poorer neurodevelopmental outcomes compared with healthy controls. Methods A total of 44 full-term neonates, 28 with CHD and 16 without, were enrolled in the study. Inclusion criteria included confirmed diagnosis of CHD, stable hemodynamic status, and being no more than 12 days old. Exclusion criteria included intraventricular hemorrhage and intubation. Cerebral autoregulation was determined by measuring regional cerebral oxygenation during a postural change. The Einstein Neonatal Neurobehavioral Assessment Scale was used to measure overall neurodevelopmental outcomes (motor, visual, and auditory functions). Results Of the 28 neonates with CHD, 8 had single-ventricle physiology. A χ2 analysis indicated no significant difference in impaired cerebral autoregulation between neonates with CHD and controls (P = .38). Neonates with CHD had lower regional cerebral oxygenation than did neonates without CHD (P < .001). Regression analyses with adjustments for cerebral autoregulation indicated that neonates with CHD had poorer total neurodevelopmental outcomes scores (β = 9.3; P = .02) and motor scores (β = 7.6; P = .04). Conclusion Preoperative neonates with CHD have poorer developmental outcomes and more hypoxemia than do controls. © 2018 American Association of Critical-Care Nurses.

Pulmonary Screening in Subjects after the Fontan Procedure - Liptzin, D.R.; Di Maria, M.V.; Younoszai, A.; Narkewicz, M.R.; Kelly, S.L.; Wolfe, K.R.; Veress, L.A. (Journal of Pediatrics, 2018)
Objectives: To review the pulmonary findings of the first 51 patients who presented to our interdisciplinary single-ventricle clinic after undergoing the Fontan procedure. Study design: We performed an Institutional Review Board–approved retrospective review of 51 patients evaluated following the Fontan procedure. Evaluation included history, physical examination, pulmonary function testing, and 6-minute walk. Descriptive statistics were used to describe the population and testing data. Results: Sixty-one percent of the patients had a pulmonary concern raised during the visit. Three patients had plastic bronchitis. Abnormal lung function testing was present in 46% of patients. Two-thirds (66%) of the patients had significant desaturation during the 6-minute walk test. Patients who underwent a fenestrated Fontan procedure and those who underwent unfenestrated Fontan were compared in terms of saturation and 6-minute walk test results. Sleep concerns were present in 45% of the patients. Conclusions: Pulmonary morbidities are common in patients after Fontan surgery and include plastic bronchitis, abnormal lung function, desaturations with walking, and sleep concerns. Abnormal lung function and obstructive sleep apnea may stress the Fontan circuit and may have implications for cognitive and emotional functioning. A pulmonologist involved in the care of patients after Fontan surgery can assist in screening for comorbidities and recommend interventions. © 2018 Elsevier Inc.
Keywords: altitude; congenital; executive function; heart defects; hypoplastic left heart syndrome; neuropsychology; sleep apnea syndromes; sternotomy

Heart and heart–liver transplantation in adults with failing Fontan physiology - Reardon, L.C.; DePasquale, E.C.; Tarabay, J.; Cruz, D.; Laks, H.; Biniwale, R.M.; Busuttil, R.W.; Kaldas, F.M.; Saab, S.; Venick, R.S.; Lin, J.P.; Nsair, A.; et al. (Clinical Transplantation, 2018)
Background: As the population of patients with a Fontan palliation grows so does, the number of patients with cardiac failure necessitating orthotopic heart transplant (OHT) and combined heart–liver transplant (CHLT). There is recent evidence that current era cardiac transplant in Fontan patients has improved outcomes, but most studies have a preponderance of pediatrics patients in their cohorts. We examine our institutional experience with adult OHT and CHLT transplantation for failed Fontan physiology. Methods and Results: Retrospective analysis of patients at the Ahmanson/UCLA Adult Congenital Heart Disease Center who underwent OHT or CHLT for failing Fontan physiology from January 1, 2002 to May 31, 2017. We identified 20 patients with single-ventricle physiology and Fontan palliation who underwent OHT or CHLT. The median age was 29.5 years (range 19-44). Five patients underwent CHLT because of biopsy proven hepatic cirrhosis. The median length of hospital stay was 23 days (range 8-76) post-OHT and 51 days (range 26-77) post-CHLT. During a median follow-up of 56 months (range 2-178), there was one mortality occurring at 34 months post-OHT due to coronary vasculopathy. Most frequent early postoperative complications included bleeding and infection (55% and 20%, respectively) and surgical reintervention for bleeding complications (n = 8, 40%). One CHLT patient experienced clinically significant hepatic rejection requiring admission and steroid treatment. Conclusions: Despite inherent risks and complexities of OHT or CHLT in patients with a failed Fontan, transplant is a reasonable therapy. Peri- and postoperative complications are common and may require surgical reintervention. Continued observation of practices and unifying themes may help improve patient selection, pre- and postoperative treatment and ultimately outcomes. © 2018 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd
Keywords: fontan procedure; liver; outcomes research; transplantation

Perception scores of siblings and parents of children with hypoplastic left heart syndrome - Caris, E.C.; Dempster, N.; Wernovsky, G.; Miao, Y.; Moore-Clingenpeel, M.; Neely, T.; Fonseca, R.; Miller-Tate, H.; Allen, R.; Fichtner, S.; Stewart, J.; Cua, C.L. (Congenital Heart Disease, 2018)
Objectives: Siblings of children with chronic medical conditions endorse a lower quality of life compared to age-matched peers. Caregiver and sibling-self report of adjustment are often discordant. Congenital heart disease significantly affects family life. To date, there have been no studies addressing the functioning of siblings of children with hypoplastic left heart syndrome, one of the most severe forms of congenital heart disease. The goal of this study was to assess the impact of hypoplastic left heart syndrome on sibling's quality of life as well as the caregiver's perception of this effect. Study Design: Cross-sectional study using a web-based survey distributed via various listservs targeted towards families of children with hypoplastic left heart syndrome. Employed the Sibling Perception Questionnaire, designed to assess sibling and caregiver perceptions of adjustment to chronic illness. A Negative Adjustment Composite Score was calculated for each respondent, with higher values representing more negative adjustment. Results: Thirty-five caregivers responded. Majority of caregivers were female (74%), white (86%) and college educated (54%). Thirty-two siblings participated, ranging in age from 7 to 30 years of age (12.5 ± 6.3). Most children with hypoplastic left heart syndrome (73%) had undergone the third stage of palliation. Forty-two caregiver-sibling pairs were examined. Caregiver Negative Adjustment Composite Scores were significantly higher than sibling scores, with caregivers reporting more adjustment problems (2.4 ± 0.4) than siblings (2.3 ± 0.3, P <.05). Sibling age was correlated with worse caregiver and sibling scores (r 0.35, P <.05). Conclusions: Caregivers of children with hypoplastic left heart syndrome perceive their siblings as struggling more than the children self-report. Siblings tend to report worse adjustment as they get older. These data suggest that programs should include support for the entire family through all ages to optimize quality of life. © 2018 Wiley Periodicals, Inc.
Keywords: congenital heart disease; hypoplastic left heart syndrome; siblings; survey

Chest computed tomography angiography in children on extracorporeal membrane oxygenation (ECMO) - Hull, N.C.; Schooler, G.R.; Binkovitz, L.A.; Williamson, E.E.; Araoz, P.A.; Yu, L.; Young, P.M. (Pediatric Radiology, 2018)
Performing chest CT angiography on pediatric patients on extracorporeal membrane oxygenation (ECMO) can be challenging. Successfully performing CT angiography in these children requires substantial communication and coordination between the radiologists and clinical care providers. Additionally, the radiologist must understand the child’s anatomy and disease pathophysiology, flow dynamics of the ECMO circuit, image acquisition timing, contrast injection site, and volume, rate and duration of contrast administration. In this article we highlight the vital factors the radiologist needs to consider to optimize the chest CT angiography in pediatric patients on ECMO. © 2017, Springer-Verlag GmbH Germany, part of Springer Nature.
Keywords: Chest; Children; Computed tomography; Computed tomography angiography; Extracorporeal membrane oxygenation (ECMO)

Transition experiences between hospital- and home-care for parents of children with hypoplastic left heart syndrome - March, S.; Keim-Malpass, J. (Journal for Specialists in Pediatric Nursing, 2018)
Purpose: Children with hypoplastic left heart syndrome (HLHS) experience numerous vulnerabilities during transitions from hospital to home during their first year of life. This paper examines the parents’ responses to the situations they experience during the initial interstage transition as described through illness blogs. Design and methods: A qualitative descriptive design through inductive theme development using thematic analysis was performed for this study. Text data were used from publically available blogs written by parents of HLHS children on their feelings and experiences during transitions between hospital- and home-care during the interstage period. Results: Six blogs were analyzed. Overall, the lack of difference in normalcy for these parents and their families was apparent. Major themes included: thoughts and feelings when discharged from the hospital, difficulties with hospital readmissions, protecting their child from infection, and developing a support system. Conclusions: Parents looked forward to going home and learned all they could about properly caring for their child before going home. They were disappointed and frustrated when returning to the hospital for either emergency or scheduled admissions and were not prepared to see their child in the intensive care unit environment again. Many parents isolated themselves and avoided the hospital as much as possible to avoid their child developing an infection. All parents had support systems through family and/or friends and found an unexpected sense of support through their blog families. © 2018 Wiley Periodicals, Inc.
Keywords: blog analysis; congenital heart defect; hypoplastic left heart syndrome; interstage; transitions in care

Impact of Ventricular Morphology on Fiber Stress and Strain in Fontan Patients - Ghelani, S.J.; Colan, S.D.; Azcue, N.; Keenan, E.M.; Harrild, D.M.; Powell, A.J.; Geva, T.; Rathod, R.H. (Circulation. Cardiovascular imaging, 2018)
BACKGROUND: Right ventricular (RV) morphology has been associated with adverse clinical outcomes in Fontan patients. The impact of RV versus left ventricular morphology on ventricular stress and strain in single ventricles is not well known. METHODS AND RESULTS: Cardiac magnetic resonance examinations in 193 patients with the Fontan circulation were retrospectively analyzed. Ventricular mass, volume, global circumferential and longitudinal strain, and global average end-systolic fiber stress were calculated using previously published methods. Compared with left ventricular morphology, RV morphology (48%) was associated with higher ventricular end-diastolic volume (110 mL/BSA1.3 versus 84 mL/BSA1.3, P<0.001), lower mass-to-volume ratio (0.46 versus 0.57, P<0.001), higher global average end-systolic fiber stress (23 kPa versus 20 kPa, P=0.002), worse global circumferential strain (-21% versus -24%, P<0.001), and higher prevalence of greater than or equal to moderate atrioventricular valve regurgitation (25% versus 6%, P<0.001). Ejection fraction and global longitudinal strain were similar between the groups. Death or listing for heart transplantation occurred in 24 (12%) with a median follow-up of 6.2 years. On univariate analysis, RV morphology, ventricular dilatation, and worse global circumferential strain were associated with this composite outcome. CONCLUSIONS: In comparison to Fontan patients with a dominant left ventricle, those with a dominant RV have higher fiber stress, a higher rate of ventricular dilatation, lower circumferential fiber shortening, and similar longitudinal shortening. RV morphology, ventricular dilation, and worse circumferential strain are associated with death or heart transplantation. The difference in myofiber architecture may contribute to suboptimal adaptation of the RV as a systemic ventricle. © 2018 American Heart Association, Inc.
Keywords: blood pressure; dilatation; heart transplantation; prevalence

A Novel Mechanism for Improved Exercise Performance in Pediatric Fontan Patients After Cardiac Rehabilitation - Wittekind, S.; Mays, W.; Gerdes, Y.; Knecht, S.; Hambrook, J.; Border, W.; Jefferies, J.L. (Pediatric Cardiology, 2018)
Patients with a Fontan circulation have impaired exercise capacity. Cardiac rehabilitation (CR) has shown promise in enhancing peak exercise parameters in this population, but an improvement in submaximal exercise has not been consistently demonstrated. We assessed the hypothesis that participation in CR will be associated with more efficient oxygen extraction and ventilation during submaximal exercise. In this prospective study, pediatric Fontans completed two 60 min CR sessions per week for 12 weeks. Cardiopulmonary exercise testing and stress echocardiography were performed at baseline and last CR session, and then compared with a paired sample t test. Ten pediatric Fontans completed the study. Five had tricuspid atresia and five had hypoplastic left heart syndrome. No serious adverse events occurred during CR sessions. Peak indexed oxygen consumption increased by a mean of 3.7 mL/kg/min (95% CI 1.5–5.9; p = 0.004), and peak oxygen pulse increased by a mean of 0.9 mL/beat (95% CI 0.4–1.4; p = 0.004). The peak respiratory exchange ratio did not change significantly. The significant difference in oxygen pulse became evident during submaximal exercise without a corresponding difference in echocardiographic stroke volume. Indexed oxygen consumption at ventilatory anaerobic threshold increased by a mean of 3.0 mL/kg/min (95% CI − 0.07 to 6.0; p = 0.055). The slope for the volume of expired ventilation to volume of carbon dioxide production improved by a mean of 4.5 (95% CI − 8.4 to − 0.6; p = 0.03). We observed significant improvements in both submaximal and peak exercise performance in pediatric Fontans undergoing CR with no serious adverse events. These changes appeared to be mediated, at least in part, by more efficient oxygen extraction and ventilation. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Cardiac rehabilitation; Congenital heart disease; Exercise testing; Exercise therapy; Fontan circulation

“How long will I continue to be normal?” Adults with a Fontan circulation's greatest concerns - du Plessis, K.; Peters, R.; King, I.; Robertson, K.; Mackley, J.; Maree, R.; Stanley, T.; Pickford, L.; Rose, B.; Orchard, M.; Stewart, H.; d'Udekem, Y. (International Journal of Cardiology, 2018)
Background: Little is known about adults living with a Fontan circulation's concerns outside the scope of their clinical outcomes. We examined adults with a Fontan circulations' greatest concerns, as well as their concerns around anti-coagulation, pregnancy and finances. Methods: Adults with a Fontan circulation in the Australian and New Zealand Fontan Registry were invited to complete an anonymous online survey, of which 57 participated. A qualitative method approach using thematic analyses was used. Results: The greatest concerns for adults living with a Fontan circulation were fear of death/uncertainty around life expectancy which for many individuals colored their concerns around physical health, pregnancy and having children, quality of life and finances. Improving information about outcomes to patients with a Fontan circulation might alleviate uncertainties about their future. Conclusions: Fear of death is the primary concern of adults with a Fontan circulation. It may require improved communication and targeted psychological interventions. Physical exercise incorporated as part of their lifestyle should be encouraged to alleviate physical concerns and also improve psychological well-being. © 2018 Elsevier B.V.
Keywords: Adult congenital; Congenital heart disease; Fontan; Qualitative research

Tissue-engineered Vascular Grafts in Children With Congenital Heart Disease: Intermediate Term Follow-up - Sugiura, T.; Matsumura, G.; Miyamoto, S.; Miyachi, H.; Breuer, C.K.; Shinoka, T. (Seminars in Thoracic and Cardiovascular Surgery, 2018)
Tissue engineering holds great promise for the advancement of cardiovascular surgery as well as other medical fields. Tissue-engineered vascular grafts have the ability to grow and remodel and could therefore make great advances for pediatric cardiovascular surgery. In 2001, we began a human clinical trial evaluating these grafts in patients with a univentricular physiology. Herein, we report the long-term results of patients who underwent implantation of tissue-engineered vascular grafts as extracardiac total cavopulmonary conduits. Tissue-engineered vascular grafts seeded with autologous bone marrow mononuclear cells were implanted in 25 patients with univentricular physiology. The graft is composed of a woven fabric of poly-l-lactide acid or polyglycolic acid and a 50:50 poly (l-lactic-co-ε-caprolactone) copolymer. Patients were followed up with postoperatively in a multidisciplinary clinic. Median patient age at operation was 5.5 years and the mean follow-up period was 11.1 years. There was no graft-related mortality during the follow-up period. There was also no evidence of aneurysmal formation, graft rupture, graft infection, or calcification. Seven (28%) patients had asymptomatic graft stenosis and underwent successful balloon angioplasty. Stenosis is the primary complication of the tissue-engineered vascular graft. Avoidance of anticoagulation therapy would improve patients’ quality of life. Tissue-engineered vascular grafts have feasibility in pediatric cardiovascular surgery. © 2018 Elsevier Inc.
Keywords: congenital heart disease; Fontan surgery; pediatric cardiac surgery; tissue-engineering; univentricular physiology

Computational Investigation of a Self-Powered Fontan Circulation - Ni, M.W.; Prather, R.O.; Rodriguez, G.; Quinn, R.; Divo, E.; Fogel, M.; Kassab, A.J.; DeCampli, W.M. (Cardiovascular Engineering and Technology, 2018)
Children born with anatomic or functional “single ventricle” must progress through two or more major operations to sustain life. This management sequence culminates in the total cavopulmonary connection, or “Fontan” operation. A consequence of the “Fontan circulation”, however, is elevated central venous pressure and inadequate ventricular preload, which contribute to continued morbidity. We propose a solution to these problems by increasing pulmonary blood flow using an “injection jet” (IJS) in which the source of blood flow and energy is the ventricle itself. The IJS has the unique property of lowering venous pressure while enhancing pulmonary blood flow and ventricular preload. We report preliminary results of an analysis of this circulation using a tightly-coupled, multi-scale computational fluid dynamics model. Our calculations show that, constraining the excess volume load to the ventricle at 50% (pulmonary to systemic flow ratio of 1.5), an optimally configured IJS can lower venous pressure by 3 mmHg while increasing systemic oxygen delivery. Even this small decrease in venous pressure may have substantial clinical impact on the Fontan patient. These findings support the potential for a straightforward surgical modification to decrease venous pressure, and perhaps improve clinical outcome in selected patients. © 2018, Biomedical Engineering Society.
Keywords: Fontan palliation; Hypoplastic left heart syndrome; Injection jet; Multi-scale; Pulmonary vascular resistance; Total cavopulmonary connection

Brain abnormalities in cognition, anxiety, and depression regulatory regions in adolescents with single ventricle heart disease - Pike, N.A.; Roy, B.; Gupta, R.; Singh, S.; Woo, M.A.; Halnon, N.J.; Lewis, A.B.; Kumar, R. (Journal of Neuroscience Research, 2018)
Background: Single ventricle heart disease (SVHD) adolescents show cognitive impairments and anxiety and depressive symptoms, indicating the possibility of brain injury in regions that control these functions. However, brain tissue integrity in cognition, anxiety, and depression regulatory sites in SVHD remains unclear. We examined brain tissue changes in SVHD compared to controls using T2-relaxometry procedures, which measure free water content and show tissue injury. Methods: Proton-density and T2-weighted images, using a 3.0-Tesla MRI, as well as anxiety (Beck anxiety inventory [BAI]), depressive symptoms (patient health questionnaire-9 [PHQ-9]), and cognition (wide range assessment of memory and learning 2 [WRAML2] and Montreal cognitive assessment [MoCA]) data were collected from 20 SVHD (age: 15.8 ± 1.1 years, male/female: 11/9) and 36 controls (age: 16.0 ± 1.1 years, male/female: 19/17). Whole-brain T2-relaxation maps were calculated, normalized to a common space, smoothed, and compared between groups and sexes (analysis of covariance; covariates: age, sex; p < 0.001). Results: SVHD subjects showed significantly increased BAI and PHQ-9 and reduced MoCA and WRAML2 scores over controls. Several brain regions in SVHD showed increased T2-relaxation values (chronic injury), including the cingulate, and insula, hippocampus/para-hippocampal gyrus, thalamus, hypothalamus, amygdala, frontal white matter, corpus callosum, brainstem, and cerebellar areas. Decreased T2-relaxation values (acute injury) emerged in a few regions, including the prefrontal and cerebellar cortices in SVHD over controls. In addition, male SVHD showed more brain changes over female SVHD. Conclusions: Adolescents with SVHD showed significant brain injury with variable male–female differences in areas that control cognition, anxiety, and depression, which may contribute to functional deficits found in the condition. © 2018 Wiley Periodicals, Inc.
Keywords: cingulate; congenital heart disease; hippocampus; insula; magnetic resonance imaging; T2-relaxometry

Useful References in Pediatric Cardiac Intensive Care: The 2017 Update - Uzark, K.C.; Costello, J.M.; DeSena, H.C.; Thiagajaran, R.; Smith-Parrish, M.; Gist, K.M. (Pediatric Critical Care Medicine, 2018)
Objectives: Pediatric cardiac intensive care continues to evolve, with rapid advances in knowledge and improvement in clinical outcomes. In the past, the Board of Directors of the Pediatric Cardiac Intensive Care Society created and subsequently updated a list of sentinel references focused on the care of critically ill children with congenital and acquired heart disease. The objective of this article is to provide clinicians with a compilation and brief summary of updated and useful references that have been published since 2012. Data Selection: Pediatric Cardiac Intensive Care Society members were solicited via a survey sent out between March 20, 2017, and April 28, 2017, to provide important references that have impacted clinical care. The survey was sent to approximately 523 members. Responses were received from 45 members, of which some included multiple references. Data Extraction: Following review of the list of references, and removing editorials, references were compiled by the first and last author. The final list was submitted to members of the society's Research Briefs Committee, who ranked each publication. Data Synthesis: Rankings were compiled and the references with the highest scores included. Research Briefs Committee members ranked the articles from 1 to 3, with one being highly relevant and should be included and 3 being less important and should be excluded. Averages were computed, and the top articles included in this article. The first (K.C.U.) and last author (K.M.G.) reviewed and developed summaries of each article. Conclusions: This article contains a compilation of useful references for the critical care of children with congenital and acquired heart disease published in the last 5 years. In conjunction with the prior version of this update in 2012, this article may be used as an educational reference in pediatric cardiac intensive care. © 2018 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: pediatric cardiac intensive care; pediatric cardiac surgery; pediatric cardiology; pediatric intensive care

Managing fertile women under lithium treatment: The challenge of a Teratology Information Service - Neri, C.; De Luca, C.; D'oria, L.; Licameli, A.; Nucci, M.; Pellegrino, M.; Caruso, A.; De Santis, M. (Minerva Ginecologica, 2018)
BACKGROUND: The objective of the present study is to review the literature regarding the management of fertile patients under lithium treatment for bipolar disorder and to report the experience of our Teratology Information Service over the past thirteen years in managing women treated with lithium during preconception, pregnancy and breastfeeding. METHODS: This research focuses on a selective review of the literature and a retrospective survey has been carried out on fertile women under lithium treatment who called our service at A. Gemelli University Hospital in Rome from May 2002 to December 2015. RESULTS: A total of 140 women under lithium treatment called our TIS. A complete follow-up has been performed on 34 patients: 29 called during pregnancy and 5 called during preconception. None of the patients called during breastfeeding, while half of the patients were taking concomitant drugs during pregnancy. One major cardiac malformation (hypoplastic left heart syndrome) has been reported. No minor malformations have been detected. Twenty-one patients delivered a living child, with one premature neonate. Two patients underwent voluntary interruption of pregnancy and six patients had early spontaneous abortion. In one patient, intrauterine growth retardation occurred, but with no adverse neonatal outcomes. Four neonates experienced transient respiratory distress at birth. Two children developed mild to severe language delay, but normal motor development. CONCLUSIONS: Lithium treatment in fertile women is a very delicate topic, where risks and benefits of discontinuing therapy when women plan to become pregnant should be accurately evaluated. Thorough peri-conceptional counselling is crucial for the outcome of pregnancy and for maternal health status during preconception, gestation and breastfeeding. © 2018 EDIZIONI MINERVA MEDICA.
Keywords: Lithium; Preconception care; Pregnancy

Feasibility of initiating early enteral nutrition after congenital heart surgery in neonates and infants - Kalra, R.; Vohra, R.; Negi, M.; Joshi, R.; Aggarwal, N.; Aggarwal, M.; Joshi, R. (Clinical Nutrition ESPEN, 2018)
Objective: To assess the feasibility of initiating enteral nutrition support with first 24 h of congenital heart repairs in neonates and Infants and its impact on outcomes following surgery. Design: It is a prospective randomized control single blind study. Setting: It is a single centre prospective study carried out in a tertiary care centre at Pediatric cardiac intensive care unit. Patients: All patients with the cyanotic congenital heart disease with increase pulmonary blood flow, weighing less than 5 kg and undergoing congenital heart repair during the study period were included in the study. Patients with single ventricle status, those undergoing palliative procedures (PA band), open chest, requiring ECMO before leaving operating room, having any other contraindication for starting enteral feeding or those who refuse for consent were excluded from study. Interventions: The patients were randomized into two groups. Group 1 received trophic feeds (10–20 ml/kg/day) starting 4–6 h after surgery while feeds children in group 2 were kept NPO and received feeds after 48 h after surgery. Measurements and main results: 15 children enrolled in both the groups. Both pre-operative and intraoperative variables were comparable in both the groups. There was no complication (vomiting, diarrhea, NEC, bowel necrosis) noted in the children who received feeds after surgery. Mean duration of mechanical ventilation in the feeds group was 58.2 ± 4.71 h, which was less then significantly less than those in the NPO group (P value 0.05). Similarly, duration of ICU stay was only 179.04 ± 41.28 h in feeds group as compared to 228.72 ± 85.44 h in the NPO group. Conclusions: Neonates and Infants tolerate feeds immediately following congenital heart repairs. Moreover, feeds appear to decrease duration of mechanical ventilation and duration of ICU stay. © 2018 European Society for Clinical Nutrition and Metabolism
Keywords: Congenital heart surgery; CPB; Enteral nutrition; Infants

Visuospatial processing in adolescents with critical congenital heart disease: Organization, integration, and implications for academic achievement - Bean Jaworski, J.L.; White, M.T.; DeMaso, D.R.; Newburger, J.W.; Bellinger, D.C.; Cassidy, A.R. (Child Neuropsychology, 2018)
Among the most significant factors affecting quality of life in individuals with critical congenital heart disease (CCHD) are neurodevelopmental challenges, including deficits in visuospatial processing and academic achievement. Few studies have compared outcomes across CCHD subgroups, despite their significant differences in anatomy/physiology and medical/surgical courses. This study compared visuospatial processing abilities using the Developmental Scoring System for the Rey–Osterrieth Complex Figure (DSS-ROCF) across groups of adolescents with CCHD (d-transposition of the great arteries [TGA, n = 139], Tetralogy of Fallot [TOF, n = 68], single-ventricle cardiac anatomy requiring the Fontan operation [SVF, n = 145]) and a group of healthy controls (CTR, n = 111), and examined the validity of visuospatial processing in predicting concurrent academic outcomes. The CCHD subgroups were found to differ in Organization, ps <.001, Structural Accuracy, ps <.001, and Incidental Elements Accuracy scores, ps ≤.008; the post hoc analyses show that the SVF group tended to underperform compared to the other CCHD groups. With respect to academic skills, all CCHD groups scored lower than the CTR group, ps ≤.007; however, the CCHD groups were not different from each other, ps >.23. The regression results showed that the DSS-ROCF Style rating (reflecting integration) accounted for a small yet statistically significant portion of unique variance in “assembled” academic outcomes, over and above the variance already accounted for by DSS-ROCF Organization, p <.01. These findings support the need for comprehensive neuropsychological assessment and monitoring of children and adolescents with CCHD, as well as targeted intervention for organization and integration deficits that may increase their risk for academic underachievement. © 2017 Informa UK Limited, trading as Taylor & Francis Group.
Keywords: Adolescence; Cardiac; Congenital heart defect; Rey–Osterrieth Complex Figure; Visuospatial

Delayed puberty and abnormal anthropometry and its associations with quality of life in young Fontan survivors: A multicenter cross-sectional study - Menon, S.C.; Al-Dulaimi, R.; McCrindle, B.W.; Goldberg, D.J.; Sachdeva, R.; Goldstein, B.H.; Seery, T.; Uzark, K.C.; Chelliah, A.; Butts, R.; Henderson, H.; Johnson, T.; et al. (Congenital Heart Disease, 2018)
Introduction: We sought to evaluate the prevalence of delayed puberty and abnormal anthropometry and its association with quality of life (QoL) in young Fontan survivors. Methods: This was a cross-sectional study at 11 Pediatric Heart Network centers. Demographic and clinical data, anthropomety, and Tanner stage were collected. Anthropometric measurements and pubertal stage were compared to US norms. QoL was assessed using Pediatric Quality of Life inventory (PedsQL). Mixed effects regression modeling adjusting for clustering by center was used to evaluate factors associated with abnormal anthropometry and delayed puberty and associations with QoL. Results: Of the 299 subjects, 42% were female. The median enrollment age was 13.9 years, and the median age at Fontan was 3 years. Fontan survivors had a higher prevalence of short stature relative to normative data (20% vs 5%, P <.0001) and an increased prevalence of abnormal BMI (16% vs 10%, P <.0001) (low [43%] and high [57%]). Fontan subjects, both males (58%) and females (58%), had a delay of 1.5‒2 years in ≥1 Tanner stage parameter compared to normal population. There was no association between delayed puberty and QoL. Abnormal anthropometry was associated with lower overall (62.3 ± 17.3 vs 72.5 ± 16.6; P <.001) and physical appearance scores (72.2 ± 27.4 vs 79.8 ± 21.5; P <.01). Lower exercise capacity was associated with abnormal anthropometry and >2 surgeries before Fontan was associated with delayed puberty. Lower family income (<$25 000) and hypoplastic left heart syndrome were associated with lower QoL. Conclusion: Compared to the normal population, Fontan survivors have high prevalence of short stature, abnormal BMI and delayed puberty. Abnormal anthropometry, but not delayed puberty, was associated with lower overall QoL and perceived physical appearance scores. Routine screening for abnormal anthropometry, especially in HLHS and in lower socioeconomic status families, should be considered to allow interventions, which might ameliorate the negative psychosocial impact. © 2018 Wiley Periodicals, Inc.
Keywords: abnormal growth; delayed puberty; Fontan; quality of life

A multinational observational investigation of illness perceptions and quality of life among patients with a Fontan circulation - Holbein, C.E.; Fogleman, N.D.; Hommel, K.; Apers, S.; Rassart, J.; Moons, P.; Luyckx, K.; Sluman, M.A.; Enomoto, J.; Johansson, B.; Yang, H.-L.; Dellborg, M.; et al. (Congenital Heart Disease, 2018)
Objective: First, to compare QOL and illness perceptions between patients with a Fontan circulation and patients with anatomically simple defects (ie, atrial septal defects [ASD] or ventricular septal defects [VSD]). Second, to explore illness perceptions as a mediator of the association between congenital heart disease (CHD) diagnosis and QOL. Design: Cross-sectional observational study. Setting: Twenty-four cardiology centers from 15 countries across five continents. Patients: Four hundred thirty-five adult patients with congenital heart disease (177 Fontan and 258 ASD/VSD) ages 18-83 years. Outcome Measures: QOL and illness perceptions were assessed by the Satisfaction With Life Scale and the Brief Illness Perceptions Questionnaire, respectively. Results: Patients with a Fontan circulation reported lower QOL (Wald Z = −3.59, p = <.001) and more negative perceptions of their CHD (Wald Z = −7.66, p <.001) compared with patients with ASD/VSD. After controlling for demographics, anxiety, depressive symptoms, and New York Heart Association functional class, path analyses revealed a significant mediation model, αβ = 0.15, p =.002, 95% CI = 0.06-0.25, such that CHD diagnosis was indirectly related to QOL through illness perceptions. Conclusions: The Fontan sample's more negative perceptions of CHD were likely a reflection of life with a more complex defect. Illness perceptions appear to account for unique differences in QOL between groups of varying CHD complexity. Psychosocial screening and interventions may be important treatment components for patients with CHD, particularly those with Fontan circulations. © 2018 Wiley Periodicals, Inc.
Keywords: congenital heart disease; Fontan circulation; illness perceptions; quality of life

Acute Hypoxemia in Infants With Cyanotic Complex Cardiac Anatomy: Simulation Cases for Pediatric Fellows - Peddy, S.B. (MedEdPORTAL : the journal of teaching and learning resources, 2018)
Introduction: Cardiopulmonary compromises are infrequent but high-acuity events that occur at pediatric hospitals. Simulation is a powerful modality to teach fellows in pediatric critical care, cardiology, and neonatology important clinical skills in managing complex cardiorespiratory pathophysiology in infants with cyanotic heart disease. Methods: We developed three simulation cases of hypoxemia involving differing complex cardiorespiratory pathophysiology in neonates/infants with cyanotic heart disease. Through teamwork, the participants were expected to recognize hypoxemia, work through a differential diagnosis, and implement the medical intervention needed to temporize while awaiting further procedures. Assessment of the participants' performance was via direct observation during the simulated activity. Debriefing occurred immediately using a formal debriefing framework. Results: In 10 years, these three cases have been utilized approximately 48 times. Participants subjectively increased their confidence in managing cardiopulmonary events and improved their teamwork and communication skills in similar high-stress events. Discussion: This unique module advanced learners' knowledge by building on their Pediatric Advanced Life Support and Neonatal Resuscitation Program foundation, identified management deficits in the care of patients with complex cardiorespiratory pathophysiology, and taught effective teamwork with role assignment and closed-loop communication.
Keywords: Hypoplastic Left Heart Syndrome; Hypoxemia; Hypoxia; Tetralogy of Fallot; Transposition of Great Arteries; Transposition of Great Vessels

A randomised trial of early palliative care for maternal stress in infants prenatally diagnosed with single-ventricle heart disease - Hancock, H.S.; Pituch, K.; Uzark, K.; Bhat, P.; Fifer, C.; Silveira, M.; Yu, S.; Welch, S.; Donohue, J.; Lowery, R.; Aiyagari, R. (Cardiology in the Young, 2018)
Children with single-ventricle disease experience high mortality and complex care. In other life-limiting childhood illnesses, paediatric palliative care may mitigate maternal stress. We hypothesised that early palliative care in the single-ventricle population may have the same benefit for mothers. In this pilot randomised trial of early palliative care, mothers of infants with prenatal single-ventricle diagnoses completed surveys measuring depression, anxiety, coping, and quality of life at a prenatal visit and neonatal discharge. Infants were randomised to receive early palliative care - structured evaluation, psychosocial/spiritual, and communication support before surgery - or standard care. Among 56 eligible mothers, 40 enrolled and completed baseline surveys; 38 neonates were randomised, 18 early palliative care and 20 standard care; and 34 postnatal surveys were completed. Baseline Beck Depression Inventory-II and State-Trait Anxiety Index scores exceeded normal pregnant sample scores (mean 13.76±8.46 versus 7.0±5.0 and 46.34±12.59 versus 29.8±6.35, respectively; p=0.0001); there were no significant differences between study groups. The early palliative care group had a decrease in prenatal to postnatal State-Trait Anxiety Index scores (-7.6 versus 0.3 in standard care, p=0.02), higher postnatal Brief Cope Inventory positive reframing scores (p=0.03), and a positive change in PedsQL Family Impact Module communication and family relationships scores (effect size 0.46 and 0.41, respectively). In conclusion, these data show that mothers of infants with single-ventricle disease experience significant depression and anxiety prenatally. Early palliative care resulted in decreased maternal anxiety, improved maternal positive reframing, and improved communication and family relationships. © Cambridge University Press 2018.
Keywords: CHD; hypoplastic left heart syndrome; paediatric palliative care; parental stress

Respiratory Training Late After Fontan Intervention: Impact on Cardiorespiratory Performance - Ait Ali, L.; Pingitore, A.; Piaggi, P.; Brucini, F.; Passera, M.; Marotta, M.; Cadoni, A.; Passino, C.; Catapano, G.; Festa, P. (Pediatric Cardiology, 2018)
Fontan palliation allows patients with “single ventricle” circulation to reach adulthood with an acceptable quality of life, although exercise tolerance is significantly reduced. To assess whether controlled respiratory training (CRT) increases cardiorespiratory performance. 16 Adolescent Fontan patients (age 17. 5 ± 3.8 years) were enrolled. Patients were divided into CRT group (n = 10) and control group (C group, n = 6). Maximal cardiopulmonary test (CPT) was repeated at the end of CRT in the CRT group and after an average time of 3 months in the C group. In the CRT group a CPT endurance was also performed before and after CRT. In the CRT group there was a significant improvement in cardiovascular and respiratory response to exercise after CRT. Actually, after accounting for baseline values, the CRT group had decreased breathing respiratory reserve (− 15, 95% CI −22.3 to − 8.0, p = 0.001) and increased RR peak (+ 4.8, 95% CI 0.7–8.9, p = 0.03), VE peak (+ 13.7, 95% CI 5.6–21.7, p = 0.004), VO2 of predicted (+ 8.5, 95% CI 0.1–17.0, p = 0.05), VO2 peak (+ 4.3, 95% CI 0.3 to 8.2, p = 0.04), and VO2 workslope (+ 1.7, 95% CI 0.3–3.1, p = 0.02) as compared to the control group. Moreover, exercise endurance time increased from 8.45 to 17.7 min (p = 0.01). CRT improves cardiorespiratory performance in post-Fontan patients leading to a better aerobic capacity. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Congenital heart disease; Controlled respiratory training; Ergospirometry; Fontan circulation

Functional outcome in contemporary children with total cavopulmonary connection – Health-related physical fitness, exercise capacity and health-related quality of life - Hock, J.; Reiner, B.; Neidenbach, R.C.; Oberhoffer, R.; Hager, A.; Ewert, P.; Müller, J. (International Journal of Cardiology, 2018)
Objective: Children and adolescents with an univentricular heart after total cavopulmonary connection (TCPC) have functional impairments. This study assesses health-related physical fitness (HRPF) and exercise capacity, as well as their relation to health-related quality of life (HRQoL) in patients with an univentricular heart after total-pulmonary connection (TCPC). Patients and methods: Between July 2014 and October 2016 a total of 78 children and adolescents with TCPC (12.0 ± 3.2 years, 21 female) performed a motor test including five tasks for strength and flexibility during their routine follow-up appointment. They also underwent a symptom limited cardio-pulmonary exercise test and filled in a HRQoL questionnaire (KINDL-R). Patients' data were compared to a recent sample of healthy children (n = 1650, 12.6 ± 2.4 years, 49% female). Results: Multivariable regressions corrected for sex, age and BMI showed that TCPC patients achieved 12.4 repetitions of curl-ups (p < 0.001) and 2.6 push-ups (p = 0.010) less than healthy counterparts. They had impairments in trunk (− 8.5 cm; p < 0.001), shoulder (− 7.5 cm; p < 0.001) and lower limb flexibility (− 4.7 cm; p < 0.001). Peak oxygen uptake was reduced to 34.8 ± 7.5 ml/min/kg and 77.7% respectively, compared to peers (p < 0.001). Ventilatory efficiency was also impaired (healthy: 27.5 ± 2.9 vs. TCPC: 31.6 ± 3.3; p < 0.001). HRQoL did not differ significantly (p = 0.233). Conclusions: Children and adolescents with TCPC still present impaired HRPF and exercise capacity whereas HRQoL is similar to healthy peers. Since low HRPF may yield to worse motor competence and exercise capacity, early screening for HRPF and early treatment, if indicated, is recommended. © 2017 Elsevier Ireland Ltd
Keywords: Congenital heart disease; Fontan; Motor competence; Peak oxygen uptake; Univentricular heart

Quality of life and sexual well-being in patients with a Fontan circulation: An explorative pilot study with a mixed method design - Wolff, D.; van de Wiel, H.B.M.; de Muinck Keizer, M.E.; van Melle, J.P.; Pieper, P.G.; Berger, R.M.F.; Ebels, T.; Weijmar Schultz, W.C.M. (Congenital Heart Disease, 2018)
Objective: To get an impression of the quality of life (QOL) and sexual well-being in the Fontan population, and to generate hypotheses for future research. Methods: For this cross-sectional pilot study, questionnaires regarding health-related QOL, sexual function and fertility/pregnancy were completed by 21 patients with a Fontan circulation >16 years old, followed at the University Medical Center Groningen, the Netherlands. Semi-structured qualitative interviews were conducted in 8 patients. Results: Fontan patients scored significantly lower on general health than their healthy peers (t(19)=-3.0, P =.008), whereas their scores on other QOL domains and sexual well-being were comparable to normal values. During childhood, most patients experienced physical limitations and the feeling of being an outsider, and frequently faced bullying. Regarding sexual well-being, large interindividual differences were noted. Four interviewed patients (25-30 years) reported a good sexual well-being, whereas the other interviewed patients (33-47 years) reported erectile dysfunction, low self-esteem and avoidance of sexual intercourse. Both the QOL domains mental health and role restrictions due to emotional problems were associated with female avoidance (P =.083, respectively, P =.089) and dyspareunia (P = ns respectively P =.094). In males, role restrictions due to physical problems and health change were related to sexual dissatisfaction (P =.056) respectively nonsensuality (P =.025). Conclusions: Overall, Fontan patients have a relatively preserved quality of life and sexual wellbeing but face more social isolation and bullying during childhood/adolescence than their healthy peers. Sexual problems were mainly associated with physical limitations in males and with psychosocial limitations in females. Finally, sexual dysfunction was more common in older Fontan patients, and future research has to clarify whether progressive attrition of the Fontan circulation affects the patients' QOL and sexual well-being. © 2018 The Authors. Congenital Heart Disease published by Wiley Periodicals, Inc.
Keywords: congenital heart disease; Fontan physiology; quality of life; sexual functioning; special populations

Association of Habitual Activity and Body Mass Index in Survivors of Congenital Heart Surgery: A Study of Children and Adolescents With Tetralogy of Fallot, Transposition of the Great Arteries, and Fontan Palliation - O'Byrne, M.L.; McBride, M.G.; Paridon, S.; Goldmuntz, E. (World journal for pediatric & congenital heart surgery, 2018)
BACKGROUND: Obesity is associated with increased lifelong morbidity and reduced life span and is increasingly prevalent in the congenital heart disease population. Habitual exercise is an important aspect of a healthy lifestyle and primary prevention of obesity in the general population. The association between habitual activity and body mass index (BMI) has not been studied in children with congenital heart disease. METHODS: A cross-sectional analysis of two previously collected cohorts was performed, including participants 8 to 18 years old with tetralogy of Fallot, transposition of the great arteries, and single ventricle heart disease after a Fontan operation. The association between BMI and duration of habitual exercise (measured by questionnaire) was studied. Secondary analyses assessing the effect of other possible factors for BMI were performed. RESULTS: In total, 172 participants were studied (45% Tetralogy of Fallot, 12% transposition of the great arteries, and 43% Fontan). Median BMI was 18.2, and 29% of the participants were obese or overweight. Median habitual exercise was 5.9 h/wk. Thirty-eight percent of participants reported having their activity restricted by their cardiologist. Increasing exercise duration was associated with lower BMI ( P = .01) in univariate analysis. In secondary analyses, restriction to mild exertion and participation in low-intensity exercise were both associated with increased BMI. CONCLUSION: Increased habitual activity was associated with lower BMI, emphasizing the potential role of recreational sport in the health of children with congenital heart disease.
Keywords: exercise physiology; hypoplastic left heart syndrome; outcomes research; pediatric cardiology; transposition of the great arteries

“Will she live a long happy life?” Parents' concerns for their children with Fontan circulation - du Plessis, K.; Peters, R.; King, I.; Robertson, K.; Mackley, J.; Maree, R.; Stanley, T.; Pickford, L.; Rose, B.; Orchard, M.; Stewart, H.; d'Udekem, Y. (IJC Heart and Vasculature, 2018)
Background: Families of children at the worst end of the congenital heart disease endure a significant burden which is often not clearly delineated in the clinical literature. We examined the greatest concerns of parents whose children have a Fontan circulation. Methods: Parents (N = 107) of children in the Australian and New Zealand Fontan Registry completed online surveys with open-ended and closed questions. A qualitative method approach incorporating thematic analyses was used. Results: The greatest concerns for parents of a child with a Fontan circulation were centered on fear of death for their child and psychosocial well-being, followed by lesser themes around anti-coagulation use, pregnancy and financial burdens. Conclusions: Fear of death and the psychological well-being of their children were the main parental concerns. It highlights the need to clearly communicate information on outcomes to families, and the need for family-focused psychological interventions to improve the psychosocial functioning of both parents and young people. © 2017
Keywords: Congenital heart disease; Fontan; Parents of children with a Fontan circulation; Qualitative research

Can endurance training improve physical capacity and quality of life in young Fontan patients? - Hedlund, E.R.; Lundell, B.; Soderstrom, L.; Sjoberg, G. (Cardiology in the Young, 2018)
Objective Children after Fontan palliation have reduced exercise capacity and quality of life. Our aim was to study whether endurance training could improve physical capacity and quality of life in Fontan patients. Methods Fontan patients (n=30) and healthy age- And gender-matched control subjects (n=25) performed a 6-minute walk test at submaximal capacity and a maximal cycle ergometer test. Quality of life was assessed with Pediatric Quality of Life Inventory Version 4.0 questionnaires for children and parents. All tests were repeated after a 12-week endurance training programme and after 1 year. Results Patients had decreased submaximal and maximal exercise capacity (maximal oxygen uptake 35.0±5.1 ml/minute per·kg versus 43.7±8.4 ml/minute·per·kg, p<0.001) and reported a lower quality of life score (70.9±9.9 versus 85.7±8.0, p<0.001) than controls. After training, patients improved their submaximal exercise capacity in a 6-minute walk test (from 590.7±65.5 m to 611.8±70.9 m, p<0.05) and reported a higher quality of life (p<0.01), but did not improve maximal exercise capacity. At follow-up, submaximal exercise capacity had increased further and improved quality of life was sustained. The controls improved their maximal exercise capacity (p<0.05), but not submaximal exercise capacity or quality of life after training. At follow-up, improvement of maximal exercise capacity was sustained. Conclusions We believe that an individualised endurance training programme for Fontan patients improves submaximal exercise capacity and quality of life in Fontan patients and the effect on quality of life appears to be long-lasting. © Cambridge University Press 2017A.
Keywords: Endurance training; Fontan palliation; Physical capacity; Quality of life

Transcoronary cell infusion with the stop-flow technique in children with single-ventricle physiology - Eitoku, T.; Baba, K.; Kondou, M.; Kurita, Y.; Fukushima, Y.; Hirai, K.; Ohtsuki, S.; Ishigami, S.; Sano, S.; Oh, H. (Pediatrics International, 2018)
Background: Almost all reports on cardiac regeneration therapy have referred to adults, and only a few have focused on transcoronary infusion of cardiac progenitor cells using the stop-flow technique in children. Methods: Intracoronary autologous cardiosphere-derived cell (CDC) transfer was conducted at Okayama University as a phase 1 clinical trial for seven patients with hypoplastic left heart syndrome between January 2011 and December 2012, and as a phase 2 clinical trial for 34 patients with single-ventricle physiology between July 2013 and March 2015. Results: A total of 41 patients with single-ventricle physiology underwent transcoronary infusion of CDC with the stop-flow technique. The median age was 33 months (range, 5–70 months) and the median weight was 10.1 kg (range, 4.1–16.0 kg). Transient adverse events occurred during the procedure, including ST-segment elevation or depression, hypotension, bradycardia, and coronary artery vasospasm. All patients completely recovered. There were no major procedure-related adverse events. In this study, transcoronary infusion of CDC using the stop-flow technique was successfully completed in all patients. Conclusion: Transcoronary infusion of CDC using the stop-flow technique in children is a feasible and safe procedure. © 2017 Japan Pediatric Society
Keywords: congenital heart disease; regeneration therapy; stop-flow technique; temporary occlusion balloon; transcoronary infusion

Physical activity perceptions and behaviors among young adults with congenital heart disease: A mixed-methods study - McKillop, A.; McCrindle, B.W.; Dimitropoulos, G.; Kovacs, A.H. (Congenital Heart Disease, 2018)
Objective: A physically active lifestyle can help maintain positive physical and psychosocial health outcomes among adults with congenital heart disease (CHD). This study explored the physical activity perceptions and behaviors among young adults with CHD. Design: This was a cross-sectional, mixed-methods study that included objectively measured physical activity assessment (accelerometer), individual semistructured interviews, and psychosocial questionnaires. Results: Fifteen participants (67% male; 21 ± 3 years old) with moderate (n = 10) or complex (n = 5) CHD were recruited from an outpatient adult CHD clinic. Participants accumulated 26 ± 16 minutes of moderate-to-vigorous physical activity per day, and reported a high quality of life, moderate self-efficacy for exercise, and low cardiac-focused anxiety. Qualitative data indicated that participants reported more positive perceptions toward activity if their family members encouraged physical activity participation, including siblings that engaged in physical activity alongside participants. Participants described parents as supportive rather than overprotective. Activity precautions were perceived by participants as being instructions from cardiologists rather than restrictions by parents. Participants described some physical limitations compared to peers, but managed challenges by either working within their limitations or choosing activities that met their expectations and/or in which they could fully participate. Participants often described childhood physical activity in the context of school, physical education, and organized sports. Whereas physical activity in childhood was viewed as recreational, the cardiac health-promoting aspects became more prominent in adulthood. Activities performed during one's employment were considered sufficient to meet physical activity recommendation levels, and participants reported limited time and/or energy to participate in activity outside of work. Conclusions: The influence of family appeared to help participants adopt a positive perception toward activity participation in childhood that was carried forward to young adulthood. Future clinical work should target adolescents with CHD with less social supports and/or negative perceptions toward physical activity. © 2017 Wiley Periodicals, Inc.
Keywords: congenital heart disease; exercise; physical activity; qualitative

Posterior spinal fusion for scoliosis after Fontan procedure: A case series - Uehara, M.; Takahashi, J.; Akazawa, Y.; Kuraishi, S.; Ikegami, S.; Futatsugi, T.; Oba, H.; Kato, H. (Journal of Orthopaedic Science, 2018)
Background: As the surgical treatment of scoliosis after a Fontan procedure is very challenging due to the risk of various perioperative complications, case reports are scarce. We herein describe three patients who were successfully treated for scoliosis following a Fontan procedure and discuss their clinical and radiological outcomes. Methods: We retrospectively reviewed three cases of scoliosis treated by posterior spinal fusion after a Fontan procedure. Results: Mean preoperative major curve Cobb angle was 83.7°, mean surgical time was 233.0 min, and mean blood loss was 1167 g. The mean correction rate of the major curve was 48.0%. Surgical outcome as evaluated by Scoliosis Research Society-22 patient questionnaires revealed acceptable results without any severe complications. Conclusions: Corrective surgery for scoliosis after a Fontan procedure becomes a stronger option if cardiac insufficiency is prevented during the perioperative period and a conservative plan is carried out with minimal invasiveness and operation time. © 2017 The Japanese Orthopaedic Association

Higher Cost of Hospitalizations for Non-cardiac Diagnoses in Adults with Congenital Heart Disease - Seckeler, M.D.; Thomas, I.D.; Andrews, J.; Meziab, O.; Moe, T.; Heller, E.; Klewer, S.E. (Pediatric Cardiology, 2018)
Adults with congenital heart disease (CHD) are a rapidly increasing population and their impact on healthcare resources is not fully understood. The purpose of this study was to describe the costs of hospitalizations for non-cardiac disease for adults with CHD. We conducted a retrospective review of hospital discharge data from the University HealthSystem Consortium Clinical Data Base/Resource Manager from January 2011 through December 2013. Patients were ≥ 18 years old at admission with any ICD-9 code for moderate or high severity CHD; cardiac surgical admissions were excluded. The comparison group consisted of patients ≥ 18 years old with no ICD-9 codes for any severity CHD. There were 9,169,700 non-CHD, 28,224 moderate CHD, and 3045 high severity CHD hospital admissions. Total length of stay was longer for acute kidney injury, depressive disorder, esophageal reflux, and obstructive sleep apnea for any severity CHD; ICU admission rates were higher for all diagnoses with any severity CHD. Mean observed direct costs were higher for all diagnoses for moderate CHD and all diagnoses except dehydration, type 2 diabetes, obesity, and obstructive sleep apnea for high severity CHD. This review identified significantly increased hospitalization costs for adults with moderate and high severity CHD who are admitted for non-cardiac medical conditions not associated with concomitant cardiac surgical procedures. Admissions with CHD diagnoses had higher ICU admission rates, longer lengths of stay, and higher mortality for most non-cardiac admission diagnoses. These data will add to our understanding of the economic impact of adults with CHD. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: Administrative dataset; Cost comparison; Fontan procedure; Heart defects, congenital; Hospitalizations; Tetralogy of fallot; Transposition of the great arteries

What determines the quality of life of adult patients after fontan procedure? - Smaś-Suska, M.; Dłużniewska, N.; Weryński, P.; Pająk, J.; Płazak, W.; Olszowska, M.; Podolec, P.; Tomkiewicz-Pająk, L. (Cardiology Journal, 2018)
Background: Despite the low early mortality of Fontan procedures, Fontan patients are prone to various cardiac and extra-cardiac complications in the long term. This may influence patient perception of their health and outcome. The aim of the study was to assess the relationship of multi-organ complications and physical efficiency with self-reported health-related quality of life (QOL) in adult Fontan patients. Methods: Quality of life was assessed with the Short Form-36 questionnaire. Laboratory tests were done together with echocardiography, plethysmography, and cardiopulmonary exercise test. Results: The QOL was poorer in patients than in control subjects. The physical characteristics of patients correlated with dynamic ventilatory parameters, heart rate at the peak of exercise, alanine aminotransferase and albumin level. Conclusions: Liver impairment and chronotropic incompetence during exercise are associated with poor QOL in patients after Fontan procedure. In these patient, hepatic, pulmonary and cardiac functions should be carefully monitored. © 2018, Via Medica. All rights reserved.
Keywords: Adult Fontan patients; Exercise tolerance; Multiorgan complications; Pulmonary function test; Quality of life; SF-36

Regional brain gray matter changes in adolescents with single ventricle heart disease - Singh, S.; Kumar, R.; Roy, B.; Woo, M.A.; Lewis, A.; Halnon, N.; Pike, N. (Neuroscience Letters, 2018)
Adolescents with single ventricle heart disease (SVHD) show autonomic, mood, and cognitive deficits, indicating aberrations in brain areas that regulate these functions. However, the gray matter integrity in autonomic, mood, and cognitive control sites is unclear. We examined regional brain gray matter changes, using high-resolution T1-weighted images (3.0-T magnetic resonance scanner) with voxel based morphometry procedures, as well as mood and cognitive functions in SVHD (n = 18; age, 15.7 ± 1.1 years; male, 10) and controls (n = 31; age, 16.0 ± 1.1 years; male, 17). High-resolution T1-weighted images were realigned, gray matter tissue type partitioned, normalized to a common space, smoothed, and compared between groups (analysis of covariance; covariates, age and gender). The mood and cognitive scores were compared between groups using independent samples t-tests. SVHD subjects showed significantly altered mood and cognitive functions over controls. Significantly reduced gray matter emerged in multiple brain areas, including the thalamus, caudate nuclei, putamen, insula, prefrontal, post-central and precentral gyrus, occipital gyrus, para-hippocampal gyrus, temporal gyrus, and cerebellar sites in SVHD over controls. SVHD subjects show compromised gray matter integrity in autonomic, mood and cognitive control sites. The findings indicate that frequent deficits found in SVHD subjects have a brain structural basis in the condition. © 2017 Elsevier B.V.
Keywords: Cognition; Congenital heart disease; Gray matter; Magnetic resonance imaging; Voxel based morphometry

Histopathological abnormalities in the central arteries and veins of Fontan subjects - Hays, B.S.; Baker, M.; Laib, A.; Tan, W.; Udholm, S.; Goldstein, B.H.; Sanders, S.P.; Opotowsky, A.R.; Veldtman, G.R. (Heart, 2018)
Objective Fontan circulations have obligatory venous hypertension, depressed cardiac output and abnormal arterial elastance. Ventriculovascular coupling is known to be abnormal, but the underlying mechanisms are poorly defined. We aim to describe the histopathological features of vascular remodelling encountered in the central arteries and veins in the Fontan circulation as a possible underlying pathological representation of abnormal ventriculovascular coupling. Methods Postmortemvasculature (inferior vena cava (IVC), superior vena cava (SVC), pulmonary artery (PA), pulmonary vein (PV) and aorta) of 13 patients with a Fontan circulation (mean age 29.9 years, range 9.0-59.8 years) and 2 biventricular controls (ages 17.9 and 30.2 years) was examined. Results IVC and SVC: Eccentric and variable intimal fibromuscular proliferation occurred in 11 Fontan subjects. There was variable loss of medial smooth muscle bundles with reciprocal replacement with dense collagenous tissue. PA: Similar intimal fibromuscular proliferation was seen; however, these intimal changes were accompanied by medial thinning rather than expansion, medial myxoid degeneration and elastic alteration. PV: The PVs demonstrated intimal fibroproliferation and disorganisation of the muscular media. Aorta: The aortic lamina intima was thickened, with associated fibromuscular proliferation and elasticisation. There was also moderate lymphocytic inflammation in the aortic wall. Conclusions Vascular architectural remodelling is common in Fontan patients. The central veins demonstrate profound changes of eccentric intimal expansion and smooth muscle replacement with collagen. The pulmonary demonstrated abnormal intimal proliferation, and aortic remodelling was characterised by intima lamina thickening and a moderate degree of aortic wall inflammation. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2018.
Keywords: Congenital Heart Disease; Fontan Physiology; Vascular Biology

Oxidation Reduction Potential (ORP) is Predictive of Complications Following Pediatric Cardiac Surgery - Schmidt, A.E.; Gore, E.; Henrichs, K.F.; Conley, G.; Dorsey, C.; Bjugstad, K.B.; Refaai, M.A.; Blumberg, N.; Cholette, J.M. (Pediatric Cardiology, 2018)
Oxidation reduction potential (ORP) or Redox is the ratio of activity between oxidizers and reducers. Oxidative stress (OS) can cause cellular injury and death, and is important in the regulation of immune response to injury or disease. In the present study, we investigated changes in the redox system as a function of cardiopulmonary bypass (CPB) in pediatric patients. 664 plasma samples were collected from 162 pediatric patients having cardiac surgery of various CPB times. Lower ORP values at 12 h post-CPB were associated with poor survival rate (mean ± SD 167 ± 20 vs. 138 ± 19, p = 0.005) and higher rate of thrombotic complications (153 ± 21 vs. 168 ± 20, p < 0.008). Similarly, patients who developed infections had lower ORP values at 6 h (149 ± 19 vs. 160 ± 22, p = 0.02) and 12 h (156 ± 17 vs. 168 ± 21, p = 0.004) post-CPB. Patients that developed any post-operative complication also had lower 6 h (149 ± 17 vs. 161 ± 23, p = 0.002) and 12 h (157 ± 18 vs. 170 ± 21, p = 0.0007) post-CPB ORP values. Free hemoglobin and IL-6, IL-10, and CRP were not associated with ORP levels. However, higher haptoglobin levels preoperatively were protective against decreases in ORP. Decreased ORP is a marker for poor outcome and predictive of post-operative thrombosis, infection, and other complications in critically ill pediatric cardiac surgery patients. These results suggest that redox imbalance and OS may contribute to the risk of complications and poor outcome in pediatric CBP patients. Haptoglobin may be a marker for increased resilience to OS in this population. © 2017, Springer Science+Business Media, LLC.
Keywords: Blood; Cardiac surgery; Complications; Oxidation reduction potential; Pediatrics; Red blood cells

Ventricular assist device in a failing total cavopulmonary connection: A new step-by-step approach - Napoleone, C.P.; Cascarano, M.T.; Deorsola, L.; Valori, A. (Interactive Cardiovascular and Thoracic Surgery, 2018)
The management of failing Fontan patients with mechanical circulatory support has been reported with unsatisfactory results. A 5-yearold girl, listed for heart transplantation for failing Fontan, underwent rescue extracorporeal membrane oxygenation support. As it was necessary to move the patient to the Berlin Heart Excor, a step-by-step approach was designed to obtain a gradual adaptation to this form of support. A central extracorporeal membrane oxygenation, with a Berlin Heart apical and aortic cannulae, was implanted leaving the previously positioned femoral vein cannula in parallel with the outflow apical one. The femoral vein cannula was removed when the lungs recovered from the effects of surgical trauma. Four days later, the Fontan fenestration was closed, and after 4 more days, a gradual reduction of gas support was planned without problems. Oxygenator was then removed, and 4 days later, a 30-ml Berlin Heart EXCOR ventricle replaced the centrifugal pump. This sequential approach, which has never been described before, can improve the results of the ventricular assist device support in failing Fontan patients, because it allows a gradual adaptation, even in patients with damaged lungs. © 2017 The Author.
Keywords: Extracorporeal membrane oxygenation; Fontan procedureFontan procedure; Ventricular assist device

Strain of ascending aorta on cardiac magnetic resonance in 1027 patients: Relation with age, gender, and cardiovascular disease - Scarabello, M.; Codari, M.; Secchi, F.; Cannaò, P.M.; Alì, M.; Di Leo, G.; Sardanelli, F. (European Journal of Radiology, 2018)
Objectives To evaluate ascending aortic strain (AAS) with cardiac magnetic resonance (CMR) in a large consecutive series of patients with different types of cardiovascular disease (CVD). Methods Two-dimensional phase-contrast gradient-echo sequences of the ascending aorta were retrospectively reviewed in 1027 patients (726 males, 301 females). Aortic lumen area was segmented using a semi-automatic approach to calculate AAS values. Subgroup analysis was performed for patients with normal CMR, tetralogy of Fallot (ToF), and ischemic heart disease (IHD). Multivariate and post-hoc analyses were performed to evaluate the effect of age, gender, and CVD on AAS values. Shapiro-Wilk, three- and two-way ANOVA, Mann-Whitney U, and Spearman correlation statistics were used. Results Multivariate analysis showed significant differences in AAS among decades of age (p < 0.001), genders (p = 0.006) and CVD subgroups (p < 0.001) without interaction among these factors. A gender-related difference (higher AAS in females) was significant in ToF (p = 0.008), while an AAS reduction during aging was observed in all CVD subgroups. Post-hoc analysis showed a significantly lower AAS in ToF and IHD patients compared to subjects with normal CMR (p < 0.001). Conclusion Differences in age, gender, and CVD independently affect AAS. The lower AAS observed in ToF fosters its assessment during follow-up in adulthood. Future studies on causes and clinical implications of a higher AAS in females affected by ToF are warranted. © 2017 Elsevier B.V.
Keywords: Aging; Ascending aorta; Ischemic heart disease; Magnetic resonance imaging; Tetralogy of Fallot

Children with hypoplastic left heart syndrome have lower quality of life than healthy controls and children with other illnesses - Dempster, N.; Cua, C.L.; Wernovsky, G.; Caris, E.; Neely, T.; Allen, R.; Butz, C. (Cardiology in the Young, 2018)
Objective Previous studies suggest that children with congenital cardiac diagnoses report lower quality of life when compared with healthy norms. A few studies have evaluated quality of life specifically in children born with hypoplastic left heart syndrome, a condition requiring several surgeries before age three. The aim of this study was to use an empirically validated and standardised measure - the Pediatric Quality of Life Inventory - to evaluate quality of life in children with hypoplastic left heart syndrome and compare the findings with similar, medically complicated samples. Methods The parent-report Pediatric Quality of Life Inventory was administered, and demographic information was collected through an internet portal. A total of 121 caregivers of children with hypoplastic left heart syndrome responded. The sample included children aged 2-18 years (M=10.81 years). Independent sample t-tests were used to compare our sample with published norms of healthy children and children with acute or chronic illnesses. Results Children with hypoplastic left heart syndrome were rated as having significantly lower overall quality-of-life scores (M=59.69) compared with published norms of children without medical diagnoses (M=83.00) and those with acute (M=78.70) or chronic (M=77.19) illnesses (p<0.001). Children with hypoplastic left heart syndrome complicated by a stroke or seizure (15%) reported the lowest quality of life. The results held for all subscales (p<0.001). Conclusions Children with hypoplastic left heart syndrome appear to be a significantly vulnerable population with difficulties in functioning across psychosocial domains and across the age span. Further research is required to facilitate early identification of the need for resources for these children and families, especially for children who experience additional medical complications. © Cambridge University Press 2017.
Keywords: adjustment; Hypoplastic left heart syndrome; quality of life

Stress and quality of life among parents of children with congenital heart disease referred for psychological services - Kaugars, A.; Shields, C.; Brosig, C. (Congenital Heart Disease, 2018)
Objective: The study examined parent stress and health-related quality of life (HRQOL) among families of children with congenital heart disease (CHD) referred for psychological services. Methods: Parents of 54 children (85% boys) aged 3 to 13 (Mage = 7.48, SD = 2.38) completed measures to assess parenting stress (Parenting Stress Index – Short Form; Pediatric Inventory for Parents) and the PedsQL Family Impact Module. Medical information was retrieved from medical record review. Results: Half of parents of children with single ventricle anatomy had clinically significant levels of parenting stress. Parents of children with single ventricle anatomy reported more frequent illness-related stress and more difficulty dealing with illness-related stress than parents of children with two ventricle anatomy. Younger gestational age at birth and referral for attention or behavior problems were associated with greater likelihood of parent at-risk psychosocial functioning. Conclusions: Among children referred for psychological services, many parents report significant stress and significant negative impact of the child's medical condition on the family. Results underscore the need to consider assessing parent psychosocial functioning and providing additional support for parents of children with CHD. © 2017 Wiley Periodicals, Inc.
Keywords: children; congenital heart disease; health-related quality of life; parent stress; parents

Utilisation of early intervention services in young children with hypoplastic left heart syndrome - Mussatto, K.A.; Hollenbeck-Pringle, D.; Trachtenberg, F.; Sood, E.; Sananes, R.; Pike, N.A.; Lambert, L.M.; Mahle, W.T.; Goldberg, D.J.; Goldberg, C.S.; Dunbar-Masterson, C.; Otto, M.; et al. (Cardiology in the Young, 2018)
Objective Children with hypoplastic left heart syndrome are at a risk for neurodevelopmental delays. Current guidelines recommend systematic evaluation and management of neurodevelopmental outcomes with referral for early intervention services. The Single Ventricle Reconstruction Trial represents the largest cohort of children with hypoplastic left heart syndrome ever assembled. Data on life events and resource utilisation have been collected annually. We sought to determine the type and prevalence of early intervention services used from age 1 to 4 years and factors associated with utilisation of services. Methods Data from 14-month neurodevelopmental assessment and annual medical history forms were used. We assessed the impact of social risk and geographic differences. Fisher exact tests and logistic regression were used to evaluate associations. Results Annual medical history forms were available for 302 of 314 children. Greater than half of the children (52-69%) were not receiving services at any age assessed, whereas 20-32% were receiving two or more therapies each year. Utilisation was significantly lower in year 4 (31%) compared with years 1-3 (with a range from 40 to 48%) (p<0.001). Social risk factors were not associated with the use of services at any age but there were significant geographic differences. Significant delay was reported by parents in 18-43% of children at ages 3 and 4. Conclusion Despite significant neurodevelopmental delays, early intervention service utilisation was low in this cohort. As survival has improved for children with hypoplastic left heart syndrome, attention must shift to strategies to optimise developmental outcomes, including enrolment in early intervention when merited. © Cambridge University Press 2017.
Keywords: CHD; early intervention; neurodevelopmental disorders

Second annual Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs) report: Pre-implant characteristics and outcomes - Blume, E.D.; VanderPluym, C.; Lorts, A.; Baldwin, J.T.; Rossano, J.W.; Morales, D.L.S.; Cantor, R.S.; Miller, M.A.; St. Louis, J.D.; Koehl, D.; Sutcliffe, D.L.; Eghtesady, P.; et al. (Journal of Heart and Lung Transplantation, 2018)
Background Expanded use of pediatric ventricular assist devices (VADs) has decreased mortality in children awaiting heart transplantation. Pediatric Interagency Registry for Mechanical Circulatory Support (Pedimacs), a National Heart, Lung, and Blood Institute–sponsored North American database, provides a platform to understand this emerging population. Methods Between September 2012 and September 2016, patients aged younger than 19 years who underwent VAD implantation were enrolled in Pedimacs. FDA approved durable devices as well as temporary support devices were included. The second annual report updates the current Pedimacs data. Patients implanted with temporary devices are included in Pedimacs and this analysis includes this group of paracorporeal continuous flow VADs. Results Over the 4 years, 42 hospitals implanted 432 devices in 364 patients less than 19 yrs of age. Diagnoses included cardiomyopathy in 223 (61%), myocarditis in 41 (11%), and congenital heart disease in 77 (21%), of which 48 had single-ventricle physiology. At implant, 87% were at Intermacs patient profile 1 or 2. The age distribution of children (59% male) supported on VAD included 69 (19%) aged younger than 1 year, 66 (18%) aged 1 to 6 years, 56 (15%) aged 6 to 10 years, and 173 (48%) aged 11 to 19 years. Median follow-up was 2.2 months (range, 1 day to 41.5 months). Median (interquartile) age at implant was 1.7 (0.3–10.0) years for paracorporeal continuous-flow pumps (n = 60), 1.7 (0.4–5.3) years for paracorporeal pulsatile pumps (n = 105), and 15.0 (11.3–16.9) years for implantable continuous-flow pumps (n = 174). Support strategies included LVAD in 293 (80%), biventricular device in 55 (15%), and total artificial heart in 8 (2%). Nearly 50% of patients underwent transplantation within 6 months, with overall mortality of 19%. Adverse event burden continues to be high. Conclusions Pedimacs constitutes the largest longitudinal pediatric VAD registry. Preimplant data across centers will be helpful at creating shared protocols with which to improve outcomes. Adverse events continue to be the major challenge, especially among the young critically ill children with complex congenital disease. © 2018 International Society for the Heart and Lung Transplantation
Keywords: advanced heart failure; bridge to transplant; children; mechanical support; pediatrics; Pedimacs; ventricular assist device

Neurodevelopmental Outcome in Children with Single Ventricle after Total Cavopulmonary Connection - Vahsen, N.; Bröder, A.; Hraska, V.; Schneider, M. (Klinische Padiatrie, 2018)
Background The purpose of the present study was to assess a broad range of neuropsychological outcome variables in children with functionally single ventricle hearts after a total cavopulmonary connection and to examine potential risk factors for impaired neurodevelopment. Patients & Method A total of 104 patients aged 2 to 20 years underwent follow-up standardized psychological testing, including measures of intelligence, motor function, visuospatial abilities, behavioural outcome and health-related quality of life. Results With a mean fluid intelligence score of 93.0 and a mean crystallized intelligence score of 92.3, patients scored significantly lower on tests of intelligence compared to the general population (p<0.001). Reduced motor function was found in 34% of the patients (p<0.001), impaired visuospatial abilities in 51%; parents reported significantly more behavioural problems (p<0.001). There was no difference in the self-reported quality of life compared to the general population. Risk factors for reduced fluid intelligence were deep hypothermic circulatory arrest times (p=0.03) and complications causing suboptimal brain perfusion prior to the total cavopulmonary connection (e. g. seizures; p=0.04). Conclusions Patients with functionally single ventricle hearts palliated with a total cavopulmonary connection are at an increased risk of neurodevelopmental delays and behavioural disorders. Nevertheless, they adapt well in terms of quality of life. Early diagnostics and interventions are necessary when developmental delays are suspected.
Keywords: follow-up studies; neurodevelopmental outcome; quality of life; risk factors; Total cavopulmonary connection

Arrhythmias in children with a single ventricle - Plotnikova, I.V.; Dzhaffarova, O.Yu.; Svintsova, L.I.; Saushkin, V.V.; Kovalev, I.A. (Bulletin of Siberian Medicine, 2018)
The paper presents the findings on the prevalence rate and structure of arrhythmias and conduction disorder in children with chronic heart defect (CHD) and a functionally univentricular heart (FUH) at the stages of hemodynamic correction. The article also analyses factors determining the risk of arrhythmia development. Seventy patients with CHD and FUH who underwent all the stages of hemodynamic correction were examined. At each stage of surgical correction all children had an examination, including cardiac ultrasound, pulse oximetry, cardiac catheterization and angiopneumography, ECG, and 24-hour ECG monitoring before and after surgery, in order to reveal arrhythmia and conduction disorder. Absence of rhythm disturbances at the first stage of hemodynamic correction was 98.1%, at the second - 80%, at the third - 48.6% and at the fourth stage - 41.5%. Starting from the second stage of hemodynamic correction, the most frequent rhythm disturbance was dysfunction of the sinus node. Statistical analysis showed that there was a significant decrease in oxygen saturation in capillary blood (73 ± 12% and 81 ± 4%, respectively, p <0.05) and an increase in the average pressure in the pulmonary artery after total cavopulmonary connection (TCPC) (9.6 ± 4.2% and 11.5 ± 5.8%, respectively, p <0.05) in the group of children with heart rhythm disturbances as compared to children without arrhythmias. The average age of patients with arrhythmias in the group of patients having TCPC and, respectively, after the closure of fenestration, was statistically significantly higher than in the group of children without arrhythmias (72 ± 43 months and 52 ± 27 months, respectively, p <0.05). The study of arrhythmias in patients with a functionally univentricular heart requires prospective observation, since they significantly affect the prognosis of the disease and the quality of life. © 2018 Siberian State Medical University. All rights reserved.
Keywords: Children; Postoperative arrhythmias; Stages of hemodynamic correction of congenital heart defect; Univentricular heart

Externally applied compression therapy for Fontan patients - Hernandez, J.; Chopski, S.G.; Lee, S.; Moskowitz, W.B.; Throckmorton, A.L. (Translational Pediatrics, 2018)
Background: Limited therapeutic options are available for Fontan patients with dysfunctional or failing single ventricle physiology. This study describes the evaluation of an alternative, non-invasive, at-home therapeutic compression treatment for Fontan patients. Our hypothesis is that routinely administered, externally applied compression treatments to the lower extremities will augment systemic venous return, improve ventricular preload, and thus enhance cardiac output in Fontan patients. Methods: To initially evaluate this hypothesis, we employed the NormaTec pneumatic compression device (PCD) in a pilot clinical study (n=2). This device is composed of inflatable trouser compartments that facilitate circumferentially and uniformly applied pressure to a patient’s lower extremities. Following an initial health screening, test subjects were pre-evaluated with a modified-Bruce treadmill exercise stress test, and baseline data on cardiorespiratory health was collected. After training, test subjects conducted 6 days of external compression therapy at-home. Subjects were then re-evaluated with a final treadmill stress test and data acquisition of new cardiorespiratory parameters. Results: Both subjects demonstrated improvement in exercise duration time, peak oxygen volume, and ventilator threshold, as compared to the baseline evaluation. Conclusions: These findings are promising and provide the foundation for future studies that will focus on increasing study participation (sample size) to better assess the clinical benefit of compression therapy for Fontan patients. © Translational Pediatrics. All rights reserved.
Keywords: Congenital heart disease (CHD); Enhanced external counterpulsation (EECP); Single ventricle physiology

Recent advances and challenges on application of tissue engineering for treatment of congenital heart disease - Mantakaki, A.; Fakoya, A.O.J.; Sharifpanah, F. (PeerJ, 2018)
Congenital heart disease (CHD) affects a considerable number of children and adults worldwide. This implicates not only developmental disorders, high mortality, and reduced quality of life but also, high costs for the healthcare systems. CHD refers to a variety of heart and vascular malformations which could be very challenging to reconstruct the malformed region surgically, especially when the patient is an infant or a child. Advanced technology and research have offered a better mechanistic insight on the impact of CHD in the heart and vascular system of infants, children, and adults and identified potential therapeutic solutions. Many artificial materials and devices have been used for cardiovascular surgery. Surgeons and the medical industry created and evolved the ball valves to the carbon-based leaflet valves and introduced bioprosthesis as an alternative. However, with research further progressing, contracting tissue has been developed in laboratories and tissue engineering (TE) could represent a revolutionary answer for CHD surgery. Development of engineered tissue for cardiac and aortic reconstruction for developing bodies of infants and children can be very challenging. Nevertheless, using acellular scaffolds, allograft, xenografts, and autografts is already very common. Seeding of cells on surface and within scaffold is a key challenging factor for use of the above. The use of different types of stem cells has been investigated and proven to be suitable for tissue engineering. They are the most promising source of cells for heart reconstruction in a developing body, even for adults. Some stem cell types are more effective than others, with some disadvantages which may be eliminated in the future. Copyright 2018 Mantakaki et al.
Keywords: Biomaterials; Bioprosthetics; Cardiac progenitor cells; Congenital heart disease; Scaffolds; Stem cells; Tissue engineering

The major clinical presentations and echocardiographic features of structural cardiac disease among children in Kordofan, Sudan - Mustafa, A.E.M.; Tahir Ali, N.M.; Elrahim, S.Y.A.; Bharti, R.K.R.; Chaudhary, S. (Pakistan Journal of Medical and Health Sciences, 2018)
Background: Patterns of heart diseases differ between the high income countries and low income countries. 1, 2 Acquired heart diseases like RHD, cardiomyopathies, pericarditis are still a public health burden while congenital heart diseases still carry a poor outcome among children 3 . The absence of early diagnosis, surgical intervention and inadequate access to medication and the existing burden of communicable diseases increases the strain on a staggering economy of most sub Saharan countries. Aim: To assess the clinical and echocardiographic pattern of cardiac disease in children in Kordofan state and to develop a road map plan of their further management. Methods: An analytical cross sectional hospital based study. The study included the children of age groups 1 day up to 18 years with diagnosed or strongly suspected congenital or acquired cardiac disease who have their follow up in the pediatric sections of El-Obied hospitals in the western central part of the Sudan. Every child in the study group was assessed clinically with focused history taken and relevant physical examination. Chest x-ray and proper echocardiography was done for every child in the study group. Management plan was put by the pediatric cardiologist for all the children in the study group. Eighty children were enrolled in this study. Results: 80 children studied, 55% were males and females represent 45%. Most of the children with cardiac disease in the study were from the age group 1-5 years (27.5%) followed by infants (26.2%).after that, 5-10 years, more than 10 years and less than one month. Nine patients (11.25%) were severely affected, 26 (32.5%) were moderately affected and the growth of 45 (56.25%) was normal. Clinical evaluation of the study group revealed that, 19 children (24%) presented with respiratory symptoms and /or respiratory distress. A cardiac murmur was heard in most of the patients in this series, systolic murmurs heard in 55 patients (69%) of which 21 were pansystolic (26%) and 8 were ejection systolic murmurs (10%). Hepatomegaly was found in 25 patients (31%) and Hepatosplenomegaly in 4 patients (5%). Down syndrome was found in 5 patients (6%), William syndrome in one patient. Congenital HD found in 56 patients (70%) and acquired HD in 24 (30%), 19 patients (79% of the acquired heart disease and 23.7% of the total study group was diagnosed as having rheumatic heart disease and cardiomyopathy was found in 5 patients (20.8% of acquired heart disease). Conclusion: Rheumatic cardiac disease is preventable through the proper and complete antibiotic treatment of streptococcal pharyngitis and tonsillitis and it is vital to apply and strict to the recommendations of the national program of prevention of rheumatic fever and rheumatic heart disease. © 2018 Lahore Medical And Dental College. All Rights Reserved.
Keywords: Children; Echocardiography; Management; Rheumatic Cardiac Disease; Sudan

Current state of pediatric cardiac transplantation - Dipchand, A.I. (Annals of Cardiothoracic Surgery, 2018)
Pediatric heart transplantation is standard of care for children with end-stage heart failure. The diverse age range, diagnoses, and practice variations continue to challenge the development of evidence-based practices and new technologies. Outcomes in the most recent era are excellent, especially with the more widespread use of ventricular assist devices (VADs). Waitlist mortality remains high and knowledge of risk factors for death while waiting and following transplantation contributes to decision-making around transplant candidacy and timing of listing. The biggest gap impacting both waitlist and overall survival remains mechanical support options for infants and patients with single ventricle physiology. Though acute rejection has decreased progressively, both diagnosis and management of antibody-mediated rejection has become increasingly challenging and complex, as has the ability to understand the implication of anti-HLA antibodies detected both pre- and post-transplantation-including when and how to intervene. Trends in immunosuppression protocols include more use of induction therapy and steroid avoidance or withdrawal protocols. Common long-term morbidities include renal insufficiency, which can be mitigated with surveillance and renal-sparing strategies, and infections. Functional outcomes are excellent, but significant psychosocial challenges exist in relation to neurodevelopment, non-adherence, and transition from child-centered to adult-centered care. Cardiac allograft vasculopathy (CAV) remains a barrier to long-term survival, though it is more apparent that objective evidence of an impact on the allograft is important with regards to impact on outcomes. Retransplantation is rare in pediatric heart transplant recipients. Pediatric heart transplantation continues to evolve in order to address the challenges of the diverse group of patients that reach end-stage heart failure during childhood. © Annals of Cardiothoracic Surgery.
Keywords: Heart transplant; Mechanical support; Outcomes; Sensitization; Waitlist

Exercise performance after univentricular palliation - Talwar, S.; Kumar, M.; Sreenivas, V.; Gupta, V.; Choudhary, S.; Airan, B. (Annals of Pediatric Cardiology, 2018)
Background : The optimal timing, need for primary/staged procedure in patients undergoing univentricular palliation, is debatable. Aims : We performed this study to assess the exercise performance of patients undergoing various forms of univentricular palliation. Setting and Design : This was a retrospective, prospective comparative study conducted at a multispecialty tertiary referral center. Patients and Methods : Between January 2012 and June 2015, 117 patients undergoing either bidirectional Glenn (BDG) (n = 43) or Fontan (total cavopulmonary connection [TCPC]) (n = 74) underwent exercise testing. Statistical Analysis : Comparisons between subgroups for continuous data were made with Student's ttest if normally distributed and Wilcoxon ranksum test otherwise. Tests between subgroups for qualitative data were made with Pearson's Chisquare test. Results : Patients who underwent BDG with open antegrade pulmonary blood flow (APBF) had higher saturations (oxygen saturation [SpO2]) compared to those without it (87.5 ± 5.0% vs. 81.1 ± 4.8%; P = 0.0001). However, we found no differences in exercise parameters of patients undergoing BDG with or without APBF. Extracardiac TCPC (n = 42) patients demonstrated better exercise capacity (15.0 ± 7.7 vs. 11.2 ± 6.2 min; P = 0.02) and increased SpO2 on exercise (87.0 ± 8.0% vs. 83.4 ± 7.6%; P ≤ 0.05) compared to lateral tunnel TCPC (n = 32). Fenestrated TCPC (n = 30) patients had higher exercise capacity reflected by higher metabolic equivalents (METs) consumption (6.4 ± 2.3 vs. 5.2 ± 2.0 METs, P = 0.02), fewer pleural effusions (7.0 ± 3.2 vs. 9.2 ± 6.2 days, P ≤ 0.05), and lower hospital stay (9.5 ± 4.0 vs. 12.7 ± 7.7 days, P = 0.04) compared to nonfenestrated TCPC (n = 44) patients. Conclusions : We observed no differences in exercise parameters of patients undergoing BDG with or without APBF. Extracardiac TCPC patients had better exercise capacity but longer postoperative hospital stay and pleural effusions than patients with lateral tunnel Fontan. Fenestrated TCPC patients seemed to fare better than nonfenestrated ones. Patients undergoing TCPC had better exercise capacity than patients undergoing BDG alone.
Keywords: Bidirectional Glenn; exercise performance; fontan operation; single ventricle

Recombinant factor VIIa as a rescue therapy in severe haemoptysis in a patient with a Fontan circulation - Mason, T.W.; Retter, A.; Morgan, G.J. (Cardiology in the Young, 2018)
We describe the successful use of recombinant factor VIIa (rFVIIa) in the control of massive haemoptysis in a 17-year-old patient with a Fontan circulation. The patient was intubated and ventilated in the ICU with deteriorating gas exchange. Conventional methods to control the haemoptysis were ineffective, and rFVIIa was successfully administered as a rescue therapy. rFVIIa is a powerful pro-thrombotic agent, which is only licensed in haemophiliacs with acquired inhibitors to anticoagulation. It has been used off-license in the treatment of massive haemorrhage, although a Cochrane review did not show any significant benefit; however, it may have a role as a rescue therapy where alternatives options have been exhausted after careful risk-benefit analysis. © Cambridge University Press 2017.
Keywords: factor VIIa; Fontan; haemoptysis; rFVIIa

Risk of dementia in adults with congenital heart disease: Population-based cohort study - Bagge, C.N.; Henderson, V.W.; Laursen, H.B.; Adelborg, K.; Olsen, M.; Madsen, N.L. (Circulation, 2018)
BACKGROUND: More children with congenital heart disease (CHD) are surviving to adulthood, and CHD is associated with risk factors for dementia. We compared the risk of dementia in CHD adults to that of the general population. METHODS: In this cohort study, we used medical registries and a medical record review covering all Danish hospitals to identify adults with CHD diagnosed between 1963 and 2012. These individuals with CHD were followed from January 1, 1981, 30 years of age, or date of first CHD registration (index date for matched members of the general population cohort) until hospital diagnosis of dementia, death, emigration, or end of study (December 31, 2012). For each individual with CHD, we identified 10 members of the general population utilizing the Danish Civil Registration System matched on sex and birth year. We computed cumulative incidences and hazard ratios (HRs) of dementia, adjusting for sex and birth year. RESULTS: The cumulative incidence of dementia was 4% by 80 years of age in 10 632 adults with CHD (46% male). The overall HR comparing adults with CHD with the general population cohort was 1.6 (95% confidence interval [CI], 1.3-2.0). The HR among individuals with CHD without extracardiac defects was 1.4 (95% CI, 1.1-1.8). Adults with mild-to-moderate CHD had an HR of 1.5 (95% CI, 1.1-2.0), whereas the HR was 2.0 (95% CI, 1.2-3.3) for severe CHD, including univentricular hearts. The HR for early onset dementia (<65 years of age) was 2.6 (95% CI, 1.8-3.8), whereas the late-onset HR was 1.3 (95% CI, 1.0-1.8). CONCLUSIONS: CHD was associated with an increased risk of dementia compared with the general population, in particular for early onset dementia. Further understanding of dementia risk in the population with CHD is a potential target for future investigation. © 2018 American Heart Association, Inc.
Keywords: Cohort study; Congenital heart disease; Dementia; Epidemiology; Long-term outcome

Applicability of a modified EFAST protocol (r-EFAST) to evaluate hemodynamically unstable patients after percutaneous cardiac intervention - Vázquez Martínez, J.L.; Quiñones Coneo, K.L.; Villegas, T.V.; Sánchez Porras, M.; Macarrón, C.P.-C.; Pérez, A.C.; Pineda, L.F. (Critical Ultrasound Journal, 2017)
Percutaneous cardiac intervention is an invasive diagnostic and therapeutic technique which carries a significant complication rate. Although the usefulness of EFAST protocol is widely recognised, this paper will attempt to explore a modified approach involving a focused examination on the retroperitoneal (r-EFAST). We have provided examples of 3 cases where r-EFAST was used to detect retroperitoneal bleeding in critical situations. © 2017, The Author(s).
Keywords: Cardiac catheterization; Congenital heart defect; Hematoma; Retroperitoneal space

Psychosocial impact on families with an infant with a hypoplastic left heart syndrome during and after the interstage monitoring period – a prospective mixed-method study - Stoffel, G.; Spirig, R.; Stiasny, B.; Bernet, V.; Dave, H.; Knirsch, W. (Journal of Clinical Nursing, 2017)
Aims and objectives: To investigate parents’ experiences, coping ability and quality of life while monitoring their sick child with hypoplastic left heart syndrome at home. Background: Interstage home monitoring for children with hypoplastic left heart syndrome reduces interstage mortality between Norwood stages I and II. Little is known about the psychosocial impact of interstage home monitoring. Design: Prospective mixed-method study. Methods: This study assessed the psychosocial impact on parents during interstage home monitoring. This contains for quantitative assessment the Short Form Health Survey questionnaire and the Impact of Family Scale administered one and five weeks following discharge before and after stage II. For qualitative assessment, semi-structured interviews focussing on the postdischarge coping strategies were conducted twice, five weeks after hospital discharge before and after stage II. Results: Ten infants (eight males) with hypoplastic left heart syndrome (n = 7) or other types of univentricular heart malformations (n = 3), and their parents (nine mother/father two-parent households, one single mother) were included. There were no interstage deaths. Mental Health Composite Summary scores were low in both parents (mothers: 40·45 ± 9·07; fathers: 40·58 ± 9·69) and lowest for the item ‘vitality’ (mothers: 37·0 ± 19·46; fathers: 43·12 ± 25·9) before and after stage II. Impact of Family Scale values showed higher daily and social burdens for mothers. ‘Becoming a family’ was the most important task as coping strategy to equilibrate the fragile emotional balance. The parents judged interstage home monitoring as a protective intervention. Conclusions: Although psychosocial burden before and after stage II remains high, becoming a family is an essential experience for parents and confirms their parenthood. Relevance to clinical practice: Healthcare professionals must be aware of parents’ needs during this vulnerable interstage period and to provide psychosocial and nursing support. © 2016 John Wiley & Sons Ltd
Keywords: family; hypoplastic left heart syndrome; infant; interstage monitoring; psychosocial impact; quality of life

Health-related quality of life in paediatric patients with congenital heart defects: association with the type of heart defect and the surgical technique - Heusch, A.; Kahl, H.J.; Hensel, K.O.; Calaminus, G. (Quality of Life Research, 2017)
Summary: The aim of the study was to investigate the impact of a number of surgical interventions for a various congenital cardiac defects (CHDs) on self-reported HRQoL. Methods: Patients who had received corrective surgery of several congenital heart defects (surgical VSD closure, Fallot, TGA after atrial or arterial switch or Fontan-type circulation for univentricular AV-connection) were interviewed in the office of their home peadiatric cardiologist. HRQoL in children along 7 dimensions was assessed using a standardised questionnaire (PEDQoL); information on the medical case history of each respondent was also collected. Statistics: HRQoL was assessed in the questionnaire by asking about the frequency (never, rarely, often, always) of specific negative experiences; more frequent experiences indicate a lower quality of life. Frequency expressions were transformed into numerical values (25, 50, 75, 100%), and mean values for HRQoL were calculated for each patient and for each domain. Differences in HRQoL among patients with different types of interventions were analysed using the Mann–Whitney Test or the Kruskal–Wallis Test as appropriate; p values <0.05 were considered to indicate significant differences, while p values <0.1 were considered to indicate notable trends. Results: Patients: 169 patients (60% male, 40% female) were part of the study. The mean age was 11.6 years; 50 patients had surgical VSD closure, 52 surgeries for Tetralogy of Fallot (22 transannular patch, 18 no transannular patch, 12 inaccurate description), 40 had complete transposition of the great arteries (28 atrial switch, 12 arterial switch), 22 had a Fontan-type procedure for univentricular AV-connection. HRQoL differed little among patients with different CHDs for the items “relation to friends,” “interactions in the affected families”, and “own body image”. For other items, notable differences emerged: patients with univentricular hearts rated their physical capacity worse and showed a tendency towards negative ratings in other domains. On the other hand, patients after Fallot or TGA correction tended to rate their HRQoL in several domains as relatively high. Focusing on the mode of surgery for Fallot repair, respectively, TGA correction the only significant difference was found for “physical capacity” in TGA (atrial vs. arterial repair). Mustard patients tended to rate most items worse. Physical capacity was rated worst by patients with a Fontan circulation. Repeated surgery led to lower ratings for all domains except “physical capacity” and “body image”. Conclusions: Different surgical techniques for CHD do not affect children’s and adolescents’ self-reported HRQoL to the extent that one would expect. This observation is in line with observations in groups of children with different chronic diseases. Specialised psychosocial support is necessary in order to maintain this positive self-evaluation and to ensure patients are able to lead autonomous personal and professional lives. © 2017, Springer International Publishing AG.
Keywords: Congenital heart defect; Heart surgery; Quality of life

Effect of Fontan geometry on exercise haemodynamics and its potential implications - Tang, E.; Wei, Z.; Whitehead, K.K.; Khiabani, R.H.; Restrepo, M.; Mirabella, L.; Bethel, J.; Paridon, S.M.; Marino, B.S.; Fogel, M.A.; Yoganathan, A.P. (Heart, 2017)
Objective Exercise intolerance afflicts Fontan patients with total cavopulmonary connections (TCPCs) causing a reduction in quality of life. Optimising TCPC design is hypothesised to have a beneficial effect on exercise capacity. This study investigates relationships between TCPC geometries and exercise haemodynamics and performance. Methods This study included 47 patients who completed metabolic exercise stress test with cardiac magnetic resonance (CMR). Phase-contrast CMR images were acquired immediately following supine lower limb exercise. Both anatomies and exercise vessel flow rates at ventilatory anaerobic threshold (VAT) were extracted. The vascular modelling toolkits were used to analyse TCPC geometries. Computational simulations were performed to quantify TCPC indexed power loss (iPL) at VAT. Results A highly significant inverse correlation was found between the TCPC diameter index, which factors in the narrowing of TCPC vessels, with iPL at VAT (r=0.723, p<0.001) but positive correlations with exercise performance variables, including minute oxygen consumption (VO 2) at VAT (r=0.373, p=0.01), VO 2 at peak exercise (r=0.485, p=0.001) and work at VAT/weight (r=0.368, p=0.01). iPL at VAT was negatively correlated with VO 2 at VAT (r=0.337, p=0.02), VO 2 at peak exercise (r=0.394, p=0.007) and work at VAT/weight (r=0.208, p=0.17). Conclusions Eliminating vessel narrowing in TCPCs and reducing elevated iPL at VAT could enhance exercise tolerance for patients with TCPCs. These findings could help plan surgical or catheter-based strategies to improve patients' exercise capacity. © Article author(s) (or their employer(s) unless otherwise stated in the text of the article) 2017. All rights reserved.
Keywords: congenital heart disease; Fontan procedure; exercise hemodynamics; computational fluid dynamics

Congenital heart disease - Puri, K.; Allen, H.D.; Qureshi, A.M. (Pediatrics in Review, 2017)
1. On the basis of clinical consensus and research observation, newborns with ductal-dependent congenital heart disease (CHD) may present with cyanosis or shock as the patent ductus arteriosus starts to close, indicating a need for prostaglandin to maintain output to the pulmonary or systemic circulation. (5)(7)(8) 2. On the basis of research evidence, as well as clinical consensus, children with acyanotic shunting lesions can present with features of congestive heart failure and require nutritional and diuretic optimization until the time of early surgical correction. (1)(2)(9) 3. On the basis of research evidence, as well as clinical consensus, children with cyanotic heart disease may undergo early corrective surgery or, in some instances, undergo palliation with a shunt (modified Blalock-Taussig-Thomas shunt) to supply pulmonary blood flow prior to their corrective surgery. (22)(32) 4. On the basis of strong clinical evidence, children who undergo single-ventricle palliation are at risk for developing complications at any stage of the palliation. (31) 5. On the basis of clinical evidence, as well as clinical consensus, although most children with corrected CHD have a normal quality of life, lifelong cardiology follow-up is needed for all of these patients to monitor the development of any long-term complications and/or sequelae. (13)(14)(20)(24)(27)(30)(39). © 2017 by the American Academy of Pediatrics. All rights reserved.

Parenting a child at home with hypoplastic left heart syndrome: Experiences of commitment, of stress, and of love - Cantwell-Bartl, A.M.; Tibballs, J. (Cardiology in the Young, 2017)
Objective To evaluate the experiences of parenting a child with hypoplastic left heart syndrome after the child has been discharged home from hospital. Design A study of the parents' experiences using face-to-face interviews and psychometric measures with parents whose child had survived stage surgery. Setting Parents were interviewed within the home environment or within the hospital if that was their choice. Subjects A total of 29 parents (16 mothers and 13 fathers) of surviving children. Intervention A semi-structured face-to-face interview plus psychometric tests (parent demographics, Maslach Burnout Inventory, Impact on Family Scale, and the Psychological Check List-Civilian). Measurements and main results The parents' experience in supporting a child with hypoplastic left heart syndrome is one of stress, of commitment, and of love. Although parents experienced joy in their child, they were also subjected to anxiety with four parents test positive to post-traumatic stress disorder and hypervigilance while monitoring their child's condition. Parents lived with many difficulties, and demands. © 2017 Cambridge University Press.
Keywords: adaptation; grief; Hypoplastic left heart syndrome; parents; stress

Impact of the location of the fenestration on Fontan circulation haemodynamics: A three-dimensional, computational model study - Sughimoto, K.; Asakura, Y.; Brizard, C.P.; Liang, F.; Fujiwara, T.; Miyaji, K.; Liu, H. (Cardiology in the Young, 2017)
Objectives There is no consensus or theoretical explanation regarding the optimal location for the fenestration during the Fontan operation. We investigated the impact of the location of the fenestration on Fontan haemodynamics using a three-dimensional Fontan model in various physiological conditions. Methods A three-dimensional Fontan model was constructed on the basis of CT images, and a 4-mm-diameter fenestration was located between the extracardiac Fontan conduit and the right atrium at three positions: Superior, middle, and inferior part of the conduit. Haemodynamics in the Fontan route were analysed using a three-dimensional computational fluid dynamic model in realistic physiological conditions, which were predicted using a lumped parameter model of the cardiovascular system. The respiratory effect of the caval flow was taken into account. The flow rate through the fenestration, the effect of lowering the central venous pressure, and wall shear stress in the Fontan circuit were evaluated under central venous pressures of 10, 15, and 20 mmHg. The pulse power index and pulsatile energy loss index were calculated as energy loss indices. Results Under all central venous pressures, the middle-part fenestration demonstrated the most significant effect on enhancing the flow rate through the fenestration while lowering the central venous pressure. The middle-part fenestration produced the highest time-averaged wall shear stress, pressure pulse index, and pulsatile energy loss index. Conclusions Despite slightly elevated energy loss, the middle-part fenestration most significantly increased cardiac output and lowered central venous pressure under respiration in the Fontan circulation. © 2017 Cambridge University Press.
Keywords: computer fluid dynamics; fenestration; Fontan; haemodynamics

Exercise Capacity and Self-Efficacy are Associated with Moderate-to-Vigorous Intensity Physical Activity in Children with Congenital Heart Disease - Banks, L.; Rosenthal, S.; Manlhiot, C.; Fan, C.-P.S.; McKillop, A.; Longmuir, P.E.; McCrindle, B.W. (Pediatric Cardiology, 2017)
This study sought to determine whether exercise capacity, self-efficacy, and gross motor skills are associated with moderate-to-vigorous physical activity (MVPA) levels in children, and if these associations differ by congenital heart disease (CHD) type. Medical history was abstracted from chart review. We assessed MVPA levels (via accelerometry), percent-predicted peak oxygen consumption (VO2; cardiopulmonary exercise test), gross motor skill percentiles (test of gross motor development version-2), and self-efficacy [children’s self-perceptions of adequacy and predilection for physical activity scale (CSAPPA scale)]. CHD patients (n = 137, range 4–12 years) included children with a repaired atrial septal defect (n = 31, mean ± standard deviation MVPA = 454 ± 246 min/week), transposition of the great arteries after the arterial switch operation (n = 34, MVPA = 423 ± 196 min/week), tetralogy of Fallot after primary repair (n = 37, MVPA = 389 ± 211 min/week), or single ventricle after the Fontan procedure (n = 35, MVPA = 405 ± 256 min/week). MVPA did not differ significantly between CHD groups (p = 0.68). Higher MVPA was associated with a higher percent-predicted VO2 (EST[95% CI] = 16.9[−0.2, 34] MVPA min/week per 10% increase in percent-predicted VO2,p = 0.05) and higher self-efficacy (EST[95% CI] = 5.2[1.0, 9.3] MVPA min/week per 1-unit increase in CSAPPA score, p = 0.02), after adjustment for age, sex, and testing seasonality, with no association with CHD type. Higher MVPA was not associated with gross motor skill percentile (p = 0.92). There were no significant interactions between CHD type and percent-predicted VO2, self-efficacy scores, and gross motor skill percentiles regarding their association with MVPA (p > 0.05 for all). Greater MVPA was associated with higher exercise capacity and self-efficacy, but not gross motor skills. © 2017, Springer Science+Business Media New York.
Keywords: Accelerometry; Gross motor skill development; Peak oxygen consumption; Self-efficacy

Pediatric cardiac transplantation - Ryan, T.D.; Chin, C. (Seminars in Pediatric Surgery, 2017)
Heart transplantation in pediatric patients generally arises as a treatment option of last resort, that is, the indication is for patients with heart failure of various etiologies, with potential or actual end-organ dysfunction, in whom there are no reasonable, long-term options for life-prolonging therapy. The concept of heart failure is complex in a pediatric population, particularly those with congenital heart disease. While heart failure may refer simply to systolic dysfunction leading to low cardiac output, it can also encompass: diastolic dysfunction in restrictive cardiomyopathy; single ventricle physiology without an option for stable palliation. A good candidate should have a predicted life expectancy less than the median lifetime of a transplanted heart. Significant improvement in survival has been observed over time with 1- and 5-year survival approximately 90% and 80% in the contemporary era. © 2017
Keywords: Heart; Pediatric; Transplantation

Plasma microvesicle analysis identifies microRNA 129-5p as a biomarker of heart failure in univentricular heart disease - Ramachandran, S.; Lowenthal, A.; Ritner, C.; Lowenthal, S.; Bernstein, H.S. (PLoS ONE, 2017)
Biomarkers of heart failure in adults have been extensively studied. However, biomarkers to monitor the progression of heart failure in children with univentricular physiology are less well understood. We proposed that as mediators of diverse pathophysiology, miRNAs contained within circulating microvesicles could serve as biomarkers for the presence and progression of heart failure in univentricular patients. To test this, we studied the association of heart failure with elevations in specific miRNAs isolated from circulating microvesicles in a cohort of children with univentricular heart disease and heart failure. We conducted a single site cross-sectional observational study of 71 children aged 1 month-7 years with univentricular heart disease and heart failure. We demonstrated that levels of miR129-5p isolated from plasma microvesicles were inversely related to the degree of clinical heart failure as assessed by Ross score. We then showed that miR129-5p levels are downregulated in HL1 cells and human embryonic stem cell-derived cardiomyocytes exposed to oxidative stress. We demonstrated that bone morphogenetic protein receptor 2, which has been implicated in the development of pulmonary vascular disease, is a target of miR129-5p, and conversely regulated in response to oxidative stress in cell culture. Levels of miR129-5p were inversely related to the degree of clinical heart failure in patients with univentricular heart disease. This study demonstrates that miR129-5p is a sensitive and specific biomarker for heart failure in univentricular heart disease independent of ventricular morphology or stage of palliation. Further study is warranted to understand the targets affected by miR129-5p with the development of heart failure in patients with univentricular physiology. © 2017 Ramachandran et al. This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Inspiratory muscle training is associated with improved inspiratory muscle strength, resting cardiac output, and the ventilatory efficiency of exercise in patients with a fontan circulation - Laohachai, K.; Winlaw, D.; Selvadurai, H.; Gnanappa, G.K.; d'Udekem, Y.; Celermajer, D.; Ayer, J. (Journal of the American Heart Association, 2017)
Background-Patients with a Fontan circulation have reduced exercise capacity and respiratory muscle strength. Inspiratory muscle training (IMT) improves exercise capacity and quality of life in adults with heart failure. We assessed whether 6 weeks of a home-based program of IMT improves inspiratory muscle strength and the ventilatory efficiency of exercise in adolescent patients with a Fontan circulation. Methods and Results-Twenty-three adolescent participants (aged 16±2 years) with a Fontan circulation underwent 6 weeks of IMT for 30 minutes daily. Respiratory muscle strength (maximal inspiratory pressure and expiratory pressure), lung function, and exercise capacity (cardiopulmonary exercise testing) were assessed. Fourteen of 23 participants also underwent exercise cardiac magnetic resonance imaging to examine the effects of IMT on cardiac output and systemic and pulmonary blood flow. Six weeks of IMT improved maximal inspiratory pressure by 36±24 cm H2O (61±46%) with no change in maximal expiratory pressure. Ventilatory efficiency of exercise improved after 6 weeks of IMT (from 34.2±7.8 to 32.2±5.6, P=0.04). In those who underwent exercise cardiac magnetic resonance imaging, IMT increased resting cardiac output (from 4.2±1.2 to 4.5±1.0 L/min, P=0.03) and ejection fraction (from 50.1±4.3 to 52.8±6.1%, P=0.03). Conclusions-Six weeks of IMT is associated with improved inspiratory muscle strength, ventilatory efficiency of exercise, and resting cardiac output in young Fontan patients. IMT may be a simple beneficial addition to the current management of Fontan patients, potentially reducing exercise intolerance and long-term morbidity and mortality. © 2017 The Authors and Medtronic.
Keywords: Exercise; Exercise capacity; Fontan procedure; Inspiratory muscle strength

An antenatal marker of neurodevelopmental outcomes in infants with congenital heart disease - Siddiqui, S.; Fifer, W.P.; Ordonez-Retamar, M.; Nugent, J.D.; Williams, I.A. (Journal of Perinatology, 2017)
Objective: Prenatal exposures are known to alter fetal neurodevelopment and autonomic control. We aimed to explore the correlation between fetal autonomic activity, measured by fetal heart rate variability, and 18-month developmental outcome in subjects with congenital heart disease. Study design: From 2010 to 2013, 5 fetuses with hypoplastic left heart syndrome, 9 with transposition of the great arteries and 9 with tetralogy of Fallot were included in this prospective cohort study. A maternal abdominal fetal electrocardiogram monitor recorded fetal heart rate at 34 to 38 weeks gestational age. We assessed associations between fetal heart rate parameters including interquartile range and s.d. of the fetal RR intervals and 18-month Bayley Scales of Infant Development-III scores using Pearson's correlation coefficient. Multivariable regression modeling identified predictors of neurodevelopmental scores. Results: Fetal heart rate variability parameters at 34 to 38 weeks gestational age correlated with 18-month Cognition (r=0.47, P=0.03) and Motor scores (r=0.66, P=0.001). The interquartile range of the fetal RR intervals predicted Cognition (β=0.462, P=0.028, R 2 =0.282) and Motor (β=0.637, P<0.001, R 2 =0.542) scores. Conclusions: In fetuses with congenital heart disease, low heart rate variability at 34 to 38 weeks gestational age predicts diminished 18-month Cognitive and Motor performance. Prenatal autonomic activity may serve as a marker of early childhood development in these high-risk patients. © 2017 Nature America, Inc., part of Springer Nature. All rights reserved.

The Ethics of Treatment for Hypoplastic Left Heart Syndrome (HLHS) - Spike, J.P. (American Journal of Bioethics, 2017)

Parents’ perceptions during the transition to home for their child with a congenital heart defect: How can we support families of children with hypoplastic left heart syndrome? - March, S. (Journal for Specialists in Pediatric Nursing, 2017)
Purpose: The aim of the study was to explore the literature related to transitions in healthcare between the hospital and home that caregivers experience with a child who has a congenital heart defect (CHD), specifically related to hypoplastic left heart syndrome (HLHS). Design and Methods: A systematic literature review was conducted searching OVID Medline, CINAHL, and PubMed to discover the caregivers’ perceptions on their transitions between hospital care and home care of their child with a CHD. Articles included those with focus on the transitions of caregivers between hospital and home care for children with CHD. Excluded articles were studies focused on adolescents, transition to adult healthcare, mortality results, other diseases associated with CHDs, comparison of CHD treatments, feasibility studies, differences in care between hospitals, home monitoring, and comparison of videoconference and telephone home communication. Results: Ten articles were selected. Many parents voiced their concerns with feeding their child, learning medical skills and knowledge, reported a disrupted relationship between parents and their child, and identified stress and anxiety associated with taking care of a child with a CHD. Practice Implications: There were limited studies on caregivers’ transitions with a child with HLHS, but there also was limited focus on the caregivers’ experiences with transitions between hospital and home care for their child with any CHD. Research on the transition experience between hospital care and home care for caregivers of children born with a CHD, and a specific focus on HLHS from the caregivers’ viewpoint, would provide insight into the perspective of caregivers during the numerous transitions. © 2017 Wiley Periodicals, Inc.
Keywords: caregiver; congenital heart; discharge; home care; hospital care; hypoplastic left heart syndrome; parents; transition

Building a comprehensive team for the longitudinal care of single ventricle heart defects: Building blocks and initial results - Texter, K.; Davis, J.A.M.; Phelps, C.; Cheatham, S.; Cheatham, J.; Galantowicz, M.; Feltes, T.F. (Congenital Heart Disease, 2017)
Introduction: With increasing survival of children with HLHS and other single ventricle lesions, the complexity of medical care for these patients is substantial. Establishing and adhering to best practice models may improve outcome, but requires careful coordination and monitoring. Methods: In 2013 our Heart Center began a process to build a comprehensive Single Ventricle Team designed to target these difficult issues. Results: Comprehensive Single Ventricle Team in 2014 was begun, to standardize care for children with single ventricle heart defects from diagnosis to adulthood within our institution. The team is a multidisciplinary group of providers committed to improving outcomes and quality of life for children with single ventricle heart defects, all functioning within the medical home of our heart center. Standards of care were developed and implemented in five target areas to standardize medical management and patient and family support. Under the team 100 patients have been cared for. Since 2014 a decrease in interstage mortality for HLHS were seen. Using a team approach and the tools of Quality Improvement they have been successful in reaching high protocol compliance for each of these areas. Conclusions: This article describes the process of building a successful Single Ventricle team, our initial results, and lessons learned. Additional study is ongoing to demonstrate the effects of these interventions on patient outcomes. © 2017 Wiley Periodicals, Inc.
Keywords: care coordination; hypoplastic left heart; quality improvement

Cognitive dysfunction in adult CHD with different structural complexity - Tyagi, M.; Fteropoulli, T.; Hurt, C.S.; Hirani, S.P.; Rixon, L.; Davies, A.; Picaut, N.; Kennedy, F.; Deanfield, J.; Cullen, S.; Newman, S.P. (Cardiology in the Young, 2017)
Objective We carried out a cross-sectional study to assess cognitive function in a sample of adult CHD patients, within the Functioning in Adult Congenital Heart Disease study London. The association between cognitive functioning and disease complexity was examined. Methods A total of 310 patients participated in this study. Patients were classified into four structural complexity groups - tetralogy of Fallot, transposition of the great arteries, single ventricle, and simple conditions. Each patient underwent neuropsychological assessment to evaluate cognitive function, including memory and executive function, and completed questionnaires to assess depression and anxiety. Results Among all, 41% of the sample showed impaired performance (>1.5 SD below the normative mean) on at least three tests of cognitive function compared with established normative data. This was higher than the 8% that was expected in a normal population. The sample exhibited significant deficits in divided attention, motor function, and executive functioning. There was a significant group difference in divided attention (F=5.01, p=0.002) and the mean total composite score (F=5.19, p=0.002) between different structural complexity groups, with the simple group displaying better cognitive function. Conclusion The results indicate that many adult CHD patients display impaired cognitive function relative to a healthy population, which differs in relation to disease complexity. These findings may have implications for clinical decision making in this group of patients during childhood. Possible mechanisms underlying these deficits and how they may be reduced or prevented are discussed; however, further work is needed to draw conclusive judgements. © Cambridge University Press 2016.
Keywords: Adult CHD; cognition; mood; neuropsychological assessment

Comparison of self-expandable and balloon-expanding stents for hybrid ductal stenting in hypoplastic left heart complex - Goreczny, S.; Qureshi, S.A.; Rosenthal, E.; Krasemann, T.; Nassar, M.S.; Anderson, D.R.; Morgan, G.J. (Cardiology in the Young, 2017)
Objectives We aimed to compare the procedural and mid-term performance of a specifically designed self-expanding stent with balloon-expandable stents in patients undergoing hybrid palliation for hypoplastic left heart syndrome and its variants. Background The lack of specifically designed stents has led to off-label use of coronary, biliary, or peripheral stents in the neonatal ductus arteriosus. Recently, a self-expanding stent, specifically designed for use in hypoplastic left heart syndrome, has become available. Methods We carried out a retrospective cohort comparison of 69 neonates who underwent hybrid ductal stenting with balloon-expandable and self-expanding stents from December, 2005 to July, 2014. Results In total, 43 balloon-expandable stents were implanted in 41 neonates and more recently 47 self-expanding stents in 28 neonates. In the balloon-expandable stents group, stent-related complications occurred in nine patients (22%), compared with one patient in the self-expanding stent group (4%). During follow-up, percutaneous re-intervention related to the ductal stent was performed in five patients (17%) in the balloon-expandable stent group and seven patients (28%) in self-expanding stents group. Conclusions Hybrid ductal stenting with self-expanding stents produced favourable results when compared with the results obtained with balloon-expandable stents. Immediate additional interventions and follow-up re-interventions were similar in both groups with complications more common in those with balloon-expandable stents. © Cambridge University Press 2016.
Keywords: ductal stenting; hybrid procedure; Hypoplastic left heart syndrome

Rates of autism and potential risk factors in children with congenital heart defects - Bean Jaworski, J.L.; Flynn, T.; Burnham, N.; Chittams, J.L.; Sammarco, T.; Gerdes, M.; Bernbaum, J.C.; Clancy, R.R.; Solot, C.B.; Zackai, E.H.; McDonald-McGinn, D.M.; Gaynor, J.W. (Congenital Heart Disease, 2017)
Objective: Atypical development, behavioral difficulties, and academic underachievement are common morbidities in children with a history of congenital heart defects and impact quality of life. Language and social-cognitive deficits have been described, which are associated with autism spectrum disorders. The current study aimed to assess the rates of autism spectrum disorders in a large sample of children with a history of congenital heart defects and to assess medical, behavioral, and individual factors that may be associated with the risk of autism spectrum disorders. Design: Participants included 195 children with a history of congenital heart defects, who are followed in a large-scale longitudinal study. Measures included behavioral data from 4-year-old neurodevelopmental evaluations and parent-report data from a later annual follow-up. Results: Using established cutoffs on an autism spectrum disorder screener, children with congenital heart defects showed higher rates of “possible” autism spectrum disorders than national rates, (Chi-square Test of Equal Proportions), all Ps <.05. A stepwise variable selection method was used to create a “best prediction model” and multivariable logistic regression was used to identify variables predicting diagnostic status. Factors associated with diagnostic risk included medical (delayed sternal closure, prematurity, positive genetic findings), behavioral (cognitive, language, attention issues), and individual (socioeconomic, cultural/racial) variables. ROC analyses identified a cutoff of 7 to maximize sensitivity/specificity based on parent-reported diagnosis. Conclusions: Risk of autism spectrum disorder screening status in children with congenital heart defects was higher than expected from population rates. Findings highlight the need for referral to a specialist to assess the presence and severity of social-communication issues and congenital heart defects population-specific screening thresholds for children with concern for autism spectrum disorders. © 2017 Wiley Periodicals, Inc.
Keywords: APOE genotype; autism; serious congenital heart defects

Longitudinal Outcomes of Patients With Single Ventricle After the Fontan Procedure - Atz, A.M.; Zak, V.; Mahony, L.; Uzark, K.; D'agincourt, N.; Goldberg, D.J.; Williams, R.V.; Breitbart, R.E.; Colan, S.D.; Burns, K.M.; Margossian, R.; Henderson, H.T.; et al. (Journal of the American College of Cardiology, 2017)
Background Multicenter longitudinal objective data for survival into adulthood of patients who have undergone Fontan procedures are lacking. Objectives This study sought to describe transplant-free survival and explore relationships between laboratory measures of ventricular performance and functional status over time. Methods Exercise testing, echocardiography, B-type natriuretic peptide, functional health assessment, and medical history abstraction were repeated 9.4 ± 0.4 years after the Fontan Cross-Sectional Study (Fontan 1) and compared with previous values. Cox regression analysis explored risk factors for interim death or cardiac transplantation. Results From the original cohort of 546 subjects, 466 were contacted again, and 373 (80%) were enrolled at 21.2 ± 3.5 years of age. Among subjects with paired testing, the percent predicted maximum oxygen uptake decreased (69 ± 14% vs. 61 ± 16%; p < 0.001; n = 95), ejection fraction decreased (58 ± 11% vs. 55 ± 10%; p < 0.001; n = 259), and B-type natriuretic peptide increased (median [interquartile range] 13 [7 to 25] pg/mol vs. 18 [9 to 36] pg/mol; p < 0.001; n = 340). At latest follow-up, a lower Pediatric Quality of Life Inventory physical summary score was associated with poorer exercise performance (R2 adjusted = 0.20; p < 0.001; n = 274). Cumulative complications since the Fontan procedure included additional cardiac surgery (32%), catheter intervention (62%), arrhythmia treatment (32%), thrombosis (12%), and protein-losing enteropathy (8%). Since Fontan 1, 54 subjects (10%) have received a heart transplant (n = 23) or died without transplantation (n = 31). The interval risk of death or/cardiac transplantation was associated with poorer ventricular performance and functional health status assessed at Fontan 1, but it was not associated with ventricular morphology, the subject's age, or the type of Fontan connection. Conclusions Interim transplant-free survival over 12 years in this Fontan cohort was 90% and was independent of ventricular morphology. Exercise performance decreased and was associated with worse functional health status. Future interventions might focus on preserving exercise capacity. (Relationship Between Functional Health Status and Ventricular Performance After Fontan—Pediatric Heart Network; NCT00132782) © 2017 American College of Cardiology Foundation
Keywords: adult congenital heart disease; exercise; Fontan procedure; functional health status; single ventricle

Strategies to Prevent Cast Formation in Patients with Plastic Bronchitis Undergoing Heart Transplantation - Parent, J.J.; Darragh, R.K.; Gossett, J.G.; Ryan, T.D.; Villa, C.R.; Lorts, A.; Jefferies, J.L.; Towbin, J.A.; Chin, C. (Pediatric Cardiology, 2017)
Plastic bronchitis, a rare complication after Fontan palliation, carries a high morbidity and mortality risk. Heart transplantation is an effective treatment option, but casts may occur in the early post-operative period. We present a case series detailing peri-operative management strategies to minimize morbidity and mortality related to plastic bronchitis in patients undergoing heart transplantation. Patient 1 received no treatment pre-, intra-, or post-transplant for prevention of bronchial casts and developed severe respiratory acidosis 18 h following transplant. Emergent bronchoscopy was performed and a large obstructive cast was removed. The patient recovered and received inhaled tissue plasminogen activator (tPA) for 5 days. Patient 2 received inhaled tPA before, during, and for 5 days after transplantation and no bronchial casts developed. Patient 3 underwent intraoperative bronchoscopy just prior to implantation revealing no casts. The patient underwent non-urgent, preemptive bronchoscopy on post-transplant days 1, 3, and 4, removing several partially obstructive bronchial blood clots/casts, with no casts thereafter. Heart transplantation results in eventual resolution of plastic bronchitis. Residual bronchial casts can still be problematic in the peri-operative period. Airway clearance with inhaled tPA or bronchoscopy may prevent the need for prolonged mechanical ventilation and reduce post-operative morbidity in this unique population. © 2017, Springer Science+Business Media New York.
Keywords: Fontan; Pediatric heart transplantation; Plastic bronchitis; Single ventricle

Functional Status and Quality of Life in Survivors of Extracorporeal Membrane Oxygenation After the Norwood Operation - Friedland-Little, J.M.; Uzark, K.; Yu, S.; Lowery, R.; Aiyagari, R.; Hirsch-Romano, J.C. (Annals of Thoracic Surgery, 2017)
Background Infants who require extracorporeal membrane oxygenation (ECMO) support after a Norwood operation are at increased risk for early and late death compared with patients who do not require ECMO post-Norwood. Little is known about the effect that ECMO post-Norwood has on functional status and quality of life among long-term survivors. Methods We prospectively evaluated functional status and health-related quality of life in 12 surviving patients (cases) and 19 corresponding patients (controls) from a previous retrospective case-control assessment of long-term survival in patients requiring ECMO post-Norwood. Functional status was assessed with the Vineland Adaptive Behavior Scale-II, and health-related quality of life was assessed with the Pediatric Quality of Life Inventory (PedsQL) core and cardiac modules. Results There were no differences in demographics, extracardiac or genetic anomalies, or age at follow-up assessment between ECMO cases and non-ECMO controls. The Vineland Adaptive Behavior Scale-II scores were comparable between groups, with both groups demonstrating function in the normal range in all four domains tested. The only difference in PedsQL scores between cases and controls was perceived physical appearance, which was lower among ECMO survivors by both patient and proxy report. PedsQL scores of both groups were comparable to published scores for patients with single-ventricle congenital heart disease but generally lower than scores for the healthy population. Conclusions The requirement for ECMO support after a Norwood operation does not appear to significantly affect functional status or quality of life among the subset of patients who achieve long-term survival. © 2017 The Society of Thoracic Surgeons

The multidisciplinary fetal center: clinical expertise is only part of the experience - Kett, J.C.; Wolfe, E.; Vernon, M.M.; Woodrum, D.; Diekema, D. (Acta Paediatrica, International Journal of Paediatrics, 2017)
Aim: Multidisciplinary foetal centres have recently emerged in partnership with children's hospitals throughout the United States. The aim of this investigation was to describe the patient experience of pregnant women who were referred to our foetal centres for the evaluation of foetal congenital anomalies. Methods: A qualitative interview study of women referred to our foetal centres was conducted using semi-structured telephone interviews. The data were coded and analysed using thematic networks analysis. Results: Six themes were identified (i) foetal centre evaluations had a far-reaching impact on participants’ lives, (ii) participants appreciated both expertise and support from providers, (iii) participants recognised the need to cope with uncertainty, (iv) participants sought additional support from multiple arenas, (v) participants specifically looked to the Internet for both information and support and (vi) participants had pre-established views about pregnancy termination. Conclusion: Multidisciplinary foetal centres can provide a unified source of clinical expertise to women who are carrying a foetus with a suspected or identified congenital anomaly. Despite this diagnostic acumen, uncertainty is pervasive and patients seek support and additional information from a variety of other sources. This investigation is an important initial step in the evaluation of this emerging model of care. ©2017 Foundation Acta Pædiatrica. Published by John Wiley & Sons Ltd
Keywords: Congenital anomalies; Foetal care centre; Foetal centre; Patient experience; Prenatal counselling

Feasibility of exercise stress echocardiography and myocardial response in patients with repaired congenital heart disease - Hasan, B.S.; Lunze, F.I.; Alvi, N.; Shafer, K.M.; Rhodes, J. (American Heart Journal, 2017)
Background Exercise stress echocardiography (ESE) can unmask ventricular dysfunction in asymptomatic patients with congenital heart disease (CHD), but its acquisition and interpretation is often challenging, and the method has not been validated in CHD. This study aimed to evaluate the feasibility of ESE using Doppler imaging and to assess myocardial response to exercise in patients with biventricular (BiV) and univentricular (UniV) circulation after CHD repair. Methods In this single-center prospective study, we recruited 55 participants (17 females), median age 14 years (8-22 years). Our analysis categorized participants in these three groups: with structurally normal hearts as controls (n = 21), with BiV circulation (n = 20) and with UniV circulation (n = 14). We acquired ESE images of the systemic ventricle including pulsed-wave flow and spectral tissue Doppler imaging (TDI) of lateral free wall before and immediately after standard, symptom-limited exercise tests on an electronically braked cycle ergometer. Results During ESE we obtained inflow E-wave and TDI systolic (S′) and early diastolic (E′) velocities in 93% to 100% of participants at rest and in 90% to 100% of participants post exercise. Feasibility to obtain Doppler imaging parameter was the same across study groups. The myocardial response to exercise was increase in heart rate (HR), S′ and inflow E-wave velocity in all participants. Patients with BiV circulation had preserved ventricular function at rest. While patients with UniV circulation had low S′, E′, and E-wave velocities at rest in comparison to controls and to BiV group (all P < .001), both patients with BiV and UniV circulation showed significant increases in HR, S′ velocity and inflow E-wave velocity post exercise, with magnitudes of these increases higher in controls than in the BiV and UniV group. The S′ and E′ velocities were strongly associated with lower percent predicted peak oxygen consumption VO2 (rs = 0.614 and rs = 0.64, respectively, both P < .001). Conclusion ESE with Doppler imaging is a practical noninvasive diagnostic method and sufficiently robust for the assessment of morphologic LV/systemic ventricles under exercise in patients after biventricular and univentricular CHD repair. Although patients with BiV and UniV circulation had both preserved myocardial response to exercise, the magnitude of this response was the lowest in patients with UniV circulation. © 2017 Elsevier Inc.

Adolescent and parent perspectives prior to involvement in a Fontan transition program - Du Plessis, K.; Culnane, E.; Peters, R.; D'Udekem, Y. (International Journal of Adolescent Medicine and Health, 2017)
Successful transition to adult healthcare is particularly important for congenital heart disease (CHD) patients who have undergone palliative surgery, as they risk adverse events if not followed closely. This study examines young people at the worst end of the CHD spectrum who are born with a single ventricle (pumping heart chamber), and who undergo a series of operations that culminate in the Fontan surgical procedure. To explore adolescents with a Fontan circulation, and their parents', readiness for transition to adult care and pre-implementation of a transition program. Seventeen adolescents (15-18 years) and 15 of their parents completed questionnaires at the start of their first transition clinic. Adolescents reported poor knowledge about their Fontan circulation, and 41% had a poor understanding of the purpose of their medications/treatments. Over half of the adolescents had poor knowledge around medical help-seeking (when, who, how). Most reported feeling comfortable with discussing their medical issues with their cardiologist, but considerably less so about sensitive adolescent issues, in particular, emotional wellbeing. Parents reported high levels of anxiety around transition to adult care services. Findings pre-program indicate poor adolescent health knowledge, a lack of focus in health services on emotional wellbeing and high parental anxiety. These findings highlight the need for dedicated programs that focus on early preparation, parental involvement and acknowledgment, transition as a process, strong integration and prioritisation in the health system with a youth-friendly and holistic focus, in particular, around emotional wellbeing. © 2017 2017 Walter de Gruyter GmbH, Berlin/Boston.
Article in Press
Keywords: Fontan circulation; transition from paediatric to adult care; transition support programs

Neurodevelopmental Outcome in Children after Fetal Cardiac Intervention for Aortic Stenosis with Evolving Hypoplastic Left Heart Syndrome - Laraja, K.; Sadhwani, A.; Tworetzky, W.; Marshall, A.C.; Gauvreau, K.; Freud, L.; Hass, C.; Dunbar-Masterson, C.; Ware, J.; Lafranchi, T.; Wilkins-Haug, L.; Newburger, J.W. (Journal of Pediatrics, 2017)
Objective To characterize neurodevelopmental outcomes after fetal aortic valvuloplasty for evolving hypoplastic left heart syndrome and determine the risk factors for adverse neurodevelopment. Study design Questionnaires were mailed to families of children who underwent fetal aortic valvuloplasty from 2000 to 2012, and medical records were reviewed retrospectively. The primary outcome was the General Adaptive Composite score of the Adaptive Behavior Assessment System Questionnaire-Second Edition. Other questionnaires included the Behavior Assessment System for Children, Behavior Rating Inventory of Executive Function, Ages and Stages, and Pediatric Quality of Life Inventory. Results Among 69 eligible subjects, 52 (75%) completed questionnaires at median age of 5.5 (range 1.3-12) years; 30 (58%) had biventricular status circulation. The General Adaptive Composite mean score (92±17) was lower than population norms (P<.001) and similar to published reports in patients with hypoplastic left heart syndrome without fetal intervention; scores in the single ventricular versus biventricular group were 97±19 vs 89±14, respectively (P=.10). On multivariable analysis, independent predictors of a lower General Adaptive Composite score were total hospital duration of stay in the first year of life (P=.001) and, when forced into the model, biventricular status (P=.02). For all other neurodevelopmental questionnaires (Behavior Assessment System for Children, Behavior Rating Inventory of Executive Function, Ages and Stages, Pediatric Quality of Life Inventory), most subscale scores for patients with biventricular and single ventricular status were similar. Conclusion Children who underwent fetal aortic valvuloplasty have neurodevelopmental delay, similar to patients with hypoplastic left heart syndrome without fetal intervention. Achievement of biventricular circulation was not associated with better outcomes. We infer that innate patient factors and morbidity during infancy have the greatest effect on neurodevelopmental outcomes. © 2017 Elsevier Inc.
Keywords: child development; congenital heart disease; fetal cardiac intervention; neurodevelopmental outcomes

Correlates of posttraumatic stress disorder in adults with congenital heart disease - Eslami, B. (Congenital Heart Disease, 2017)
Objective: The aims of this study were to compare the level of posttraumatic stress disorder between adults with and without congenital heart disease, and to examine the correlates of posttraumatic stress disorder (e.g., sociodemographics). Design: Cross-sectional. Setting: Two university-affiliated heart hospitals in Tehran, Iran. Patients: A sample of 347 adults with congenital heart disease aged 18–64 years (52% women), and 353 adults without congenital heart disease matched by sex and age (±2 years) was recruited. Outcome Measures: The PTSD Scale: Self-report version was used to assess the diagnosis and severity of posttraumatic stress disorder. Hierarchical multivariate logistic regression analyses were performed to explore correlates of likely posttraumatic stress disorder diagnosis among each group of participants. Results: The posttraumatic stress disorder in the patients was comparable to those of the control group, except for increased arousal (P =.027) which was scored higher among the patients. Over 52% of adults with congenital heart disease met the criteria for a likely posttraumatic stress disorder diagnosis compared with 48% of adults without congenital heart disease. The regression analyses among patients revealed that elevated depressive symptoms (OR = 1.27) and a positive history of cardiac surgery (OR = 2.02) were significantly associated with posttraumatic stress disorder. The model could explain 29% of the variance in posttraumatic stress disorder. Conclusions: The high and comparable prevalence of posttraumatic stress disorder among patients and nonpatients highlight the significance of the context in which adults with congenital heart disease may face other/additional stressors than disease-related ones, an issue that clinicians need also take into account. Furthermore, the association of posttraumatic stress disorder with elevated depressive symptoms warrant a comprehensive psychological assessment and management of adults with congenital heart disease, in particular among those with a history of invasive procedures. © 2017 Wiley Periodicals, Inc.
Keywords: cardiac surgery; depression; developing country; grown up with CHD; mental health

Structural cerebral abnormalities and neurodevelopmental status in single ventricle congenital heart disease before Fontan procedure - Knirsch, W.; Mayera, K.N.; Scheer, I.; Tuura, R.; Schranz, D.; Hahn, A.; Wetterling, K.; Beck, I.; Latal, B.; Reich, B. (European Journal of Cardio-thoracic Surgery, 2017)
OBJECTIVES: Neonates with single ventricle congenital heart disease are at risk for structural cerebral abnormalities. Little is known about the further evolution of cerebral abnormalities until Fontan procedure. METHODS: Between August 2012 and July 2015, we conducted a prospective cross-sectional two centre study using cerebral magnetic resonance imaging (MRI) and neuro-developmental outcome assessed by the Bayley-III. Forty-seven children (31 male) were evaluated at a mean age of 25.9 ± 3.4 months with hypoplastic left heart syndrome (25) or other single ventricle (22). RESULTS: Cerebral MRI was abnormal in 17 patients (36.2%) including liquor space enlargements (10), small grey (9) and minimal white (5) matter injuries. Eight of 17 individuals had combined lesions. Median (range) cognitive composite score (CCS) (100, 65-120) and motor composite score (MCS) (97, 55-124) were comparable to the reference data, while language composite score (LCS) (97, 68-124) was significantly lower (P = 0.040). Liquor space enlargement was associated with poorer performance on all Bayley-III subscores (CCS: P = 0.02; LCS: P = 0.002; MCS: P = 0.013). The number of re-operations [odds ratio (OR) 2.2, 95% confidence interval (CI) 1.1-4.3] (P = 0.03) and reinterventions (OR 2.1, 95% CI 1.1-3.8) (P = 0.03) was associated with a higher rate of overall MRI abnormalities. CONCLUSIONS: Cerebral MRI abnormalities occur in more than one third of children with single ventricle, while the neurodevelopmental status is less severely affected before Fontan procedure. Liquor space enlargement is the predominant MRI finding associated with poorer neuro-developmental status, warranting further studies to determine aetiology and further evolution until school-age. © The Author 2016.
Keywords: Congenital heart disease; MRI; Neuroimaging; Outcome

Intracoronary cardiac progenitor cells in single ventricle physiology: the perseus (cardiac progenitor cell infusion to treat univentricular heart disease) randomized phase 2 trial - Ishigami, S.; Ohtsuki, S.; Eitoku, T.; Ousaka, D.; Kondo, M.; Kurita, Y.; Hirai, K.; Fukushima, Y.; Baba, K.; Goto, T.; Horio, N.; Kobayashi, J.; et al. (Circulation Research, 2017)
Rationale: Patients with single ventricle physiology are at high risk of mortality resulting from ventricular dysfunction. The preliminary results of the phase 1 trial showed that cardiosphere-derived cells (CDCs) may be effective against congenital heart failure. Objective: To determine whether intracoronary delivery of autologous CDCs improves cardiac function in patients with single ventricle physiology. Methods and Results: We conducted a phase 2 randomized controlled study to assign in a 1:1 ratio 41 patients who had single ventricle physiology undergoing stage 2 or 3 palliation to receive intracoronary infusion of CDCs 4 to 9 weeks after surgery or staged reconstruction alone (study A). The primary outcome measure was to assess improvement in cardiac function at 3-month follow-up. Four months after palliation, controls had an alternative option to receive late CDC infusion on request (study B). Secondary outcomes included ventricular function, heart failure status, somatic growth, and health-related quality of life after a 12-month observation. At 3 months, the absolute changes in ventricular function were significantly greater in the CDC-treated group than in the controls (+6.4% [SD, 5.5] versus +1.3% [SD, 3.7]; P=0.003). In study B, a late CDC infusion in 17 controls increased the ventricular function at 3 months compared with that at baseline (38.8% [SD, 7.7] versus 34.8% [SD, 7.4]; P<0.0001). At 1 year, overall CDC infusion was associated with improved ventricular function (41.4% [SD, 6.6] versus 35.0% [SD, 8.2]; P<0.0001) and volumes (P<0.001), somatic growth (P<0.0001) with increased trophic factors production, such as insulin-like growth factor-1 and hepatocyte growth factor, and quality of life, along with a reduced heart failure status (P<0.0001) and cardiac fibrosis (P=0.014) relative to baseline. Conclusions: Intracoronary infusion of CDCs after staged palliation favorably affected cardiac function by reverse remodeling in patients with single ventricle physiology. This impact may improve heart failure status, somatic growth, and quality of life in patients and reduce parenting stress for their families. Clinical Trial Registration: URL: http://www.clinicaltrials.gov. Unique identifier: NCT01829750. © 2017 American Heart Association, Inc.
Keywords: cell therapy; heart disease; heart failure; hypoplastic left heart syndrome; stem cell

Psychiatric disorders in adolescents with single ventricle congenital heart disease - DeMaso, D.R.; Calderon, J.; Taylor, G.A.; Holland, J.E.; Stopp, C.; White, M.T.; Bellinger, D.C.; Rivkin, M.J.; Wypij, D.; Newburger, J.W. (Pediatrics, 2017)
BACKGROUND AND OBJECTIVES: Mental health outcomes for survivors of critical congenital heart disease (CHD) remain under-investigated. We sought to examine psychiatric disorders and psychosocial functioning in adolescents with single ventricle CHD and to explore whether patient-related risk factors predict dysfunction. METHODS: This cohort study recruited 156 adolescents with single ventricle CHD who underwent the Fontan procedure and 111 healthy referents. Participants underwent comprehensive psychiatric evaluation including a clinician-rated psychiatric interview and parent-and self-report ratings of anxiety, disruptive behavior, including attention-deficit/hyperactivity disorder (ADHD), and depressive symptoms. Risk factors for dysfunction included IQ, medical characteristics, and concurrent brain abnormalities. RESULTS: Adolescents with single ventricle CHD had higher rates of lifetime psychiatric diagnosis compared with referents (CHD: 65%, referent: 22%; P < .001). Specifically, they had higher rates of lifetime anxiety disorder and ADHD (P < .001 each). The CHD group scored lower on the primary psychosocial functioning measure, the Children's Global Assessment Scale, than referents (CHD median [interquartile range]: 62 [54-66], referent: 85 [73-90]; P < .001). The CHD group scored worse on measures of anxiety, disruptive behavior, and depressive symptoms. Genetic comorbidity did not impact most psychiatric outcomes. Risk factors for anxiety disorder, ADHD, and lower psychosocial functioning included lower birth weight, longer duration of deep hypothermic circulatory arrest, lower intellectual functioning, and male gender. CONCLUSIONS: Adolescents with single ventricle CHD display a high risk of psychiatric morbidity, particularly anxiety disorders and ADHD. Early identification of psychiatric symptoms is critical to the management of patients with CHD. Copyright © 2017 by the American Academy of Pediatrics.

Health-related quality of life in children with surgery for CHD: A study from the Swedish National Registry for Congenital Heart Disease - Svensson, B.; Idvall, E.; Nilsson, F.; Liuba, P. (Cardiology in the Young, 2017)
Background As survival of children with CHD needing surgery has improved significantly, the need for follow-up in terms of health-related quality of life has become increasingly important. In this study, we sought to describe health-related quality of life in children with CHD in relation to cardiac surgery. Methods A retrospective Swedish National Registry for Congenital Heart Disease survey measured using DISABKIDS chronic generic measure-short version included 337 children (age 9-17 years; 39% girls). The majority (n=319, 95%) of children had a biventricular heart, whereas the remaining had a univentricular heart. Cardiac surgery was performed in 197 (58%) children. Health-related quality of life was expressed as total score (100 highest) and given as medians and 10-90th percentiles. Results The overall total score was 95 (88-100). Children with a biventricular heart who had undergone three or more surgeries (n=31; 9%) had the lowest total score of 81 (61-97; p<0.001). Children with two or more surgeries and those with univentricular heart were classified in NYHA II more frequently than children with one or no cardiac surgery (p=0.005 and <0.001, respectively). Children with three or more surgeries and those with univentricular heart needed more help at school (p<0.001). Compared with children with other chronic diseases, children with CHD had a high total score except for children with three or more surgeries who had comparable total scores with children with other chronic diseases. Conclusion Children with three or more cardiac surgeries and those with a univentricular heart appear to have lower health-related quality of life, cognitive ability, and NYHA classification. © Cambridge University Press 2016.
Keywords: CHD; children; Health-related quality of life; registry study

Pressure–volume loop-derived cardiac indices during dobutamine stress: a step towards understanding limitations in cardiac output in children with hypoplastic left heart syndrome - Wong, J.; Pushparajah, K.; de Vecchi, A.; Ruijsink, B.; Greil, G.F.; Hussain, T.; Razavi, R. (International Journal of Cardiology, 2017)
Background Children with a single systemic right ventricle, such as in hypoplastic left heart syndrome (HLHS), frequently experience reduced exercise capacity. Elucidating the causes could help with optimising treatment strategies. Methods Prospective data from 10 consecutive symptomatic patients with HLHS undergoing clinical cardiac magnetic resonance with catheterisation (XMR) were analysed. Mean age 8.6 years (range 3.5–11.6 years), mean time since Fontan completion 5.5 years. MR-compatible catheters were placed in the systemic right ventricle and branch pulmonary arteries to record pressures at rest, with dobutamine infusion at 10 mcg/kg/min and at 20 mcg/kg/min. Cine short-axis stacks of the ventricle were performed at each condition and used to construct pressure–volume loops. Results Compared to rest, cardiac index increased with low-dose dobutamine (p < 0.01) with no further rise at peak stress despite a further, albeit, blunted rise in heart rate (p = 0.002). A fall in stroke volume occurred (p = 0.014) despite good contractility (74% increase, p = 0.045) and a well-coupled ventriculo-arterial ratio. End-diastolic pressure and early active relaxation, markers of diastolic function, were normal at rest. However, preload fell at peak stress (p < 0.008) while pulmonary vascular resistance (PVR) was low throughout. This group of HLHS patients demonstrated a fall in SV at peak stress, coinciding with a fall in preload. Conclusions Markers of systolic and diastolic function remained normal. Failure to adequately fill the ventricle implies a ceiling of maximal flow through the Fontan circuit despite low PVR. © 2016
Keywords: Catheterisation; Congenital heart disease; Fontan procedure; Hypoplastic left heart syndrome; Magnetic resonance imaging

Neurocognitive functioning in adults with congenital heart disease - Ilardi, D.; Ono, K.E.; McCartney, R.; Book, W.; Stringer, A.Y. (Congenital Heart Disease, 2017)
Objective: Adults with congenital heart disease (CHD) are at increased risk of psychological disorders and cognitive deficiencies due to structural/acquired neurological abnormalities and neurodevelopmental disorders as children. However, limited information is known about the neuropsychological functioning of adults with CHD. This study screened neuropsychological abilities and explored group differences related to cardiac disease severity and neurological risk factors in adults with CHD. Design: Participants completed brief neuropsychological testing. Information about neurobehavioral and psychological symptoms, employment, education, and disability were also collected from the patient and a family member. Results: Forty-eight participants with adult CHD completed neuropsychological testing. Visuospatial skills and working memory were worse than expected compared to the typical population. Frequency of neurological comorbidities (e.g., stroke, seizures) was higher in those with more severe heart disease (e.g., single ventricle or cyanotic disease), and executive functioning was weaker in those with neurological comorbidities. Those with more severe heart disease were more likely to be unemployed and to receive disability benefits, but educational attainment did not differ. Those who received disability performed worse on tasks of executive functioning. Conclusions: Findings suggest concerns about neuropsychological functioning that need to be more comprehensively assessed in adults with CHD. Understanding the cognitive limitations of this aging population can help guide access to resources, transition of care, and medical care engagement, thus improving quality of care and quality of life. © 2016 Wiley Periodicals, Inc.
Keywords: adult congenital heart disease; adult transition; cognitive functioning; executive functioning; neurodevelopmental outcomes; neuropsychological outcomes

Comparison of participants and non-participants in patient-reported outcome surveys: The case of Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease-International Study - Berghammer, M.C.; Mattsson, E.; Johansson, B.; Moons, P.; Dellborg, M. (Cardiology in the Young, 2017)
Background The last decade has seen a vast increase in the use of patient-reported outcomes. As patient-reported outcomes are used in order to capture patients' perspectives of their health and illness, it is a prerequisite for accurate patient-reported outcome evaluations to use representative samples. In order to evaluate representativeness, the present study focussed on the comparison between participants and non-participants in the Swedish branch of the international study APPROACH-IS (Assessment of Patterns of Patient-Reported Outcomes in Adults with Congenital Heart disease-International Study), regarding demographic, clinical, and health status characteristics. Methods Eligible patients for APPROACH-IS were identified and selected from SWEDCON, the Swedish registry for congenital heart disease (CHD). Overall, 912 eligible patients were identified, of whom 471 participated, 398 did not participate, and 43 were either unreachable or declined to participate in APPROACH-IS. The participants and non-participants were compared in terms of statistical significance and effect sizes. Results Significant differences were observed between participants and non-participants for sex, age, primary diagnosis, number of cardiac operations, and fatigue; however, the effect sizes were in general small, except for the difference in primary diagnosis. No differences between the two groups were found in number of catheterisations, implanted device, the distribution of NYHA functional class, or health status and symptoms. Conclusions This study shows that participants and non-participants are relatively comparable groups, which confirms the representativeness of the participants. The Swedish data from APPROACH-IS can therefore be reliably generalised to the population of adults with CHD in Sweden. © Cambridge University Press 2016.
Keywords: Adults; comparison; congenital; heart defect; multicentre study; patient-reported outcome

Neurodevelopmental Outcome and Health-related Quality of Life in Children With Single-ventricle Heart Disease Before Fontan Procedure - Reich, B.; Heye, K.; Tuura, R.; Beck, I.; Wetterling, K.; Hahn, A.; Hofmann, K.; Schranz, D.; Akintürk, H.; Latal, B.; Knirsch, W. (Seminars in Thoracic and Cardiovascular Surgery, 2017)
Neurodevelopmental impairment and impaired quality of life constitute a major source of morbidity among children with complex congenital heart disease, in particular for single-ventricle (SV) morphologies. Risk factors and quality of life determining clinical and neurodevelopmental outcome at 2 years of age are examined. In a 2-center cohort study, 48 patients with SV morphology (26 hypoplastic left heart syndrome and 22 other types of univentricular heart defect) have been examined before Fontan procedure between 2010 and 2015. Patients were assessed with the Bayley Scales of Infant and Toddler Development, Third Version (Bayley-III), and the Preschool Children Quality of Life (TAPQOL) questionnaire. A total of 44 patients underwent hybrid procedure (n = 25), Norwood procedure (n = 7), or shunt or banding procedure (n = 12) as first surgery before subsequent bidirectional cavopulmonary anastomosis (n = 48). Median cognitive, language, and motor composite scores on the Bayley-III were 100 (range 65-120), 97 (68-124), and 97 (55-124), respectively. The language composite score was significantly below the norm (P = 0.025). Risk factors for poorer neurodevelopmental outcome were prolonged mechanical ventilation, longer days of hospital stay, and more reinterventions (all P < 0.05). Parents reported a good quality of life for their children. Children undergoing Fontan procedure show a favorable development and good quality of life. More complicated postoperative course and reinterventions constitute risk factors for impaired neurodevelopment. Improving postoperative management and implementing routine follow-up assessments aremeasures to further improve the neurodevelopmental outcome of this high-risk patient population. © 2017 Elsevier Inc.
Keywords: congenital heart disease; neurodevelopmental outcome; risk factors

Long-Term Follow-Up on Health-Related Quality of Life after Mechanical Circulatory Support in Children - Fleck, T.P.K.; Dangel, G.; Bächle, F.; Benk, C.; Grohmann, J.; Kroll, J.; Siepe, M.; Höhn, R.; Kirschner, J.; Beyersdorf, F.; Stiller, B. (Pediatric Critical Care Medicine, 2017)
Objective: The objective of this study was to evaluate health-related quality of life in long-term survivors of mechanical circulatory support after acute cardiopulmonary failure. Design: Prospective follow-up study. Setting: Single-institutional in a center for congenital heart disease and pediatric cardiology. Patients: Fifty patients who underwent 58 mechanical circulatory support therapies in our institution from 2001 to 2012. Median age was 2 (0-213) months, and median supporting time was 5 (1-234) days. Indication groups: 1) extracorporeal life support in low cardiac output: 30 cases (52%); 2) extracorporeal cardiopulmonary resuscitation: 13 cases (22%); 3) extracorporeal membrane oxygenation in acute respiratory distress syndrome: four cases (7%); and 4) ventricular assist devices: 11 cases (19%). Interventions: Health-related quality of life was measured using standardized questionnaires according to the age group and completed by either parent proxies in children under 7 years old or the survivors themselves. Measurements and Main Results: Fifty percentage of the patients were discharged home, and 22 long-term survivors (44%) were studied prospectively for health-related quality of life. Median follow-up period was 4.5 (0.3-11.3) years. Median age at follow-up was 5 (0.6-29) years old. Nineteen long-term survivors filled in the health-related quality of life questionnaires and were classified into three age groups: 0-4 years (n = 7): median health-related quality of life score, 69 (59-86) points; 4-12 years (n = 7): median health-related quality of life score, 50 (48-85) points; older than 12 years (n = 5): median health-related quality of life score, 90 (80-100) points. Conclusion: Long-term survivors' health-related quality of life as reported by their parents is lower than that of healthy children. However, the self-assessed health-related quality of life of the patients older than 12 years in our group is comparable to a healthy control population. © 2017 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Children; congenital heart disease; extracorporeal membrane oxygenation; health-related quality of life; mechanical circulatory support

Academic outcomes in children with congenital heart defects - Oster, M.E.; Watkins, S.; Hill, K.D.; Knight, J.H.; Meyer, R.E. (Circulation: Cardiovascular Quality and Outcomes, 2017)
Background - Most studies evaluating neurocognitive outcomes in children with congenital heart defects (CHD) have focused on high-risk patients or used specialized, resource-intensive testing. To determine the association of CHD with academic outcomes and compare outcomes according to the severity of CHD, we linked state educational records with a birth defects registry and birth certificates. Methods and Results - We performed a retrospective cohort study using data from the North Carolina Birth Defects Monitoring Program, North Carolina Department of Public Instruction, and North Carolina Department of Health and Human Services vital records. We performed logistic regression, adjusting for maternal education, race/ethnicity, enrollment in public pre-Kindergarten, and gestational age, to determine the association of CHD with not meeting standards on reading and math end-of-grade examinations in third grade in 2006 to 2012. Of 5624 subjects with CHD and 10 832 with no structural birth defects, 2807 (50%) and 6355 (59%) were linked, respectively. Children with CHD had 1.24× the odds of not meeting standards in either reading or math (95% confidence interval, 1.12-1.37), with 44.6% of children with CHD not meeting standards in at least one of these areas compared with 37.5% without CHD. Although children with both critical and noncritical CHD had poorer outcomes, those with critical CHD were significantly more likely to receive exceptional services compared with the noncritical group (adjusted odds ratio, 1.46; 95% confidence interval, 1.15-1.86). Conclusions - Children with all types of CHD have poorer academic outcomes compared with their peers. Evaluation for exceptional services should be considered in children with any type of CHD. © 2017 American Heart Association, Inc.
Keywords: birth certificates; child; education; gestational age; heart defects, congenital; registries

Bedside Ultrasound for the Diagnosis of Abnormal Diaphragmatic Motion in Children after Heart Surgery - Gil-Juanmiquel, L.; Gratacós, M.; Castilla-Fernández, Y.; Piqueras, J.; Baust, T.; Raguer, N.; Balcells, J.; Perez-Hoyos, S.; Abella, R.F.; Sanchez-De-Toledo, J. (Pediatric Critical Care Medicine, 2017)
Objective: To assess the utility of bedside ultrasound combining B-and M-mode in the diagnosis of abnormal diaphragmatic motion in children after heart surgery. Design: Prospective post hoc blinded comparison of ultrasound performed by two different intensivists and fluoroscopy results with electromyography. Setting: Tertiary university hospital. Subjects: Children with suspected abnormal diaphragmatic motion after heart surgery. Interventions: None. Measurements and Main Results: Abnormal diaphragmatic motion was suspected in 26 children. Electromyography confirmed the diagnosis in 20 of 24 children (83.3%). The overall occurrence rate of abnormal diaphragmatic motion during the study period was 7.5%. Median patient age was 5 months (range, 16 d to 14 yr). Sensitivity and specificity of chest ultrasound performed at the bedside by the two intensivists (91% and 92% and 92% and 95%, respectively) were higher than those obtained by fluoroscopy (87% and 83%). Interobserver agreement (k) between both intensivists was 0.957 (95% CI, 0.87-100). Conclusions: Chest ultrasound performed by intensivists is a valid tool for the diagnosis of diaphragmatic paralysis, presenting greater sensitivity and specificity than fluoroscopy. Chest ultrasound should be routinely used after pediatric heart surgery given its reliability, reproducibility, availability, and safety. © 2017 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Diaphragmatic paralysis; electromyography; fluoroscopy; pediatric heart surgery; ultrasound

Single-stage, three-fold repair for Ebstein's anomaly - Mostafa, E.A.; El Midany, A.A.H.; Elnahas, Y.; Helmy, A.; Mansour, S.A. (Interactive Cardiovascular and Thoracic Surgery, 2017)
OBJECTIVES: Favourable outcomes in the repair of Ebstein's anomaly are predicated on tricuspid valve competence, right ventricular function and presence of arrhythmia. We report our experience with a single-stage, three-fold repair of Ebstein's anomaly, namely, cone reconstruction of the tricuspid valve supplemented by bidirectional cavopulmonary anastomosis and right atrial electrocautery maze. METHODS: From 2010 to 2014, 37 consecutive patients with Ebstein's anomaly, median age 17.3 (9.1-56.2) years, underwent this singlestage, three-fold surgical procedure. The principal elements of the procedure include (i) cone reconstruction of the tricuspid valve, limited plication at the level of the displaced valve, insertion of a homemade annuloplasty ring, defect repair and reduction atrioplasty supplemented by (ii) right atrial electrocautery maze and (iii) bidirectional cavopulmonary anastomosis. Postoperatively, all patients were followed up regularly for a mean period of 2.3 (1-4) years by clinical, electrocardiographic and echocardiographic examinations. RESULTS: The in-hospital mortality rate was 2.7% (1 patient) with no late deaths. Mean cardiopulmonary bypass time was 110 ± 18.3 min and aortic cross-clamp time was 48.5 ± 7.4 min. Echocardiographic examination showed significant improvement of valve regurgitation (P < 0.0001). NYHA functional class was I in 77.8% of the survivors and II in 22.2%. The cardiothoracic ratio decreased significantly (P < 0.05). No deleterious effects of the Glenn shunts have been reported. Sinus rhythm has remained stable in 31 patients (86.1%) during the follow-up period. CONCLUSIONS: Single-stage, three-fold repair for the management of Ebstein's anomaly offers good outcome in terms of low mortality and morbidity rates. It can achieve a durable valve-sparing repair, good functional mid-term outcomes and good quality of life among survivors. © The Author 2016. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Cone reconstruction of tricuspid valve; Congenital heart disease; Ebstein's anomaly; One-and-a-half ventricular repair

Effects of milk flow on the physiological and behavioural responses to feeding in an infant with hypoplastic left heart syndrome - Pados, B.F.; Thoyre, S.M.; Estrem, H.H.; Park, J.; Knafl, G.J.; Nix, B. (Cardiology in the Young, 2017)
Infants with hypoplastic left heart syndrome often experience difficulty with oral feeding, which contributes to growth failure, morbidity, and mortality. In response to feeding difficulty, clinicians often change the bottle nipple, and thus milk flow rate. Slow-flow nipples have been found to reduce the stress of feeding in other fragile infants, but no research has evaluated the responses of infants with hypoplastic left heart syndrome to alterations in milk flow. The purpose of this study was to evaluate the physiological and behavioural responses of an infant with hypoplastic left heart syndrome to bottle feeding with either a slow-flow (Dr. Brown's Preemie) or a standard-flow (Dr. Brown's Level 2) nipple. A single infant was studied for three feedings: two slow-flow and one standard-flow. Oral feeding, whether with a slow-flow or a standard-flow nipple, was distressing for this infant. During slow-flow feeding, she experienced more coughing events, whereas during standard-flow she experienced more gagging. Disengagement and compelling disorganisation were most common during feeding 3, that is slow-flow, which occurred 2 days after surgical placement of a gastrostomy tube. Clinically significant changes in heart rate, oxygen saturation, and respiratory rate were seen during all feedings. Heart rate was higher during standard-flow and respiratory rate was higher during slow-flow. Further research is needed to examine the responses of infants with hypoplastic left heart syndrome to oral feeding and to identify strategies that will support these fragile infants as they learn to feed. Future research should evaluate an even slower-flow nipple along with additional supportive feeding strategies. © Cambridge University Press 2016.
Keywords: bottle feeding; feeding methods; Hypoplastic left heart syndrome

Clinical profile of cyanotic congenital heart disease in neonatal intensive care unit at Sohag University Hospital, Upper Egypt - Abou-Taleb, A.; Abdelhamid, M.A.; Bahkeet, M.A.M. (Egyptian Journal of Medical Human Genetics, 2017)
Background Cyanotic congenital heart disease (CCHD) accounts for 25% of congenital heart defects and has a high morbidity and mortality in neonates. Objective The aim of this work was to study clinical profile and available therapeutic modalities used in the management of CCHD. Subjects and methods This was a prospective study carried out for a period of one year, starting from January 2011, and included 50 neonates admitted to neonatal intensive care unit (NICU) of Sohag University Hospital, Sohag, Upper Egypt. All included patients were subjected to thorough clinical history, full clinical examination, initial and frequent measurement of oxygen saturation by pulse oximetry, blood gas analysis, and echocardiography. Also, therapeutic modalities used in management of CCHD were noted. Results 50 neonates were diagnosed as having CCHD, out of them 39 (78%) were males with male to female ratio 3.55:1. The mean age of presentation was 11.78 ± 9.4 days. CCHD frequency was found to be 9.5% (50/524) in our NICU population. The most common type of CCHD was d-transposition of great arteries (D-TGA) (66%) followed by complex CCHD (12%) and hypoplastic left heart syndrome (HLHS) (12%), whereas the less common type was hypoplastic right ventricle (2%). All cases presented with central cyanosis and needed medical treatment whereas balloon atrial septostomy was performed in 26% of cases. Seventy-four percent of cases were improved and referred to higher centers while 26% were expired during hospital stay. Conclusion CCHD is a leading cause of neonatal morbidity and mortality. CCHD frequency was significant (9.5%) in our study population with D-TGA being the commonest type. Majority of neonates with CCHD showed survival with suitable management. Early diagnosis and referral to pediatric cardiac center for proper management will improve the outcome. Neonatologists and pediatric cardiologists should be familiar with diagnosis and management of CCHD. © 2016 Ain Shams University
Keywords: Cyanotic congenital heart disease; Echocardiography; Transposition of great arteries

Abnormalities in serum biomarkers correlate with lower cardiac index in the Fontan population - Marino, B.S.; Goldberg, D.J.; Dorfman, A.L.; King, E.; Kalkwarf, H.; Zemel, B.S.; Smith, M.; Pratt, J.; Fogel, M.A.; Shillingford, A.J.; Deal, B.J.; John, A.S.; et al. (Cardiology in the Young, 2017)
Background Fontan survivors have depressed cardiac index that worsens over time. Serum biomarker measurement is minimally invasive, rapid, widely available, and may be useful for serial monitoring. The purpose of this study was to identify biomarkers that correlate with lower cardiac index in Fontan patients. Methods and results This study was a multi-centre case series assessing the correlations between biomarkers and cardiac magnetic resonance-derived cardiac index in Fontan patients ≥6 years of age with biochemical and haematopoietic biomarkers obtained ±12 months from cardiac magnetic resonance. Medical history and biomarker values were obtained by chart review. Spearman's Rank correlation assessed associations between biomarker z-scores and cardiac index. Biomarkers with significant correlations had receiver operating characteristic curves and area under the curve estimated. In total, 97 cardiac magnetic resonances in 87 patients met inclusion criteria: median age at cardiac magnetic resonance was 15 (6-33) years. Significant correlations were found between cardiac index and total alkaline phosphatase (-0.26, p=0.04), estimated creatinine clearance (0.26, p=0.02), and mean corpuscular volume (-0.32, p<0.01). Area under the curve for the three individual biomarkers was 0.63-0.69. Area under the curve for the three-biomarker panel was 0.75. Comparison of cardiac index above and below the receiver operating characteristic curve-identified cut-off points revealed significant differences for each biomarker (p<0.01) and for the composite panel [median cardiac index for higher-risk group=2.17 L/minute/m2 versus lower-risk group=2.96 L/minute/m2, (p<0.01)]. Conclusions Higher total alkaline phosphatase and mean corpuscular volume as well as lower estimated creatinine clearance identify Fontan patients with lower cardiac index. Using biomarkers to monitor haemodynamics and organ-specific effects warrants prospective investigation. © Cambridge University Press 2015Â.
Keywords: biomarkers; cardiac index; cardiac MRI; Fontan

“Frontiers in Fontan failure: A summary of conference proceedings” - Hebson, C.; Book, W.; Elder, R.W.; Ford, R.; Jokhadar, M.; Kanter, K.; Kogon, B.; Kovacs, A.H.; Levit, R.D.; Lloyd, M.; Maher, K.; Reshamwala, P.; et al. (Congenital Heart Disease, 2017)
“Frontiers in Fontan Failure” was the title of a 2015 conference sponsored by Children's Healthcare of Atlanta and Emory University School of Medicine. In what is hoped to be the first of many such gatherings, speakers and attendees gathered to discuss the problem of long-term clinical deterioration in these patients. Specific focuses included properly defining the problem and then discussing different treatment strategies, both medical and surgical. The health of the liver after Fontan palliation was a particular point of emphasis, as were quality of life and future directions. © 2016 Wiley Periodicals, Inc.
Keywords: cardiac surgery; circulatory failure; cirrhosis; congenital heart disease; Fontan; hepatology

Use of 3D models of congenital heart disease as an education tool for cardiac nurses - Biglino, G.; Capelli, C.; Koniordou, D.; Robertshaw, D.; Leaver, L.-K.; Schievano, S.; Taylor, A.M.; Wray, J. (Congenital Heart Disease, 2017)
Background: Nurse education and training are key to providing congenital heart disease (CHD) patients with consistent high standards of care as well as enabling career progression. One approach for improving educational experience is the use of 3D patient-specific models. Objectives: To gather pilot data to assess the feasibility of using 3D models of CHD during a training course for cardiac nurses; to evaluate the potential of 3D models in this context, from the nurses' perspective; and to identify possible improvements to optimise their use for teaching. Design: A cross-sectional survey. Setting: A national training week for cardiac nurses. Participants: One hundred cardiac nurses (of which 65 pediatric and 35 adult). Methods: Nurses were shown nine CHD models within the context of a specialized course, following a lecture on the process of making the models themselves, starting from medical imaging. Participants were asked about their general learning experience, if models were more/less informative than diagrams/drawings and lesion-specific/generic models, and their overall reaction to the models. Possible differences between adult and pediatric nurses were investigated. Written feedback was subjected to content analysis and quantitative data were analyzed using nonparametric statistics. Results: Generally models were well liked and nurses considered them more informative than diagrams. Nurses found that 3D models helped in the appreciation of overall anatomy (86%), spatial orientation (70%), and anatomical complexity after treatment (66%). There was no statistically significant difference between adult and pediatric nurses' responses. Thematic analysis highlighted the need for further explanation, use of labels and use of colors to highlight the lesion of interest amongst improvements for optimizing 3D models for teaching/training purposes. Conclusion: 3D patient-specific models are useful tools for training adult and pediatric cardiac nurses and are particularly helpful for understanding CHD anatomy after repair. © 2016 Wiley Periodicals, Inc.
Keywords: 3D printing; cardiovascular nursing; congenital heart defects; training

Differentiation of Impaired from Preserved Hemodynamics in Patients with Fontan Circulation Using Real-time Phase-velocity Cardiovascular Magnetic Resonance - Körperich, H.; Müller, K.; Barth, P.; Gieseke, J.; Haas, N.; Schulze-Neick, I.; Burchert, W.; Kececioglu, D.; Laser, K.T. (Journal of Thoracic Imaging, 2017)
Purpose: Progressive impairment of hemodynamics in patients with Fontan circulation is common, multifactorial, and associated with decreased quality of life and increased morbidity. We sought to assess hemodynamic differences between patients with preserved (preserved Fontans) and those with impaired circulation (impaired Fontans) after pulmonary vasodilation using oxygen and under forced breathing conditions. Materials and Methods: Real-time phase-contrast cardiovascular magnetic resonance was performed using non-ECG triggered echo-planar imaging (temporal resolution=24 to 28 ms) in the ascending aorta (AAo) and superior vena cava (SVC)/inferior vena cava (IVC) on room air, after 100% oxygen inhalation (4 L/min; 10 min) and on forced breathing in 29 Fontan patients (17.2±7.3 y) and in 32 controls on room air (13.4±3.7 y). The simultaneously recorded patients' respiratory cycle was divided into 4 segments (expiration, end-expiration, inspiration, and end-inspiration) to generate respiratory-dependent stroke volumes (SVs). The imaging data were matched with physiological data and analyzed with home-made software. Results: The mean SVi (AAo) was 46.1±11.1 mL/m2 in preserved Fontans versus 30.4±6.2 mL/m2 in impaired Fontans (P=0.002) and 51.1±6.9 mL/m2 in controls (P=0.107). The cutoff value for differentiation of Fontan groups was SVi (AAo, end-expiratory) of 32.1 mL/m2. After hyperoxygenation, the mean SVi (AAo) increased to 48.7±12.7 mL/m2 in preserved Fontans (P=0.045) but remained unchanged in impaired Fontans (31.1±5.8 mL/m2, P=0.665). Simultaneously, heart rates decreased from 75.2±15.9 to 70.8±16.4 bpm (preserved; P=0.000) but remained unchanged in impaired circulation (baseline: 84.1±9.8 bpm, P=0.612). Compared with physiological respiration, forced breathing increased the maximum respiratory-related cardiac index difference (ΔCImax) in preserved Fontans (SVC: 2.5-fold, P=0.000; and IVC: 1.8-fold, P=0.000) and to a lower extent in impaired Fontans (both veins, 1.5-fold; P(SVC)=0.011, P(IVC)=0.013). There was no impact on mean blood flow. Conclusions: Oxygen affected the pulmonary vascular system by vasodilation and increased SV i in preserved Fontans but had no effect on impaired Fontans. Forced breathing increased ΔCImax but did not change the mean blood flow by sole activation of the ventilatory pump. End-expiratory aortic SV i represents a valuable measure for classifying the severity of Fontan hemodynamics impairment. Copyright © 2017 Wolters Kluwer Health, Inc. All rights reserved.
Keywords: congenital; heart Defects; hemodynamics; magnetic resonance imaging; respiration; vasodilation

Variable Myocardial Response to Load Stresses in Infants with Single Left Ventricular Anatomy: Influence of Initial Physiology and Surgical Palliative Strategy - Horriat, N.L.; Deatsman, S.L.; Stelter, J.; Frommelt, P.C.; Hill, G.D. (Pediatric Cardiology, 2016)
Initial surgical strategies in neonates with single left ventricular (LV) anatomy vary based on adequacy of pulmonary and systemic blood flow. Differing myocardial responses to these strategies, as reflected in indices of systolic function, ventricular size, and mass have not been well defined. We sought to evaluate single LV myocardial response to varied physiology and initial palliation and determine whether the response is consistent and predictable. Infants with single LV physiology were divided based on neonatal palliation: no palliation/PA band (NO); BT shunt only (BT); or Norwood procedure (NP). Echo measures were obtained at presentation, early post-bidirectional Glenn (BDG), late post-BDG follow-up, and post-Fontan procedure. Measures included ejection fraction, LV mass indexed to height2.7 and end diastolic volume indexed to body surface area, and mass/volume ratio. The cohort included 38 children (13 NO, 13 BT, 12 NP). Ejection fraction was similar but depressed in all groups at all stages. LV mass was higher in the NP group than the BT group at early post-BDG (p = 0.03) and higher than both BT and NO groups (p < 0.01) at late post-BDG, but the difference was resolved by post-Fontan follow-up. The NP group had the most remarkable remodeling in LV size from BDG to Fontan, suggesting that volume unloading is most valuable in this subgroup. Ventricular remodeling can be identified by echocardiography in children with single LV physiology, despite variable initial surgical palliative strategies. Importantly, these initial surgical strategies do not result in significant differences after Fontan palliation during early childhood. © 2016, Springer Science+Business Media New York.
Keywords: Echocardiography; Fontan; Glenn; Single ventricle

Anxiety Scores in Caregivers of Children with Hypoplastic Left Heart Syndrome - Caris, E.C.; Dempster, N.; Wernovsky, G.; Butz, C.; Neely, T.; Allen, R.; Stewart, J.; Miller-Tate, H.; Fonseca, R.; Texter, K.; Nicholson, L.; Cua, C.L. (Congenital Heart Disease, 2016)
Objectives: Caring for children with congenital heart disease places significant stress on caregivers. Minimal data exist evaluating stress levels in caregivers of children with hypoplastic left heart syndrome (HLHS). The goal of this study was to obtain baseline stress scores for caregivers of children with HLHS and determine if associations exist between scores and specific caregiver factors. Study Design: A cross-sectional study using a web-based survey targeted towards caregivers of children with HLHS was performed. Baseline demographics of the caregiver and child with HLHS were obtained. Caregivers completed three validated questionnaires including the Pediatric Quality of Life Inventory (PedsQL), Parenting Stress Index- Short Form (PSI-SF) and the Pediatric Inventory for Parents (PIP). Results: Four hundred fifty-nine caregivers completed at least one questionnaire. PSI-SF total score was 80.5 ± 23.1 (> 86 = significant stress), PIP frequency total score was 119.0 ± 37.2, and PIP difficulty total score was 118.1 ± 35.7. Lower quality of life was significantly correlated with higher scores on the PSI-SF (r = −0.6), the presence of a developmental issue in the child (r = 0.3) as well as higher scores on the PIP frequency (r = −0.5) and difficulty scales (r = 0.4). Other demographic values for the caregiver and child did not significantly correlate with PSI or PIP total scores. Conclusions: Anxiety/stress scores of caregivers with children with HLHS are correlated with how well the child is perceived to be doing physically and developmentally by the caregivers. Caregivers with physical and/or developmental concerns may need added psychosocial support. © 2016 Wiley Periodicals, Inc.
Keywords: Congenital Heart Disease; Hypoplastic Left Heart; Parenting Stress; Survey

Parental refusal of surgery in an infant with tricuspid atresia - Kon, A.A.; Patel, A.; Leuthner, S.; Lantos, J.D. (Pediatrics, 2016)
We present a case of a fetal diagnosis of tricuspid atresia (TA). The pregnant woman and her husband requested that the baby be treated with only palliative care. The cardiologist did not think it would be appropriate to withhold life-prolonging surgery once the infant was born. The neonatologist argued that outcomes for TA are similar to those for hypoplastic left heart syndrome, and the standard practice at the institution was to allow parents to choose surgery or end-of-life care for those infants. The team requested an ethics consultation to assist in determining whether forgoing life-prolonging interventions in this case would be ethically supportable. In this article, we ask a pediatric intensivist, a pediatric cardiologist, and a neonatologist to discuss the ethics of withholding life-sustaining treatment of a baby with TA. Copyright © 2016 by the American Academy of Pediatrics.

Reduced physical exercise and health-related quality of life after Fontan palliation - Hedlund, E.R.; Lundell, B.; Villard, L.; Sjöberg, G. (Acta Paediatrica, International Journal of Paediatrics, 2016)
Aim: A growing number of patients with Fontan circulation are reaching adulthood, and there is increasing concern about their physical performance and quality of life. This study compared self-reported exercise and measured activity with quality of life in patients after Fontan palliation and healthy controls. Methods: Physical exercise during an average school week was reported by 30 Fontan circulation patients aged eight to 20 years, and 25 healthy controls, followed by accelerometer recordings over seven days. All subjects and their parents answered a questionnaire on quality of life. Results: Patients reported spending less time exercising each week than the controls (114 ± 66 minutes vs. 228 ± 147 minutes, p < 0.001). However, the overall measured activity and moderate-to-vigorous activity was similar for patients and controls. Patients reported a lower quality of life score than the controls (70.9 ± 9.9 vs. 85.7 ± 8.0, p < 0.001). Conclusion: In spite of similar measured total activity, Fontan patients reported less time engaged in regular physical exercise than healthy controls and their quality of life was lower than the controls. We speculate that promoting structured regular physical exercise could improve the quality of life of Fontan patients. ©2016 Foundation Acta Pædiatrica. Published by John Wiley & Sons Ltd
Keywords: Accelerometer; Fontan circulation; Fontan palliation; Physical exercise; Quality of life

Current therapy for hypoplastic left heart syndrome and related single ventricle lesions - Ohye, R.G.; Schranz, D.; D'Udekem, Y. (Circulation, 2016)
Universally fatal only 4 decades ago, the progress in the 3-stage palliation of hypoplastic left heart syndrome and related single right ventricular lesions has drastically improved the outlook for these patients. Although the stage II operation (hemi-Fontan or bidirectional Glenn) and stage III Fontan procedure have evolved into relatively low-risk operations, the stage I Norwood procedure remains one of the highest-risk and costliest common operations performed in congenital heart surgery. Yet, despite this fact, experienced centers now report hospital survivals of >90% for the Norwood procedure. This traditional 3-stage surgical palliation has seen several innovations in the past decade aimed at improving outcomes, particularly for the Norwood procedure. One significant change is a renewed interest in the right ventricle-to-pulmonary artery shunt as the source of pulmonary blood flow, rather than the modified Blalock-Taussig shunt for the Norwood. The multi-institutional Single Ventricle Reconstruction trial randomly assigned 555 patients to one or the other shunt, and these subjects continue to be followed closely as they now approach 10 years postrandomization. In addition to modifications to the Norwood procedure, the hybrid procedure, a combined catheter-based and surgical approach, avoids the Norwood procedure in the newborn period entirely. The initial hybrid procedure is then followed by a comprehensive stage II, which combines components of both the Norwood and the traditional stage II, and later completion of the Fontan. Proponents of this approach hope to improve not only short-term survival, but also potentially longer-term outcomes, such as neurodevelopment, as well. Regardless of the approach, traditional surgical staged palliation or the hybrid procedure, survivals have vastly improved, and large numbers of these patients are surviving not only through their Fontan in early childhood, but also into adolescence and young adulthood. As this population grows, it becomes increasingly important to understand the longer-term outcomes of these Fontan patients, not only in terms of survival, but also in terms of the burden of disease, neurodevelopmental outcomes, psychosocial development, and quality of life. © 2016 American Heart Association, Inc.
Keywords: congenital; heart defects; heart ventricles; hybrid imaging; hypoplastic left heart syndrome; surgery

Survival status and functional outcome of children who required prolonged intensive care after cardiac surgery - Namachivayam, S.P.; d'Udekem, Y.; Millar, J.; Cheung, M.M.; Butt, W. (Journal of Thoracic and Cardiovascular Surgery, 2016)
Background Children who require prolonged intensive care after cardiac surgery are at risk of high mortality. The long-term survival and functional outcome of these children have not been studied in detail. Methods Children who stayed in intensive care for >28 days after cardiac surgery from 1997 to 2012 were studied in a single institution. A total of 116 patients were identified; 107 (92%) were <1 year of age and 63 (54%) had univentricular physiology. Results The incidence of children requiring prolonged intensive care increased from 1.01/100 undergoing cardiac surgery in 1997 to 2000 to 2.66/100 in 2009 to 2012 (P trend = .002). This increase coincided with an increase in the number of children with hypoplastic left heart syndrome having prolonged intensive care during the same period (0.13/100 in 1997-2000 to 1.0/100 in 2009-2012; P trend = .001). Survival to pediatric intensive care unit (PICU) discharge was 74% (95% confidence interval [CI], 65-82) and 51% (95% CI, 41-59) at 3 years. Factors associated with mortality were univentricular repair (hazard ratio [HR], 2.12; 95% CI, 1.21-3.70; P = .008) and acute renal failure (HR, 3.01; 95% CI, 1.77-5.12; P < .001), but era did not influence mortality (1997-2005 vs 2006-2012; log-rank P = .66). Among PICU survivors, 3-year survival in those who did not need early reoperation was 81% (95% CI, 66-90), compared with 58% (95% CI, 42-71) in those who required early reoperation (log-rank P = .01). Among survivors, 36% had either moderate or severe disability and 13% had poor quality of life. Conclusions The incidence of children requiring prolonged intensive care after cardiac surgery has increased in our institution. Our data suggest that the long-term outcome for most of these children is poor, especially after univentricular repair. © 2016 The American Association for Thoracic Surgery
Keywords: functional outcome; pediatric cardiac surgery; prolonged intensive care; survival status

Evolving heart transplantation across the lifespan: A growing population of adults with congenital heart disease - Cohen, S.; Marelli, A. (Archives of Cardiovascular Diseases, 2016)
Keywords: Congenital heart disease; Heart failure; Heart transplantation

Parents' preparedness for their infants' discharge following first-stage cardiac surgery: Development of a parental early warning tool - Gaskin, K.L.; Barron, D.J.; Daniels, A. (Cardiology in the Young, 2016)
Aim The aim of this study was to explore parental preparedness for discharge and their experiences of going home with their infant after the first-stage surgery for a functionally univentricular heart. Background Technological advances worldwide have improved outcomes for infants with a functionally univentricular heart over the last 3 decades; however, concern remains regarding mortality in the period between the first and second stages of surgery. The implementation of home monitoring programmes for this group of infants has improved this initial inter-stage survival; however, little is known about parents' experiences of going home, their preparedness for discharge, and parents' recognition of deterioration in their fragile infant. Method This study was conducted in 2011-2013; eight sets of parents were consulted in the research planning stage in September, 2011, and 22 parents with children aged 0-2 years responded to an online survey during November, 2012-March, 2013. Description of categorical data and deductive thematic analysis of the open-ended questions were undertaken. Results Not all parents were taught signs of deterioration or given written information specific to their baby. The following three themes emerged from the qualitative data: mixed emotions about going home, knowledge and preparedness, and support systems. Conclusions Parents are not adequately prepared for discharge and are not well equipped to recognise deterioration in their child. There is a role for greater parental education through development of an early warning tool to address the gap in parents' understanding of signs of deterioration, enabling appropriate contact and earlier management by clinicians. © Cambridge University Press 2016.
Keywords: CHD; family; heart defects; Hypoplastic left heart syndrome; infants; parents; patient discharge

Dilated right internal thoracic artery as a systemic pulmonary shunt - Kaneda, K.; Yokoyama, S.; Nagato, H.; Nagasaka, S.; Nishiwaki, N.; Taniguchi, S. (Journal of Cardiac Surgery, 2016)
We report the use of a dilated right internal thoracic artery as a systemic-pulmonary shunt in a patient with a single ventricle who developed a systemic-pulmonary shunt stenosis following a modified Norwood's procedure. The systemic-to-pulmonary artery shunt was performed at 13 months of age, and the patient has stable oxygen saturations five years after the surgery. © 2016 Wiley Periodicals, Inc.

Endothelial Function and Arterial Stiffness Relate to Functional Outcomes in Adolescent and Young Adult Fontan Survivors - Goldstein, B.H.; Urbina, E.M.; Khoury, P.R.; Gao, Z.; Amos, M.A.; Mays, W.A.; Redington, A.N.; Marino, B.S. (Journal of the American Heart Association, 2016)
Background: Fontan survivors demonstrate diminished vascular function and functional outcomes, but the relationships between these measures have not been established. Methods and Results: We performed a cross-sectional study of 60 Fontan survivors (52% male) with a mean age of 13.9±4.1 years and mean Fontan duration of 9.9±4.2 years. Multimodality assessment of endothelial function (reactive hyperemia index and flow-mediated dilation) and arterial stiffness (augmentation index and baseline pulse amplitude) was performed with peripheral arterial tonometry and brachial flow-mediated dilation. Aerobic capacity was determined using cardiopulmonary exercise testing; mean peak and percentage of predicted oxygen consumption (VO2) were 27.8±7.6 mL/kg per minute and 71.0±21.2%, respectively. Quality of life and physical activity were assessed using the Pediatric Quality of Life Inventory (PedsQL) and the Physical Activity Questionnaire. Vascular measures served as predictor variables, whereas functional measures served as outcome variables. In all cases, worse vascular measures were associated with worse functional measures. Flow-mediated dilation-derived reactive hyperemia index (P<0.05) was positively associated with VO2 at anaerobic threshold. Peripheral arterial tonometry-derived baseline pulse amplitude (P<0.05) was negatively associated with the ratio of minute ventilation to carbon dioxide at anaerobic threshold. Flow-mediated dilation-derived reactive hyperemia index and peripheral arterial tonometry-derived augmentation index (P<0.05) were positively and negatively associated, respectively, with peak VO2. Maximum flow-mediated dilation (P<0.05) was positively associated with Physical Activity Questionnaire score. Peripheral arterial tonometry-derived augmentation index and baseline pulse amplitude (P<0.05) were negatively associated with parent-reported PedsQL total and physical heath summary scores. Conclusions: Increased arterial stiffness and decreased endothelial function are associated with lower aerobic capacity, physical activity, and quality of life in adolescent and young adult Fontan survivors. Understanding the cause-effect relationship between vascular function and functional outcomes is an important next step. © 2016 The Authors. Published on behalf of the American Heart Association, Inc., by Wiley Blackwell.
Keywords: Arterial stiffness; Endothelial function; Exercise capacity; Fontan procedure; Quality of life

Cardiopulmonary exercise test among children with congenital heart diseases: a multicenter study - Gavotto, A.; Amedro, P.; Guillaumont, S.; Vincenti, M.; De La Villeon, G.; Soulatges, C.; Bredy, C.; Matecki, S. (Archives of Cardiovascular Diseases Supplements, 2016)

Increasing cumulative exposure to volatile anesthetic agents is associated with poorer neurodevelopmental outcomes in children with hypoplastic left heart syndrome - Diaz, L.K.; Gaynor, J.W.; Koh, S.J.; Ittenbach, R.F.; Gerdes, M.; Bernbaum, J.C.; Zackai, E.H.; Clancy, R.R.; Rehman, M.A.; Pennington, J.W.; Burnham, N.; Spray, T.L.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2016)
Objectives Despite improved survival in children with hypoplastic left heart syndrome (HLHS), significant concern persists regarding their neurodevelopmental (ND) outcomes. Previous studies have identified patient factors, such as prematurity and genetic syndromes, to be associated with worse ND outcomes. However, no consistent relationships have been identified among modifiable management factors, including cardiopulmonary bypass strategies, and ND outcomes after cardiac surgery in infancy. Studies in immature animals, including primates, have demonstrated neurodegeneration and apoptosis in the brain after certain levels and extended durations of anesthetic exposure. Retrospective human studies have also suggested relationships between adverse ND effects and anesthetic exposure. Methods Cumulative minimum alveolar concentration hours (MAC-hrs) of exposure to volatile anesthetic agents (VAA) (desflurane, halothane, isoflurane, and sevoflurane) were collected from an anesthetic database and medical record review for 96 patients with HLHS or variants. ND testing was performed between ages 4 and 5 years, including full-scale IQ, verbal IQ, performance IQ, and processing speed. Four generalized linear modes were hypothesized a priori and tested using a Gaussian (normal) distribution with an identity link. Results Cumulative VAA exposure ranged from 0 to 35.3 MAC-hrs (median 7.5 hours). Using specified covariates identified previously as significant predictors of ND outcomes, statistically significant relationships were identified between total MAC-hrs exposure and worse full-scale IQ and verbal IQ scores (P's < .05) alone and after adjusting for relevant covariates. Conclusions Increased cumulative MAC-hrs exposure to VAA is associated with worse ND outcomes in certain domains in children with HLHS and variants. © 2016 The American Association for Thoracic Surgery
Keywords: anesthesia; congenital heart surgery; neurodevelopment; neurotoxicity

Impact of Surgical Complexity on Health-Related Quality of Life in Congenital Heart Disease Surgical Survivors - O'Connor, A.M.; Wray, J.; Tomlinson, R.S.; Cassedy, A.; Jacobs, J.P.; Jenkins, K.J.; Brown, K.L.; Franklin, R.C.; Mahony, L.; Mussatto, K.; Newburger, J.W.; Wernovsky, G.; et al. (Journal of the American Heart Association, 2016)
BACKGROUND: Surgical complexity and related morbidities may affect long-term patient quality of life (QOL). Aristotle Basic Complexity (ABC) score and Risk Adjustment in Congenital Heart Surgery (RACHS-1) category stratify the complexity of pediatric cardiac operations. The purpose of this study was to examine the relationship between surgical complexity and QOL and to investigate other demographic and clinical variables that might explain variation in QOL in pediatric cardiac surgical survivors. METHODS AND RESULTS: Pediatric Cardiac Quality of Life (PCQLI) study participants who had undergone cardiac surgery were included. The PCQLI database provided sample characteristics and QOL scores. Surgical complexity was defined by the highest ABC raw score or RACHS-1 category. Relationships among surgical complexity and demographic, clinical, and QOL variables were assessed using ordinary least squares regression. A total of 1416 patient-parent pairs were included. Although higher ABC scores and RACHS-1 categories were associated with lower QOL scores (P<0.005), correlation with QOL scores was poor to fair (r=-0.10 to -0.29) for all groups. Ordinary least squares regression showed weak association with R(2)=0.06 to R(2)=0.28. After accounting for single-ventricle anatomy, number of doctor visits, and time since last hospitalization, surgical complexity scores added no additional explanation to the variance in QOL scores. CONCLUSIONS: ABC scores and RACHS-1 categories are useful tools for morbidity and mortality predictions prior to cardiac surgery and quality of care initiatives but are minimally helpful in predicting a child's or adolescent's long-term QOL scores. Further studies are warranted to determine other predictors of QOL variation. © 2016 The Authors. Published on behalf of the American Heart Association, Inc., by Wiley Blackwell.
Keywords: Aristotle Basic Complexity; congenital heart disease surgery; quality of life; Risk Adjustment in Congenital Heart Surgery

Diagnosis of occult diastolic dysfunction late after the Fontan procedure using a rapid volume expansion technique - Averin, K.; Hirsch, R.; Seckeler, M.D.; Whiteside, W.; Beekman, R.H.; Goldstein, B.H. (Heart, 2016)
Objectives Diastolic dysfunction (DD), a key driver of long-term Fontan outcomes, may be concealed during standard haemodynamic evaluation. We sought to identify Fontan patients with occult DD using 'ventricular stress testing' with rapid volume expansion (RVE). Methods Cardiac catheterisation with RVE was performed routinely in Fontan patients between 11/2012 and 4/2015. Baseline and post-stress haemodynamic data were compared using t test, Mann-Whitney U test, Ï ‡ 2 and Fisher's exact tests. A post-stress ventricular end diastolic pressure (EDP) threshold of 15 mm Hg defined occult DD. Results Forty-six Fontan patients (48% female, median age 14.1 (IQR 9.1 to 21.3) years) were included. The median Fontan duration was 10.8 (IQR 5.1 to 17.8) years and dominant left ventricular morphology was present in 63% of patients. Volume expansion increased mean Fontan pressure (15.2±2.5 vs 12.4±2.2 mm Hg, p<0.001), pulmonary capillary wedge pressure (11.3±2.6 vs 7.9±2 mm Hg, p<0.001) and EDP (12.7±3.3 vs 8.5±2.1 mm Hg, p<0.001). Sixteen patients (35%) had occult DD, demonstrating higher baseline EDP (10.3±1.9 vs 7.6±1.5 mm Hg, p<0.001) and greater increase in EDP (6.3±2.4 vs 3.1±1.4 mm Hg, p<0.001) compared with patients without DD. Higher baseline EDP, lower baseline cardiac index and longer duration of Fontan circulation were associated with higher post-stress EDP. There were no complications related to RVE. Conclusions Ventricular stress testing by RVE is feasible, safe and identifies a subgroup of Fontan patients with occult DD. Higher baseline EDP and longer duration of Fontan circulation are associated with worse diastolic function. Future work is necessary to better understand the aetiology, associations and clinical implications of occult DD in Fontan survivors. © 2016 Published by the BMJ Publishing Group Limited. For permission to use.

Outcomes of Fontan conversion for failing Fontan circulation: Mid-term results - Park, H.K.; Shin, H.J.; Park, Y.H. (Interactive Cardiovascular and Thoracic Surgery, 2016)
OBJECTIVES We investigated the results of a revision of a previous Fontan connection to total cavopulmonary connection (TCPC) in patients with failing Fontan circulation. METHODS From July 1998 to April 2013, 21 patients who had failing Fontan circulation underwent revision of the previous Fontan operation to TCPC. The median age at TCPC conversion was 17.9 years (range, 4.6-38.1 years) and the median interval between initial Fontan operation and TCPC was 13.8 years (range, 2.1-25.4 years). There were 37 indications for Fontan revision in 21 patients. The indications were huge right atrium (n = 15), atrial arrhythmia (n = 8), intra-atrial thrombi (n = 6), protein-losing enteropathy (PLE) (n = 3) and more than mild atrioventricular valve regurgitation (n = 5). The previous Fontan operation was revised to extracardiac conduit replacement (n = 20) and intra-atrial lateral tunnel (n = 1). Concomitant surgery for atrial arrhythmia was performed in 8 patients. Fenestration was performed in 7 patients. The median follow-up duration was 7.1 years (range, 0.3-13.4 years). RESULTS There were no operative deaths and two late deaths occurred 7.9 and 8.1 years after operation. Actuarial 5- and 10-year survival rates were 92.3 and 83.1%, respectively. Postoperative complications included bleeding (n = 3), deep sternal infection (n = 1) and prolonged pleural effusion for more than 2 weeks (n = 5). During follow-up, atrial arrhythmia recurred in 6 patients, PLE recurred in 2 patients and pleural effusion recurred in 2 patients. All patients were classified as New York Heart Association Class I (n = 15) or Class II (n = 4). CONCLUSIONS Fontan conversion to TCPC in patients with failing Fontan circulation can be performed with low risk of morbidity and mortality. The procedure confers better quality of life and is functional for patients with failed Fontan circulation. © 2016 The Author 2016. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Fontan operation

Echocardiography and magnetic resonance imaging based strain analysis of functional single ventricles: a study of intra- and inter-modality reproducibility - Ghelani, S.J.; Harrild, D.M.; Gauvreau, K.; Geva, T.; Rathod, R.H. (International Journal of Cardiovascular Imaging, 2016)
The purpose of this study was to measure reproducibility in strain measurements by echocardiography and cardiac magnetic resonance imaging (CMR) in functional single ventricles in the Fontan circulation. Fontan echocardiograms and CMRs between 1/2005 and 6/2013 were analyzed retrospectively. Patients were included if studies occurred <1 year apart and without interim catheter-based or surgical intervention. Global peak systolic circumferential (GCS) and longitudinal (GLS) strain, and strain rates (GCSR and GLSR) were measured by speckle or feature tracking (echocardiogram vs. CMR) using commercial software. 134 study pairs were identified; 74 with dominant left and 60 with dominant right ventricles. Agreement for strain and strain rate between echocardiogram and CMR was modest for circumferential measurements, concordance correlation coefficient (Rc) = 0.56 for GCS, 0.44 for GCSR; and low for longitudinal measurements, Rc = 0.34 for GLS, and 0.27 for GLSR. There was good inter-observer agreement (n = 30) for strain measurements by echocardiogram and CMR (echocardiogram GCS Rc = 0.84, echocardiogram GLS Rc = 0.79, CMR GCS Rc = 0.94, CMR GLS Rc = 0.75). Inter-observer agreement for strain rate was slightly lower (echocardiogram GCSR Rc = 0.79, echocardiogram GLSR Rc = 0.73, CMR GCSR Rc = 0.93, CMR GLSR Rc = 0.54). Coefficients for intra-observer agreement for these variables were similar to inter-observer agreement. In conclusion, intra-modality reproducibility for strain assessment in functional single ventricles in the Fontan circulation is high, measured both by echocardiography and CMR; inter-modality reproducibility, however, is modest. These findings caution against mixing values from multiple modalities in the long-term assessment of patient health in this population. © 2016, Springer Science+Business Media Dordrecht.
Keywords: Congenital heart disease; Fontan; Single ventricle; Strain

Reversing left bronchus obstruction by compression of a pulmonary artery stent - Brown, S.C.; Proesmans, M.; Gewillig, M. (Catheterization and Cardiovascular Interventions, 2016)
We report a case where endovascular stenting as part of the treatment of complex cardiovascular disease led to airway compression. Using a novel technique, this was successfully reversed. Simultaneous inflations of two balloons—one in the obstructed bronchus and one in the aorta combined with external compression of the chest—resulted in compression the stent. This report illustrates that by thinking “out of the box” and bearing in mind spatial relationships inside the chest, it is possible to diminish the anterior–posterior diameters of a stent. This intervention proved to be successful with relief of the left bronchial compression and improvement of chronic airway infection. © 2016 Wiley Periodicals, Inc. © 2016 Wiley Periodicals, Inc.
Keywords: angioplasty; balloon; compression; obstruction; stent

Physics-driven impeller designs for a novel intravascular blood pump for patients with congenital heart disease - Chopski, S.G.; Fox, C.S.; McKenna, K.L.; Riddle, M.L.; Kafagy, D.H.; Stevens, R.M.; Throckmorton, A.L. (Medical Engineering and Physics, 2016)
Mechanical circulatory support offers an alternative therapeutic treatment for patients with dysfunctional single ventricle physiology. An intravascular axial flow pump is being developed as a cavopulmonary assist device for these patients. This study details the development of a new rotating impeller geometry. We examined the performance of 8 impeller geometries with blade stagger or twist angles varying from 100° to 800° using computational methods. A refined range of blade twist angles between 300° and 400° was then identified, and 4 additional geometries were evaluated. Generally, the impeller designs produced 4-26. mmHg for flow rates of 1-4. L/min for 6000-8000 RPM. A data regression analysis was completed and found the impeller with 400° of blade twist to be the superior performer. A hydraulic test was conducted on a prototype of the 400° impeller, which generated measurable pressure rises of 7-28. mmHg for flow rates of 1-4. L/min at 6000-8000 RPM. The findings of the numerical model and experiment were in reasonable agreement within approximately 20%. These results support the continued development of an axial-flow, mechanical cavopulmonary assist device as a new clinical therapeutic option for Fontan patients. © 2016 IPEM.
Keywords: Blood pump; CFD; Computational fluid dynamics; Heart pump; Mechanical circulatory assistance; Pediatric circulatory support; Rotary blood pump

Magnetic resonance imaging catheter stress haemodynamics post-Fontan in hypoplastic left heart syndrome - Pushparajah, K.; Wong, J.K.; Bellsham-Revell, H.R.; Hussain, T.; Valverde, I.; Bell, A.; Tzifa, A.; Greil, G.; Simpson, J.M.; Kutty, S.; Razavi, R. (European Heart Journal Cardiovascular Imaging, 2016)
Aims Exercise limitation is common post-Fontan. Hybrid X-ray and magnetic resonance imaging (XMR) catheterization allows haemodynamic assessment by means of measurement of ventricular volumes and flow in major vessels with simultaneous invasive pressures.We aim to assess haemodynamic response to stress in patients with hypoplastic left heart syndrome (HLHS) post-Fontan. Methods and results Prospective study of 13 symptomatic children (NHYA 2) with HLHS post-Fontan using XMR catheterization. Three conditions were applied: baseline (Stage 1), dobutamine at 10 mg/kg/min (Stage 2), and dobutamine at 20 μg/kg/min (Stage 3). Seven consecutive patients received inhaled nitric oxide (iNO) at peak stress. Control MRI data were from normal healthy adults. In the HLHS patients, baseline mean pulmonary vascular resistance (PVR) was 1.51±0.59WU m2 and aortopulmonary collateral flow was 17.7±13.6% of systemic cardiac output. Mean right ventricular end-diastolic pressure was 6.7±2.5 mmHg which did not rise with stress. Cardiac index (CI) increased at Stage 2 in HLHS (40%) and controls (61%) but continued to increase at Stage 3 only in controls (19%) but not in HLHS. The blunted rise in CI in HLHS was due to a continuing fall in end-diastolic volume throughout stress, with no significant change in PVR or CI at peak stress in response to iNO. Conclusion Cardiac output post-Fontan in HLHS at peak stress is blunted due to a limitation in preload which is not responsive to inhaled pulmonary vasodilators in the setting of normal PVR. © 2016 The Author.
Keywords: dobutamine; Fontan; hypoplastic left heart syndrome; MRI; pulmonary vascular resistance

Thrombus in hypoplastic aorta: An uncommon cause of acute myocardial infarction - Keraliya, A.R.; Murphy, D.J.; Steigner, M.L.; Blankstein, R. (Journal of Cardiovascular Computed Tomography, 2016)
A coronary artery embolism is an uncommon non-atherosclerotic cause of acute myocardial infarction. We present a case of coronary artery embolism in a patient with past history of hypoplastic left heart syndrome that was initially palliated via a modified Blalock–Taussig shunt followed by a Fontan anastomosis and Damus–Kaye–Stansel type anastomosis of the pulmonary valve to the ascending hypoplastic aorta. In this case we demonstrate usefulness of cardiac CT to delineate the patient's complex anatomy, identify the presence and etiology of a thromboembolic event, as well as assess for appropriate response to anticoagulation therapy. © 2016 Society of Cardiovascular Computed Tomography
Keywords: Cardiac CT; Coronary artery embolism; Hypoplastic left heart syndrome

Executive functioning and school performance among pediatric survivors of complex congenital heart disease - Gerstle, M.; Beebe, D.W.; Drotar, D.; Cassedy, A.; Marino, B.S. (Journal of Pediatrics, 2016)
Objective To investigate the presence and severity of real-world impairments in executive functioning - responsible for children's regulatory skills (metacognition, behavioral regulation) - and its potential impact on school performance among pediatric survivors of complex congenital heart disease (CHD). Study design Survivors of complex CHD aged 8-16 years (n = 143) and their parents/guardians from a regional CHD survivor registry participated (81% participation rate). Parents completed proxy measures of executive functioning, school competency, and school-related quality of life (QOL). Patients also completed a measure of school QOL and underwent IQ testing. Patients were categorized into 2 groups based on heart lesion complexity: 2-ventricle or single-ventricle. Results Survivors of complex CHD performed significantly worse than norms for executive functioning, IQ, school competency, and school QOL. Metacognition was more severely affected than behavioral regulation, and metacognitive deficits were more often present in older children. Even after taking into account demographic factors, disease severity, and IQ, metacognition uniquely and strongly predicted poorer school performance. In exploratory analyses, patients with single-ventricle lesions were rated as having lower school competency and school QOL, and patients with 2-ventricle lesions were rated as having poorer behavioral regulation. Conclusions Survivors of complex CHD experience greater executive functioning difficulties than healthy peers, with metacognition particularly impacted and particularly relevant for day-to-day school performance. Especially in older children, clinicians should watch for metacognitive deficits, such as problems with organization, planning, self-monitoring, and follow-through on tasks. © 2016 Elsevier Inc. All rights reserved.
Keywords: cardiac; child; cognitive; neuropsychology; scholastic

Experiences of informational needs and received information following a prenatal diagnosis of congenital heart defect - Carlsson, T.; Bergman, G.; Wadensten, B.; Mattsson, E. (Prenatal Diagnosis, 2016)
Objective: To explore the need for information and what information was actually received following prenatal diagnosis of a congenital heart defect, in a country where termination of pregnancy beyond 22weeks of gestation is not easily possible because of legal constraints. Methods: Twenty-six Swedish-speaking pregnant women (n=14) and partners (n=12) were consecutively recruited for semi-structured telephone interviews following the prenatal diagnosis of a congenital heart defect. Data were analyzed using content analysis. Results: Although high satisfaction with the specialist information was described, the information was considered overwhelming and complex. Objective, honest, and detailed information about multiple subjects were needed, delivered repeatedly, and supplemented by written information/illustrations. Eighteen respondents had used the Internet to search for information and identified issues involving searching difficulties, low quality, and that it was too complex, insufficient, or unspecific. Those who terminated their pregnancy criticized that there was a lack of information about termination of pregnancy, both from health professionals and online sources, resulting in unanswered questions and unpreparedness. Conclusion: Individuals faced with a prenatal diagnosis of a congenital heart defect need individualized and repeated information. These needs are not all adequately met, as individuals are satisfied with the specialist consultation but left with unanswered questions regarding pregnancy termination. What's Already Known About This Topic? The introduction of ultrasound screening during the second trimester of pregnancy has increased the detection rate of major congenital heart defects. Information matched to individual needs is crucial for women to cope with the situation following a prenatal diagnosis. What Does This Study Add? There is a need for information on multiple subjects following the prenatal diagnosis of congenital heart defect, including termination of pregnancy. Although information is available on the Internet on congenital heart defects, it is not easily searchable and its quality may be less than desired. Apparently, there is insufficient information about termination of pregnancy following the prenatal diagnosis of congenital heart defect. © 2016 John Wiley & Sons, Ltd.

Creating a Fontan fenestration in a child with dextrocardia and interrupted inferior vena cava - Charlagorla, P.; Breinholt, J.P. (Annals of Pediatric Cardiology, 2016)
Plastic bronchitis is a rare life-threatening complication of the Fontan operation. Transcatheter Fontan fenestration can ameliorate symptoms by decompressing elevated venous pressures. Transcatheter creation of a fenestration can be technically challenging in cases with complex venous anatomy. We report a case of a 5-year-old boy with heterotaxy, dextrocardia with unbalanced atrioventricular canal (AVC), atrial and visceral situs inversus, left-sided superior vena cava (SVC), and left-sided interrupted inferior vena cava (IVC) with azygos continuation. With few modifications to the equipment, a successful Fontan fenestration with stent implantation was performed via transjugular approach. At 2-year follow-up, his symptoms of plastic bronchitis improved significantly.
Keywords: Fenestration; heterotaxy; lateral tunnel Fontan; plastic bronchitis; transjugular approach

Risk Factors and Clinical Significance of Lymphopenia in Survivors of the Fontan Procedure for Single-Ventricle Congenital Cardiac Disease - Morsheimer, M.M.; Rychik, J.; Forbes, L.; Dodds, K.; Goldberg, D.J.; Sullivan, K.; Heimall, J.R. (Journal of Allergy and Clinical Immunology: In Practice, 2016)
Background: Congenital cardiac anomalies are associated with immunologic perturbations. Surgical thymectomy, thoracic duct manipulation, and protein- losing enteropathy (PLE), a condition related to stressed Fontan hemodynamics, presumably contribute to low peripheral absolute lymphocyte counts (ALCs) and quantitative immunoglobulins. Clinical significance of lymphopenia and hypogammaglobulinemia in single-ventricle survivors requires additional study. Objective: Although immunologic laboratory anomalies are common in this population, we hypothesize that clinically significant immunodeficiency requiring intervention is rarely required. Methods: A retrospective chart review of the immunologic parameters of patients enrolled in the Single Ventricle Survivorship Program (SVSP) at the Children's Hospital of Philadelphia was performed. Results: The age range of the 178 SVSP patients was 3 to 26 years, with a median of 10.8 years. Most of the SVSP patients had some degree of lymphopenia. In the non-PLE group, the range of ALCs varied from 530 to 5322 cells/μL, with 17 patients without PLE maintaining an ALC of less than 1000 cells/μL. Among those with PLE, the median ALC and the IgG level were lower (672 cells/μL and 200 mg/dL, respectively) than in those without (1610 cells/μL and 868 mg/dL, respectively). Despite lymphopenia in the majority, few were severely clinically affected: 24% had delayed clearance of cutaneous viral infections, 63% had atopy, and 1 died of EBV-associated Hodgkin lymphoma. Immunoglobulin replacement was clinically indicated for 3 patients, 1 of whom had common variable immunodeficiency. Four patients with normal splenic function were treated with daily antibiotic prophylaxis. Conclusions: Patients with repaired single-ventricle physiology often demonstrate T-cell lymphopenia and hypogammaglobulinemia. A significant portion of patients without PLE also have lymphopenia. The most common clinical manifestation was delayed clearance of cutaneous viral infections, but significant systemic opportunistic infections were not seen despite laboratory abnormalities and lack of antimicrobial prophylaxis. © 2016 Elsevier Inc.
Keywords: Fontan; Hypogammaglobulinemia; Protein-losing enteropathy (PLE); Secondary immunodeficiency; Single ventricle; T-cell lymphopenia; Warts

Effect of Ambrisentan on Exercise Capacity in Adult Patients after the Fontan Procedure - Cedars, A.M.; Saef, J.; Peterson, L.R.; Coggan, A.R.; Novak, E.L.; Kemp, D.; Ludbrook, P.A. (American Journal of Cardiology, 2016)
The Fontan operation is a common end point for children born with a single functional ventricle. Fontan patients typically experience physiological deterioration leading to transplant or death in their third or fourth decades of life. This deterioration is partially attributable to progressive increases in pulmonary vascular resistance (PVR) and as such endothelin receptor antagonists, which are known to decrease pulmonary vascular resistance, have been proposed as potentially beneficial in this population. We conducted a single-center, randomized, double-blind, placebo-controlled, crossover study of 12 weeks of ambrisentan therapy (10 mg per day) versus placebo to test the hypothesis that endothelin receptor antagonism will improve cardiopulmonary exercise test parameters and 36-item short form (SF-36) assessed quality of life in adult Fontan patients. Twenty-eight patients entered the trial, 19 patients completed the protocol. Ambrisentan therapy improved peak oxygen consumption by 1.7 ml/kg/min in patients who achieved a respiratory exchange ratio of >0.95 (p = 0.05) and decreased the slope of the ventilatory equivalent ratio for oxygen (-2.8, p = 0.019) in all completers. It did not change SF-36 physical function score compared with placebo (p = 0.28). Ambrisentan therapy resulted in a decrease in (-1.4 g/dl, p <0.001) with no change in liver or renal function. Therapy was generally well tolerated, with no greater rate of side effects than placebo. In conclusion, ambrisentan is well tolerated and improves exercise capacity in adult Fontan patients. © 2016 Elsevier Inc. All rights reserved.

Neurodevelopmental outcome in hypoplastic left heart syndrome: Impact of perioperative cerebral tissue oxygenation of the Norwood procedure - Hansen, J.H.; Rotermann, I.; Logoteta, J.; Jung, O.; Dütschke, P.; Scheewe, J.; Kramer, H.-H. (Journal of Thoracic and Cardiovascular Surgery, 2016)
Objectives Patients with hypoplastic left heart syndrome are at risk for neurodevelopmental impairment. Hypoxic-ischemic brain injury during neonatal treatment might be a relevant cause. We evaluated the association between cerebral oxygenation in the perioperative course of the Norwood procedure and neurodevelopmental outcome. Methods Cerebral tissue oxygen saturation (ScO2) was obtained by near-infrared spectroscopy for 24 hours before and 48 hours after surgery in 43 patients. Full-scale, verbal, and performance IQ scores were evaluated with the Wechsler Preschool and Primary Scale of Intelligence at a median of 4.5 years (range, 3.5-6.8 years). Cognitive functions were assessed with the German Kognitiver Entwicklungstest für das Kindergartenalter (KET-KID). Results Mean IQ scores and KET-KID percentile ranks were in the lower-normal range (full-scale IQ, 94 ± 11; verbal IQ, 97 ± 13; performance IQ, 93 ± 9; KET-KID global, 42 ± 27; verbal, 48 ± 29; nonverbal, 37 ± 23). Scores were below average (full scale IQ <85 or KET-KID <16th percentile) in 12 cases. Mean preoperative ScO2 was lower in patients scoring below average (56.8% ± 7.1% vs 61.7% ± 5.8%; P =.028) and was correlated with full-scale IQ (r = 0.495; P =.001), verbal IQ (r = 0.524; P =.001), and performance IQ (r = 0.386; P =.012) scores, and with global (r = 0.360; P =.018) and verbal (r = 0.395, P =.009) KET-KID scores. A relationship between IQ or KET-KID scores and postoperative ScO2 was not found. Gestational age, head circumference z-score, age at surgery, and postoperative length of stay were associated with IQ and KET-KID scores. Conclusions Neurodevelopmental outcome was in the lower-normal range. Along with innate patient factors, preoperative cerebral tissue oxygenation is likely an important determinant of cognitive development. © 2016 The American Association for Thoracic Surgery.
Keywords: hypoplastic left heart syndrome, developmental outcome, near-infrared spectroscopy

Pulmonary venous hypertension may allow delayed palliation of single ventricle physiology with pulmonary hypertension - Kalantre, A.; Sunil, G.S.; Kumar, R.K. (Annals of Pediatric Cardiology, 2016)
Pulmonary vascular disease develops early in untreated single ventricle patients with increased pulmonary flow. Pulmonary artery (PA) banding is done at a young age in these patients in order to protect the lung vasculature and maintain low pulmonary artery pressures (PAP) and pulmonary vascular resistance (PVR). This also enables future completion of the single ventricle palliation. Pulmonary venous hypertension (PVH) secondary to left sided obstruction if present in addition in this setting contributes to the pulmonary arterial hypertension (PAH) but involves an element of reversibility of the PAH if the obstruction is relieved. We present two cases of single ventricle both of who re-presented late with PAH and PVH (secondary to mitral valve obstruction) and underwent delayed PA banding at 9.5 and 4.5 years of age respectively. Both patients however had different outcomes. The patient undergoing PA banding at 9.5 years successfully underwent a cavo-pulmonary shunt at the age of 12 years. The patient with PA banding at 4.5 years however, has residual PAH that presently precludes a cavo-pulmonary shunt.
Keywords: Delayed pulmonary artery banding; hemodynamics; pulmonary venous hypertension (PVH); single ventricle

Supporting pediatric patients with short-term continuous-flow devices - Conway, J.; Al-Aklabi, M.; Granoski, D.; Islam, S.; Ryerson, L.; Anand, V.; Guerra, G.; Mackie, A.S.; Rebeyka, I.; Buchholz, H. (Journal of Heart and Lung Transplantation, 2016)
Background Short-term continuous-flow ventricular assist devices (STCF-VADs) are increasingly being used in the pediatric population. However, little is known about the outcomes in patients supported with these devices. Methods All pediatric patients supported with a STCF-VAD, including the Thoratec PediMag or CentriMag, or the Maquet RotaFlow, between January 2005 and May 2014, were included in this retrospective single-center study. Results Twenty-seven patients (15 girls [56%]) underwent 33 STCF-VAD runs in 28 separate hospital admissions. The STCF-VAD was implanted 1 time in 23 patients (85%), 2 times in 2 patients (7%), and 3 times in 2 patients (7%). Implantation occurred most commonly in the context of congenital heart disease in 14 runs (42.2%), cardiomyopathy in 11 (33%), and after transplant in 6 (18%). The median age at implantation was 1.7 (interquartile range [IQR] 0.1, 4.1) years, and median weight was 8.9 kg (IQR 3.7, 18 kg). Patients were supported for a median duration of 12 days (IQR 6, 23 days) per run; the longest duration was 75 days. Before implantation, 15 runs (45%) were supported by extracorporeal membrane oxygenation (ECMO). After implantation, an oxygenator was required in 20 runs (61%) and continuous renal replacement therapy in 21 (64%). Overall, 7 runs (21%) resulted in weaning for recovery, 14 (42%) converted to a long-term VAD, 4 (12%) resulted in direct transplantation, 3 (9%) were converted to ECMO, and 5 (15%) runs resulted in death on the device or within 1 month after decannulation. The most common complication was bleeding requiring reoperation in 24% of runs. In addition, 18% of runs were associated with neurologic events and 15% with a culture-positive infection. Hospital discharge occurred in 19 of 28 STCF-VAD admissions (67%). In follow-up, with a median duration of 9.2 months (IQR 2.3, 38.3 months), 17 patients (63%) survived. Conclusions STCF-VADs can successfully bridge most pediatric patients to recovery, long-term device, or transplant, with an acceptable complication profile. Although these devices are designed for short-term support, longer support is possible and may serve as an alternative approach to patients not suitable for the current long-term devices. © 2016 International Society for Heart and Lung Transplantation.
Keywords: CentriMag; continuous-flow; pediatric patients; PediMag; RotaFlow; short-term support; ventricular assist device

The use of pre-operative halo traction to minimize risk for correction of severe scoliosis in a patient with Fontan circulation: a case report and review of literature - Chan, C.Y.W.; Lim, C.Y.; Shahnaz Hasan, M.; Kwan, M.K. (European Spine Journal, 2016)
Purpose: Patients with Fontan circulation have increased cardio-respiratory risk during major spinal surgery. We report a case of severe scoliosis with a Cobb angle of 123.3° in a 16-year-old boy with Fontan circulation treated with single stage posterior segmental pedicle screw instrumentation and fusion. Methods: Case report. Results: The use pre-operative halo-ring traction for a duration of 6 weeks in this case lead to improvement in cobb angle from 123.3°, kyphotic angle 87.1° to cobb angle of 78.0°, kyphotic angle 57.2° (on bending and stress films). The operation was completed in 150 min, blood loss 1050 ml (25 ml/kg), and cell salvage of 490 ml. He was immediately extubated post correction, but monitored in ICU for a day. Total length of stay was 8 days without any perioperative morbidity or allogeneic blood transfusion. Final post-operative radiograph showed a cobb angle of 44.2°, kyphotic angle 22.8°. Follow up at 27 months showed solid union with no significant loss of correction. Conclusion: From this case experience, pre-operative halo traction is a useful surgical strategy in patients with Fontan circulation with severe kyposcoliosis to achieve adequate correction without additional osteotomies to minimize the risk of surgical correction. © 2016, Springer-Verlag Berlin Heidelberg.
Keywords: Fontan Circulation; Halo Traction; Scoliosis

Harnessing teams and technology to improve outcomes in infants with single ventricle - Shirali, G.; Erickson, L.; Apperson, J.; Goggin, K.; Williams, D.; Reid, K.; Bradley-Ewing, A.; Tucker, D.; Bingler, M.; Spertus, J.; Rabbitt, L.; Stroup, R. (Circulation: Cardiovascular Quality and Outcomes, 2016)
Infants with single ventricle require staged cardiac surgery, with stage I typically performed shortly after birth, stage II at 4 to 6 months of age, and stage III at 3 to 5 years of age. There is a high risk of interstage mortality and morbidity after infants are discharged from the hospital between stages I and II. Traditional home monitoring requires caregivers to record measurements of weight and oxygen saturation into a binder and requires families to assume a surveillance role. We have developed a tablet PC-based solution that provides secure and nearly instantaneous transfer of patient information to a cloud-based server, with the capacity for instant alerts to be sent to the caregiver team. The cloud-based IT infrastructure lends itself well to being able to be scaled to multiple sites while maintaining strict control over the privacy of each site. All transmitted data are transferred to the electronic medical record daily. The system conforms to recently released Food and Drug Administration regulation that pertains to mobile health technologies and devices. Since this platform was developed in March 2014, 30 patients have been monitored. There have been no interstage deaths. The experience of care providers has been unanimously positive. The addition of video has added to the use of the monitoring program. Of 30 families, 23 expressed a preference for the tablet PC over the notebook, 3 had no preference, and 4 preferred the notebook to the tablet PC. © 2016 American Heart Association, Inc.
Keywords: caregivers; congenital; mortality; survival; telemedicine

Long-Term Serial Follow-Up of Pulmonary Artery Size and Wall Shear Stress in Fontan Patients - Bossers, S.S.M.; Cibis, M.; Kapusta, L.; Potters, W.V.; Snoeren, M.M.; Wentzel, J.J.; Moelker, A.; Helbing, W.A. (Pediatric Cardiology, 2016)
Pulmonary arterial (PA) flow is abnormal after the Fontan operation and is marked by a lack of pulsatility. We assessed the effects of this abnormal flow on the size and function of the PA’s in Fontan patients in long-term serial follow-up. Twenty-three Fontan patients with serial follow-up were included. Median age was 11.1 (9.5–16.0) years at baseline and 15.5 (12.5–22.7) years at follow-up. Median follow-up duration was 4.4 (4.0–5.8) years. Flow and size of the left pulmonary artery were determined using phase-contrast MRI. From this wall shear stress (WSS), distensibility and pulsatility were determined. A group of healthy peers was included for reference. Flow and pulsatility were significantly lower in patients than in controls (p < 0.001). Mean area was comparable in patients and controls, but distensibility was significantly higher in controls (p < 0.001). Mean and peak WSS were significantly lower in Fontan patients (p < 0.001). Between baseline and follow-up, there was a significant increase in normalized flow (15.1 (14.3–19.1) to 18.7 (14.0–22.6) ml/s/m2, p = 0.023). Area, pulsatility, distensibility and WSS did not change, but there was a trend toward a lower mean WSS (p = 0.068). Multivariable regression analysis showed that flow, area and age were important predictors for WSS. WSS in Fontan patients is decreased compared to healthy controls and tends to decrease further with age. Pulsatility and distensibility are significantly lower compared to healthy controls. Pulmonary artery size, however, is not significantly different from healthy controls and long-term growth after Fontan operation is proportionate to body size. © 2016, The Author(s).
Keywords: Cardiac magnetic resonance imaging; Fontan; Pulmonary arteries; Shear stress; TCPC

A cohort study of women with a Fontan circulation undergoing preconception counselling - Cauldwell, M.; Von Klemperer, K.; Uebing, A.; Swan, L.; Steer, P.J.; Babu-Narayan, S.V.; Gatzoulis, M.A.; Johnson, M.R. (Heart, 2016)
Objective To describe outcomes for women with a Fontan circulation attending preconception counselling (PCC). Exploring (1) impact of counselling on decision to become pregnant; (2) pregnancy rates in those opting for pregnancy and (3) short-term and long-term outcome of those who succeeded in becoming pregnant. Methods Retrospective review of women aged 16-45 years with a Fontan circulation from 1994 to 2014. Results 58 women were offered PCC, 3 declined and 55 received PCC. Following PCC, 15 opted against conception, 16 decided to delay pregnancy, 19 attempted pregnancy and 5 were lost to follow-up. Of the 19 women, 14 succeeded, becoming pregnant a total of 43 times (median 1, range 1-9). Of these, 6 miscarried all pregnancies. 8 carried 14 pregnancies to viability. Baseline hypoxaemia and cardiac disease in pregnancy (CARPREG) score was similar in those opting for and against pregnancy, but CARPREG score was better in those delaying conception. Women exclusively miscarrying or unable to conceive were more likely to have baseline hypoxaemia and greater CARPREG score. Cardiac complications included arrhythmia requiring treatment (n=4) and one thromboembolism. Obstetric complications were greater in women with a Fontan circulation, 10 preterm births (<37 weeks) and 8 small for gestational age babies (<10th centile). There was one neonatal death. At follow-up, there was no deterioration in clinical status as determined by echo. Conclusions Most women accept PCC and decided to pursue pregnancy; in some cases, this was despite being advised of a poor prognosis. Pregnancy outcome was related to baseline hypoxia and CARPREG scores.

Percutaneous lymphatic embolization of abnormal pulmonary lymphatic flow as treatment of plastic bronchitis in patients with congenital heart disease - Dori, Y.; Keller, M.S.; Rome, J.J.; Gillespie, M.J.; Glatz, A.C.; Dodds, K.; Goldberg, D.J.; Goldfarb, S.; Rychik, J.; Itkin, M. (Circulation, 2016)
Background - Plastic bronchitis is a potentially fatal disorder occurring in children with single-ventricle physiology, and other diseases, as well, such as asthma. In this study, we report findings of abnormal pulmonary lymphatic flow, demonstrated by MRI lymphatic imaging, in patients with plastic bronchitis and percutaneous lymphatic intervention as a treatment for these patients. Methods and Results - This is a retrospective case series of 18 patients with surgically corrected congenital heart disease and plastic bronchitis who presented for lymphatic imaging and intervention. Lymphatic imaging included heavy T2-weighted MRI and dynamic contrast-enhanced magnetic resonance lymphangiogram. All patients underwent bilateral intranodal lymphangiogram, and most patients underwent percutaneous lymphatic intervention. In 16 of 18 patients, MRI or lymphangiogram or both demonstrated retrograde lymphatic flow from the thoracic duct toward lung parenchyma. Intranodal lymphangiogram and thoracic duct catheterization was successful in all patients. Seventeen of 18 patients underwent either lymphatic embolization procedures or thoracic duct stenting with covered stents to exclude retrograde flow into the lungs. One of the 2 patients who did not have retrograde lymphatic flow did not undergo a lymphatic interventional procedure. A total of 15 of 17(88%) patients who underwent an intervention had significant symptomatic improvement at a median follow-up of 315 days (range, 45-770 days). The most common complication observed was nonspecific transient abdominal pain and transient hypotension. Conclusions - In this study, we demonstrated abnormal pulmonary lymphatic perfusion in most patients with plastic bronchitis. Interruption of the lymphatic flow resulted in significant improvement of symptoms in these patients and, in some cases, at least temporary resolution of cast formation. © 2016 American Heart Association, Inc.
Keywords: bronchitis; heart defects, congenital; lymphatic vessels; lymphography

Assessment of Quality of Life in Young Patients with Single Ventricle after the Fontan Operation - Uzark, K.; Zak, V.; Shrader, P.; McCrindle, B.W.; Radojewski, E.; Varni, J.W.; Daniels, K.; Handisides, J.; Hill, K.D.; Lambert, L.M.; Margossian, R.; Pemberton, V.L.; et al. (Journal of Pediatrics, 2016)
Objectives To assess self-reported quality of life (QOL) in a large multicenter cohort of adolescent and young adults surviving Fontan. Study design Cross-sectional. The Pediatric Quality of Life Inventory (PedsQL) was administered to 408 survivors of Fontan ages 13-25 years enrolled in the Pediatric Heart Network Fontan Follow-up Study. Subjects also completed either the Child Health Questionnaire (age <19 years) or Short Form Health Survey (age ≥19 years). PedsQL data were compared with matched controls without a chronic health condition. Correlations between the measures were examined. Results Mean PedsQL scores for subjects receiving Fontan were significantly lower than those for the control group for physical and psychosocial QOL (P <.001). Overall, 45% of subjects receiving Fontan had scores in the clinically significant impaired range for physical QOL with 30% in the impaired range for psychosocial QOL. For each 1 year increase in age, the physical functioning score decreased by an average of 0.76 points (P =.004) and the emotional functioning score decreased by an average of 0.64 points (P =.03). Among subjects ≥19 years of age, the physical functioning score decreased by an average of 2 points for each year increase in age (P =.02). PedsQL scale scores were significantly correlated with conceptually related Child Health Questionnaire (P <.001) and Short Form Health Survey scores (P <.001). Conclusions Survivors of Fontan are at risk for significantly impaired QOL which may decline with advancing age. Routine assessment of QOL is essential to inform interventions to improve health outcomes. The PedsQL allowed QOL assessment from pediatrics to young adulthood. Trial registration ClinicalTrials.gov: NCT00132782. © 2016 Elsevier Inc.

Assessing ST Segment Changes and Ischemia During Exercise Stress Testing in Patients with Hypoplastic Left Heart Syndrome and Fontan Palliation - Kyle, W.B.; Denfield, S.W.; Valdes, S.O.; Penny, D.J.; Bolin, E.H.; Lopez, K.N. (Pediatric Cardiology, 2016)
While exercise stress testing (EST) is an important tool, little is known about its use for determining ischemia in patients with hypoplastic left heart syndrome (HLHS) and Fontan palliation. We sought to determine the frequency of ST segment changes during EST in HLHS patients after Fontan and examine results of further testing performed in response to ST changes. A single-center chart review of HLHS patients post-Fontan from January 1995 to December 2012 was performed. Data collected included demographics, indications for EST, resting electrocardiogram findings, EST and echocardiogram results and outcomes. ESTs were evaluated for ST segment changes concerning for ischemia. Results of additional testing performed based on concerning EST findings were collected. Twenty-seven patients underwent 64 ESTs (mean 2.4 ESTs/patient). Median age at first EST was 9.6 years (range 6.2–16.4). EST was concerning for ischemia in 13 patients (48 %) on 25 (39 %) ESTs. Based on EST results, two patients had stress sestamibi testing, two underwent coronary angiography, and one had both. No reversible perfusion defects or coronary artery obstructions were demonstrated. No patient who underwent EST has died. ST segment depression was not associated with ventricular dysfunction prior to EST or at the end of follow-up (p > 0.05). In patients with HLHS post-Fontan palliation, ST segment depression on EST is common. In patients who underwent further testing, no evidence of ischemia or coronary abnormalities was found. Additional testing may not be necessary in all patients. © 2016, Springer Science+Business Media New York.
Keywords: Congenital heart disease; Exercise stress testing; Fontan; Hypoplastic left heart syndrome; Ischemia; ST segment abnormality

Does functional health status predict health-related quality of life in children after Fontan operation? - Dulfer, K.; Bossers, S.S.M.; Utens, E.M.W.J.; Duppen, N.; Kuipers, I.M.; Kapusta, L.; Van Iperen, G.; Schokking, M.; Ten Harkel, A.D.J.; Takken, T.; Helbing, W.A. (Cardiology in the Young, 2016)
Purpose It is important to identify those children with a Fontan circulation who are at risk for impaired health-related quality of life. We aimed to determine the predictive value of functional health status - medical history and present medical status - on both physical and psychosocial domains of health-related quality of life, as reported by patients themselves and their parents. Methods We carried out a prospective cross-sectional multi-centre study in Fontan patients aged between 8 and 15, who had undergone staged completion of total cavopulmonary connection according to a current technique before the age of 7 years. Functional health status was assessed as medical history - that is, age at Fontan, type of Fontan, ventricular dominance, and number of cardiac surgical procedures - and present medical status - assessed with magnetic resonance imaging, exercise testing, and rhythm assessment. Health-related quality of life was assessed with The TNO/AZL Child Questionnaire Child Form and Parent Form. Results In multivariate prediction models, several medical history variables, such as more operations post-Fontan completion, lower age at Fontan completion, and dominant right ventricle, and present medical status variables, such as smaller end-diastolic volume, a higher score for ventilatory efficiency, and the presence of sinus node dysfunction, predicted worse outcomes on several parent-reported and self-reported physical as well as psychosocial health-related quality of life domains. Conclusions Medical history and worse present medical status not only predicted worse physical parent-reported and self-reported health-related quality of life but also worse psychosocial health-related quality of life and subjective cognitive functioning. These findings will help in identifying patients who are at risk for developing impaired health-related quality of life. ©Cambridge University Press 2015.
Keywords: congenital heart disease; Fontan circulation; quality of life

Restrictive atrial septum after the Fontan procedure - Penford, G.; Quandt, D.; Stumper, O. (Cardiology in the Young, 2016)
In this study, three patients presenting with early or late postoperative Fontan complications were identified to suffer from restriction of the native atrial septum. This caused significant obstruction to pulmonary venous return and elevated systemic venous pressure. Dobutamine stress testing was used in one patient to identify this lesion. Transcatheter stenting was performed in the other two patients. Patients improved after relief of the obstruction. ©Cambridge University Press 2015.
Keywords: Fontan procedure; hypoplastic left heart syndrome; protein-losing enteropathy; stent

Can a Home-based Cardiac Physical Activity Program Improve the Physical Function Quality of Life in Children with Fontan Circulation? - Jacobsen, R.M.; Ginde, S.; Mussatto, K.; Neubauer, J.; Earing, M.; Danduran, M. (Congenital Heart Disease, 2016)
Objective: Patients after Fontan operation for complex congenital heart disease (CHD) have decreased exercise capacity and report reduced health-related quality of life (HRQOL). Studies suggest hospital-based cardiac physical activity programs can improve HRQOL and exercise capacity in patients with CHD; however, these programs have variable adherence rates. The impact of a home-based cardiac physical activity program in Fontan survivors is unclear. This pilot study evaluated the safety, feasibility, and benefits of an innovative home-based physical activity program on HRQOL in Fontan patients. Methods: A total of 14 children, 8-12 years, with Fontan circulation enrolled in a 12-week moderate/high intensity home-based cardiac physical activity program, which included a home exercise routine and 3 formalized in-person exercise sessions at 0, 6, and 12 weeks. Subjects and parents completed validated questionnaires to assess HRQOL. The Shuttle Test Run was used to measure exercise capacity. A Fitbit Flex Activity Monitor was used to assess adherence to the home activity program. Results: Of the 14 patients, 57% were male and 36% had a dominant left ventricle. Overall, 93% completed the program. There were no adverse events. Parents reported significant improvement in their child's overall HRQOL (P<.01), physical function (P<.01), school function (P=.01), and psychosocial function (P<.01). Patients reported no improvement in HRQOL. Exercise capacity, measured by total shuttles and exercise time in the Shuttle Test Run and calculated VO2max, improved progressively from baseline to the 6 and 12 week follow up sessions. Monthly Fitbit data suggested adherence to the program. Conclusion: This 12-week home-based cardiac physical activity program is safe and feasible in preteen Fontan patients. Parent proxy-reported HRQOL and objective measures of exercise capacity significantly improved. A 6-month follow up session is scheduled to assess sustainability. A larger study is needed to determine the applicability and reproducibility of these findings in other age groups and forms of complex CHD. © 2016 Wiley Periodicals, Inc.
Keywords: Congenital Heart Disease; Exercise; Fontan; Physical Activity; Quality of Life; Rehabilitation

The post-anesthetic care of pediatric patients with pulmonary hypertension - Chau, D.F.; Gangadharan, M.; Hartke, L.P.; Twite, M.D. (Seminars in Cardiothoracic and Vascular Anesthesia, 2016)
Few conditions make even the most experienced pediatric anesthesiologists take pause. Pulmonary hypertension is one such condition due to the associated high perioperative morbidity and mortality. Much is written about the intraoperative management of pediatric pulmonary hypertension. This article will instead focus on postoperative care and review the evidence in support of a risk stratification approach for the post-anesthetic disposition of these patients. The total risk for post-anesthetic adverse events includes the patient's baseline risk factors and the incremental risks imposed by the procedure and anesthetic. A proposal with recommendations to guide practitioners and a table summarizing relevant factors are provided. Last, the readers' attention is drawn to the heterogeneity of pulmonary hypertensive disease. Pulmonary arterial hypertension (precapillary) differs significantly from pulmonary venous hypertension (postcapillary); the anesthetic management for one may be relatively contraindicated in the other. Their dissimilarities justify the need to distinguish them for study and research endeavors. © SAGE Publications.
Keywords: cardiac anesthesia; children; hypertension; pediatric intensive care; perioperative mortality; postoperative care; postoperative complications; pulmonary artery pressure

Quality of Life of Pediatric Patients with Long QT Syndrome - Czosek, R.J.; Kaltman, J.R.; Cassedy, A.E.; Shah, M.J.; Vetter, V.L.; Tanel, R.E.; Wernovksy, G.; Wray, J.; Marino, B.S. (American Journal of Cardiology, 2016)
Children with long QT syndrome (LQTS) live with the risk of sudden death, activity restrictions, and the need for daily medications. We sought to evaluate the quality of life (QOL), self-perception, and behavior of patients with LQTS as perceived by both patients and their parents and identify predictors of lower QOL. QOL (Pediatric QOL Inventory [PedsQL] and Pediatric Cardiac Quality of Life Inventory [PCQLI]), self-perception, and behavioral inventories were completed by patients with LQTS and their parents. Comparison of PedsQL scores was made to published data for healthy children using t tests, and PCQLI scores were compared with those of patients with differing complexity of congenital heart disease. Mixed modeling was used for multivariable analysis. Sixty-one patients with LQTS were evaluated (age 13.6 ± 3.0 years; male 49%). Compared with healthy children, the PedsQL Total, Psychosocial, and Physical Health Summary scores were significantly lower for patients with LQTS and parent proxy reports (p ≤0.001). In general, PCQLI scores of patients with LQTS and parents were similar to those of patients with tetralogy of Fallot (p ≥0.2), lower than those of patients with bicuspid aortic valve (p ≤0.02), and higher than those of patients with single ventricle (p ≤0.03). Lower patient and parent PCQLI scores were associated with internalizing problems. For parents, the presence of a cardiac device and medication side effects were additionally associated with lower PCQLI scores. In conclusion, patients with LQTS and their parents report lower QOL than normal children secondary to physical and psychosocial factors. Increasing focus on the psychological well-being of these patients is needed in an effort to improve their QOL. © 2016 Elsevier Inc.

Results of Fontan operation in patients with congenitally corrected transposition of great arteries - Talwar, S.; Bansal, A.; Choudhary, S.K.; Kothari, S.S.; Juneja, R.; Saxena, A.; Airan, B. (Interactive Cardiovascular and Thoracic Surgery, 2016)
OBJECTIVES The purpose of this study was to examine the outcome after the Fontan operation in patients with congenitally corrected transposition of great arteries with ventricular septal defect and pulmonary stenosis (ccTGA-VSD-PS). METHODS Patient- and procedure-related variables were analysed in 23 patients with ccTGA-VSD-PS operated between April 2003 and April 2015. RESULTS The mean age was 14.07 ± 6.38 years (range 4-23, median 11 years), with 82% patients being male (19/23). Dextrocardia was present in 52% (12/23) of patients and left superior vena cava was present in 26% (6/23) of patients. Most patients underwent extracardiac Fontan (n = 18), whereas in 5 patients lateral tunnel Fontan was performed. All patients received polytetrafluoroethylene grafts of size 18-22 mm for extracardiac Fontan. In 8 patients, conduits were fenestrated to reduce the intraconduit pressure. The mean hospital stay was 15.7 ± 11.24 days (5-60, median 14 days). The most common cause for prolonged hospital stay was pleural effusion in 5 patients (21.7%). One 7-year old patient developed conduit thrombosis, intracranial bleed, seizures and died. The mean follow-up was 46.4.4 ± 32.2 months (range 8-142, median 42 months) and was available for 21 patients (91.3%). There was 1 mid-term non-cardiac death after 3 years of operation. Of the total, 85.7% (18/21) patients in follow-up are in NYHA class I, whereas 3 patients are in class II. The actuarial event-free survival rate was 81.8 ± 13.2% at 10 years. CONCLUSIONS In ccTGA-VSD-PS patients with non-routable VSD and in those with difficult options for biventricular repair, the Fontan approach provides satisfactory mid-term palliation. © The Author 2015.
Keywords: Anatomical repair; Corrected transposition; Fontan operation

Takotsubo cardiomyopathy in a 22-year-old single-ventricle patient - Derk, G.R.; Aboulhosn, J.; Reardon, L.C. (Texas Heart Institute Journal, 2016)
We report a highly unusual case of a 22-year-old woman with single-ventricle anatomy and a history of Fontan palliation who developed takotsubo cardiomyopathy. To our knowledge, takotsubo cardiomyopathy has not previously been described in a patient with single-ventricle anatomy, or more generally in any patient with congenital heart disease. The patient presented at our clinic for urgent examination after a 2-day history of chest pain that had begun upon the death of her dog. Invasive evaluation was refused by the patient; instead, she underwent electrocardiogram-gated coronary computed tomographic angiography, to rule out obstructive coronary disease. A physician who suspects takotsubo cardiomyopathy in a patient should look for new-onset chest pain and dyspnea coupled with these features: immediate onset of segmental akinesia in the midventricular or apical aspects of the heart, elevation of brain natriuretic peptide level 12 to 24 hours after onset of akinesia, elevation of troponin level 24 to 48 hours after onset, and disappearance of the segmental akinesia a few days after onset. © 2016 by the Texas Heart® Institute, Houston.
Keywords: Apical-ballooning syndrome; Cardiomyopathies/diagnosis; Congenital; Coronary vasospasm/complications; Female; Fontan procedure; Heart disease; Psychological/complications; Single ventricle; Stress; Takotsubo cardiomyopathy/diagnosis/epidemiology/therapy; Treatment outcome; Ventricular dysfunction/etiology/radiography

Effect of Tadalafil on Myocardial and Endothelial Function and Exercise Performance After Modified Fontan Operation - Sabri, M.-R.; Zolfi-Gol, A.; Ahmadi, A.; Haghjooy-Javanmard, S. (Pediatric Cardiology, 2016)
Better postoperative management of patients who have undergone single ventricle (SV) Fontan procedure could potentially reduce long-term complications and improve the quality of life for patients. The present study determined the effect of tadalafil on myocardial and endothelial function and exercise performance after modified Fontan operation. Patients who had undergone SV modified Fontan operation were enrolled in this clinical trial. The demographic characteristics of the patients were recorded. Before administration of tadalafil and after the trial, ventricular function (MPI, EF, FS, E/A, VTI), exercise performance, and endothelial function were evaluated for sonographic and biochemical markers (FMD, IMT, ICAM, VCAM, NO) using echocardiography, exercise testing, vascular ultrasonography, and biochemical measurements, respectively. A single dose of tadalafil of 1 mg/kg was administered daily for 6 weeks, and the functional class of the patients before and after tadalafil was determined. A total of 15 patients completed this clinical trial. Tadalafil was shown to have a significant effect on myocardial function, exercise performance, and improvement in NYHA functional class (p < 0.05) of study population. It had no significant effect on the biochemical variables and endothelial function except for IMT (p > 0.05), which decreased significantly after tadalafil administration (p < 0.05). The findings indicate that tadalafil is a safe, well-tolerated agent for the use after modified Fontan operation to improve myocardial function and exercise performance and possibly reduce long-term morbidity and mortality of patients. More conclusive results could be obtained from further study with a larger sample size and long-term follow-up. © 2015, Springer Science+Business Media New York.
Keywords: Endothelial function; Exercise; Fontan procedure; Single ventricle; Tadalafil

Effect of Sildenafil on Pressure–Volume Loop Measures of Ventricular Function in Fontan Patients - Butts, R.J.; Chowdhury, S.M.; Baker, G.H.; Bandisode, V.; Savage, A.J.; Atz, A.M. (Pediatric Cardiology, 2016)
Sildenafil has been reported to improve exercise capacity in Fontan patients, but the physiologic mechanisms behind these findings are not completely understood. The objective of this study was to study the acute effect of sildenafil on pressure–volume loop (PVL) measures of ventricular function in Fontan patients. Patients after Fontan operation who were presenting for a clinically indicated catheterization were enrolled. Patients were randomized in a double-blinded fashion to receive placebo (n = 9) or sildenafil (n = 10) 30–90 min prior to catheterization. PVLs were recorded using microconductance catheters at baseline and after infusion of dobutamine (10 mcg/kg/min). The primary outcome was change in ventriculoarterial (VA) coupling. For the entire cohort, VA coupling trended toward improvement with dobutamine (1.4 ± 0.4 to 1.8 ± 0.9, p = 0.07). End-systolic elastance showed improvement (2.6 ± 0.9 to 3.8 ± 1.4 mmHg m2/ml, p < 0.01) with dobutamine infusion. The cohorts had similar VA coupling at baseline (p = 0.32), but the sildenafil cohort trended toward having less of an improvement in VA coupling with dobutamine stress (p = 0.06). There were no differences between PVL measures of systolic or diastolic function between treatment groups, both at baseline and after dobutamine infusion. Patients with Fontan circulation had improved contractility and trended toward improvement in VA coupling with dobutamine stress. Acute sildenafil administration was not associated with improved PVL measurements of ventricular function in this population. These results suggest that clinical improvements seen with administration of sildenafil in Fontan patients are not associated with an acute improvement in ventricular function. Clinical Trial Registration: www.clinicaltrials.gov; Clinicaltrials.gov Identifier: NCT01815502. © 2015, Springer Science+Business Media New York.
Keywords: Fontan; Pressure–volume loop; Sildenafil; Single-ventricle heart disease

Neurocognitive development and behaviour in school-aged children after surgery for univentricular or biventricular congenital heart disease - Sarrechia, I.; Miatton, M.; De Wolf, D.; François, K.; Gewillig, M.; Meyns, B.; Vingerhoets, G. (European Journal of Cardio-thoracic Surgery, 2016)
OBJECTIVES: To assess the long-term neuropsychological and behavioural profile of school-aged children who were treated for univentricular heart (UVH) conditions or biventricular heart defect (BiVH) in infancy in a cross-sectional study design. METHODS: Sixty-three patients, 17 UVH (13 males, 4 females) and 46 BiVH (19 males, 27 females), were assessed at a mean age of 9.1 years (2.2 years) with an intelligence and neuropsychological test battery. Results were compared between subgroups (UVH, BiVH and a healthy control group). Associations between cognitive outcome, medical and socio-demographic factors were explored. Parents completed the Child Behavior Checklist (CBCL). RESULTS: Mean intelligence and neuropsychological scores were found within normal ranges for all diagnostic groups. Significant differences between UVH patients and controls emerged on auditory sustained and alternating attention, fine motor skills, visuospatial information processing, and to a lesser extent, memory performance. Parents of UVH patients reported more externalizing problems and school problems. Patient groups did not differ on neuropsychological outcome measures, nor on behavioural problems as rated by parents. CONCLUSIONS: After Fontan completion, patients at school age display intelligence scores within normal population-based ranges. However, they were found at risk for subtle shortcomings in attention, fine motor skills, visuospatial information processing and externalizing behaviour problems. Considerations pertaining to neurobehavioural outcome in school-aged children are discussed. © The Author 2015.
Keywords: Congenital heart defect; Hypoplastic left heart; Neurodevelopmental outcome; Neuropsychology; Tricuspid atresia

Half a century's experience with the superior cavopulmonary (classic glenn) shunt - Zahr, R.A.; Kirshbom, P.M.; Kopf, G.S.; Sainathan, S.; Steele, M.M.; Elder, R.W.; Karimi, M. (Annals of Thoracic Surgery, 2016)
Background Five decades after its introduction, the Glenn shunt remains an integral step for patients undergoing single-ventricle palliation. We performed a longitudinal follow-up of the original cohort of patients who underwent Glenn shunt. Methods We performed a retrospective study of the original cohort of patients who underwent Glenn shunt at Yale between 1958 and 1988. Electronic medical records and chart review up to current era were used to collect data. Results Ninety-one patients underwent a Glenn shunt at an average age of 6.6 ± 2.5 years, of which 89 were classic Glenn shunts. Median overall survival was 43 years (range, 2 to 56; 95% confidence interval [CI], 39.5 to 46.5) while median survival from the Glenn shunt was 31.4 years (range, 0 to 45; 95% CI, 23.9 to 38.9). Forty-six patients died, 7 in the early postoperative period and 39 late deaths. Twenty-six patients were lost to follow-up. Nineteen patients remain alive with active clinical follow-up, 6 of whom still live with their classic Glenn shunt without conversion to bidirectional Glenn. Twenty-six patients (31%) developed pulmonary arteriovenous fistula with 11 patients (42%) requiring coil embolization. No patient developed thrombosis of the Glenn shunt. There were a total of 28 patients who developed arrhythmias, mostly in the tricuspid atresia group (n = 16), with the majority being atrial tachyarrhythmias (48%). Sixteen patients required permanent pacemaker placement for sinus node dysfunction. Conclusions The Glenn shunt continues to provide excellent staged palliation in single-ventricle patients and a bridge to two-ventricle repair. Arrhythmias and pulmonary arteriovenous fistulas were common among single-ventricle cohort. Quality-of-life evaluation of the surviving patients would be an important outcome measure for future investigation. © 2016 The Society of Thoracic Surgeons.

Successful bronchoscopy in a pregnant patient with plastic bronchitis - Patil, M.H.; Siddiqi, A.; Jeffrey Mador, M. (Respiratory Medicine Case Reports, 2016)
Plastic bronchitis is a rare disorder, characterized by formation of thick fibrinous bronchial casts which can obstruct the airway and present as a life threatening emergency (1). It is more common in the pediatric population after corrective or palliative surgery for congenital heart disease like fontan procedure but has rarely been reported in adults as well (1). Pregnancy is a relative contraindication for bronchoscopy. Bronchoscopy in the pregnant patient poses significant risks as manipulation of the airway can lead to impaired oxygenation and ventilation. In addition, the drugs used during this procedure to provide sedation can have a direct impact on the developing fetus (2). In spite of these risks bronchoscopy should not be withheld in an emergent situation as it can be a lifesaving measure. We report a case of successful bronchoscopy using Propofol as the sedating agent in a pregnant female with plastic bronchitis who presented with respiratory distress. © 2016 The Authors.
Keywords: Bronchoscope; Plastic bronchitis; Pregnancy; Propofol

Selective serotonin reuptake inhibitors and congenital heart anomalies: Comparative cohort studies of women treated before and during pregnancy and their children - Petersen, I.; Evans, S.J.; Gilbert, R.; Marston, L.; Nazareth, I. (Journal of Clinical Psychiatry, 2016)
Background: Large databases and population registers are increasingly used to examine adverse birth outcomes, congenital heart anomalies, in particular, following antidepressant exposures in pregnancy. Yet many studies have failed to account for other characteristics of the women who were prescribed antidepressants. Objective: To examine the characteristics of women who are prescribed selective serotonin reuptake inhibitors (SSRIs) in pregnancy and women who are not, associations between SSRIs prescribed in pregnancy and congenital heart anomalies, and the association between social and lifestyle characteristics of pregnant women and congenital heart anomalies. Method: Using data from The Health Improvement Network primary care database in the United Kingdom between January 1, 1990, and January 31, 2011, we set up a comparative study including 4 cohorts of children of women with and without different antidepressant exposures before and during pregnancy. 5,154 women were receiving SSRIs before pregnancy, 2,776 were receiving SSRIs during pregnancy, 992 were receiving other antidepressants during pregnancy, and 200,213 were receiving no antidepressants before or during pregnancy. Our primary outcome was congenital heart anomalies. Results: Less than 1% of children had a record of congenital heart anomalies within 5 years of birth, and there were no significant differences related to antidepressant exposure in pregnancy (women not prescribed antidepressants versus women prescribed SSRIs in first trimester: odds ratio [OR] = 1.00; 95% CI, 0.65-1.52); however, independent of antidepressant prescribing, diabetes (OR = 2.23; 95% CI, 1.79-2.77), increasing age (OR = 1.01; 95% CI, 1.00-1.02), alcohol problem (OR = 2.58; 95% CI, 1.55-4.29, illicit drug problems (OR = 1.89; 95% CI, 1.09-3.25), and obesity (OR = 1.38; 95% CI, 1.13-1.69) were associated with an increased risk of having a child with congenital heart anomalies. Conclusions: There was no difference in congenital heart anomalies in children born to women with different antidepressant prescribing exposure status. However, we confirmed an increased risk of congenital heart anomalies in children of older women and in children of women with diabetes, a body mass index above 30 kg/m2, and a history of alcohol and illicit drug problems independent of the prescription of antidepressants. Future research in this field must account for these characteristics. On the basis of existing evidence, advising women to stop antidepressant treatment in pregnancy may be counterproductive. © Copyright 2016 Physicians Postgraduate Press, Inc.

Berlin heart ventricular assist device as a long-term bridge to transplantation in a Fontan patient with failing single ventricle - Halaweish, I.; Ohye, R.G.; Si, M.S. (Pediatric Transplantation, 2015)
The use of VADs as a BTT in children with heart failure has increased due to enhanced device design and reliability, leading to improved survival, functional capacity, and quality of life. However, the use of VADs in patients with Fontan physiology as a BTT is rare with few case reports. Here, we describe a case of implantation of the Berlin VAD as a BTT for 179 days, one of the longest reported periods of mechanical support, in a child with failing single ventricle. © 2015 John Wiley & Sons A/S. Published by John Wiley & Sons Ltd.
Keywords: Fontan; single ventricle; transplant; ventricular assist device; ventricular assist device

Quality of Life of Children with Congenital Heart Diseases: A Multicenter Controlled Cross-Sectional Study - Amedro, P.; Dorka, R.; Moniotte, S.; Guillaumont, S.; Fraisse, A.; Kreitmann, B.; Borm, B.; Bertet, H.; Barrea, C.; Ovaert, C.; Sluysmans, T.; De La Villeon, G.; et al. (Pediatric Cardiology, 2015)
To assess the health-related quality of life (QoL) in children with congenital heart diseases (CHD) with a validated questionnaire in comparison with control children. We prospectively recruited 282 children with CHD aged from 8 to 18 years in two tertiary care centers (France and Belgium) and 180 same-age controls in randomly selected French schools. Children’s QoL was self-reported with the KIDSCREEN-52 questionnaire and reported by parents with the KIDSCREEN-27. QoL scores of each dimension were compared between CHD and controls and between the classes of disease severity. Both centers were comparable for most demographic and clinical data. Age- and gender-adjusted self-reported QoL scores were lower in CHD children than in controls for physical well-being (mean ± SEM 45.97 ± 0.57 vs 50.16 ± 0.71, p < 0.0001), financial resources (45.72 ± 0.70 vs 48.85 ± 0.87, p = 0.01), peers/social support (48.01 ± 0.72 vs 51.02 ± 0.88, p = 0.01), and autonomy in the multivariate analysis (47.63 ± 0.69 vs 49.28 ± 0.85, p = 0.04). Parents-reported scores were lower in CHD children for physical (p < 0.0001), psychological well-being (p = 0.04), peers/social support (p < 0.0001), and school environment (p < 0.0001) dimensions. Similarly, the disease severity had an impact on physical well-being (p < 0.001), financial resources (p = 0.05), and peers/social support (p = 0.01) for self-reported dimensions, and on physical well-being (p < 0.001), psychological well-being (p < 0.01), peers/social support (p < 0.001), and school environment (p < 0.001) for parents-reported dimensions. However, in multivariate analysis on self-reported QoL, disease severity was significantly associated with the self-perception dimension only. Self-reported QoL of CHD children was similar to that of same-age healthy children in seven of 10 dimensions, but parents-reported QoL was impaired in four of five dimensions. © 2015, Springer Science+Business Media New York.
Keywords: Children; Congenital heart disease; Kidscreen; Pediatric cardiology; Quality of life

Obstructive jaundice secondary to Morgagni hernia in an infant with Fontan circulation - Halaweish, I.; Ralls, M.; Siddiqui, S.; Dickinson, C.; Jarboe, M.D. (Pediatric Surgery International, 2015)
The vast majority of congenital diaphragmatic cases present with severe respiratory distress in the immediate neonatal period. Obstructive jaundice secondary to CDH is a rare presenting symptom, previously unreported with Morgagni type hernias which comprise 2 % of all CDHs. Although the safety of minimally invasive repair for CDH has been shown previously, there has been little data on its safety for patients with complex congenital cardiac disease. In this case report, we present an 18-month old infant with Fontan circulation presenting with jaundice secondary to Morgagni hernia who ultimately underwent laparoscopic repair. A brief discussion of the safety of laparoscopic surgery in patients post-Fontan is included. © 2015, Springer-Verlag Berlin Heidelberg.
Keywords: Diaphragmatic; Fontan; Hernia; Jaundice; Morgagni; Pediatric

Neuropsychological performance of school-aged children after staged surgical palliation of hypoplastic left heart syndrome - Bergemann, A.; Hansen, J.H.; Rotermann, I.; Voges, I.; Scheewe, J.; Otto-morris, C.; Geiger, F.; Kramer, H.-H. (European Journal of Cardio-thoracic Surgery, 2015)
OBJECTIVES: Despite advances in perioperative management during surgical treatment of hypoplastic left heart syndrome (HLHS), patients are still at risk for adverse neurodevelopmental sequelae including cognitive dysfunction. This study aimed to assess a neuropsychological profile of HLHS patients at school age who underwent the Norwood operation between 1996 and 2003 with deep hypothermic circulatory arrest (DHCA) or antegrade selective cerebral perfusion (ASCP), respectively. METHODS: Forty HLHS patients (DHCA: n = 11 and ASCP: n = 29) were compared with healthy controls (DHCA controls: n = 10 and ASCP controls: n = 24), recruited according to age, sex and socioeconomic status. Neuropsychological assessment included non-verbal intelligence (IQ norms) and raw score measures of visual and verbal short- and long-term memory as well as executive functions, processing speed and concentration. Neuropsychological data were correlated with bypass and circulatory arrest times. RESULTS: Compared with control subjects, both patient groups had average non-verbal intelligence scores [DHCA: 102 (72-112) and ASCP: 92 (70-127)], but showed reduced long-term memory capacities and decreased executive performance as well as reduced processing speed. DHCA patients, furthermore, had a reduced visual attention span, and ASCP patients scored less on the verbal learning task than controls. The duration of DHCA and cardiopulmonary bypass (CPB) was associated with visual executive functions and short-term memory. In the DHCA group, the duration of DHCA was correlated with the time to complete the Trail Making Test A measuring visual executive functions (Spearman rank correlation, rS = 0.867, P = 0.018). In patients provided with ASCP, the cumulated CPB duration was negatively correlated with the score of the block span test measuring visual short memory (rS = -0.476, P = 0.020) as well as with the copy score of the Rey Figure assessing visual executive functions (rS = -0.399, P = 0.032). CONCLUSIONS: School-age children with HLHS who underwent the Norwood procedure either with DHCA or ASCP show cognitive impairments compared with healthy controls. Our data indicate deficits in specific cognitive domains such as memory, executive functions and processing speed rather than basic intellectual dysfunction. © The Author 2014. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Cardiopulmonary bypass; Hypoplastic left heart syndrome; Hypothermic circulatory arrest; Norwood operation

Health-Related Quality of Life in Adult Survivors After the Fontan Operation - Kukreja, M.; Bryant, A.S.; Cleveland, D.C.; Dabal, R.; Hingorani, N.; Kirklin, J.K. (Seminars in Thoracic and Cardiovascular Surgery, 2015)
The primary objective of this study was to ascertain the long-term health-related quality of life (HRQOL) of adult patients who underwent a childhood Fontan operation for palliation of univentricular cardiac anomalies. The secondary objective was to compare the long-term HRQOL of Fontan survivors to that of pediatric heart transplant recipients. This cross-sectional study examined adult survivors (>19 years) who underwent a Fontan operation during childhood (Fontan group) or a pediatric heart transplant (HT group) between 1988 and 2011 (23-year span). HRQOL was assessed using the short form 36 survey. The study group consisted of 49 Fontan group patients and 13 HT group patients who responded to the survey. HRQOL scores of the Fontan group were similar to those of an age-controlled healthy US population in social and mental functioning, energy or vitality, and overall mental component score (P ≥ 0.2). However, Fontan scores in physical functioning, bodily pain, general health, and overall by physical component were significantly lower than those of the age-controlled US population (P < 0.05). No differences were identified between Fontan and HT patients. This favorable life-satisfaction period (average 18 years) should be considered when informing patients and families of expectations with the Fontan pathway vs certain higher-risk procedures. © 2015 Elsevier Inc.
Keywords: Fontan procedures; health-related quality of life; single-ventricle conditions

Transparency in a Pediatric Quality Improvement Collaborative: A Passionate Journey by NPC-QIC Clinicians and Parents - Lihn, S.L.; Kugler, J.D.; Peterson, L.E.; Lannon, C.M.; Pickles, D.; Beekman, R.H. (Congenital Heart Disease, 2015)
Transparency-sharing data or information about outcomes, processes, protocols, and practices-may be the most powerful driver of health care improvement. In this special article, the development and growth of transparency within the National Pediatric Cardiology Quality Improvement Collaborative is described. The National Pediatric Cardiology Quality Improvement Collaborative transparency journey is guided by equal numbers of clinicians and parents of children with congenital heart disease working together in a Transparency Work Group. Activities are organized around four interrelated levels of transparency (individual, organizational, collaborative, and system), each with a specified purpose and aim. A number of Transparency Work Group recommendations have been operationalized. Aggregate collaborative performance is now reported on the public-facing web site. Specific information that the Transparency Work Group recommends centers provide to parents has been developed and published. Almost half of National Pediatric Cardiology Quality Improvement Collaborative centers participated in a pilot of transparently sharing their outcomes achieved with one another. Individual centers have also begun successfully implementing recommended transparency activities. Despite progress, barriers to full transparency persist, including health care organization concerns about potential negative effects of disclosure on reputation and finances, and lack of reliable definitions, data, and reporting standards for fair comparisons of centers. The National Pediatric Cardiology Quality Improvement Collaborative's transparency efforts have been a journey that continues, not a single goal or destination. Balanced participation of clinicians and parents has been a critical element of the collaborative's success on this issue. Plans are in place to guide implementation of additional transparency recommendations across all four levels, including extension of the activities beyond the collaborative to support transparency efforts in national cardiology and cardiac surgery societies. © 2015 Wiley Periodicals, Inc.
Keywords: Congenital heart disease; Hypoplastic left heart syndrome; Public reporting; Quality improvement collaborative; Transparency

Transcoronary infusion of cardiac progenitor cells in hypoplastic left heart syndrome: Three-year follow-up of the Transcoronary Infusion of Cardiac Progenitor Cells in Patients with Single-Ventricle Physiology (TICAP) trial - Tarui, S.; Ishigami, S.; Ousaka, D.; Kasahara, S.; Ohtsuki, S.; Sano, S.; Oh, H. (Journal of Thoracic and Cardiovascular Surgery, 2015)
Objectives Our aim was to assess midterm safety and clinical outcomes of intracoronary infusion of cardiosphere-derived cells (CDCs) after staged palliation in patients with hypoplastic left heart syndrome (HLHS). Methods In this prospective, controlled study, 14 consecutive patients with HLHS who were undergoing 2- or 3-stage surgical palliations were assigned to receive intracoronary CDC infusion 1 month after cardiac surgery (n = 7), followed by 7 patients allocated to a control group with standard care alone. The primary end point was to assess procedural feasibility and safety; the secondary end point was to evaluate cardiac function and heart failure status through 36-month follow-up. Results No complications, including tumor formation, were reported within 36 months after CDC infusion. Echocardiography showed significantly greater improvement in right ventricular ejection fraction (RVEF) in infants receiving CDCs than in controls at 36 months (+8.0% ± 4.7% vs +2.2% ± 4.3%; P =.03). These cardiac function improvements resulted in reduced brain natriuretic peptide levels (P =.04), lower incidence of unplanned catheter interventions (P =.04), and higher weight-for-age z score (P =.02) at 36 months relative to controls. As independent predictors of treatment responsiveness, absolute changes in RVEF at 36 months were negatively correlated with age, weight-for-age z score, and RVEF at CDC infusion. Conclusions Intracoronary CDC infusion after staged procedure in patients with HLHS is safe and improves RVEF, which persists during 36-month follow-up. This therapeutic strategy may enhance somatic growth and reduce incidence of heart failure. © 2015 The American Association for Thoracic Surgery.
Keywords: cardiosphere; congenital heart disease; heart failure; hypoplastic left heart syndrome; stem cell therapy

Left Ventricular Remodeling and Function in Children with Biventricular Circulation After Fetal Aortic Valvuloplasty - Friedman, K.G.; Freud, L.; Escobar-Diaz, M.; Banka, P.; Emani, S.; Tworetzky, W. (Pediatric Cardiology, 2015)
Fetal aortic valvuloplasty (FAV) has shown promise in averting the progression of fetal aortic stenosis to hypoplastic left-heart syndrome. Altered loading conditions due to valvar disease, intrinsic endomyocardial abnormalities, and procedures that alter endomyocardial mechanics may place patients with biventricular circulation (BiV) after FAV at risk of abnormal LV remodeling and function. Using the most recent echo data on BiV patients after technically successful FAV (n = 34), we evaluated LV remodeling pattern, risk factors for pathologic LV remodeling, and the association between LV remodeling pattern and LV function. Median age at follow-up was 4.7 years (range 1.0–12.5). Cardiac interventions were common. At latest follow-up, no patient had hypoplastic LV. Nineteen patients (55 %) had dilated LV, and five (16 %) patients had severely dilated LV. LV remodeling patterns were as follows: 12 (35 %) normal ventricle, 11 (32 %) mixed hypertrophy, 8 (24 %) eccentric hypertrophy or remodeling, and 3 (9 %) concentric hypertrophy. Univariate factors associated with pathologic LV remodeling were long-standing AR, ≥2 cardiac interventions, EFE resection, and aortic or mitral regurgitation ≥ moderate at most recent follow-up. In multivariate analysis, only long-standing AR fraction remained associated with pathologic remodeling. Pathologic LV remodeling was associated with depressed ejection fraction, lower septal E´, and higher E/E´. Pathologic LV remodeling, primarily eccentric or mixed hypertrophy, is common in BiV patients after FAV and is related to LV loading conditions imposed by valvar disease. Pathologic remodeling is associated with both systolic and diastolic dysfunction in this population. © 2015, Springer Science+Business Media New York.
Keywords: Aortic stenosis; Diastolic dysfunction; Fetal cardiology; Left ventricular remodeling

Committed to Life: Adolescents' and Young Adults' Experiences of Living with Fontan Circulation - Berghammer, M.C.; Brink, E.; Rydberg, A.M.; Dellborg, M.; Ekman, I. (Congenital Heart Disease, 2015)
Background: Single ventricle defects are among the most complex congenital heart defects and the development of advanced surgical procedures in recent decades has created the first generation of adolescents and young adults living with this condition. Yet little is known about how these individuals experience life and what impact the heart defect has on their life in general. Objective: The aim was to illuminate and gain a deeper understanding of adolescents' and young adults' experiences of living with a surgically palliated univentricular heart. Design: Seven open-ended in-depth interviews were conducted, transcribed, and analyzed according to the henomenological hermeneutical method. All adolescents and young adults operated before 1995 according to the Fontan procedure or the total cavo-pulmonary connection procedure at one pediatric cardiology unit were included in the study. They were 17-32 years of age (median age 22 years). Results: The interpretation of the interview transcripts showed that the participants experienced living with a surgically palliated univentricular heart in terms of feeling exceptional, strong, and healthy. This was supported by two structural analyses, where three themes emerged: happiness over being me, focusing on possibilities, and being committed to life. Conclusion: Living with a Fontan circulation included negative experiences but the analyses clearly demonstrated a feeling of being strong and healthy. An appreciation of having survived and being committed to life was found to be an integral part of the development of the interviewees' existential growth. This probably strengthens them further in their ability to balance expectations and hurdles in life. This study provides valuable insights into the experience of patients after the Fontan procedure and the importance of a positive health care environment throughout their lives. © 2015 Wiley Periodicals, Inc.
Keywords: Adolescents and Young Adults; Fontan Circulation; In-Depth Interviews; Lived Experience; Phenomenological Hermeneutics; Univentricular Heart

Clinical Profile and Quality of Life of Adult Patients After the Fontan Procedure - Bordin, G.; Padalino, M.A.; Perentaler, S.; Castaldi, B.; Maschietto, N.; Michieli, P.; Crepaz, R.; Frigo, A.C.; Vida, V.L.; Milanesi, O. (Pediatric Cardiology, 2015)
Increasingly, more patients with univentricular heart reach adulthood. Therefore, long-term psychological features are an important concern. The aim of this study was to evaluate the clinical and psychological profile of post-Fontan adult patients and to identify the most significant determinants of quality of life. In this retrospective cross-sectional study, we reviewed the surgical and medical history of post-Fontan adult patients. Patients underwent a 24-h electrocardiogram, echocardiography and exercise testing. Self-report questionnaires were used to assess the Work Ability Index, quality of life (Satisfaction with Life Scale), perceived health status (SF-36 questionnaire), coping strategies (Brief Cope questionnaire) and presence of mood disorders (Hospital Anxiety and Depression Scale). Thirty-nine patients aged between 18 and 48 years (mean 27.5 years) were enrolled. The mean follow-up was 21.5 years. Most patients were unmarried (82.9 %), had a high school diploma (62.9 %) and were employed (62.9 %). Twenty-nine patients (82.3 %) had at least one long-term complication. The median single ventricle ejection fraction was 57 %, and the median maximal oxygen consumption was 26.8 ml/min/kg. This population tended to be anxious and to use adaptive coping strategies. Quality of life was perceived as excellent or good in 57.2 % of cases and was not related to either cardiac function or exercise capacity. Both quality of life and SF-36 domains were related to the Work Ability Index. This cohort of post-Fontan adult patients enjoyed a good quality of life irrespective of disease severity. © 2015, Springer Science+Business Media New York.
Keywords: Follow-up study; Fontan procedure; Quality of life

Older age at completion of fontan procedure: Is associated with improved percentage of predicted maximum oxygen uptake - Bolin, E.H.; Maskatia, S.A.; Tate, A.L.; Petit, C.J. (Texas Heart Institute Journal, 2015)
We tested the hypothesis that later completion of the Fontan procedure is associated with improved exercise capacity in the current period of staged single-ventricle palliation. We performed a retrospective study, in Fontan patients, of exercise stress test data from April 2003 through March 2011. Patients were included if they had received staged palliations in accordance with current surgical strategy, defined as the performance of a superior cavopulmonary connection at ≤1 year of age, followed in subsequent years by Fontan completion. Patients with a pacemaker or respiratory exchange ratio <1 were excluded. Early and late Fontan groups were created on the basis of whether Fontan completion had been performed at <4 or ≥ 4 years of age. The primary predictor variable was age at Fontan completion, and the primary marker of exercise performance was the percentage of predicted maximum oxygen consumption. During the study period, 55 patients were identified (mean age, 11.7 ± 2.8 yr). Older age at Fontan completion correlated positively with higher percentages of predicted maximum oxygen consumption (R=0.286, P=0.034). Patients in whom Fontan completion was performed at ≥4 years of age had higher percentages of predicted maximum oxygen consumption than did those in whom completion was at <4 years of age (84.4 ± 21.5 vs 72.9 ± 18.1; P=0.041). Later Fontan completion might be associated with improved exercise capacity in patients palliated in accordance with contemporary surgical strategy. © 2015 by the Texas Heart ® Institute, Houston.
Keywords: Child, preschool; Congenital/ surgery; Exercise test; Fontan procedure/adverse effects; Heart defects; Hemodynamics/ physiology; Hypoplastic left heart syndrome; Longitudinal studies; Oxygen consumption/ physiology; Physical exertion; Postoperative complications; Pulmonary circulation; Retrospective studies; Tricuspid atresia/surgery; Vascular resistance

Immune Abnormalities in Fontan Protein-Losing Enteropathy: A Case-Control Study - Magdo, H.S.; Stillwell, T.L.; Greenhawt, M.J.; Stringer, K.A.; Yu, S.; Fifer, C.G.; Russell, M.W.; Schumacher, K.R. (Journal of Pediatrics, 2015)
Objective To comprehensively characterize the immunologic characteristics of patients with protein-losing enteropathy (PLE) post-Fontan and compare them with patients without PLE post-Fontan. Study design Patients with PLE post-Fontan and age-matched controls post-Fontan were prospectively studied with laboratory markers of immune function. Infectious history was obtained by interview and chart review. The groups' demographics, cardiac history, immune characteristics, and infection history were compared using appropriate 2-group statistics. Results A total of 16 patients enrolled (8 patients with PLE and 8 controls). All patients with PLE had lymphopenia compared with 25% of controls (P =.01). All patients with PLE had markedly depressed CD4 T cell counts (median 58 cells/μL) compared with controls (median 450 cells/μL, P =.0002); CD4% was also low in the PLE group (12.3%) and normal in control (36.9%, P =.004). Both groups had mildly depressed CD8 T cells and normal to slightly elevated natural killer and B-cell subsets. A majority of patients with PLE (62.5%) had negative titers to measles, mumps, and rubella vaccination, compared with no control Fontan with a negative titer (P =.03). Despite profoundly low CD4 counts, the frequency of infection was not different between groups with no reported opportunistic infections. Conclusions Patients with Fontan-associated PLE have extensive quantitative immune abnormalities, particularly CD4 deficiency. These immune abnormalities are similar to those found in non-Fontan patients with PLE caused by intestinal lymphangiectasia. © 2015 Elsevier Inc.

Parental mental health moderates the efficacy of exercise training on health-related quality of life in adolescents with congenital heart disease - Dulfer, K.; Duppen, N.; Van Dijk, A.P.J.; Kuipers, I.M.; Van Domburg, R.T.; Verhulst, F.C.; Van der Ende, J.; Helbing, W.A.; Utens, E.M.W.J. (Pediatric Cardiology, 2015)
To evaluate the moderating influence of parental variables on changes in health-related quality of life (HRQoL) in adolescents with Tetralogy of Fallot (ToF) or a Fontan circulation after participation in standardized exercise training. A multicenter randomized controlled trail in which 56 patients, aged 10–15, were randomly allocated (stratified by age, gender, and congenital heart disease) to a 12-week period with either: (a) 3 times per week standardized exercise training or (b) care-as-usual (randomization ratio 2:1). Adolescents and their parents filled in online questionnaires at baseline and at 12-week follow-up. In this randomized controlled trail, primary analyses involved influence of parental mental health and parental social support for exercise on changes in the TNO/AZL Child Quality of Life Questionnaire Child Form at followup. Secondary analyses concerned comparing levels of parental characteristics with normative data. Compared with controls, adolescents in the exercise group reported a decrease in social functioning when their parents had more anxiety/insomnia or severe depression themselves. Adolescents also reported a decrease in social functioning when their parents showed poorer overall mental health themselves. Parents reported comparable or even better mental health compared with normative data. The effect of a standardized exercise program on HRQoL changes in adolescents with ToF or a Fontan circulation is moderated by parental mental health, more specifically by parental anxiety/insomnia and severe depression. The trial registration number of this article is NTR2731 (www.trialregister.nl). © Springer Science+Business Media New York 2014.
Keywords: Adolescents; Aerobic exercise; Children; Congenital heart defects; Parents

Ventricular function and cardiac reserve in contemporary Fontan patients - Bossers, S.S.M.; Kapusta, L.; Kuipers, I.M.; Van Iperen, G.; Moelker, A.; Kroft, L.J.M.; Romeih, S.; De Rijke, Y.; Ten Harkel, A.D.J.; Helbing, W.A. (International Journal of Cardiology, 2015)
Background/objective Total cavopulmonary connection (TCPC) has been the preferred treatment for patients with univentricular hearts. Current TCPC-techniques are the intra-atrial lateral tunnel (ILT) and the extracardiac conduit (ECC). We aimed to determine ventricular function during rest and stress, and to compare results for both techniques and for left (LV) versus right ventricular (RV) dominance. Methods 99 patients, aged 12.5 ± 4.0 years underwent echocardiography and magnetic resonance imaging (MRI), and 69 patients underwent stress MRI. Results Echocardiography showed impaired systolic and diastolic function. MRI parameters were comparable between ILT and ECC at rest. During dobutamine there was a decrease in end-diastolic volume (EDVi) (91 ± 21 vs. 80 ± 20 ml/m2 p < 0.001). Ejection fraction (EF) and cardiac index (CI) during dobutamine were lower for ILT patients (59 ± 11 (ILT) vs. 64 ± 7% (ECC), p = 0.027 and 4.2 ± 1.0 (ILT) vs. 4.9 ± 1.0 L/min/m2 (ECC), p = 0.006), whereas other parameters were comparable. TEI-index was higher in ILT-patients (0.72 ± 0.27 (ILT) vs. 0.56 ± 0.22 (ECC), p = 0.002). Diastolic function was frequently impaired in patients with a dominant RV (67% (RV) vs. 39% (LV), p = 0.011). Patients with dominant LV's had smaller end-systolic volume (ESVi) (40 ± 13 (LV) vs. 47 ± 16 (RV) ml/m2, p = 0.030) and higher EF (55 ± 8 (LV) vs. 49 ± 9 ml/m2 (RV), p = 0.001) and contractility (2.3 ± 0.8 (LV) vs. 1.9 ± 0.7 mm Hg/ml/m2 (RV), p = 0.050) during rest and higher EF during dobutamine (63 ± 8 (LV) vs. 58 ± 10 ml/m2 (RV), p = 0.043). Conclusion Ventricular function is relatively well preserved in modern-day Fontan patients. With dobutamine stress there is a decrease in EDVi. ECC patients have higher CI and EF during stress. Patients with a dominant RV have lower systolic, including impaired contractility, and diastolic function. © 2015 Published by Elsevier Ireland Ltd.
Keywords: Cardiac function; Congenital heart disease; Echocardiography; Fontan; MRI; Total cavopulmonary connection

The prevalence of attention-deficit/hyperactivity disorder following neonatal aortic arch repair - Sistino, J.J.; Atz, A.M.; Simpson, K.N.; Ellis, C., Jr.; Ikonomidis, J.S.; Bradley, S.M. (Cardiology in the Young, 2015)
Objective: We sought to determine the prevalence of attention-deficit/hyperactivity disorder in a population of children who underwent neonatal heart surgery involving repair of the aortic arch for Norwood Stage I, interrupted aortic arch, and combined repair of aortic coarctation with ventricular septal defect. Methods: Children between the ages of 5 and 16 were surveyed using the ADHD-IV and the Child Heath Questionnaire-50. Classification as attention-deficit/hyperactivity disorder was defined for this study as either a parent-reported diagnosis of attention-deficit/hyperactivity disorder or ADHD-IV inattention score of ≥93 percentile. Results: Of the 134 surveys, 57 (43%) were returned completed. A total of 25 (44%) children either had a diagnosis of attention-deficit/hyperactivity disorder and/or ADHD-IV inattention score ≥93 percentile. Eleven of the 13 (85%) children with interrupted aortic arch, 3 of the 7 (42.9%) children with combined coarctation/ventricular septal defect repair, and 9 of the 33 (27.3%) children with hypoplastic left-heart syndrome were classified as having attention-deficit/hyperactivity disorder. Only 7 of the 25 (28%) children received medical treatment for this condition. Quality of life indicators in the Child Heath Questionnaire-50 Questionnaire were highly correlated with the ADHD-IV scores. Conclusion: The risks for the development of attention-deficit/hyperactivity disorder are multifactorial but are significantly increased in this post-surgical population. This study revealed a low treatment rate for attention-deficit/hyperactivity disorder, and a significant impact on the quality of life in these children. © Cambridge University Press, 2014.
Keywords: aortic arch repair; Attention-deficit/hyperactivity disorder; hypoplastic left-heart syndrome; neonatal cardiac surgery

Rehospitalization Following Neonatal Cardiac Surgery: Risk Factors and Outcomes - Soliman, A.; Aggarwal, S.; Natarajan, G. (American Journal of Perinatology, 2015)
Objective The aim of the study is to determine the number and indications of unplanned hospital readmissions and emergency room visits for children with hypoplastic left heart syndrome (HLHS) or transposition of great arteries (TGA). Design This retrospective chart review involved children with HLHS or TGA who underwent neonatal surgical repair in a single Children's Hospital. Statistical analysis (SPSS 22.0) included chi-square test, t-test, and binary logistic regression. Results Our study cohort (n=117) comprised 28 children with HLHS and 89 with TGA who were followed for a mean (standard deviation, SD) duration of 4.7 (3.2) years. Unplanned readmissions (n=153) occurred in 46 (39.3%) children, a mean (SD) number of 1.3 (2.8) for a median (interquartile range, IQR) of 8 (2-28) days per patient. Indications were respiratory (57.5%), gastrointestinal (18.3%), and cardiac (12.4%) in nature. On binary regression, with birth weight, race, and gestational age as covariates, among children with HLHS, increasing gestational age tended to be associated with a lower risk of readmissions (odds ratio [OR] 0.138; 95% confidence interval [CI]: 0.018-1.031, p=0.054]. The mean (SD) number of emergency room visits (n=261) was 3.2 (9.7) in 42 (35.9%) infants for minor illnesses (64%) or gastrointestinal (13.8%) problems. Conclusion The majority of children with HLHS and TGA have unplanned readmissions. Home-care surveillance programs may reduce health-care utilization in this population.
Keywords: hypoplastic left heart syndrome; rehospitalization; transposition of great arteries

Quality of life in pediatric patients affected by electrophysiologic disease - Czosek, R.J.; Cassedy, A.E.; Wray, J.; Wernovsky, G.; Newburger, J.W.; Mussatto, K.A.; Mahony, L.; Tanel, R.E.; Cohen, M.I.; Franklin, R.C.; Brown, K.L.; Rosenthal, D.; et al. (Heart Rhythm, 2015)
Background Treatment of electrophysiologic (EP) disease in pediatric patients has improved; however, the effects on quality of life (QOL) are unknown. Objective The purpose of this study was to compare QOL within EP disease groups and to other congenital heart diseases, to evaluate the effects of cardiac rhythm devices on QOL, and to identify drivers of QOL in EP disease. Methods Cross-sectional study of patient/parent proxy-reported Pediatric Cardiac Quality of Life Inventory scores (Total, Disease Impact, Psychosocial Impact) in subjects aged 8 to 18 years from 11 centers with congenital complete heart block (CCHB), ventricular tachycardia (VT), supraventricular tachycardia (SVT), and long QT syndrome (LQTS). QOL was compared between EP disease groups and congenital heart disease groups [bicuspid aortic valve (BAV), tetralogy of Fallot (TOF), and Fontan]. General linear modeling was used to perform group comparisons and to identify predictors of QOL variation. Results Among 288 patient-parent pairs, mean age was 12.8 ± 3.0 years. CCHB (μ = 83) showed higher patient Total QOL than other EP disease cohorts (P ≤.02; LQTS μ = 73; SVT μ = 74). SVT (μ = 75) and LQTS (μ = 75) had lower patient Total scores than BAV (μ = 81; P ≤.008). Patient/parent-proxy QOL scores for all EP disease groups were not different than TOF and higher than Fontan. The presence of a cardiac rhythm device was associated with lower QOL scores in LQTS (μ = 66 vs μ = 76; P <.01). Predictors of lower patient/parent-proxy QOL included EP disease type (P ≤.03), increased medical care utilization (P ≤.04), and no parental college degree (P ≤.001). Conclusion Given the significant variation in QOL in EP disease type, stratification by EP disease type and increased medical care utilization may allow for targeted interventions to improve QOL. © 2015 Heart Rhythm Society. All rights reserved.
Keywords: Arrhythmia; Cardiac rhythm devices; Channelopathy; Electrophysiology; Pediatrics; Quality of life

Bronchoscopic guidance of endovascular stenting limits airway compression - Ebrahim, M.; Hagood, J.; Moore, J.; El-Said, H. (Catheterization and Cardiovascular Interventions, 2015)
Objective Bronchial compression as a result of pulmonary artery and aortic arch stenting may cause significant respiratory distress. We set out to limit airway narrowing by endovascular stenting, by using simultaneous flexible bronchoscopy and graduated balloon stent dilatation, or balloon angioplasty to determine maximum safe stent diameter. Methods Between August 2010 and August 2013, patients with suspected airway compression by adjacent vascular structures, underwent CT or a 3D rotational angiogram to evaluate the relationship between the airway and the blood vessels. If these studies showed close proximity of the stenosed vessel and the airway, simultaneous bronchoscopy and graduated stent re-dilation or graduated balloon angioplasty were performed. Results Five simultaneous bronchoscopy and interventional catheterization procedures were performed in four patients. Median age/weight was 33 (range 9-49) months and14 (range 7.6-24) kg, respectively. Three had hypoplastic left heart syndrome, and one had coarctation of the aorta (CoA). All had confirmed or suspected left main stem bronchial compression. In three procedures, serial balloon dilatation of a previously placed stent in the CoA was performed and bronchoscopy was used to determine the safest largest diameter. In the other two procedures, balloon testing with simultaneous bronchoscopy was performed to determine the stent size that would limit compression of the adjacent airway. In all cases, simultaneous bronchoscopy allowed selection of an ideal caliber of the stent that optimized vessel diameter while minimizing compression of the adjacent airway. Conclusion In cases at risk for airway compromise, flexible bronchoscopy is a useful tool to guide endovascular stenting. Maximum safe stent diameter can be determined without risking catastrophic airway compression. © 2014 Wiley Periodicals, Inc. © 2014 Wiley Periodicals, Inc.
Keywords: branch pulmonary arteries; bronchial compression; bronchoscopy; LPA; stent

Case studies of patients successfully and unsuccessfully managed pre- and post-fontan procedure - Ono, Y.; Mitsushita, N. (International Heart Journal, 2015)
As a result of advances and modifications in surgical procedures and the development of drugs for pulmonary arterial hypertension, many patients who have undergone Fontan procedures are able to enjoy good quality of life, without pulmonary arterial hypertension and severe complications. In Shizuoka Children’s Hospital, drugs for pulmonary arterial hypertension have long been given to Fontan candidates and patients with established Fontan circulation to maintain sufficient pulmonary blood flow and suppress pulmonary arterial hypertension. We present three typical cases that were treated with anti-pulmonary hypertensive drugs before or after Fontan procedure. The first case had asplenia syndrome, and a single ventricle with major aortopulmonary collateral arteries. Anti-pulmonary hypertensive therapy permitted a Fontan procedure and maintained a good long-term quality of life. The second case was a Down syndrome patient who had progressive cyanosis after a Fontan operation. Anti-pulmonary hypertensive therapy improved cyanosis. The third case suffered from protein-losing enteropathy, for which all procedures and medical therapies were ineffective. Fontan candidates and patients with Fontan circulation have varied anatomical backgrounds and pulmonary properties. We must identify the conditions that lead to successful Fontan procedure and Fontan circulation correction, as well as conditions that result in failed Fontan procedure and poorly-controlled Fontan circulation. © 2015, International Heart Journal Association. All rights reserved.
Keywords: Beraprost; Bosentan; Cardiac malformation; Fenestration; Pulmonary hypertension; Sildenafil

Adverse pulmonary vascular remodeling in the Fontan circulation - Ridderbos, F.-J.S.; Wolff, D.; Timmer, A.; Van Melle, J.P.; Ebels, T.; Dickinson, M.G.; Timens, W.; Berger, R.M.F. (Journal of Heart and Lung Transplantation, 2015)
Background The Fontan circulation is a palliation for patients with a functionally univentricular heart. It is characterized by gradual attrition over time. An increase in pulmonary vascular resistance could be a key factor in the long-term failure of the Fontan circulation. In this study we aimed to identify pulmonary vascular remodeling in patients with a Fontan circulation. Methods Pulmonary vascular histomorphometric analysis and immunohistochemistry were performed in lung tissue obtained at autopsy from 12 Fontan patients. These patients had died either peri-operatively (Group A: death during or <15 days after Fontan completion; n = 5) or in mid to long-term follow-up (Group B: death >5 years after Fontan completion; n = 7). Two age-matched control groups (n = 10 and n = 14, respectively) were included. Results Intra-acinar pulmonary vessels in the Fontan Group B patients showed decreased medial thickness (p = 0.028) compared with age-matched controls, whereas intimal thickness was increased (p = 0.002). Intimal thickness in the Fontan Group B patients correlated with age at death (r = 0.964, p < 0.001) and with the length of time that the Fontan circulation had been in place (r = 0.714, p = 0.036). Immunohistochemistry revealed a reduction of vascular smooth muscles cells in the medial layer of the intra-acinar pulmonary vessels. The eccentric intimal thickening was composed of mainly acellular fibrosis with collagen deposition. Conclusions We observed a unique pattern of adverse pulmonary vascular remodeling in patients with a long-standing Fontan circulation who had died during follow-up. This remodeling pattern may play a major role in long-term attrition of the Fontan circulation. © 2015 International Society for Heart and Lung Transplantation. All rights reserved.
Keywords: congenital heart disease; failing Fontan; Fontan operation; pulmonary vascular remodeling; pulmonary vascular resistance; shear stress

Caregiver anxiety due to interstage feeding concerns - Stewart, J.; Dempster, R.; Allen, R.; Miller-Tate, H.; Dickson, G.; Fichtner, S.; Principe, A.J.; Fonseca, R.; Nicholson, L.; Cua, C.L. (Congenital Heart Disease, 2015)
Introduction: Improved weight gain during the interstage (IS) period has been shown to improve overall outcomes in patients with single ventricle physiology (SVP). This emphasis on nutrition may have untoward effects, such as increasing anxiety/stress levels in caregivers, who are already known to be at risk for increased anxiety/stress levels. The goal of this study was to evaluate anxiety/stress levels of caregivers as it pertains to feeding during the IS period and to determine if certain characteristics were associated with higher anxiety/stress scores. Methods: Caregivers of children with SVP who completed the IS period, defined as the time between the first and second cardiac surgeries, were recruited. Baseline demographics were obtained. Anxiety/stress levels were measured via eight questions using a 0- to 10-point scale. Correlations were performed between demographic variables and anxiety/stress level scores. Results: Fifty-six surveys were completed (39 males, 27 females) on 43 children. Fourteen children required tube feeds during the IS period. There were significant correlations between anxiety/stress scores and caregiver's gender, caregiver's age, caregiver's level of education, percent of time a caregiver spent feeding the child, if caregivers were taking medications for anxiety, and if the child was seen in the emergency room during the IS period. There were no correlation of anxiety/stress scores with caregiver's race, child's underlying cardiac diagnosis, age of child, route of feeding during the IS period, birth order of the child or number of children in the family, relationship status, or distance from the hospital. Conclusion: In general, caregivers of children with SVP experience anxiety/stress during the IS period specifically due to feeding concerns. Certain intrinsic and extrinsic characteristics were associated with higher anxiety/stress levels. Future studies are needed to determine how to minimize anxiety/stress levels during this stressful time period. © 2015 Wiley Periodicals, Inc.
Keywords: Anxiety; Hypoplastic left heart; Interstage; Nutrition; Single ventricle

Sports participation and quality of life in adolescents and young adults with congenital heart disease - Dean, P.N.; Gillespie, C.W.; Greene, E.A.; Pearson, G.D.; Robb, A.S.; Berul, C.I.; Kaltman, J.R. (Congenital Heart Disease, 2015)
Background: Adolescents and young adults with congenital heart disease (CHD) are often restricted from physical activity and sports participation, which may have adverse effects. Objectives: To determine the amount of physical activity, type of sports participation, and reasons for sports restrictions, and to evaluate the effect of sports participation on quality of life (QoL) in a cohort of patients with CHD. Methods: Individuals with CHD aged 13-30 years were recruited at outpatient visits or via mailings. They completed a questionnaire addressing physical activity, sports participation, sports restrictions, and QoL (Pediatric Quality of Life Inventory). We also reviewed the patient's medical record. Results: Of the 177 patients who responded (mean age 20 years), 31% have mild CHD, 40% have moderate CHD, and 29% have severe CHD. In the cohort, 52% participate in competitive sports, 25% recreational sports, and 23% no sports. Among patients with severe CHD, 29% participate in competitive sports that would be restricted by published guidelines (36th Bethesda Conference). After controlling for age, sex, CHD severity, residual hemodynamic disease, and comorbidities, participation in competitive sports and increased frequency of physical activity are independently associated with a higher QoL (P = .003 and P = .001, respectively). In an identical model, competitive sports participation and frequency of physical activity are associated with higher maximum predicted oxygen consumption (VO2) (n = 40; P = .002 and .02) and slightly lower body mass index (BMI) (P = .02 and .01). All findings were similar when analyses were stratified by recruitment method. Conclusions: Patients with CHD commonly participate in competitive sports, and such participation is associated with higher QoL, improved exercise capacity, and lower BMI. © 2014 Wiley Periodicals, Inc.
Keywords: Adult congenital heart disease; Congenital heart disease; Sports cardiology; Sports participation

Effect of maternal diabetes on the embryo, fetus, and children: Congenital anomalies, genetic and epigenetic changes and developmental outcomes - Ornoy, A.; Reece, E.A.; Pavlinkova, G.; Kappen, C.; Miller, R.K. (Birth Defects Research Part C - Embryo Today: Reviews, 2015)
Introduction: Pregestational and gestational diabetes mellitus (PGDM; GDM) are significant health concerns because they are associated with an increased rate of malformations and maternal health complications. Methods: We reviewed the data that help us to understand the effects of diabetes in pregnancy. Results: Diabetic embryopathy can affect any developing organ system, but cardiovascular and neural tube defects are among the most frequent anomalies. Other complications include preeclampsia, preterm delivery, fetal growth abnormalities, and perinatal mortality. Neurodevelopmental studies on offspring of mothers with diabetes demonstrated increased rate of Gross and Fine motor abnormalities, of Attention Deficit Hyperactivity Disorder, learning difficulties, and possibly also Autism Spectrum Disorder. The mechanisms underlying the effects of maternal hyperglycemia on the developing fetus may involve increased oxidative stress, hypoxia, apoptosis, and epigenetic changes. Evidence for epigenetic changes are the following: not all progeny are affected and not to the same extent; maternal diet may influence pregnancy outcomes; and maternal diabetes alters embryonic transcriptional profiles and increases the variation between transcriptomic profiles as a result of altered gene regulation. Research in animal models has revealed that maternal hyperglycemia is a teratogen, and has helped uncover potential therapeutic targets which, when blocked, can mitigate or ameliorate the negative effects of diabetes on the developing fetus. Conclusions: Tight metabolic control, surveillance, and labor management remain the cornerstone of care for pregnant women with diabetes, but advances in the field indicate that new treatments to protect the mother and baby are not far from becoming clinical realities. © 2015 Wiley Periodicals, Inc.
Keywords: Congenital anomalies; Developmental disorders; Diabetic embryopathy; Epigenetics; GDM; PGDM

Early Results of Neurodevelopment Following Hybrid Stage I for Hypoplastic Left Heart Syndrome - Cheatham, S.L.; Carey, H.; Chisolm, J.L.; Heathcock, J.C.; Steward, D. (Pediatric Cardiology, 2015)
Motor skills and neurodevelopment in infants with hypoplastic left heart syndrome (HLHS) who have undergone Hybrid Stage I palliation is unknown. The purpose of this study is to assess early neurodevelopment in infants with HLHS after Hybrid Stage I palliation. Developmental assessment was performed in HLHS infants who underwent Hybrid Stage I palliation at 2 and 4 months of age using the Test of Infant Motor Performance, and at 6 months of age, prior to undergoing the second staged surgery, using the Bayley Scales of Infant and Toddler Development, 3rd edition (Bayley-III). Results were compared to healthy control subjects and norm-referenced data. The HLHS group scored between −1 and −2 standard deviations (SD) below the mean at 2 months of age (p = 0.002), and within −1 SD of the mean, at 4 months of age (p = 0.0019), on the TIMP. Compared to the control group, composite motor skills were significantly lower at 6 months of age on the Bayley-III in the HLHS group (p = 0.0489), however, not significant for cognitive (p = 0.29) or language (p = 0.68). Percentile rank motor scores were 17 ± 20 % in the HLHS group compared to 85 ± 12 % for the healthy age-matched control group. Infants with HLHS who undergo Hybrid Stage I palliation score lower on standardized motor skill tests compared to healthy age-matched controls and the norm-referenced population. This suggests that infants with HLHS have poorer motor skill performance than typically developing infants at 6 months of age. © 2014, Springer Science+Business Media New York.
Keywords: Congenital heart disease; Hybrid; Hypoplastic left heart syndrome; Neurodevelopment

Cyclic stretch of embryonic cardiomyocytes increases proliferation, growth, and expression while repressing Tgf-β signaling - Banerjee, I.; Carrion, K.; Serrano, R.; Dyo, J.; Sasik, R.; Lund, S.; Willems, E.; Aceves, S.; Meili, R.; Mercola, M.; Chen, J.; Zambon, A.; et al. (Journal of Molecular and Cellular Cardiology, 2015)
Perturbed biomechanical stimuli are thought to be critical for the pathogenesis of a number of congenital heart defects, including Hypoplastic Left Heart Syndrome (HLHS). While embryonic cardiomyocytes experience biomechanical stretch every heart beat, their molecular responses to biomechanical stimuli during heart development are poorly understood. We hypothesized that biomechanical stimuli activate specific signaling pathways that impact proliferation, gene expression and myocyte contraction. The objective of this study was to expose embryonic mouse cardiomyocytes (EMCM) to cyclic stretch and examine key molecular and phenotypic responses. Analysis of RNA-Sequencing data demonstrated that gene ontology groups associated with myofibril and cardiac development were significantly modulated. Stretch increased EMCM proliferation, size, cardiac gene expression, and myofibril protein levels. Stretch also repressed several components belonging to the Transforming Growth Factor-β (Tgf-β) signaling pathway. EMCMs undergoing cyclic stretch had decreased Tgf-β expression, protein levels, and signaling. Furthermore, treatment of EMCMs with a Tgf-β inhibitor resulted in increased EMCM size. Functionally, Tgf-β signaling repressed EMCM proliferation and contractile function, as assayed via dynamic monolayer force microscopy (DMFM). Taken together, these data support the hypothesis that biomechanical stimuli play a vital role in normal cardiac development and for cardiac pathology, including HLHS. © 2014 Elsevier Ltd.
Keywords: Cardiac development; Cardiomyocytes; Cell biology/structural biology; Contractile function; Contractility; Gene regulation; Hypoplastic Left Heart Syndrome; Mechanical stretch; Other myocardial biology; Pediatric and congenital heart disease; Physiologic and pathologic control of gene expression; Subject Codes

Physical and neurodevelopmental outcomes in children with single-ventricle circulation - Davidson, J.; Gringras, P.; Fairhurst, C.; Simpson, J. (Archives of Disease in Childhood, 2015)
Objective: To investigate longer-term physical and neurodevelopmental outcomes of patients with hypoplastic left heart syndrome (HLHS) compared with other patients with functionally single-ventricle circulation surviving beyond the age of 10 years. Design: A retrospective, observational study from a UK tertiary centre for paediatric cardiology. Results: 58 patients with HLHS and 44 non-HLHS patients with single-ventricle physiology were included. Subjective reduction in exercise tolerance was reported in 72% (95% CI 61% to 84%) of patients with HLHS and 45% (31% to 60%) non-HLHS patients. Compared with non-HLHS patients, educational concerns were reported more frequently in patients with HLHS, 41% (29% to 54%) vs 23% (10% to 35%), as was a diagnosis of a behaviour disorder (autism or attention deficit hyperactivity disorder) 12% (4% to 21%) vs 0%, and referral to other specialist services 67% (55% to 79%) vs 48% (33% to 63%). Conclusions: Within a group of young people with complex congenital heart disease, those with HLHS are likely to have worse physical, psychological and educational outcomes. © 2015, BMJ Publishing Group. All rights reserved.

Parental vigilance in caring for their children with hypoplastic left heart syndrome - Meakins, L.; Ray, L.; Hegadoren, K.; Rogers, L.G.; Rempel, G.R. (Pediatric Nursing, 2015)
Hypoplastic left heart syndrome (HLHS) is a complex heart malformation that requires life-saving treatments. Parents experience numerous challenges as they learn to parent a child with complex care requirements. The following research question guided this qualitative study: Is the parenting process among parents of a child with HLHS characterized by exaggerated vigilant parental action, and if so, how does this influence parental response? Situated within a larger program of pediatric cardiology research, this study included data from two grounded theory studies with parents of children with HLHS. This secondary analysis involved a thematic content analysis using sensitizing concepts of uncertainty, protectiveness, support, and mastery of complex care. Transcribed data from 55 interviews with 24 mothers and 17 fathers of young children with HLHS were analyzed for relevant and recurring themes. In mastering skills required to care for their child with HLHS, parents contrasted what was in their hands with what was out of their hands. Vigilant parental actions were evident as parents became skilled at providing complex care. Parents said they were sometimes excessive in their vigilant actions. In retrospect they viewed this vigilance as appropriate in some situations but exaggerated in other situations. Understanding parents’ vigilant actions in response to their child’s complex care can guide health care providers’ interactions with families. Long-term follow up, both clinically and through research, is needed to assess the long-term consequences of exaggerated vigilant parental action on the child, parent, and family, and to determine and evaluate appropriate and timely intervention. © 2015, Anthony J. Jannetti Publications, Inc. All rights reserved.

Hypoplastic left heart syndrome: Diagnosis, care and management from fetal life and beyond - Moodley, S.; Tacy, T.A. (NeoReviews, 2015)
Hypoplastic left heart syndrome (HLHS) accounts for 2% to 3% of all congenital heart disease but is responsible for 25% to 40% of all neonatal cardiac deaths. Although the exact genetic origins of HLHS have not been clearly defined, various genetic and chromosomal associations have been identified. Advancements in fetal echocardiography have resulted in accurate diagnosis of congenital heart disease. On the basis of physical examination findings, fetuses may be candidates for prenatal intervention. In general, after prenatal diagnosis of HLHS, parents are faced with 2 choices: termination or continuation of pregnancy. If pregnancy is continued to delivery, patients may choose comfort care, surgical palliation with the Fontan procedure, or transplantation. A once lethal congenital anomaly, HLHS has undergone a marked evolution in management and prognosis during the last several decades.With advancements in prenatal diagnosis, neonatal management, and surgical palliation, patient survival has drastically improved: at an experienced center, current survival rates are very high after the Norwood procedure, with high rates of overall freedom from death or transplantation through 20 years. With survival becoming more promising, the issues that now take precedence are neurodevelopmental outcomes, Fontan procedure complications, and quality of life. Although much progress has been made in caring for this patient population, HLHS remains a high-risk condition that requires lifelong medical follow-up and has significant long-term morbidity, affecting overall quality of life for patients and their families. © 2015 by the American Academy of Pediatrics. All rights reserved.

Pediatric heart transplantation - Schweiger, M.; Stiasny, B.; Dave, H.; Cavigelli-Brunner, A.; Balmer, C.; Kretschmar, O.; Bürki, C.; Klauwer, D.; Hübler, M. (Journal of Thoracic Disease, 2015)
Pediatric heart transplantation (pHTx) represents a small (14%) but very important and particular part in the field of cardiac transplantation. This treatment has lifelong impact on children. To achieve the best short and especially long-term survival with adequate quality of life, which is of crucial importance for this young patient population, one has to realize and understand the differences with adult HTx. Indication for transplantation, waitlist management including ABO incompatible (ABOi) transplantation and immunosuppression differ. Although young transplant recipients are ultimately likely to be considered for re-transplantation. One has to distinguish between myopathy and complex congenital heart disease (CHD). The differences in anatomy and physiology make the surgical procedure much more complex and create unique challenges. These recipients need a well-organized and educated team with pediatric cardiologists and intensivists, including a high skilled surgeon, which is dedicated to pHTx. Therefore, these types of transplants are best concentrated in specialized centers to achieve promising outcome.
Keywords: Heart defects congenital; Heart transplantation (HTx); Transplant recipients

Survival and quality of life for children with end-stage heart failure who are not candidates for cardiac transplant - Sabati, A.A.; Szmuszkovicz, J.R.; Herrington, C.; Hermes, M.; Mahmoud, H.A.; Phei Wee, C.; Starnes, V.A.; Menteer, J. (Journal of Heart and Lung Transplantation, 2015)
Background Some pediatric patients referred for heart transplant (HTx) are sub-optimal candidates. Their outcomes without HTx are presumed to be dismal, but have not been well described. Knowledge about their outcomes is critical when weighing the risks between a high-risk transplant and "terminal" palliation. Methods We retrospectively reviewed all HTx referrals from January 2005 to July 2013. We excluded those who were listed for HTx, or who were denied HTx due to being "too well," seeking only those who were in need of but not suitable for HTx. End-points included mortality and length of survival. Results Of 212 referrals, 39 (19%) (age 0 to 19 years, median 3.5 years) were denied HTx for reasons other than being too well. Twenty-eight (72%) had palliated congenital heart disease. Overall mortality during the follow-up period was 38% (n = 15) with a median follow-up time of 195 days (8 to 2,832 days). Ten patients received subsequent cardiac surgery with 1 death (10%) and median follow-up of 2.6 years. Mortality risk was not influenced by age, weight, growth failure, congenital heart disease or single-ventricle physiology. Mechanical ventilation (hazard ratio 6.31, p = 0.001) and inotrope dependence (hazard ratio 4.79, p = 0.006) were associated with the highest risk of mortality. Quality of life was measured with the PedsQL cardiac module and completed by 11 of 16 eligible patients with an overall average score of 70.2 ± 23.9. Conclusions An advanced heart failure program can achieve satisfactory results for pediatric patients who are not suitable candidates for HTx. For some children, high-risk palliative surgery can result in better outcome than high-risk HTx. Mortality was related to the degree of heart failure at presentation rather than underlying heart disease. © 2015 International Society for Heart and Lung Transplantation.
Keywords: alloimmunization; congenital heart disease; congenital heart surgery; panel reactive antibodies; Pediatric heart failure; pediatric heart transplant

Design of axial blood pumps for patients with dysfunctional fontan physiology: Computational studies and performance testing - Kafagy, D.H.; Dwyer, T.W.; Mckenna, K.L.; Mulles, J.P.; Chopski, S.G.; Moskowitz, W.B.; Throckmorton, A.L. (Artificial Organs, 2015)
Limited treatment options for patients having dysfunctional single ventricle physiology motivate the necessity for alternative therapeutic options. To address this unmet need, we are developing a collapsible axial flow blood pump. This study investigated the impact of geometric simplicity to facilitate percutaneous placement and maintain optimal performance. Three new pump designs were numerically evaluated. A transient simulation explored the impact of respiration on blood flow conditions over the entire respiratory cycle. Prototype testing of the top performing pump design was completed. The top performing Rec design generated the highest pressure rise range of 2-38mmHg for flow rates of 1-4L/min at 4000-7000RPM, exceeding the performance of the other two configurations by more than 26%. The blood damage indices for the new pump designs were determined to be below 0.5% and predicted hemolysis levels remained low at less than 7×10-5g/100L. Prototype testing of the Rec design confirmed numerical predictions to within an average of approximately 22%. These findings demonstrate that the pumps are reasonably versatile in operational ability, meet pressure-flow requirements to support Fontan patients, and are expected to have low levels of blood trauma. © 2015 International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Blood pump; Computational fluid dynamics; Fontan physiology; Intravascular blood pump; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Total cavopulmonary connection

Supporting families in neonatal loss: relationship and faith key to comfort - Holston, J.T. (Journal of Christian nursing : a quarterly publication of Nurses Christian Fellowship, 2015)
Around 20,000 neonatal deaths occur each year, many from congenital heart defects such as hypoplastic left heart syndrome. Nurses are on the frontline of caring for families experiencing neonatal loss. Careful spiritual and cultural assessment, attention to beliefs, focusing on relationship, and helping families create legacy can assist with grieving and making meaning out of loss.

Nutrition and growth in neonates undergoing cardiac surgery - Fogg, K.L.; Zyblewski, S.C. (NeoReviews, 2015)
Growth failure is a widespread health problem in infants with congenital heart disease, specifically infants with single ventricle heart lesions, including hypoplastic left heart syndrome. Optimizing nutrition delivery for neonates undergoing cardiac surgery is challenging given environmental and physiologic barriers. Concomitant with nutrition delivery challenges, wide practice variations exist among clinicians. Malnutrition and poor growth are associated with poor wound healing, increased infection risk, prolonged hospitalizations, and long-term neurodevelopmental disability, including worse school performance. The cause of early postnatal growth failure is multifactorial and related to the delay in onset of enteral feedings, increased metabolic stress of cardiac surgery, cyanosis, low cardiac output, increased energy expenditure, altered splanchnic perfusion, and gastrointestinal morbidities. In addition, cardiac infants are susceptible to unique complications, including chylothorax, vocal cord dysmotility, and swallowing dysfunction. © 2015 by the American Academy of Pediatrics. All rights reserved.

Survival data and predictors of functional outcome an average of 15years after the fontan procedure: The pediatric heart network fontan cohort - Atz, A.M.; Zak, V.; Mahony, L.; Uzark, K.; Shrader, P.; Gallagher, D.; Paridon, S.M.; Williams, R.V.; Breitbart, R.E.; Colan, S.D.; Kaltman, J.R.; Margossian, R.; et al. (Congenital Heart Disease, 2015)
Objective: Multicenter longitudinal outcome data for Fontan patients surviving into adulthood are lacking. The aim of this study was to better understand contemporary outcomes in Fontan survivors by collecting follow-up data in a previously well-characterized cohort. Design: Baseline data from the Fontan Cross-Sectional Study (Fontan 1) were previously obtained in 546 Fontan survivors aged 11.9 ± 3.4years. We assessed current transplant-free survival status in all subjects 6.8 ± 0.4years after the Fontan 1 study. Anatomic, clinical, and surgical data were collected along with socioeconomic status and access to health care. Results: Thirty subjects (5%) died or underwent transplantation since Fontan 1. Subjects with both an elevated (>21pg/mL) brain natriuretic peptide and a low Child Health Questionnaire physical summary score (<44) measured at Fontan 1 were significantly more likely to die or undergo transplant than the remainder, with a hazard ratio of 6.2 (2.9-13.5). Among 516 Fontan survivors, 427 (83%) enrolled in this follow-up study (Fontan 2) at 18.4 ± 3.4years of age. Although mean scores on functional health status questionnaires were lower than the general population, individual scores were within the normal range in 78% and 88% of subjects for the Child Health Questionnaire physical and psychosocial summary score, and 97% and 91% for the SF-36 physical and mental aggregate score, respectively. Since Fontan surgery, 119 (28%) had additional cardiac surgery; 55% of these (n = 66) in the interim between Fontan 1 and Fontan 2. A catheter intervention occurred in 242 (57%); 32% of these (n = 78) after Fontan 1. Arrhythmia requiring treatment developed in 118 (28%) after Fontan surgery; 58% of these (n = 68) since Fontan 1. Conclusions: We found 95% interim transplant-free survival for Fontan survivors over an average of 7years of follow-up. Continued longitudinal investigation into adulthood is necessary to better understand the determinants of long-term outcomes and to improve functional health status. © 2014 Wiley Periodicals, Inc.
Keywords: Congenital; Fontan procedure; Functional health status; Heart defects; Pediatrics

Unplanned admissions to a pediatric cardiac critical care unit: A review of 2 years' experience - Penk, J.S.; Loke, Y.-H.; Waloff, K.R.; Frank, L.H.; Stockwell, D.C.; Spaeder, M.C.; Berger, J.T. (Pediatric Critical Care Medicine, 2015)
OBJECTIVES: Unplanned admissions to the pediatric cardiac ICU may be a large and high-risk group. Our study describes the frequency of unplanned pediatric cardiac ICU admissions, their admission data, and outcomes. DESIGN: All admissions to a pediatric cardiac ICU over 2 years were reviewed and those that were unplanned were identified for a detailed chart abstraction. Demographic, laboratory, diagnostic, and outcome data were collected. Readmission or admission for adverse event was noted. SETTING: Single, tertiary, pediatric cardiac center. PATIENTS: All patients admitted unexpectedly to the pediatric cardiac critical care unit between May 2008 and May 2010. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: There were 1,203 admissions to the cardiac ICU, and 426 (35%) were unplanned. The most common reasons for admission were new heart disease (25%), infection (19%), arrhythmia (13%), and congestive heart failure (11%). The majority of unplanned admissions (62%) occurred at night. Shock was present at admission in 18.5% of patients. Structural heart disease was present in 79%, and 39% of those were patients with single ventricle. Overall mortality among unplanned admissions was 7.3%, which is higher than that reported for elective surgical admissions. Mortality for the subset of patients readmitted within 30 days was 5.5%. Mean creatinine at admission was higher among nonsurvivors (0.7) than survivors (0.5). CONCLUSIONS: Unplanned admissions accounted for over one third of all admissions and had a high mortality rate. The majority of these occur at night, which may affect staffing models. Acute deterioration leading to unplanned admission, rather than readmission status, may be the driving factor in increased mortality. However, the risk of readmission, lower renal function, or other indices may identify patients at higher risk of an unplanned admission. Continued efforts to identify patients at risk for unplanned admissions are warranted given the outcomes in this cohort. Copyright © 2015 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: cardiac intensive care unit; mortality; outcomes; pediatric critical care; readmissions; unplanned admissions

Prenatally diagnosed neck masses: Long-term outcomes and quality of life - Sheikh, F.; Akinkuotu, A.; Olutoye, O.O.; Pimpalwar, S.; Cassady, C.I.; Fernandes, C.J.; Ruano, R.; Lee, T.C.; Cass, D.L. (Journal of Pediatric Surgery, 2015)
Purpose To determine long-term outcomes of fetuses with neck masses (NM), including functional and cosmetic results. Methods A retrospective review was performed of all fetuses evaluated for NM from November 2001 to March 2014. Quality of life (QOL) was evaluated using the validated PedsQL™ questionnaire. Results Of 35 fetuses evaluated, 9 died perinatally and 1 died late from tracheostomy complications. NM ranged from 4 to 20 cm (mean, 9.1 cm); 18 were delivered by EXIT. Of 25 surviving patients, 22 had mass resection, 7 requiring more than one procedure. Surviving patients with lymphatic malformations (LM) had the highest incidence of moderate and severe disfigurement and a higher rate of persistent/recurrent disease (100% vs. 31%, p = 0.002) and cranial nerve dysfunction (50% vs. 0%, p = 0.005) compared to those with non-LM diagnoses. Of 9 children attending school, 78% achieve grades of A/B's. QOL for 13 patients revealed a mean score of 83/100 for physical and 78/100 for psychosocial functioning. Median follow-up was 6 years (7 months-17 years). Conclusion Unlike those with teratoma or other lesions, children with congenital cervicofacial LM are at high-risk for persistent disease, nerve dysfunction and moderate-severe disfigurement. There is substantial perinatal morbidity for fetuses with neck masses, but for those surviving, the long-term functional and cognitive outcomes are good. © 2015 Elsevier Inc.
Keywords: Cervical lymphatic malformation; Cervical teratoma; Cervical thyroid cyst; Cervical vascular malformation; Fetal neck mass

Exercise capacity in single-ventricle patients after Fontan correlates with haemodynamic energy loss in TCPC - Khiabani, R.H.; Whitehead, K.K.; Han, D.; Restrepo, M.; Tang, E.; Bethel, J.; Paridon, S.M.; Fogel, M.A.; Yoganathan, A.P. (Heart, 2015)
Objective: Elevated energy loss in the total cavopulmonary connection (TCPC) is hypothesised to have a detrimental effect on clinical outcomes in singleventricle physiology, which may be magnified with exercise. This study investigates the relationship between TCPC haemodynamic energy dissipation and exercise performance in single-ventricle patients. Methods: Thirty consecutive Fontan patients with TCPC and standard metabolic exercise testing were included. Specific anatomies and flow rates at rest and exercise were obtained from cardiac MR (CMR) and phaseencoded velocity mapping. Exercise CMR images were acquired immediately following supine lower limb exercise using a CMR-compatible cycle ergometer. Computational fluid dynamics simulations were performed to determine power loss of the TCPC anatomies using in vivo anatomies and measured flows. Results: A significant negative linear correlation was observed between indexed power loss at exercise and (a) minute oxygen consumption (r=-0.60, p<0.0005) and (b) work (r=-0.62, p<0.0005) at anaerobic threshold. As cardiac output increased during exercise, indexed power loss increased in an exponential fashion (y=0.9671x3.0263, p<0.0001). Conclusions: This is the first study to demonstrate the relationship between power loss and exercise performance with the TCPC being one of the few modifiable factors to allow for improved quality of life. These results suggest that aerobic exercise tolerance in Fontan patients may, in part, be a consequence of TCPC power loss. © 2014, BMJ Publishing Group. All rights reserved.

Anomalous Origin of Coronary Artery From Main Pulmonary Artery in Hypoplastic Left Heart Syndrome - Turiy, Y.; Douglas, W.; Balaguru, D. (Annals of Thoracic Surgery, 2015)
We report a case of anomalous origin of the left anterior descending coronary artery (LAD) from the main pulmonary artery in a child with hypoplastic left heart syndrome (mitral atresia/aortic atresia). Mechanical circulatory support was necessary because of the inability to wean from cardiopulmonary bypass after the Norwood procedure. The patient died at 4 months of age having continued depressed right ventricular function. The diagnosis was made during a catheterization performed 6 weeks after surgery because of concern for stenosis of Blalock-Taussig shunt. We believe his prolonged postoperative recovery and eventual demise can partially be attributed to lack of cardioplegia to the anomalous LAD territory during surgery. © 2015 The Society of Thoracic Surgeons

Risk factors of post-cardiac surgery diaphragmatic paralysis in children with congenital heart disease - Akbariasbagh, P.; Mirzaghayan, M.R.; Akbariasbagh, N.; Shariat, M.; Ebrahim, B. (Journal of Tehran University Heart Center, 2015)
Background: Injured phrenic nerve secondary to cardiac surgeries is the most common cause of diaphragmatic paralysis (DP) in infants. The aim of this study was to determine the risk factors for DP caused by congenital heart defect corrective surgeries in pediatrics. Methods: This cross-sectional study, conducted in a 2-year period (2006–2008), included 451 children with congenital heart diseases admitted to the Pediatric Cardiac Surgery Ward of Imam Khomeini Hospital. The diaphragmatic function was examined via fluoroscopy, and the frequency of DP and its relevant parameters were evaluated. Results: Of the 451 patients, comprising 268 males and 183 females at an age range of 3 days to 204 months (28.2 ± 33.4 months), 25 (5.5%) infants (60% male and 40% female, age range = 15 days to 132 months, 41.2 ± 28.1 months) had DP as follows: 48% unilateral right-sided and 36% unilateral left-sided. Additionally, 68% had cyanotic congenital heart disease and 84% had DP following total correction surgery. The highest prevalence rates of DP resulting in phrenic hemiparesis were observed after arterial switch operation, Fontan procedure, and Blalock–Taussig shunt surgery, respectively. Thirteen (52%) of the 25 DP patients underwent surgical diaphragmatic plication because of severe respiratory distress and dependency on mechanical ventilation, and most of the cases of plication underwent arterial switch operation. The rate of mortality was 24% (6 patients). Conclusion: DP with a prevalence of 5.5% was one of the most common complications secondary to cardiac surgeries in the infants included in the present study. Effective factors were age, weight, cyanotic congenital heart defects, and previous cardiac surgery. Diaphragmatic plication improved prognosis in severe cases. © 2015, Tehran Heart Center. All rights reserved.
Keywords: Cardiac surgical procedures; Diaphragmatic; Infant, newborn; Phrenic nerve

Mitral atresia with hypoplastic left ventricle and multiple shunt lesions - Aliyu, I.; Gambo, S.; Igoche, P.D. (Journal of Cardiovascular Echography, 2015)
Mitral atresia is a rare congenital heart defect when compared to atresia of other valves and it is often associated with other cardiac malformation such as patent ductus arteriosus, coarctation of the aorta, transposition of the great arteries, pulmonary stenosis, shunt defects, cor triatriatum, chamber, and valvular anomalies. There have been few reports of mitral atresia, therefore, the case of a 5-month-old male child with complaint of difficulty with breathing and echocardiographic diagnosis of atretic mitral valves, atrial septal defect of 15 mms, ventricular septal defect (VSD) of 10 mms and hypoplastic left ventricle is reported.
Keywords: Atrial septal defect; mitral atresia; ventricular hypoplasia; ventricular septal defect

Hospital Resource Utilization for Common Noncardiac Diagnoses in Adult Survivors of Single Cardiac Ventricle - Seckeler, M.D.; Moe, T.G.; Thomas, I.D.; Meziab, O.; Andrews, J.; Heller, E.; Klewer, S.E. (American Journal of Cardiology, 2015)
Single ventricle congenital heart disease (SV CHD) has transformed from a nearly universally fatal condition to a chronic illness. As the number of adults living with SV CHD continues to increase, there needs to be an understanding of health care resource utilization (HCRU), particularly for noncardiac conditions, for this patient population. We performed a retrospective database review of the University HealthSystem Consortium Clinical Database/Resource Manager for adult patients with SV CHD hospitalized for noncardiac conditions from January 2011 to November 2014. Patients with SV CHD were identified using International Classification of Disease (ICD)-9 codes associated with SV CHD (hypoplastic left heart, tricuspid atresia, and SV) and stratified into 2 groups by age (18 to 29 years and 30 to 40 years). Direct cost, length of stay (LOS), intensive care unit (ICU) admission rate and mortality data were compared with age-matched patients without CHD. There were 2,083,651 non-CHD and 590 SV CHD admissions in Group 1 and 2,131,046 non-CHD and 297 SV CHD admissions in Group 2. There was no difference in LOS in Group 1, but there were higher costs for several diagnoses. LOS and costs were higher for several diagnoses in Group 2. ICU admission rate and in-hospital mortality were higher for several diagnoses for patients with SV CHD in both groups. In conclusion, adults with SV CHD admitted for noncardiac diagnoses have higher HCRU (longer LOS and higher ICU admission rates) compared with similarly aged patients without CHD. These findings stress the importance of good primary care in this population with complex, chronic cardiac disease to prevent hospitalizations and higher HCRU. © 2015 Elsevier Inc.

Tricuspid atresia and pulmonary atresia in a child with Rubinstein-Taybi syndrome - Loomba, R.S.; Geddes, G. (Annals of Pediatric Cardiology, 2015)
Rubinstein-Taybi syndrome is a well-characterized condition causing distinctive physical characteristics, intellectual disability, and multiple congenital malformations. Cardiac abnormalities are found in a third of individuals with this condition and usually consist of isolated septal defects or patent ductus arteriosus, although more complex congenital lesions have been described. We present the first reported case of tricuspid atresia and pulmonary atresia with hypoplasia of the right ventricle in the setting of Rubenstein-Taybi syndrome.
Keywords: Hypoplastic right ventricle; Rubinstein-Taybi syndrome; tricuspid atresia

Prenatal counseling and care for single-ventricle heart disease: One center's model for care - Lafranchi, T.; Lincoln, P. (Critical Care Nurse, 2015)
Advances in prenatal imaging allow early detection of single-ventricle congenital heart disease, which may enhance prenatal care and maximize care options and decision making. Boston Children's Hospital's Advanced Fetal Care Center and fetal cardiology program provide prenatal counseling and care for single-ventricle congenital heart disease. Key points for optimal prenatal counseling and education include explanation of the diagnosis, delivery, the first surgery, cardiac neurodevelopmental issues, feeding and growth issues, quality of life and long-term care, family stressors, and fetal cardiac intervention. Such counseling and education help families make the difficult decisions required in this situation. © 2015 American Association of Critical-Care Nurses.

Association of Interstage Home Monitoring with Mortality, Readmissions, and Weight Gain: A Multicenter Study from the National Pediatric Cardiology Quality Improvement Collaborative - Oster, M.E.; Ehrlich, A.; King, E.; Petit, C.J.; Clabby, M.; Smith, S.; Glanville, M.; Anderson, J.; Darbie, L.; Beekman, R.H. (Circulation, 2015)
Background-Daily home monitoring of oxygen saturation and weight has been reported to improve outcomes for patients with single-ventricle heart disease during the period between stage I palliation and stage II palliation. However, these studies have been limited to single institutions and used historical control subjects. Our objective was to determine the association of various interstage home monitoring strategies with outcomes using a multicenter cohort with contemporary control subjects. Methods and Results-We performed a retrospective cohort study using prospectively collected data from the National Pediatric Cardiology Quality Improvement Collaborative from 2008 to 2012. We compared interstage mortality, unscheduled readmissions, and change in weight-for-age Z score for various home monitoring strategies of oxygen saturation (n=494) or weight (n=472), adjusting for sex, syndrome, tricuspid regurgitation, arch obstruction, and shunt type. Overall interstage mortality was 8.1%, and 47% had ≥1 unscheduled readmission. We did not find any associations of home oxygen saturation or weight monitoring with mortality or readmission. Although there was no difference in weight-for-age Z score for daily (0.33±0.12) versus weekly (0.34±0.18, P=0.98) weight monitoring, daily home weight monitoring was superior to no home weight monitoring (-0.15±0.18; P<0.01). Conclusions-Home weight monitoring is associated with improved weight gain during the interstage period, but we did not find any benefits in other clinical outcomes for either home oxygen saturation monitoring or home weight monitoring. © 2015 American Heart Association, Inc.
Keywords: heart defects, congenital; home care services; hypoxia; mortality; patient readmission

Iatrogenic aortopulmonary communications after transcatheter interventions on the right ventricular outflow tract or pulmonary artery: Pathophysiologic, diagnostic, and management considerations - Torres, A.; Sanders, S.P.; Vincent, J.A.; El-Said, H.G.; Leahy, R.A.; Padera, R.F.; McElhinney, D.B. (Catheterization and Cardiovascular Interventions, 2015)
Objectives To investigate the spectrum, etiology, and management of traumatic aortopulmonary (AP) communications after transcatheter interventions on the pulmonary circulation. Background An iatrogenic AP communication is an unusual complication after balloon pulmonary artery (PA) angioplasty or stenting, or transcatheter pulmonary valve replacement (TPVR). However, with the increasing application of transcatheter therapies for postoperative PA stenosis and right ventricular outflow tract (RVOT) dysfunction, including percutaneous pulmonary valve replacement, consideration of the etiology, diagnosis, and management of this problem is important for interventional cardiologists performing such procedures. Methods and Results We present three new cases, as well as gross anatomy and histopathology data, related to AP communications after PA interventions. We also review the literature relevant to this topic. Including these new cases, there have been 18 reported cases of iatrogenic AP communication after transcatheter interventions on the PAs or RVOT, primarily patients with transposition of the great arteries who underwent PA angioplasty after an arterial switch operation, or after TPVR in patients who had undergone a Ross procedure. The likely cause of such defects is PA trauma plus distortion of the neo-aortic anastomosis resulting from angioplasty or stenting of the RVOT or central PAs, with subsequent dissection through the extravascular connective tissue and into the closely adjacent vessel through the devitalized tissue at the anastomosis. Conclusions Cardiologists performing PA or RVOT interventions should be aware of the possibility of a traumatic AP communication and consider this diagnosis when confronted with suggestive signs and symptoms. © 2015 Wiley Periodicals, Inc. © 2015 Wiley Periodicals, Inc.
Keywords: balloon angioplasty; complications; congenital heart disease; pediatric catheterization/intervention; pediatrics; percutaneous intervention; pulmonary valve disease; stent bare metal

Combined surgical and interventional approaches for treating patients with congenital heart disease - Vida, V.L.; Guariento, A.; Zucchetta, F.; Padalino, M.A.; Milanesi, O.; Maschietto, N.; Stellin, G. (Journal of Cardiac Surgery, 2015)
Aims During the last decade the cooperation between surgeons and cardiologists has further expanded by combining surgical and interventional techniques (CCBSI) performed in the operating room, without the use of fluoroscopy. We sought to evaluate the results of our experience with CCBSI. Methods All children with congenital heart disease (CHD) who underwent a CCBSI in the operating room between June 2007 and January 2014 were enrolled. Results Sixty-eight patients were included. Median age at CCBSI was five months (range 1-48 months). The three main diagnoses leading to surgery included: (1) tetralogy of Fallot (TOF) (n = 40), (2) muscular ventricular septal defects (VSD) (n = 12), (3) single ventricle with pulmonary artery branch stenosis (n = 4). There were 72 catheter-based procedures associated with surgical maneuvres, including: (1) transatrial balloon dilation (BD) of the pulmonary valve (n = 45), (2) transinfundibular BD of the main pulmonary artery trunk (n = 12), (3) perventricular VSD closure with septal occluder (n = 8), (4) BD of pulmonary artery branches (n = 5), and other less common procedures (n = 2). There were no procedure-related complications and no hospital deaths. Median follow-up time was four years (range 0.95-7.9 years). There was one late death for respiratory distress after transapical balloon dilation of the aortic valve. One patient required BD and stenting of the left pulmonary artery branch 3.6 years after intraoperative BD for residual stenosis. Conclusions The CCBSI represents a safe and effective treatment for selected patients with complex CHD. It will be helpful in minimizing patients' surgical trauma and in shortening or avoiding the use of cardiopulmonary bypass. © 2015 Wiley Periodicals, Inc.

Heart transplantation in adults with congenital heart disease: 100% survival with operations performed by a surgeon specializing in congenital heart disease in an adult hospital - Mori, M.; Vega, D.; Book, W.; Kogon, B.E. (Annals of Thoracic Surgery, 2015)
Background Cardiac transplantation in adult patients with congenital heart disease poses numerous challenges. The optimal operative and postoperative management strategies remain unclear. The purpose of our study was to (1) characterize the adult patient with a congenital heart condition undergoing transplantation, the operation, and the postoperative course; (2) report the survival after heart transplantation at our center; and (3) discuss issues surrounding the unique setting we provide for the operative and postoperative care of this complex patient cohort. Methods We performed a retrospective cohort study of 12 consecutive adult patients with a prior history of congenital heart disease who underwent heart transplantation at a single, large, academic center between September 1, 2005, and September 1, 2013. The operations were performed by a surgeon specializing in congenital heart disease in an adult hospital. Postoperative care was provided jointly by that surgeon and the adult cardiac transplantation team. Results At operation, the median age and weight were 41 years (range, 16 to 72 years) and 65 kg (range, 45 to 104 kg), and 100% of patients had undergone previous operations. The median donor ischemic time was 197 minutes (range, 137 to 282 minutes). The median cardiopulmonary bypass time was 210 minutes (range, 175 to 457 minutes), and the median total operating time was 582 minutes (range, 389 to 968 minutes). Three patients required mechanical support to be weaned from cardiopulmonary bypass. Postoperatively, 3 patients required the addition of mechanical support in the intensive care unit, and 3 patients required tracheostomy for prolonged ventilation. The majority of patients had a complicated postoperative course (66%). The median number of noncardiac consultants required to help care for these patients was four (range, two to 12). The mortality was 0%. Conclusions Cardiac transplantation in adults with congenital cardiac disease is challenging, is fraught with adverse events, and requires meticulous care and teamwork for success. A surgeon specializing in congenital heart conditions may be best to handle the operative challenges, and an adult hospital with access to certain technology and consultant services may be best to handle the postoperative challenges in this difficult patient population. © 2015 The Society of Thoracic Surgeons.

Intratracheal heparin improves plastic bronchitis due to sulfur mustard analog - Houin, P.R.; Veress, L.A.; Rancourt, R.C.; Hendry-Hofer, T.B.; Loader, J.E.; Rioux, J.S.; Garlick, R.B.; White, C.W. (Pediatric Pulmonology, 2015)
Background: Inhalation of sulfur mustard (SM) and SM analog, 2-chloroethyl ethyl sulfide (CEES), cause fibrinous cast formation that occludes the conducting airways, similar to children with Fontan physiology-induced plastic bronchitis. These airway casts cause significant mortality and morbidity, including hypoxemia and respiratory distress. Our hypothesis was that intratracheal heparin, a highly cost effective and easily preserved rescue therapy, could reverse morbidity and mortality induced by bronchial cast formation. Methods: Sprague-Dawley rats were exposed to 7.5% CEES via nose-only aerosol inhalation to produce extensive cast formation and mortality. The rats were distributed into three groups: non-treated, phosphate-buffered saline (PBS)-treated, and heparin-treated groups. Morbidity was assessed with oxygen saturations and clinical distress. Blood and bronchoalveolar lavage fluid (BALF) were obtained for analysis, and lungs were fixed for airway microdissection to quantify the extent of airway cast formation. Results: Heparin, given intratracheally, improved survival (100%) when compared to non-treated (75%) and PBS-treated (90%) controls. Heparin-treated rats also had improved oxygen saturations, clinical distress and airway cast scores. Heparin-treated rats had increased thrombin clotting times, factor Xa inhibition and activated partial thromboplastin times, indicating systemic absorption of heparin. There were also increased red blood cells (RBCs) in the BALF in 2/6 heparin-treated rats compared to PBS-treated control rats. Conclusions: Intratracheal heparin 1 hr after CEES inhalation improved survival, oxygenation, airway obstruction, and clinical distress. There was systemic absorption of heparin in rats treated intratracheally. Some rats had increased RBCs in BALF, suggesting a potential for intrapulmonary bleeding if used chronically after SM inhalation. © 2014 Wiley Periodicals, Inc.
Keywords: CEES; Heparin; Inhalation injury; Plastic bronchitis; Pulmonology; Sulfur mustard

Acute ischaemic heart block in hypoplastic left heart syndrome - Burkett, D.A.; Wilson, N.; Mitchell, M.B.; Younoszai, A.K. (Cardiology in the Young, 2014)
In hypoplastic left heart syndrome, thrombosis of the native ascending aorta is rare and often fatal; there are no previously reported cases presenting with acute heart block. We review a case of native ascending aorta thrombosis in a 2-year-old boy with hypoplastic left heart syndrome, presenting with acute heart block. This case highlights the benefit of multi-modality imaging in complex cases. © Cambridge University Press 2014.
Keywords: complete heart block; congenital heart disease; Echocardiography; myocardial infarction

Genetic knowledge and attitudes of parents of children with congenital heart defects - Fitzgerald-Butt, S.M.; Klima, J.; Kelleher, K.; Chisolm, D.; Mcbride, K.L. (American Journal of Medical Genetics, Part A, 2014)
Clinical genetic testing for specific isolated congenital heart defects (CHD) is becoming standard of care in pediatric cardiology practice. Both genetic knowledge and attitudes toward genetic testing are associated with an increased utilization of genetic testing, but these factors have not been evaluated in parents of children with CHD. We mailed a survey to measure the demographics, genetic knowledge, and attitudes towards genetic testing of parents of children with CHD who previously consented to participate in a separate research study of the genetic etiology of left ventricular outflow tract malformations (LVOT). Of the 378 eligible families, 190 (50%) returned surveys with both parents completing surveys in 97 (51%) families, resulting in 287 participants. Genetic knowledge was assessed on an adapted measure on which the mean percent correct was 73.8%. Educational attainment and household income were directly and significantly associated with genetic knowledge (P<0.001). Attitudes about the health effects of genetic testing were favorable with at least 57% agreeing that genetic testing would be used for managing health care and finding cures for disease. Conversely, a minority of participants found it likely that genetic testing would be used for insurance (up to 39.9%), employment (15.8%), or racial/social discrimination (up to 11.2%). Parents of younger children were less likely to endorse employment or racial/social discrimination. Genetic knowledge was not correlated with specific attitudes. Among parents of children with CHD, genetic knowledge was directly associated with household income and education, but additional research is necessary to determine what factors influence attitudes towards genetic testing. © 2014 Wiley Periodicals, Inc.
Keywords: And practice; Attitudes; Congenital; Genetic testing; Health knowledge; Heart defects; Multifactorial inheritance

Maternal depression, antidepressant prescriptions, and congenital anomaly risk in offspring: A population-based cohort study - Ban, L.; Gibson, J.E.; West, J.; Fiaschi, L.; Sokal, R.; Smeeth, L.; Doyle, P.; Hubbard, R.B.; Tata, L.J. (BJOG: An International Journal of Obstetrics and Gynaecology, 2014)
Objective: To estimate risks of major congenital anomaly (MCA) among children of mothers prescribed antidepressants during early pregnancy or diagnosed with depression but without antidepressant prescriptions. Design: Population-based cohort study. Setting: Linked UK maternal-child primary care records. Population: A total of 349 127 singletons liveborn between 1990 and 2009. Methods: Odds ratios adjusted for maternal sociodemographics and comorbidities (aORs) were calculated for MCAs, comparing women with first-trimester selective serotonin reuptake inhibitors (SSRIs) or tricyclic antidepressants (TCAs) and women with diagnosed but unmedicated depression, or women without diagnosed depression. Main: outcome measures Fourteen system-specific MCA groups classified according to the European Surveillance of Congenital Anomalies and five specific heart anomaly groups. Results: Absolute risks of MCA were 2.7% (95% confidence interval, 95% CI, 2.6-2.8%) in children of mothers without diagnosed depression, 2.8% (95% CI 2.5-3.2%) in children of mothers with unmedicated depression, and 2.7% (95% CI 2.2-3.2%) and 3.1% (95% CI 2.2-4.1%) in children of mothers with SSRIs or TCAs, respectively. Compared with women without depression, MCA overall was not associated with unmedicated depression (aOR 1.07, 95% CI 0.96-1.18), SSRIs (aOR 1.01, 95% CI 0.88-1.17), or TCAs (aOR 1.09, 95% CI 0.87-1.38). Paroxetine was associated with increased heart anomalies (absolute risk 1.4% in the exposed group compared with 0.8% in women without depression; aOR 1.78, 95% CI 1.09-2.88), which decreased marginally when compared with women with diagnosed but unmedicated depression (aOR 1.67, 95% CI 1.00-2.80). Conclusions: Overall MCA risk did not increase with maternal depression or with antidepressant prescriptions. Paroxetine was associated with increases of heart anomalies, although this could represent a chance finding from a large number of comparisons undertaken. © 2014 The Authors.
Keywords: Antidepressants; Congenital anomaly; Depression; SSRIs; TCAs

Maternal bond with cardiosurgically treated infant. Qualitative analysis of mothers' narratives - Sikora, K.; Janusz, B. (Developmental period medicine, 2014)
The aim of this work is to describe the experience of being a mother by women who together with their children stay on the ward after cardiac surgical correction of congenital heart defects. The research material consisted of the narratives of mothers whose children were born with a heart defect and surgically treated. Four women aged 21-30 years were participants of this study. The age of the subjects' children ranged from 5 weeks to 1 year and three months. The heart defects with which the children were born were hypoplastic left heart syndrome (HLHS ) or atrioventricular canal defect. The research was carried out using the narrative interview. Qualitative analysis was carried out according to the rules of thematic analysis. The results of the research confirm that cardiac treatment can have a significant impact on maternal care patterns and the mother-infant bonding process. Intermittent contact with an infant can lead to loss of control over what happens to the child and the loss of a sense of competence to care for him. Medical staff face the challenge of supporting the parents of hospitalized children in the process of building relationships with a sick infant. The actions of doctors and nurses to enable parents to care for a baby can help foster their sense of competence and responsibility.

First-trimester exposure to bupropion and risk of cardiac malformations - Louik, C.; Kerr, S.; Mitchell, A.A. (Pharmacoepidemiology and Drug Safety, 2014)
Purpose: Bupropion is a drug uniquely used both to treat depression and as an aid to smoking cessation. We investigated previously reported associations between first-trimester exposure to bupropion and cardiac defects. Methods: Using data gathered since 2003 by the Slone Epidemiology Center's Case-control Birth Defects Study, we classified subjects with cardiac defects into subgroups. Exposure categories included first-trimester bupropion alone or in combination with other antidepressants, first-trimester antidepressants other than bupropion, and no exposure to any antidepressant at any time from 2months prior to pregnancy through delivery. We calculated odds ratios and 95% confidence intervals, controlling for confounding using logistic regression. Results: There were 8611 non-malformed infants and 7913 infants with cardiac defects. Eight cardiac subgroups had sufficient subjects (two or more exposed cases) for analysis. The adjusted odds ratio (aOR) for first-trimester bupropion use in relation to ventricular septal defect (VSD) was slightly elevated (1.6, 95% confidence interval 1.0-2.8); for exposure to bupropion alone, the aOR was 2.5 (95% confidence interval 1.3-5.0). Risks were not materially elevated for bupropion in relation to the other seven cardiac subgroups. Conclusions: We did not confirm previously reported associations for left-sided defects overall but had too few exposed cases to evaluate specific defects in this category. We did observe an elevated risk of VSD following first-trimester bupropion use, particularly when used without other antidepressants. This pattern for bupropion alone was observed in all our risk comparisons and was not explained by higher doses or gestational timing. © 2014 John Wiley & Sons, Ltd.
Keywords: Antidepressants; Bupropion; Cardiac malformations; Pharmacoepidemiology

Effect of exercise training on sports enjoyment and leisure-time spending in adolescents with complex congenital heart disease: The moderating effect of health behavior and disease Knowledge - Dulfer, K.; Duppen, N.; Blom, N.A.; van Dijk, A.P.J.; Helbing, W.A.; Verhulst, F.C.; Utens, E.M.W.J. (Congenital Heart Disease, 2014)
Objective: The aim of this study was to evaluate the effects of a standardized exercise program on sports enjoyment and leisure-time spending in adolescents with congenital heart disease and to know what the moderating impact of their baseline health behavior and disease knowledge is. Methods: Included were 93 patients, aged 10 to 25, with surgical repair for tetralogy of Fallot or with a Fontan circulation for single-ventricle physiology, of 5 participating centers of pediatric cardiology in NLD. They were randomly allocated, stratified for age, gender, and type of congenital heart disease to a 12-week period with either: (1) three times per week standardized exercise training or (2) care as usual (randomization ratio 2:1). At baseline and after 12 weeks, participants completed Web-based questionnaires and were interviewed by phone. Outcome Measures: Primary analyses tested changes from baseline to follow-up in sports enjoyment and leisure-time spending in the exercise group vs. control group. Secondary analyses concerned the moderating influence of baseline health behavior and disease knowledge on changes from baseline to follow-up, and comparison with normative data. Results: At follow-up, the exercise group reported a decrease in passive leisure-time spending (watching television and computer usage) compared with controls. Exercise training had no effect on sports enjoyment and active leisure-time spending. Disease knowledge had a moderating effect on improvement in sports enjoyment, whereas health behavior did not. Compared with normative data, patients obtained similar leisure time scores and lower frequencies as to drinking alcohol and smoking. Conclusions: Exercise training decreased passive, but not active, leisure-time spending. It did not influence sports enjoyment. © 2013 Wiley Periodicals, Inc.
Keywords: Adolescents; Aerobic Exercise; Behavior; Children; Congenital Heart Disease; Randomized Controlled Trial

Challenges in implementing a pediatric cardiovascular home telehealth project - Black, A.K.; Sadanala, U.K.; Mascio, C.E.; Hornung, C.A.; Keller, B.B. (Telemedicine and e-Health, 2014)
Objective: Infants with "single ventricle" congenital heart disease are at high risk for sudden death following palliative surgical management. We developed a pilot telemedicine project to evaluate the feasibility of using Web-based daily reporting of clinical data with the goal of reducing unexpected admissions and sudden death. Subjects and Methods: We enrolled 9 subjects (enrolled subjects [ES]) following surgical palliation over 12 months. Parents electronically transmitted ES daily weight and oxygen saturation and then completed an automated 10-point phone questionnaire on nutrition, activity, and distress. Subject enrollment continued until a second surgical palliative procedure (n=5), sudden death (n=2), or disenrollment (n=2). We collected clinical data on all ES and 9 historical controls (HC) from the preceding 18 months and analyzed clinical management, including outpatient telephone surveillance success, scheduled and unscheduled office and emergency department visits, hospitalizations, procedures, and adverse events, including death. Results: Subject recruitment was more difficult than expected. Weight transmission success was high, but there was poor correlation between telemedicine system-measured oxygen saturation and a commercial monitor. The outpatient clinical telephone surveillance success rate for HC and ES was approximately 30%. After technical adjustments, parents of all ES (100%) were able to transmit questionnaire data. There were 9 emergency room visits for ES versus 11 unscheduled emergency room visits for HC. Sudden death occurred in 1 of 9 HC and 2 of 9 ES. Conclusions: Telemedicine monitoring for high-risk congenital heart disease patients is feasible but challenging, may reduce unscheduled visits, but may not impact the primary end point of preventing sudden death in this high-risk pediatric population. © 2014 Mary Ann Liebert, Inc.
Keywords: congenital heart disease; home health monitoring; hypoplastic left heart syndrome; interstage sudden death; pediatrics; telemedicine

Foetal therapy, what works? An overview - Mellander, M.; Gardiner, H. (Cardiology in the Young, 2014)
The update course in foetal cardiology held by the Fetal Working Group of the Association for European Paediatric and Congenital Cardiology in Istanbul in May 2012 included a session on foetal cardiac therapy. In the introductory overview to this symposium, we critically examine the level of evidence supporting or refuting proposed foetal cardiac therapies including transplacental treatment of foetal tachyarrhythmias, steroid treatment in foetal atrioventricular block, and foetal aortic valvuloplasty. In summary, the evidence for the ef ficiency and safety of currently available foetal cardiac therapies is low, with no therapy based on a randomised controlled trial. Transplacental treatment of foetal tachycardia is generally accepted as effective and safe, based on extensive and widespread clinical experience; however, there is no consensus on which drugs are the most effective in different electrophysiological situations. Randomised studies may be able to resolve this, but this is complicated because tachyarrhythmias are relatively rare conditions, the foetus is not accessible for direct treatment, and it is the healthy mother who accepts treatment she does not need on behalf of her foetus. The indications for steroid treatment in foetal atrioventricular block and for foetal valvuloplasty are even more controversial. Although randomised trials would be desirable, the practical issues of recruiting sufficient sample sizes and controlling for variation in practice across multiple sites is not to be underestimated. Multicentre registries, analysed free of bias, may be an alternative way to improve the evidence base of foetal cardiac therapy. © Cambridge University Press, 2014.
Keywords: Evidence based medicine; Foetal heart; Foetal therapies

Hemodynamic causes of exercise intolerance in Fontan patients - Hebert, A.; Jensen, A.S.; Mikkelsen, U.R.; Idorn, L.; Sørensen, K.E.; Thilen, U.; Hanseus, K.; Søndergaard, L. (International Journal of Cardiology, 2014)
Background Exercise intolerance is frequent among Fontan patients and an important determinant for quality of life. This study investigated the hemodynamic causes of impaired exercise capacity in Fontan patients with particular focus on the influence of stroke volume index (SVI) and heart rate (HR). Methods and results In 38 Fontan patients, peak oxygen consumption (VO2), SVI and HR were recorded during incremental load exercise test and compared with 19 age and gender matched controls. SVI (ml/m2) was lower in patients than controls during warm-up (28[26-31] vs. 35[30-39], p = 0.0093), at submaximal (40[37-43] vs. 55[51-59], p < 0.0001) and at maximal exercise (38[35-40] vs. 54[51-58], p < 0.0001). Similarly, HR (% of expected maximum) was lower in patients at warm-up (45[43-48]% vs. 64[57-64]%, p < 0.0001), submaximal (71[68-75]% vs 85[82-88]%, p < 0.0001) and maximal exercise (84[80-88]% vs. 97[95-99]%, p < 0.0001). Furthermore, SVI dropped 14% (from 44[41-48] to 38[35-40] ml/m2) in Fontan patients from the peak plateau to maximal exercise vs. 5% (from 57[53-61] to 54[51-58] ml/m 2) in controls, p < 0.0001. The low SVI and HR explained 67% and 20% of the difference in peak VO2 between Fontan patients and controls respectively. Conclusion SVI decreased significantly in Fontan patients near the end of maximal effort exercise. The low SVI at maximal exercise was the most important hemodynamic factor limiting exercise capacity in Fontan patients, whereas chronotropic impairment had a smaller impact. The low SVI and HR at maximal exercise accounted for the difference in peak VO2 between Fontan patients and controls in this study. Clinical trial registration http://www.cvk.sum.dk/CVK/Home/English.aspx (protocol nr: H-3-2010-045). © 2014 Elsevier Ireland Ltd. All rights reserved.
Keywords: Cardio-pulmonary exercise test; Chronotropic impairment; Fontan; Stroke volume

Successful treatment of plastic bronchitis by selective lymphatic embolization in a Fontan patient - Dori, Y.; Keller, M.S.; Rychik, J.; Itkin, M. (Pediatrics, 2014)
Plastic bronchitis is a rare and often fatal complication of single-ventricle surgical palliation after total cavopulmonary connection. Although lymphatic abnormalities have been postulated to play a role in the disease process, the etiology and pathophysiology of this complication remain incompletely understood. Here we report on the etiology of plastic bronchitis in a child with total cavopulmonary connection as demonstrated by magnetic resonance (MR) lymphangiography. We also report on a new treatment of this disease. The patient underwent noncontrast T2-weighted MR lymphatic mapping and dynamic contrast MR lymphangiography with bi-inguinal intranodal contrast injection to determine the anatomy and flow pattern of lymph in his central lymphatic system. The MRI scan demonstrated the presence of a dilated right-sided peribronchial lymphatic network supplied by retrograde lymphatic flow through a large collateral lymphatic vessel originating from the thoracic duct. After careful analysis of the MRI scans we performed selective lymphatic embolization of the pathologic lymphatic network and supplying vessel. This provided resolution of plastic bronchitis for this patient. Five months after the procedure, the patient remains asymptomatic off respiratory medications. Copyright © 2014 by the American Academy of Pediatrics.
Keywords: Fontan; Lymphatics; Plastic bronchitis; Single ventricle

Psychosocial responses of parents to their infant's diagnosis of hypoplastic left heart syndrome - Cantwell-Bartl, A.M.; Tibballs, J. (Cardiology in the Young, 2014)
Objective: To evaluate the psychosocial status of mothers and fathers in response to their infant's diagnosis of hypoplastic left heart syndrome. Design: A study on interviews with parents whose children had survived staged surgery. Setting: Tertiary hospital paediatric ICU. Subjects: A total of 29 parents (16 mothers and 13 fathers) of surviving children. Intervention: A semi-structured face-to-face interview was conducted to explore experiences of parents in response to their infant's diagnosis, their interaction with the doctor delivering the diagnosis, their deliberation about staged surgery, and their reasons for this choice. Measurement and Main Results: All parents were devastated about their infant's diagnosis, and most (83%) of them said that the time of the diagnosis and the aftermath was the worst time of their lives. Parents reported helpful and unhelpful communication at this time. Although all parents in this study chose surgery for their infant, when faced with the choice, 17 of them made an immediate decision to protect their infant's life, 8 were initially unsure when their infant was diagnosed in utero, and 4 were unsure when the infant was diagnosed after birth. Parents also experienced loss and other stressors. Conclusions: All parents of the infants diagnosed with hypoplastic left heart syndrome experienced intense loss and stressors. Physicians need to be sensitive to the needs and thinking of the parents when discussing treatment options before surgery. The nature of the relationship with the doctor at this time can support parents or be a further source of stress. © © Cambridge University Press 2014.
Keywords: adaptation; hypoplastic left heart syndrome; Intensive care; parents; psychological; stress

A young child with bilateral diaphragmatic palsy after bilateral bidirectional Glenn shunt - Shamsuddin, A.K.; Biswas, S.K.; Rahman, M.Z.; Biswas, S.; Hasan, N.A.; Sharifuzzaman, M. (Mymensingh medical journal : MMJ, 2014)
A 13-months old boy was admitted in National Heart Foundation Hospital and Research Institute on 3 August 2011 with the diagnosis of Dextrocardia, A-V discordance, DORV, large perimembranous VSD, severe infundibular and valvular PS, bilateral SVC. He was operated on 10 August 2011. Bilateral bidirectional Glenn shunt was done off pump along with interruption of PDA. Antegrade pulmonary blood flow was minimized by tight PA banding. Baby was extubated 3 hours after surgery but had to reintubate immediately due to intense respiratory distress. Subsequent three trials of extubation failed. Chest x-ray revealed elevation of both the hemidiaphragm. Ultrasonogram of abdomen and Bronchogram along with fluoroscopy done and bilateral diaphragmatic palsy was diagnosed. Tracheostomy was done on 25th August 2011. Plication of left hemidiaphragm was done on 27th August and right hemidiaphragm plication was done on 10th September 2011. Though it took long period of time we managed to take him out of ventilator on 57th postoperative day. He was oxygen dependent for a period of time and finally he managed to take his own breath without tracheostomy tube from 67th postoperative day. After a long eventful postoperative hospital stay he was discharged home on 78th postoperative day. Discharge Chest x-ray revealed well expanded lung with flattened diaphragm. Echo revealed well functioning bilateral Glenn shunt. Tracheostomy wound healed nicely and there was no evidence of tracheal stenosis.

Recurrent abortion in a patient with ebstein anomaly - Ranjbar, A.; Parizad, R.; Tabrizi, M.T. (International Journal of Women's Health and Reproduction Sciences, 2014)
Most maternal cardiac disease in Western societies is now congenital in origin. This relates to the significant improvements in congenital cardiac surgery during the last years. Some patients will present for the first time in pregnancy with symptoms and learn that they have congenital heart disease. So all patients should have a detailed evaluation and appropriate counseling before pregnancy. Ebstein anomaly is a rare and complex congenital heart disorder occurring in 1 per 200 000 live births and, first described by a German physician Wilhelm Ebstein in 1866 in a report titled, “Concerning a very rare case of insufficiency of the tricuspid valve caused by a congenital malformation. This anomaly accounts for 0.5%-0.7% of cases of congenital heart disease. The average life duration of patients with Ebstein’s anomaly is 25-30 years. The malformation consists of apical displacement of the tricuspid valve with resultant regurgitation and enlargement of the right heart chambers, resulting in arrhythmias and heart failure. The common cardiac anomalies associated with the condition are atrial septal defect (ASD) in 90% of patients, anatomic or functional tricuspid atresia in 30%, Wolff-Parkinson-White (WPW) syndrome in 15% and less commonly ventricular septal defect (VSD), pulmonic stenosis or atresia and mitral valve prolapse. Survival into adulthood is common and patients present with cyanosis, dyspnea and palpitations. © 2014 The Author(s).
Keywords: Box Shaped Heart; Ebstein Anomaly; Pregnancy; Recurrent Abortion

Diagnosis and treatment of fetal cardiac disease: A scientific statement from the american heart association - Donofrio, M.T.; Moon-Grady, A.J.; Hornberger, L.K.; Copel, J.A.; Sklansky, M.S.; Abuhamad, A.; Cuneo, B.F.; Huhta, J.C.; Jonas, R.A.; Krishnan, A.; Lacey, S.; Lee, W.; et al. (Circulation, 2014)
Background - The goal of this statement is to review available literature and to put forth a scientific statement on the current practice of fetal cardiac medicine, including the diagnosis and management of fetal cardiovascular disease. Methods and Results - A writing group appointed by the American Heart Association reviewed the available literature pertaining to topics relevant to fetal cardiac medicine, including the diagnosis of congenital heart disease and arrhythmias, assessment of cardiac function and the cardiovascular system, and available treatment options. The American College of Cardiology/ American Heart Association classification of recommendations and level of evidence for practice guidelines were applied to the current practice of fetal cardiac medicine. Recommendations relating to the specifics of fetal diagnosis, including the timing of referral for study, indications for referral, and experience suggested for performance and interpretation of studies, are presented. The components of a fetal echocardiogram are described in detail, including descriptions of the assessment of cardiac anatomy, cardiac function, and rhythm. Complementary modalities for fetal cardiac assessment are reviewed, including the use of advanced ultrasound techniques, fetal magnetic resonance imaging, and fetal magnetocardiography and electrocardiography for rhythm assessment. Models for parental counseling and a discussion of parental stress and depression assessments are reviewed. Available fetal therapies, including medical management for arrhythmias or heart failure and closed or open intervention for diseases affecting the cardiovascular system such as twin-twin transfusion syndrome, lung masses, and vascular tumors, are highlighted. Catheter-based intervention strategies to prevent the progression of disease in utero are also discussed. Recommendations for delivery planning strategies for fetuses with congenital heart disease including models based on classification of disease severity and delivery room treatment will be highlighted. Outcome assessment is reviewed to show the benefit of prenatal diagnosis and management as they affect outcome for babies with congenital heart disease. Conclusions - Fetal cardiac medicine has evolved considerably over the past 2 decades, predominantly in response to advances in imaging technology and innovations in therapies. The diagnosis of cardiac disease in the fetus is mostly made with ultrasound; however, new technologies, including 3- and 4-dimensional echocardiography, magnetic resonance imaging, and fetal electrocardiography and magnetocardiography, are available. Medical and interventional treatments for select diseases and strategies for delivery room care enable stabilization of high-risk fetuses and contribute to improved outcomes. This statement highlights what is currently known and recommended on the basis of evidence and experience in the rapidly advancing and highly specialized field of fetal cardiac care. © 2014 American Heart Association, Inc.
Keywords: AHA scientific statements; Cardiology pediatric; Congenital; Fetus; Heart defects congenital

Effects of exercise training on behavioral and emotional problems in adolescents with tetralogy of Fallot or a Fontan circulation: A randomized controlled trial - Dulfer, K.; Duppen, N.; Blom, N.A.; Van Domburg, R.T.; Helbing, W.A.; Verhulst, F.C.; Utens, E.M.W.J. (International Journal of Cardiology, 2014)
Keywords: Adolescents; Aerobic exercise; Behavioral problems; Congenital heart defects; Emotional problems

Management of plastic bronchitis with nebulized tissue plasminogen activator: Another brick in the wall - Colaneri, M.; Quarti, A.; Pozzi, M.; Gasparini, S.; Carloni, I.; De Benedictis, F.M. (Italian Journal of Pediatrics, 2014)
Plastic bronchitis is a rare complication of a variety of respiratory diseases and congenital heart disease surgery, particularly Fontan procedure. Bronchial casts with rubber-like consistency develop acutely and may cause severe life-threatening respiratory distress. The management of plastic bronchitis is yet not well defined. Early intermittent, self-administered nebulization of tissue plasminogen activator was found to be effective in preventing deterioration of acute respiratory symptoms in a patient with primary ciliary dyskinesia and recurrent cast formation. Further investigation into new therapeutic strategies for this devastating disease is advocated. © 2014 Colaneri et al.; licensee BioMed Central Ltd.
Keywords: Plastic bronchitis; Primary ciliary dyskinesia; Tissue plasminogen activator

Hospital-associated venous thromboembolism in children: Incidence and clinical characteristics - Takemoto, C.M.; Sohi, S.; Desai, K.; Bharaj, R.; Khanna, A.; McFarland, S.; Klaus, S.; Irshad, A.; Goldenberg, N.A.; Strouse, J.J.; Streiff, M.B. (Journal of Pediatrics, 2014)
Objective To determine incidence and clinical characteristics of hospital-associated venous thromboembolism (VTE) in pediatric patients. Study design A retrospective analysis of patients with hospital-associated VTE at the Johns Hopkins Hospital from 1994 to 2009 was performed. Clinical characteristics of patients aged 21 years and younger who developed VTE symptoms after 2 days of hospitalization or <90 days after hospital discharge were examined. International Classification of Diseases, Ninth Revision codes were used to categorize patients with complex chronic medical conditions and trauma. Results There were 270 episodes of hospital-associated VTE in 90â€̂485 admissions (rate 30 per 10â€̂000 admissions). Young adults (18-21 years) and adolescents (14-17 years) had significantly increased rates of VTE compared with children (2-9 years) (incidence rate ratio [IRR] 7.7, 95% CI 5.1-12.0; IRR 4.3, 95% CI 2.7-6.8, respectively). A central venous catheter (CVC) was present in 50% of patients, and a surgical procedure was performed in 45% of patients before VTE diagnosis. For patients without a CVC, trauma was the most common admitting diagnosis. CVC-related VTE was diagnosed most frequently in infants (<1 year old) and in patients with malignancy. Renal and cardiac diseases were associated with the highest rates of VTE (51 and 48 per 10 000, respectively). Rates were significantly higher among those with ≥4 medical conditions compared with those with 1 medical condition (IRR 4.0, 95% CI 1.4-8.9). Conclusion Older age and multiple medical conditions were associated with increased rates of hospital-associated VTE. These data can contribute to the design of future clinical trials to prevent hospital-associated VTE in high-risk children.
Keywords: CCC; Central venous catheter; Complex chronic condition; CVC; Deep venous thrombosis; DVT; HLHS; Hypoplastic left heart syndrome; ICD-9; Incidence rate ratio; International Classification of Diseases, Ninth Revision; IRR; PE; Pulmonary embolism; Venous thromboembolism; VTE

How not to tell parents about their child's new diagnosis of congenital heart disease: An internet survey of 841 parents - Hilton-Kamm, D.; Sklansky, M.; Chang, R.-K. (Pediatric Cardiology, 2014)
An online survey for parents of children with congenital heart disease (CHD) was developed to study the perceptions and experiences of parents when receiving the diagnosis. The survey was distributed to online support groups. A total of 841 responses from parents of children with CHD in the United States were received over a 4-week period in 2010. The authors hypothesized that the counseling and demeanor of the pediatric cardiologist (PC) may be important factors in determining whether parents of children with CHD seek second opinions, and that the terminology used in counseling may be variably interpreted. Of the 841 respondents, 349 (41 %) received the diagnosis prenatally. A minority of the respondents received: support group information (14 %), Internet resources (21 %), success rates at other hospitals (16 %), or maximum ages of survivors (29 %). Among 26 % of the parents who reported seeking a second opinion from another PC, the majority (71 %) chose the second PC for long-term follow-up care. Those receiving a prenatal diagnosis were more likely to seek a second opinion than those receiving the diagnosis postnatally (32 vs 22 %; p < 0.01). Parents' perception of the PC's compassion and empathy was inversely related to the likelihood of seeking a second opinion. Parents were more likely to seek a second opinion when they were not optimistic about their child's life expectancy, felt pressured by the PC to terminate the pregnancy, were told that their child's death was "somewhat" or "very" likely, or were told the child's CHD was "rare" (all p < 0.01). Two thirds (66 %) of the respondents were told that their child's condition was "rare." The majority of these (77 %) reported that the term was used by the PC. "Rare" was interpreted as "occurring in less than a million births" by 25 %, and as "few or no other people alive with this defect" by 27 %. Parental interpretation of "rare" was unrelated to their levels of education. As reported by the respondents, 13 % felt pressured to terminate the pregnancy by the PC. Those with hypoplastic left heart syndrome were more likely to report feeling pressure to terminate the pregnancy by the PC (21 vs 9 %; p < 0.001) or the perinatologist (23 vs 14 %; p = 0.026). The approach to counseling and the demeanor of the PC have important implications for parents' perceptions of their child's chance of survival. The information given at diagnosis, the manner in which it is presented, and the parents' understanding and interpretation of that information are critical factors in shaping parents' perceptions and management decisions. © 2013 Springer Science+Business Media New York.
Keywords: Congenital heart disease; Counseling; Hypoplastic left heart syndrome; Internet survey; Parent perceptions; Psychosocial needs; Support groups

The nuchal translucency examination leading to early diagnosis of structural fetal anomalies - Goldstein, I.; Weizman, B.; Nizar, K.; Weiner, Z. (Early Human Development, 2014)
Objective: To evaluate the ability to diagnose structural fetal anomalies during or soon after an extended nuchal translucency (NT) examination. Methods: The study population included all women who had a routine NT examination in the ultrasound division of one of three centers. Also included in the study were women referred to these centers following an abnormal NT examination. The sonographers were instructed to pay attention to fetal anomalies while performing the NT examination. Each examination was initially attempted transabdominally. Failure to obtain adequate views transabdominally was an indication for a transvaginal examination. When a structural fetal anomaly was detected or suspected, a full fetal anomaly scan was performed. When a diagnosis could not be established, fetal anatomy scan was repeated after 14. weeks of gestation. Fetal cardiac scanning was performed transvaginally, immediately or within 3. days after an increased NT was observed. When fetal anomalies were diagnosed the patients were informed about the possibilities of terminating the pregnancy or continuing the work-up and follow-up. Overall, ascertainment of fetal outcome was available in 85% of the study population. Results: We performed 4467 NT examinations during the study period and additional 123 fetal cardiac scanning following an abnormal NT examination. Overall, we performed 365 fetal cardiac scanning between 11 and 14. weeks of gestation. The fetal anomalies detected included the following: three skeletal anomalies, seven brain anomalies, four urinary system anomalies, four abdominal anomalies, two facial anomalies, and 13 cardiac anomalies. Six of the 13 cardiac anomalies were found in the atrioventricular canal. One third of the patients (11/33) elected to discontinue the pregnancy a short time after the detection of the congenital anomaly (until 14. weeks of gestation) and half of the patients (16\33) asked for termination of pregnancy later. More than 60% of the patients (20/33) with congenital anomalies detected following the NT examination refused to have chorionic villous sampling (CVS) or amniocentesis. Conclusion: The opportunity to scan the fetal anatomy in the early stages of pregnancy, when the NT examination is performed, justifies the approach of extended NT examination. © 2013 Elsevier Ireland Ltd.
Keywords: Nuchal translucency; Structural fetal anomalies

Aerobic exercise influences quality of life of children and youngsters with congenital heart disease: A randomized controlled trial - Dulfer, K.; Duppen, N.; Kuipers, I.M.; Schokking, M.; Van Domburg, R.T.; Verhulst, F.C.; Helbing, W.A.; Utens, E.M.W.J. (Journal of Adolescent Health, 2014)
Purpose To evaluate effects of an exercise program on health-related quality of life (HRQoL) in children and adolescents with tetralogy of Fallot (ToF) or a Fontan circulation. Methods Stratified, randomized, controlled intervention study conducted in five participating centers of pediatric cardiology in The Netherlands. In total, 93 patients, aged 10-25 years, with surgical repair for tetralogy of Fallot or with a Fontan circulation for single-ventricle physiology were included. They were randomly allocated with a ratio of 2:1 to: (1) a 12-week period with an exercise program for 3 times per week or (2) to a control group. Randomization was stratified by age, gender, and cardiac diagnosis. At baseline and follow-up after 12 weeks, all participants completed Web-based age-appropriate HRQoL questionnaires. Primary analyses involved change in HRQoL during follow-up. Secondary analyses concerned influence of cardiac diagnosis and comparison with normative data. Results Forty-eight (86%) and 32 (86%) patients in the exercise-group and control-group respectively completed all questionnaires at baseline and follow-up. Compared with the control-group, children, aged 10-15 years, in the exercise-group improved significantly on self-reported cognitive functioning, p <.05, r =.30, and parent-reported social functioning, p <.05, r =.30. Youngsters aged 16-25 years did not change their HRQoL. Cardiac diagnosis had no influence on pre/post changes. Children and youngsters in this study reported comparable or better HRQoL than norm groups. Conclusions Participation in an exercise program improved HRQoL of children with ToF or a Fontan circulation, especially in those with low baseline QoL. © 2014 Society for Adolescent Health and Medicine. All rights reserved.
Keywords: Adolescents; Aerobic exercise; Children; Congenital heart disease; Quality of life; Randomized controlled trial; Young adults

Aortic dissection in hospitalized children and young adults: A multiinstitutional study - Shamszad, P.; Barnes, J.N.; Morris, S.A. (Congenital Heart Disease, 2014)
Objective.: To describe the incidence, characteristics, and outcomes of hospitalized children and young adults with aortic dissection (AD). Design.: Retrospective review. Setting.: The Pediatric Health Information System database, a multiinstitutional administrative database. Patients.: All index cases of patients <30 years old hospitalized with AD between January 2004 and June 2011. Outcome Measures.: The primary outcome measure was inpatient mortality. Results.: Of 3800964 hospitalizations, AD was identified in 124 (<1%), accounting for 110 patients (69% male, P = .003) at a median age of 12.9 (interquartile range 3.9-16.8) years with a bimodal distribution in infancy and late adolescence. Associated diagnoses included congenital heart disease (CHD) (38%), trauma (24%), connective tissue disease (CTD) (16%), and isolated hypertension (HTN) (8%). Common CHD diagnoses included aortic arch (24%) and valve (21%) disease, hypoplastic left heart syndrome (10%), and transposition of the great arteries (10%). CHD patients were younger and more likely to undergo inpatient non-AD-related cardiovascular procedures compared with other diagnostic groups (P < .001 for both). Marfan and Ehlers-Danlos syndrome were present in 72% and 11% of CTD patients, respectively. Overall in-hospital mortality in patients with AD was 13% compared with 1% in the database population (odds ratio 12.0, 95% confidence interval 6.9-21.1). By diagnostic category, mortality was 22% in HTN, 22% in CTD, 12% in CHD, and 4% in trauma. Conclusions.: AD is rare in children and young adults but most commonly occurs in CHD and CTD and in males. AD is associated with high inpatient mortality. © 2013 Wiley Periodicals, Inc.
Keywords: Aortic Disease; Hospital Utilization; Mortality; Pediatrics; Risk Factors

Health-related quality of life outcomes in children and adolescents with congenital heart disease - Mellion, K.; Uzark, K.; Cassedy, A.; Drotar, D.; Wernovsky, G.; Newburger, J.W.; Mahony, L.; Mussatto, K.; Cohen, M.; Limbers, C.; Marino, B.S. (Journal of Pediatrics, 2014)
Objectives To compare health-related quality of life (HRQOL) in a group of pediatric patients with congenital heart disease (CHD) and healthy controls and patients with other chronic diseases, and to compare HRQOL among patients with CHD of various severity categories with one another, with controls, and with patients with other chronic diseases. Study design In this cross-sectional survey, t tests were used to compare patient and proxy-reported Pediatric Quality of Life Inventory 4.0 Generic Core Scales (PedsQL) scores (including total, physical health, and psychosocial health summary scores) in children (aged 8-12 years) and adolescents (aged 13-18 years) between controls and (1) a composite CHD population; and (2) patients in each of 3 CHD severity categories: mild (no intervention), biventricle (BV; postintervention), and single ventricle (SV; postpalliation). PedsQL scores among CHD severity categories were compared by ANOVA. PedsQL scores were also compared in the CHD population and children with other chronic diseases without age stratification using t tests. Results There were 1138 (children, n = 625; adolescents, n = 513) and 771 (children, n = 528; adolescents, n = 243) patient and/or proxy reporters in the CHD and healthy control groups, respectively. Total, physical health, and psychosocial health summary scores were lower in the composite CHD, BV, and SV groups compared with controls (P <.0001). There were significant differences among disease severity categories for all scores (P <.01). The composite CHD, BV, and SV groups had similar PedsQL scores as end-stage renal disease, asthma, and obesity populations. Conclusion Children and adolescents with BV and SV CHD have significantly lower HRQOL than healthy controls and similar HRQOL as patients with other chronic pediatric diseases. Interventions targeting both physical and psychosocial domains are needed to improve HRQOL in this high-risk population. © 2014 Mosby Inc. All rights reserved.

Paediatric pulmonary haemorrhage: Independent lung ventilation as effective strategy in management - Murkute, A.; Angadi, U.; Jain, P.; Sharique, T.; Hegde, R. (Indian Journal of Critical Care Medicine, 2014)
Pulmonary haemorrhage is an uncommon symptom in paediatrics with the etiology varying among the series by age, location, and the diagnostic tests employed. Once airway protection and volume resuscitation are ensured, localization of the anatomic site of bleeding, isolation of the involved airway, control of haemorrhage and treatment of the underlying cause of becomes essential. In localized persistent bleeding, airway control may be achieved by lung isolation with double lumen endotracheal tube and synchronous independent lung ventilation.
Keywords: Double lumen endotracheal tube; Independent lung ventilation; Pulmonary haemorrhage

Psychosocial risk in families of infants undergoing surgery for a serious congenital heart disease - Hearps, S.J.; McCarthy, M.C.; Muscara, F.; Hearps, S.J.C.; Burke, K.; Jones, B.; Anderson, V.A. (Cardiology in the Young, 2014)
Objective: The aim of this study was to explore the acute psychosocial risk in families with infants undergoing surgery for a congenital heart disease and, secondarily, to explore the psychosocial impact of antenatal versus post-natal diagnoses. Method: The study sample comprised 39 caregivers (28 mothers) of 29 children diagnosed with a congenital heart disease and requiring surgery within the first 4 weeks of life. Psychosocial risk was measured using the Psychosocial Assessment Tool, which was adapted to include four novel items examining infant risk factors, namely, sleeping, feeding, crying, and bonding difficulties. Parents' psychosocial risk was measured within 4 weeks after their child's surgery and stratified into a three-tiered framework: Universal, Targeted, and Clinical risk. Results: Of the total sample, 61.5% of parents were classified as Universal, that is, at lowest risk; 35.9% as Targeted, and 2.6% as Clinical. The within-family parent total Psychosocial Assessment Tool score correlations were non-significant, and there were no differences between families of infants who received post-natal versus antenatal diagnosis or single ventricle versus biventricular repair. Linear regression found that a higher parent education significantly predicted a lower total Psychosocial Assessment Tool score. Conclusions: Findings indicate that, although the majority of parents adapt to the acute stress of surgery for a serious cardiac illness in their infant, the remaining 38.5% report an increased psychosocial risk associated with higher rates of emotional distress, which may impact on the parental quality of life and capacity for optimal parenting. The distribution of psychosocial risk in parents of children undergoing surgery for a congenital heart disease is consistent with that described for parents of children with other serious paediatric diagnoses. © Cambridge University Press 2013.
Keywords: acute stress.; child; congenital heart disease; Psychosocial risk

Two-dimensional global longitudinal strain rate is a preload independent index of systemic right ventricular contractility in hypoplastic left heart syndrome patients after fontan operation - Schlangen, J.; Petko, C.; Hansen, J.H.; Michel, M.; Hart, C.; Uebing, A.; Fischer, G.; Becker, K.; Kramer, H.-H. (Circulation: Cardiovascular Imaging, 2014)
Background: Assessment of systemic right ventricular (RV) function in patients with hypoplastic left heart syndrome is important during long-term follow-up after Fontan repair. Traditional echocardiographic parameters to evaluate systolic ventricular function are affected by loading conditions. The only generally accepted load-independent parameter of systolic function, end systolic elastance (Ees), requires invasive catheterization. Therefore, we sought to determine if parameters obtained by 2-dimensional speckle tracking (2DST) were affected by acute changes in preload and correlated with catheterization-derived indices of RV contractility in hypoplastic left heart syndrome patients after Fontan palliation. Methods and Results: Fifty-two patients with hypoplastic left heart syndrome (median age, 6.6; range 2.9-22.2 years) were prospectively enrolled to have echocardiography and conductance catheter studies performed simultaneously. We compared traditional echo, 2-dimensional speckle tracking and catheterization-derived parameters during different states of preload at baseline and during dobutamine infusion. Global longitudinal strain (S) showed a tendency to decrease with preload reduction, whereas global longitudinal strain rate (SR) did not change (S: -17.7±3.4% versus -16.9±3.8%, P=0.08; SR: -1.30±0.29 versus -1.34±0.34 s-1, P=0.3). S did not change with dobutamine infusion (-17.7±3.4% versus -18.4±3.9%, P=0.24), whereas SR increased significantly (-1.30±0.29 versus -2.26±0.49 s-1, P<0.001). RV Ees correlated with SR (rs= -0.47, P<0.001), but not with S (rs=0.07, P=0.5) or other echocardiographic parameters. Conclusions: In contrast to S, SR was not affected by preload and correlated with Ees of the systemic RV. SR may be a useful noninvasive surrogate of RV contractility and suitable for follow-up of patients with hypoplastic left heart syndrome after Fontan palliation. © 2014 American Heart Association, Inc.
Keywords: Hypoplastic left heart syndrome; Ventricular function

Functional health status in children and adolescents after Fontan: Comparison of generic and disease-specific assessments - Mccrindle, B.W.; Zak, V.; Pemberton, V.L.; Lambert, L.M.; Vetter, V.L.; Lai, W.W.; Uzark, K.; Margossian, R.; Atz, A.M.; Cook, A.; Newburger, J.W. (Cardiology in the Young, 2014)
Purpose: The aim of this study was to compare associations between generic versus disease-specific functional health status assessments and patient and clinical characteristics for patients with severe congenital heart disease. Methods: This was a cross-sectional observational study involving 325 single ventricle patients, aged 10-18 years, after Fontan procedure. Enrolled patients underwent a medical history review, laboratory testing, and assessment of the functional health status by completion of the generic Child Report Child Health Questionnaire and the disease-specific Congenital Heart Adolescent and Teenage questionnaire. Correlated conceptually equivalent domains from both questionnaires were identified and their associations with patient and clinical variables were compared. Results: From the generic assessment, patients perceived marginally lower physical functioning (p = 0.05) but greater freedom from bodily pain compared with a normal population (p < 0.001). The equivalent physical functioning/limitations domain of the generic instrument, compared with the disease-specific instrument, had similar associations (higher multi-variable model R2) with medical history variables (R 2 = 0.14 versus R2 = 0.12, respectively) and stronger associations with exercise testing variables (R2 = 0.22 versus R 2 = 0.06). Similarly, the corresponding freedom from bodily pain/symptoms domains from both questionnaires showed a greater association for the generic instrument with medical history variables (R2 = 0.15 versus R2 = 0.09, respectively) and non-cardiac conditions (R 2 = 0.13 versus R2 = 0.06). The associations of each questionnaire with echocardiographic results, cardiac magnetic resonance imaging results, and serum brain natriuretic peptide levels were uniformly weak (R 2 range <0.01 to 0.04). Conclusions: Assessment of the physical functional health status using generic and disease-specific instruments yields few differences with regard to associations between conceptually similar domains and patient and clinical characteristics for adolescents after Fontan procedure. © Cambridge University Press 2013.
Keywords: cardiac defects; congenital; Fontan procedure; paediatrics

The relationship of patient medical and laboratory characteristics to changes in functional health status in children and adolescents after the Fontan procedure - McCrindle, B.W.; Zak, V.; Breitbart, R.E.; Mahony, L.; Shrader, P.; Lai, W.W.; Burns, K.M.; Colan, S.D.; Williams, R.V.; Goldberg, D.; Hill, K.D.; Khaikin, S.; et al. (Pediatric Cardiology, 2014)
Despite hypothesized concerns about deterioration beginning in adolescence, longitudinal data and associated factors regarding standardized assessment of physical functioning are not available for Fontan patients. Parents who participated in the Fontan Cross-Sectional Study completed the Child Health Questionnaire at 2 time points for 245 subjects ages 6-18 years. Associations between change in Physical Functioning Summary Score and baseline patient, medical, and laboratory characteristics (mean age 9.5 ± 1.7 years) and follow-up patient and medical characteristics (mean age 16.2 ± 1.6 years) were determined by regression analyses. During a mean of 6.7 ± 0.4 years, a small (not clinically important) but statistically significant decrease in score from 46.2 ± 11.7 to 44.5 ± 12.1 (p < 0.03) was noted. Subjects with higher baseline scores had a greater decrease in score (r = -0.48; p < 0.001). A multivariable model of patient and medical characteristics (R2 = 0.11) showed that a greater decrease in score was significantly associated with interim development of asthma (n = 13; parameter estimate [PE] -6.6; p < 0.05) or other chronic respiratory, lung, or breathing problems (n = 13; PE -12.5; p < 0.001) and the presence of protein-losing enteropathy at any time (n = 12; PE -9.4; p = 0.006). Change in score was not significantly associated with baseline laboratory measures of exercise capacity and ventricular characteristics and function. Therefore, although physical functioning may be stable during adolescence for many Fontan patients, deterioration occurs in some in association with respiratory conditions and protein-losing enteropathy. Further longitudinal study is necessary to better understand the relationship between clinical morbidities and functional health status as these patients transition into adulthood. © 2013 Springer Science+Business Media.
Keywords: Congenital; Fontan procedure; Functional health status; Heart defects; Pediatrics

Longitudinal assessment of growth in hypoplastic left heart syndrome: Results from the Single Ventricle Reconstruction Trial - Burch, P.T.; Gerstenberger, E.; Ravishankar, C.; Hehir, D.A.; Davies, R.R.; Colan, S.D.; Sleeper, L.A.; Newburger, J.W.; Clabby, M.L.; Williams, I.A.; Li, J.S.; Uzark, K.; et al. (Journal of the American Heart Association, 2014)
Background-We sought to characterize growth between birth and age 3 years in infants with hypoplastic left heart syndrome who underwent the Norwood procedure. Methods and Results-We performed a secondary analysis using the Single Ventricle Reconstruction Trial database after excluding patients < 37 weeks gestation (N=498). We determined length-for-age z score (LAZ) and weight-for-age z score (WAZ) at birth and age 3 years and change in WAZ over 4 clinically relevant time periods. We identified correlates of change in WAZ and LAZ using multivariable linear regression with bootstrapping. Mean WAZ and LAZ were below average relative to the general population at birth (P < 0.001, P=0.05, respectively) and age 3 years (P < 0.001 each). The largest decrease in WAZ occurred between birth and Norwood discharge; the greatest gain occurred between stage II and 14 months. At age 3 years, WAZ and LAZ were < -2 in 6% and 18%, respectively. Factors associated with change in WAZ differed among time periods. Shunt type was associated with change in WAZ only in the Norwood discharge to stage II period; subjects with a Blalock-Taussig shunt had a greater decline in WAZ than those with a right ventricle-pulmonary artery shunt (P=0.002). Conclusions-WAZ changed over time and the predictors of change in WAZ varied among time periods. By age 3 years, subjects remained small and three times as many children were short as were underweight (> 2 SD below normal). Failure to find consistent risk factors supports the strategy of tailoring nutritional therapies to patient- and stage-specific targets. © 2014 The Authors.
Keywords: Growth; Hypoplastic left heart syndrome; Pediatrics; Risk factors

Mechanical ventricular assist device as a bridge to recovery post-ABO-incompatible heart transplantation for failed Fontan circulation - Seitz, S.; Buchholz, H.; Rebeyka, I.; Ross, D.; West, L.; Urschel, S. (Transplant International, 2014)
A girl received an ABO-incompatible heart transplantation (ABOiHTx) at the age of 3.5 years for failed univentricular palliation with protein-losing enteropathy (PLE). She was born with a hypoplastic left heart syndrome and underwent multistage palliation to a Fontan circulation at 2 years of age. After the Fontan surgery, she developed PLE, necessitating a Fontan revision, followed by a Fontan takedown and eventually HTx, which was performed with a blood group B heart into an O recipient. Right ventricular (RV) failure secondary to increased pulmonary vascular resistance (PVR) evolved immediately after HTx. A temporary right ventricular assist device (RVAD) was implanted and later switched to a pneumatic pulsatile RVAD. With the adaption of PVR on the RVAD, the PLE resolved and the RVAD was explanted. In the following 12 months, she developed multiple relapses of PLE which eventually resolved after exchange of the calcineurin inhibitor. © 2014 Steunstichting ESOT.
Keywords: ABO incompatibility; allograft dysfunction; failed Fontan circulation; heart transplantation; mechanical circulatory support; protein-losing enteropathy

Bosentan improves exercise capacity in adolescents and adults after fontan operation: The TEMPO (treatment with endothelin receptor antagonist in fontan patients, a randomized, placebo-controlled, double-blind study measuring peak oxygen consumption) study - Hebert, A.; Mikkelsen, U.R.; Thilen, U.; Idorn, L.; Jensen, A.S.; Nagy, E.; Hanseus, K.; Sørensen, K.E.; Søndergaard, L. (Circulation, 2014)
Background-The Fontan procedure has improved survival in children with functionally univentricular hearts. With time, however, complications such as reduced exercise capacity are seen more frequently. Exercise intolerance is multifactorial, but pulmonary vascular resistance probably plays a crucial role. Elevated pulmonary vascular resistance has been associated with raised levels of endothelin-1, which are common both before and after Fontan operations. Treatment with endothelin-1 receptor antagonists could theoretically improve cardiopulmonary hemodynamics and exercise capacity. The aim of this study was therefore to examine the efficacy and safety of bosentan in Fontan patients. Methods and Results-Seventy-five adolescents and adults were randomized 1:1 to 14 weeks of treatment with bosentan or placebo. Cardiopulmonary exercise test, functional class, blood samples, and quality-of-life questionnaires were evaluated at baseline and at the end of treatment. Sixty-nine patients (92%) completed the study. Peak oxygen consumption increased 2.0 mL·kg-1·min-1 (from 28.7 to 30.7 mL·kg-1·min-1) in the bosentan group compared with 0.6 mL·kg-1·min-1 (from 28.4 to 29.0 mL·kg-1·min-1) in the placebo group (P=0.02). Cardiopulmonary exercise test time increased by 0.48 minute (from 6.79 to 7.27 minutes) versus 0.08 minute (from 6.94 to 7.02 minutes; P=0.04). Nine bosentan-treated patients improved 1 functional class, whereas none improved in the placebo group (P=0.0085). Side effects were mild and occurred equally in both groups. No serious adverse effects were seen, and no patients had liver enzyme levels above the 3-fold upper limit. Conclusions-Bosentan improves exercise capacity, exercise time, and functional class in Fontan patients without serious adverse events or hepatotoxicity. © 2014 American Heart Association, Inc.
Keywords: Bosentan; Congenital; Exercise test; Fontan procedure; Heart defects; Vasodilation

Health related quality of life after corrective surgery for congenital heart disease - Heusch, A.; Calaminus, G.; Kahl, J.; Schmidt, K. (Klinische Padiatrie, 2014)
After corrective surgery for congenital heart defects (CHD) many patients suffer from residual defects, some with reduced cardiorespiratory capacity and possible impairment of their health related quality of life (HRQoL). The aim of our study is to evaluate, how children after surgery for CHD rate their HRQoL. Method: A standardised questionnaire developed for self-rating in children between 8 and 18 years and dealing with 7 different domains concerning the HRQoL (friends, family, physical functioning, cognition, body image, emotional function and autonomy) was independently answered from patients and their parents during an outpatient visit at their pediatric cardiologist throughout Germany. Results: 173 patients (40% female, 60% male, mean age 11.6 years) were interviewed, 167 questionnaires could be evaluated. The mean time interval after surgery was 9.8±3.4 years. Patient had had surgery for complete different types of CHD (ventricular septal defects n=50, Tetralogy of Fallot n=51, univentricular heart n=26, transposition of great arteries n=40). The results were compared with those of an age-matched control group (n=169). Patients with CHD reported a better HRQoL than the controls for all items (p<0.01). There was no significant gender specific difference. After puberty, the rating for most items, except of body image, had become very similar compared to controls. Parents assessed their children significantly worse in 3 domains (friends, body image and emotion; p<0.01). Conclusion: Children with congenital heart defects are able to develop coping structures, that enable them to live a normal life from their individual point of view. Integration in psychosocial structures seems to be rather normal when compared to healthy controls. Many patients considered their HRQoL as even better. © Georg Thieme Verlag KG Stuttgart New York.
Keywords: children; congenital; health related quality; heart defect; parents

Late consequences of the fontan operation - Rychik, J.; Goldberg, D.J. (Circulation, 2014)

The International Society for Heart and Lung Transplantation Guidelines for the management of pediatric heart failure: Executive summary - Kirk, R.; Dipchand, A.I.; Rosenthal, D.N.; Addonizio, L.; Burch, M.; Chrisant, M.; Dubin, A.; Everitt, M.; Gajarski, R.; Mertens, L.; Miyamoto, S.; Morales, D.; et al. (Journal of Heart and Lung Transplantation, 2014)

Sonographic dynamic assessment of lung injury in a child with hypoplastic left heart syndrome undergoing extracorporeal membrane oxygenation - Biasucci, D.G.; Ricci, Z.; Conti, G.; Cogo, P. (Pediatric Pulmonology, 2014)
Introduction: Performed for many years in clinical settings, pleural and lung ultrasound (PLUS) has emerged to be an invaluable tool to diagnose underlying conditions of respiratory failure, to monitor disease progression and to ensure appropriate therapeutic intervention. PLUS basically relies on the analysis of two prevalent ultrasound artefacts: A-lines and B-lines. A-lines are hyperechoic reverberation artefacts of the pleural line. A-lines combined with lung sliding show that lungs are well aerated. B-lines are vertical hyperechoic reverberation artefacts arising from pleural line extending to the bottom of the screen. The prevalence of B-lines indicates a pathologic parenchyma. Since PLUS is readily available, easily affordable, and biologically non-invasive, it is especially suitable for bedside clinical care in critically ill and unstable adult patients. Several authors have recently proposed PLUS for application in critically ill neonates and children. We report a case in which PLUS was used to clinically monitor a complex lung lesion during treatment of a child with congenital heart disease suffering from severe lung injury. Case Description: A 1-year-old male with hypoplastic left heart syndrome underwent bidirectional Glenn procedure and systemic-to-left pulmonary artery shunt for heart palliation. After surgery, he developed a severe acute respiratory distress syndrome (ARDS) and extra-corporeal membrane oxygenation (ECMO) treatment was started. PLUS was performed daily to monitor the disease's progression and response to treatment during lung rest. As B-lines were decreasing and A-lines were becoming visible, we were able to monitor the improving aeration of the injured lung. The ultrasound showed high consistency with traditional imaging. Discussion: Due to its non-ionizing nature, low cost, easy availability, easy repeatability and real-time results, PLUS is a feasible and beneficial bedside imaging technique for critically ill and unstable adult and pediatric patients. A reliable monitoring of ongoing treatments is certainly helpful to provide appropriate intervention, correctly schedule chest X-ray and CT-scan, and optimize ECMO weaning. The present case suggests that PLUS may be a successful and useful tool for monitoring lung diseases in children with CHD with severe postoperative complex lung injury. © 2014 Wiley Periodicals, Inc.
Keywords: Congenital heart diseases; ECMO; Heart surgery; Lung ultrasound; Mechanical ventilation; Pediatric critical care; Respiratory failure

Early mother-infant relationships after cardiac surgery in infancy - Jordan, B.; Franich-Ray, C.; Albert, N.; Anderson, V.; Northam, E.; Cochrane, A.; Menahem, S. (Archives of Disease in Childhood, 2014)
Objective: The critical importance of a secure mother-infant attachment relationship for long-term physical and mental health of the child is well established. Our study aim was to explore mothers' subjective experience of the mother-infant relationship after discharge from hospital following neonatal cardiac surgery. Design: Participants were 97 infants who underwent cardiac surgery before the age of 3 months and their mothers. Mothers completed Maternal Postnatal Attachment Scale (MPAS) and Edinburgh Postnatal Depression Scale (EPDS) questionnaires and were interviewed after the infant had been discharged home for 4 weeks. Interviews were analysed using inductive thematic analysis. Results: Mean sores on the MPAS were similar to community norms (84.5 (SD 7.2) vs 84.6 (SD 7), p=0.47). 66/91 mothers interviewed described impacts which encompassed four themes; enhanced emotional ties (n=34, 37%), 'bonding' difficulties (n=22, 23%), anxiety and worry (n=17, 19%), and caregiving behaviours (n=10, 11%). Mothers who described bonding difficulties had lower MPAS scores (mean 80.6 (SD 10) vs 85.7 (SD 5.7), p=0.0047), were more likely to have a prenatal diagnosis of the cardiac abnormality (OR 2.6, 95% CI 0.89 to 8.9) and higher EPDS score (9.1 (SD 5.3) vs 6.2 (SD 3.9), p=0.01). Higher EPDS scores were associated with lower MPAS scores (r= -0.44, p=0.0001). Conclusions: Most mothers report a positive relationship with their infant following cardiac surgery but almost a quarter have difficulties forming a strong emotional tie. Clinical care (including prenatal) of the infant with congenital heart disease requiring surgery should include screening, assessment and appropriate referral for early intervention if mothers are struggling to form a bond with their infant.

Clinical experience of more than 2 months usage of extracorporeal membrane oxygenation (Endumo® 4000) without circuit exchange - Kusajima, K.; Hoashi, T.; Kagisaki, K.; Yoshida, K.; Nishigaki, T.; Hayashi, T.; Ichikawa, H. (Journal of Artificial Organs, 2014)
A 5-year-old girl with right atrial isomerism, complete atrioventricular septal defect, hypoplastic left ventricle, double outlet right ventricle, and mixed-type total anomalous pulmonary venous connection with totally occluded left pulmonary veins presented at our center for fenestrated total cavo-pulmonary connection with an extra cardiac conduit at the age of 3 years. Eleven months after the Fontan completion, she developed protein-losing enteropathy (PLE). Spontaneously closed fenestration was thought to be the cause of the PLE, and she underwent revision of fenestration at the age of 5 years. After the operation, PLE did not improve, and newly developed hypoxemia impaired her systemic ventricular function, leading to the initiation of veno-arterial extracorporeal membrane oxygenation (ECMO) with the Endumo® system 18 days after the operation to treat her hemodynamic instability. Although the ECMO circuit was changed three times during the first 8 days, the fourth circuit could be used for 74 days without hemolysis and serum leakage, until the patient unfortunately died 82 days after the operation due to multi-organ failure. © 2013 The Japanese Society for Artificial Organs.
Keywords: Endumo; Extracorporeal membrane oxygenation; Fontan; Pediatric

Computational fluid dynamics in fontan patients to evaluate power loss during simulated exercise - Bossers, S.S.M.; Cibis, M.; Gijsen, F.J.; Schokking, M.; Strengers, J.L.M.; Verhaart, R.F.; Moelker, A.; Wentzel, J.J.; Helbing, W.A. (Heart, 2014)
Objective Exercise intolerance is common in total cavopulmonary connection (TCPC) patients. It has been suggested that power loss (Ploss) inside the TCPC plays a role in reduced exercise performance. Our objective is to establish the role of Ploss inside the TCPC during increased flow, simulating exercise in a patient-specific way. Methods Cardiac MRI (CMR) was used to obtain flow rates from the caval veins during rest and increased flow, simulating exercise with dobutamine. A 3D reconstruction of the TCPC was created using CMR data. Computational fluid dynamics (CFD) simulations were performed to calculate Ploss inside the TCPC structure for rest and stress conditions. To reflect the flow distribution during exercise, a condition where inferior caval vein (IVC) flow was increased twofold compared with rest was added. 29 TCPC patients (15 intra-atrial lateral tunnel (ILT) and 14 extracardiac conduit (ECC)) were included. Results Mean Ploss at rest was 1.36±0.94 (ILT) and 3.20±1.26 (ECC) mW/m2( p<0.001), 2.84±1.95 (ILT) and 8.41±3.77 (ECC) mW/m2 (p<0.001) during dobutamine and 5.21±3.50 (ILT) and 15.28±8.30 (ECC) mW/m2 (p=0.001) with twofold IVC flow. The correlation between cardiac index and Ploss was exponential (ILT: R2=0.811, p<0.001; ECC: R2=0.690, p<0.001). Conclusions Ploss inside the TCPC structure is limited but increases with simulated exercise. This relates to the anatomy of TCPC and the surgical technique used. In all flow conditions, ILT patients have lower Ploss than ECC patients. We did not find a relationship between Ploss and exercise capacity.

Feeding dysfunction in single ventricle patients with feeding disorder - Hill, G.; Silverman, A.; Noel, R.; Bartz, P.J. (Congenital Heart Disease, 2014)
Purpose: To determine whether caregivers of children with single ventricle heart defects identified as having feeding disorder will report more frequent feeding dysfunction, or maladaptive mealtime behavior and/or interactions, when compared with reference populations. Methods: As part of routine evaluation, parents of children evaluated at the Feeding, Swallowing, and Nutrition Center at the Children's Hospital of Wisconsin completed previously validated questionnaires to assess feeding dysfunction and parental stress. Parental responses for single ventricle patients were compared with all other children evaluated with a feeding disorder. Results: Questionnaires were completed in eight patients with single ventricle heart defects. The mean age was 36 ± 23 months, with five females (63%). Mean weight-for-age z-score was -1.4 ± 0.9. Compared with noncardiac feeding clinic children, there was more reported child resistance to eating (83 ± 15% vs. 44 ± 2%; P = .05). Single ventricle parents were more likely to report distress (50 ± 18% vs. 21 ± 2%; P = .04) and a difficult child (63 ± 17% vs. 31 ± 2%; P = .05). There was also more defensive responding among parents of single ventricle children (63 ± 17% vs. 29 ± 2%; P = .04). Conclusion: Single ventricle patients evaluated for disordered feeding more frequently showed resistance to eating and parental distress than noncardiac feeding clinic patients. Parents of these children underestimated the degree of feeding difficulty by defensive responding and had more parental distress. These findings suggest that feeding dysfunction can contribute to longer-term feeding and growth problems in single ventricle patients with feeding disorder. © 2013 Wiley Periodicals, Inc.
Keywords: Feeding; Growth; Nutrition; Single Ventricle

Outcomes of straightforward extracardiac Fontan operation in advanced-age group - Prachasilchai, P.; Promphan, W.; Katanyuwong, P.; Layangool, T.; Sangtawesin, C.; Kirawittaya, T.; Mokarapong, P. (Journal of the Medical Association of Thailand, 2014)
Introduction: Fontan operation is a palliative procedure used in patients with univentricular heart (UVH). There have been numerous modifications to the technique. The appropriate strategy for treating patients with UVH in Thailand is still a major concern. Objective: To describe the outcomes of patients after straightforward Fontan operation at advanced-age and evaluate their post-surgical cardiac performance. Material and Method: A cross sectional study was performed in post-Fontan operation patients at Rajvithi Hospital between 2000 and 2009. Post-operative cardiac performance was analyzed using the echocardiogram and treadmill exercise stress test (EST). Results: Thirty-nine patients were enrolled in the present study. The mean age was 11.7 years and the mean age at operation was 7.4 years. The predominant systemic chamber was morphologic left ventricle. Straightforward Fontan operation was performed in 60% of cases. Mean of Fontan index, mean of McGoon ratio, and mean of Nakata index were 2.63, 2.32, and 414.15 sqmm/sqm, respectively. Mean of the PVR and PAP were 1.98 U/m2 and 11.05 mmHg. Eighteen percent of patients died in the early post-operative period. Most of the patients died from septicemia. The mean EF was 58.43 %. Systolic dysfunction in 17.9% of the cases was abnormal, whereas diastolic dysfunction was present in half of the cases. Thirty-nine percent had MPI abnormality. During EST, three cases developed arrhythmias and 3 cases had hypotension. Patients were categorized into 3 groups (Group 1: normal systolic and diastolic functions, Group 2: diastolic dysfunction, Group 3: impairment of both systole and diastole). Pre-operative cardiac catheterization parameters, surgical data and cardiac performance showed no statistical significance. However, there was a significant correlation between those with abnormal cardiac performance and arrhythmias or hypotension during EST (p = 0.003). Conclusion: The selection of suitable cases and good pre-operative evaluation could decrease the morbidity and mortality in patients undergoing the Fontan procedure. This study also found a correlation between abnormal cardiac performance and transient cardiac arrhythmia during exercise. The evaluation of cardiac performance and EST remains to be performed for following-up of patients who have undergone the Fontan operation, even for the asymptomatic cases. © 2014, Medical Association of Thailand. All rights reserved.
Keywords: Fontan operation; Outcome; Post

Impact of chylothorax on the early post operative outcome after pediatric cardiovascular surgery - Ismail, S.R.; Kabbani, M.S.; Najm, H.K.; Shaath, G.A.; Jijeh, A.M.Z.; Hijazi, O.M. (Journal of the Saudi Heart Association, 2014)
Background and aim: Chylothorax is the accumulation of chyle in the pleural cavity, which usually develops after disruption of the thoracic duct along its intra-thoracic route. In the majority of cases, this rupture is secondary to trauma (including cardio thoracic surgeries). Chylothorax is a potentially serious complication after cardiovascular surgeries that require early diagnosis and adequate management. This study aims to determine the risk factors and the impact of chylothorax on the early postoperative course after pediatric cardiac surgery. Methods: A retrospective study of all cases complicated with chylothorax after pediatric cardiac surgery was conducted at King Abdulaziz Cardiac Center between January 2007 and December 2009. Results: There were 1135 cases operated on during the study period. Of these, 57 cases (5%) were complicated by chylothorax in the postoperative period. Thirty patients (54%) were males, while 27 (47%) were females. Ages ranged from 4 to 2759. days. The most common surgeries complicated by chylothorax were the single ventricle repair surgeries (15 cases, 27%); arch repairs (10 cases, 18%); ventricular septal defect repairs (10 cases, 18%); atrioventricular septal defect repairs (7 cases, 12%); arterial switch repair (6 cases, 11%), and others (8 cases, 14%). The intensive care unit (ICU) and the length of hospital stays were significantly longer in the chylothorax group. Additionally, some early postoperative parameters such as incidence of sepsis, ventilation time, and inotropes duration and number were higher in the chylothorax group. Conclusion: Chylothorax after pediatric cardiac surgery is not a rare complication. It occurs more commonly with single ventricle repair and aortic arch repair surgeries, and has a significant impact on the postoperative course and post operative morbidity. © 2014 King Saud University.
Keywords: Cardiac surgery; Chylothorax; Pediatric; Post operative

Dynamic pulmonary computed tomography angiography: A new standard for evaluation of combined airway and vascular abnormalities in infants - Greenberg, S.B.; Dyamenahalli, U. (International Journal of Cardiovascular Imaging, 2014)
Airway abnormalities are frequently associated with congenital heart disease in infants and children. Respiratory distress in these children frequently requires prolonged respiratory support. Wide-detector dynamic pulmonary computed tomography angiography (DP-CTA) is a non-invasive technique that completely evaluates vascular and airway abnormalities during a single breathe. Our purpose was to evaluate the efficacy of DP-CTA to provide unique actionable information for patient care in newborns and infants with congenital heart disease and persistent respiratory distress. 23 infants with congenital heart disease and persistent respiratory distress underwent DP-CTA. All were intubated at the time of the examinations. The most common cardiac anomalies were tetralogy of Fallot (6) and hypoplastic left heart syndrome variants (5). The most common cardiac surgeries prior to DP-CTA were Norwood (4) and hybrid (3) procedures. The protocol for DP-CTA for intubated infants is four gantry rotations in 1.4 s after intravenous contrast injection. 3D and multiplanar reconstruction with cine loops were created for combined cardiopulmonary imaging. Tracheobronchomalacia was present in 17 children. Lobar bronchomalacia was identified in six children. Branch pulmonary artery stenosis was the most common vascular finding (10 children). Medical management was changed or a surgical procedure performed based on the information resulting from DP-CTA in 16 of the 23 patients (70%). DP-CTA is non-invasive, fast and provides unique information for the management of infants with congenital heart disease and persistent respiratory distress. DP-CTA is uniquely suited for comprehensive and simultaneous evaluation of airway and vascular abnormalities in infants. © Springer Science+Business Media 2013.
Keywords: Bronchomalacia; Computed tomography; Congenital heart disease; Respiratory distress; Tracheomalacia

Successful noninvasive mechanical ventilation in a child on prolonged and life-threatening invasive mechanical ventilation after Fontan operation - Yaman, A.; Kendirli, T.; Ödek, C.; Karadeniz, C.; Uçar, T.; Göllü, G.; Eyileten, Z.; Ince, E. (Turkish Journal of Pediatrics, 2014)
For many decades, the primary treatment of acute respiratory failure has been mechanical ventilation. Intubation and mechanical ventilation carry complications such as upper respiratory system trauma, barotrauma, volutrauma, oxytrauma, atelectrauma, and nosocomial infection, and they increase mortality. Noninvasive mechanical ventilation (NIMV) applied to a specially selected group of patients has more advantages than invasive ventilation, especially the decreased number of complications. We present a three-year-old girl who had prolonged invasive mechanical ventilation (IMV) and weaning failure due to severe tracheal bleeding after Fontan operation. She could not be extubated for 20 days after admission to our Pediatric Intensive Care Unit (PICU) because of life-threatening airway bleedings from within the endotracheal tube. Owing to the severe bleedings during endotracheal aspirations, it was decided to change her mechanical ventilation to NIMV. NIMV was performed successfully for 12 days without difficulty, and she was discharged from the hospital on the 55th postoperative day with normal clinical findings. Noninvasive ventilation has an increasing use in critically ill children. NIMV should be considered in prolonged mechanical ventilation and weaning failure from IMV in critically ill children.
Keywords: Children; Fontan operation; Noninvasive mechanical ventilation; Prolonged invasive mechanical ventilation

The modified Fontan procedure with use of extracardiac conduit in adults: Analysis of 32 consecutive patients - Ly, M.; Roubertie, F.; Kasdi, R.; Chatti, S.; Vergnat, M.; Luu, D.; Le Bret, E.; Roussin, R.; Capderou, A.; Belli, E. (Annals of Thoracic Surgery, 2014)
Background Uncommonly, adults with functionally univentricular hearts are becoming candidates for a Fontan procedure. The purpose of this study was to evaluate the course of patients undergoing the modified Fontan procedure with an extracardiac conduit in recent years. Methods Between January 2003 and December 2013, 32 adult patients (17 female and 15 male) underwent total cavopulmonary connection (TCPC) with extracardiac conduit. The median age at procedure was 24.5 years (interquartile range [IQR] 20 to 33 years). The diagnoses included double-inlet left ventricle (DILV) in 10 patients (31.2%), tricuspid atresia in 8 patients (25%), double-outlet right ventricle in 4 patients (12.5%), heterotaxia in 4 patients (12.5%), and mitral atresia in 2 patients (6.2%). Seventy-eight percent of patients had undergone at least one prior palliative procedure; the most common procedures were Blalock-Taussig shunt (16 patients), superior cavopulmonary shunt (12 patients), and pulmonary artery banding (6 patients). All patients underwent cardiac catheterization preoperatively. Aortic cross-clamping was necessary in 15 patients for intracardiac procedures. Fenestration was required in 9 patients (28%). Four concomitant intraoperative cryoablation procedures were performed. Results There was no hospital mortality. One patient (3.1%) died 6 months after undergoing TCPC. Morbidities included prolonged pleural effusion lasting more than 7 days in 20 patients (62.5%), atrial arrhythmias in 4 patients (12.5%), and permanent pacemakers in 3 patients (9.3%). The median follow-up time was 33 months (interquartile range [IQR], 10.5 to 50 months). Actuarial survival was 91.83% (95% confidence limits, 71.07 to 97.89) at 1 year and 5 years. Ninety-two percent of patients were in New York Heart Association class I or II at follow-up. The median postoperative oxygen saturation was 95% (IQR, 93% to 95.5%). Cardiac arrhythmia occurred in 4 patients. Systolic ventricular function improved during follow-up for all patients except 1 patient, who underwent cardiac transplantation 7 months after the TCPC. Conclusions The modified Fontan procedure with use of an extracardiac conduit can be performed in adults with encouraging early and midterm results. The majority of late survivors had improved quality of life. The incidence of late death, reoperation, arrhythmias, and thromboembolic events was low during follow-up. © 2014 The Society of Thoracic Surgeons.

Factors associated with neurodevelopment for children with single ventricle lesions - Goldberg, C.S.; Lu, M.; Sleeper, L.A.; Mahle, W.T.; Gaynor, J.W.; Williams, I.A.; Mussatto, K.A.; Ohye, R.G.; Graham, E.M.; Frank, D.U.; Jacobs, J.P.; Krawczeski, C.; et al. (Journal of Pediatrics, 2014)
Objective To measure neurodevelopment at 3 years of age in children with single right-ventricle anomalies and to assess its relationship to Norwood shunt type, neurodevelopment at 14 months of age, and patient and medical factors. Study design All subjects in the Single Ventricle Reconstruction Trial who were alive without cardiac transplant were eligible for inclusion. The Ages and Stages Questionnaire (ASQ, n = 203) and other measures of behavior and quality of life were completed at age 3 years. Medical history, including measures of growth, feeding, and complications, was assessed through annual review of the records and phone interviews. The Bayley Scales of Infant Development, Second Edition (BSID-II) scores from age 14 months were also evaluated as predictors. Results Scores on each ASQ domain were significantly lower than normal (P <.001). ASQ domain scores at 3 years of age varied nonlinearly with 14-month BSID-II. More complications, abnormal growth, and evidence of feeding, vision, or hearing problems were independently associated with lower ASQ scores, although models explained <30% of variation. Type of shunt was not associated with any ASQ domain score or with behavior or quality-of-life measures. Conclusion Children with single right-ventricle anomalies have impaired neurodevelopment at 3 years of age. Lower ASQ scores are associated with medical morbidity, and lower BSID-II scores but not with shunt type. Because only a modest percentage of variation in 3-year neurodevelopmental outcome could be predicted from early measures, however, all children with single right-ventricle anomalies should be followed longitudinally to improve recognition of delays. Copyright © 2014 Elsevier Inc. All rights reserved.

Use of high-frequency oscillatory ventilation in patients with acute respiratory distress syndrome and cavopulmonary connections: A case report - Sanchez-de-Toledo, J.; Vega, L.; Gil, L.; Balcells, J.; Abella, F.; Gran, F. (Experimental and Clinical Cardiology, 2014)
Mechanical ventilation hampers passive venous flow to the lungs in patients with cavopulmonary connections. When feasible, early extubation may be beneficial in this patient population. In cases of required ventilatory support, understanding of cardiopulmonary interactions is paramount for the election of appropriate ventilatory strategies. Results on the use of high-frequency oscillatory ventilation in these patients remain controversial. We present the case of a child with single ventricle physiology palliated with a cavopulmonary connection who developed acute respiratory distress syndrome in whom the use of high-frequency oscillatory ventilation improved the respiratory and hemodynamic status. The reduced peak inspiratory pressures achieved with high frequency ventilation versus similar parameters of conventional mechanical ventilation may better maintain hemodynamics in patients with parenchymal lung disease and cavopulmonary connections.
Keywords: Acute respiratory distress syndrome; Cavopulmonary anastomosis; Congenital heart disease; Ventilation

Histologic changes in the adrenal gland reflect fetal distress in hydrops fetalis - Taweevisit, M.; Atikankul, T.; Thorner, P.S. (Pediatric and Developmental Pathology, 2014)
The distribution of lipid in the fetal adrenal cortex is reported to correlate with the duration of hypoxia and degree of fetal stress. The original studies were based on Oil Red O staining, requiring frozen tissue that is often not available. To investigate the reliability of these observations, the distribution of lipid in the fetal adrenal cortex was studied in hydrops fetalis (HF) of different etiologies, using immunostaining for adipophilin on formalin-fixed material. Twenty cases of HF due to hemoglobin (Hb) Bart were compared to 34 cases of HF due to other causes. In the fetal zone, lipid distribution was more diffuse in Hb Bart HF compared to other causes of HF, including those due to anemia, supporting the concept that increased lipid in the fetal zone is associated with severity of hypoxia. A more diffuse distribution of lipid correlated with adrenal cytomegaly (P < 0.01) and extramedullary hematopoiesis (P < 0.01) but not Hb level (P = 0.68) nor compact cell change (P = 0.7) or cystic degeneration (P = 0.07) in the definitive zone. A greater degree of cystic degeneration correlated with lower gestational age, rather than the specific etiology of HF. Thus, cystic degeneration is more a reflection of the onset of fetal stress than severity. The combined histologic changes in the fetal and definitive zones of the adrenal gland provide complementary information about fetal status in HF. Immnunostaining for adipophilin circumvents the need for frozen tissue for assessing lipid content by Oil Red O staining, facilitating studies based on archival material. © 2014 Society for Pediatric Pathology.
Keywords: Adipophilin immunohistochemistry; Adrenal gland; Definitive zone; Fetal zone; Hemoglobin Bart; Hydrops fetalis

Endoscopic removal of subgaleal hematoma in a 7-year-old patient treated with anticoagulant and antiplatelet agents - Hayashi, Y.; Kita, D.; Furuta, T.; Oishi, M.; Hamada, J.-I. (Surgical Neurology International, 2014)
Background: Subgaleal hematomas frequently occur in children after head trauma and extend over the cranial sutures. Although conservative treatment suffices in most cases, surgical removal of a subgaleal hematoma is indicated when the patient presents with anemia and headache associated with its progressive enlargement. Copyright: Case Description: We present the case of a 7-year-old boy who was medicated with warfarin and aspirin due to a hypoplastic left ventricle and fell from a rock wherein he hit his head in the frontal region. Although a computed tomography scan of the head revealed no intracranial lesion, an extracranial hematoma was found to extend over the cranial sutures, leading to the diagnosis of subgaleal hematoma. The hematoma continued to grow gradually despite the cessation of warfarin and aspirin therapy immediately after the head trauma. Since the patient's headache and anemia were progressing as the hematoma enlarged, removal of the hematoma was performed 3 days after admission. Endoscopic hematoma removal was planned to enable accurate coagulation of the sites of bleeding and removal of the maximal amount of hematoma through minimal incision. The hematoma was completely removed, and the patient's postoperative course was excellent with alleviation of both the anemia and the headache. No sign of hematoma recurrence could be detected during 2 years follow-up. Conclusion: An angled endoscope can allow visualization of the deep subgaleal space, and this technique enabled direct visualization of the bleeding sites and accurate coagulation to prevent recurrence of hematoma. Endoscopic techniques, such as minimally invasive techniques, can allow sufficient removal of subgaleal hematoma with minimal morbidity, especially in patients such as ours. © 2014 Hayashi Y.
Keywords: Anticoagulant agent; Endoscope; Removal; Subgaleal hematoma

Aldosterone-cortisol imbalance immediately after Fontan operation with implications for abnormal fluid homeostasis - Saiki, H.; Kuwata, S.; Kurishima, C.; Iwamoto, Y.; Ishido, H.; Masutani, S.; Senzaki, H. (American Journal of Cardiology, 2014)
Abnormal water metabolism is frequently observed after Fontan surgery. We hypothesized that patients' adrenal hormones show unique responses immediately after Fontan operation and that such a hormonal profile is related to postoperative hemodynamics and water imbalance. Twenty-eight patients who underwent a Fontan operation (n = 16) or a non-Fontan type operation (n = 12; controls) under cardiopulmonary bypass were studied. Postoperative urine cortisol and aldosterone levels were measured daily to minimize the influence of circadian rhythms and temporal hemodynamic variations. Cortisol excretion was markedly elevated on postoperative day (POD) 0 in controls, consistent with a stress-induced cortisol response. Cortisol excretion was not high on POD 0 in Fontan patients and was markedly lower than that in the controls (444 ± 150 vs 34 ± 6 μg/m2/day, p <0.05), indicating an adrenal insufficiency status. Conversely, aldosterone levels were significantly higher in Fontan patients than in controls immediately after surgery and remained so thereafter. The cortisol-to-aldosterone ratio was significantly lower in Fontan patients on POD 0 (p <0.05 vs controls); low cortisol-to-aldosterone ratios were associated with a longer pleural drainage duration and intensive care unit stay. Daily cortisol and aldosterone levels were significantly associated with postoperative hemodynamics; low cortisol levels correlated with low cardiac and urine outputs, whereas high aldosterone levels correlated with low cardiac output and increased blood pressure and central venous pressure. Thus, aldosterone-to-cortisol imbalance occurred specifically after the Fontan operation. This unique hormonal profile significantly affected patients' postoperative water balance and hemodynamics. Modulation of the adrenal hormone could be useful for reducing postoperative complications after the Fontan operation. © 2014 Elsevier Inc. All rights reserved.

Novel curved balloon catheter for dilating postoperative angled lesions associated with congenital heart disease - Kise, H.; Miyata, A.; Tomita, H.; Fujii, T.; Fujimoto, K.; Kiguchi, H.; Oyama, N.; Soga, T.; Hata, Y.; Hirata, M.; Itoh, A.; Ishino, K.; et al. (Journal of Interventional Cardiology, 2014)
Objectives This study aimed to analyze the surface stress generated by a novel curved balloon and assess its efficacy for treating angular lesions associated with congenital heart disease. Background Obstructions at the anastomosis of aortopulmonary shunts and cavopulmonary connections may occur postoperatively. Catheter interventions are often performed for such lesions; however, acute angulation may cause balloon slippage or inappropriate stress on the vessel wall. Methods We dilated the curved balloon in a curved vessel model and measured the resultant wall stress and its distribution. Clinical evaluations were performed using this balloon in angled lesions. Results In the curved vessel model, curved balloons generated uniform stress on the lesser and greater curvatures (curved type, lesser/greater=0.343MPa/0.327MPa; P=0.61), whereas straight balloons caused disproportionate stress (straight type, lesser/greater=0.358MPa/0.254MPa; P=0.19). However, the difference in average stress was not statistically significant. Furthermore, the stress was uniform along the entire length of the curved balloon, but differed between the mid and end portions of the straight balloon. Curved balloon dilations were performed for 10 lesions in 7 patients. The curved balloon conformed well to the angulated lesion without slipping. The median percent change in the minimal lumen diameter (MLD) was 64% (range, 0-206%). In 5 lesions, MLD increased by ≥50%. Oxygen saturation increased by 5% (0-9%). Conclusions Although further clinical evaluation is necessary, this novel curved balloon may be a reasonable alternative in angled lesions, providing better conformability and preventing excessive stress to the vessel wall adjacent to the stenosis. (J Interven Cardiol 2014;27:408-413) © 2014, Wiley Periodicals, Inc.

One and a half ventricle repair in association with tricuspid valve repair according to "peacock tail" technique in patients with ebstein's malformation and failing right ventricle - Prifti, E.; Baboci, A.; Esposito, G.; Kajo, E.; Dado, E.; Vanini, V. (Journal of Cardiac Surgery, 2014)
Objectives The aim of this study was to evaluate the outcome in a series of patients with Ebstein's anomaly and a failing right ventricle (RV) undergoing tricuspid valve (TV) repair and bidirectional Glenn cavopulmonary anastomosis (BDG). Materials and Method Between January 2006 and September 2013, 11 consecutive patients diagnosed with severe forms of Ebstein's anomaly and a failing RV underwent TV surgery and BDG. The mean age was 16.5 ± 7 years. Most frequently found symptoms were cyanosis, dyspnea, and arrhythmias. The azygos or hemiazygos veins were left open. The TV was repaired using the "peacock tail" technique, which consisted of total detachment of the anterior and posterior leaflets of the TV and rotation in both directions reimplanting them to the true annulus. The mean follow-up was 3.8 ± 2.4 years (range three months to six years). Results Hospital mortality was 9% (one patient). TV repair was possible in 10 patients. None of the patients had AV block postoperatively. At one year after surgery, the indexed RV and RA diameter were reduced significantly versus the preoperative data (p = 0.003 and p < 0.001). The mean TVR and indexed TV area were 1.2 ± 0.42 and 1.6 ± 0.6 (mm/m2), significantly lower than preoperatively (p = 0.001 and p = 0.008, respectively). The mean NYHA functional class, SaO2, and cardiothoracic ratio were significantly improved. Conclusions The peacock tail technique for TV repair in combination with BDG in patients with Ebstein's malformation and depressed RV function results in TV preservation, a low incidence of recurrent regurgitation, favorable functional status and RV function, and resolution of cyanosis. © 2013 Wiley Periodicals, Inc.

Validation of association of the apolipoprotein e ε2 allele with neurodevelopmental dysfunction after cardiac surgery in neonates and infants - Gaynor, J.W.; Kim, D.S.; Arrington, C.B.; Atz, A.M.; Bellinger, D.C.; Burt, A.A.; Ghanayem, N.S.; Jacobs, J.P.; Lee, T.M.; Lewis, A.B.; Mahle, W.T.; Marino, B.S.; et al. (Journal of Thoracic and Cardiovascular Surgery, 2014)
Objective Apolipoprotein E (APOE) genotype is a determinant of neurologic recovery after brain ischemia and traumatic brain injury. The APOE ε2 allele has been associated with worse neurodevelopmental (ND) outcome after repair of congenital heart defects (CHD) in infancy. Replication of this finding in an independent cohort is essential to validate the observed genotype-phenotype association. © 2014 The American Association for Thoracic Surgery Methods The association of APOE genotype with ND outcomes was assessed in a combined cohort of patients with single-ventricle CHD enrolled in the Single Ventricle Reconstruction and Infant Single Ventricle trials. ND outcome was assessed at 14 months using the Psychomotor Development Index (PDI) and Mental Development Index (MDI) of the Bayley Scales of Infant Development-II. Stepwise multivariable regression was performed to develop predictive models for PDI and MDI scores. Results Complete data were available for 298 of 435 patients. After adjustment for preoperative and postoperative covariates, the APOE ε2 allele was associated with a lower PDI score (P =.038). Patients with the ε2 allele had a PDI score approximately 6 points lower than those without the risk allele, explaining 1.04% of overall PDI variance, because the ε2 allele was present in only 11% of the patients. There was a marginal effect of the ε2 allele on MDI scores (P =.058). Conclusions These data validate the association of the APOE ε2 allele with adverse early ND outcomes after cardiac surgery in infants, independent of patient and operative factors. Genetic variants that decrease neuroresilience and impair neuronal repair after brain injury are important risk factors for ND dysfunction after surgery for CHD.

Use of computational fluid dynamics to estimate hemodynamic effects of respiration on hypoplastic left heart syndrome surgery: Total cavopulmonary connection treatments - Liu, J.; Qian, Y.; Sun, Q.; Liu, J.; Umezu, M. (The Scientific World Journal, 2013)
Total cavopulmonary connection (TCPC), a typical kind of Fontan procedure, is commonly used in the treatment of a functional single ventricle. The palliative cardiothoracic procedure is performed by connecting the superior vena cava and the inferior vena cava to the pulmonary arteries. Due to the difficulty of direct study in vivo, in this paper, computational fluid dynamics (CFD) was introduced to estimate the outcomes of patient-specific TCPC configuration. We mainly focused on the influence of blood pulsation and respiration. Fast Fourier transforms method was employed to separate the measured flow conditions into the rate of breath and heart beat. Blood flow performance around the TCPC connection was investigated by analyzing the results of time-varying energy losses, blood flow distribution rate, local pressure, and wall shear stress distributions. It was found that the value of energy loss including the influence of respiration was 1.5 times higher than the value of energy loss disregarding respiratory influences. The results indicated that the hemodynamic outcomes of TCPC treatment are obviously influenced by respiration. The influence of respiration plays an important role in estimating the results of TCPC treatment and thus should be included as one of the important conditions of computational haemodynamic analysis. © 2013 Jinlong Liu et al.

Biventricular repair after stage II univentricular surgery: Palliation is not a one-way path - Qureshi, M.Y.; Burkhart, H.M.; Hagler, D.J. (Annals of Thoracic Surgery, 2013)
Surgical decision in mild forms of hypoplastic left heart syndrome can be challenging. Once a univentricular pathway has been chosen, it can be difficult to reconsider a biventricular repair. A commitment to a palliative pathway is usually considered irreversible after initial univentricular repair. We present this case as an example in which the primary surgical palliation pathway was altered, and eventually a successful biventricular repair was performed in a mild variant of hypoplastic left heart syndrome, despite the fact that maneuvers to promote left ventricular growth were not recruited at the time of initial surgery. © 2013 by The Society of Thoracic Published by Elsevier Inc.

Twin pregnancy in a patient after the fontan operation: Report of a case - Nir, A.; Elchalal, U.; Hammerman, C.; Rein, A.J. (Congenital Heart Disease, 2013)
Singleton pregnancy in patients with single ventricle after the Fontan operation has been reported with significant offspring and maternal complications. We report a twin pregnancy and premature delivery, in a patient following the Fontan operation. © 2013 Wiley Periodicals, Inc.
Keywords: Cesarean Section; Fontan; Pregnancy; Prematurity; Single Ventricle; Twins

Higher-hazard, no benefit research involving children: Parental perspectives - Sachdeva, T.; Morris, M.C. (Pediatrics, 2013)
OBJECTIVES: US regulations allow local institutional review boards to approve greater than minimal risk, no-benefit research when the research enrolls children with the condition under study but not when it enrolls healthy children. We aim to describe the opinions of parents regarding higher-hazard, no-benefit research METHODS: Quantitative and qualitative interviews with parents of children without heart disease or chronic medical conditions (no heart disease [noHD], n = 30), children with fully correctable heart disease (FCHD, n = 30), and children with life-altering heart disease (LAHD, n = 30). RESULTS: Parents of children with heart disease endorse higherhazard, no-benefit heart disease research more strongly than noHD parents. Eight of 30 noHD parents, 19 of 30 FCHD parents, and 26 of 30 LAHD parents reported willingness to enroll their children in a heart disease research study involving an otherwise unnecessary chest radiograph (P , .01). There was no difference among groups in willingness to enroll their children in a similar study focused on childhood cancer. Twenty-two of 30 FCHD and 30 of 30 LAHD parents reported that parents have a responsibility to enroll their children in medical research to help future children with heart disease. Twentyone of 30 noHD parents, 29 of 30 FCHD parents, and 30 of 30 LAHD parents feel able to evaluate the risks of medical research (P = .01). CONCLUSIONS: Parental opinions regarding higher-hazard, no-benefit research align with federal regulations. Parental willingness to enroll their children in higher-hazard, no-benefit research is driven in part by a sense of obligation to a community of families affected by childhood heart disease. Pediatrics 2013;132:e1302-e1309. Copyright © 2013 by the American Academy of Pediatrics.
Keywords: Best-interest standard; Research ethics higher-hazard no-benefit research

Quality of life and cognitive function in Fontan patients, a population-based study - Idorn, L.; Jensen, A.S.; Juul, K.; Overgaard, D.; Nielsen, N.P.; Sørensen, K.; Reimers, J.I.; Søndergaard, L. (International Journal of Cardiology, 2013)
Background After the Fontan procedure patients are at risk for reduced quality of life (QoL) and cognitive function. We aimed to assess these important factors in Danish Fontan patients and to compare the results with a group of healthy controls. Methods All Fontan patients living in Denmark were identified and invited to participate. QoL was evaluated using the Pediatric Quality of Life Inventory (PedsQL) version 4.0 generic core module in patients < 16 years and the Short Form 36 questionnaire (SF-36) in patients ≥ 16 years. Cognitive function was evaluated in all patients ≥ 6 years using the Quick Test of Cognitive Speed. To evaluate if QoL correlated with exercise capacity, patients performed a symptom-limited bicycle test. Results 158 of 179 eligible patients (88%) consented to participate. Median age was 13.9 years (IQR: 10.2-19.3). PedsQL scores increased with age but were significantly lower among patients than among controls. SF-36 physical scores were significantly lower in patients compared to controls while psychosocial scores were similar. Cognitive speed was significantly reduced in patients at all ages compared to controls. No significant difference in PedsQL-/SF-36 scores or cognitive speed was found between hypoplastic left heart syndrome (HLHS) and non-HLHS Fontan patient. PedsQL-/SF-36 scores in patients ≥ 10 years correlated significantly to cognitive speed but not to peak exercise capacity. Conclusion QoL is reduced in Fontan children compared to their healthy counterparts whereas in patients ≥ 16 years only physical, but not psychosocial QoL is reduced. Cognitive speed was significantly lower in patients at all ages compared to controls. © 2013 Elsevier Ireland Ltd.
Keywords: Cognitive function; Congenital heart disease; Fontan patients; Quality of life

Effect of inhaled iloprost on the exercise function of Fontan patients: A demonstration of concept - Rhodes, J.; Ubeda-Tikkanen, A.; Clair, M.; Fernandes, S.M.; Graham, D.A.; Milliren, C.E.; Daly, K.P.; Mullen, M.P.; Landzberg, M.J. (International Journal of Cardiology, 2013)
Background Exercise capacity following Fontan surgery is often depressed. An inability to reduce pulmonary vascular resistance appropriately during exercise may contribute to this phenomenon. The aim of this study was to determine whether administration of iloprost, a selective pulmonary vasodilator, would improve exercise function after Fontan procedure. Methods Double-blind, randomized, placebo controlled, crossover trial. Patients performed two cardiopulmonary exercise tests (CPX) separated by < 1 month. A single nebulizer treatment (iloprost or placebo) was administered before each CPX. Results 18 patients aged 12-49 (median 17) years were recruited. Mild throat discomfort developed in 10/18 patients during iloprost administration; all but 1 were able to complete treatment. No symptoms developed during placebo treatments (p < 0.001). Two additional patients did not complete CPX: one with atrial flutter; another with developmental issues that precluded adequate CPX. In the 15 remaining subjects oxygen pulse (a surrogate for forward stroke volume) at peak exercise was higher following iloprost (median increase 1.2 ml/beat; p < 0.001). Peak VO2 also rose (median increase 1.3 ml/kg/min; p < 0.04). Nine patients had peak VO2 < 30 ml/kg/min; each of these patients had higher peak VO2 following iloprost. Only 3/6 patients with peak VO2 > 30 ml/kg/min had higher peak VO2 following iloprost (p < 0.04). Conclusions Iloprost improves the peak oxygen pulse and peak VO2 of patients with Fontan physiology and appears to be particularly beneficial among patients with impaired exercise function. Treatment is associated with minor side effects. These findings support the concept of pulmonary vasodilator therapy in Fontan patients with limited functional capacity. © 2013 Elsevier Ireland Ltd. All rights reserved.
Keywords: Exercise testing; Fontan procedure; Heart defects, congenital; Vasodilation

Health-related quality of life and congenital heart disease in Australia - Eagleson, K.J.; Justo, R.N.; Ware, R.S.; Johnson, S.G.; Boyle, F.M. (Journal of Paediatrics and Child Health, 2013)
Aim To determine whether, in children with congenital heart disease (CHD), disease severity is associated with health-related quality of life (HRQOL) and impact on the family. Methods Cross-sectional, single-centre study comparing HRQOL outcomes of age and sex matched children with hypoplasia of the left ventricle (HLV) (n = 31) and tetralogy of Fallot (n = 29) was performed in Queensland, Australia. HRQOL was assessed using generic and disease-specific components of the Paediatric Quality of Life Inventory Measurement Model (PedsQL). Intra-diagnostic age group comparisons of HRQOL were examined. Impact of CHD on families and parental HRQOL was assessed using the PedsQL Family Impact Scale. Results Child and parent-proxy reporting indicate children with HLV have significantly lower overall HRQOL than children with tetralogy of Fallot across generic domains of HRQOL (P < 0.0001), with significantly lower scores in physical (P < 0.0001) and psychosocial (P < 0.0001) health domains. No significant difference in child reporting across domains of the Cardiac Module is evident. Parent-proxy reporting indicates significantly lower scores on the symptom scales for children with HLV (P < 0.001), with greater cognitive problems (P < 0.02) and perceived treatment anxiety (P < 0.01). No significant differences in HRQOL were identified between age groups. HLV has a greater overall family impact, with significantly lower parental HRQOL (P = 0.0001) and family functioning (P < 0.0001) summary scores. Conclusions The more severe condition of HLV is associated with poorer HRQOL in some domains and has greater impact on parental HRQOL and family functioning. © 2013 The Authors. Journal of Paediatrics and Child Health.
Keywords: congenital heart disease; paediatrics; quality of life

Pharmacotherapy challenges of fontan-associated plastic bronchitis: A rare pediatric disease - Brooks, K.; Caruthers, R.L.; Schumacher, K.R.; Stringer, K.A. (Pharmacotherapy, 2013)
Pediatric pharmacotherapy is often challenging due to the paucity of available clinical data on the safety and efficacy of drugs that are commonly used in children This quandary is even more prevalent in children with rare diseases. Although extrapolations for dosing and administration are often made from available adult data with similar disease states, this translation becomes even more problematic in rare pediatric diseases. Understanding of rare disease pathophysiology is typically poor, and few, if any, effective therapies have been studied and identified. One condition that illustrates these issues is plastic bronchitis, a rare, most often pediatric disease that is characterized by the production of obstructive bronchial airway casts. This illness primarily occurs in children with congenital heart disease, often after palliative surgery. Plastic bronchitis is a highly clinically relevant and therapeutically challenging problem with a high mortality rate, and, a generally accepted effective pharmacotherapy regimen has yet to be identified. Furthermore, the disease is ill defined, which makes timely identification and treatment of children with plastic bronchitis difficult. The pharmacotherapies currently used to manage this disease are largely anecdotal and vary between the use of macrolide antibiotics, mucolytics, bronchodilators, and inhaled fibrinolytics in a myriad of combinations. The purpose of this review is 2-fold: first, to highlight the dilemma of treating plastic bronchitis, and second, to bring attention to the continuing need for studies of drug therapies used in children so safe and effective drug regimens can be established, particularly for rare diseases. © 2013 Pharmacotherapy Publications, Inc.
Keywords: Adverse effects; Antiinflammatory agents; Congenital heart disease; Fibrinolysis; Fontan procedure; Pulmonary disease

Pharmacological and non-pharmacological therapy for arrhythmias in the pediatric population: EHRA and AEPC-Arrhythmia Working Group joint consensus statement - Brugada, J.; Blom, N.; Sarquella-Brugada, G.; Blomstrom-Lundqvist, C.; Deanfield, J.; Janousek, J.; Abrams, D.; Bauersfeld, U.; Brugada, R.; Drago, F.; De Groot, N.; Happonen, J.-M.; et al. (Europace, 2013)
In children with structurally normal hearts, the mechanisms of arrhythmias are usually the same as in the adult patient. Some arrhythmias are particularly associated with young age and very rarely seen in adult patients. Arrhythmias in structural heart disease may be associated either with the underlying abnormality or result from surgical intervention. Chronic haemodynamic stress of congenital heart disease (CHD) might create an electrophysiological and anatomic substrate highly favourable for re-entrant arrhythmias.As a general rule, prescription of antiarrhythmic drugs requires a clear diagnosis with electrocardiographic documentation of a given arrhythmia. Risk-benefit analysis of drug therapy should be considered when facing an arrhythmia in a child. Prophylactic antiarrhythmic drug therapy is given only to protect the child from recurrent supraventricular tachycardia during this time span until the disease will eventually cease spontaneously. In the last decades, radiofrequency catheter ablation is progressively used as curative therapy for tachyarrhythmias in children and patients with or without CHD. Even in young children, procedures can be performed with high success rates and low complication rates as shown by several retrospective and prospective paediatric multi-centre studies. Three-dimensional mapping and non-fluoroscopic navigation techniques and enhanced catheter technology have further improved safety and efficacy even in CHD patients with complex arrhythmias.During last decades, cardiac devices (pacemakers and implantable cardiac defibrillator) have developed rapidly. The pacing generator size has diminished and the pacing leads have become progressively thinner. These developments have made application of cardiac pacing in children easier although no dedicated paediatric pacing systems exist. © 2013 The Author.
Keywords: Antiarrhythmic drugs; Arrhythmias; Electrical devices; Paediatrics; Radiofrequency ablation

A non-discrete method for computation of residence time in fluid mechanics simulations - Esmaily-Moghadam, M.; Hsia, T.; Marsden, A.L. (Physics of Fluids, 2013)
Cardiovascular simulations provide a promising means to predict risk of thrombosis in grafts, devices, and surgical anatomies in adult and pediatric patients. Although the pathways for platelet activation and clot formation are not yet fully understood, recent findings suggest that thrombosis risk is increased in regions of flow recirculation and high residence time (RT). Current approaches for calculating RT are typically based on releasing a finite number of Lagrangian particles into the flow field and calculating RT by tracking their positions. However, special care must be taken to achieve temporal and spatial convergence, often requiring repeated simulations. In this work, we introduce a non-discrete method in which RT is calculated in an Eulerian framework using the advection-diffusion equation. We first present the formulation for calculating residence time in a given region of interest using two alternate definitions. The physical significance and sensitivity of the two measures of RT are discussed and their mathematical relation is established. An extension to a point-wise value is also presented. The methods presented here are then applied in a 2D cavity and two representative clinical scenarios, involving shunt placement for single ventricle heart defects and Kawasaki disease. In the second case study, we explored the relationship between RT and wall shear stress, a parameter of particular importance in cardiovascular disease. © 2013 AIP Publishing LLC.

Psychosocial experiences of parents of infants with hypoplastic left heart syndrome in the PICU - Cantwell-Bartl, A.M.; Tibballs, J. (Pediatric Critical Care Medicine, 2013)
Objective: To evaluate the psychosocial status of mothers and fathers of infants with hypoplastic left heart syndrome while in the PICU. Design: A retrospective study combining interviews and psychometric testing of parents. Setting: Tertiary hospital PICU. Subjects: Twenty-nine parents (16 mothers and 13 fathers) of surviving children. Intervention: A semistructured face-to-face interview was conducted to explore parental experiences, and a Structured Clinical Interview for Diagnosis-Clinical Version (posttraumatic stress disorder module) was conducted to determine the possibility of an acute stress disorder or a posttraumatic stress disorder. Measurement and Main Results: All parents reported multiple stresses which commenced with their infant's diagnosis and endured throughout their infant's time in PICU. The Structured Clinical Interview for Diagnosis revealed that acute stress disorder or posttraumatic stress disorder developed in 24 parents (83%). Of 18 parents whose infants were diagnosed with hypoplastic left heart syndrome in utero, eight of nine mothers (88%) and six of nine fathers (66%) had posttraumatic stress disorder. Of 11 parents whose infants were diagnosed with hypoplastic left heart syndrome postbirth, six of seven mothers had acute stress disorder and one mother had posttraumatic stress disorder, and of four fathers, two fathers had acute stress disorder and one father had posttraumatic stress disorder. The prevalence of parental stress-related disorder was not different between mothers and fathers (p = 0.85). Only five parents were free of traumatic stress-related illness. Parents also experienced losses. Many parents were marginalized from their infant's care by the environment of PICU. Fifty percent of mothers experienced difficulties with parental-infant bonding. Ten parents (34%) began the process of adaptation to their infant's hypoplastic left heart syndrome and were assisted by the support and sensitivity of staff or had discovered other resources. Conclusions: All parents of surviving infants with hypoplastic left heart syndrome in PICU, irrespective of timing of diagnosis, experienced numerous stresses and losses, and the majority exhibited clinical levels of traumatic stress. Receiving the diagnosis itself is very traumatic and is compounded by the environment of the PICU which alienates parents from their infants and interferes with parent-infant bonding. Parental adaptation to this situation can be assisted by staff. Copyright © 2013 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Acute stress disorder; Adaptation; Hypoplastic left heart syndrome; Intensive care; Parents; Posttraumatic stress disorder; Psychological; Stress

Use of diagnostic information submitted to the United Kingdom Central Cardiac Audit Database: Development of categorisation and allocation algorithms - Brown, K.L.; Crowe, S.; Pagel, C.; Bull, C.; Muthialu, N.; Gibbs, J.; Cunningham, D.; Utley, M.; Tsang, V.T.; Franklin, R. (Cardiology in the Young, 2013)
Abstract Objective To categorise records according to primary cardiac diagnosis in the United Kingdom Central Cardiac Audit Database in order to add this information to a risk adjustment model for paediatric cardiac surgery. Design Codes from the International Paediatric Congenital Cardiac Code were mapped to recognisable primary cardiac diagnosis groupings, allocated using a hierarchy and less refined diagnosis groups, based on the number of functional ventricles and presence of aortic obstruction. Setting A National Clinical Audit Database. Patients Children undergoing cardiac interventions: the proportions for each diagnosis scheme are presented for 13,551 first patient surgical episodes since 2004. Results In Scheme 1, the most prevalent diagnoses nationally were ventricular septal defect (13%), patent ductus arteriosus (10.4%), and tetralogy of Fallot (9.5%). In Scheme 2, the prevalence of a biventricular heart without aortic obstruction was 64.2% and with aortic obstruction was 14.1%; the prevalence of a functionally univentricular heart without aortic obstruction was 4.3% and with aortic obstruction was 4.7%; the prevalence of unknown (ambiguous) number of ventricles was 8.4%; and the prevalence of acquired heart disease only was 2.2%. Diagnostic groups added to procedural information: of the 17% of all operations classed as not a specific procedure, 97.1% had a diagnosis identified in Scheme 1 and 97.2% in Scheme 2. Conclusions Diagnostic information adds to surgical procedural data when the complexity of case mix is analysed in a national database. These diagnostic categorisation schemes may be used for future investigation of the frequency of conditions and evaluation of long-term outcome over a series of procedures. © 2012 Cambridge University Press.
Keywords: congenital heart disease; Keywords Outcomes; quality assurance

Experimental characterization of powered Fontan hemodynamics in an idealized total cavopulmonary connection model - Kerlo, A.-E.M.; Delorme, Y.T.; Xu, D.; Frankel, S.H.; Giridharan, G.A.; Rodefeld, M.D.; Chen, J. (Experiments in Fluids, 2013)
A viscous impeller pump (VIP) based on the Von Karman viscous pump is specifically designed to provide cavopulmonary assist in a univentricular Fontan circulation. The technology will make it possible to biventricularize the univentricular Fontan circulation. Ideally, it will reduce the number of surgeries required for Fontan conversion from three to one early in life, while simultaneously improving physiological conditions. Later in life, it will provide a currently unavailable means of chronic support for adolescent and adult patients with failing Fontan circulations. Computational fluid dynamics simulations demonstrate that the VIP can satisfactorily augment cavopulmonary blood flow in an idealized total cavopulmonary connection (TCPC). When the VIP is deployed at the TCPC intersection as a static device, it stabilizes the four-way flow pattern and is not obstructive to the flow. Experimental studies are carried out to assess performance, hemodynamic characteristics, and flow structures of the VIP in an idealized TCPC model. Stereoscopic particle image velocimetry is applied using index-matched blood analog. Results show excellent performance of the VIP without cavitation and with reduction of the energy losses. The non-rotating VIP smoothes and accelerates flow, and decreases stresses and turbulence in the TCPC. The rotating VIP generates the desired low-pressure Fontan flow augmentation (0-10 mmHg) while maintaining acceptable stress thresholds. © 2013 Springer-Verlag Berlin Heidelberg.

Newer imaging modalities in the assessment of heart function in single ventricle hearts - Khoo, N.S.; Tham, E.B.; Kantor, P.F. (Canadian Journal of Cardiology, 2013)
The limitations of geometry assumptions in 2-dimensional echocardiographic assessment of the single ventricle (SV) have been overcome by recent advances in 3-D echocardiography. Improved reproducibility for measuring ventricular volumes and ejection fraction using 3-D echocardiography makes it ideally suited for serial monitoring of SV systolic function and should be considered in routine echocardiography imaging protocols for SV. The moderate correlation of Doppler derived E/e' ratio with invasive ventricular end diastolic pressure in SV, suggests it might be useful in the assessment of SV diastolic function. Speckle tracking imaging is intensely studied and promises to be a simple and repeatable imaging tool for quantifying SV function. In contrast, the advances in cardiac magnetic resonance imaging techniques promise to offer insights into the pathogenesis of myocardial dysfunction in SV. Late gadolinium enhancement imaging is a robust tool in assessing macroscopic myocardial scarring and T1 mapping and stress perfusion imaging are newer modalities that might improve understanding of the mechanisms in progressive myocardial dysfunction in SV hearts. © 2013 Canadian Cardiovascular Society.

Cardiac performance and quality of life in patients who have undergone the Fontan procedure with and without prior superior cavopulmonary connection - Atz, A.M.; Travison, T.G.; McCrindle, B.W.; Mahony, L.; Glatz, A.C.; Kaza, A.K.; Breitbart, R.E.; Colan, S.D.; Kaltman, J.R.; Margossian, R.; Pasquali, S.K.; Wang, Y.; et al. (Cardiology in the Young, 2013)
Background A superior cavopulmonary connection is commonly performed before the Fontan procedure in patients with a functionally univentricular heart. Data are limited regarding associations between a prior superior cavopulmonary connection and functional and ventricular performance late after the Fontan procedure. Methods We compared characteristics of those with and without prior superior cavopulmonary connection among 546 subjects enrolled in the Pediatric Heart Network Fontan Cross-Sectional Study. We further compared different superior cavopulmonary connection techniques: bidirectional cavopulmonary anastomosis (n equals 229), bilateral bidirectional cavopulmonary anastomosis (n equals 39), and hemi-Fontan (n equals 114). Results A prior superior cavopulmonary connection was performed in 408 subjects (75%); the proportion differed by year of Fontan surgery and centre (p-value less than 0.0001 for each). The average age at Fontan was similar, 3.5 years in those with superior cavopulmonary connection versus 3.2 years in those without (p-value equals 0.4). The type of superior cavopulmonary connection varied by site (p-value less than 0.001) and was related to the type of Fontan procedure. Exercise performance, echocardiographic variables, and predominant rhythm did not differ by superior cavopulmonary connection status or among superior cavopulmonary connection types. Using a test of interaction, findings did not vary according to an underlying diagnosis of hypoplastic left heart syndrome. Conclusions After controlling for subject and era factors, most long-term outcomes in subjects with a prior superior cavopulmonary connection did not differ substantially from those without this procedure. The type of superior cavopulmonary connection varied significantly by centre, but late outcomes were similar. © 2012 Cambridge University Press.
Keywords: Congenital heart disease; Fontan; functionally univentricular heart; quality of life

Impact of bosentan on exercise capacity in adults after the Fontan procedure: A randomized controlled trial - Schuuring, M.J.; Vis, J.C.; Van Dijk, A.P.J.; Van Melle, J.P.; Vliegen, H.W.; Pieper, P.G.; Sieswerda, G.T.; De Bruin-Bon, R.H.A.C.M.; Mulder, B.J.M.; Bouma, B.J. (European Journal of Heart Failure, 2013)
AimsAn endothelin-1 receptor blocker, shown to be effective in patients with pulmonary arterial hypertension, might decrease pulmonary vascular resistance to increase cardiac filling and consequently improve exercise capacity in Fontan patients.Methods and resultsThis was a prospective, multicentre randomized open label trial in Fontan patients. One group received bosentan for 6 months. The other group did not receive study medication for the first 3 months, followed by bosentan for 6 months. The primary endpoint was exercise capacity, and secondary endpoints were NT-proBNP level, cardiac output, SF-36 (Short Form-36) quality of life (QoL), and NYHA class. Forty-two adults (median age 29 (range 18-56) years, 52% male, 88% NYHA class I-II) from five tertiary referral centres participated in the study. Ten patients were on diuretics. Ten patients were not motivated to finish the study. Analysis of all 32 patients who finished the study at 6 months of treatment showed that mean peak V'O2 (24 vs. 25 mL/kg/min), median SQUASH score (6614 vs. 6390), median NT-proBNP (314 vs. 274 ng/L), and mental QoL (50 vs. 51) remained unchanged as compared with baseline (P = NS, for all). After treatment, NYHA class had improved in 6 (19%), was unchanged in 24 (75%), and declined in 2 (6%) patients. Subgroup analysis on age, ventricular morphology, type of Fontan circulation, or baseline NT-proBNP level did not reveal efficacy of bosentan. Six transient adverse effects were reported.ConclusionAn increased NT-proBNP level was present in the majority of Fontan patients. Six months of bosentan treatment was not beneficial.Trial registrationNTR1557All rights reserved. © 2013 The Author.
Keywords: Bosentan; Exercise capacity; Fontan

Dual-pump support in the inferior and superior vena cavae of a patient-specific fontan physiology - Throckmorton, A.L.; Lopez-Isaza, S.; Moskowitz, W. (Artificial Organs, 2013)
The implementation of simultaneous mechanical cavopulmonary assistance having blood pumps located in both of the vena cavae is investigated as an approach to treating patients with an ailing Fontan physiology. Identical intravascular blood pumps are employed to model the hemodynamic support of a patient-specific Fontan. Pressure flow characteristics, energy gain calculations, and blood damage analyses are assessed for each model. The performance of the dual-support scenario is compared to conditions of mechanical support in the inferior vena cava only and to a nonsupported cavopulmonary circuit. The blood pump in the superior vena cava generates pressures ranging from 1 to 22mmHg for flow rates of 1-4L/min at operating speeds of 1250-2500rpm. The blood pump in the inferior vena cava produces pressures at levels approximately 20% lower. The blood pumps positively augment the hydraulic energy in the total cavopulmonary connection circuit as a function of flow rate and rotational speed. Scalar stress levels and fluid residence times are at acceptable levels. Damage indices for the dual-support case, however, are elevated slightly above 3.5%. These results suggest that concurrent, mechanical assistance of the inferior vena cava and superior vena cava in Fontan patients has the potential to be beneficial, but additional studies are needed to further explore this approach. © 2013, Authors. Artificial Organs © 2013, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Artificial right ventricle; Blood pump; Cavopulmonary assist device; Computational fluid dynamics; Fontan physiology; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Total cavopulmonary connection

The effect of Bosentan on exercise capacity in Fontan patients; rationale and design for the TEMPO study - Hebert, A.; Jensen, A.S.; Idorn, L.; Sørensen, K.E.; Søndergaard, L. (BMC Cardiovascular Disorders, 2013)
Background: Palliative treatment with the Fontan procedure has greatly improved survival for children with functionally univentricular heart. Since Fontan performed the first successful operation, the procedure has evolved and is now performed as Total Cavo-Pulmonary Connection (TCPC).An increasing prevalence and longer life expectancy of TCPC patients have raised new challenges. The survivors are often suffering complications such as arrhythmias, myocardial dysfunction, thromboembolic events, neuropsychological deficit, protein-losing enteropathy and reduced exercise capacity. Several causes for the reduced exercise capacity may be present e.g. impaired function of the single ventricle, valve dysfunction and chronotropic impairment, and perhaps also increased pulmonary vascular resistance. Thus, plasma endothelin-1 has been shown to correlate with increased pulmonary vascular resistance and the risk of failing Fontan circulation. This has raised the question of the role for pulmonary vasodilation therapy, especially endothelin receptor antagonist in the management of TCPC patients.Methods/Design: The TEMPO trial aims to investigate whether Bosentan, an endothelin receptor antagonist, can be administered safely and improve exercise capacity in TCPC patients. The trial design is randomized, double-blind and placebo-controlled. Bosentan/placebo is administered for 14 weeks with control visits every four weeks. The primary endpoint is change in maximal oxygen consumption as assessed on bicycle ergometer test. Secondary endpoints include changes in pulmonary blood flow during exercise test, pro brain natriuretic peptide and quality of life.Discussion: We hypothesize that treatment with Bosentan, an endothelin receptor antagonist, can be administered safely and improve exercise capacity in TCPC patients.Trial registration: clinicaltrials.gov NCT01292551. © 2013 Hebert et al.; licensee BioMed Central Ltd.
Keywords: Endothelin receptor antagonist; Exercise capacity; Fontan; Randomized placebo-controlled trial; Univentricular heart

Prognosis of children with cardiomyopathy submitted to fontan surgery: 30 years of experience at the Hospital Infantil de México Federico Gómez - Bolio-Cerdán, A.; Ruiz-González, S.; Romero-Cárdenas, P.; Hernández-Morales, G.; Villasís-Keever, M.A. (Boletin Medico del Hospital Infantil de Mexico, 2013)
Background. At the present time, the Fontan procedure is indicated for patients with univentricular cardiac pathology. In Mexico, few tertiary centers are performing Fontan surgery in the pediatric population. The objective was to analyze the results of patients with congenital heart disease with univentricular physiology who have undergone Fontan surgery since 1980 in the Hospital Infantil de Mexico Dr. Federico Gomez. Methods. We present a retrospective analysis of pediatric patients undergoing Fontan surgery. We included variables related to preoperative mortality and morbidity, those related to surgery and to the postoperative period. A bivariate analysis with the comparison of averages and odds ratio was performed. Kaplan-Meier survival curves were constructed. Results. From 1983 to 2012, 53 Fontan surgeries have been performed. Of the total, comprehensive data of 32 patients were gathered. The most common congenital heart anomaly was tricuspid atresia IB (39.4%); according to type of surgery, in 48% of patients extracardiac Fontan was performed followed by intracardiac Fontan (24%). In 87% of patients fenestration was performed. The most common complications were acute renal failure, neurological problems and pleural effusion. Overall survival was 65.6%; 90.9% of patients died within the first month of surgery. Patients have been reported with >20 years of survival (average actuarial survival 14.5 years). Variables associated with mortality were younger age at surgery, type of Fontan performed, surgical technique complications, lack of fenestration and acute renal failure. Conclusions. Evolution of Fontan surgery during the past 30 years has been satisfactory. In patients undergoing this procedure, mortality and quality of life have shown improvements.
Keywords: Congenital heart disease; Fontan surgery; Prognosis

Mechanical support as failure intervention in patients with cavopulmonary shunts (MFICS): Rationale and aims of a new registry of mechanical circulatory support in single ventricle patients - Rossano, J.W.; Woods, R.K.; Berger, S.; Gaynor, J.W.; Ghanayem, N.; Morales, D.L.S.; Ravishankar, C.; Mitchell, M.E.; Shah, T.K.; Mahr, C.; Tweddell, J.S.; Adachi, I.; et al. (Congenital Heart Disease, 2013)
It is now recognized that a majority of single ventricle patients, those with functionally univentricular hearts, who have survived palliative cavopulmonary connection will experience circulatory failure and end-organ dysfunction due to intrinsic inadequacies of a circulation supported by a single ventricle. Thus, there are an increasing number of patients with functional single ventricles presenting with failing circulations that may benefit from mechanical circulatory support (MCS). The paucity of experience with MCS in this population, even at high volume cardiac centers, contributes to limited available data to guide MCS device selection and management. Thus, a registry of MCS in this population would be beneficial to the field. A conference was convened in January 2012 of pediatric and adult cardiologists, pediatric cardiac intensivists, congenital heart surgeons, and adult cardiothoracic surgeons to discuss the current state of MCS, ventricular assist device, and total artificial heart therapy for patients who have undergone cavopulmonary connection, either superior cavopulmonary connection or total cavopulmonary connection. Specifically, individual experience and challenges with VAD therapy in this population was reviewed and creation of a multiinstitutional registry of MCS/ventricular assist device in this population was proposed. This document reflects the consensus from the meeting and provides a descriptive overview of the registry referred to as Mechanical Support as Failure Intervention in Patients with Cavopulmonary Shunts. © 2013 Wiley Periodicals, Inc.
Keywords: Registry; Single Ventricle; Ventricular Assist Device

Lymphoscintigraphy in plastic bronchitis, A pediatric case report - Ezmigna, D.R.; Morgan, W.J.; Witte, M.H.; Brown, M.A. (Pediatric Pulmonology, 2013)
Plastic bronchitis (PB) is an uncommon, potentially fatal disease, marked by endobronchial cast formation causing variable degrees of respiratory distress. Primary and secondary pulmonary lymphatic abnormalities have been identified among the underlying mechanisms of cast formation. We present a case of PB where lymphoscintigraphy demonstrated the underlying lymphatic defect. A 6-year-old Hispanic male with congenital heart disease (CHD; post-Fontan) presented with recurrent pneumonia, respiratory distress. Bronchoscopy showed inflamed hypervascular mucosa and thick mucus plugs; no casts were seen. Later, PB was diagnosed after the patient expectorated a bronchial cast. Cast analysis showed lymphocytic aggregates with mucin and fibrin. Lymphoscintigraphy revealed abnormal lymphatic collaterals and retrograde trace reflux into the superior mediastinum, a picture consistent with thoracic duct lymph leakage into the tracheobronchial tree. The pathogenesis of PB is not fully understood, especially in patients with CHD. Chyle in bronchial casts suggests abnormal lymphatic flow. Reports of lymph flow abnormalities, especially endobronchial lymph leakage in CHD are limited. Lymphoscintigraphy in our case demonstrated clear evidence of retrograde lymph reflux and leakage into the bronchial tree. The case presented suggests that in some patients following Fontan surgery, high intrathoracic lymphatic pressure and retrograde lymph flow may contribute to recurrent cast formation. Finding the underlying lymphatic abnormality helps in specific case management. Lymphoscintigraphy is a safer and easier method than lymphangiography. Surgical lymphatic-venous shunting may be possible in select cases. © 2012 Wiley Periodicals, Inc.
Keywords: congenital heart disease; lymph leakage; lymphoscintigraphy; plastic bronchitis

Cavopulmonary anastomosis without cardiopulmonary bypass - Mostafa, E.A.; El Midany, A.A.H.; Zalat, M.M.; Helmy, A. (Interactive Cardiovascular and Thoracic Surgery, 2013)
OBJECTIVESThere is an increasing trend to perform the bidirectional superior cavopulmonary (Glenn) anastomosis without cardiopulmonary bypass. In this report, we present our results of off-pump bidirectional Glenn operation done without using a venoatrial shunt to decompress the randomized comparative study was superior vena cava during clamping.METHODSA prospective, non-randomized comparative study was conducted in 50 patients with functional single ventricle anomalies who underwent bidirectional Glenn anastomosis without cardiopulmonary bypass. The patients were divided into two groups: Group I (n = 25), where it was done without a veno-atrial shunt, and Group II (n = 25), where it was done with a veno-atrial shunt. Two patients in Group I and 4 patients in Group II had a bilateral bidirectional Glenn shunt. Five patients in Group I and three patients in Group II had a previous left modified Blalock-Taussig shunt. All patients underwent a complete neurological examination both preoperatively as well as postoperatively.RESULTSThe early hospital mortality was 4% (2/50), one in each group. The median follow-up was 14 months. The mean internal venous pressure on clamping the superior vena cava was 37.07 ± 7.12 mmHg in Group I and 24 ± 4.4 mmHg in Group II. The mean clamp time was 9.85 ± 3.52 min in Group I and 21.3 ± 4.4 min in Group II. The transcranial pressure gradient was 62.37 ± 15.01 mmHg in Group I, while 65.08 ± 13.89 in Group II. The mean intensive care unit stay was 2.57 ± 75 days in Group I, 3.3 ± 1.09 in Group II. There were no major neurological complications apart from treatable convulsions in one case in Group I (4%), 2 cases in Group II (8%), and delayed recovery in one case (4%) in Group I.CONCLUSIONSOff-pump bidirectional Glenn operation without caval decompression is a safe, simple and more economic procedure. © 2013 The Author 2013.
Keywords: Bidirectional Glenn shunt; Coronary heart disease; Off-pump surgery; Univentricular heart

In favor of the hybrid stage 1 as the initial palliation for hypoplastic left heart syndrome - Galantowicz, M. (Seminars in Thoracic and Cardiovascular Surgery: Pediatric Cardiac Surgery Annual, 2013)
There are many reasons to consider using the Hybrid Stage 1 procedure as the initial palliation for hypoplastic left heart syndrome. It allows all options for treatment, including a delayed traditional approach, as well as a platform to evolve our overall approach to this challenging heart defect. © 2013 Elsevier Inc.

Congenital heart disease in elementary school children in rural Thailand: The role of the trained noncardiologist - Cholkraisuwat, E.; Buddharaksa, Y.; Sayasathid, J. (Asian Biomedicine, 2013)
Background: Congenital heart diseases (CHD) comprise about one-third of all major birth defects. Children with delayed diagnosis and improper treatment are at a high risk of morbidity and mortality. Objective: To determine the prevalence of unrecognized congenital heart disease among elementary school students and study the types and frequency of congenital heart disease in Phitsanulok, Pichit, and Kampangpetch provinces of Thailand using trained nurses and other health care personnel. Methods: Between September 2008 and September 2010, 138,529 students from 1,243 elementary schools were screened for abnormal heart conditions by trained nurses or health care workers. The students who were suspected to have CHD were referred to a pediatric cardiologist for complete evaluation and identification of the lesions. Results: Five hundred forty eight students were suspected to have heart diseases and 102 students were diagnosed as CHD. The average prevalence of unrecognized CHD in Phitsanulok, Pichit, and Kampangpetch was 0.74 per 1,000. Simple acyanotic lesions (ventricular septal defect, atrial septal defect, and pulmonary stenosis) were common in this study (32.35%, 16.67%, and 11.76%, respectively). Conclusion: Qualified nurses or health care workers can be useful for identifying patients with CHD. The role of these personnel in the national heart screening program should be further clarified.
Keywords: Congenital heart disease screening in children; Prevalence; Thailand

Myocardial perfusion abnormalities in patients occurring more than 1 year after successful univentricular (fontan surgery) and biventricular repair (complete repair of tetralogy of fallot) - Priyadarshini, A.; Saxena, A.; Patel, C.; Paul, V.K.; Lodha, R.; Airan, B. (Pediatric Cardiology, 2013)
The outcome of children born with cyanotic congenital heart disease has markedly improved over the years. Follow up is recommended for most post-operated cases as complications may occur over long term. One of the complications is the development of ventricular dysfunction, often seen after a successful Fontan surgery (or one of its modifications) for single ventricle. The aim of this study was to determine the prevalence of myocardial perfusion abnormalities in the ventricular myocardium of asymptomatic patients, older than 8 years of age, who had earlier undergone either a univentricular palliation (modified Fontan procedure) or a biventricular repair for tetralogy of Fallot, more than a year ago. All eligible patients underwent screening electrocardiogram (to rule out rhythm disturbance) and echocardiography. Patients with ventricular ejection fraction of more than 50 % by echocardiography were included. Enrolled patients were subjected to gated stress-rest myocardial perfusion imaging using Technitium-99m tetrofosmin single photon emission-computerized tomography (SPECT). Ventricular ejection fraction was also calculated from gated rest study. For the Fontan group, we also analyzed data to see if the morphology of the systemic ventricle would make a difference as far as myocardial perfusion was concerned. Twenty-six patients were enrolled (11 had undergone Fontan surgery and 15 had complete repair of tetralogy of Fallot). Seven of 11 patients in the Fontan group had myocardial perfusion defects (63.6 %) as against none in the repaired tetralogy of Fallot group (p < 0.001). The ejection fraction was within normal range in both the groups; it was statistically higher in the post tetralogy of Fallot repair group (p < 0.04). There were two subgroups in the post Fontan group depending on the morphology of systemic ventricle-left (4 patients) and non-left (7 patients). Higher number and larger size of perfusion defects were present in the non-left ventricular systemic ventricle morphology as compared with left ventricular morphology, but this difference did not reach statistical significance. Myocardial perfusion defects are common in patients who have undergone univentricular repair more than one year ago in contrast to patients who had a biventricular repair for tetralogy of Fallot. In the Fontan group, the morphology of the systemic ventricle was not predictive of prevalence of perfusion defect. © 2012 Springer Science+Business Media New York.
Keywords: Fontan procedure; Myocardial perfusion defects; Tetralogy of Fallot

1q21.1 Microduplication expression in adults - Dolcetti, A.; Silversides, C.K.; Marshall, C.R.; Lionel, A.C.; Stavropoulos, D.J.; Scherer, S.W.; Bassett, A.S. (Genetics in Medicine, 2013)
Purpose:Rare, recurrent chromosome 1q21.1 duplications have been associated with developmental delay, congenital anomalies, and macrocephaly in children. Data on adult clinical expression would help to inform genetic counseling.Methods:A systematic review of 22 studies reporting 107 individuals (59 children and 48 adults) with 1q21.1 duplications was conducted. We compiled the available phenotypic data to attempt to identify the most highly associated clinical features and to determine expression in adults. We also report on seven adult cases newly identified in the studies of schizophrenia and tetralogy of Fallot at our center.Results:Five cases were ascertained as controls, 32 as relatives of probands, and 70 as having clinical features: autism spectrum disorder (n = 15), congenital heart disease (n = 12), schizophrenia (n = 10), or other, mostly developmental, features (n = 33). The 1q21.1 duplication was significantly enriched in the cohorts with schizophrenia (P = 0.0155) and tetralogy of Fallot (P = 0.0040) at our center as compared with controls. There was a paucity of clinical data for adults; the most common features, other than those used for ascertainment, included macrocephaly and abnormalities of possible connective tissue origin (e.g., carpal tunnel syndrome).Conclusion: Further data are needed to characterize lifetime expression of 1q21.1 duplications. These initial results, however, suggest that anticipatory care should include attention to later-onset conditions such as schizophrenia.
Keywords: 1q21.1 duplication; copy-number variation; macrocephaly; schizophrenia; tetralogy of Fallot

Living at altitude adversely affects survival among patients with a fontan procedure - Johnson, J.T.; Lindsay, I.; Day, R.W.; Van Dorn, C.S.; Hoffman, J.; Everitt, M.D.; Yetman, A.T. (Journal of the American College of Cardiology, 2013)
Objectives: This study sought to determine whether survival in this cohort of patients was adversely affected by increased residential altitude. Background: The success of the Fontan procedure depends in large part on low pulmonary vascular resistance (PVR). Factors that increase PVR, including an increase in residential altitude, may adversely affect long-term outcome. Higher altitude has been shown to affect functional well-being in patients with a Fontan circulation. Methods: Databases from a tertiary cardiac care center in the Intermountain West (elevation 5,000 feet) were analyzed for patients born with single-ventricle anatomy who would now be of adult age. Complete data were then collected on all identified patients who subsequently underwent the Fontan operation. Correlates of, and time to, adverse outcome, defined as death, cardiac transplantation, or clinical decompensation requiring a move to sea level, were determined. Results: Of 149 patients with single-ventricle anatomy, 103 underwent the Fontan procedure, with 70 surviving to adulthood at moderate altitude. Adverse outcome occurred in 55, with death in 24 (23%), cardiac transplantation in 18 (17%), and clinical decompensation requiring move to sea level in 13 (13%). There was no relationship between type, age at, or era of Fontan procedure and long-term outcome. Correlates of long-term, transplant-free survival at moderate altitude included lower residential altitude (4,296 vs. 4,637 feet, p < 0.001), and lower pulmonary artery pressures before the Fontan procedure (13 vs. 15 mm Hg, p = 0.01), and after (14 vs. 18 mm Hg, p = 0.01). Conclusions Long-term outcome after the Fontan procedure is adversely impacted by higher residential altitude. © 2013 by the American College of Cardiology Foundation.
Keywords: Altitude; Fontan; Protein-losing enteropathy; Survival

Perioperative management of shock in two fontan patients with plastic bronchitis - Singhal, N.R.; Da Cruz, E.M.; Nicolarsen, J.; Schwartz, L.I.; Merritt, G.R.; Barrett, C.; Twite, M.D.; Ing, R.J. (Seminars in Cardiothoracic and Vascular Anesthesia, 2013)
Plastic bronchitis is potentially a life-threatening complication of long-standing surgically palliated single ventricle congenital heart disease. Patients can present with hypoxia requiring urgent bronchoscopy for removal of bronchial casts. Perioperative care for these patients is challenging and anesthesia is associated with significant cardiac risk. As more surgically corrected single ventricle patients survive to adulthood, these patients are expected to present more frequently. This report details the perioperative management of 2 Fontan patients with hypoxia and significant plastic bronchitis disease burden. © The Author(s) 2013.
Keywords: angiotensin-converting enzyme inhibitors; cardiac anesthesia; cardiovascular risk; children; circulatory arrest pediatric; congenital heart disease; critical care; heart failure; intensive care unit; near-infrared spectroscopy

Parenting under Pressure: A grounded theory of parenting young children with life-threatening congenital heart disease - Rempel, G.R.; Ravindran, V.; Rogers, L.G.; Magill-Evans, J. (Journal of Advanced Nursing, 2013)
Aim. To report a grounded theory study to describe the process of parenting young children who have survived hypoplastic left heart syndrome to inform parent-focused interventions. Background. Technological advances in paediatric cardiology worldwide have improved the survival rates for young children with hypoplastic left heart syndrome who undergo staged surgical palliation. These children, however, are at risk for life-threatening complications and parents are charged with the responsibility to monitor their children at home with minimal support and guidance from healthcare professionals once home. Design. A constructivist grounded theory study. Method. The study was conducted in 2006-2008. Participants were 25 parents (15 mothers, 10 fathers) and 28 grandparents (17 grandmothers, 11 grandfathers) of 15 young children (6months-4·5years) who had undergone the Sano surgical approach for hypoplastic left heart syndrome. The 53 interviews were digitally recorded, transcribed and analysed using open and focused coding, constant comparative analysis and memoing. Findings. A process of Parenting under Pressure emerged that was characterized by four overlapping and re-emerging phases: (1) realizing and adjusting to the inconceivable; (2) growing increasingly attached; (3) watching for and accommodating the unexpected; and (4) encountering new challenges. Conclusions. In-depth understanding of the phases of Parenting under Pressure provides direction for nurses to support parents of children who survive hypoplastic left heart syndrome. Interventions that help carers of children with complex health conditions move through the phases of our Parenting under Pressure process may help them safeguard the survival of their children, and their own survival as parents as they manage multiple demands. © 2012 Blackwell Publishing Ltd.
Keywords: Congenital heart disease; Grounded theory; Hypoplastic left heart syndrome; Nursing; Parenting; Qualitative research

Living with half a heart-experiences of young adults with single ventricle physiology: A qualitative study - Overgaard, D.; King, C.; Christensen, R.F.; Schrader, A.-M.; Adamsen, L. (Journal of Cardiovascular Nursing, 2013)
BACKGROUND AND RESEARCH OBJECTIVE:: Approximately 3% of children with congenital heart disease born in Denmark have single ventricle physiology (SVP). In previous decades, these children did not survive into adulthood. However, because of new surgical techniques and improved medical care, they now have a 90% survival rate. Several studies have described the somatic status of SVP patients using clinical parameters; however, only a few studies have researched the life perspectives and coping skills in this patient group. The aim of this study was to investigate how young adults with an SVP diagnosis are coping with adulthood and the emotional experiences of daily life. SUBJECTS AND METHODS:: Semistructured, qualitative interviews were held with 11 SVP respondents, selected by physical and psychological parameters identified in an earlier quantitative study. Data from the interviews were analyzed by a research group using a phenomenological methodology. RESULTS AND CONCLUSIONS:: The goal for SVP patients is to gain control over their disease to live normal lives. Patients require special support from their core network to overcome physical and psychological challenges. Respondents underscored the need for friends and resource persons outside the family to help lift them out of their role as disabled cardiac patients and provide them with "normal" life experiences. Copyright © 2013 Lippincott Williams & Wilkins.
Keywords: congenital heart disease; lived experiences; network; normalization; single ventricle physiology

Use of aerosolized tissue plasminogen activator in the treatment of plastic bronchitis - Lubcke, N.L.; Nussbaum, V.M.; Schroth, M. (Annals of Pharmacotherapy, 2013)
OBJECTIVE: To present a case of nebulized tissue plasminogen activator (t-PA) treatment for symptomatic plastic bronchitis in a pediatric patient years after a Fontan procedure. CASE SUMMARY: A 13-year-old boy with a history of corrected congenital heart disease was admitted to the pediatric intensive care unit after 2 weeks of worsening respiratory distress. A chest radiograph and subsequent bronchoscopy revealed extensive mucus plugging due to plastic bronchitis. Casts reaccumulated quickly after manual removal of the mucus and a regimen of aerosolized t-PA was initiated to break down the casts and prevent further cast formation over the 17-day hospital course. The treatment was successful and the patient was discharged home without evidence of bronchial casts. DISCUSSION: Plastic bronchitis is a potentially devastating condition in which pulmonary infiltrates line the bronchial tree, forming casts and prohibiting effective oxygen exchange. There are few effective treatment options for this condition. The use of aerosolized t-PA for the treatment of plastic bronchitis has been reported to be safe and effective in 4 cases but no consistent regimen, dose, or duration of treatment has been established. CONCLUSIONS: t-PA can be nebulized and inhaled for successful inhibition of bronchial cast formation. More information to determine the most effective dose and duration of therapy is needed to effectively improve the lives of people with plastic bronchitis. © 1967-2013 Harvey Whitney Books Co. All rights reserved.

Sertraline exposure leads to small left heart syndrome in adult mice - Haskell, S.E.; Hermann, G.M.; Reinking, B.E.; Volk, K.A.; Peotta, V.A.; Zhu, V.; Roghair, R.D. (Pediatric Research, 2013)
Background: Sertraline, a selective serotonin reuptake inhibitor (SSRI), is the most commonly prescribed therapy for maternal depression. Epidemiologic studies have linked SSRI exposure with decreased fetal growth, altered autonomic regulation, and cardiac malformations. We hypothesized that SSRI exposure decreases left-ventricular (LV) volumes and increases adult sympathetic nervous system activation, resulting in increased adult heart rates.Methods:C57BL/6 mice received saline or sertraline (5 or 15 mg/kg/day i.p.) on postnatal days 1-14. Adult phenotypes were assessed at 5 mo.Results:Sertraline-exposed mice had smaller LV internal diameters in diastole (control 4.0 ± 0.1 mm, SSRI 3.7 ± 0.1 mm, P < 0.05), decreased stroke volumes (control 46 ± 2.6, SSRI 37 ± 2.3, P < 0.05), higher heart rates (control 530 ± 13 beats per minute (bpm), SSRI 567 ± 6 bpm, P <0.05), and increased urinary excretion of noradrenaline (control 174 ± 29.4 ng/ml, SSRI 276 ± 35.1 ng/ml, P < 0.05). These changes were associated with increased cerebral serotonin transporter (5-HTT) expression.Conclusion:Neonatal sertraline exposure causes long-term changes in cardiac morphology and physiology. We speculate that early-life SSRI exposure impairs cardiomyocyte growth and central serotonin signaling, leading to a small left heart syndrome in adult mice. Copyright © 2013 International Pediatric Research Foundation, Inc.

Pulse oximetry home monitoring in infants with single-ventricle physiology and a surgical shunt as the only source of pulmonary blood flow - Öhman, A.; Strömvall-Larsson, E.; Nilsson, B.; Mellander, M. (Cardiology in the Young, 2013)
Background Shunt occlusion is a major cause of death in children with single ventricle. We evaluated whether one daily measurement of oxygen saturation at home could detect life-threatening shunt dysfunction. Methods A total of 28 infants were included. Parents were instructed to measure saturation once daily and if less than or equal to 70% repeat the measurement. Home monitoring was defined as positive when a patient was admitted to Queen Silvia Children's Hospital because of saturation less than or equal to 70% on repeated measurement at home. A shunt complication was defined as arterial desaturation and a narrowing of the shunt that resulted in an intervention to relieve the obstruction or in death. Parents' attitude towards the method was investigated using a questionnaire. Results A shunt complication occurred out of hospital eight times in eight patients. Home monitoring was positive in five out of eight patients. In two patients, home monitoring was probably life saving; in one of them, the shunt was replaced the same day and the other had an emergency balloon dilatation of the shunt. In three out of eight patients, home monitoring was negative; one had an earlier stage II and survived, but two died suddenly at home from thrombotic shunt occlusion. On seven occasions in three patients home monitoring was positive but there was no shunt complication. The method was well accepted by the parents according to the results of the questionnaire. Conclusion Home monitoring of oxygen saturation has the potential to detect some of the life-threatening shunt obstructions between stages I and II in infants with single-ventricle physiology. © Cambridge University Press 2012.
Keywords: home monitoring; hypoplastic left heart syndrome; oxygen saturation; psychosocial aspects; Single ventricle; surgical shunt

Head and neck vessel size by angiography predicts neo-aortic arch obstruction after norwood/sano operation for hypoplastic left heart syndrome - Seckeler, M.D.; Raucci, F.J.; Saunders, C.; Gangemi, J.J.; Peeler, B.B.; Anitha Jayakumar, K. (Journal of Invasive Cardiology, 2013)
Objectives: To identify and predict neo-aortic arch obstruction (NAAO) in children after Norwood/Sano operation (NO) for hypoplastic left heart syndrome (HLHS). Background: NAAO is associated with morbidity and mortality after NO for HLHS and no objective measure has predicted the initial occurrence of NAAO. Computational flow models of aortic coarctation demonstrate increased wall shear stress (WSS) in vessels proximal to the coarctation segment, which we believe also occurs with NAAO. These vessels respond by increasing their luminal diameter to maintain normal WSS. We hypothesized that the relative increase in diameters of head and neck vessels to the isthmus, as measured by angiography, would identify hemodynamically significant NAAO and predict future NAAO. Methods: Retrospective review of patients with HLHS and at least one catheterization with aortic angiography after NO. Diameters of head and neck vessels were totaled and divided by the isthmus diameter to give a head and neck index (HNI), which was compared to coarctation index (CI) for identifying and predicting future NAAO. Results: Forty-four patients were identified, 17 with and 27 without NAAO. Receiver operator characteristic analysis using a value for CI ≤0.5 showed a sensitivity of 47% and specificity of 89%. For HNI, a value >2.65 gave a sensitivity of 77% and specificity of 93%. Three patients who developed NAAO after their initial catheterization had CI >0.5, but abnormally high HNI >2.65. Conclusions: HNI is a more robust indicator of hemodynamically significant NAAO than CI and may predict its future occurrence after NO for HLHS.

Outcomes of general anesthesia for noncardiac surgery in a series of patients with Fontan palliation - Rabbitts, J.A.; Groenewald, C.B.; Mauermann, W.J.; Barbara, D.W.; Burkhart, H.M.; Warnes, C.A.; Oliver Jr., W.C.; Flick, R.P. (Paediatric Anaesthesia, 2013)
Objectives To describe the experience of a single, tertiary care institution in the care of patients with Fontan physiology undergoing anesthesia for noncardiac surgery. Background The Fontan procedure was developed in 1971 to palliate patients with univentricular cardiac physiology leading to long-term survival of these patients, who may now present as adults for noncardiac surgery. Methods We retrospectively reviewed the medical records of Fontan patients 16 years and older who underwent general anesthesia for noncardiac surgery at Mayo Clinic in Rochester, Minnesota. Preoperative data, perioperative course, intraoperative and postoperative hemodynamic, pulmonary, cardiovascular, and renal complications were described. Results Thirty-nine general anesthetics were administered to 31 patients for noncardiac surgery after Fontan palliation. Perioperative complications occurred in 12 of the 39 (31%) noncardiac surgeries, and there was one postoperative death that occurred on day 13 after ventral hernia repair. The two patients who had complications that did not resolve (long-term dialysis and death) had ejection fractions well below the mean for the group (22% and 28%). Conclusion It may be more appropriate for Fontan patients to undergo anesthesia for noncardiac surgery in a tertiary institution, particularly patients with an ejection fraction of <30%. Intraoperative arterial blood pressure monitoring and overnight admission are likely appropriate for most cases. © 2012 Blackwell Publishing Ltd.
Keywords: congenital heart disease; single ventricle; univentricular

Large eddy simulation of powered Fontan hemodynamics - Delorme, Y.; Anupindi, K.; Kerlo, A.E.; Shetty, D.; Rodefeld, M.; Chen, J.; Frankel, S. (Journal of Biomechanics, 2013)
Children born with univentricular heart disease typically must undergo three open heart surgeries within the first 2-3 years of life to eventually establish the Fontan circulation. In that case the single working ventricle pumps oxygenated blood to the body and blood returns to the lungs flowing passively through the Total Cavopulmonary Connection (TCPC) rather than being actively pumped by a subpulmonary ventricle. The TCPC is a direct surgical connection between the superior and inferior vena cava and the left and right pulmonary arteries. We have postulated that a mechanical pump inserted into this circulation providing a 3-5 mmHg pressure augmentation will reestablish bi-ventricular physiology serving as a bridge-to-recovery, bridge-to-transplant or destination therapy as a "biventricular Fontan" circulation. The Viscous Impeller Pump (VIP) has been proposed by our group as such an assist device. It is situated in the center of the 4-way TCPC intersection and spins pulling blood from the vena cavae and pushing it into the pulmonary arteries. We hypothesized that Large Eddy Simulation (LES) using high-order numerical methods are needed to capture unsteady powered and unpowered Fontan hemodynamics. Inclusion of a mechanical pump into the CFD further complicates matters due to the need to account for rotating machinery. In this study, we focus on predictions from an in-house high-order LES code (WenoHemoTM) for unpowered and VIP-powered idealized TCPC hemodynamics with quantitative comparisons to Stereoscopic Particle Imaging Velocimetry (SPIV) measurements. Results are presented for both instantaneous flow structures and statistical data. Simulations show good qualitative and quantitative agreement with measured data. © 2012 Elsevier Ltd.
Keywords: Fontan circulation; High order large eddy simulation; Viscous impeller pump

Closure of a tracheocutaneous fistula by two hinged turnover skin flaps and a muscle flap: A case report - Tatekawa, Y.; Yamanaka, H.; Hasegawa, T. (International Journal of Surgery Case Reports, 2013)
INTRODUCTION: Tracheocutaneous fistula is a complication of tracheostomy. Tracheocutaneous fistulectomy followed by primary closure carries a high possibility of complications. PRESENTATION OF CASE: An 11-year-old boy underwent surgery to repair a tracheocutaneous fistula, using skin and muscle flaps. A vertical incision was made around the fistula and 3 skin flaps were prepared: 2 hinge flaps, and 1 to cover the skin defect (advanced flap). The 2 hinged turnover flaps were invaginated by multiple layered sutures, and a strap muscle flap was placed over the resulting tracheal closure. An advanced skin flap was used to cover the area of the previous defect. The patient was extubated immediately after surgery. He was discharged on the sixth postoperative day without tracheal leakage or subcutaneous emphysema. The patient is currently doing well, with no respiratory symptoms and no recurrence at the postoperative 5 months. DISCUSSION: Our technique is minimally invasive and has a low risk of lumen stenosis, other complications, or recurrence. CONCLUSION: This technique demonstrates the multiple-layered closure of a tracheocutaneous fistula, using skin flaps and a muscle flap. © 2012 Surgical Associates Ltd.
Keywords: Hinge flap; Muscle flap; Tracheocutaneous fistula

Quality of life 4 years after complex heart surgery in infancy - Garcia Guerra, G.; Robertson, C.M.T.; Alton, G.Y.; Joffe, A.R.; Dinu, I.A.; Nicholas, D.; Ross, D.B.; Rebeyka, I.M. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Objective: To determine the health-related quality of life at 4 years of age in children who had undergone cardiac surgery for congenital heart disease in early infancy. Methods: A prospective cohort study of infants undergoing cardiac surgery at 6 weeks of age or younger from July 2000 to June 2005 at the Stollery Children's Hospital. The quality of life was assessed using the Pediatric Quality of Life Inventory, version 4.0, generic core scales, and compared with normative values for the same age. The association between the perioperative variables and health-related quality of life was explored. Results: A total of 242 infants underwent complex heart surgery during the study period. Of the 166 eligible survivors, 130 were included. No significant differences were present between the children with single ventricle versus biventricular repairs, except for lower physical health summary scores in the single ventricle patients (P = .007). Compared with the normative data, the children with biventricular repair had lower total Pediatric Quality of Life Inventory, version 4.0, scores (P = .001) and psychosocial health summary scores (P < .001). The children with single ventricle repair also had lower physical health summary scores (P = .003). Older age at surgery and markers of postoperative low cardiac output syndrome were associated with worse health-related quality of life, and greater socioeconomic status was associated with better quality of life. Conclusions: At 4 years of age, health-related quality of life was significantly lower in children who had undergone surgery for congenital heart disease in early infancy. An association was found between age at surgery and postoperative low cardiac output and socioeconomic status and quality of life. Copyright © 2013 by The American Association for Thoracic Surgery.

Editorial - Gournay, V.; Guérin, P. (Archives of Cardiovascular Diseases, 2013)

Anxiety, depressive and somatic symptoms in adults with congenital heart disease - Eslami, B.; Sundin, T.; Macassa, G.; Khankeh, H.R.; Soares, J.J.F. (Journal of Psychosomatic Research, 2013)
Objective: Despite the improvement in life-expectancy of adults with congenital heart disease, they may experience unique medical and social challenges that could impact on their psychological functioning. The aims of this study were to address the experience of anxiety, depressive and somatic symptoms among adults with congenital heart disease in comparison with that of non-heart diseased persons considering the role of various factors (e.g. socio-economic). Methods: In cross-sectional case-control study, the participants consisted of 347 patients with congenital heart disease (18-64. years, 52.2% female) and 353 matched (by sex/age) non-heart diseased persons. The participants completed a questionnaire. The data were analyzed with bivariate and multivariate methods. Results: In bivariate analyses, scores in anxiety and somatic symptoms were higher among patients than the healthy controls (both at p≤ 0.001), whereas the groups did not differ in depressive symptoms. Following multiple-linear-regression-analyses, only the association between congenital heart disease and somatic symptoms was confirmed. Among the patients, perceived financial strain was significantly related to anxiety, depressive and somatic symptoms; lower perceived social support to anxiety and depression; and low annual income to somatic symptoms. Additionally, somatic symptoms were associated with anxiety and depressive symptoms, and vice versa. And no medical variables were related to anxiety, depressive and somatic symptoms. Conclusions: Congenital heart disease was only independently associated with somatic symptoms. Financial strain, social support and co-existence of emotional distress with somatic symptoms should be considered in developing appropriate interventions to improve the well-being of patients with congenital heart disease. However, longitudinal research is warranted to clarify causality. © 2012 Elsevier Inc..
Keywords: Congenital heart disease; Grown-up; Mental health; Psychosomatic; Social functioning

Performance evaluation of a pediatric viscous impeller pump for Fontan cavopulmonary assist - Giridharan, G.A.; Koenig, S.C.; Kennington, J.; Sobieski, M.A.; Chen, J.; Frankel, S.H.; Rodefeld, M.D. (Journal of Thoracic and Cardiovascular Surgery, 2013)
Objective: The anatomic and physiologic constraints for pediatric cavopulmonary assist differ markedly from adult Fontan circulations owing to smaller vessel sizes and risk of elevated pulmonary resistance. In this study, hemodynamic and hemolysis performance of a catheter-based viscous impeller pump (VIP) to power the Fontan circulation is assessed at a pediatric scale (∼15 kg) and performance range (0-30 mm Hg). Methods: Computer simulation and mock circulation studies were conducted to assess the hydraulic performance, acute hemodynamic response to different levels VIP support, and the potential for vena caval collapse. Computational fluid dynamics simulations were used to estimate VIP hydraulic performance, shear rates, and potential for hemolysis. Hemolysis was quantified in a mock loop with fresh bovine blood. Results: A VIP augmented 4-way total cavopulmonary connection flow at pediatric scales and restored systemic pressures and flows to biventricular values, without causing flow obstruction or suction. VIP generated flows up to 4.1 L/min and pressure heads of up to 38 mm Hg at 11,000 rpm. Maximal shear rate was 160 Pa, predicting low hemolysis risk. Observed hemolysis was low with plasma free hemoglobin of 11.4 mg·dL-1·h-1. Conclusions: A VIP will augment Fontan cavopulmonary flow in the proper pressure and flow ranges, with low hemolysis risk under more stringent pediatric scale and physiology compared with adult scale. This technology may be developed to simultaneously reduce systemic venous pressure and improve cardiac output after stage 2 or 3 Fontan repair. It may serve to compress surgical staging, lessening the pathophysiologic burden of repair. Copyright © 2013 by The American Association for Thoracic Surgery.

The continuing importance of how neonates die - Verhagen, A.A.E.; Janvier, A. (JAMA Pediatrics, 2013)

Maternal race/ethnicity and survival experience of children with congenital heart disease - Wang, Y.; Liu, G.; Druschel, C.M.; Kirby, R.S. (Journal of Pediatrics, 2013)
Objective To investigate the existence of racial/ethnic disparity in mortality risk among children with individual congenital heart defects and identify any other risk factors. Study design The study cohort, comprising children born between 1983 and 2006 with a selected congenital heart defect, was matched to death records to ascertain vital status. The birth and maternal risk factors were obtained from birth certificates. Results After adjusting for covariates using a multivariate regression model, the risk of mortality was significantly higher in children of non-Hispanic black mothers with transposition of the great arteries (hazard ratio (HR), 1.31; 95% CI, 1.07-1.60), tetralogy of Fallot (HR, 1.34; 95% CI, 1.06-1.69), and coarctation of the aorta (HR, 1.40; 95% CI, 1.10-1.79), compared with children of non-Hispanic white mothers. Time trends analysis examining the mortality risk by survival age and birth period found a significant decrease in 5-year mortality risk from 1983 to 2003 births, with a nearly 50% reduction for hypoplastic left heart syndrome and coarctation of the aorta across 3 maternal racial/ethnic groups examined. Conclusion Our findings may help identify at-risk populations and mortality risk factors and thereby contribute to improved survival and quality of life for these children across the lifespan. © 2013 Mosby Inc. All rights reserved.

Capture of complexity of specialty care in pediatric cardiology by work RVU measures - Bergersen, L.; Gauvreau, K.; McElhinney, D.; Fenwick, S.; Kirshner, D.; Harding, J.; Hickey, P.; Mayer, J.; Marshall, A. (Pediatrics, 2013)
OBJECTIVE: We sought to determine the relationship between relative value units (RVUs) and intended measures of work in catheterization for congenital heart disease. METHODS: RVU was determined by matching RVU values to Current Procedural Terminology codes generated for cases performed at a single institution. Differences in median case duration, radiation exposure, adverse events, and RVU values by risk category and cases were assessed. Interventional case types were ranked from lowest to highest median RVU value, and correlations with case duration, radiation dose, and a cases-predicted probability of an adverse event were quantified with the Spearman rank correlation coefficient. RESULTS: Between January 2008 and December 2010, 3557 of 4011 cases were identified with an RVU and risk category designation, of which 2982 were assigned a case type. Median RVU values, radiation dose, and case duration increased with procedure risk category. Although all diagnostic cases had similar RVU values (median 10), adverse event rates ranged from 6% to 21% by age group (P , .001). Median RVU values ranged from 9 to 54 with the lowest in diagnostic and biopsy cases and increasing with isolated and then multiple interventions. Among interventional cases, no correlation existed between ranked RVU value and case duration, radiation dose, or adverse event probability (P = .13, P = .62, and P = .43, respectively). CONCLUSIONS: Time, skill, and stress inherent to performing catheterization procedures for congenital heart disease are not captured by measurement of RVU alone. Copyright © 2013 by the American Academy of Pediatrics.
Keywords: Catheterization; Congenital heart disease; Outcomes; RVU

Novel Fenestration Designs for Controlled Venous Flow Shunting in Failing Fontans With Systemic Venous Hypertension - Albal, P.G.; Menon, P.G.; Kowalski, W.; Undar, A.; Turkoz, R.; Pekkan, K. (Artificial Organs, 2013)
The Fontan procedure is employed as the final-stage palliation in single-ventricle congenital heart patients and results in diversion of venous blood directly to the pulmonary arteries. Fontan patients have been known to suffer from postoperative systemic venous hypertension, which in turn is associated with pleural effusions and protein losing enteropathy, leading to a decreased duration and quality of life. Despite the ongoing debate on its benefits, a circular fenestration hole (typically 4mm) establishing a venous shunt to the common atrium is traditionally employed to relieve venous pressure in the Fontan conduit and improve early postoperative Fontan hemodynamics. However, these improvements come at the cost of reduced oxygen saturation due to excessive right-to-left shunting if the fenestration is permanent. The ideal "selective" fenestration would therefore limit or eliminate shunt flow at tolerable systemic venous pressures and allow increased flow at high pressures. The objective of this study is to introduce new fenestration designs that exhibit these desirable pressure-flow characteristics. Novel plus-shaped and S-shaped fenestration designs with leaflets are introduced as alternatives to the traditional circular fenestration, each having identical effective orifice areas at the fully open states. In vitro steady leakage flow tests were performed for physiological flow-driving pressures in order to obtain pressure-drop versus flow-rate characteristics. In addition, the leaflet opening kinematics of the plus-shaped fenestration was investigated computationally using finite element simulation. Fluid-structure interaction analysis was performed to determine leaflet displacements and pressure-flow characteristics at low pressures. Further, a lumped parameter model of the single-ventricle circuit was created to simulate pulsatile flow conditions For the plus-shaped fenestration, the flow rate was found to increase nonlinearly with increased driving systemic venous pressures at high physiological-pressure drops which did not cause the leaflets to fully open, and linearly for low driving pressures. These results indicate that leaflets of the plus-shaped fenestration design activated passively after a critical systemic venous pressure threshold. This feature is ideal for minimizing undesirable excessive venous shunting. A large variability in shunting flow rate may be obtained by changing the shape, thickness, size, and material of the fenestration to suit requirements of the patient, which can further limit shunt flow in a controlled manner. © 2013, The Authors. Artificial Organs © 2013, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Fenestration; Fontan surgery; Systemic venous hypertension; Venous flow shunting

Self-reported health status (EQ-5D) in adults with congenital heart disease - Berghammer, M.; Karlsson, J.; Ekman, I.; Eriksson, P.; Dellborg, M. (International Journal of Cardiology, 2013)
Purpose: Today, more patients with congenital heart disease (CHD) reach adulthood. There are conflicting findings concerning the relationship between quality of life (QoL) or health state for adults with CHD and the complexity of their CHD. The aim of the study was, firstly, to compare the reported health status and health perception of adult patients with CHD and, secondly, to investigate what variables influenced the patients' health status and health perception. Methods: Data from 1435 patients completing the EQ-5D questionnaire, which includes reported health status and health perception, were analyzed. Results: Valid EQ-5D data were reported by 1274 patients, showing overall results indicating a good health status. Problems were most frequently reported in the dimension "pain/discomfort" (31.9%) and "anxiety/ depression" (29.8%). Higher occurrence of problems were reported by patients with complex disease i.e. single ventricle (p < 0.001) and by female patients (p < 0.0001). Symptomatic patients reported a lower health status (p < 0.0001) and a lower perceived health on EQ-VAS (p < 0.0001). Of the asymptomatic patients, 20.5% nevertheless reported problems in "pain/discomfort" and 22.2% in the "anxiety/depression" dimension. Conclusion: The health status of adults with CHD is influenced by symptoms, NYHA-classification, age and gender. Adults with CHD report a lower occurrence of problems in comparison to previously published results from a general population, but the importance of actively asking about the patient's experience is demonstrated by the high degree of asymptomatic patients reporting problems on EQ-5D. © 2011 Elsevier Ireland Ltd.
Keywords: Adult congenital heart disease (ACHD); EQ-5D; Health state; Self-reported health status

A near lethal case of plastic bronchitis following truncal valve replacement - Lang, K.; Champion, E.; Cosper, G.; Peeler, B.; Maxey, T. (Journal of Pediatric Intensive Care, 2013)
Plastic bronchitis is a condition in which large, rubber-like, bronchial casts develop in the tracheobronchial tree causing airway obstruction. It is an unusual disorder that occurs in various disease states. Most case reports of plastic bronchitis associated with congenital heart disease are in patients palliated with Fontan physiology. We describe a 13-year-old girl with DiGeorge syndrome and truncus arteriosus who underwent an uneventful truncal valve replacement. The child developed plastic bronchitis on postoperative day eight requiring extra-corporeal membrane oxygenation support and daily bronchoscopy to remove bronchial casts. Our patient did not have elevated systemic venous pressures or Fontan physiology. We speculate the etiology of plastic bronchitis may have been surgical trauma to the lymphatic channels surrounding the bronchi and disruption of pleural adhesions. A comprehensive evaluation revealed no specific cause and the diagnosis of idiopathic plastic bronchitis was made. © 2013 - IOS Press and the authors. © 2012 - IOS Press and the authors.
Keywords: Bronchial casts; Congenital heart disease; Plastic bronchitis; Truncal valve replacement; Truncus arteriosus

Evaluation of Silent Thrombus after the Fontan Operation - Grewal, J.; Al Hussein, M.; Feldstein, J.; Kiess, M.; Ellis, J.; Human, D.; Leipsic, J. (Congenital Heart Disease, 2013)
Background: Thromboembolic complications have been noted after the Fontan operation. However, the prevalence of silent events among an adult contemporary population is not known. Noninvasive screening by any method including computed tomography (CT) has been technically limited to date. Objectives: The objective of this study was to evaluate a novel dual-energy CT (DECT) protocol in determining the prevalence of "silent" intracardiac thrombus and thrombus in the Fontan and pulmonary circulations among adults after the Fontan operation. Methods: All post-Fontan patients attending the Pacific Adult Congenital Heart Clinic were approached for study participation. Those agreeable underwent a full clinical assessment, cardiopulmonary stress testing, transthoracic echocardiogram, and DECT low kilovoltage imaging protocol. Results: Twenty-three patients were included in the study (30 ± 10 years, 26% women). Three (13%) patients had evidence of silent thrombi detected on DECT. All three of these patients had an extracardiac conduit and mural thrombus was found within the conduit. Older age at the time of the Fontan operation was associated with the presence of thrombus (21 ± 14 vs. 11 ± 6 years, P =.05). Conclusions: Thirteen percent of adult patients post-Fontan procedure have clinically silent thrombi. These were all found among patients with an extracardiac conduit traditionally thought to be at low risk for thromboembolism. Given the significant risk of thromboembolic complications, large randomized prospective studies looking at anticoagulation therapy in all Fontan patients are urgently needed. In the meanwhile, given the important rate of silent thrombi, a systematic robust screening protocol that includes noninvasive low radiation methods such as DECT methods should be considered. © 2012 Wiley Periodicals, Inc.
Keywords: Cardiac; CT; Embolism; Fontan; Pulmonary artery; Thrombus

Natural and modified history of single-ventricle physiology in adult patients - Angeli, E.; Pace napoleone, C.; Balducci, A.; Formigari, R.; Lovato, L.; Candini, L.; Oppido, G.; Gargiulo, G. (European Journal of Cardio-thoracic Surgery, 2012)
Objective: To define the evolution of the single-ventricle (SV) heart in adult patients in terms of morbidity, mortality and quality of life. Methods: Sixty-two patients with SV physiology and aged older than 16 years were retrospectively reviewed. Three patients (5%) were in natural history, one had received a Blalock-Taussig shunt, one a Waterstone anastomosis, one a pulmonary artery banding, three a bidirectional cavopulmonary anastomosis, eight a classic Fontan procedure and 46 a total cavopulmonary connection (TCPC). The morphology of the SV was left in 48 patients (77%), right in nine (14%) and indeterminable in five (8%). Thirty-three patients underwent magnetic resonance imaging (MRI) to assess ventricular mass (VM), ventricular systolic function, pulmonary artery branch diameter and potential thrombosis of the conduit. Cardiopulmonary exercise testing (CPTE) was carried out to evaluate exercise tolerance. The quality of life was monitored with two different specific tests, the Short Form-36 (SF-36) and the congenital heart disease-TNO/AZL adult quality of life (CHD-TAAQOL). The mean follow-up time was 8.0 ± 9.1 years. Results: Two of the three patients in natural history underwent primary TCPC. Re-interventions were necessary in seven patients (11%). Three patients (5%) died during follow-up. Five patients (8%) underwent cardiac transplantation. Protein losing enteropathy appeared in six (10%), while the arrhythmic disorder was detected in 13 patients. On the MRI, the mean end-diastolic ventricular volume was 106 ± 448 ml/m. 2, the mean ejection fraction (EF) was 52.3 ± 10% and VM was 56 ± 22.1 g/m. 2. On CPTE, the peak of oxygen uptake (peak VO. 2) was moderately impaired in 92% of patients, while 4% presented a severely impaired and 4% a normal peak of VO. 2. No correlations were found among the peak of VO. 2 and the quality-of-life evaluation. Conclusions: Adult patients with SV are at high risk of reoperations and need of transplant and complications. Nevertheless, in the presence of a moderately reduced peak of VO. 2 and a moderate reduction in the EF detected at the MRI, the results of the evaluation of daily quality of life are incredibly high. © The Author 2012. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Cardiopulmonary exercise test; Fontan operation; Quality of life; Single-ventricle physiology

Outcome of extremely preterm infants (<1,000 g) with congenital heart defects from the national institute of child health and human development neonatal research network - Pappas, A.; Shankaran, S.; Hansen, N.I.; Bell, E.F.; Stoll, B.J.; Laptook, A.R.; Walsh, M.C.; Das, A.; Bara, R.; Hale, E.C.; Newman, N.S.; Boghossian, N.S.; et al. (Pediatric Cardiology, 2012)
Little is known about the outcomes of extremely low birth weight (ELBW) preterm infants with congenital heart defects (CHDs). The aim of this study was to assess the mortality, morbidity, and early childhood outcomes of ELBW infants with isolated CHD compared with infants with no congenital defects. Participants were 401-1,000 g infants cared for at National Institute of Child Health and Human Development Neonatal Research Network centers between January 1, 1998, and December 31, 2005. Neonatal morbidities and 18-22 months' corrected age outcomes were assessed. Neurodevelopmental impairment (NDI) was defined as moderate to severe cerebral palsy, Bayley II mental or psychomotor developmental index <70, bilateral blindness, or hearing impairment requiring aids. Poisson regression models were used to estimate relative risks for outcomes while adjusting for gestational age, small-for-gestational-age status, and other variables. Of 14,457 ELBW infants, 110 (0.8 %) had isolated CHD, and 13,887 (96 %) had no major birth defect. The most common CHD were septal defects, tetralogy of Fallot, pulmonary valve stenosis, and coarctation of the aorta. Infants with CHD experienced increased mortality (48 % compared with 35 % for infants with no birth defect) and poorer growth. Surprisingly, the adjusted risks of other short-term neonatal morbidities associated with prematurity were not significantly different. Fifty-seven (52 %) infants with CHD survived to 18-22 months' corrected age, and 49 (86 %) infants completed follow-up. A higher proportion of surviving infants with CHD were impaired compared with those without birth defects (57 vs. 38 %, p = 0.004). Risk of death or NDI was greater for ELBW infants with CHD, although 20 % of infants survived without NDI. © 2012 Springer Science+Business Media, LLC.
Keywords: Congenital heart defects; Extremely low birth weight; Neurodevelopmental follow-up

Quality of life, health status, and depression: Comparison between adolescents and adults after the fontan procedure with healthy counterparts - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Eastwood, J.-A.; Lewis, A.B.; Child, J.S. (Journal of Cardiovascular Nursing, 2012)
BACKGROUND: Quality of life (QOL) in adolescents and adults who have undergone the Fontan procedure and are living with only 1 ventricle is presumed to be diminished. OBJECTIVES: This study aimed to compare QOL, health status, and prevalence of depression in adolescents/adults after the Fontan procedure with healthy counterparts and to identify predictors of QOL in the Fontan group. METHODS: Using a comparative, cross-sectional design, 54 adolescents and adults with single ventricle congenital heart disease who have undergone the Fontan procedure were compared with 66 age-matched healthy counterparts. Quality of life, health status, depression, and social support were measured using the Satisfaction With Life Scale, Short Form Survey Version 2, Patient Health Questionnaire Depression Module, and Multidimensional Scale of Perceived Social Support. Clinical variables were abstracted from medical records. Predictors of QOL were determined using multiple linear regression. RESULTS: Adolescents and adults in the Fontan group reported lower physical health status (mean [SD] = 46.5 [9.3] vs mean [SD] = 55.9 [5.1], P < .001) and were more depressed (mean [SD] = 7.3 [5.9] vs mean [SD] = 4.5 [4.3], P < .004) than their healthy counterparts. There were no differences in QOL, mental health status, or social support between the 2 groups. Functional status (New York Heart Association class), depression, and social support accounted for 55% of the variance in QOL in the Fontan group. CONCLUSIONS: Despite lower levels of physical health, the QOL of Fontan patients was comparable with that of their healthy counterparts; this finding contradicts previous proxy reports, self-reports, and assumptions that QOL is lower in patients with complex single ventricle congenital heart disease. However, because Fontan patients were more depressed than their healthy counterparts, the need for early screening and detection is warranted. Copyright © 2012 Lippincott Williams & Wilkins. Unauthorized reproduction of this article is prohibited.
Keywords: depression; Fontan; health status; quality of life; single ventricle congenital heart disease

Steady Flow Analysis of Mechanical Cavopulmonary Assistance in MRI-Derived Patient-Specific Fontan Configurations - Downs, E.A.; Moskowitz, W.B.; Throckmorton, A.L. (Artificial Organs, 2012)
This numerical study examined the performance of an intravascular axial flow blood pump for mechanical hemodynamic support of patients in the setting of Fontan failure, which presently has few treatment options. Three anatomically accurate geometries of the total cavopulmonary connection (TCPC) were generated using patients' magnetic resonance imaging data. These patient-specific geometries, as well as an idealized version with cylindrical vessels, were computationally analyzed with and without a pump in the inferior vena cava. Pressure flow characteristics, energy gain calculations, and blood damage analyses were performed for each model. The pump produced pressures of 1-14mmHg for 1500-4000 revolutions per minute, flow rates of 1-4L/min, and pulmonary artery pressures of 8-24mmHg. Comparison of pump performance among the four models showed minimal intermodel differences (<5% deviation) in the pressure rise generated by the pump, the IVC pressure, and the energy imparted to the system by the pump. Blood damage analysis showed maximum fluid scalar stress values of 372Pa or less, and the blood damage index was less than 2% in all of the models. These results suggest that this axial flow blood pump performs consistently in a variety of TCPC vessel geometries with low risk of blood trauma. © 2012, Copyright the Authors. Artificial Organs. © 2012, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Artificial right ventricle; Blood pump; Cavopulmonary assist device; Computational fluid dynamics (CFD); Fontan physiology; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Total cavopulmonary connection

Explanatory Value of the Ability Index as Assessed by Cardiologists and Patients with Congenital Heart Disease - Overgaard, D.; Schrader, A.-M.; Lisby, K.H.; King, C.; Christensen, R.F.; Jensen, H.F.; Moons, P. (Congenital Heart Disease, 2012)
Introduction. The Ability Index was developed to classify patients with congenital heart disease into four functional classes. Functional class is typically determined by the cardiologist, based on data from a clinical interview. The validity of the Ability Index as assessed by the patient has never been scrutinized. Objective. We tested the agreement between cardiologists and patients in assessing functional status using the Ability Index and compared the accuracy of the two assessments in explaining patient-reported outcomes (PRO). Methods. The Ability Index Scale was completed for 57 patients, independently by cardiologists and patients. Cohen's Kappa coefficient with quadratic weighting (Kw) was calculated. The area under the receiver operating characteristic (ROC) curve (AUC) (=C-index) was used to test the accuracy of the Ability Index in explaining PRO, as assessed by the cardiologist or the patient. Results. Agreement was observed in 61.4% of the patients. The Kw was 0.55, showing a moderate agreement; and the R2 was 0.29, displaying a limited shared variance. The AUC for cardiologists' assessments of the Ability Index in explaining PRO was consistently lower than the AUC for patients' assessments. The appraisal of the patients was more accurate. Discussion. When cardiologists and patients are assessing functional status using the Ability Index, two different constructs are measured. These assessments cannot be interchanged, but should be used complementarily. Because the assessment of the patients regarding the Ability Index is more precise in terms of explaining PRO, it could be valuable as a simple crude marker to identify patients at risk for poor functional and psychosocial outcomes. © 2012 Wiley Periodicals, Inc.
Keywords: Ability index; Congenital heart disease; Functional status; Patient-Reported Outcomes (PRO); Single Ventricle Physiology (SVP)

Physician counseling, informed consent and parental decision making for infants with hypoplastic left-heart syndrome - Paris, J.J.; Moore, M.P.; Schreiber, M.D. (Journal of Perinatology, 2012)
Until the development in 1980 by William Norwood of a staged palliative surgical procedure for hypoplastic left heart syndrome (HPLHS), there was no treatment for that condition. With medical developments in the 1980s, parents had the option of the Norwood procedure, transplantation or comfort care for a child born with HPLHS. With an improvement in the survival rate for the Norwood procedure from an initial 30% to now better than 80%, some physicians believe that comfort care should no longer be an option. If, however, medically sophisticated parents, who know the neurological and motor skills impairments that accompany HPLHS, object to the surgery, they are allowed to opt for comfort care. This two-pronged approach to medical treatment seems to violate the norms on equity and fairness in the care of the patient. Parents need to be informed about long-term neurological and motor skill development as well as survival rates to give informed consent. © 2012 Nature America, Inc. All rights reserved.
Keywords: hypoplastic left heart syndrome; informed consent; parental decision making; physician counseling

50 Years Ago in The Journal of Pediatrics: Growth Disturbance in Congenital Heart Disease - Gidding, S.S. (Journal of Pediatrics, 2012)

Risk factors for neurodevelopmental impairments in school-age children after cardiac surgery with full-flow cardiopulmonary bypass - Von Rhein, M.; Dimitropoulos, A.; Valsangiacomo Buechel, E.R.; Landolt, M.A.; Latal, B. (Journal of Thoracic and Cardiovascular Surgery, 2012)
Objective: To determine the risk factors for adverse neurodevelopmental outcomes in school-age children after full flow open-heart surgery for congenital heart disease. Methods: The outcome was assessed in 117 children without a genetic comorbidity at a mean age of 10.4 ± 2.5 years. Intelligence was assessed using the Raven's Progressive Matrices and neuromotor function using the Zurich Neuromotor Assessment. Risk factors were retrieved from detailed chart review. Results: The mean intelligence score was 89 ± 16, significantly lower than the norm (P < .001). Cerebral palsy was diagnosed in 10% of patients. Poor neuromotor performance (less than p10) was present in 15% to 20% of the children, depending on the motor task (all P < .001). Pure motor and static balance performance was also significantly impaired when patients with cerebral palsy were excluded (P < .01). Intelligence was only related to socioeconomic status (P = .006), and neuromotor outcome was related to the length of hospital stay and postoperative neurologic abnormalities (P < .03). The extracorporeal circulation time was related to adaptive fine motor performance (P = .05). All other variables were not related to outcome. Conclusions: Children without a genetic comorbidity are at risk of long-term intellectual and motor impairments also after full-flow cardiac repair. Surgery-related parameters play a less important role for adverse outcomes than postoperative complications. Our findings stress the importance of specialized follow-up assessments for all children with CHD undergoing open heart surgery. Copyright © 2012 by The American Association for Thoracic Surgery.

Uniquely shaped cardiovascular stents enhance the pressure generation of intravascular blood pumps - Throckmorton, A.L.; Carr, J.P.; Moskowitz, W.B.; Gangemi, J.J.; Haggerty, C.M.; Yoganathan, A.P. (Journal of Thoracic and Cardiovascular Surgery, 2012)
Objective: Advances in the geometric design of blood-contacting components are critically important as the use of minimally invasive, intravascular blood pumps becomes more pervasive in the treatment of adult and pediatric patients with congestive heart failure. The present study reports on the evaluation of uniquely shaped filaments and diffuser blades in the development of a protective stent for an intravascular cavopulmonary assist device for patients with a single ventricle. Methods: We performed numeric modeling, hydraulic testing of 11 stents with an axial flow blood pump, and blood bag experiments (n = 6) of the top-performing stent geometries to measure the levels of hemolysis. A direct comparison using statistical analyses, including regression analysis and analysis of variance, was completed. Results: The stent geometry with straight filaments and diffuser blades that extended to the vessel wall outperformed all other stent configurations. The pump with this particular stent was able to generate pressures of 2 to 32 mm Hg for flow rates of 0.5 to 4 L/min at 5000 to 7000 RPM. A comparison of the experimental performance data to the numeric predictions demonstrated an excellent agreement within 16%. The addition of diffuser blades to the stent reduced the flow vorticity at the pump outlet. The average and maximum normalized index of hemolysis level was 0.0056 g/100 L and 0.0064 g/100 L, respectively. Conclusions: The specialized design of the stents, which protect the vessel wall from the rotating components of the pump, proved to be advantageous by further augmenting the pressure generation of the pump, reducing the flow vorticity at the pump outlet, and enhancing flow control. Copyright © 2012 by The American Association for Thoracic Surgery.

B-type natriuretic peptide at the early stage of univentricular circulation reflects inadequate adaptation to volume overload - Inuzuka, R.; Tatebe, S.; Wakiguchi, S.; Nakajima, H.; Ohtsu, H.; Dimopoulos, K.; Aotsuka, H. (International Journal of Cardiology, 2012)
Background: Recent studies showed that children with univentricular heart have elevated plasma B-type natriuretic peptide (BNP) levels prior to bidirectional cavopulmonary anastomosis (BDCPA). However, it remains to be established whether BNP levels reflect the degree of hemodynamic overload and relate to long-term outcome in univentricular circulation. Methods: Fifty one consecutive children with functionally univentricular heart prior to BDCPA were studied. All patients underwent cardiac catheterization and BNP measurement. Ventricular end-systolic wall stress (ESWS) and end-diastolic wall stress (EDWS) were calculated from cardiac catheterization data. Results: Median age was 1.1 years and 34% were female. Median BNP concentration was 90.4 pg/ml. Patients with high BNP (≥ 100 pg/ml) had higher pulmonary to systemic flow ratio (p = 0.014), a greater end-diastolic volume (p = 0.009), more severe atrioventricular valve regurgitation (p = 0.02) and lower ventricular mass to end-diastolic volume ratio (p = 0.006). BNP levels strongly related to EDWS (r = 0.75, p < 0.0001) and ESWS (r = 0.63, p < 0.0001). During median follow-up period of 3.2 years, 15 patients died and one underwent heart transplantation for refractory heart failure. On multivariate Cox regression analysis, high BNP concentration was an independent predictor of death or transplantation (HR 3.05, CI: 1.06-8.83, p = 0.04). Conclusions: High BNP concentration at the first palliative stage towards Fontan circulation reflects high wall stress due to high volume load and insufficient ventricular hypertrophy. Moreover, high BNP levels at this stage were independently related to long-term outcome. BNP may be used as a guide to identify patients with high workload due to inadequate adaptation to hemodynamic load, who are at high risk. © 2011 Elsevier Ireland Ltd.
Keywords: Congenital; Heart defect; Heart failure; Hemodynamics; Natriuretic peptide; Stress

Twisted cardiovascular cages for intravascular axial flow blood pumps to support the Fontan physiology - Throckmorton, A.L.; Downs, E.A.; Hazelwood, J.A.; Monroe, J.O.; Chopski, S.G. (International Journal of Artificial Organs, 2012)
Failing single ventricle physiology represents an ongoing challenge in mechanical assist device development, requiring pressure augmentation in the cavopulmonary circuit, reduction of systemic venous pressure, and increased cardiac output to achieve hemodynamic stabilization. To meet these requirements, we are developing a percutaneously-placed, axial flow blood pump to support ailing single ventricle physiology in adolescents and adults. We have modified the outer cage of the device to serve as both a protective and functional design component. This study examined the performance of 3 cage geometries with varying directions of filament twist using numerical simulations and hydraulic experiments. All 3 cage and pump models performed in acceptable ranges to support Fontan patients. The cage design employing filaments that are twisted in the opposite direction to the impeller blades and in the direction of the diffuser blades (against-with) demonstrated superior performance by generating a pressure rise range of 5-38 mm Hg of flow rates of 0.5-6 l/min at rotational speeds of 5000-7000 rpm. The blood damage indices for all of the cages were found to be well below 2%, and the scalar stress levels were below 200 Pa. This study represents ongoing progress in the development of the impeller and cage assembly. Validation of the results will continue in experiments with blood bag evaluation as well as by particle image velocimetry measurements. © 2012 Wichtig Editore.
Keywords: Artificial heart pump; Axial flow blood pump; Cardiovascular stent; Mechanical circulatory support; Rotary blood pump

Quality of life of pediatric cardiac patients who previously required extracorporeal membrane oxygenation - Costello, J.M.; O'Brien, M.; Wypij, D.; Shubert, J.; Salvin, J.W.; Newburger, J.W.; Laussen, P.C.; Arnold, J.H.; Fynn-Thompson, F.; Thiagarajan, R.R. (Pediatric Critical Care Medicine, 2012)
OBJECTIVES: We sought to assess quality of life of pediatric cardiac extracorporeal membrane oxygenation survivors. We hypothesized that these patients would have decreased quality of life when compared to that of a general U.S. population sample. DESIGN: Cross-sectional study. SETTING: Patient homes and Children's Hospital Boston. PATIENTS: Cardiac extracorporeal membrane oxygenation survivors currently 5-18 yrs old. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Quality of life was assessed by parent proxy report using the Child Health Questionnaire Parent Form 50 and was compared to that of a general U.S. population sample and other cardiac populations. Factors associated with lower quality of life were sought. Physical summary scores for 41 cardiac extracorporeal membrane oxygenation survivors were lower than the mean of the general population sample (42.4 ± 16.4 vs. 53.0 ± 8.8; p < .001) but similar to those of children with Fontan physiology or an automatic implantable cardioverter defibrillator. Psychosocial summary scores in extracorporeal membrane oxygenation patients were not different from those of the general population (48.2 ± 11.8 vs. 51.2 ± 9.1; p = .11) or of other cardiac samples. Postcardiotomy extracorporeal membrane oxygenation, more noncardiac operations, total intensive care and hospital days, noncardiac medical conditions, medications, and the need for physical, occupational, or speech therapy were associated with low physical summary scores. More noncardiac operations, noncardiac medical conditions, and the need for special education, physical, occupational, or speech therapy were associated with low psychosocial summary scores. CONCLUSIONS: In pediatric cardiac extracorporeal membrane oxygenation survivors, the physical component of health-related quality of life is lower than that of the general population but similar to that of patients with complex cardiac disease, whereas psychosocial quality of life is similar to that of the general population and of other pediatric cardiac populations. Copyright © 2012 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: congenital heart defect; extracorporeal membrane oxygenation; pediatric; quality of life

Mortality and neurodevelopmental outcome at 1 year of age comparing hybrid and Norwood procedures - Knirsch, W.; Liamlahi, R.; Hug, M.I.; Hoop, R.; von Rhein, M.; Prêtre, R.; Kretschmar, O.; Latal, B. (European Journal of Cardio-thoracic Surgery, 2012)
Objectives: Neonates with hypoplastic left heart syndrome (HLHS) are at risk of high mortality and neurodevelopmental morbidity. As an alternative to Norwood-type stage I palliation, the hybrid procedure has been developed. It consists of bilateral pulmonary artery banding, catheter-based stenting of the arterial duct and balloon atrioseptostomy and delays open-heart surgery. Thus, it may be associated with a better outcome. The aim of this study was to determine the mortality and neurodevelopmental outcome in patients with HLHS and other univentricular heart (UVH) defects treated with hybrid or Norwood procedures. Methods: Thirty-one children (18 males) with HLHS and other UVH defects undergoing Norwood or hybrid procedure between 2004 and 2008 were consecutively enrolled. Mortality and neurodevelopmental outcome at 1 year of age were determined. RESULTS: One-year mortality was 36% (31% in the hybrid vs. 39% in the Norwood group, P = 0.71). Predictors of mortality were lower birth weight (P = 0.02), older age at first procedure (P = 0.02) and smaller size of ascending aorta (P = 0.05). Overall, median psychomotor development index (PDI) and mental development index (MDI) of the Bayley Scales of Infant Development II were lower than the norm of 100 [PDI 57 (49-99), P < 0.001; MDI 91 (65-109), P = 0.002]. No effect of surgical treatment on neurodevelopmental outcome was found. Predictors of impaired motor outcome were length of hospital stay (LOHS) (P = 0.01), lower body weight at second procedure (P = 0.004) and female sex (P = 0.01). Predictors of impaired cognitive outcome were longer mechanical ventilation time (P = 0.03), intensive care unit stay (P = 0.04) and LOHS (P < 0.001), respectively. Conclusions: Mortality at 1 year of age is comparable between patients undergoing hybrid and Norwood procedures. Early neurodevelopmental outcome is significantly impaired in patients with both HLHS and other UVH defects. Multicentre randomized studies are needed to determine the long-term neurodevelopmental outcome of children treated with the hybrid procedure. © The Author 2012. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Cardiopulmonary bypass; Congenital heart defects; Hybrid procedure; Hypoplastic left heart syndrome; Neurocognitive deficits; Norwood operation

Cardiovascular hybrid procedure in severe congenital diaphragmatic hernia with significant left heart hypoplasia - Sroka, M.; Haponiuk, I.; Chojnicki, M.; Czauderna, P. (European Journal of Cardio-thoracic Surgery, 2012)
The authors discuss an early hybrid cardiovascular intervention in a neonate with left-sided congenital diaphragmatic hernia and significant left heart hypoplasia. The operation included persistent ductus arteriosus stenting and right pulmonary artery calibrated banding (3.5 mm) to increase blood flow in the aorta and to decrease right ventricle overload and decrease blood pressure and overflow in pulmonary circulation. The operation improved the child's general condition and gained time for left ventricle growth and restoration of its function. © The Author 2012. Published by Oxford University Press on behalf of the European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Cardiovascular hybrid intervention; Congenital diaphragmatic hernia; Left heart hypoplasia

Influence of surgical arch reconstruction methods on single ventricle workload in the Norwood procedure - Itatani, K.; Miyaji, K.; Qian, Y.; Liu, J.L.; Miyakoshi, T.; Murakami, A.; Ono, M.; Umezu, M. (Journal of Thoracic and Cardiovascular Surgery, 2012)
Objective: The study objective was to evaluate various types of Norwood arch reconstruction methods and to show the factors that affect the cardiac workload of the single ventricle. The Norwood procedure is one of the most challenging congenital heart surgeries. Several aortic arch reconstruction techniques have been reported to avoid recoarctation, ensure coronary perfusion, and improve long-term outcomes. Inside the arch, complicated turbulent flow is generated; however, little is known about the cause of the disadvantageous inefficient flow and the surgical techniques to avoid it. Methods: We created patient-specific computational hemodynamic models of 9 patients who underwent different types of arch reconstruction methods. Four patients had aortic atresia, and 5 patients had aortic stenosis. Flow profiles were defined by echocardiography data corrected with body surface area. Turbulent pulsatile flow was analyzed with the finite volume method. Flow energy loss was calculated to estimate cardiac workload, and wall shear stress was calculated to estimate vessel wall stiffness increase. Results: Recoarctation and acute arch angles increased wall shear stress and energy loss. In the patients with aortic atresia, a longitudinal incision toward the descending aorta was effective in creating a smooth arch angle. In the patients with aortic stenosis, arch repair with the Damus-Kaye-Stansel procedure in a single anastomotic site was effective in creating sufficient anastomosis space and a smooth arch angle. Conclusions: Creation of a large anastomotic space and a smooth aortic arch angle reduced wall shear stress and energy loss, and should improve long-term cardiac performance after the Norwood procedure. Copyright © 2012 by The American Association for Thoracic Surgery.

Increase in N-Terminus-Pro-B-Type natriuretic peptide during exercise of patients with univentricular heart after a total cavopulmonary connection - Hager, A.; Christov, F.; Hess, J. (Pediatric Cardiology, 2012)
An increase in N-terminus pro-B-type natriuretic peptide (NT-proBNP) during exercise is related to myocardial ischemia, myocardial dysfunction, and inflammatory stress. Its value for patients with a univentricular heart after total cavopulmonary connection (TCPC) is unknown. For 66 patients with TCPC, a cardiopulmonary exercise test was performed. Venous NT-proBNP samples were drawn with the patient at rest and then 2-3 min after peak exercise. The median NT-proBNP during rest was 82 ng/l (range, 11-2,554 ng/l), with 22 patients above the upper reference limit. A higher NT-proBNP during rest was related to a worse peak oxygen uptake (peak VO 2), a higher ventilatory equivalent (VE/VCO 2 slope), and a need for diuretics administration. A small but significant increase in NT-proBNP during exercise at 6 ng/l (range, 0-314 ng/l) was related mainly to its resting value. The relative increase was solely related to a higher body mass and not to any of the investigated functional parameters. Usually, NT-proBNP during rest is not elevated in TCPC patients. If so, it is a valuable predictor of cardiac function. During exercise, only a minor increase in NT-proBNP occurs. Its extent is not related to any of the investigated functional parameters. Maybe the filling restriction from the lungs prevents atrial and ventricular overload as well as BNP secretion in TCPC patients.
Keywords: Congenital heart disease; Exercise test; NT-proBNP; Total cavopulmonary connection; Univentricular heart

Sex and age differences in body-image, Self-Esteem, and Body mass index in adolescents and adults after single-ventricle palliation - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Eastwood, J.-A.; Lewis, A.B.; Child, J.S. (Pediatric Cardiology, 2012)
Single-ventricle congenital heart disease (SVCHD) requires multiple palliative surgical procedures that leave visible surgical scars and physical deficits, which can alter body-image and self-esteem. This study aimed to compare sex and age differences in body-image, selfesteem, and body mass index (BMI) in adolescents and adults with SVCHD after surgical palliation with those of a healthy control group. Using a comparative, cross-sectional design, 54 adolescent and adult (26 male and 28 female) patients, age 15-50 years, with SVCHD were compared with 66 age-matched healthy controls. Body-image and self-esteem were measured using the Multidimensional Body-Self Relations Questionnaire-Appearance Scale and Rosenberg Self-Esteem Scale. Height and weight were collected from retrospective chart review, and BMI was calculated. Female adolescents and adult patients with SVCHD reported lower body image compared with males patients with SVCHD and healthy controls (p = 0.003). Specific areas of concern were face (p = 0.002), upper torso or chest (p = 0.002), and muscle tone (p = 0.001). Patients with SVCHD who were \21 years of age had lower body image compared with healthy controls (p = 0.006). Self-esteem was comparable for both patients with SVCHD and healthy peers. There were no sex differences in BMI; BMI was higher in subjects[21 years of age (p = 0.01). Despite the similarities observed in selfesteem between the two groups, female patients with SVCHD\21 years of age reported lower perceived bodyimage. Our findings support the need to recognize poor psychological adjustment related to low self-esteem in patients with SVCHD; female patients warrant increased scrutiny. Strategies to help patients with SVCHD cope with nonmodifiable aspects of body-image during the difficult adolescent-to-young adult years may potentially enhance self-esteem and decrease psychological distress. © Springer Science+Business Media, LLC 2012.
Keywords: Body mass index; Body-image; Self-esteem; Single-ventricle congenital heart disease.

Ultrasound contrast and real-time perfusion in conjunction with supine bicycle stress echocardiography for comprehensive evaluation of surgically corrected congenital heart disease - Kutty, S.; Olson, J.; Danford, C.J.; Sandene, E.K.; Xie, F.; Fletcher, S.E.; Erickson, C.C.; Kugler, J.D.; Danford, D.A.; Porter, T.R. (European Heart Journal Cardiovascular Imaging, 2012)
Aims: We sought to evaluate the efficacy of ultrasound contrast (UC) and low mechanical index real-time perfusion (RTP) in the haemodynamic and anatomic assessment of repaired congenital heart disease (CHD) at rest and during supine bicycle stress echocardiography (BSE). Methods and results: Patients with CHD (n = 51, median age 21.5 years) were prospectively studied. All had compromised image quality, 20 (39%) had arrhythmias, and 10 (20%) had pacemakers. RTP was performed at rest and during BSE using Definity and Contrast Pulse Sequencing, with assessment of Doppler pressure gradients. Diagnoses included tetralogy of Fallot (n = 27), transposition of the great arteries (TGA) atrial switch (n = 10), TGA arterial switch (n = 2), aortic valve disease (n = 4), Fontan (n = 4), and Kawasaki disease (n = 4). UC with RTP improved endocardial border definition, with increased number of left ventricular (LV) and right ventricular (RV) segments visualized at rest (P < 0.0001) and during stress. LV ejection fraction (EF) and RV fractional area change (FAC) were measurable at rest and peak stress, RV FAC correlating closely with same-day magnetic resonance EFs (r = 0.72; P < 0.001). UC enhanced Doppler signals, enabling subpulmonary ventricular systolic pressure measurements at rest and stress. In six patients, marked elevations of subpulmonary ventricular systolic pressure were detected with UC during BSE, and quantifiable ventricular dysfunction. No adverse events occurred, other than transient low back pain in one patient. Conclusion: UC at rest and with supine BSE enables safe and comprehensive assessment of anatomy, haemodynamics, and biventricular functional and perfusion reserve in adolescents and young adults with surgically modified CHD. ClinicalTrials.gov Identifier: NCT00861848. Published on behalf of the European Society of Cardiology. All rights reserved. © The Author 2011.
Keywords: Adult congenital heart disease; Paediatric cardiology; Real-time perfusion; Stress testing; Ultrasound contrast; Wall motion

Fluid-structure interaction simulations of the Fontan procedure using variable wall properties - Long, C.C.; Hsu, M.-C.; Bazilevs, Y.; Feinstein, J.A.; Marsden, A.L. (International Journal for Numerical Methods in Biomedical Engineering, 2012)
Children born with single ventricle heart defects typically undergo a staged surgical procedure culminating in a total cavopulmonary connection (TCPC) or Fontan surgery. The goal of this work was to perform physiologic, patient-specific hemodynamic simulations of two post-operative TCPC patients by using fluid-structure interaction (FSI) simulations. Data from two patients are presented, and post-op anatomy is reconstructed from MRI data. Respiration rate, heart rate, and venous pressures are obtained from catheterization data, and inflow rates are obtained from phase contrast MRI data and are used together with a respiratory model. Lumped parameter (Windkessel) boundary conditions are used at the outlets. We perform FSI simulations by using an arbitrary Lagrangian-Eulerian finite element framework to account for motion of the blood vessel walls in the TCPC. This study is the first to introduce variable elastic properties for the different areas of the TCPC, including a Gore-Tex conduit. Quantities such as wall shear stresses and pressures at critical locations are extracted from the simulation and are compared with pressure tracings from clinical data as well as with rigid wall simulations. Hepatic flow distribution and energy efficiency are also calculated and compared for all cases. There is little effect of FSI on pressure tracings, hepatic flow distribution, and time-averaged energy efficiency. However, the effect of FSI on wall shear stress, instantaneous energy efficiency, and wall motion is significant and should be considered in future work, particularly for accurate prediction of thrombus formation. © 2012 John Wiley & Sons, Ltd.
Keywords: Congenital heart disease; Finite element method; Fluid-structure interaction; Fontan procedure

Hepatic blood flow distribution and performance in conventional and novel Y-graft Fontan geometries: A case series computational fluid dynamics study - Yang, W.; Vignon-Clementel, I.E.; Troianowski, G.; Reddy, V.M.; Feinstein, J.A.; Marsden, A.L. (Journal of Thoracic and Cardiovascular Surgery, 2012)
Objectives: A novel Y-shaped baffle has been proposed for the Fontan operation with promising initial results. However, previous studies have relied either on idealized models or a single patient-specific model. The objective of this study is to comprehensively compare the hemodynamic performance and hepatic blood flow distribution of the Y-graft Fontan baffle with 2 current designs using multiple patient-specific models. Methods: Y-shaped and tube-shaped grafts were virtually implanted into 5 patient-specific Glenn models forming 3 types of Fontan geometries: Y-graft, T-junction, and offset. Unsteady flow simulations were performed at rest and at varying exercise conditions. The hepatic flow distribution between the right and left lungs was carefully quantified using a particle tracking method. Other physiologically relevant parameters such as energy dissipation, superior vena cava pressure, and wall shear stress were evaluated. Results: The Fontan geometry significantly influences the hepatic flow distribution. The Y-graft design improves the hepatic flow distribution effectively in 4 of 5 patients, whereas the T-junction and offset designs may skew as much as 97% of hepatic flow to 1 lung in 2 cases. Sensitivity studies show that changes in pulmonary flow split can affect the hepatic flow distribution dramatically but that some Y-graft and T-junction designs are relatively less sensitive than offset designs. The Y-graft design offers moderate improvements over the traditional designs in power loss and superior vena cava pressure in all patients. Conclusions: The Y-graft Fontan design achieves overall superior hemodynamic performance compared with traditional designs. However, the results emphasize that no one-size-fits-all solution is available that will universally benefit all patients and that designs should be customized for individual patients before clinical application. Copyright © 2012 by The American Association for Thoracic Surgery.

Impact of severity of congenital heart diseases on university graduation rate among male patients - Özcan, E.E.; Küçük, A. (Turk Kardiyoloji Dernegi Arsivi, 2012)
Objectives: This study examines university graduation rates among individuals with congenital heart disease (CHD) in comparison to their healthy peers. The effect of disease severity, type of surgery, and timing of surgery on graduation rate was also evaluated. Study design: One hundred forty-five male patients with CHD at military age were enrolled in the study between the dates of January 2005 and May 2007. Severity of disease was operationalised in term of initial diagnosis (According to classification of 32th ACC Bethesta Conference Task Force 1). University graduation rates of among two groups of CHD patients (mild disease (group 1) or moderate to severe disease (group 2)) are compared to each other and to healthy peers. Results: Patients with CHD have reduced rates of participation in higher education compared with healthy individuals (13.1% vs 20.7%, p=0.01). Furthermore, this negative effect on education participation rate is independent of the severity of disease (group 1, 16.4%, p=0.01; group 2, 9.7%, p<0.001). Although the university graduation rate was relatively higher in patients with mild disease severity, no significant difference was found between the two patient groups (p=0.23). Having an operation does not effect graduation rate (p=0.58), however greater age at the time of operation increases the likelihood of graduation (p=0.02). Conclusion: Being born with CHD significantly reduces the chance of completing higher education. This negative impact on university graduation rate is independent of the severity of the disease. No negative effects of disease related surgery or subsequent corrective surgery on education were observed. Patients who were operated on later in life were more likely to complete university education. Mean operation age of this group corresponds to the typical age during the last year of elementary school in Turkey. © 2012 Turkish Society of Cardiology.
Keywords: Adult; Cardiology/education; Cardiovascular/ etiology; Congenital; Heart defects; Quality of life

Patients with univentricular heart in early childhood: Parenting stress and child behaviour - Sarajuuri, A.; Lönnqvist, T.; Schmitt, F.; Almqvist, F.; Jokinen, E. (Acta Paediatrica, International Journal of Paediatrics, 2012)
Aims: To assess perceptions of child behaviour and parenting stress among the parents of young children with hypoplastic left heart syndrome (HLHS) and other forms of functionally univentricular heart defects (UVH). Methods: As part of our prospective nation-wide neurodevelopmental follow-up study, the parents of 23 patients with HLHS, 14 with UVH and 46 healthy controls at the mean age of 18 months received the questionnaires Child Behavior Checklist and Parenting Stress Index. Results: The reported level of total parenting stress was significantly higher among the mothers (mean score 241 vs 205, p < 0.001) and fathers (235 vs 202, p = 0.003) of patients with HLHS compared with those of controls. The parents of patients with HLHS reported significantly more total (mean T score 52 vs 45, p = 0.005) and internalizing (51 vs 41, p < 0.001) behaviour problems than the controls, but among the syndrome scales, a significant difference was only found in somatic complaints. The parents of patients with UVH did not report more parenting stress or emotional problems than the controls. Conclusion: Hypoplastic left heart syndrome, a severe congenital heart defect, increases parenting stress. The reported emotional maladjustment in affected children might in part be owing to somatic complaints. © 2011 The Author(s)/Acta Pædiatrica © 2011 Foundation Acta Pædiatrica.
Keywords: Child behaviour; Congenital heart defect; Hypoplastic left heart syndrome; Parents; Psychological stress

Minor symptoms of depression in patients with congenital heart disease have a larger impact on quality of life than limited exercise capacity - Müller, J.; Hess, J.; Hager, A. (International Journal of Cardiology, 2012)
Objective: In patients with congenital heart disease quality of life is only marginally associated with exercise capacity. The aim of this study was to determine the prevalence of depression and its impact on quality of life and exercise capacity. Patients and methods: From November 2007 to October 2009 a total of 767 patients (352 female, 14-67 years) with various congenital heart diseases (37 palliated/native cyanotic, 57 Fontan, 74 Transposition of the Great Arteries (TGA) after atrial switch, 50 other TGA, 136 Fallot, 38 Ebstein, 47 Pulmonic stenosis/regurgitation, 68 aortic coarctation, 103 aortic stenosis, 90 isolated shunts, 67 other) completed the health-related quality of life questionnaire SF-36 and the German translation of the "Center for Epidemiologic Studies Depression Scale" (CES-D) to assess depressive symptoms. Afterwards a cardiopulmonary exercise test was performed. Results: Only 66 patients (8.6%) showed depressive symptoms fulfilling the CES-D definition for depression. The total prevalence of depression was lower than in the general population (Wilcoxon test, p < 0.001) and did not differ substantially in between the diagnostic subgroups (Kruskal-Wallis test, p = 0.195). CES-D score was correlated to all of the nine dimensions of quality of life (r = -0.170 to r = -0.740, p < 0.001) and less pronounced to exercise capacity (r = -0.164, p < 0.001). Correlation of peak oxygen uptake to quality of life was weaker than the CES-D scores in all subscales of life quality. Conclusions: Patients with congenital heart disease are rarely depressive. However, even minor depressive symptoms have a stronger impact on quality of life than limited exercise capacity as seen in many patients. © 2011 Published by Elsevier Ireland Ltd.
Keywords: Congenital heart disease; Depression; Exercise capacity; Quality of life

Severely impaired wound healing in a Fontan patient after neurosurgery: a novel topic in univentricular heart physiology? - Kovacevic, A.; Schmidt, K.G.; Schaper, J.; Messing-Juenger, M.; Hoehn, T. (Child's nervous system : ChNS : official journal of the International Society for Pediatric Neurosurgery, 2012)

Uncommon congenital extracardiac vascular anomalies detected on MSCT (Multi-Slice Computed Tomography) aortic angiography with 64-multislice technology - El Kheshen, A.M.M. (Egyptian Journal of Radiology and Nuclear Medicine, 2012)
Objective: The purpose of this study was to evaluate the role of CT angiography in different encountered congenital vascular anomalies of pediatric age groups using 64 multislice CT scanner. Subjective and methods: Through one year, a total of 15 patients having congenital extracardiac anomalies were encountered from those attending big trauma and emergency center and were studied in this work. Each patient's parent was thoroughly asked about the detailed clinical history after reviewing the referring imaging request and laboratory findings. Exclusion criteria for CT were as follows: previous allergic reactions to iodine contrast media and severe renal insufficiency. CT examination was performed using 64 multislice CT machine. Results: CTA examination was performed in a total of 15 patients. The age of the patients was ranging from 2 days to 14 yrs and 5 cases were females. Four cases came with cyanosis; one case came with follow up after operation for transposition of great arteries, while the remaining cases were suffering from medical problems such as respiratory distress or hypertension. Aortic arch hypoplasia, right sided aortic arch with mirror image or with aberrant left subclavian artery, hypoplastic left pulmonary artery with left sided aortic arch and aberrant right subclavian artery, hypoplastic left heart chambers, retrotracheal left pulmonary artery with patent ductus arteriosus (PDA), right superior partial anomalous pulmonary venous drainage (PAPVD) with ASD sinus venosum, postoperative assessment of transposition of great arteries (TGA), fibromuscular dysplasia involving the renal and common iliac arteries, and bilateral double renal arteries with ectopic right kidney were the different extracardiac vascular anomalies encountered in this work. Conclusion: CTA provides an excellent means to detect a number of extracardiac vascular anomalies and allows accurate and fast noninvasive characterization of extracardiac vascular anatomy. It is a helpful tool in establishing the primary diagnosis, defining anatomic landmarks and relationships, identifying vascular anomalies and helping in postoperative follow-up. © 2011 Egyptian Society of Radiology and Nuclear Medicine. Production and hosting by Elsevier B.V. All rights reserved.
Keywords: Anomalies; Aortic; Cardiac; CTA; Vascular

Perspectives in ablation of arrhythmias in children and patients with congenital heart disease - Pflaumer, A. (Internal Medicine Journal, 2012)
Although most arrhythmias in children have a benign outcome, recurrent arrhythmic events have a significant impact on quality of life. Electrophysiology studies with ablation have good short-term success and an acceptably low complication rate. The long-term outlook for this patient group is incompletely defined, however. Factors that require special consideration in children include the need to limit the size, depth and number of lesions, and the radiation exposure incurred during fluoroscopy-guided catheters manipulation. The use of cryoablation seems promising in limiting lesion size. Three-dimensional (3D) mapping systems clearly have been shown to reduce the radiation dose. In congenital heart disease, these advances in technology have helped to further our understanding of the mechanisms underlying arrhythmias. It is anticipated that earlier intervention and newer operative techniques will reduce the incidence of postoperative arrhythmias in the future. For those patients who still develop tachyarrythmias after cardiac surgery, the use of three-dimensional systems and other new technologies permits more efficient intervention in the electrophysiology laboratory. © 2012 The Author and 2012 Royal Australasian College of Physicians.
Keywords: Ablation technique; Arrhythmia; Cardiac; Child; Congenital; Electrophysiology; Heart defect

Adult congenital surgery: Current management - Vouhé, P.R. (Seminars in Thoracic and Cardiovascular Surgery, 2011)
The population of adults with congenital heart disease (CHD) (commonly called grown-ups with congenital heart disease or GUCH) is increasing steadily and exceeds the population of children with CHD already. The specificities of GUCH surgery are multiple and include (1) variety of the anatomo-clinical situations (defects repaired during childhood, malformations either nonoperated or palliated, nonreparable defects), (2) usual multiorgan involvement, and (3) many technical differences related to cardiopulmonary bypass, myocardial protection, and surgical technique. The surgical indications should be taken after a precise evaluation of the risk/benefit ratio on an individual basis; a balanced attitude should be kept between unwise interventionism and excessive waiting policy. It is now agreed that GUCH surgery should be performed in specialized centers with large patient volumes and expertise of both surgical and medical disciplines. Much remains to be done to implement these recommendations and to accumulate experience and evidence-based information to provide optimal outcome. © 2011 Elsevier Inc.
Keywords: Adult cardiac surgery; Congenital heart disease

Three-dimensional simulations in glenn patients: Clinically based boundary conditions, hemodynamic results and sensitivity to input data - Troianowski, G.; Taylor, C.A.; Feinstein, J.A.; Vignon-Clementel, I.E. (Journal of Biomechanical Engineering, 2011)
While many congenital heart defects can be treated without significant long term sequelae, some achieve successful palliation as their definitive endpoints. The single-ventricle defect is one such defect and leaves the child with only one operational ventricle, requiring the systemic and the pulmonary circulations to be placed in series through several operations performed during early childhood. Numerical simulations may be used to investigate these hemodynamic conditions and their relation to post-operative sequelae; however, they rely heavily on boundary condition prescription. In this study, we investigate the impact of hemodynamic input data uncertainties on simulation results. Imaged-based patient-specific models of the multi-branched pulmonary arteries and superior vena cava were built for five cavopulmonary connection (i.e. Glenn) patients. Magnetic resonance imaging and catheterization data were acquired for each patient prior to their Fontan surgery. Inflow and outflow boundary conditions were constructed to match available clinical data and resulted in the development of a framework to incorporate these types of clinical data into patient-specific simulations. Three-dimensional computational fluid dynamics simulations were run and hemodynamic indicators were computed. Power loss was low (and efficiency very high) and a linear correlation was found between power loss and cardiac index among the five patients. Other indicators such as low wall shear stress were considered to better characterize these patients. Flow was complex and oscillatory near the anastomosis, and laminar in the smaller branches. While common trends were seen among patients, results showed differences among patients, especially in the 3D maps, strengthening the importance of patient-specific simulations. A sensitivity analysis was performed to investigate the impact of input data (clinical and modeling) to construct boundary conditions on several indicators. Overall, the sensitivity of the output indicators to the input data was small but non-negligible. The sensitivity of commonly used hemodynamic indicators to compare patients is discussed in this context. Power efficiency was much more sensitive to pressure variation than power loss. To increase the precision of such indicators, mean flow split between right and left lungs needs to be measured with more accuracy with higher priority than refining the model of how the flow is distributed on average among the smaller branches. Although ± 10 % flow split imprecision seemed reasonable in terms of patient comparison, this study suggests that the common practice of imposing a right pulmonary artery/left pulmonary artery flow split of 55 %/45 % when performing patient specific simulations should be avoided. This study constitutes a first step towards understanding the hemodynamic differences between pre-and post Fontan surgery, predicting these differences, and evaluating surgical outcomes based on preoperative data. © 2011 American Society of Mechanical Engineers.
Keywords: boundary conditions; clinical data; congenital heart disease; numerical simulations; sensitivity analysis

12th Annual C. Walton Lillehei Memorial Lecture in Cardiovascular Surgery: Fontan conversion - The Chicago experience - Backer, C.L. (Cardiology in the Young, 2011)
Between 1994 and 2011, we performed 133 Fontan conversions with arrhythmia surgery. Most patients had tricuspid atresia or double-inlet left ventricle with prior atriopulmonary connection. Operative mortality was 1.5%, and mean length of stay was 14 days. A total of eight patients (6%) have had late cardiac transplantation. Freedom from arrhythmia recurrence is 85% at 10 years. For properly selected patients with a functionally univentricular heart who have had an atriopulmonary Fontan procedure, Fontan conversion with arrhythmia surgery significantly improves quality of life. © 2011 Cambridge University Press.
Keywords: arrhythmia surgery; cavopulmonary connection; congenital heart disease; Cox-maze III; Fontan procedure; Functionally univentricular heart

Patient-reported outcomes in adult survivors with single-ventricle physiology - Overgaard, D.; Schrader, A.-M.; Lisby, K.H.; King, C.; Christensen, R.F.; Jensen, H.F.; Idorn, L.; Søndergaard, L.; Moons, P. (Cardiology, 2011)
Objectives: Data on patient-reported outcomes (PROs) in patients with single-ventricle physiology (SVP) are scarce. We sought (1) to describe the perceived health status, quality of life, symptoms of anxiety and depression, and sense of coherence in adult survivors with SVP, (2) to compare PROs across functional classes, and (3) to compare PROs between patients and controls. Methods: A case-control study in two adult congenital heart programmes with 62 adult survivors with SVP were matched to 172 healthy controls. A wide range of PROs were measured using validated questionnaires. The treating physician classified patients according to the Ability Index. Results: Patients with SVP have a good functional status. Patients in Ability Index class I consistently reported the best scores, similar to those of healthy controls. Negative associations were found between functional class and outcomes of perceived health and quality of life. For patients in Ability Index class II and III, PROs were poorer. Conclusions: PROs in patients with SVP are generally good. © 2011 S. Karger AG, Basel.
Keywords: Congenital heart disease; Patient-reported outcomes; Perceived health; Quality of life; Single-ventricle physiology

New concepts: Development of a survivorship programme for patients with a functionally univentricular heart - Goldberg, D.J.; Dodds, K.; Rychik, J. (Cardiology in the Young, 2011)
Children with functionally univentricular hearts are now surviving into their third and fourth decades of life. Although survival alone is a remarkable achievement, a lot must still be done to improve the quality and duration of life after the Fontan operation. Challenges that may be faced by these patients include the impact of the Fontan operation on the liver and the density of bone, protein-losing enteropathy, and plastic bronchitis. Paediatric cardiologists are familiar with the haemodynamic issues inherent in Fontan physiology; however, training in cardiology is often not sufficient to give us a complete understanding of the pathophysiology of the complications or of the options for treatment. Collaboration with other subspecialists including gastroenterologists, endocrinologists, and pulmonologists is essential in order to provide the rigorous and nuanced care that our patients need and deserve. A clinic in which a patient can see multiple subspecialists, and in which the subspecialists, as a group, can discuss each patient, can provide a unique and valuable service for patients with a functionally univentricular heart. © 2011 Cambridge University Press.
Keywords: follow-up; Fontan; functionally univentricular heart; single ventricle

Changing attitudes to the management of hypoplastic left heart syndrome: A European perspective - Murtuza, B.; Elliott, M.J. (Cardiology in the Young, 2011)
Background and aims Several years ago, one of us described the difference in attitude to patients with hypoplastic left heart syndrome in the United States of America and Europe as similar to that between Mars and Venus. Uncertainty remains with regard to the long-term prognosis for patients with hypoplastic left heart syndrome. This prognosis may be considered in terms of survival, functional performance, including exercise capacity and neurodevelopment, as well as psychosocial effects on the patient, family, and siblings. Counselling parents where either an antenatal or postnatal diagnosis of hypoplastic left heart syndrome has been made requires practitioners to give information on these prognostic aspects. We wanted to see how attitudes among European surgeons have changed over the last few years.Methods We performed a review of recent European data for hypoplastic left heart syndrome and conducted a survey among surgeons in major European centres to ascertain key aspects of their attitudes to the management of patients with hypoplastic left heart syndrome and how they counsel parents.Results and conclusions As of January, 2011, 2392 citations in the PubMed database were available for the search string "hypoplastic left heart". The majority of these were from the centres from the United States of America and Europe. The European Association for Cardio-Thoracic Surgery Congenital Heart Surgery Database shows an annual increase in the number of Norwood (Stage I) operations for hypoplastic left heart syndrome from 2003 to 2009, with a corresponding reduction in mortality. European rates of antenatal detection vary widely between centres, as do the rates of termination for a prenatal diagnosis of hypoplastic left heart syndrome. We observed a wide variation in the estimates of surgeons for survival and quality of life for surgical palliation of hypoplastic left heart syndrome, as well as in their estimates for actual rates of termination of pregnancy in their centres. Further, there was marked inconsistency in the information given to parents as part of the process of counselling. These issues remain to be resolved if parents are to make a fully informed decision for their child. © 2011 Cambridge University Press.
Keywords: antenatal diagnosis; comfort care; counselling; European; foetal diagnosis; hypoplasia of the left heart; hypoplastic left heart syndrome; Norwood; pregnancy termination; single-ventricle repair; surgical palliation

Treatment of plastic bronchitis by orthotopic heart transplantation - Laubisch, J.E.; Green, D.M.; Mogayzel, P.J.; Reid Thompson, W. (Pediatric Cardiology, 2011)
This case illustrates the successful use of orthotopic heart transplantation for the treatment of plastic bronchitis in a 6-year-old boy with hypoplastic left heart syndrome, which developed 2 years after Fontan procedure. Transplantation was undertaken after he failed medical management of airway obstruction. He is currently 1-year post-cardiac transplantion and has no evidence of plastic bronchitis despite weaning of an aggressive airway clearance regimen. © 2011 Springer Science+Business Media, LLC.
Keywords: Congenital heart disease; Plastic bronchitis; Transplantation

Coming from behind to win - A Qualitative research about psychological conditions of adolescents who have undergone open-heart surgery for single ventricle between the ages 0-5 - Zahmacioglu, O.; Yildiz, C.E.; Koca, B.; Ugurlucan, M.; Gokalp, S.; Cetin, G.; Guler Eroglu, A.; Oztunc, F. (Journal of Cardiothoracic Surgery, 2011)
Early recognition of congenital cardiac pathologies and their treatment by means of palliative or corrective surgery at birth or infancy has vital importance. Successful repair of congenital cardiac defects by surgical methods has gained importance especially during the last twenty years. As the scope of the surveillance increased so did the interest in the outcomes of these treatments when the patients had reached puberty and adulthood. The purpose of our research was to study the psychological framework of the adolescents who had experienced these surgeries by listening both the children and the parents talk about their feelings and experiences. Our data was accumulated through interviews with 17 adolescents and their families, using qualitative methods. The main theme at the end of the analysis was "to be strong and resistive". We reached the conclusion that this condition was not a pathological build up but an attitude of coping, as it did not cause loss of functionality. The defensive psychological mechanisms used by these adolescents consisted of repression, compensation and reaction formation. We believe that this information is important to understand the real meaning of the manners displayed when these adolescents and their families pursue their daily lives, communicate and make relationships with their environment and especially professionals in the health services. © 2011 Zahmacioglu et al; licensee BioMed Central Ltd.
Keywords: Congenital heart disease; Coping styles; Defense mechanisms; experiences; Fontan operation; Single ventricle

The Impact of Extracorporeal Membrane Oxygenation on Survival in Pediatric Patients With Respiratory and Heart Failure: Review of Our Experience - Goto, T.; Suzuki, Y.; Suzuki, Y.; Osanai, A.; Aoki, K.; Yamazaki, A.; Daitoku, K.; Fukuda, I. (Artificial Organs, 2011)
Extracorporeal membrane oxygenation (ECMO) is widely used for circulatory support in pediatric cardiac patients with low cardiac output and hypoxemia. We retrospectively evaluated the efficacy of ECMO support for respiratory and heart failure in infants and children. From April 2002 to February 2011, 14 patients aged 19 days to 20 years old (average 44 months), with body weight 2.6kg to 71kg (median 14.1kg), underwent ECMO support for failing cardiac function, hypoxemia, and low cardiac output syndrome. In 12 patients, ECMO was introduced after operation for congenital heart disease (four with complete repair including Fontan circulation, and eight with palliative repair). In one patient, ECMO was introduced after partial pulmonary resection for congenital cystic adenomatoid malformation because of respiratory failure. ECMO was introduced in a patient with severe heart failure caused by fulminant myocarditis. Patients' demographics, duration of extracorporeal membrane oxygenation, additional support, and outcomes were analyzed. Ten patients (71%) were successfully weaned from ECMO, and eight patients (57%) were discharged from the hospital. The mean duration of ECMO support was 332h (range 11-2030h). Although management of the ECMO circuit, including anticoagulation (activated clotting time: 150-250), was conducted following the institutional practice guidelines, it was difficult to control the bleeding. Seven patients required renal replacement therapy during ECMO support using peritoneal dialysis or continuous hemodiafiltration. Five patients had additional operative procedures: systemic-pulmonary shunt in two, bidirectional Glenn takedown with right modified Blalock-Taussig shunt, total cavopulmonary connection takedown, and redo ECMO in one patient each. The patient who had the longest ECMO support for respiratory failure due to acute respiratory distress syndrome after lung surgery was successfully weaned from ECMO because high-frequency oscillation (HFO) improved respiratory function. ECMO for heart and respiratory failure in infants and children is effective and allows time for recovery of cardiac dysfunction and acute hypoxic insult. The long-term ECMO support for over 2000h was very rare, but it was possible to wean this patient from ECMO using HFO. © 2011, Copyright the Authors. Artificial Organs © 2011, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Acute respiratory distress syndrome; Congenital cardiac surgery; Extracorporeal membrane oxygenation; Heart failure

Mechanical Cavopulmonary Assistance of a Patient-Specific Fontan Physiology: Numerical Simulations, Lumped Parameter Modeling, and Suction Experiments - Throckmorton, A.L.; Carr, J.P.; Tahir, S.A.; Tate, R.; Downs, E.A.; Bhavsar, S.S.; Wu, Y.; Grizzard, J.D.; Moskowitz, W.B. (Artificial Organs, 2011)
This study investigated the performance of a magnetically levitated, intravascular axial flow blood pump for mechanical circulatory support of the thousands of Fontan patients in desperate need of a therapeutic alternative. Four models of the extracardiac, total cavopulmonary connection (TCPC) Fontan configuration were evaluated to formulate numerical predictions: an idealized TCPC, a patient-specific TCPC per magnetic resonance imaging data, and each of these two models having a blood pump in the inferior vena cava (IVC). A lumped parameter model of the Fontan physiology was used to specify boundary conditions. Pressure-flow characteristics, energy gain calculations, scalar stress levels, and blood damage estimations were executed for each model. Suction limitation experiments using the Sylgard elastomer tubing were also conducted. The pump produced pressures of 1-16mmHg for 2000-6000rpm and flow rates of 0.5-4.5L/min. The pump inlet or IVC pressure was found to decrease at higher rotational speeds. Maximum scalar stress estimations were 3Pa for the nonpump models and 290Pa for the pump-supported cases. The blood residence times for the pump-supported cases were shorter (0.9s) as compared with the nonsupported configurations (2.5s). However, the blood damage indices were higher (1.5%) for the anatomic model with pump support. The pump successfully augmented pressure in the TCPC junction and increased the hydraulic energy of the TCPC as a function of flow rate and rotational speed. The suction experiments revealed minimal deformation (<3%) at 9000rpm. The findings of this study support the continued design and development of this blood pump. © 2011, Copyright the Authors. Artificial Organs © 2011, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Artificial right ventricle; Blood pump; Cavopulmonary assist device; Computational fluid dynamics; Fontan physiology; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Total cavopulmonary connection

High-frequency oscillatory ventilation and short-term outcome in neonates and infants undergoing cardiac surgery: A propensity score analysis - Bojan, M.; Gioanni, S.; Mauriat, P.; Pouard, P. (Critical Care, 2011)
Introduction: Experience with high-frequency oscillatory ventilation (HFOV) after congenital cardiac surgery is limited despite evidence about reduction in pulmonary vascular resistance after the Fontan procedure. HFOV is recommended in adults and children with acute respiratory distress syndrome. The aim of the present study was to assess associations between commencement of HFOV on the day of surgery and length of mechanical ventilation, length of Intensive Care Unit (ICU) stay and mortality in neonates and infants with respiratory distress following cardiac surgery.Methods: A logistic regression model was used to develop a propensity score, which accounted for the probability of being switched from conventional mechanical ventilation (CMV) to HFOV on the day of surgery. It included baseline characteristics, type of procedure and postoperative variables, and was used to match each patient with HFOV with a control patient, in whom CMV was used exclusively. Length of mechanical ventilation, ICU stay and mortality rates were compared in the matched set.Results: Overall, 3,549 neonates and infants underwent cardiac surgery from January 2001 through June 2010, 120 patients were switched to HFOV and matched with 120 controls. After adjustment for the delay to sternal closure, duration of renal replacement therapy, occurrence of pulmonary hypertension and year of surgery, the probability of successful weaning over time and the probability of ICU delivery over time were significantly higher in patients with HFOV, adjusted hazard ratios and 95% confidence intervals: 1.63, 1.17 to 2.26 (P = 0.004). and 1.65, 95% confidence intervals: 1.20 to 2.28 (P = 0.002) respectively. No association was found with mortality.Conclusions: When commenced on the day of surgery in neonates and infants with respiratory distress following cardiac surgery, HFOV was associated with shorter lengths of mechanical ventilation and ICU stay than CMV. © 2011 Bojan et al.; licensee BioMed Central Ltd.

Impact of Fontan conversion with arrhythmia surgery and pacemaker therapy - Hiramatsu, T.; Iwata, Y.; Matsumura, G.; Konuma, T.; Yamazaki, K. (European Journal of Cardio-thoracic Surgery, 2011)
Objective: In the long-term period after Fontan operation, atrial arrhythmia was one of the important factors to decide the postoperative quality of life. We reviewed the impact of Fontan conversion with arrhythmia surgery and pacemaker therapy. Methods: Thirty-eight patients underwent Fontan conversion using extracardiac conduit from 1992, and 22 patients with atrial arrhythmia underwent maze procedure simultaneously using cryoablation or radiofrequency ablation and epicardial DDD pacemaker implantation and 16 patients had regular 'sinus' rhythm before Fontan conversion. Mean follow-up period was 52 months. Pre- and postoperative clinical course were analyzed. Average weight, age at Fontan conversion, and years after first Fontan operation were 49.0kg, 25.8 years old, 14.7 years, respectively. Nineteen percent of patients were in New York Heart Association class I (NYHA I), and 74% of patients were in NYHA II, and 7% were in NYHA III, respectively. Results: Except three early deaths, actual survival rate at 1 year and 5 years were 80% and 64%, respectively. In survivors, 80% of the patients obtained regular heart rhythm including artificial pacemaker rhythm, although only 43% of the patients had regular 'sinus' rhythm before the Fontan conversion. Postoperative average cardiothoracic ratio and oxygen saturation (SpO 2) were 50% and 94%, and 74% of patients were in NYHA I and 26% were in NYHA II, respectively, after Fontan conversion. Conclusions: Mid-term results of Fontan conversion with arrhythmia surgery and pacemaker therapy were acceptable. Restoration of regular rhythm might improve the postoperative NYHA status and the activity of the daily life. © 2011 European Association for Cardio-Thoracic Surgery.
Keywords: Arrhythmia surgery; Fontan conversion; Pacemaker therapy

Patients with single-ventricle physiology: Prognostic implications of stress testing - Bauer, B.S.; Aboulhosn, J.A.; Williams, R.J.; Child, J.S. (Pediatric Cardiology, 2011)
This study used a retrospective analysis of adults with single-ventricle physiology to ascertain the predictive power of cardiopulmonary stress-testing parameters in determining patients at increased risk of suffering from adverse clinical outcomes. We found that the specific parameters of percent of maximum predicted heart rate achieved and maximum oxygen consumption were significantly correlated with adverse clinical outcomes in patients with single-ventricle congenital heart disease. © 2011 Springer Science+Business Media, LLC.
Keywords: Adult congenital heart disease; Cardiopulmonary stress testing; Single ventricle physiology

Fetal and post-natal diagnosis of major congenital heart disease: Implications for medical and psychological care in the current era - Sholler, G.F.; Kasparian, N.A.; Pye, V.E.; Cole, A.D.; Winlaw, D.S. (Journal of Paediatrics and Child Health, 2011)
Aim: The fetal or post-natal diagnosis of major congenital cardiac abnormality has important medical and psychological consequences. Methods: We reviewed infants who underwent cardiac surgery in the first year of life at the Heart Centre for Children, The Children's Hospital at Westmead during 2009. The aims of this study were to: (i) examine the key features of cardiac diagnosis and clinical outcome, and (ii) consider how these data can inform priorities for the delivery of clinical services. Results: Over the 12-month study period, a first cardiac surgical procedure was performed on 195 infants, with 85 infants (44%) diagnosed in the antenatal period. Of the total sample, a subset of 90 babies (46%) underwent their first procedure in the neonatal period, with 62% having had a fetal diagnosis. Major intracardiac lesions including truncus arteriosus (100%), single ventricular lesions (83%), pulmonary atresia with ventricular septal defect (78%) and transposition of the great arteries (53%) were diagnosed prior to birth. Improved haemodynamic stability at initial presentation was found in those with a fetal diagnosis. The overall mortality rate for all patients was 6.1% at 12 months, with a higher mortality in infants with single ventricle. Conclusions: The contemporary paradigm of care for infants with major congenital heart disease requires a multidisciplinary approach to care, with improvements in clinician-clinician and clinician-family communication, and psychological support and education for families. Changes in the allocation of resources are required to meet this model of best practice. © 2011 The Authors.
Keywords: cardiac surgery; congenital heart disease; fetal; psychological care

Progress of surgical treatment of pediatric congenital heart disease - Xu, Z.-W. (Journal of Shanghai Jiaotong University (Medical Science), 2011)
In recent years, the surgical treatment and operative procedure for congenital heart disease (CHD) have been greatly improved. The surgical results of hypoplastic left heart syndrome (HLHS) have been improved by modified operative procedure and intervention. With proper management of the right ventricle outflow tract in tetralogy of Fallot (TOF), right ventricle heart function can be improved after operation. The surgical repair of pulmonary venous obstruction after operation of total abnormal pulmonary venous connection (TAPVC), and the renewed operative procedure of transposition of the great arteries (TGA) and congenital corrected transposition of the great arteries (ccTGA) facilitate the rational surgical treatment of complex CHD. With improvement of operative procedure for CHD, the operative successful rate is increased, the incidence of complications is decreased, and the quality of life and long-term surgical outcomes are improved.
Keywords: Complete transposition of the great arteries; Congenital corrected transposition of the great arteries; Congenital heart disease; Hypoplastic left heart syndrome; Tetralogy of Fallot; Total abnormal pulmonary venous connection

Undiagnosed heart disease leading to sudden unexpected death in childhood: A retrospective study - Ilina, M.V.; Kepron, C.A.; Taylor, G.P.; Perrin, D.G.; Kantor, P.F.; Somers, G.R. (Pediatrics, 2011)
OBJECTIVES: Heart disease accounts for a significant proportion of sudden unexpected deaths among children. We describe here demographic features, pathological conditions, and the frequency of premonitory symptoms in a retrospective series of cases of sudden unexpected cardiac death (SUCD) attributable to undiagnosed structural heart disease. METHODS: A chart review of autopsies involving children 0 to 17 years of age that were performed at the Hospital for Sick Children (Toronto, Ontario, Canada) between 1984 and 2003 was conducted. Cases of sudden unexpected death within 24 hours after clinical presentation with previously undetected fatal heart disease were included. Cases with multiple or thoracic trauma and chronic or multisystem disease were excluded. RESULTS: During the 20-year study period, 4926 autopsies were performed. A total of 103 cases (2.1%), involving 51 male patients and 52 female patients 1 day to 15 years of age (mean: 2.9 ± 4.2 years), were diagnosed as having SUCD. The most common diagnoses were myocarditis (n-37 [35.9%]), hypoplastic left heart syndrome (HLHS) (n = 19 [18.4%]), dilated cardiomyopathy (DCM) (n = 16 [16.5%]), coronary artery anomalies (n = 6 [5.8%]), and aortic stenosis (n = 5 [4.9%]). There was a significant difference in the mean age of presentation between leading causes of SUCD (6.5 days for HLHS, 1.7 years for DCM, and 5.4 years for myocarditis; P < .0001). Of 103 cases, 27 (26.2%) had premonitory symptoms documented. CONCLUSION: SUCD accounted for 2.1% of all autopsies, and HLHS, DCM, and myocarditis were the 3 most common diagnoses, which presented at increasing ages. Copyright © 2011 by the American Academy of Pediatrics.
Keywords: Cardiomyopathy; Congenital heart disease; Hypoplastic left heart syndrome; Myocarditis; Sudden cardiac death

Perioperative cerebral and somatic oxygenation in neonates with hypoplastic left heart syndrome or transposition of the great arteries - Uebing, A.; Furck, A.K.; Hansen, J.H.; Nufer, E.; Scheewe, J.; Dütschke, P.; Jung, O.; Kramer, H.-H. (Journal of Thoracic and Cardiovascular Surgery, 2011)
Objective: Significant depression in cerebral oxygen saturation has been observed in patients with hypoplastic left heart syndrome (HLHS) undergoing Norwood operations. We monitored cerebral oxygen saturation with near-infrared spectroscopy before and after this procedure. Patients with transposition of great arteries (TGA) before and after arterial switch operation were also studied to elucidate whether post-cardiopulmonary bypass (CPB) changes in cerebral oxygen saturation are related to CPB or hemodynamic alterations inherent in single-ventricle physiology. Methods: We monitored 33 patients with HLHS and 20 with TGA 24 hours before and 48 hours after CPB. In addition to cerebral oxygen saturation, routine measurements of oxygen transport and delivery were performed. Results: Preoperatively, cerebral oxygen saturation was higher in patients with HLHS than with TGA (61% ± 7% vs 56% ± 8%, P = .04). After CPB, cerebral oxygen saturation was markedly depressed in both groups but increased toward end of monitoring (HLHS vs TGA minimal value 42% ± 12% vs 54% ± 11%, P < .001, value 48 hours after CPB 62% ± 7% vs 80% ± 8%, P < .0001). Routine measures of oxygen delivery, such as arterial and central venous oxygen saturations, were similar at minimal cerebral oxygen saturation and 48 hours after CPB. Conclusions: Depression of cerebral oxygen saturation is prevalent among neonates with congenital heart disease regardless of whether univentricular or biventricular circulation is present, suggesting that cerebral desaturation is mainly induced by CPB's effect on cerebral blood flow. Routine measures of oxygen delivery fail to indicate cerebral desaturation. Copyright © 2011 by The American Association for Thoracic Surgery.

The fontan operation: The pursuit of associated lesions and cumulative trauma - Hannan, R.L.; Zabinsky, J.A.; Salvaggio, J.L.; Rossi, A.F.; Khan, D.M.; Alonso, F.A.; Ojito, J.W.; Nykanen, D.G.; Zahn, E.M.; Burke, R.P. (Pediatric Cardiology, 2011)
Our programmatic approach to the Fontan operation has evolved to include using an extracardiac conduit with aggressive presumptive treatment of associated lesions either in the catheterization laboratory or the operating room. Fenestration is used selectively based on hemodynamics, anatomy, and presence of associated lesions. We reviewed our experience to determine the effectiveness and outcome of this strategy and to assess the cumulative trauma to the patients. The records of 137 consecutive patients who underwent Fontan at Miami Children's Hospital from 1995 to 2008 were reviewed. At mean follow up of 5.76 years, freedom from death or transplantation is 94.2% (129/137). Median age at operation was 4.6 years. Longer length of stay correlated with older operative age (P = 0.0056). Pacemakers were implanted in 11.7% (16/137). Additional (not pre-Glenn or pre-Fontan) interventional catheterizations were performed in 51.8% (71/137). Additional operations were done in 10.2% (14/137). No patient has required replacement or revision of the extracardiac conduit. Our current approach to the Fontan operation provides acceptable midterm results. The pursuit of residual lesions results in a significant number of additional interventional catheterizations and operative procedures but might have an important influence on long-term survival after the Fontan procedure. © 2011 The Author(s).
Keywords: Cardiac catheterization/intervention; Cardiac surgery; Congenital heart disease Pediatric

Significance of the residual aortic obstruction in multistage repair of hypoplastic left heart syndrome - Januszewska, K.; Kozlik-Feldmann, R.; Kordon, Z.; Urschel, S.; Netz, H.; Reichart, B.; Malec, E. (European Journal of Cardio-thoracic Surgery, 2011)
Objective: The population of children who received right ventricle-to-pulmonary artery shunt (RV-PA) at Norwood procedure (NP) is growing, but limited data are available regarding the long-term outcome. The aim of this study was to present operative outcomes and mid-term hemodynamics and to assess the impact of the residual aortic obstruction on the results in patients undergoing three-staged surgery with RV-PA application at NP. Methods: Between June 2001 and June 2009, 229 children with hypoplastic left heart syndrome (HLHS) and variants underwent NP with RV-PA; 172 have proceeded to stage II and 95 to stage III. The medical records (clinical data, echocardiographic records, cardiac catheterization reports, electrocardiograms, and surgical notes) were retrospectively reviewed. Results: The later era of NP was associated with significantly better outcome (2001-2004: 1- and 5-years' survival were 64.3% and 59.8%, respectively; 2005-2009: 1- and 4-years' survival were 93.1% and 86.9%, respectively) (p< 0.001). There was no association between long-term survival and diagnosis (HLHS/HLHS variant) (p= 0.39). The incidence of depressed ventricular function and moderate or severe systemic atrioventricular valve regurgitation among the children who required balloon aortoplasty (BA) before stage II surgery was significantly higher than in children without aortic arch obstruction (p= 0.027, p= 0.008, respectively). In midterm follow-up, BA had no significant influence on the actuarial survival (p= 0.089). No ventricular arrhythmias were noticed at any stage. Conclusions: The RV-PA shunt is a safe technique that does not seem to impair systolic or electrical ventricular function; its outcomes continue to improve with growing experience. Combined cardiologic interventional and surgical procedures are required to optimize the outcomes. © 2010 European Association for Cardio-Thoracic Surgery.
Keywords: Aortic obstruction; Hypoplastic left heart syndrome; Norwood procedure; Right ventricle-to-pulmonary artery shunt

Usefulness of peripheral vascular function to predict functional health status in patients with fontan circulation - Goldstein, B.H.; Golbus, J.R.; Sandelin, A.M.; Warnke, N.; Gooding, L.; King, K.K.; Donohue, J.E.; Gurney, J.G.; Goldberg, C.S.; Rocchini, A.P.; Charpie, J.R. (American Journal of Cardiology, 2011)
After the Fontan operation, patients are at a substantial risk of the development of impaired functional health status. Few early markers of suboptimal outcomes have been identified. We sought to assess the association between peripheral vascular function and functional health status in Fontan-palliated patients. Asymptomatic Fontan patients (n = 51) and age- and gender-matched healthy controls (n = 22) underwent endothelial pulse amplitude testing using a noninvasive fingertip peripheral arterial tonometry (PAT) device. Raw data were transformed into the PAT ratio, an established marker of vascular function. Cardiopulmonary exercise testing was performed using the Bruce protocol. In the Fontan cohort, 94% of patients were New York Heart Association functional class I and 88% had a B-type natriuretic peptide level of <50 pg/ml. The baseline pulse amplitude, a measure that reflects the arterial tone at rest, was greater in the Fontan patients than in the controls (median 2.74, interquartile range 1.96 to 4.13 vs median 1.86, interquartile range 1.14 to 2.79, p = 0.03). The PAT ratio, a measure of reactive hyperemia, was lower in Fontan patients (median 0.17, interquartile range -0.04 to 0.44, vs median 0.50, interquartile range 0.27 to 0.74, p = 0.002). The key parameters of exercise performance, including peak oxygen consumption (median 28.8 ml/kg/min, interquartile range 25.6 to 33.2 vs median 45.5 ml/kg/min, interquartile range 41.7 to 49.9, p <0.0001) and peak work (median 192 W, interquartile range 150 to 246 vs median 330, interquartile range 209 to 402 W, p <0.0001), were lower in Fontan patients than in the controls. The PAT ratio correlated with the peak oxygen consumption (r = 0.28, p = 0.02) and peak work (r = 0.26, p = 0.03). In conclusion, in an asymptomatic Fontan population, there is evidence of reduced basal peripheral arterial tone and vasodilator response, suggesting dysfunction of the endothelium-derived nitric oxide pathway. Vasodilator function appears to correlate with exercise performance. © 2011 Elsevier Inc.

The promise of cardiovascular biomarkers in assessing children with cardiac disease and in predicting cardiovascular events in adults - Wilkinson, J.D.; Diamond, M.; Miller, T.L. (Progress in Pediatric Cardiology, 2011)
Cardiac and vascular biomarkers are used in the diagnosis, assessment, and prognosis of a variety of cardiovascular diseases in adults and children. For children, cardiac biomarkers are most often used to assess cardiomyopathy or congenital cardiovascular malformations or for monitoring during cardio-pulmonary bypass and pre- and post-heart transplantation. Because the risk for cardiovascular events in adulthood can be tracked from childhood, interest is high in identifying biomarkers of vascular inflammation in children that might also predict atherosclerotic events later in life. Here, we review the most common and promising biomarkers and comment on their current and potential uses in monitoring and predicting cardiovascular dysfunction. © 2011 Elsevier Ireland Ltd.
Keywords: Atherosclerosis; Biomarkers; Cardiomyopathy; Child; Congenital heart disease; Heart failure

Parenting children with hypoplastic left heart syndrome: Finding a balance - Lee, A.; Rempel, G.R. (Journal for Specialists in Pediatric Nursing, 2011)
Purpose. This study described the role normalization played for parents related to their young children with hypoplastic left heart syndrome. Design and Methods. The data source for this secondary analysis was 30 interviews with 16 parents. Results. Three themes were identified: normalization, parental perception of child vulnerability, and optimistic appraisal. Parents engaged in a balancing act between worrying about their children's vulnerability and marveling at their children's survival, using normalization as a coping strategy. Practice Implications. Nurses can collaborate with parents to determine strategies to restore a sense of normalcy to simultaneously promote child independence and parent well-being. © 2011, Wiley Periodicals, Inc.
Keywords: Congenital heart disease; Hypoplastic left heart syndrome; Normalization; Parenting; Qualitative research; Secondary analysis

Catheter takedown in the management of the acutely failing Fontan circulation - Anderson, B.W.; Barron, D.J.; Jones, T.J.; Edwards, L.; Brawn, W.; Stumper, O. (Annals of Thoracic Surgery, 2011)
The acutely failing Fontan circulation requires urgent management to decompress the systemic venous pressures and augment cardiac output. This may involve the use of extracorporeal membrane oxygenation support to preserve life. Catheter-based effective Fontan takedown is an alternative to surgery in these patients, who are acutely unstable, and offers the potential for an adjustable fenestration. © 2011 The Society of Thoracic Surgeons.

Heart transplantation in biventricular congenital heart disease: Indications, techniques, and outcomes - Mora, B.N.; Huddleston, C.B. (Current Cardiology Reviews, 2011)
Heart transplantation is an accepted therapeutic modality for end-stage congenital heart disease for both biventricular and univentricular anomalies. Many transplant centers have pushed the limits of transplantation to include patients with high pulmonary vascular resistance, high panel reactive antibodies, positive cross-matches, and ABOincompatibility. Excellent results have been possible, particularly with the development of improved diagnostic and therapeutic algorithms to prevent and treat rejection, infection, and post-transplant lymphoproliferative disease. Late graft failure and chronic rejection remain vexing problems. The vast majority of patients with biventricular congenital heart disease have undergone prior cardiac surgical procedures. Indications for transplantation in this subgroup are primarily progressive refractory heart failure following prior cardiac surgical reconstructive procedures. Contraindications to transplantation mimic those for other forms of end-stage heart disease. A determination of pulmonary vascular resistance is important in listing patients with biventricular congenital heart disease for heart transplantation. Modifications in the implant technique are necessary and vary depending on underlying recipient anatomy. Risk factors for perioperative outcomes in patients with biventricular congenital heart disease include the need for reoperation, the degree of anatomic reconstruction necessary during the implant procedure, and the degree of antibody sensitization, in addition to a number of other recipient and donor factors. Postoperative outcomes and survival are very good but remain inferior to those with cardiomyopathy in most series. In conclusion, patients with end-stage biventricular congenital heart disease represent a complex group of patients for heart transplantation, and require careful evaluation and management to ensure optimal outcomes. © 2011 Bentham Science Publishers.
Keywords: Biventricular; Cardiac transplantation; Congenital heart disease; Failing ventricle; Heart failure; Heart transplant; Orthotopic heart transplantation; Pediatric cardiac surgery; Perioperative and long-term outcomes

The quality of life of young children and infants with chronic medical problems: Review of the literature - Payot, A.; Barrington, K.J. (Current Problems in Pediatric and Adolescent Health Care, 2011)
The question "what makes a good quality of life?" is a philosophical one which could be thought immune to scientific investigations. However, over the last few decades there has been great progress in developing tools to quantify quality of life (QoL) to make comparisons between different health states, evaluate the effectiveness of medical interventions, and describe the life trajectories of individuals or groups. Using a series of vignettes, we explore and review the biomedical literature to demonstrate how QoL is affected by chronic health conditions in childhood, and how it evolves as individuals pass into adulthood. Individuals experiencing serious chronic illnesses generally have reduced health-related QoL: their health status has significant repercussions of their everyday life, but scores are usually much better than healthy individuals expect, and better than physicians predict. Global QoL is more than a health status concept. QoL is a complex relationship between objectivity and subjectivity; it requires substantial and valid facts, and it defines itself by an interpretation of health within different schemes of values: societal, medical, and those of the subject themselves. QoL is dynamic; purely physical influences diminish as individuals age, and psychosocial factors become much more important. Resilience frequently allows adaptation to adverse health states, leading to acceptable QoL for most children with disabilities. © 2011 Mosby, Inc. All rights reserved.

Endoscopic treatment of plastic bronchitis - Silva, R.C.; Simons, J.P.; Chi, D.H.; Yellon, R.F.; Alper, C.M. (Archives of Otolaryngology - Head and Neck Surgery, 2011)
Plastic bronchitis is a rare condition, characterized by the formation of thick mucus plugs that cause airway obstruction. It is seen in a variety of disorders, including congenital cyanotic heart disease following palliative surgery. We describe the case of a 5-year-old child with hypoplastic left-heart syndrome who had undergone a Fontan procedure and developed recurrent bronchial cast formation. These casts were treated aggressively with repeated rigid bronchoscopy and adjuvant medical therapy. We present a brief review of the pathogenesis, treatment options, and description of the challenges involved with endoscopic removal of bronchial casts. ©2011 American Medical Association. All rights reserved.

Experience with bidirectional cavopulmonary anastomosis and modified Fontan operation in patients with single ventricle and concomitant visceral heterotaxy - Yurlov, I.A.; Podzolkov, V.P.; Zelenikin, M.M.; Kovalev, D.V.; Babaev, G.K.; Putiato, N.A.; Zaets, S.B. (Interactive Cardiovascular and Thoracic Surgery, 2011)
The object of our study was to analyze the results of bidirectional cavopulmonary anastomosis (BCPA) and modified Fontan operations (MFO) in patients with a functionally single ventricle and heterotaxy syndrome and to reveal risk factors for these surgical interventions. During 1983-2010, 681 patients underwent BCPA or MFO. Thirty-nine had heterotaxy syndrome. The median follow-up period after BCPA and MFO was nine and 1.5 years, respectively. Risk factors for lethal outcomes were determined by logistic regression analysis. Hospital mortality after BCPA and MFO was 7.9% and 12.5%, respectively and did not significantly differ from patients without heterotaxy. The most frequent hospital complications were heart failure, pleural effusions, and arrhythmias. Late mortality after BCPA and MFO was 8.7% and did not significantly differ from patients without heterotaxy. Late deaths were caused by congestive heart failure or pulmonary thromboembolism. The main non-lethal complication was arrhythmia. Patients have significantly improved their functional class at followup. The independent risk factor for lethal outcomes after BCPA and MFO was preoperative regurgitation at atrioventricular valves (P=0.012). BCPA and MFO in patients with a functionally single ventricle and heterotaxy syndrome allow to significantly improves their quality of life. Preoperative regurgitation at atrioventricular valves worsens surgical results. © 2011 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Bidirectional cavopulmonary anastomosis; Heterotaxy syndrome; Left isomerism; Modified Fontan operation; Right isomerism; Single ventricle

Impact of oral sildenafil on exercise performance in children and young adults after the fontan operation: A randomized, double-blind, placebo-controlled, crossover trial - Goldberg, D.J.; French, B.; McBride, M.G.; Marino, B.S.; Mirarchi, N.; Hanna, B.D.; Wernovsky, G.; Paridon, S.M.; Rychik, J. (Circulation, 2011)
Background-: Children and young adults with single-ventricle physiology have abnormal exercise capacity after the Fontan operation. A medication capable of decreasing pulmonary vascular resistance should allow improved cardiac filling and improved exercise capacity. Methods and results-: This study was a double-blind, placebo-controlled, crossover trial conducted in children and young adults after Fontan. Subjects were randomized to receive placebo or sildenafil (20 mg three times daily) for 6 weeks. After a 6-week washout, subjects crossed over for an additional 6 weeks. Each subject underwent an exercise stress test at the start and finish of each phase. After taking sildenafil, subjects had a significantly decreased respiratory rate and decreased minute ventilation at peak exercise. At the anaerobic threshold, subjects had significantly decreased ventilatory equivalents of carbon dioxide. There was no change in oxygen consumption during peak exercise, although there was a suggestion of improved oxygen consumption at the anaerobic threshold. Improvement at the anaerobic threshold was limited to the subgroup with single left or mixed ventricular morphology and to the subgroup with baseline serum brain natriuretic peptide levels 100 pg/mL. Conclusions-: In this cohort, sildenafil significantly improved ventilatory efficiency during peak and submaximal exercise. There was also a suggestion of improved oxygen consumption at the anaerobic threshold in 2 subgroups. These findings suggest that sildenafil may be an important agent for improving exercise performance in children and young adults with single-ventricle physiology after the Fontan operation. © 2011 American Heart Association, Inc.
Keywords: exercise; Fontan procedure; physiology; trials

Longitudinal findings from a Norwegian case-cohort study on internalizing problems in children with congenital heart defects - Stene-Larsen, K.; Brandlistuen, R.E.; Holmstrøm, H.; Landolt, M.A.; Eskedal, L.T.; Engdahl, B.; Vollrath, M.E. (Acta Paediatrica, International Journal of Paediatrics, 2011)
Aim: To examine the association of the severity of congenital heart defects (CHDs) with internalizing problems in 18-month-olds and to explore the extent to which the internalizing problems are influenced by maternal distress and emotional reactivity in the child at age 6 months. Methods: We linked prospective data from the Norwegian Mother and Child Cohort Study, conducted by the Norwegian Institute of Public Health, with a nationwide CHD registry and identified 198 18-month-olds with CHDs in a cohort of 47 692 toddlers. Maternal reports on the children's emotional reactivity at age 6 months, the children's internalizing problems (anxiety, sleep problems, emotional reactivity) at age 18 months and maternal distress were assessed by questionnaires. Results: We found an association at age 18 months between the severity of the CHD and anxiety but not sleep problems or emotional reactivity. Children with severe but not with mild or moderate CHDs were twice as likely to experience the symptoms of anxiety compared with controls. These symptoms are not merely sequelae of earlier psychological reactions or concurrent maternal distress. Conclusion: Should these findings be replicated, future studies ought to investigate the mechanisms leading to elevated anxiety in toddlers with CHDs. In addition, clinical interventions should address the child's anxiety as well as the interaction between the parents and the child. © 2010 Foundation Acta Pædiatrica.
Keywords: Child internalizing problems; Congenital heart defects (CHD)

Disturbance of glucose homeostasis after pediatric cardiac surgery - Verhoeven, J.J.; Hokken-Koelega, A.C.S.; Den Brinker, M.; Hop, W.C.J.; Van Thiel, R.J.; Bogers, A.J.J.C.; Helbing, W.A.; Joosten, K.F.M. (Pediatric Cardiology, 2011)
This study aimed to evaluate the time course of perioperative blood glucose levels of children undergoing cardiac surgery for congenital heart disease in relation to endogenous stress hormones, inflammatory mediators, and exogenous factors such as caloric intake and glucocorticoid use. The study prospectively included 49 children undergoing cardiac surgery. Blood glucose levels, hormonal alterations, and inflammatory responses were investigated before and at the end of surgery, then 12 and 24 h afterward. In general, blood glucose levels were highest at the end of surgery. Hyperglycemia, defined as a glucose level higher than 8.3 mmol/l (>150 mg/dl) was present in 52% of the children at the end of surgery. Spontaneous normalization of blood glucose occurred in 94% of the children within 24 h. During surgery, glucocorticoids were administered to 65% of the children, and this was the main factor associated with hyperglycemia at the end of surgery (determined by univariate analysis of variance). Hyperglycemia disappeared spontaneously without insulin therapy after 12-24 h for the majority of the children. Postoperative morbidity was low in the study group, so the presumed positive effects of glucocorticoids seemed to outweigh the adverse effects of iatrogenic hyperglycemia. © 2010 The Author(s).
Keywords: Cardiac surgery; Child; Critical illness; Glucocorticoids; Hyperglycemia; Insulin

The severe end of the spectrum: Hypoplastic left heart in Potocki-Lupski syndrome - Sanchez-Valle, A.; Pierpont, M.E.; Potocki, L. (American Journal of Medical Genetics, Part A, 2011)
Potocki-Lupski syndrome (PTLS) is a recently described microduplication syndrome associated with duplication 17p11.2, including the RAI1 gene. Features of PTLS include hypotonia, feeding difficulties, failure to thrive, developmental delay and behavioral abnormalities including autistic spectrum disorder, anxiety, and inattention. Cardiovascular anomalies were not recognized as a feature of duplication 17p11.2 until 2007 when noted in over 50% of a clinically characterized cohort. We report a patient with hypoplastic left heart syndrome whose diagnosis of PTLS was delayed until a genetic evaluation at age 4 years because of severe expressive language impairment. We suggest that array comparative genomic hybridization be performed in infants with severe congenital heart defects. © 2011 Wiley-Liss, Inc.
Keywords: Autism; Chromosome 17p duplication; Failure to thrive; Hypoplastic left heart syndrome; Left ventricular outflow track; RAI1

Successful use of extracorporeal membrane oxygenation for pH1N1-induced refractory hypoxemia in a child with hypoplastic left heart syndrome - Gandhi, N.N.; Hartman, M.E.; Williford, W.L.; Peters, M.A.; Cheifetz, I.M.; Turner, D.A. (Pediatric Critical Care Medicine, 2011)
Objective: To report the first successful use of extracorporeal membrane oxygenation for acute respiratory distress syndrome secondary to 2009 pH1N1 influenza A infection in a child status post the Fontan operation for hypoplastic left heart syndrome. Design: Individual case report. Setting: Pediatric intensive care unit. PATIENT:: We describe a 7-yr-old boy with a history of the Fontan operation for hypoplastic left heart syndrome admitted with acute respiratory distress syndrome secondary to 2009 pH1N1 influenza A infection. Intervention: Cannulation for venoarterial extracorporeal membrane oxygenation. Measurements and Main Results: In this patient with a history of complex congenital heart disease and repair, extracorporeal membrane oxygenation was a successful rescue therapy for refractory pH1N1-induced respiratory failure. Conclusion: Extracorporeal membrane oxygenation can be successfully applied for refractory respiratory failure, even in the setting of significant underlying comorbidity. With emerging data to support the role of extracorporeal membrane oxygenation in improving mortality for refractory hypoxemia secondary to pH1N1, it is prudent to strongly consider the use of extracorporeal support in patients with underlying diseases or comorbidities that may have previously precluded them from being candidates for this therapy. © 2011 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: acute lung injury; acute respiratory distress syndrome; congenital heart disease; extracorporeal membrane oxygenation; Fontan procedure; H1N1 influenza; hypoplastic left heart syndrome; hypoxemia; mechanical ventilation; pediatric; pneumonia

Clinical profile of the adolescent/adult fontan survivor - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Koniak-Griffin, D.; Lewis, A.B.; Child, J.S. (Congenital Heart Disease, 2011)
Objectives. The study aims to describe the clinical profile of the adult Fontan survivor and identify the worries, symptoms, and the impact of cardiac surveillance most commonly experienced. Design. A descriptive, cross-sectional design was used. Setting. The study was performed in outpatient adult and pediatric cardiology clinics in university-affiliated and private practice offices. Patients. Fifty-four adolescent and adult patients with single ventricle congenital heart disease who have undergone the Fontan procedure participated in the study. The mean age was 26 ± 9 years with 52% female and 63% Caucasian. Outcome Measures. Demographic and clinical data were obtained by a standard intake form and retrospective chart reviews. The Congenital Heart Disease TNO/AZL Adult Quality Of Life questionnaire was completed to assess worries, symptoms, and the impact of cardiac surveillance. Results. The majority were single (73%), employed or full-time students (93%), with health insurance (94%), had a single left ventricle (78%), the diagnosis of tricuspid atresia or double inlet left ventricle (59%), lateral tunnel Fontan type (44%), history of arrhythmias (76%), left ventricle ejection fraction percentage >50 (66%), oxygen saturations >90% (70%), frequent headaches (50%), scoliosis (22%), varicose veins, ascites, and liver cirrhosis (46%), normal body mass index (59%), and New York Heart Association class I (48%) and II-III (52%). Primary worries related to current health (83%), job/employment (69%), ability to work, (61%) and living independently (54%). The most bothersome symptoms were shortness of breath with ambulation (69%), dizziness (61%), and palpitations (61%). Conclusions. Fontan survivors experience residua and sequelae from multiple surgical procedures and the natural disease course. Our results support the need for ongoing assessment of both physical symptoms and psychosocial concerns, and suggest the need for multiple risk factor intervention strategies that improve physical and emotional health in Fontan survivors © 2011 Copyright the Authors. Congenital Heart Disease © 2011 Wiley Periodicals, Inc.
Keywords: Congenital Heart Disease; Fontan; Health-related Quality of Life; Single Ventricle

Self perception and quality of life of adolescents who had undergone open-heart surgery due to cyanotic congenital heart disease in their infancy - Yildiz, C.E.; Zahmacioǧlu, O.; Koca, B.; Oktay, V.; Gökalp, S.; Eroǧlu, A.G.; Çetin, G.; Öztunç, F. (Turk Pediatri Arsivi, 2011)
Aim: To assess together with their parents, the quality-of-life of the teenage patients who had undergone open heart surgery because of cyanotic heart disease during their infancy and to compare their self-perception to that of physically healthy control group. Material and Method: This study includes 53 patients who had undergone operation for cyanotic congenital heart disease in Istanbul University, Institute of Cardiology, between 1989-1994. The relatives and the patients were informed with a consent form approved by Istanbul University, Cerrahpaşa Medical Faculty, Clinical Studies, Ethics Commitee (Decree no. D-005, Date: 11-10-2009). Group 1 was the healthy control group (15 patients, median age: 19 years, 8 months), Group 2 included patients with single ventricle who had undergone Fontan procedure (20 patients, median age: 19 years, 6 months; 10 of them had tricuspid atresia, five of them had pulmonary atresia with intact ventricular septum, three of them had double inlet left ventricle, one of them had double outlet right ventricle, one of them had ventricular septal defect and pulmonary atresia), group 3 included patients who had undergone operation for congenital cyanotic heart disease (33 patients, median age: 19 years, 2 months; 18 of them had transposition of the great arteries, 10 of them had tetralogy of Fallot, two of them had complete atrioventricular canal defect and pulmonary stenosis, two of them had double outlet right ventricle, one of them had pentalogy of Fallot). In this study, the quality of life and self perception scales were used. Quality of life scale was filled by patients, healthy adolescents and their parents separately. Self perception scale was only filled by patients and healthy adolescents. The comparison of age and self perception scores between the groups was carried out with unidirectional Analysis of variance (ANOVA) and the multicomparisons with LSD (Least Significant Difference). Since the quality of life variable does not have a normal distribution, the comparions were carried out with Kruskal-Wallis nonparametric ANOVA test and the multicomparisons with Dunn's test. Results: There was not a significant difference between the groups in terms of age and sex. In the quality of life scale (QOLS), for the replies to related questions, a significant difference was determined between the groups. The replies of group 2 and 3 for about quality of life of both children and the parents were far more negative when compared to those of the control group. When the groups were compared via multiple comparison tests, there was no significant difference between group 2 and 3. The replies of the parents regarding their children's quality of life, were statistically more negative than those of their children (p<0.001). Within the self perception scale, between group 1 and 3, there were significant differences about the social acceptance, behaviours in relationships and general self perception (p=0.03, p=0.03 and p=0.01; respectively). The most significant difference that was detected between group 1 and 2, was about the behaviour in relationships (p=0.04). Conclusions: With the help of developing technology, and surgical experience, many complex cyanotic heart diseases are treated successfully and most patients reach puberty. However the responses for quality of life and self perception paremeters of this group of patients are more negative than those of the control group. Therefore, these adolescents and especially their parents may need psychosocial support.
Keywords: Adolescent; Congenital heart disease; Cyanosis; Quality of life; Self-perception profile

Grandparents and siblings of children with congenital heart disease - Ravindran, V.P.; Rempel, G.R. (Journal of Advanced Nursing, 2011)
Aim: This paper is a report of a study of the process of grandparent involvement with siblings of preschool children with hypoplastic left heart syndrome. Background: An increasing number of grandparents are involved in parental or near-parental roles with their grandchildren. Most research concerns grandparent involvement due to parental issues (e.g. teenage pregnancy, mental illness, addiction). Some research addresses grandparent involvement when their grandchild is ill. Grandparents''double concern' for both their adult children and their ill grandchildren is reported in the literature. In this paper, we describe a third concern for grandparents: the sibling(s) of their sick grandchild. Method: Individual interviews were conducted in 2007 with 15 grandparents of six preschool children with complex congenital heart disease. Open and selective coding, categorization, and theoretical memoing were used to analyse the data. Findings: 'Stepping in as needed' and 'safeguarding relationships' were identified as two core categories related to grandparenting siblings of children with heart disease. Grandparents stepped into a parent role with toddler and preschool-aged siblings by attending to their daily care routines, recreational and play times, and relational needs while parents were occupied with their sick and hospitalized infants. Grandparents' concerted efforts to sustain parent-child and child-sibling relationships were also striking. Conclusion: Our findings extend the concept of 'double concern' to 'triple concern', and direct a research and practice focus towards the unexplored roles and needs of grandparents and siblings in families whose young children have life-threatening illnesses. © 2010 The Authors. Journal of Advanced Nursing © 2010 Blackwell Publishing Ltd.
Keywords: Congenital heart defect; Family-centred care; Grandparents; Grounded theory; Nursing; Siblings; Sick children

Postoperative mortality in children after 101,885 anesthetics at a tertiary pediatric hospital - Van Der Griend, B.F.; Lister, N.A.; McKenzie, I.M.; Martin, N.; Ragg, P.G.; Sheppard, S.J.; Davidson, A.J. (Anesthesia and Analgesia, 2011)
BACKGROUND: Mortality is a basic measure for quality and safety in anesthesia. There are few anesthesia-related mortality data available for pediatric practice. Our objective for this study was to determine the incidence of 24-hour and 30-day mortality after anesthesia and to determine the incidence and nature of anesthesia-related mortality in pediatric practice at a large tertiary institution. METHODS: Children ≤18 years old who had an anesthetic between January 1, 2003, and August 30, 2008, at the Royal Children's Hospital, Melbourne, Australia, were included for this study. Data were analyzed by merging a database for every anesthetic performed with an accurate electronic record of mortality of children who had ever been a Royal Children's Hospital patient. Cases of children dying within ≤30 days and 24 hours of an anesthetic were identified and the patient history and anesthetic record examined. Anesthesia-related death was defined as those cases whereby a panel of 3 senior anesthesiologists all agreed that anesthesia or factors under the control of the anesthesiologist more likely than not influenced the timing of death. RESULTS: During this 68-month period, 101,885 anesthetics were administered to 56,263 children. The overall 24-hour mortality from any cause after anesthesia was 13.4 per 10,000 anesthetics delivered and 30-day mortality was 34.5 per 10,000 anesthetics delivered. The incidence of death was highest in children ≤30 days old. Patients undergoing cardiac surgery had a higher incidence of 24-hour and 30-day mortality than did those undergoing noncardiac surgery. From 101,885 anesthetics there were 10 anesthesia-related deaths. The incidence of anesthesia-related death was 1 in 10,188 or 0.98 cases per 10,000 anesthetics performed (95%confidence interval, 0.5 to 1.8). In all 10 cases, preexisting medical conditions were identified as being a significant factor in the patient's death. Five of these cases (50%) involved children with pulmonary hypertension. CONCLUSIONS: Anesthesia-related mortality is higher in children with heart disease and in particular those with pulmonary hypertension. The lack of anesthetic-related deaths in children who did not have major comorbidities reinforces the safety of pediatric anesthesia in healthy children. Copyright © 2011 International Anesthesia Research Society.

Ischemic myocardial injuries after cardiac malformation repair in infants may be associated with oxidative stress mechanisms - Oliveira, M.S.; Floriano, E.M.; Mazin, S.C.; Martinez, E.Z.; Vicente, W.V.A.; Peres, L.C.; Rossi, M.A.; Ramos, S.G. (Cardiovascular Pathology, 2011)
Background: Despite advances in pediatric cardiac surgery, perioperative myocardial injury can be the major determinant of postoperative dysfunction after cardiac surgery. This study investigated the pathology-related differences in 29 infants with congenital heart disease that led to death. The infants were treated at the University Hospital of Ribeirão Preto, Brazil. Methods: The patients were divided into four groups: Group 1, 16 infants who underwent operations for congenital heart disease on cardiopulmonary bypass; Group 2, four infants who underwent off-cardiopulmonary bypass operations for congenital heart disease; Group 3, nine infants who died from congenital heart disease prior to surgical treatment; and Group 4 (control group), five infants with no congenital heart disease and who died from other causes. The myocardial injuries and oxidative stress mechanisms were assessed by histopathology and immunohistochemistry and were quantified by morphometrical analyses. Results: Contraction band necrosis and dystrophic calcification were found primarily in infants of Group 1. Coagulation necrosis and healing were prominent in Group 2, while infants without repair (Group 3) showed mainly colliquative myocytolysis. Apoptotic cells were more prominent in the operative groups. The control group showed no significant myocardial lesions. Lipid peroxidation was the principal mechanism of oxidative stress accounting for the myocardial lesions. Conclusion: The diversity of the lesions observed in these hearts seemed to indicate a large spectrum of cell damage due to inadequate myocardial perfusion, especially when these infants underwent surgery. Oxidative mechanisms could be a common mediator in the pathogenesis of myocardial injuries, mediated by peroxidation of the membrane phospholipids and resulting in changes in the permeability of the cell membrane, cell death, and intracellular calcium overload. Furthermore, an immature and often hypertrophied myocardium may promote unfavorable conditions, leading to heart failure and a lethal outcome. © 2011 Elsevier Inc. All rights reserved.
Keywords: Congenital heart disease; Infants; Ischemia; Lipid peroxidation; Myocardial injury; Oxidative stress

Growth differentiation factor 15-an early marker of abnormal function of the Fontan circuit in patients with univentricular hearts - Raedle-Hurst, T.M.; Koenigstein, K.; Gruenhage, F.; Raedle, J.; Herrmann, E.; Abdul-Khaliq, H. (American Heart Journal, 2010)
Background: In patients after the Fontan procedure, assessment of ventricular function is difficult and amino-terminal pro-B-type natriuretic peptide levels failed to be directly related to echocardiographic measures of systolic ventricular function. The aim of the study was to evaluate growth differentiation factor 15 (GDF-15), a marker of various stress pathways in the heart and extracardiac tissues. Methods: Plasma GDF-15 levels were measured in 38 consecutive patients after the Fontan procedure and compared to clinical, echocardiographic, and laboratory data; liver tissue stiffness; and venous hepatic flow velocities. Results: Mean GDF-15 levels were 987.2 ± 440.5 pg/mL in patients with an ejection fraction (EF) <50% as compared to 520.2 ± 143.1 pg/mL in those with an EF ≥50% (P < .001). Growth differentiation factor 15 levels were significantly related to the EF of the single ventricle (r = -0.66, P < .001), New York Heart Association functional class (r = 0.43, P = .008), and γGT levels (r = 0.50, P = .002) but weakly to liver tissue stiffness. According to receiver operating characteristic curve analysis, an EF <50% was best predicted by GDF-15 levels (area under the curve [AUC] 0.90, P < .001), peak venous hepatic flow at deep inspiration (AUC 0.89, P = .002), and age at Fontan operation (AUC 0.86, P = .001). Growth differentiation factor 15 and age at Fontan operation proved to be independent predictors in the multivariate analysis. The optimal cutoff of GDF-15 for the prediction of an EF <50% was calculated to be 613 pg/mL with a sensitivity of 90.0% and specificity of 85.7%. Conclusions: Growth differentiation factor 15 might be helpful in detecting early abnormal function of the Fontan circuit in patients with univentricular hearts. In patients with GDF-15 levels exceeding 613 pg/mL, further cardiac evaluation should be considered because impaired systolic function of the single ventricle may be present. © 2010 Mosby, Inc.

Congenital heart surgery in the adult - Fraser, C.D.; Carberry, K.E. (Texas Heart Institute Journal, 2010)

Filament support spindle for an intravascular cavopulmonary assist device - Throckmorton, A.L.; Kapadia, J.Y.; Wittenschlaeger, T.M.; Medina, T.J.; Hoang, H.Q.; Bhavsar, S.S. (Artificial Organs, 2010)
We are developing an intravascular axial flow blood pump to support adolescent and adult Fontan patients. To protect the blood vessel, this pump has an outer cage with radially arranged filaments and a newly designed spindle at the pump outlet. The outlet spindle is included to limit the axial movement of the rotor and to house bearings that support the rotor. This study evaluates the impact of the outlet spindle on pump performance using computational fluid dynamics (CFD) and experimental testing of a prototype configuration. We measured the pressure-flow performance of the prototype with a protective cage using a blood analog fluid. The pump with the cage filaments and spindle generated 1 to 16 mm Hg of pressure rise for flow rates of 1 to 4 L/min at 4000 to 7000 rpm. The difference between the CFD predictions and experimental results was found to be approximately 9.8%. Scalar stress levels remained below 570 Pa with exposure times on the order of 1.5 s. These results are acceptable and support the continued development of this cavopulmonary assist device with an outlet spindle to reinforce the protective cage filament design. © 2010, the Authors. Artificial Organs © 2010, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Artificial right ventricle; Cavopulmonary assist device; Fontan completion; Heart pump; Intravascular blood pump; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Ventricular assist device

Examination of the physical and psychosocial determinants of health behaviour in 4-5-year-old children with congenital cardiac disease - Casey, F.A.; Stewart, M.; McCusker, C.G.; Morrison, M.L.; Molloy, B.; Doherty, N.; Craig, B.G.; Sands, A.J.; Rooney, N.; Mulholland, H.C. (Cardiology in the Young, 2010)
Objectives: To assess the general health and activity levels of 4- and 5-year-old children after intervention for congenital cardiac disease. Methods: Health behaviour outcomes were assessed in 91 children who had surgery or catheter intervention for congenital cardiac disease. The children were classified into four groups according to severity. The main parameters of classification were the presence of residual symptoms, frequency of visits to general practitioner or the Accident and Emergency Department, and ability to participate in physical activity according to a calculated "activity score". Results: Children had very few residual symptoms after "corrective surgery". Those with complex congenital cardiac disease post-Fontan-type repair still had symptoms on average 18.2 days per month. Surprisingly, the complex group had fewer days "sick" from non-cardiac causes and had fewer visits to general practitioner or Accident and Emergency Departments. Regression analysis indicates that three variables had significant relevance to the general practitioner or Accident and Emergency visits: complex congenital cardiac disease, fewer visits; Townsend score - more deprivation - more visits; and maternal worry - higher maternal worry score - more visits. Regression analysis indicates that lower activity score is significantly related to complex cardiac disease and higher maternal worry score. Conclusions: The majority of this group of 4- and 5-year-old children had few residual symptoms and had good exercise tolerance. Maternal worry is a significant factor in influencing both activity levels and frequency of unscheduled health service demands - general practitioner or Accident and Emergency visits. Copyright © Cambridge University Press 2010.
Keywords: activity; outcomes; Paediatric cardiology; psychological well-being

Transthoracic echocardiographic assistance for interatrial stenting in low birth-weight neonates with hypoplastic left heart syndrome and intact atrial septum - Petit, C.J.; Altman, C.A.; Pignatelli, R.H. (Catheterization and Cardiovascular Interventions, 2010)
Infants with hypoplastic left heart syndrome and intact or highly restrictive atrial septum require emergent therapy to relieve pulmonary congestion. Transcatheter stenting has become, in most large centers, the mainstay of therapy for relief of left atrial hypertension. Normally, this procedure is performed with the assistance of transesophageal echocardiographic guidance. However, the transesophageal approach is untenable in neonates of low birth weight, as the transducers can be traumatic and can cause ventilatory difficulty. We present two cases in which transthoracic echocardiographic guidance was used to guide atrial perforation and stenting in low birth-weight neonates with hypoplastic left heart syndrome with intact or highly restrictive atrial septum. Both procedures were straightforward and there were no complications. Real-time biplane imaging greatly assisted in the intervention in one case. The advantages of this approach are discussed. © 2010 Wiley-Liss, Inc.
Keywords: Intracardiac echo; Pediatric interventions; Transeptal cath

Pulmonary vascular resistance, collateral flow, and ventricular function in patients with a fontan circulation at rest and during dobutamine stress - Schmitt, B.; Steendijk, P.; Ovroutski, S.; Lunze, K.; Rahmanzadeh, P.; Maarouf, N.; Ewert, P.; Berger, F.; Kuehne, T. (Circulation: Cardiovascular Imaging, 2010)
Background-The role, interplay, and relative importance of the multifactorial hemodynamic and myocardial mechanisms causing dysfunction of the Fontan circulation remain incompletely understood. Methods and Results-Using an MRI catheterization technique, we performed a differential analysis of pulmonary vascular resistance and aortopulmonary collateral blood flow in conjunction with global ventricular pump function, myocontractility (end-systolic pressure-volume relation), and diastolic compliance (end-diastolic pressure-volume relation) in 10 patients with a Fontan circulation at rest and during dobutamine stress. Pulmonary and ventricular pressures were measured invasively and synchronized with velocity-encoded MRI-derived pulmonary and aortic blood flows and cine MRI-derived ventricular volumes. Pulmonary vascular resistance and end-systolic and end-diastolic pressure-volume relations were then determined. Aortopulmonary collateral flow was calculated as the difference between aortic and pulmonary flow. Compared to rest, dobutamine caused a small increase in mean pulmonary pressures (P<0.05). Collateral flow was significantly augmented (P<0.001) and contributed importantly to an increase in pulmonary flow (P<0.01). Pulmonary vascular resistance decreased significantly (P<0.01). Dobutamine did not increase stroke volumes significantly despite slightly enhanced contractility (end-systolic pressure-volume relation). Active early relaxation (τ) was inconspicuous, but the end-diastolic pressure-volume relation shifted upward, indicating reduced compliance. Conclusions-In patients with a Fontan circulation, aortopulmonary collateral flow contributes substantially to enhanced pulmonary flow during stress. Our data indicate that pulmonary vascular response to augmented cardiac output was adequate, but decreased diastolic compliance was identified as an important component of ventricular dysfunction. © 2010 American Heart Association, Inc.
Keywords: Congenital; Heart defects; Heart failure; Magnetic resonance imaging; Pulmonary heart disease

Differential changes in TGF-β/BMP signaling pathway in the right ventricular myocardium of newborns with hypoplastic left heart syndrome - Ricci, M.; Mohapatra, B.; Urbiztondo, A.; Birusingh, R.J.; Morgado, M.; Rodriguez, M.M.; Lincoln, J.; Vatta, M. (Journal of Cardiac Failure, 2010)
Background: Hypoplastic left heart syndrome (HLHS) is characterized by underdevelopment of the left ventricle (LV) and increased biomechanical stress on the right ventricle (RV) from single ventricle physiology. Despite the clinical significance, the signaling pathways active during RV remodeling and disease progression are not known. To address this, we examined differential changes in expression of genes associated with transforming growth factor-β (TGF-β)/bone morphogenetic protein (BMP) signaling in RV tissue isolated from HLHS patients relative to RV and LV tissue from control subjects. Methods and Results: Quantitative real-time polymerase chain reaction was used to detect changes in expression of 84 genes involved in TGF-β/BMP-mediated cardiac development, cell growth, and differentiation in RV tissue collected from 6 neonates with HLHS undergoing stage 1 Norwood procedure (age, 1-7 days; mean, 4 days) and RV and LV tissue obtained from 5 infants with noncardiac pathology (age range, 1-135 days: mean, 85 days) that served as controls. Analysis of gene expression profiles between control-LV and control-RV revealed significant depression of TGF-β/BMP signaling in RV compared with LV. Of the 84 genes analyzed, 38 were differentially expressed between HLHS-RV and control-RV, whereas only 22 compared with control-LV. Significant changes were observed in: tissue remodeling genes including Activin receptor type IIA (ACVR2A) (+2.13) and Activin receptor-like kinase 1 (ACVRL1) (+2.22); and cell survival, growth, and differentiation genes including CDC25A (+2.18), p21 (-3.64), p15 (+2.15), BMP5 (+4.58), BMP3 (+2.16), GDF3 (+8.59), NODAL (+2.32), and BMP binding endothelial regulator (BMPER) (+4.58). The most significant changes common to HLHS-RV versus control-RV and control-LV sample groups is observed for Anti müllerian hormone receptor 2 (AMHR2) (+18.79 control-RV, +3.38 control-LV), and the BMP antagonist Inhibin alpha (INHA) (+11.47 control-RV, +5.73 control-LV). Conclusions: Although this descriptive study does not allow cause-effect inferences, our results suggest changes in cardiac development pathways and upregulation of genes associated with cell growth and differentiation in the neonatal RV of children with HLHS. These molecular profiles are more closely related to those observed in the normal LV rather than normal RV at similar maturational age. This work provides the basis for future mechanistic studies to elucidate the molecular mechanisms regulating RV remodeling in HLHS. © 2010 Elsevier Inc. All rights reserved.
Keywords: gene expression; heart failure; Hypoplastic left heart

Hepatic adenomatosis in a 7-year-old child treated earlier with a fontan procedure - Babaoglu, K.; Binnetoglu, F.K.; Aydoǧan, A.; Altun, G.; Gürbüz, Y.; Inan, N.; Çorapçioǧlu, F. (Pediatric Cardiology, 2010)
Patients who undergo a Fontan procedure experience some degree of liver disease. Hemodynamic changes such as central venous hypertension, depressed dynamic cardiac output, and late ventricular dysfunction combined with long-standing hypoxia preceding the Fontan procedure all are recognized risk factors for hepatic injury. The histopathologic changes associated with cardiac hepatopathy include chronic passive congestion, centrilobular necrosis, and cardiac cirrhosis. However, hepatic adenoma and hepatic adenomatosis (HA) are not well-known pathologies during the course of cardiac hepatopathy. This study focused on a 7-year-old girl with chronic hepatic changes and HA who had undergone a Fontan procedure. Hepatic adenomatosis was diagnosed on the basis of magnetic resonance imaging (MRI) and MRI-guided liver biopsy. To the best of the authors' knowledge, this case involved the youngest patient with hepatocellular adenomatosis documented in the literature. It was a unique case because the patient experienced HA after a Fontan procedure. © 2010 Springer Science+Business Media, LLC.
Keywords: Cardiac cirrhosis; Fontan procedure; Hepatic adenomatosis

Aggressive bronchoscopic management of plastic bronchitis - Preciado, D.; Verghese, S.; Choi, S. (International Journal of Pediatric Otorhinolaryngology, 2010)
Plastic bronchitis or " Bronchitis Plastica" is a rare disease characterized by the formation of thick, tenacious, arborizing mucofibrinous tracheobronchial casts that result in life-threatening airway obstruction and pulmonary failure. We review three children who developed recurrent plastic bronchitis after undergoing a Fontan procedure for single ventricle physiology. Case series of three patients with plastic bronchitis at a tertiary referral children's hospital. All patients required repeated bronchoscopies, one requiring four separate ones over a week's period, for removal of the rigid casts. Extra-corporal membrane oxygenation (ECMO) was needed in two children because of severe respiratory failure. All were also managed with adjunctive intensive medical support. Pulmonary function returned to normal in all children, but recurred 2 months later in one who subsequently expired due to pulmonary failure. Plastic bronchitis is an unusual condition of unknown cause that occurs in multiple clinical settings, but especially in those children who have undergone a Fontan operation. Management of this distressing situation is difficult and early diagnosis and aggressive measures to remove rigid casts combined with intensive medical care are necessary. The intrinsic cardiopulmonary physiology of children with Fontan procedures, including the risk of arrhythmias, hypo-oxygenation, and pulmonary hypertension make this condition even more complex. © 2010 Elsevier Ireland Ltd.
Keywords: Bronchial casts; Fontan; Plastic bronchitis

Constrained optimization of an idealized Y-shaped baffle for the Fontan surgery at rest and exercise - Yang, W.; Feinstein, J.A.; Marsden, A.L. (Computer Methods in Applied Mechanics and Engineering, 2010)
Coupling shape optimization to three-dimensional unsteady cardiovascular simulations poses several key challenges, including high computational cost, a need to handle constraints, and a need for automatic generation of parameterized vessel geometry. In this work we extend our previous framework for cardiovascular optimization to include constraints, pulsatile flow under both rest and exercise conditions, and multiple geometric parameters. Optimization is performed using a derivative-free algorithm called the surrogate management framework, with constraints enforced using a filter method. In this work, we examine a specific surgery called the Fontan, which is performed to treat single-ventricle heart patients. These patients typically undergo a series of three surgeries, the last of which connects the inferior vena cava to the pulmonary arteries. Our group and others have recently proposed and evaluated a new Y-graft modification of the Fontan operation that replaces the current tube shaped baffle. Preliminary simulations have shown that the Y-graft modification is a promising design that increases energy efficiency and improves flow distribution to the pulmonary arteries. In this work, we perform optimization on a model Y-graft design problem. This work represents the first use of formal design optimization methods for the Fontan surgery, and also demonstrates the applicability of the optimization framework on a pulsatile flow problem with multiple design parameters and constraints. The idealized Y-graft model was parameterized with six geometric parameters including graft diameter and anastomosis locations, and the optimization procedure, including model construction, meshing, and simulation, was executed automatically. Energy efficiency was chosen as the objective function. A constraint on the wall shear stress (WSS), a presumed correlate to thrombosis risk, was added to the problem using a filter method, which allowed for exploration of the trade-offs between WSS and energy efficiency. Optimization was performed at two exercise levels with effects of respiration incorporated, and differences in optimal solutions were examined. It was shown that optimal shapes differed between rest and exercise, as well as steady and pulsatile flow conditions, with wide-span branches and decreasing graft branch size favored with increasing exercise level. The optimization method was found to be robust for different polling strategies, and computationally efficient both with and without constraints. © 2010 Elsevier B.V.
Keywords: Cardiovascular surgery; CFD; Derivative-free optimization; Fontan surgery; Mesh adaptive direct search; Pediatric cardiology; Surrogate management framework

Dual-platform proteomics study of plasma biomarkers in pediatric patients undergoing cardiopulmonary bypass - Umstead, T.M.; Lu, C.-J.K.; Freeman, W.M.; Myers, J.L.; Clark, J.B.; Thomas, N.J.; Chinchilli, V.M.; Vrana, K.E.; Ündar, A.; Phelps, D.S. (Pediatric Research, 2010)
Plasma samples from pediatric cardiac patients undergoing cardiopulmonary bypass (CPB) procedures were used to identify and characterize patterns of changes in potential biomarkers related to tissue damage and inflammation. These included proteins associated with systemic inflammatory response syndrome. Potential biomarkers were identified using a dual-platform proteomics approach requiring ∼150 μL of plasma, which included two-dimensional difference gel electrophoresis (2D-DIGE) and a multiplexed immunoassay. Methods used in the dual approach measured levels of 129 proteins in plasma from pediatric CPB patients. Of these, 70 proteins changed significantly (p < 0.05) between time points, and 36 of these retained significance after the highly stringent Bonferroni correction [p < 0.001 for 2D-DIGE and p < 0.00056 for multianalyte profile (MAP) assays]. Many of the changing proteins were associated with tissue damage, inflammation, and oxidative stress. This study uses a novel approach that combines two discovery proteomics techniques to identify a pattern of potential biomarkers changing after CPB. This approach required only 150 μL of plasma per time point and provided quantitative information on 129 proteins. The changes in levels of expression of these proteins may provide insight into the understanding, treatment, and prevention of systemic inflammation, thereby helping to improve the outcomes of pediatric CPB patients. © 2010 International Pediatric Research Foundation, Inc.

Intravascular ultrasound catheter for transesophageal echocardiography in congenital heart surgery - A case report - Kim, H.-J.; Kim, J.-Y.; Baek, S.-H.; Kim, H.-K. (Korean Journal of Anesthesiology, 2010)
Transesophageal echocardiography (TEE) has an important role during congenital heart surgery. TEE in small infants is associated with complications, including an inability to pass the TEE probe, esophageal trauma, airway compression, aortic compression, and interference with ventilation. Recently, a monoplane intravascular ultrasound catheter (IVUC) has been developed for intracardiac echocardiography. The efficacy of IVUC for transesophageal use has been shown in numerous animal studies and several human studies, but there have been few reports involving small infants using an IVUC probe. We examined 15 pediatric patients undergoing congenital cardiac surgery using an 8-Fr AcuNav IVUC probe. We checked the cardiac anatomy, cardiac function pre-operatively and de-aeration before weaning from CPB; the surgical repairs were evaluated post-operatively. Although the IVUC probe has limitations associated with the monoplane, we found the IVUC probe to be useful in small infants and safer than the TEE. Copyright © Korean Society of Anesthesiologists, 2010.
Keywords: Congenital heart surgery; Intravascular ultrasound catheter; Transesophageal echocardiography

Hybrid procedures: Adverse events and procedural characteristics - results of a multi-institutional registry - Holzer, R.; Marshall, A.; Kreutzer, J.; Hirsch, R.; Chisolm, J.; Hill, S.; Galantowicz, M.; Phillips, A.; Cheatham, J.; Bergerson, L. (Congenital Heart Disease, 2010)
Introduction: Procedural cooperation between cardiac surgeon and interventional cardiologist to facilitate interventions such as device delivery or angioplasty (hybrid procedure) has become increasingly common in the management of patients with congenital heart disease. Design: Data were prospectively collected using a multicenter registry (C3PO). Between February 2007 and December 2008, seven institutions submitted data regarding 7019 cardiac catheterization procedures. Procedural data and adverse events (AEs) of 128 hybrid procedures were evaluated. Results: There was significant variability in the number of hybrid procedures per center, ranging from one to 89 with a median of eight. A total of 60% of interventional (vs. strictly diagnostic) hybrid procedures were performed by one center. The median weight was 3.7 kg (0.7-86 kg). Single-ventricle circulation was present in 60% of the procedures. Hybrid procedures included: patent ductus arteriosus (PDA) stent placement (n = 55), vascular rehabilitation (n = 25), ventricular septal defect (VSD) device closure (n = 7), valvotomy (n = 3), and diagnostic hybrid procedures (n = 38). Sixteen AEs occurred in 15/128 (12%) procedures. These included minor or trivial AEs (n = 9), moderate AEs (n = 5), major AEs (n = 1), and catastrophic AEs (n = 1). The type of AE documented included arrhythmias (n = 6), hypoxia or hypotension (n = 3), vessel or cardiac trauma (n = 2), and other events (n = 5). Of documented AEs, 9/16 (56%) were classified as not preventable, 6/16 (38%) as possibly preventable, and 1/16 (6%) as preventable. The incidence of AE related to PDA stent placement with surgical exposure (5/50, 10%) was significantly lower when compared with PDA stent placement performed percutaneously (4/5, 80%, P= .002). Conclusion: Hybrid procedures appear to have a low incidence of associated major AEs. PDA stent placement performed as a palliation of hypoplastic left heart syndrome (HLHS) or complex single/two ventricle patients may have a lower incidence of AEs if performed using a direct approach with surgical exposure rather than a percutaneous approach. Accurate definitions of these innovative procedures are required to facilitate prospective data collection. © 2010 Copyright the Authors. Journal Compilation © 2010 Wiley Periodicals, Inc.
Keywords: Adverse events; Cardiac catheterization; Hybrid procedures

Care of the Pediatric Cardiac Surgery Patient-Part 2 - Gazit, A.Z.; Huddleston, C.B.; Checchia, P.A.; Fehr, J.; Pezzella, A.T. (Current Problems in Surgery, 2010)

The BNP concentrations and exercise capacity assessment with cardiopulmonary stress test in cyanotic adult patients with congenital heart diseases - Trojnarska, O.; Gwizdala, A.; Katarzynski, S.; Katarzynska, A.; Oko-Sarnowska, Z.; Grajek, S.; Kramer, L. (International Journal of Cardiology, 2010)
Cyanosis is observed in patients with complex congenital heart disease (CHD) and pulmonary hypertension, heart failure represents an important clinical problem in such patients. The aim of this study was to evaluate the exercise capacity in patients with cyanotic CHDs using cardiopulmonary exercise test, measuring serum BNP levels as well as to seek correlation between BNP levels and cardiopulmonary exercise test parameters and identify the effects of blood oxygen desaturation and pulmonary hypertension on these indices. The study group consisted of 53 patients (21 males) at the mean age of 39.4±14.3 years, of whom 19 were operated on at the mean age of 9.6±8.6 years. Mean blood oxygen saturation (SO2) in patients was 81.2±6.2%. Twenty four patients presented with Eisenmenger syndrome, 16-univentricular hearts, 4-transposition of the great arteries, 6-Fallot's tetralogy, and 3-Ebstein anomaly. The control group comprised 32 healthy individuals (16 males) at the mean age of 40.7±9.9 years. Cardiopulmonary stress test showed significantly lower exercise capacity in patients with cyanosis than in controls: maximal oxygen uptake (VO2max) 15.5±4.9 vs. 31.6±7.1 ml/kg/min (p=0.00001), maximum heart rate at peak exercise (HR max): 139.5±22.5 bpm vs. 176.6±12.1 (p=0.0001), VE/VCO2 slope: 46.4±10.1 vs. 27.3±2.9 (p=0.00001), forced vital capacity FVC: 3.1±1.1 l vs. 4.4±0.8 l (p=0.00001). Subjects with the evidence of pulmonary hypertension (PH+) had lower exercise capacity than those without (PH-): VO2max: 17.2±4.2 vs. 12.8±4.8 ml/kg/min (p=0.002), VE/VCO2: 43.7±11.1 vs. 50.9±6.4 (p=0.01), FVC: 3.46±1.05 l vs. 2.37±0.91 l (p=0.0002). Plasma BNP levels in the study group were higher than in controls: 122.4±106.7 vs. 21.1±20.2 pg/ml p=0.00001 and did not differ between PH+ and PH- groups (115.7±99.0 vs. 127.9±114.1 pg/ ml p=0.78). Negative correlations between BNP levels and VO2max (r=-0.389, p=0.006), FVC (r=-0.395 p=0.005), FEV1 (r=-0.386 p=0.006), SO2 (r=-0.445 p=0.00001), and positive correlation between BNP level and VE/VCO2 (r=0.369 p=0.009) were found. © 2008 Published by Elsevier Ireland Ltd.
Keywords: BNP level in adult patients with congenital heart disease; Cardiopulmonary exercise test; Heart failure

A New Multiparameter Approach to Computational Simulation for Fontan Assessment and Redesign - Marsden, A.L.; Reddy, V.M.; Shadden, S.C.; Chan, F.P.; Taylor, C.A.; Feinstein, J.A. (Congenital Heart Disease, 2010)
Introduction: Despite an abundance of prior Fontan simulation articles, there have been relatively few clinical advances that are a direct result of computational methods. We address a few key limitations of previous Fontan simulations as a step towards increasing clinical relevance. Previous simulations have been limited in scope because they have primarily focused on a single energy loss parameter. We present a multi-parameter approach to Fontan modeling that establishes a platform for clinical decision making and comprehensive evaluation of proposed interventions. Methods: Time-dependent, 3-D blood flow simulations were performed on six patient-specific Fontan models. Key modeling advances include detailed pulmonary anatomy, catheterization-derived pressures, and MRI-derived flow with respiration. The following performance parameters were used to rank patients at rest and simulated exercise from best to worst performing: energy efficiency, inferior and superior vena cava (IVC, SVC) pressures, wall shear stress, and IVC flow distribution. Results: Simulated pressures were well matched to catheterization data, but low Fontan pressure did not correlate with high efficiency. Efficiency varied from 74% to 96% at rest, and from 63% to 91% with exercise. Distribution of IVC flow ranged from 88%/12% (LPA/RPA) to 53%/47%. A " transcatheter" virtual intervention demonstrates the utility of computation in evaluating interventional strategies, and is shown to result in increased energy efficiency. Conclusions: A multiparameter approach demonstrates that each parameter results in a different ranking of Fontan performance. Ranking patients using energy efficiency does not correlate with the ranking using other parameters of presumed clinical importance. As such, current simulation methods that evaluate energy dissipation alone are not sufficient for a comprehensive evaluation of new Fontan designs. © 2010 Copyright the Authors. Journal Compilation © 2010 Wiley Periodicals, Inc.
Keywords: Computational Fluid Dynamics; Exercise; Fontan Surgery; Hemodynamics; Patient-Specific Modeling

Optimization of inflow waveform phase-difference for minimized total cavopulmonary power loss - Dur, O.; DeGroff, C.G.; Keller, B.B.; Pekkan, K. (Journal of Biomechanical Engineering, 2010)
The Fontan operation is a palliative surgical procedure performed on children, born with congenital heart defects that have yielded only a single functioning ventricle. The total cavo-pulmonary connection (TCPC) is a common variant of the Fontan procedure, where the superior vena cava (SVC) and inferior vena cava (IVC) are routed directly into the pulmonary arteries (PA). Due to the limited pumping energy available, optimized hemodynamics, in turn, minimized power loss, inside the TCPC pathway is required for the best optimal surgical outcomes. To complement ongoing efforts to optimize the anatomical geometric design of the surgical Fontan templates, here, we focused on the characterization of power loss changes due to the temporal variations in between SVC and IVC flow waveforms. An experimentally validated pulsatile computational fluid dynamics solver is used to quantify the effect of phase-shift between SVC and IVC inflow waveforms and amplitudes on internal energy dissipation. The unsteady hemodynamics of two standard idealized TCPC geometries are presented, incorporating patient-specific real-time PC-MRI flow waveforms of "functional" Fontan patients. The effects of respiration and pulsatility on the internal energy dissipation of the TCPC pathway are analyzed. Optimization of phase-shift between caval flows is shown to lead to lower energy dissipation up to 30% in these idealized models. For physiological patient-specific caval waveforms, the power loss is reduced significantly (up to 11%) by the optimization of all three major harmonics at the same mean pathway flow (3 L/min). Thus, the hemodynamic efficiency of single ventricle circuits is influenced strongly by the caval flow waveform quality, which is regulated through respiratory dependent physiological pathways. The proposed patient-specific waveform optimization protocol may potentially inspire new therapeutic applications to aid postoperative hemodynamics and improve the well being of the Fontan patients. Copyright © 2010 by ASME.

Anatomic, Imaging, and Clinical Characteristics of Double-Inlet, Double-Outlet Right Ventricle - Saleeb, S.F.; Juraszek, A.; Geva, T. (American Journal of Cardiology, 2010)
The purposes of this study were to characterize the morphologic, imaging, and clinical characteristics of double-inlet, double-outlet right ventricle (DI-DORV), a rare congenital heart disease, and to compare these findings to those in patients with double-inlet left ventricle (DILV). The clinical records, imaging studies, and heart specimens of 22 consecutive patients with DI-DORV were reviewed. A comparison group of 44 patients with DILV was matched by age at latest follow-up. Among the 22 patients with DI-DORV, 14 had clinical data, 5 had clinical and autopsy data, and 3 had only autopsy data. Abdominal and atrial situs were normal in all, and heart position was levocardia in 91%. The morphology of the atrioventricular valves was variable, with 15 patients showing neither a typical tricuspid nor mitral valve. In the remaining 7 patients, 1 or both atrioventricular valves resembled a tricuspid or a mitral valve. Myocardial architecture was characterized by atypical muscle bundles of varying degrees of hypertrophy and orientation. Most patients had bilateral conus, and 82% had either aortic or pulmonary outflow tract obstructions. The rate of overall mortality or heart transplantation was 36%. Significant differences between DI-DORV and DILV included the type of ventricular loop, the type of conus, and a higher mortality rate in patients with DI-DORV. In conclusion, DI-DORV is a distinct type of functional single ventricle congenital heart disease with variable atrioventricular valve morphology and myocardial architecture. Accurate diagnosis using noninvasive imaging techniques is of paramount importance for optimal management. © 2010 Elsevier Inc. All rights reserved.

Validation of the pediatric cardiac quality of life inventory - Marino, B.S.; Tomlinson, R.S.; Wernovsky, G.; Drotar, D.; Newburger, J.W.; Mahony, L.; Mussatto, K.; Tong, E.; Cohen, M.; Andersen, C.; Shera, D.; Khoury, P.R.; et al. (Pediatrics, 2010)
OBJECTIVE: The purpose of this multicenter study was to confirm the validity and reliability of the Pediatric Cardiac Quality of Life Inventory (PCQLI). METHODS: Seven centers recruited pediatric patients (8-18 years of age) with heart disease (HD) and their parents to complete the PCQLI and generic health-related quality of life (Pediatric Quality of Life Inventory [PedsQL]) and non-quality of life (Self-Perception Profile for Children [SPPC]/Self-Perception Profile for Adolescents [SPPA] and Youth Self-Report [YSR]/Child Behavior Checklist [CBCL]) tools. PCQLI construct validity was assessed through correlations of PCQLI scores between patients and parents and with severity of congenital HD, medical care utilization, and PedsQL, SPPC/SPPA, and YSR/CBCL scores. PCQLI test-retest reliability was evaluated. RESULTS: The study enrolled 1605 patient-parent pairs. Construct validity was substantiated by the association of lower PCQLI scores with Fontan palliation and increased numbers of cardiac operations, hospital admissions, and physician visits (P < .001); moderate to good correlations between patient and parent PCQLI scores (r = 0.41-0.61; P < .001); and fair to good correlations between PCQLI total scores and PedsQL total (r = 0.70-0.76), SPPC/SPPA global self-worth (r = 0.43-0.46), YSR/CBCL total competency (r = 0.28-0.37), and syndrome and Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition oriented scale (r = -0.58 to -0.30; P < .001) scores. Test-retest reliability correlations were excellent (r = 0.78-0.90; P < .001). CONCLUSIONS: PCQLI scores are valid and reliable for children and adolescents with congenital and acquired HD and may be useful for future research and clinical management. Copyright © 2010 by the American Academy of Pediatrics.
Keywords: Acquired heart disease; Congenital heart disease; Health-related quality of life; Reliability; Validity

Laboratory measures of exercise capacity and ventricular characteristics and function are weakly associated with functional health status after fontan procedure - McCrindle, B.W.; Zak, V.; Sleeper, L.A.; Paridon, S.M.; Colan, S.D.; Geva, T.; Mahony, L.; Li, J.S.; Breitbart, R.E.; Margossian, R.; Williams, R.V.; Gersony, W.M.; et al. (Circulation, 2010)
Background: Patients after the Fontan procedure are at risk for suboptimal functional health status, and associations with laboratory measures are important for planning interventions and outcome measures for clinical trials. Methods and Results: Parents completed the generic Child Health Questionnaire for 511 Fontan Cross-Sectional Study patients 6 to 18 years of age (61% male). Associations of Child Health Questionnaire Physical and Psychosocial Functioning Summary Scores (FSS) with standardized measurements from prospective exercise testing, echocardiography, magnetic resonance imaging, and measurement of brain natriuretic peptide were determined by regression analyses. For exercise variables for maximal effort patients only, the final model showed that higher Physical FSS was associated only with higher maximum work rate, accounting for 9% of variation in Physical FSS. For echocardiography, lower Tei index (particularly for patients with extracardiac lateral tunnel connections), lower indexed end-systolic volume, and the absence of atrioventricular valve regurgitation for patients having Fontan procedure at age <2 years were associated with higher Physical FSS, accounting for 14% of variation in Physical FSS. For magnetic resonance imaging, ratio of lower mass to end-diastolic volume and midquartiles of indexed end-systolic volume (nonlinear) were associated with higher Physical FSS, accounting for 11% of variation. Lower brain natriuretic peptide was significantly but weakly associated with higher Physical FSS (1% of variation). Significant associations for Psychosocial FSS with laboratory measures were fewer and weaker than for Physical FSS. Conclusions: In relatively healthy Fontan patients, laboratory measures account for a small proportion of the variation in functional health status and therefore may not be optimal surrogate end points for trials of therapeutic interventions. © 2010 American Heart Association. All rights reserved.
Keywords: Fontan procedure; Heart defects, congenital; Pediatrics

Anthropometric measures after Fontan procedure: Implications for suboptimal functional outcome - Cohen, M.S.; Zak, V.; Atz, A.M.; Printz, B.F.; Pinto, N.; Lambert, L.; Pemberton, V.; Li, J.S.; Margossian, R.; Dunbar-Masterson, C.; McCrindle, B.W. (American Heart Journal, 2010)
Background: Abnormal height and adiposity are observed after the Fontan operation. These abnormalities may be associated with worse functional outcome. Methods: We analyzed data from the National Heart, Lung, and Blood Institute Pediatric Heart Network cross-sectional study of Fontan patients. Groups were defined by height (z-score <-1.5 or ≥-1.5) and body mass index (body mass index [BMI] z-score <-1.5 or -1.5 to 1.5 or ≥1.5). Associations of anthropometric measures with measurements from clinical testing (exercise, echocardiography, magnetic resonance imaging) were determined adjusting for demographics, anatomy, and pre-Fontan status. Relationships between anthropometric measures and functional health status (FHS) were assessed using the Child Health Questionnaire. Results: Mean age of the cohort (n = 544) was 11.9 ± 3.4 years. Lower height-z patients (n = 124, 23%) were more likely to have pre-Fontan atrioventricular valve regurgitation (P = .029), as well as orthopedic and developmental problems (both P < .001). Lower height-z patients also had lower physical and psychosocial FHS summary scores (both P < .01). Higher BMI-z patients (n = 45, 8%) and lower BMI-z patients (n = 53, 10%) did not have worse FHS compared to midrange BMI-z patients (n = 446, 82%). However, higher BMI-z patients had higher ventricular mass-to-volume ratio (P = .03) and lower % predicted maximum work (P = .004) compared to midrange and lower BMI-z patients. Conclusions: Abnormal anthropometry is common in Fontan patients. Shorter stature is associated with poorer FHS and non-cardiac problems. Increased adiposity is associated with more ventricular hypertrophy and poorer exercise performance, which may have significant long-term implications in this at-risk population. © 2010 Mosby, Inc.

Atrial Remodeling After the Fontan Operation - Wolf, C.M.; Seslar, S.P.; den Boer, K.; Juraszek, A.L.; McGowan, F.X.; Cowan, D.B.; Del Nido, P.; Triedman, J.K.; Berul, C.I.; Walsh, E.P. (American Journal of Cardiology, 2009)
The hemodynamics after Fontan surgery are notable for hypertension and dilation of the right atrium (RA). The effect of this stress on atrial cytoarchitecture has not been systematically studied and might be relevant to arrhythmias and their treatment. Morphologic and histopathologic analyses were performed on tissue from the RA and left atrium (LA) from autopsy specimens of Fontan hearts (n = 47). The findings were compared to those from control samples from young patients with normal atrial hemodynamics (n = 15). Most Fontan specimens were from young patients who died after a relatively short duration of Fontan physiology. The tissues were analyzed for wall thickness, fibrosis content, and fibrosis pattern. The mean wall thickness for the RA (3.0 ± 1.0 mm) and LA (2.3 ± 0.6 mm) in the Fontan hearts was significantly greater than that in the control hearts (RA, 1.8 ± 0.4 mm; LA, 1.8 ± 0.5 mm; p <0.001 and p = 0.024, respectively). The predictors for thickening of the RA included (1) older age at Fontan surgery, (2) older age at death, and (3) longer duration of Fontan circulation. The Fontan hearts and control hearts exhibited nearly identical fibrosis patterns in the RA and LA. Neither wall thickness nor fibrosis varied with the underlying heart defect or style of Fontan connection. In conclusion, atrial remodeling after Fontan surgery for univentricular heart physiology involves increased wall thickness in both the RA and LA. Interstitial fibrosis was also observed in the Fontan atria; however, because a similar pattern was present in the control tissue, this likely represented normal fibroelastic atrial structure, rather than a specific response to Fontan hemodynamics. The degree of wall thickening observed in the Fontan atria was not so excessive as to preclude transmural lesions during catheter or surgical ablation of reentrant arrhythmias. © 2009 Elsevier Inc. All rights reserved.

Exercise capacity, quality of life, and daily activity in the long-term follow-up of patients with univentricular heart and total cavopulmonary connection - Müller, J.; Christov, F.; Schreiber, C.; Hess, J.; Hager, A. (European Heart Journal, 2009)
Aims Patients with congenital heart disease usually show diminished exercise capacity and quality of life. However, there is only little information about daily activity, a marker for lifestyle, exercise capacity, and the prevention of arteriosclerosis. This study investigated exercise capacity, quality of life, daily activity, and their interaction with univentricular heart physiology after total cavopulmonary connection (TCPC).Methods and resultsFifty-seven patients (18 females, 39 males, age 8-52 years) after TCPC (lateral tunnel 28, extra-cardiac conduit 29) who underwent surgery during 1994-2001 were examined in our institution. They performed a symptom-limited cardiopulmonary exercise test. Those patients 14 years of age and older filled in the health-related quality-of-life questionnaire SF-36, and those who were 8-13 years of age, the CF-87. Daily activity parameters were obtained by using a triaxial accelerometer over the next three consecutive days. Exercise capacity was severely reduced after TCPC (25.0 mL/min/kg corresponding to 59.7 of age-and sex-related reference values). Daily activity was within the recommendations of the United Kingdom Expert Consensus Group (≥60 min, ≥3 metabolic equivalent, ≥5 days/week) in 72 of the investigated patients. It was reduced in older patients (Spearman r =-0.506, P < 0.001) and patients with a lower peak oxygen uptake (Spearman r = 0.432, P = 0.001). In children <14 years, mental health was related to daily activity.ConclusionDespite their diminished exercise capacity, patients after TCPC show a fairly normal activity pattern. However, their activity depends not only on age, but also on exercise capacity, which, in contrast to healthy people, decreases already from early adolescence on.
Keywords: Congenital heart disease; Daily activity; Exercise capacity; Long-term follow-up; Quality of life; Total cavopulmonary connection

How Good Is a Good Fontan? Quality of Life and Exercise Capacity of Fontans Without Arrhythmias - d'Udekem, Y.; Cheung, M.M.H.; Setyapranata, S.; Iyengar, A.J.; Kelly, P.; Buckland, N.; Grigg, L.E.; Weintraub, R.G.; Vance, A.; Brizard, C.P.; Penny, D.J. (Annals of Thoracic Surgery, 2009)
Background: Poor long-term outcomes are expected after Fontan surgery, but these perspectives have been tainted by the poorly functioning Fontans suffering from arrhythmias. No predictions of outcome can be quoted to the increasing number of Fontan patients free from arrhythmic complications. The parameters determining improved exercise capacity and quality of life in this subgroup are yet unknown. Methods: Fontan survivors from our institution and living in Victoria were invited to participate in the study if they were more than 10 years of age, and free of arrhythmias. A mean of 17 ± 4 years after Fontan, 36 patients, 23 with a classical atriopulmonary connection (AP) and 13 with a lateral tunnel (LT) underwent transthoracic echocardiography, cycloergometer exercise study, neurohumoral screening, and assessment of quality of life. Results: The only factor predicting worse exercise capacity was the type of Fontan performed; patients with LT having better exercise capacity than those with AP (percentage of predicted anaerobic threshold: 88 ± 14% vs 72 ± 14%, p < 0.005; percentage of predicted Vo2max: 62 ± 8% vs 54 ± 7%, p < 0.005). Endothelin-1 levels were elevated in all patients (2.9 pmol/L, 2.5 to 3.7). Responses from the quality of life measures placed our Fontan cohort mainly within the normal population range. None of the preoperative and postoperative variables adversely affected patients' quality of life. Conclusions: The anaerobic threshold of arrhythmia-free Fontan patients operated with the lateral tunnel technique was relatively preserved. Despite restricted exercise capacity, Fontan patients, provided that they are free of arrhythmias, have a normal quality of life reflected in their reports of psychiatric symptoms and family relationships. © 2009 The Society of Thoracic Surgeons.

The oxidative state of children with cyanotic and acyanotic congenital heart disease - Ercan, S.; Çakmak, A.; Kösecik, M.; Erel, Ö. (Anadolu Kardiyoloji Dergisi, 2009)
Objective: The type of congenital heart disease, early diagnosis, and treatment modality all play an important role in the morbidity and mortality of these diseases. This study examined the relationship between congenital heart disease and oxidative stress in children with cyanotic and acyanotic congenital heart disease. Methods: In this case-controlled cross-sectional study, the study groups consisted of 29 patients with cyanotic heart disease, 30 patients with acyanotic heart disease, and a control group of 32 healthy individuals. For all groups, the total oxidant status (TOS), total antioxidant status (TAS), and oxidative stress index (OSI) were calculated. Of the cyanotic group, 12 were diagnosed with tetralogy of Fallot, 7 with transposition of the great arteries, 4 with tricuspid atresia, 4 with double outlet right ventricle and 2 with truncus arteriosus. In the acyanotic group 19 patients had ventricular septal defect (VSD), 5 atrial septal defect (ASD) and 6 patent ductus arteriosus (PDA). Statistical analyses were performed using Chi-square, Mann-Whitney U and Kruskal-Wallis tests. Results: The plasma TAS, TOS, and OSI were significantly higher in the cyanotic group than in the acyanotic group (p<0.0001, p<0.01, and p<0.01, respectively) and controls (p<0.0001, p<0.0001, and p<0.0001, respectively). A comparison between the acyanotic and control groups showed no statistical differences. Conclusion: The level of oxidative stress in patients with cyanotic congenital heart disease was significantly higher than in the acyanotic and control groups, which were similar. ©Copyright 2009 by AVES Yayincilik Ltd.
Keywords: Acyanotic; Child; Congenital heart diseases; Cyanotic; Oxidative stress

Parent- versus child-reported functional health status after the fontan procedure - Lambert, L.M.; Minich, L.L.; Newburger, J.W.; Lu, M.; Pemberton, V.L.; McGrath, E.A.; Atz, A.M.; Mingfen, X.; Radojewski, E.; Servedio, D.; McCrindle, B.W. (Pediatrics, 2009)
OBJECTIVE: We sought to compare perceptions of functional health status between children who had undergone a Fontan procedure and their parents. METHODS: Fontan procedure survivors 10 to 18 years of age were included in the study if the child completed the Child Health Questionnaire (CHQ) and the parent completed the parent form to assess the child's functional health status. Comparisons were made between raw domain scores for the parent- and child-completed CHQs. RESULTS: Between March 2003 and April 2004, 1078 Fontan survivors were screened. Of the 546 eligible and consented patients, 354 were 10 -18 years of age and 328 parent/child pairs completed the CHQs. Parents reported significantly lower scores (worse functioning) for their children than the children reported for themselves in the domains of physical functioning (P < .01), impact on school or activities from emotional and behavioral problems (P < .01), impact on school or activities from physical health issues (P<.01), general behavior (P < .01), mental health (P < .01), self-esteem (P < .01), and general health perceptions (P<.01). No significant differences were noted for the domains of bodily pain, family cohesiveness, or family activities. For the physical functioning domain, factors contributing to lower scores for parent versus child reports included pulmonary artery anomalies and fenestration at the time of the Fontan operation. Lower parent-reported scores also were associated with more noncardiac health problems in the child. CONCLUSIONS: Parents' perceptions of the functional health status of their children after the Fontan procedure were worse than the children's perceptions. Copyright © 2009 by the American Academy of Pediatrics.
Keywords: Congenital heart disease; Fontan procedure; Functional health status; Quality of life; Single ventricle

Pulsatile in vitro simulation of the pediatric univentricular circulation for evaluation of cardiopulmonary assist scenarios - Dur, O.; Lara, M.; Arnold, D.; Vandenberghe, S.; Keller, B.B.; Degroff, C.; Pekkan, K. (Artificial Organs, 2009)
The characteristic depressed hemodynamic state and gradually declining circulatory function in Fontan patients necessitates alternative postoperative management strategies incorporating a system level approach. In this study, the single-ventricle Fontan circulation is modeled by constructing a practical in vitro bench-top pulsatile pediatric flow loop which demonstrates the ability to simulate a wide range of clinical scenarios. The aim of this study is to illustrate the utility of a novel single-ventricle flow loop to study mechanical cardiac assist to Fontan circulation to aid postoperative management and clinical decision-making of single ventricle patients. Two different pediatric ventricular assist devices, Medos and Pediaflow Gen-0, are anastomosed in two nontraditional configurations: systemic venous booster (SVB) and pulmonary arterial booster (PAB). Optimum ventricle assist device strategy is analyzed under normal and pathological (pulmonary hypertension) conditions. Our findings indicate that the Medos ventricular assist device in SVB configuration provided the highest increase in pulmonary (46%) and systemic (90%) venous flow under normal conditions, whereas for the hypertensive condition, highest pulmonary (28%) and systemic (55%) venous flow augmentation were observed for the Pediaflow ventricular assist device inserted as a PAB. We conclude that mechanical cardiac assist in the Fontan circulation effectively results in flow augmentation and introduces various control modalities that can facilitate patient management. Assisted circulation therapies targeting single-ventricle circuits should consider disease state specific physiology and hemodynamics on the optimal configuration decisions. © 2009, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Assisted circulation/methods; Fontan procedure/methods; Hemodynamics/ physiology; Pulsatile flow; Ventricle-assist devices/utilization

Intravascular mechanical cavopulmonary assistance for patients with failing fontan physiology - Bhavsar, S.S.; Kapadia, J.Y.; Chopski, S.G.; Throckmorton, A.L. (Artificial Organs, 2009)
To provide a viable bridge-to-transplant, bridge-to-recovery, or bridge-to-surgical reconstruction for patients with failing Fontan physiology, we are developing a collapsible, percutaneously inserted, magnetically levitated axial flow blood pump to support the cavopulmonary circulation in adolescent and adult patients. This unique blood pump will augment pressure and thus flow in the inferior vena cava through the lungs and ameliorate the poor hemodynamics associated with the univentricular circulation. Computational fluid dynamics analyses were performed to create the design of the impeller, the protective cage of filaments, and the set of diffuser blades for our axial flow blood pump. These analyses included the generation of pressure-flow characteristics, scalar stress estimations, and blood damage indexes. A quasi-steady analysis of the diffuser rotation was also completed and indicated an optimal diffuser rotational orientation of approximately 12°. The numerical predictions of the pump performance demonstrated a pressure generation of 2-25 mm Hg for 1-7 L/min over 3000-8000 rpm. Scalar stress values were less than 200 Pa, and fluid residence times were found to be within acceptable ranges being less than 0.25 s. The maximum blood damage index was calculated to be 0.068%. These results support the continued design and development of this cavopulmonary assist device, building upon previous numerical work and experimental prototype testing. © 2009, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Artificial right ventricle; Blood pump; Cavopulmonary assist device; Fontan conversion; Heart pump; Intravascular blood pump; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Ventricular assist device(s)

A multicentric study of disease-related stress, and perceived vulnerability, in parents of children with congenital cardiac disease - Vrijmoet-Wiersma, C.M.J.; Ottenkamp, J.; Van Roozendaal, M.; Grootenhuis, M.A.; Koopman, H.M. (Cardiology in the Young, 2009)
Parents of children with congenitally malformed hearts can suffer from stress as a result of the medical condition of their child. In this cross-sectional study, we aimed to describe levels of parental stress, and perceived vulnerability, in parents of children who underwent major cardiac surgery, by using both generic and disease-related measures for assessment. We included parents of children who underwent open-heart surgery over the period 2002 through 2007 in the Center for congenital Anomalies Heart Amsterdam/Leiden, abbreviated to provide the acronym CAHAL. In total, we assessed 114 mothers and 82 fathers of 131 children, using the Pediatric Inventory for Parents, short form, General Health Questionnaire, Parental Stress Index-Short Form, State-Trait Anxiety Index and the Child Vulnerability Scale. Compared to the reference groups of the instruments used, parents of children with congenitally malformed hearts did not report higher generic nor disease-related stress scores, and parenting levels of stress were also comparable to reference groups. State anxiety levels, however, were higher in mothers of children with congenitally malformed hearts. Both fathers and mothers reported significantly higher rates of perceived vulnerability than did parents of healthy children. Risk factors for increased anxiety and perceived vulnerability were found in the number of surgical procedures, the time past since the last procedure, and ethnicity. Severity of the lesion did not influence parental levels of stress, but parents of children with hypoplastic left heart syndrome did report higher levels of stress than other parents. Psychosocial screening of parents of children with congenitally malformed hearts is important in order to provide appropriate counselling to those parents most in need. © 2009 Cambridge University Press.
Keywords: Children; Congenitally malformed hearts; Overprotection; Psychological problems

Is "Treat your child normally" helpful advice for parents of survivors of treatment of hypoplastic left heart syndrome? - Rempel, G.R.; Harrison, M.J.; Williamson, D.L. (Cardiology in the Young, 2009)
Background: Developing technology affords children with complex congenitally malformed hearts a chance for survival. Parents gratefully pursue life-saving options on behalf of their children, despite the risks to the life of their child, and uncertainty about outcomes. Little is known about how mothers and fathers experience parenting a child whose new state as a survivor may include less than optimal developmental sequels. Method: Our study involved multiple interactive interviews with 9 mothers and 7 fathers of infants and preschool children with hypoplastic left heart syndrome who had survived the Norwood surgical approach. Qualitative methodology included grounded theory methods of simultaneous collection and analysis of data, and we used open and selective coding of transcribed interviews. Results: Parents used normalization in the context of uncertainty regarding the ongoing survival of their child. Parents described their underweight children as being on their own growth curve, and viewed their developmental progress, however delayed, as reason for celebration, as they had been prepared for their child to die. Conclusion: There is growing evidence that children with congenitally malformed hearts who require surgical intervention during the first year of life may experience developmental delay. The use of normalization by their parents may be effective in decreasing their worry regarding the uncertain future faced by their child, but may negatively affect the developmental progress of the child if they do not seek resources to assist development. Advice from paediatric specialists for parents to view their children as normal needs to be balanced with assistance for parents to access services to support optimal growth and development of their child. Copyright © Cambridge University Press 2009.
Keywords: Cardio-thoracic nursing; Child development; Child nursing; Congenital heart disease; Early intervention; Family care

Development of a pediatric cardiology quality improvement collaborative: From inception to implementation. From the joint council on congenital heart disease quality Improvement task force - Kugler, J.D.; Beekmani III, R.H.; Rosenthal, G.L.; Jenkins, K.J.; Klitzner, T.S.; Martin, G.R.; Neish, S.R.; Lannon, C. (Congenital Heart Disease, 2009)
While clinical outcomes in pediatric cardiac disease have improved in recent years, marked institutional and individual cardiology practice variability exists. Quality improvement science has demonstrated that reducing process variation leads to more favorable outcomes, safer practices, cost savings, and improved operating efficiency. This report describes the process undertaken to develop the first collaborative quality improvement project of the Joint Council on Congenital Heart Disease. The project chosen aims to reduce mortality and improve the quality of life of infants with hypoplastic left heart syndrome during the interstage period between discharge from the Norwood procedure and admission for the bidirectional Glenn procedure. The objective of this special article is to inform the pediatric cardiology and cardiac surgery communities of the project to help ensure that the early work by the project pilot participants will spread to clinicians caring for children with cardiovascular disease. It is anticipated that this project will add to our understanding of care for this challenging group of children with hypoplastic left heart syndrome, identifying clinical care changes with the potential to lead to improvements in outcome. It will also introduce the field of pediatric cardiology to the science of collaborative quality improvement and assist in reducing clinical process variation and improving patient outcomes across centers. Finally, it will establish an ongoing network of pediatric cardiologists and their teams linked through a longitudinal data set and collaboration for improvement and research. © 2009 Copyright the Author Journal compilation © 2009 Wiley Periodicals, Inc.
Keywords: Cardiac; Pediatric; Quality improvement

Living with complex congenital heart disease - Human, D.G. (Paediatrics and Child Health, 2009)
A child with complex congenital heart disease in 2008 is very likely to survive a series of surgical and medical interventions, and confront an array of medical and psychosocial stressors that are presently poorly understood. As approaches to medical problems change, careful assessment of those results is essential, and the initial work of the multicentre Pediatric Heart Network is a huge step in the right direction, setting the stage for proper controlled trials of therapies. Major complications, notably ventricular failure, rhythm problems and thromboembolism, will affect nearly one-quarter of survivors, necessitating further interventions. Appropriate educational and psychosocial support for these children and their families is the next challenge for all of us in the field of paediatrics. How ironic would it be to have invested so much in early survival, only to allow the child to fail in life itself. © 2009 Pulsus Group Inc. All rights reserved.
Keywords: Congenital heart disease; Fontan circulation; Quality of life

Clinical profiles of adult patients with single ventricular physiology - Motoki, N.; Ohuchi, H.; Miyazaki, A.; Yamada, O. (Circulation Journal, 2009)
Background: This study was performed to clarify the present global clinical status, including medication(s) and social abilities, of adult patients with single ventricular physiology (SVP). Methods and Results: Clinical charts were retrospectively reviewed to evaluate the global clinical status, including functional capacity, medication(s), complications, and social activities of 68 adult patients with SVP aged 20-53 years (41 males); 50 had undergone the Fontan operation and they were divided into the young adult (25 patients) and adult Fontan groups. The others were cyanotic patients without the Fontan operation (non-Fontan group). Although the Fontan groups showed better functional capacity, higher arterial oxygen saturation and brain natriuretic peptide levels, and a better renal function, there was no difference in the cardiovascular events during follow-up between the 3 groups. The most frequent complication was arrhythmia without a significant group difference, although the non-Fontan group showed a high percentage of heart failure. Only 41 patients (60%) had a job and 8 (12%) were married. Conclusions: Although the Fontan groups had favorable pathophysiological conditions, the high rate of cardiovascular events, as well as unsatisfactory social situations, indicate the importance of meticulous life-long management of patients with SVP, regardless of the type of surgical intervention.
Keywords: Adult congenital heart disease; Fontan; Quality of life; Single ventricle; Survival

Left ventricular morphology influences mortality after the Norwood operation - Walsh, M.A.; McCrindle, B.W.; Dipchand, A.; Manlhiot, C.; Hickey, E.; Caldarone, C.A.; Van Arsdell, G.S.; Schwartz, S.M. (Heart, 2009)
Background: Within the spectrum of congenital heart disease referred to as hypoplastic left heart syndrome (HLHS), there is variation in the morphology and function of the left ventricle which could influence outcomes after stage I Norwood palliation. Objective: To determine if left ventricular (LV) morphology is associated with outcome after stage I Norwood palliation for HLHS. Methods: Echocardiograms were reviewed from 108 patients who had undergone Norwood palliation at our institution over the past 11 years. Total cardiac diameter, thickness of the interventricular septum (IVS), LV area and LV myocardial area were calculated. Competing risk analysis was performed for survival to a stage II operation and to determine potential predictors. Results: From the Norwood operation up to stage II operation, mortality was predicted by IVS thickness, while the absence of right ventricular (RV) dysfunction was predictive of survival to stage II operation. For the complete pathway, from Norwood to the Fontan operation, mortality was predicted by IVS, a lower RV fractional area change and the presence of significant tricuspid regurgitation. Cardiac transplantation during this period was predicted by a lower RV fractional area change (p=0.02) and a larger LV area in diastole. Conclusions: These results indicate that LV hypertrophy and decreased RV function adversely effect survival after the Norwood operation. They suggest that LV morphology, especially septal hypertrophy, can influence outcomes in HLHS and should be considered when evaluating treatment options.

Design of a protective cage for an intravascular axial flow blood pump to mechanically assist the failing fontan - Throckmorton, A.L.; Kishore, R.A. (Artificial Organs, 2009)
Currently, no long-term mechanical bridge-to-transplant or bridge-to-recovery therapeutic alternative exists for failing single ventricles. A blood pump that would augment pressure in the cavopulmonary circulation is needed, and would lead to a reduction in elevated systemic venous pressure, and improve cardiac output. Thus, we are developing a collapsible, percutaneously inserted, axial flow blood pump to support the cavopulmonary circulation in adult patients with a failing single ventricle physiology. This collapsible axial flow pump is designed for percutaneous positioning. The outer protective cage will be designed with radially arranged filaments as touchdown surfaces to protect the vessel wall from the rotating components. This study examined the geometric characteristics of the protective cage of filaments and the impeller through the development and numerical analysis of 13 models. A blood damage analysis was also performed on selected geometric models to assess the probability of blood trauma. All models demonstrated an acceptable hydraulic performance by delivering 2-6 L/min at a rotational speed of 6000-10 000 rpm and generating pressure rise of 5-20 mm Hg. Expected trends in the hydraulic performance of the pump models were found. This study represents the initial first design phase of the impeller and protective cage of filaments. Validation of these flow and performance predictions will be completed in the next round of experimental testing with blood bag evaluation. © 2009, International Center for Artificial Organs and Transplantation and Wiley Periodicals, Inc.
Keywords: Artificial right ventricle; Blood pump; Cavopulmonary assist device; Fontan conversion; Heart pump; Intravascular blood pump; Mechanical cavopulmonary assist; Pediatric circulatory support; Single ventricle physiology; Ventricular assist device

The effect of bosentan in patients with a failing Fontan circulation - Ovaert, C.; Thijs, D.; Dewolf, D.; Ottenkamp, J.; Dessy, H.; Moons, P.; Gewillig, M.; Mertens, L. (Cardiology in the Young, 2009)
Objectives: To investigate the effect of bosentan in patients with a failing Fontan circulation. Design: A multicentric open label, non-controlled study. Setting: 5 tertiary care centres for congenital cardiology. Patients: We included 10 patients with a failing Fontan circulation. Their median age at inclusion was 12.12 years, with a range from 4.41 to 33,41 years. The median interval between the Fontan operation and inclusion was 7.84 years, with a range from 1.96 to 12,18 years. Participants received half the usual dose of bosentan for 4 weeks, and then the full dose for a further 12 weeks. Main measures of outcomes: We assessed saturations of oxygen at rest and during exercise, using a 6 minutes walk test, at baseline, and during and after 16 weeks of treatment. At each visit, we assessed blood chemistry and hepatic function, and asked the patients to complete a questionnaire concerning quality of life. All medical events and possible side effects were recorded. Results: Of the cohort, 1 patient withdrew. The changes in saturations of oxygen, exercise performance, and scores for the questionnaire did not reach statistical significance for the whole group. We noted, nonetheless, that saturations of oxygen and/or exercise capacity improved in 5 of the patients. This was further confirmed when those patients deteriorated again when the drug was discontinued. Conclusions: Our study failed to show significant improvement after 3 months of treatment with bosentan in a small group of patients with failing Fontan circulations. Some individuals, nonetheless, did improve. When planning larger trials, it would be better to identify those patients who might potentially benefit from the treatment prior to commencing the trial. © 2009 Copyright © Cambridge University Press 2009.
Keywords: Congenital heart defect; Endothelin receptor antagonist; Functionally single ventricle; Pulmonary vascular resistance

Extracardiac lesions and chromosomal abnormalities associated with major fetal heart defects: Comparison of intrauterine, postnatal and postmortem diagnoses - Song, M.S.; Hu, A.; Dyhamenahali, U.; Chitayat, D.; Winsor, E.J.T.; Ryan, G.; Smallhorn, J.; Barrett, J.; Yoo, S.-J.; Hornberger, L.K. (Ultrasound in Obstetrics and Gynecology, 2009)
Objectives The clinical outcome of prenatally diagnosed congenital heart defects (CHD) continues to be affected significantly by associated extracardiac and chromosomal abnormalities. We sought to: determine the frequency and type of major extracardiac abnormalities (with impact on quality of life) and chromosomal abnormalities associated with fetal CHD; and compare the extracardiac abnormalities detected prenatally to the postnatal and autopsy findings in affected fetuses, to find the incidence of extracardiac abnormalitiesmissed on prenatal ultrasound. Methods We reviewed the computerized database of the Division of Cardiology of the Hospital for Sick Children in Toronto to identify all cases of major CHD detected prenatally from 1990 to 2002. Medical records, fetal echocardiograms and ultrasound, cytogenetic and autopsy reports were reviewed. The types of CHD detected were grouped into categories and the frequencies of major extracardiac and chromosomal abnormalities in these categories were noted. Prenatal ultrasound findings were compared with those at autopsy or postnatal examination. Results Of 491 fetuses with major structural CHD, complete data were obtained for 382. Of these, there were 141 (36.9%) with major extracardiac abnormalities at autopsy or postnatal exam, of which 46 had chromosomal abnormalities and 95 did not. In the absence of chromosomal abnormalities, the organ systems most affected were urogenital (12.2%) and gastrointestinal (11.6%). CHDs with the highest incidence of extracardiac abnormalities (>25%) included: heterotaxy, single left ventricle and tricuspid atresia, hypoplastic left heart syndrome and tetralogy of Fallot. Ninety-four of 334 (28.1%) fetuses tested had chromosomal abnormalities. The most common chromosomal abnormalities were trisomies 21 (43.6%), 18 (19.1%) and 13 (9.6%), monosomy X (7.4%) and 22q11.2 deletion (7.4%). Of 289 extracardiac abnormalities from the complete series, 134 (46.4%) were not identified prenatally. Of the missed extracardiac abnormalities, 65 were considered not detectable at prenatal ultrasound, so 23.9% (69/289) of detectable extracardiac abnormalities were missed prenatally. Conclusions Major extracardiac and chromosomal abnormalities are common in fetuses with major fetal CHD. Many important associated extracardiac abnormalities may be missed prenatally, which should be taken into consideration in the prenatal counseling for fetal CHD. © 2009 ISUOG.
Keywords: Chromosomal abnormalities; Congenital heart defects; Extracardiac lesions; Fetal echocardiography; Fetal ultrasound

Challenges and Progress of the Pediatric Cardiac Surgery in Shanghai Children's Medical Center: A 25-year Solid Collaboration With Project HOPE - Liu, J. (Seminars in Thoracic and Cardiovascular Surgery: Pediatric Cardiac Surgery Annual, 2009)
Congenital heart disease (CHD) is one of major categories of illness that, if treated, can restore health and improve quality of life. Unfortunately, in many developing countries, health professionals may not have the resources to replenish themselves with modern technology and/or surgery skills to treat a child with complex CHD. Until now, CHD remained a health challenge for many children and families. During the past few decades, due to limited medical resources and operative techniques, only a very small proportion of the children with CHD in our region were able to be operated for lesion repair. However, the situation in the last 20 years has changed dramatically. Treatment for pediatric CHDs has been greatly improved and developed in China. The collaboration with Project HOPE, an international health professional education organization, has promoted the development of our specialty. Specifically, Project HOPE has played an important role in facilitating the collaboration between Shangahi Xin Hua Hospital, Shanghai Children's Medical Center, and many world-leading pediatric health care institutions. With contributions from Project HOPE in the last 25 years, cardiovascular surgeons at Shanghai Children's Medical Center have achieved tremendous progress. The landmark of the cardiac center and successful clinical data in treating children with cardiac illness symbolizes the successful collaboration among a state-owned hospital, a non-profit organization-Project HOPE, and multiple international corporations, which have provided valuable resources to facilitate the growth of the hospital into a state-of-the-art tertiary hospital to serve children and families. © 2009 Elsevier Inc. All rights reserved.
Keywords: collaboration; Congenital heart disease; developing country; non-profit organization

Quality-of-life concerns differ among patients, parents, and medical providers in children and adolescents with congenital and acquired heart disease - Marino, B.S.; Tomlinson, R.S.; Drotar, D.; Claybon, E.S.; Aguirre, A.; Ittenbach, R.; Welkom, J.S.; Helfaer, M.A.; Wernovsky, G.; Shea, J.A. (Pediatrics, 2009)
OBJECTIVES. Mortality rates in pediatric patients with heart disease have decreased dramatically in recent decades, resulting in an increasing number of survivors with morbidities that impact quality of life. The purpose of this study was to assess and compare how heart disease affects the quality of life of the pediatric cardiac patient from the perspectives of the patient, parent, and health care provider. METHOD. Individual focus groups were conducted with children (8-12 years of age) with heart disease, adolescents (13-18 years of age) with heart disease, parents of children with heart disease, parents of adolescents with heart disease, and health care providers of pediatric patients with heart disease. A structured focus group technique was used to develop a list of potential items that might affect quality of life. Participants chose the 5 most important items from the list. These items were then categorized into preidentified dimensions (physical, psychological, social, school, and other). The percentages of the total votes for all items were calculated and distributions of responses across dimensions within group and within dimension across groups were reported and compared qualitatively. RESULTS. Patient and parent groups identified similar items as important. Providers identified different items. The physical limitation item received the largest percentage of total votes in all groups (9%-20%). Analysis across dimension revealed that those items related to the physical dimension received the highest percentage of total votes among all groups (30.2%-51.2%). Analysis within dimension revealed that patients endorsed items in the physical dimension more frequently than parents or providers. Within the psychological dimension, the children selected the fewest items relative to all other groups (7.2% vs 21.3%-37.8%), whereas health care providers endorsed these items more frequently than patients or parents (child or parent of child groups 7.2%-21.3% vs health care provider group 28.8%; adolescent or parent of adolescent groups 29.6% vs health care provider group 37.8%). Differences were noted between the child and adolescent groups in the psychological (child versus adolescent: 7.2% vs 29.6%) and school (child versus adolescent: 11.2% vs 2.1%) dimensions. CONCLUSIONS. Patients and parents generally agreed on how heart disease affects the quality of life of children and adolescents, whereas health care providers had a different opinion. Copyright © 2009 by the American Academy of Pediatrics.
Keywords: Adolescents; Children; Congenital heart disease; Focus groups; Medical providers; Quality of life

Fontan patient with plastic bronchitis treated successfully using aerosolized tissue plasminogen activator: A case report and review of the literature - Do, T.B.; Chu, J.M.; Berdjis, F.; Anas, N.G. (Pediatric Cardiology, 2009)
Plastic bronchitis is an uncommon condition characterized by the production of large pale bronchial casts that obstruct the tracheobronchial tree. The cellular content, cohesiveness, and often rubber-like consistency distinguish bronchial casts from the usual mucus plugs found with such disease states as asthma. Plastic bronchitis can be found secondary to many conditions, and a simplified classification scheme organizes it into two groups: an inflammatory type consisting of casts with an eosinophilic inflammatory infiltrate and an acellular type with a predominance of fibrin distinguished by its relative lack of cellular infiltrate, its mucin predominance, and its appearance only in children with congenital cyanotic heart disease. This report describes a 5-year-old girl who experienced plastic bronchitis 3 months after a Fontan procedure for hypoplastic left heart syndrome that was treated successfully with aerosolized tissue plasminogen activator. © 2008 Springer Science+Business Media, LLC.
Keywords: Fontan procedure; Plastic bronchitis; Tissue plasminogen activator

Invited Review: Nutrition support after neonatal cardiac surgery - Owens, J.L.; Musa, N. (Nutrition in Clinical Practice, 2009)
Congenital heart disease is the most common birth defect in the United States, with an estimated frequency of approximately 12ĝ€"14 of 1000 live births per year. Neonates with congenital heart disease often need palliative or corrective surgery requiring cardiopulmonary bypass during the first weeks of life. The neonate undergoing cardiopulmonary bypass surgery experiences a more profound metabolic response to stress than that seen in older children and adults undergoing surgery. However, compared with older children and adults, the neonate has less metabolic reserves and is extremely vulnerable to the negative metabolic impact induced by stress, which can lead to suboptimal wound healing and growth failure. There are complications associated with the metabolic derangements of neonatal surgery requiring cardiopulmonary bypass, including but not limited to acute renal failure, chylothorax, and neurological dysfunction. This article discusses the importance of nutrition and metabolic support for the neonate undergoing cardiopulmonary bypass and the immediate postoperative nutrition needs of such a patient. Also, this article uses a case study to examine the feeding methodology used at one particular institution after neonatal cardiac surgery. The purpose of the case study is to provide an illustration of the many factors and obstacles that clinicians often face in the provision and timing of nutrition support. © 2009 American Society for Parenteral and Enteral Nutrition.
Keywords: Cardiac surgical procedures; Enteral nutrition; Infant; Newborn; Nutritional support; Parenteral nutrition

Dexmedetomidine sedation for pediatric post-Fontan procedure patients - Tokuhira, N.; Atagi, K.; Shimaoka, H.; Ujiro, A.; Otsuka, Y.; Ramsay, M. (Pediatric Critical Care Medicine, 2009)
Objective: The hemodynamic, respiratory, and sedative effects of dexmedetomidine (DEX) for pediatric patients post-Fontan surgery. Design: Retrospective. Setting: Single institutional intensive care unit. Participants: Fourteen patients undergoing Fontan-type surgery. Result: A retrospective review was conducted on 14 pediatric patients who had undergone a Fontan procedure for congenital heart disease. A vital component of postoperative management of these patients is to prevent an increase in pulmonary vascular resistance (PVR) that may lead to a serious reduction in cardiac output. DEX an alpha-2 adrenergic receptor agonist might offer an advantage over current sedation methods in preventing a rise in PVR. Nine patients received sedation with DEX and five patients in a control group were administered standard regimens of sedation and analgesia. The DEX group exhibited no evidence of an increased partial pressure of arterial carbon dioxide postoperatively as opposed to the control group. This lack of respiratory depression made the DEX group less likely to increase their PVR. However, the DEX group did experience a significant incidence of bradycardia that required the use of a cardiac pacemaker. Conclusions: The results of this retrospective review of the role of DEX in the management of the post-Fontan surgical pediatric patient indicate some potential advantages. © 2009 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Alpha-2 agonists; Congenital heart surgery; Dexmedetomidine; Fontan procedure; Hemodynamics; Pediatric critical care; Postoperative sedation; Pulmonary vascular resistance

Self-estimated physical functioning poorly predicts actual exercise capacity in adolescents and adults with congenital heart disease - Gratz, A.; Hess, J.; Hager, A. (European Heart Journal, 2009)
Aims: The aim of this study is to compare self-reported health-related quality-of-life (HRQoL) with the objective of exercise performance in patients with congenital heart disease (CHD) according to diagnosis. Methods and results: 564 patients (255 females, 14-73 years) with various CHD (62 shunt, 66 left heart obstruction, 33 PS/PR, 47 Ebstein, 96 Fallot, 98 TGA after atrial switch, 38 other TGA, 31 Fontan, 32 palliated/native cyanotic, 61 others) and a group of 53 healthy controls (18 females, 14-57 years) completed a QoL questionnaire (SF-36) and performed a symptom-limited cardiopulmonary exercise test. Despite several limitations at exercise (P = 1.30 × 10-33), patients only reported reductions in HRQoL concerning physical functioning (P = 4.41 × 10-15) and general health (P = 6.17 × 10-5) and not psychosocial aspects. This could be confirmed in all diagnostic subgroups. Correlation to peak oxygen uptake was found in physical functioning (r = 0.435, P = 1.72 × 10-27) and general health (r = 0.275, P = 3.79 × 10-11). However, there was severe overestimation of physical functioning in most patients when compared with actual exercise test results. Conclusion: Patients with CHD rate their HRQoL impaired only in physical functioning and general health and not in any psychosocial aspect. Self-estimated physical functioning poorly predicts actual exercise capacity. © The Author 2008.
Keywords: Cardiopulmonary exercise testing; Congenital heart disease; Quality of life

Functional health status of adolescents after the Fontan procedure - Comparison with their siblings - Manlhiot, C.; Knezevich, S.; Radojewski, E.; Cullen-Dean, G.; Williams, W.G.; McCrindle, B.W. (Canadian Journal of Cardiology, 2009)
Background: Studies have suggested that patients who have undergone the Fontan procedure experience lower functional health status and diminished exercise capacity compared with other children. Objectives: To compare the functional health status of Fontan patients with and without siblings, assess whether there are any differences between Fontan patients and their siblings, and determine associated factors. Methods: A cross-sectional, single-centre, observational study was performed on Fontan patients 10 to 20 years of age, and their sibling closest in age, followed in a tertiary pediatric hospital. Functional health status was measured by the Child Health Questionnaire Child Form and the Pediatric Quality of Life, Inventory. Results: A total of 68 patients and 38 siblings were enrolled. Patients with siblings scored significantly lower on numerous domains of physical functional status than those without siblings. Compared with their matched siblings, Fontan patients reported significantly lower scores in all domains of the Pediatric Quality of Life Inventory and on physical (but not psychosocial) domains of the Child Health Questionnaire Child Form. Factors associated with increased patient-sibling differences included younger patient age, female sex, intracardiac lateral tunnel Fontan connection and lower ejection fraction at the time of study enrollment. Conclusions: Adolescents with Fontan physiology reported a lower functional health status in physical domains than their siblings, but had similar status in psychosocial domains. Having a sibling was associated with lower reported functional health status, suggesting an important effect of self-perceived physical limitations over true limitations. © 2009 Pulsus Group Inc. All rights reserved.
Keywords: Congenital heart disease; Fontan procedure; Functional health status; Quality of life; Single ventricle

Non-invasive positive pressure ventilation for bilateral diaphragm paralysis after pediatric cardiac surgery - Kovacikova, L.; Dobos, D.; Zahorec, M. (Interactive Cardiovascular and Thoracic Surgery, 2009)
We present the case histories of two children having respiratory failure due to bilateral diaphragm paralysis after cardiac surgery. In both children non-invasive positive pressure ventilation alleviated respiratory distress, improved gas exchange, and prevented the need for endotracheal intubation. Following unilateral recovery of diaphragmatic function both children were successfully weaned from non-invasive positive pressure ventilation. © 2009 Published by European Association for Cardio-Thoracic Surgery. All rights reserved.
Keywords: Complications; Congenital heart disease; Diaphragm; Ventilation

A large teratoma of the hard palate: a case report - Benson, R.E.; Fabbroni, G.; Russell, J.L. (British Journal of Oral and Maxillofacial Surgery, 2009)
Congenital teratoma is a rare malformation, and few papers have been published about it. We present a large teratoma that arose from the hard palate in a neonate. The obstructive mass caused maternal polyhydramnios and was identified prenatally by ultrasonography. The mother went into labour at 35 week's gestation at home. The child was in respiratory distress as a result of airway obstruction, and a tracheostomy was done when she was 4 hours old. She also had major cardiac abnormalities. The palatal mass was removed successfully at 4 weeks of age. The typical components of a teratoma were identified including immature neural glial tissue. © 2008 The British Association of Oral and Maxillofacial Surgeons.
Keywords: Epipalatus; Palate; Teratoma

Transcatheter closure of fenestration after modified fontan operation in children - Meraji, S.M.; Davari, P.N.; Aarabi, M.Y.; Shahmohammadi, A.A.; Mortezaeian, H.; Emamzadegan, R. (Journal of Tehran University Heart Center, 2008)
Background: Fenestration in the modified Fontan operation allows right-to-left shunting, which reduces the Fontan pathway pressure and improves cardiac output. However, on account of the fact that persistent right-to-left shunting results in cyanosis and paradoxical emboli, fenestration closure is recommended after recovery from the Fontan operation. Methods: This study recruited 3 patients who underwent the transcatheter closure of the Fontan fenestration with the ASD-Amplatzer because of severe cyanosis and significant intracardiac shunts. Results: Fenestration closure was performed at a mean age of 8 yr (6-12 yr) and average of 15 months after the Fontan operation. Aortic O2 saturation increased by an average of 17.6% (9-26%). During more than a two-year period of follow-up (mean: 27 months), two patients had complete occlusion on echocardiography and the other one had a small residual shunt. One of these patients had atrial flutter during the follow-up. Conclusion: The transcatheter closure of the Fontan fenestration is a safe and feasible technique that is effective in elevating systemic O2 saturation and well-being and confers acceptable growth and development in children.
Keywords: Amplatzer; Catheterization; Fontan procedure

Routine clinical cardiovascular magnetic resonance in paediatric and adult congenital heart disease: Patients, protocols, questions asked and contributions made - Fratz, S.; Hess, J.; Schuhbaeck, A.; Buchner, C.; Hendrich, E.; Martinoff, S. (Journal of Cardiovascular Magnetic Resonance, 2008)
Background: Cardiovascular Magnetic Resonance (CMR) of patients with congenital heart disease (CHD) has become routine clinical practice. However, existing CMR protocols focus predominantly on patients with ischemic heart disease, and information is limited on the types of patient with CHD who benefit from CMR investigation, and in what ways. Therefore the aim of this study was to answer the questions: What type of patients were studied by CMR in a centre specializing in paediatric and adult CHD management? What questions were asked, which protocols were used and were the questions successfully answered? To answer these questions, we conducted a cohort study of all 362 patients that received routine clinical CMR during 2007 at the Department of Paediatric Cardiology and Congenital Heart Disease at the Deutsches Herzzentrum München. Results: Underlying diagnosis was in 33% Fallot's tetralogy, 17% aortic coarctation, 8% Ebstein's disease, 6% Marfan's disease, 4% single ventricle with Fontan-like circulation, and 32% others. Median age was 26 years (7 days - 75 years). Ventricular volumes were assessed in 67% of the patients; flow in 74%; unknown anatomy only in 9%; specific individual morphology of known anatomy in 83%; myocardial fibrosis in 8%; stress-induced myocardial perfusion defects in 1%. Only in 3% of the cases the question could not be fully answered. Conclusion: Contrary to common belief, routine CMR of patients with CHD was not requested to address global anatomical questions so much as to clarify specific questions of morphology and function of known anatomy. The CMR protocols used differed markedly from those widely used in patients with ischemic heart disease. © 2008 Fratz et al; licensee BioMed Central Ltd.

Pulmonary artery size and function after fontan operation at a young age - Robbers-Visser, D.; Helderman, F.; Strengers, J.L.; Van Osch-Gevers, L.; Kapusta, L.; Pattynama, P.M.; Bogers, A.J.; Krams, R.; Helbing, W.A. (Journal of Magnetic Resonance Imaging, 2008)
Purpose: To assess pulmonary artery (PA) size, flow variables, and wall shear stress (WSS) in patients after Fontan operation at a young age. Materials and Methods: Flow in the branch PA was obtained with phase contrast velocity-encoded cardiovascular magnetic resonance imaging in 14 patients before and after low-dose dobutamine stress (7.5 μg/kg/min) and in 17 healthy controls at rest. Results: At rest, stroke index, total flow, average, and peak flow rate were all statistically significantly lower in patients than in controls (P < 0.001). With stress-testing, all variables increased in patients (P < 0.001), apart from stroke index, which did not change. At rest, branch PA area did not differ between patients and controls. Distensibility was lower in patients than in controls (P < 0.001). With stress-testing, area and distensibility did not change. At rest, WSS was lower in patients than in controls (P < 0.001). WSS increased with stress-testing (P < 0.001), but not to the same levels as during resting conditions of the control group. Conclusion: PA size is normal long-term after Fontan operation at a young age. Flow variables, distensibility, and WSS are significantly lower compared to healthy controls, and do not show adequate reactions with stress-testing, which is suggestive of pulmonary artery endothelial and/or vascular dysfunction. © 2008 Wiley-Liss, Inc.
Keywords: Endothelial function; Fontan operation; Pulmonary artery size; Shear stress

In-training examination and the general pediatric certification examination: Are there lessons? - Long, S.S. (Journal of Pediatrics, 2008)

Fontan Fenestration Closure Has No Acute Effect on Exercise Capacity but Improves Ventilatory Response to Exercise - Meadows, J.; Lang, P.; Marx, G.; Rhodes, J. (Journal of the American College of Cardiology, 2008)
Objectives: The aim of this study was to prospectively examine the effects of elective Fontan fenestration closure upon exercise capacity and ventilatory abnormalities. Background: For patients undergoing Fontan procedures as palliation of single ventricle physiology, the addition of a fenestration to the procedure mitigates perioperative morbidity. Although some fenestrations may close spontaneously, many remain patent and subject patients to arterial hypoxemia and risk for paradoxical emboli. For these reasons fenestration closure is routinely performed post-operatively in the cardiac catheterization laboratory. Although closure of Fontan fenestrations typically results in an immediate improvement in systemic arterial oxygen saturation, it is also associated with an acute decrease in cardiac index and systemic O2 delivery. The sum result of these physiologic changes upon exercise capacity has not been examined. Methods: Twenty consecutive patients, age 5 to 46 (median 10) years, underwent pre- and post-fenestration closure exercise testing with expiratory gas analysis. Results: Before fenestration closure, peak oxygen consumption (VO2) was depressed and there was systemic desaturation at rest that worsened with exercise. The ventilatory response to exercise was also abnormal, characterized by elevation of the minute ventilation (VE)/CO2 elimination slope (VE/VCO2), a low end-tidal CO2, and high end-tidal O2 at the ventilatory anaerobic threshold. Although arterial saturation improved significantly after fenestration closure, there was no change in peak VO2 (70.9 ± 18.6% to 74.0 ± 18.6%, p = NS), heart rate, or O2 pulse at peak exercise. In contrast, ventilatory abnormalities (VE/VCO2) improved considerably (44.4 ± 10.9 to 33.3 ± 5.5, p ≤ 0.001). Conclusions: Fontan fenestration closure does not significantly improve peak VO2. However, ventilatory abnormalities improve considerably. © 2008 American College of Cardiology Foundation.
Keywords: congenital heart disease; exercise testing; fenestrated Fontan

Liver and Cardiac Function in the Long Term After Fontan Operation - Camposilvan, S.; Milanesi, O.; Stellin, G.; Pettenazzo, A.; Zancan, L.; D'Antiga, L. (Annals of Thoracic Surgery, 2008)
Background: Patients who underwent Fontan operation have some degree of liver disease. We aimed to assess the long-term liver and cardiac function after Fontan operation. Methods: Patients enrolled underwent physical examination, biochemical tests (aspartate aminotransferase, alanine aminotransferase, gamma glutamyl transpeptidase, bilirubin, international normalized ratio, coagulation factor V, protein profile, fecal alpha-1-antitrypsin), echocardiogram, and liver ultrasonography. A liver disease score was adopted to compare the degree of liver involvement with hemodynamic features. Results: The study enrolled 34 patients, median age 14.7 years (range, 4.1 to 26.7), 26 with a residual left ventricle, 8 with a residual right ventricle, affected by tricuspid atresia (17), pulmonary atresia (4), hypoplastic left heart syndrome (5), double-outlet right ventricle (2), single left ventricle (2), and miscellaneous (4), with median follow-up of 11.5 years (range, 1.7 to 23.3). We found hepatomegaly in 18 of 34 (53%), splenomegaly in 3 of 33 (9%), abnormal transaminases in 10 of 33 (30%), elevated γGT in 19 of 31 (61%), elevated bilirubin in 10 of 31 (32%), coagulopathy in 17 of 29 (58%), and protein-losing enteropathy in 4 of 21 (19%). Median heart rate z-score was -1.72. Hepatic dysfunction was strictly correlated to low cardiac index (r2 = 0.34, p = 0.008) and to a lesser extent to reduced heart rate (r2 = 0.18, p = 0.07). Conclusions: In children who underwent Fontan operation, hepatic dysfunction is correlated with low cardiac index and reduced heart rate. Maintaining or reestablishing a normal cardiac index might prevent or reduce liver disease in the long-term. © 2008 The Society of Thoracic Surgeons.

Usefulness of Cardiac Magnetic Resonance Imaging Combined With Low-Dose Dobutamine Stress to Detect an Abnormal Ventricular Stress Response in Children and Young Adults After Fontan Operation at Young Age - Robbers-Visser, D.; Jan ten Harkel, D.; Kapusta, L.; Strengers, J.L.; Dalinghaus, M.; Meijboom, F.J.; Pattynama, P.M.; Bogers, A.J.; Helbing, W.A. (American Journal of Cardiology, 2008)
After Fontan operation, patients are limited in increasing cardiac output and in exercise capacity. This has been related to impaired preload or other factors leading to decreased global ventricular performance with stress. To study these factors, the stress responses of functionally univentricular hearts were assessed at rest and during low-dose dobutamine stress using cardiovascular magnetic resonance imaging. Thirty-two patients after Fontan completion at young age were included (27 with total cavopulmonary connection, 5 with atriopulmonary connection; mean age 13.3 years, range 7.5 to 22.2; 23 male patients; median follow-up after Fontan operation 8.1 years, range 5.2 to 17.8). A multiphase short-axis stack of 10 to 12 contiguous slices of the systemic ventricle was obtained at rest and during low-dose dobutamine stress cardiovascular magnetic resonance imaging (maximum 7.5 μg/kg/min). With stress-testing, heart rate, ejection fraction, and cardiac index increased adequately (p <0.001). There was an abnormal decrease in end-diastolic volume and an adequate decrease in end-systolic volume (p <0.001). Stroke volume did not change with stress testing (p = 0.15). At rest, dominant left ventricles had higher ejection fractions than dominant right ventricles (p = 0.01), but this difference disappeared with stress testing. In conclusion, a functionally univentricular heart after Fontan completion at young age has an adequate increase in ejection fraction with β-adrenergic stimulation. However, as a result of impaired preload with stress, cardiac output can be increased only by increasing heart rate. © 2008 Elsevier Inc. All rights reserved.

Prenatal diagnosis of topsy-turvy heart - Jaeggi, E.; Chitayat, D.; Golding, F.; Kim, P.; Yoo, S.-J. (Cardiology in the Young, 2008)
We describe two siblings of consanguineous parents with a prenatal diagnosis of a currently unique form of congenital cardiac disease characterized by superior-inferior atrial and ventricular arrangement, concordant atrioventricular and ventriculo-arterial connections with normal arterial relationships, and a bizarre topography of the ventricular outlets, with the arterial poles being displaced posterior-inferiorly within the thorax. The abnormally low position of the aortic arch resulted in elongation and stretching of the airways, with severe compression of the trachea and left main bronchus in the surviving sibling. The finding of the same rare abnormality in a son and a daughter born to consanguineous parents supports a single gene disorder with a recessive mode of inheritance. © 2008 Cambridge University Press.
Keywords: Fetal echocardiography; Malposition; Superior-inferior ventricles

The development of the pediatric cardiac quality of life inventory: A quality of life measure for children and adolescents with heart disease - Marino, B.S.; Shera, D.; Wernovsky, G.; Tomlinson, R.S.; Aguirre, A.; Gallagher, M.; Lee, A.; Cho, C.J.; Stern, W.; Davis, L.; Tong, E.; Teitel, D.; et al. (Quality of Life Research, 2008)
Objective: Mortality after surgery for congenital heart disease (CHD) has decreased. Quality of life (QOL) assessment in survivors has become increasingly important. The purpose of this project was to create the Pediatric Cardiac Quality of Life Inventory (PCQLI). Methods: Items were generated through nominal groups of patients, parents, and providers. The pilot PCQLI was completed by children (age 8-12), adolescents (age 13-18), and their parents at three cardiology clinics. Item reduction was performed through analysis of items, principal components, internal consistency (IC), and patterns of correlation. Results: A total of 655 patient-parent pairs completed the pilot PCQLI. Principal components identified included: impact of disease (ID); psychosocial impact (PI); and emotional environment (EE). After item reduction ID and PI had excellent IC (ID = 0.88-0.91; PI = 0.78-0.85) and correlated highly with each other (0.81-0.90) and with the total score (TS) (ID = 0.95-0.96; PI = 0.87-0.93). EE was not correlated with ID, PI, or TS and was removed from the final forms. Two-ventricle CHD patients had a higher TS than single-ventricle CHD patients across all forms (P < 0.001). Conclusion: The PCQLI has patient and parent-proxy forms, has wide age range, and discriminates between CHD subgroups. The ID and PI subscales of the PCQLI have excellent IC and correlate well with each other and the TS. © 2008 Springer Science+Business Media B.V.
Keywords: Children/adolescents; Congenital heart disease; Quality of life

Effects of transcatheter closure of fontan fenestration on exercise tolerance - Momenah, T.S.; Eltayb, H.; Oakley, R.E.; Qethamy, H.A.; Faraidi, Y.A. (Pediatric Cardiology, 2008)
Baffle fenestration is associated with a significantly better outcome in standard and high-risk patients undergoing completion of Fontan. We report the effects of subsequent transcatheter closure of fenestration on exercise capacity and oxygen saturation. Sixteen patients with a mean age of 10.3 years underwent Amplatzer septal occluder (ASO) device transcatheter closure of Fontan fenestration. All had a fenestrated Fontan operation 6 month to 8 years prior to the procedure. A stress test was performed before and after device closure of fenestration in 14 patients (2 patients did not tolerate stress test before the procedure). The fenestrations in all patients were successfully occluded with the use of the Amplatzer device occluder. No complications occurred during or after the procedure. O2 saturation increased from a mean 85.1 ± 7.89% to 94.5 ± 3.63% (p < 0.01) at rest and from 66.2 ± 12.86% to 87.2 ± 8.64% (p < 0.01) following exercise. Exercise duration has also increased from 8.22 ± 2.74 min to 10.29 ± 1.91 min (p < 0.05). Transcatheter closure of Fontan fenestration increases the duration of exercise capacity and increases O2 saturation at rest and after exercise. © 2007 Springer Science+Business Media, LLC.
Keywords: Fenestration closure; Fontan procedure; Transcatheter closure

Decreased Exercise Performance with Age in Children with Hypoplastic Left Heart Syndrome - Jenkins, P.C.; Chinnock, R.E.; Jenkins, K.J.; Mahle, W.T.; Mulla, N.; Sharkey, A.M.; Flanagan, M.F. (Journal of Pediatrics, 2008)
Objective: Children born with hypoplastic left heart syndrome (HLHS) may experience cardiac dysfunction after staged surgery or transplantation, which may worsen with age. We examined the hypothesis that exercise testing can address cardiovascular capacity and suggest interventions to improve quality of life. Study design: Children with HLHS ≥8 years old performed treadmill or bicycle ergometric testing at 4 centers. Results were compared with norms for age and sex. Results: Of the 42 participants, the mean age was 12.9 years (range, 8.5-17.0 years), 64% were boys, 20 had staged surgery, and 34 completed metabolic assessment. The percent of predicted maximal oxygen uptake (mVO2) was higher in younger children. Children aged 8 to 12 years achieved 70% of predicted mVO2; children aged 13 to 17 years achieved 60% of predicted mVO2 (P = .02). The percent of predicted peak heart rate trended higher in younger patients (83% versus 75%, P = .07). Electrocardiographic changes were more common in older children. In treadmill testing, patients who had a transplant had better exercise performance than patients who underwent staged surgery in percent of predicted exercise time (82% versus 54%, P < .0001) and peak rate-pressure product (241 × 103 versus 195 × 103, P = .02). The percent of predicted mVO2 did not differ between patients who had a transplant (66%) and patients who underwent staged surgery (61%, P = .25). Conclusion: Children with HLHS showed considerable age-related decline in exercise performance, regardless of surgical strategy. © 2008 Mosby, Inc. All rights reserved.

Feeding difficulties and growth delay in children with hypoplastic left heart syndrome versus d-transposition of the great arteries - Davis, D.; Davis, S.; Cotman, K.; Worley, S.; Londrico, D.; Kenny, D.; Harrison, A.M. (Pediatric Cardiology, 2008)
The objective of this study was to identify the incidence of feeding difficulties in infants with hypoplastic left heart syndrome (HLHS) and d-transposition of the great arteries (d-TGA). Congenital heart disease is a risk factor for growth failure. The etiologies include poor caloric intake, inability to utilize calories effectively, and increased metabolic demands. The goals of our study were to (1) identify feeding difficulties in infants with HLHS and d-TGA and (2) assess their growth in the first year of life. We performed a chart review of 27 consecutive infants with HLHS and 26 with d-TGA. Descriptive statistics were generated for demographic and clinical variables within each group and are presented as means ± standard deviations. HLHS and d-TGA groups were compared on time to achieving nutritional goals using the log rank test, on complication rate using the chi-square test, and on weight using the t-test. A significance level of 0.05 was used for all tests. Birth weight was similar for both the HLHS and d-TGA groups (3.19 ± 0.69 vs 3.35 ± 0.65 kg, respectively; p = 0.38). Infants with HLHS weighed less than those with d-TGA at l month (3.29 ± 0.58 vs 3.70 ± 0.60 kg, respectively; p = 0.021), 6 months (6.27 ± 1.06 vs 7.31 ± 1.02 kg, p = 0.003), and 12 months of age (8.40 ± 1.11 vs 9.49 ± 1.01 kg, p = 0.006). Time to achieving full caloric intake (at least 100 kcal/kg/day) for the HLHS group (24 ± 11.9 days) was significantly longer than for the d-TGA group (12.0 ± 11.2 days, p < 0.001). In addition, infants with HLHS had a higher incidence of feeding-related complications that those with d-TGA (48 vs 4%, respectively; p = 0.001). Compared to the d-TGA group, infants with HLHS weighed less at follow-up, took longer to reach nutritional goals, and had a much higher incidence of feeding-related complications. © 2007 Springer Science+Business Media, LLC.
Keywords: d-Transposition of the great arteries; Growth failure; Hypoplastic left heart syndrome; Nasogastric tube

Late follow-up of patients who underwent palliation for complex congenital heart disease in childhood - Hoffmann, A.; Wyler, F.; Günthard, J.; Grädel, E. (Congenital Heart Disease, 2008)
We report on a series of 12 patients with complex congenital heart disease who had reached adult life after surgical palliation in early childhood and who were systematically followed by clinical visits.: Patients were born between 1953 and 1979 and were followed up into 2007. All patients had complex lesions with single ventricle physiology and were palliated either by banding of the pulmonary artery or by creation of systemic-pulmonary shunts. Single operations were performed in 4 cases, and 8 patients had 1 or more further palliative interventions. Late corrective surgery and heart transplantation were performed in 1 patient each. Eight survivors reached a mean age of 36 years at follow-up (range 28-48), whereas 4 patients died at a mean age of 32 years (range 22-53). All patients were in New York Heart Association classes II and III. Complications during follow-up were bacterial endocarditis (3), cerebrovascular accidents (3), arrhythmias (3), need for pacemakers (2). Deaths occurred perioperatively at transplant (1), or were caused by sudden death (2), and hypoxia related to fall in blood pressure (1). Successfull pregnancies occurred in 3 patients with healthy (small) babies delivered by cesarean section in 2 of them, and vaginal delivery in 1. The course of life in these patients shows not only a wide spectrum with good quality of life in some of them but also a large number of potentially severe complications. Survival beyond 50 years is rare. © 2008, the Authors Journal compilation © 2008, Blackwell Publishing, Inc.
Keywords: Congenital Heart Disease; Long-Term; Palliation

HLHS - Congenital heart defect in high risk pregnancy unit in 2001-2007 - Karowicz-Bilińska, A.; Berner-Trabska, M.; Kazimierak, W.; Brzozowska, M.; Kowalska-Koprek, U.; Pasiński, J.; Kuś, E. (Ginekologia Polska, 2008)
Background: HLHS (hypoplastic left heart syndrome) is a serious congenital heart defect. In neonates with congenital heart disease HLHS accounts for nearly 25% of neonatal deaths. The etiology of HLHS is unknown. At present we expect to have those cases diagnosed in the second trimester of pregnancy. Aim: The main aim was to find the rate and outcome of the congenital heart defect - left heart hypoplasia (HLHS). Material and methods: All cases of this heart defect found in the High Risk Pregnancy Clinic in 2001-2007 were presented. Twice the congenital malformation was diagnosed after delivery and once during pregnancy - in the second trimester. All babies were delivered between 38 and 39 weeks of pregnancy, one by the spontaneous normal delivery, one by elective caesarean section and one by emergency caesarean section because of fetal distress during the delivery. All of the newborns were transported to the Pediatric Cardio surgery Unit of M.U. and operated in first weeks after delivery. Results: In two cases the operation was complicated and children died due to the cardiac arrest. One of the babies died before surgical correction. Two of the women, whose babies died after the operation gave birth to healthy newborns with no cardiac abnormalities. Conclusion: The HLHS is the most serious heart congenital malformation diagnosed often after the delivery because of lack of sufficient diagnostic system in healthy women. The prognosis for the children is bad, but the chance of giving birth to healthy children in the future is good. © 2008 Polskie Towarzystwo Ginekologiczne.
Keywords: Congenital heart defect; Hypoplastic left heart syndrome; Neonate

Identification of coronary artery disease in the pediatric cardiac transplant patient - Maiers, J.; Hurwitz, R. (Pediatric Cardiology, 2008)
Little data exist to identify pediatric patients who have developed transplant coronary artery vasculopathy (CAV). Transplant patients do not exhibit the usual signs of coronary disease, making diagnosis more difficult. The aim of this study is to assess the use of myocardial perfusion imaging to identify CAV in transplant patients and to derive an incidence of occurrence. We studied pediatric cardiac transplant recipients who have undergone myocardial perfusion imaging on a routine basis. All patients from September 1999 through November 2004 with nuclear perfusion scans were included. Twenty patients age 7-24 years (mean: 12.7), 11 male and 9 female, were studied by SPECT technetium 99M tetrofosmin imaging. Sixteen of the 20 patients were studied based on a newly instituted protocol for surveillance. Transplant was 1-14 years (mean: 7.9) earlier. Patients were also studied by stress echocardiography. Six of 20 patients (30%) had a positive perfusion scan. Ages ranged from 8 to 18 years (mean: 12). Time from transplant to positive scans ranged from 1 to 9 years (mean: 5.6). One patient showed the same perfusion defect as 2 years earlier. Five patients with positive nuclear perfusion scans showed the abnormality on the initial study; one had a previous negative study 6 months earlier. Four patients who demonstrated ischemia with exercise showed resolution at rest; the other two had no resting study. Five of these six patients with abnormal perfusion scans had negative stress echocardiograms. Only one patient identified with coronary involvement reported symptoms (exertional dyspnea). Hypertension and rejection episodes were similar in all patients and in those with positive nuclear scans. Of the six patients with positive nuclear perfusion scans, two demonstrated coronary disease at cardiac catheterization. Two patients with coronary disease at catheterization had normal nuclear perfusion scans; one of two had a normal stress echo. When three imaging modalities were used, the incidence of CAV was 30%. Symptoms in pediatric patients with CAV are seldom reported. Unfortunately, coronary arteriopathy occurs frequently and might be found as early as 1 year posttransplant. Six of 20 patients had abnormal perfusion; only 1 had any other noninvasive marker. Importantly, not all patients with CAV were identified by perfusion imaging, stress echocardiography, or coronary injection alone. Therefore, transplant patients need continued evaluation by multiple modalities for detection of developing coronary lesions. © 2007 Springer Science+Business Media, LLC.

Mechanical axial flow blood pump to support cavopulmonary circulation - Throckmorton, A.L.; Kapadia, J.; Madduri, D. (International Journal of Artificial Organs, 2008)
We are developing a collapsible, percutaneously inserted, axial flow blood pump to support the cavopulmonary circulation in infants with a failing single ventricle physiology. An initial design of the impeller for this axial flow blood pump was performed using computational fluid dynamics analysis, including pressure-flow characteristics, scalar stress estimations, blood damage indices, and fluid force predictions. A plastic prototype was constructed for hydraulic performance testing, and these experimental results were compared with the numerical predictions. The numerical predictions and experimental findings of the pump performance demonstrated a pressure generation of 2-16 mm Hg for 50-750 ml/min over 5,500-7,500 RPM with deviation found at lower rotational speeds. The axial fluid forces remained below 0.1 N, and the radial fluid forces were determined to be virtually zero due to the centered impeller case. The scalar stress levels remained below 250 Pa for all operating conditions. Blood damage analysis yielded a mean residence time of the released particles, which was found to be less than 0.4 seconds for both flow rates that were examined, and a maximum residence time was determined to be less than 0.8 seconds. We are in the process of designing a cage with hydrodynamically shaped filament blades to act as a diffuser and optimizing the impeller blade shape to reduce the flow vorticity at the pump outlet. This blood pump will improve the clinical treatment of patients with failing Fontan physiology and provide a unique catheter-based therapeutic approach as a bridge to recovery or transplantation. © Wichtig Editore, 2008.
Keywords: Artificial right ventricle; Blood pump; Cavopulmonary assist device; Fontan conversion; Heart pump; Pediatric circulatory support; Pediatric mechanical circulatory support; Pediatric ventricular assist device; Single ventricle physiology; Ventricular assist device

Resistant Hypoxemia in an Infant With a Right Ventricle-to-Pulmonary Artery (Sano) Shunt - Pieters, B.; Johnston, T.A.; Jones, T.K.; Cohen, G.; Jonmarker, C. (Journal of Cardiothoracic and Vascular Anesthesia, 2007)
Keywords: anesthesia; children; congenital heart disease; hypoplastic left-heart syndrome; infants; intensive care; surgery

Hypoplastic left heart syndrome: Attitudes among pediatric residents and nurses towards fetal and neonatal management - Renella, P.; Chang, R.-K.R.; Ferry, D.A.; Bart, R.D.; Sklansky, M.S. (Prenatal Diagnosis, 2007)
Objective: To determine the attitudes of pediatric residents and nurses towards fetal/neonatal management of hypoplastic left heart syndrome (HLHS), and their basis. Methods: Pediatric residents and nurses from three cardiac centers completed a survey with hypothetical scenarios in which their own fetuses or newborns had HLHS. While Institution A performs many HLHS surgeries, Institution C performs very few. Results: A total of 43% of residents and 50% of nurses would terminate an affected pregnancy. More experience (4 to 7 years, p = 0.04; >7 years, p = 0.05) and employment at institution C (p = 0.04) predicted termination. Expected better quality of life (QOL) (p = 0.02) and five-year survival >50% (p = 0.06) predicted not terminating. Postnatally, 48% of residents and 68% of nurses would choose, or seriously consider, comfort care. Marriage (p = 0.04) and more experience (4 to 7 years, p = 0.04; >7 years, p = 0.02) predicted choosing comfort care. Asian/Pacific Islander descent (p = 0.01) and expected 5-year survival >50% (p = 0.02) predicted choosing surgery. Conclusions: Approximately one-half of the pediatric residents and nurses surveyed would choose termination of pregnancy or seriously consider declining neonatal surgery, if their own fetus or infant had HLHS. These attitudes reflect perceptions of long-term QOL and survival. These attitudes may be of interest to caregivers who care for HLHS patients. Copyright © 2007 John Wiley & Sons, Ltd.
Keywords: Comfort care; Ethics; Pregnancy

Psychological distress in parents of children with severe congenital heart disease: The impact of prenatal versus postnatal diagnosis - Brosig, C.L.; Whitstone, B.N.; Frommelt, M.A.; Frisbee, S.J.; Leuthner, S.R. (Journal of Perinatology, 2007)
Objective: The purpose of the study was to evaluate coping and psychological functioning of parents of children prenatally or postnatally diagnosed with congenital heart disease. Study Design: Parents of 10 infants prenatally diagnosed by fetal echocardiogram and 7 infants postnatally diagnosed with severe congenital heart disease completed the Brief Symptom Inventory (BSI) at the time of diagnosis, at the time of birth and 6 months after birth. Prenatal and postnatal groups were compared to each other and to BSI norms. Result: Although both groups scored higher than test norms at the time of diagnosis, they did not differ significantly from each other. Six months after birth, the postnatal group scores did not differ from test norms, but the prenatal group scores were still significantly higher than test norms. The severity of the child's heart lesion at diagnosis was related to parental distress levels; parents with children with more severe lesions had higher BSI scores. Conclusion: Results suggest the need to provide parents with psychological support, regardless of the timing of diagnosis. Parents of children with more severe lesions may be at risk for higher levels of psychological distress, particularly over time.

Risk factors for adverse events during cardiovascular magnetic resonance in congenital heart disease - Dorfman, A.L.; Odegard, K.C.; Powell, A.J.; Laussen, P.C.; Geva, T. (Journal of Cardiovascular Magnetic Resonance, 2007)
Purpose: To assess the incidence and severity of adverse events (AE) associated with cardiovascular magnetic resonance (CMR) in a large cohort of patients with congenital heart disease and to identify independent risk factors for their occurrence. Methods: AEs were prospectively recorded from October 2002 through December 2004 and graded by 3 independent observers for severity, preventability, and attributability. The rate of adverse events was analyzed for each candidate variable using Fisher's exact test and independent predictors were identified by multiple logistic regression analysis. Results: There were 22 AEs among 1334 CMR studies (1.6%); 14 (63.5%) minor, 7 (32%) moderate, and 1 (4.5%) major. General anesthesia (GA) was used in 274 studies (20.5%) with 12 AEs (4.4%, p < 0.001). There were 7 AEs (6.3%, p = 0.001) in 112 studies on hospitalized patients, 5 AEs (5.2%, p = 0.018) in 97 patients under 1 year of age, and 3 AEs (2.2%, p = 0.479) in 134 patients with functional single ventricle. The highest rate of AEs was noted in inpatients under GA (10.4%, p < 0.001); most were in the intensive care unit. Use of anesthesia (OR 3.91 [95% CI 1.46, 10.48] p = 0.007) and inpatient status (OR 3.56 [95% CI 1.16, 10.89], p = 0.026) were independent predictors of AEs. Conclusions: CMR in patients with congenital heart disease has a low rate of AEs. Use of GA and examinations on hospitalized patients are independent risk factors for AEs with the most acutely ill patients at highest risk. Copyright © 2007 Informa Healthcare USA, Inc.
Keywords: Adverse Events; Complications; Congenital Heart Disease; Magnetic Resonance Imaging; Risk Factors

Psychosocial outcomes for preschool children and families after surgery for complex congenital heart disease - Brosig, C.L.; Mussatto, K.A.; Kuhn, E.M.; Tweddell, J.S. (Pediatric Cardiology, 2007)
The purpose of the current study was to assess the psychosocial outcomes of preschool-aged survivors (ages 3-6 years) of hypoplastic left heart syndrome (HLHS; n = 13) and transposition of the great arteries (TGA; n = 13). Parents completed the following measures: Pediatric Quality of Life Inventory, Impact on the Family Scale, Parenting Stress Index, Parent Behavior Checklist, and Child Behavior Checklist. Quality of life scores did not differ from those of healthy controls. Parents of children with HLHS reported more negative impact of the child's illness on the family and more parenting stress than parents of children with TGA. Parents of both groups of children were more permissive in their parenting style than parents of healthy controls. Children with HLHS had higher rates of attention and externalizing behavior problems than children with TGA. The results highlight the need for practitioners working with these children and families to ask about parental stress, family functioning, and behavioral expectations for the child in the context of routine medical/cardiac follow-up. © 2007 Springer Science+Business Media, LLC.
Keywords: Congenital heart disease; Psychosocial outcomes

Hypoplastic left heart syndrome - Connor, J.A.; Thiagarajan, R. (Orphanet Journal of Rare Diseases, 2007)
Hypoplastic left heart syndrome(HLHS) refers to the abnormal development of the left-sided cardiac structures, resulting in obstruction to blood flow from the left ventricular outflow tract. In addition, the syndrome includes underdevelopment of the left ventricle, aorta, and aortic arch, as well as mitral atresia or stenosis. HLHS has been reported to occur in approximately 0.016 to 0.036% of all live births. Newborn infants with the condition generally are born at full term and initially appear healthy. As the arterial duct closes, the systemic perfusion becomes decreased, resulting in hypoxemia, acidosis, and shock. Usually, no heart murmur, or a non-specific heart murmur, may be detected. The second heart sound is loud and single because of aortic atresia. Often the liver is enlarged secondary to congestive heart failure. The embryologic cause of the disease, as in the case of most congenital cardiac defects, is not fully known. The most useful diagnostic modality is the echocardiogram. The syndrome can be diagnosed by fetal echocardiography between 18 and 22 weeks of gestation. Differential diagnosis includes other left-sided obstructive lesions where the systemic circulation is dependent on ductal flow (critical aortic stenosis, coarctation of the aorta, interrupted aortic arch). Children with the syndrome require surgery as neonates, as they have duct-dependent systemic circulation. Currently, there are two major modalities, primary cardiac transplantation or a series of staged functionally univentricular palliations. The treatment chosen is dependent on the preference of the institution, its experience, and also preference. Although survival following initial surgical intervention has improved significantly over the last 20 years, significant mortality and morbidity are present for both surgical strategies. As a result pediatric cardiologists continue to be challenged by discussions with families regarding initial decision relative to treatment, and long-term prognosis as information on long-term survival and quality of life for those born with the syndrome is limited. © 2007 Connor and Thiagarajan; licensee BioMed Central Ltd.

Physical activity levels in children and adolescents are reduced after the Fontan procedure, independent of exercise capacity, and are associated with lower perceived general health - McCrindle, B.W.; Williams, R.V.; Mital, S.; Clark, B.J.; Russell, J.L.; Klein, G.; Eisenmann, J.C. (Archives of Disease in Childhood, 2007)
Objectives: To determine physical activity levels in paediatric patients who underwent the Fontan procedure, and their relationship to functional status and exercise capacity. Study Design: We studied 147 patients (ages 7-18 years) at a median of 8.1 years after Fontan, as part of the Pediatric Heart Network cross-sectional study of Fontan survivors. Assessment included medical history, self-reported physical activity, parent-completed Child Health Questionnaire (CHQ), cardiopulmonary exercise testing and physical activity level measured by accelerometry (MTI Actigraph). Results: Measured time spent in moderate and vigorous activity was markedly below normal at all ages, particularly in females, and was not significantly related to self-reported activity levels, or to maximum VO2, VO2 at anaerobic threshold or maximum work rate on exercise testing. Lower measured activity levels were significantly related to lower perceived general health but not to self-esteem, physical functioning, social impact of physical limitations or overall physical or psychosocial health summary scores. Reduced exercise capacity was more strongly related than measured activity levels to lower scores in general health, self-esteem and physical functioning. Conclusions: Physical activity levels are reduced after Fontan, independent of exercise capacity, and are associated with lower perceived general health but not other aspects of functional status.

Tension chylothorax in two pediatric patients - Wheeler, A.D.; Tobias, J.D. (Paediatric Anaesthesia, 2007)
Although the accumulation of gas is the most common cause of an expanding interpleural space, the presence of other structures or substances (hydrothorax, gastrothorax, hemothorax, urohemothorax, pyothorax, and chylothorax) under pressure may be sufficient to cause hemodynamic and respiratory compromise. We present two pediatric patients that developed hemodynamic and respiratory effects secondary to a chylothorax. The first patient presented in respiratory distress and cardiovascular collapse 4 weeks after a Fontan procedure. Placement of a chest tube resulted in the release of chyle under pressure and prompt resolution of hemodynamic and respiratory symptoms. The second patient was a 2100 g neonate who developed a chylothorax during an episode of sepsis following gastroschisis repair. On two separate occasions, the development of the chylothorax was associated with tachycardia, oliguria, and increased requirements during mechanical ventilation. Chest tube placement resulted in the release of chyle under pressure and resolution of the symptoms. These two cases demonstrate that chylothorax like pneumothorax can have deleterious effects on hemodynamic and respiratory function. © 2007 The Authors.
Keywords: Chyle; Chylothorax; Pleural effusion

Surgical Management of Ebstein's Anomaly - Stulak, J.M.; Dearani, J.A.; Danielson, G.K. (Pediatric Cardiac Surgery Annual, 2007)
Ebstein's malformation is a congenital anomaly of the tricuspid valve and right ventricle. Surgical repair of Ebstein's anomaly improves functional class and exercise tolerance, eliminates right-to-left intracardiac shunting (if present), and reduces the incidence of supraventricular tachyarrhythmias. As a result, quality of life and survival are improved. Because of the variable degree of malformation present, repair is predicated on favorable anatomic factors, most importantly the arrangement of the anterior leaflet of the tricuspid valve. When anatomic derangements threaten a durable tricuspid valve repair, valve replacement with protection of the conduction tissue and right coronary artery should be performed. The vast majority of patients can undergo a biventricular repair. The application of the bidirectional cavopulmonary anastomosis is reserved for patients with poor right ventricular function. Freedom from reoperation after tricuspid valve repair is similar when compared with valve replacement. In the current era, overall early mortality after surgical repair in children and adults has fallen to less than 3% in experienced centers. Surgical treatment of the symptomatic neonate remains a significant challenge, with approaches that include either a biventricular or single ventricle algorithm. © 2007 Elsevier Inc. All rights reserved.
Keywords: congenital tricuspid valve; Ebstein's anomaly; heart defect

Evolving Anatomic and Electrophysiologic Considerations Associated With Fontan Conversion - Mavroudis, C.; Backer, C.L.; Deal, B.J.; Stewart, R.D.; Franklin, W.H.; Tsao, S.; Ward, K. (Pediatric Cardiac Surgery Annual, 2007)
The principles of Fontan conversion with arrhythmia surgery are to restore the cardiac anatomy by converting the original atriopulmonary connection to a total cavopulmonary artery extracardiac connection and treat the underlying atrial arrhythmias. Successful outcomes of this procedure are dependent on a thorough understanding of several factors: the patient's fundamental diagnosis of single-ventricle anatomy, the resultant cardiac configuration from the original atriopulmonary Fontan connection, right atrial dilatation that leads to atrial flutter or fibrillation, and associated congenital cardiac anomalies. The purpose of this article is to present some of the more challenging anatomic and electrophysiologic problems we have encountered with Fontan conversion and arrhythmia surgery and the innovative solutions we have used to treat them. The cases reviewed herein include: takedown of a Bjork-Fontan modification, right ventricular hypertension and tricuspid regurgitation after atriopulmonary Fontan for pulmonary atresia and intact ventricular septum, takedown of atrioventricular valve isolation patch for right-sided maze procedure, resultant hemodynamic considerations leading to intraoperative pulmonary vein stenosis after Fontan conversion, unwanted inferior vena cava retraction during the extracardiac connection, right atrial cannulation in the presence of a right atrial clot, distended left superior vena cava causing left pulmonary vein stenosis, dropped atrial septum, and the modified right-sided maze procedure for various single-ventricle pathology. Since 1994 we have performed Fontan conversion with arrhythmia surgery on 109 patients with a 0.9% mortality rate. We attribute our program's success in no small measure to the strong collaborative efforts of the cardiothoracic surgery and cardiology teams. © 2007 Elsevier Inc. All rights reserved.
Keywords: arrhythmia; Fontan; maze procedure; single ventricle

Cardiovascular diseases in children - Tom-Revzon, C. (U.S. Pharmacist, 2007)
Cardiovascular diseases are becoming increasingly prevalent in children, due at least in part to the rise in childhood obesity. Public awareness is also increasing, and treatment options are improving. Pharmacists have the responsibility of counseling children and their caregivers about pharmacologic and nonpharmacologic therapies and interventions that can improve long-term prognosis. Adherence to complex medication regimens is key to optimal management. In cases of CHDs, for example, pharmacists can provide education about the rationale for drug therapy, and in cases of arrhythmia, they can obtain a thorough medication history to assist in diagnosis or avoidance. More important, pharmacists can stress the possibility of preventing the onset of cardiovascular diseases and encourage lifestyle changes that can help reduce the occurrence of hypertension and obesity.

Adults Undergoing Cardiac Surgery at a Children's Hospital: An Analysis of Perioperative Morbidity - Rossano, J.W.; Smith, E.O.'.; Fraser Jr., C.D.; McKenzie, E.D.; Chang, A.C.; Hemingway, A.; Price, J.F.; Dickerson, H.A.; Mott, A.R. (Annals of Thoracic Surgery, 2007)
Background: Limited data exist regarding the perioperative morbidity profile of adults who have cardiac operations at pediatric facilities. Methods: A retrospective review (January 2000 to December 2004) of patients (aged 18 years or older) who underwent cardiac surgery at our pediatric institution was performed. Results: There were 149 cardiac operations performed in 135 patients. There were 2 early deaths. There were 70 preoperative noncardiac morbidities in 49 patients (36%) and 140 preoperative cardiac morbidities in 78 patients (58%). Preoperative arrhythmia (n = 76) and moderate or greater ventricular systolic dysfunction (n = 24) were most common. There were 51 postoperative adverse noncardiac events in 32 patients (24%). Renal insufficiency (> 0.5 mg/dL baseline change; n = 8) was most common. There were 53 postoperative adverse cardiac events in 44 patients (33%). Ventricular tachycardia (n = 13) was most common. Risk factors for postoperative adverse noncardiac events included preoperative histories of New York Heart Association (NYHA) class III or greater (p < 0.001), seizure (p = 0.04), and psychiatric disorder (p = 0.002). Risk factors for postoperative adverse cardiac events included older patient age (p = 0.001), preoperative functional single ventricle (p = 0.006), NHYA class III or greater (p = 0.003), atrial fibrillation/flutter (p < 0.001), and ventricular tachycardia or fibrillation (p = 0.04). Conclusions: Postoperative adverse events occur frequently when adults undergo cardiac operations at children's hospitals. Older patient age, preoperative arrhythmias, and preoperative NHYA class are predictors of postoperative adverse cardiac events. © 2007 The Society of Thoracic Surgeons.

Quality of life in children with hypoplastic left heart syndrome - Mellander, M.; Berntsson, L.; Nilsson, B. (Acta Paediatrica, International Journal of Paediatrics, 2007)
Aim: To measure quality of life in children with hypoplastic left heart syndrome and their families. Methods: A questionnaire exploring socioeconomic status, structure and function of networks and psychological well-being was completed by the families of all 18 patients older than 2 years (age range 2.7-10.6). The results were compared with those of 180 healthy Swedish children matched for age and sex. Results: There were no significant differences between the groups in any of the aspects of socioeconomic status. Study group parents had not more available time for their child (p < 0.05) and more separations/divorces (p < 0.01). The patients had lower self-esteem (p < 0.05), more psychosomatic symptoms (p < 0.001) and lower peer acceptance (p < 0.01) than control children. Conclusion: With regard to psychological well-being, quality of life was significantly lower in children with hypoplastic left heart syndrome than in healthy controls. © 2006 The Author(s).
Keywords: Congenital heart defects; HLHS; Quality of life

Health-related quality of life: A closer look at related research in patients who have undergone the Fontan operation over the last decade - Pike, N.A.; Evangelista, L.S.; Doering, L.V.; Koniak-Griffin, D.; Lewis, A.B.; Child, J.S. (Heart and Lung: Journal of Acute and Critical Care, 2007)
The advancements in surgical technique and perioperative care have significantly improved the survival of children with single ventricle (SV) congenital heart disease (CHD) over the past decade. The population who have undergone the Fontan operation are growing into adulthood and facing many unique challenges. Past research has focused on functional and neurodevelopmental outcomes with inferences made to health-related quality of life (HRQOL). With the population who have undergone the Fontan operation surviving into adulthood, little research has been directed toward the self-report of HRQOL in adolescents and young adults after surgical palliation. Questions still remain on how these patients will transition into adulthood and whether they will live normal productive lives. This article reviews the literature related to HRQOL in the SV subgroup of CHD. In addition, an overview of newly developed disease-specific HRQOL instruments is presented as well as limitations and future research in HRQOL of the SV Fontan population. © 2007 Mosby, Inc. All rights reserved.

Infant Heart Transplantation Ten Years Later-Where Are They Now? - Gandhi, S.K.; Canter, C.E.; Kulikowska, A.; Huddleston, C.B. (Annals of Thoracic Surgery, 2007)
Background: Many uncertainties regarding the fate of children undergoing heart transplantation as infants were present when we and others embarked on this program. Although no truly long-term results are available, a significant cohort of children has now reached preteen and early teenage status. We reviewed our group of infants transplanted more than 10 years ago to assess survival and quality of life as they approach their teenage years. Methods: We retrospectively reviewed the medical records of all infant (younger than 6 months of age) heart transplant recipients, transplanted between 1988 and 1995, to ascertain survival statistics, incidence of complications, and current health status. Results: A total of 42 patients were identified. The majority of these underwent transplantation for hypoplastic left heart syndrome. Eleven patients have died, 4 early and 7 late. The actual survival at 10 years is 76%. Twenty-seven of the 31 long-term survivors attend regular school; 4 are in special education classes owing to developmental delay. Five patients take medication for attention-deficit disorder. Malignancies have been discovered in 5, and 1 died secondary to this. Six patients have significant renal insufficiency, 1 of whom has undergone renal transplantation. One patient has undergone retransplantation for coronary artery disease. One patient required reoperation for supravalvar aortic stenosis. Other general medical problems that are being treated include sleep apnea (n = 1), hypertension (n = 5), and recurrent pneumonias (n = 1). Conclusions: Although these children require ongoing medical attention, including daily medications and regular follow-up visits, most have a satisfactory quality of life and behave much like normal children. © 2007 The Society of Thoracic Surgeons.

Psychological symptoms in patients after surgery for congenital cardiac disease - Geyer, S.; Norozi, K.; Zoege, M.; Kempa, A.; Buchhorn, R.; Wessel, A. (Cardiology in the Young, 2006)
Aims: We studied a population of patients with surgically corrected congenital cardiac disease to determine whether limitations in activity, impaired cardiac performance, and perception of body image have effects on psychological symptoms. Methods: We undertook medical examinations, and carried out standardized interviews, in 361 patients aged between 14 and 45 years with surgically corrected congenital cardiac disease. From this data, findings from 343 patients were suitable for analysis. Subjectively reported limitations in activity were classified according to the system proposed by the New York Heart Association, while cardiopulmonary capacity was used as the indicator of cardiac performance. The Brief Symptom Inventory was used for assessing psychological symptoms, such as somatization, obsession-compulsion, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, and psychoticism. The Body Image Questionnaire was used to depict attitudes towards body image, which is assessed on the two subscales of rejection of the body and vitality. Multivariate regression analyses were conducted separately for females and males, taking into account age and socio-economic position. Results: Impairments of everyday activities had only a few substantial associations with psychological symptoms. No significant effects of cardiac functional capacity as a standardized physiological measure emerged. Psychological symptoms were strongly influenced by perceptions of body image, particularly if they rejected it, this holding particularly for males. There were no gender differences in terms of psychological symptoms. Conclusions: Limitations of activity, and impaired cardiac performance, have only minor effects on psychological symptoms in patients with surgically corrected congenital cardiac disease. The perception of body image was the strongest predictor, especially if patients rejected their body as a result of disfigurement or perceived deficiency. © 2006 Cambridge University Press.
Keywords: Body image; Cardiac performance; Gender; Limitations of activity

Neoaortic Root Modification for Late Thrombosis After Norwood Palliation - Graham, E.M.; Shakir, H.; Atz, A.M.; Ringewald, J.M.; Bradley, S.M. (Annals of Thoracic Surgery, 2006)
A 5-year-old child with hypoplastic left heart syndrome presented with myocardial infarction 2 years after Fontan completion. Evaluation identified a thrombus in his native aortic root. Retrospective review of a prior catheterization revealed stasis in the native aortic root. Surgical thrombectomy was performed after failed medical management. The neoaortic root was revised at the time of thrombectomy in an attempt to reduce stasis in the native aortic root. This case suggests the need to identify anatomic findings that may predispose to coronary artery thrombus formation after Norwood palliation. © 2006 The Society of Thoracic Surgeons.

The influence of congenital heart disease on psychological conditions in adolescents and adults after corrective surgery - Norozi, K.; Zoege, M.; Buchhorn, R.; Wessel, A.; Geyer, S. (Congenital Heart Disease, 2006)
Objective: The present study was designed to examine psychological characteristics of adolescents and adults with operated congenital heart disease (ACHD). Particularly it was to be examined whether cardiological parameters may be associated with subjectively perceived impairments and measures of psychological distress. Patients: A total of 361 men (209) and women (152) between 14 and 45years underwent medical checkups and an interview on psychological and sociological issues. Setting: The medical part consisted of a complete cardiological examination including the classification of residual symptoms according to the New York Heart Association (NYHA), and spiroergometry. The Brief Symptom Inventory was used for depicting current psychological and somatic symptoms. These were assessed on 9 subscales: somatization, obsession-compulsion, interpersonal sensitivity, depression, anxiety, hostility, phobic anxiety, paranoid ideation, and psychoticism. Results: The analyses revealed statistically significant associations between the degree of NYHA class and psychological symptoms. These findings could not be reproduced for physical fitness as measured by peak oxygen consumption. No gender differences emerged. Conclusions: Our results suggest that psychological measures of ACHD are not directly dependent on their physical fitness or on the severity of residual symptoms. Instead, patients'subjective appraisal of their disease severity and the conviction to what degree one can depend on the operated heart may be important determinants of psychological states. © 2006 the Authors; Journal compilation © 2006 Blackwell Publishing, Inc.
Keywords: Congenital heart disease; Psychological characteristic; Spiroergometry

Initial experience with the development and numerical and in vitro studies of a novel low-pressure artificial right ventricle for pediatric fontan patients - Wang, R.; Lacour-Gayet, F.G.; Lanning, C.J.; Rech, B.A.; Kilfoil, P.J.; Hertzberg, J.; Shandas, R. (ASAIO Journal, 2006)
The Fontan operation, an efficient palliative surgery, is performed for patients with single-ventricle pathologies. The total cavopulmonary connection is a preferred Fontan procedure in which the superior and inferior vena cava are connected to the left and right pulmonary artery.The overall goal of this work is to develop an artificial right ventricle that can be introduced into the inferior vena cava, which would act to reverse the deleterious hemodynamics in post-Fontan patients. We present the initial design and computational analysis of a micro-axial pump, designed with the particular hemodynamics of Fontan physiology in mind. Preliminary in vitro data on a prototype pump are also presented. Computational studies showed that the new design can deliver a variety of advantageous operating conditions, including decreased venous pressure through proximal suction, increased pressure rise across the pump, increased pulmonary flows, and minimal changes in superior vena cava pressures. In vitro studies on a scaled prototype showed trends similar to those seen computationally. We conclude that a micro-axial flow pump can be designed to operate efficiently within the low-pressure, low-flow environment of cavopulmonary flows. The results provide encouragement to pursue this design to for in vitro studies and animal studies. ©2006Amercian Society of Artificial Internal Organs.

Successful ablation of atrioventricular nodal reentry tachycardia following the atriopulmonary Fontan procedure - Abrams, D.J.; Earley, M.J.; Sporton, S.C.; Schilling, R.J. (Europace, 2006)
Arrhythmia is a prevalent complication of the atriopulmonary Fontan procedure, most commonly macro-reentrant tachycardia within the right atrium as a consequence of long-term morphological and haemodynamic changes coupled with surgical intervention. We describe a patient with a long history of supraventricular arrhythmia following the atriopulmonary Fontan procedure identified as atrioventricular nodal reentry tachycardia at electrophysiological assessment. Despite anatomical and technical difficulties related to right atrial morphological changes and loss of the tricuspid annulus with its associated anatomical landmarks, the arrhythmia was successfully ablated using a combined antegrade and retrograde mapping approach. © 2006 Oxford University Press.
Keywords: Atrioventricular nodal reentry tachycardia; Fontan; Tricuspid atresia

Design of a large cross-sectional study to facilitate future clinical trials in children with the Fontan palliation - Sleeper, L.A.; Anderson, P.; T. Hsu, D.; Mahony, L.; McCrindle, B.W.; Roth, S.J.; Saul, J.P.; Williams, R.V.; Geva, T.; Colan, S.D.; Clark, B.J. (American Heart Journal, 2006)
Background: Clinical trials in children with congenital heart disease are often limited by the absence of the following: (1) a primary outcome that can be observed in a reasonable period; (2) information regarding health-related quality of life; (3) knowledge of the correlation between health status and ventricular function and exercise performance; (4) a sufficient number of children at a single institution to provide adequate statistical power; and (5) procedural and management differences between and within institutions. Methods: The NHLBI-funded Pediatric Heart Network designed a cross-sectional study of children aged 6 to 18 years, from 7 pediatric clinical centers, who had undergone a Fontan procedure as treatment for congenital heart disease. Health-related quality of life was measured by the Child Health Questionnaire and the Congenital Heart Adolescent and Teenager Questionnaire. Ventricular function was assessed by maximal exercise testing, echocardiography, cardiac magnetic resonance imaging, and B-type natriuretic peptide. The study was designed to detect a correlation of R ≥ 0.30 between health status scores and measures of ventricular function and performance in a subcohort with all study measures completed. Results: A total of 1078 children were screened by chart review; 644 (60%) were eligible. The consent rate was 85% and 546 children were enrolled. Acquisition of echocardiograms, B-type natriuretic peptide, and health status was ≥94%; completion rates were lower for maximal exercise testing (76%) and cardiac magnetic resonance imaging (41%). Conclusions: This large study provides unique information regarding the relationship between health status and clinical measures in post-Fontan patients that will facilitate the design of future randomized trials. © 2006 Mosby, Inc. All rights reserved.

Mechanical valve replacement of the systemic atrioventricular valve in children - Reiss, N.; Blanz, U.; Breymann, T.; Kind, K.; Bairaktaris, A.; Körfer, R. (ASAIO Journal, 2006)
In children with systemic atrioventricular valve disease (SAVVD), reconstructive surgery is the primary goal. However, in cases with severely dysplastic valves or failed repair, valve replacement is the only option. The purpose of this study was to assess the early and late outcome following mechanical valve replacement in SAVVD. Between 1989 and 2003, 31 children underwent mechanical valve replacement (19 St. Jude Medical, 12 Carbomedics) in SAVVD (27 mitral, 3 tricuspid in corrected transposition of the great arteries, 1 common in an univentricular heart) at our institution. The ages ranged from 3 months to 15 years (mean 4 years) and body weight varied between 4.2 and 57 kg (mean 13.3 kg). The size of prostheses ranged between 16 and 31 mm (mean 23.9 mm). The main indication for valve replacement was severe insufficiency of left atrioventricular valve (84%); 84% of the patients had had a previous cardiac operation. The overall hospital mortality was 6.5% The mean follow up was 7.7 years (range 2-13 years). Ninety percent of children represent sinus rhythm, 87% are in NYHA class I. All patients were placed on a regimen of Phenprocoumon aiming to maintain the international normalized ratio (INR) between 3.0 and 4.0. Since 1994, INR self-management of oral anticoagulation was performed either by the patient or his or her parents. There was no anticoagulation-related complication in this patient group. Mechanical valve replacement in left atrioventricular valve disease carries a low operative risk across the spectrum of pediatric age despite previous operations in most cases. Long-term survival and quality of life are good in nearly all cases. The rate of anticoagulation-related complications is very low, especially when INR self management is performed. Copyright © American Society of Artificial Internal Organs.

Unifocalization of Major Aortopulmonary Collaterals in Single-Ventricle Patients - Reinhartz, O.; Reddy, V.M.; Petrossian, E.; Suleman, S.; Mainwaring, R.D.; Rosenthal, D.N.; Feinstein, J.A.; Gulati, R.; Hanley, F.L. (Annals of Thoracic Surgery, 2006)
Background: Unifocalization of major aortopulmonary collateral arteries (MAPCAs) in pulmonary atresia with ventricular septal defect and intracardiac repair has become the standard of care. However, there are no reports addressing unifocalization of MAPCAs in single-ventricle patients. It is unknown whether their pulmonary vascular bed can be reconstructed and low enough pulmonary vascular resistance achieved to allow for superior or total cavopulmonary connections. Methods: We reviewed data on all patients with functional single ventricles and unifocalization procedures of MAPCAs. From 1997 to 2005, 14 consecutive children with various single-ventricle anatomies were operated on. Results: Patients had a median of three surgical procedures (range, 1 to 5). Two patients had absent, all others diminutive central pulmonary arteries, with an average of 3.5 ± 1.2 MAPCAs. Seven patients (50%) had bidirectional Glenn procedures, and 3 of these had Fontan procedures. Median postoperative pulmonary artery pressures measured 12.5 mm Hg (Glenn) and 14 mm Hg (Fontan), respectively. Six patients are alive today (46%), with 1 patient lost to follow-up. Three patients died early and 3 late after initial unifocalization to shunts. One other patient survived unifocalization, but was not considered a candidate for a Glenn procedure and died after high-risk two-ventricle repair. Another patient with right-ventricle-dependent coronary circulation died of sepsis late after Glenn. Conclusions: In selected patients with functional single ventricles and MAPCAs, the pulmonary vascular bed can be reconstructed sufficiently to allow for cavopulmonary connections. Venous flow to the pulmonary vasculature decreases cardiac volume load and is likely to increase life expectancy and quality of life for these patients. © 2006 The Society of Thoracic Surgeons.

Atrial natriuretic peptide: Could it be a marker for postoperative recurrent effusions after fontan circulation in complex congenital heart defects? - Alkan, T.; Sarioǧlu, A.; Samanli, Ü.B.; Sarioǧlu, T.; Akçevin, A.; Türkoǧlu, H.; Paker, T.; Aytaç, A. (ASAIO Journal, 2006)
Fontan operation and its modifications are used for the physiological correction of complex congenital heart malformations with functionally single ventricle. Atrial natriuretic peptide (ANP), a physiological diuretic and vasodilator that-together with the effects of cardiopulmonary bypass-plays an important role in the augmentation of capillary permeability in Fontan patients. The rise in right atrial pressure and wall stress is an important stimulus for the release of ANP.ANP levels were measured before and early after surgery in Fontan group (n = 20) and control group (n = 20, patients with simple cardiac defects) to study its influence on and association with mean right atrial pressure, pulmonary vascular resistance (PVR), systemic vascular resistance, amount of drainage during early and late postoperative period, duration of intensive care unit and hospital stay, and need for colloid supplement.Early postoperative ANP values showed a negative correlation with PVR (r = -0.55) and total drainage (r = -0.88). There was no significant change in ANP during surgery or in the postoperative period in control patients.Reduction of PVR and maintenance of efficient urine output are important in the management of Fontan circulation. We conclude that high levels of ANP measured early after Fontan operation can be used as a marker for the successful establishment of Fontan circulation in patients with complex congenital heart defects. Copyright © American Society of Artificial Internal Organs.

Pediatric cardiac transplantation - Alkhaldi, A.; Chin, C.; Bernstein, D. (Seminars in Pediatric Surgery, 2006)
Pediatric heart transplantation has undergone major changes over the past two decades, marked by a substantial improvement in survival, reduction in posttransplant complications, and enhancement in quality of life for transplant recipients. Actuarial survival has improved substantially in the last decade. Indications for pediatric heart transplant have changed as surgery for complex congenital heart lesions has evolved. There are now left and right ventricular assist devices that are suitable for use in infants as a bridge to transplantation. New immunosuppressive agents have reduced the risk of rejection while minimizing side effects and strategies to reduce the risk of graft coronary disease are beginning to show promise. Finally, true long-term survival for children after heart transplant has now been demonstrated and quality of life is excellent. © 2006 Elsevier Inc. All rights reserved.
Keywords: Cardiomyopathy; Congenital heart defects; Hypoplastic left heart syndrome; Myocarditis; Pediatric heart transplant; Ventricular dysfunction

Early and long-term prognostic value of Troponin-I after cardiac surgery in newborns and children - Bottio, T.; Vida, V.; Padalino, M.; Gerosa, G.; Stellin, G. (European Journal of Cardio-thoracic Surgery, 2006)
Background: Troponin-I (Tn-I) is a well-recognized early postoperative marker for myocardial damage in adults and children. The present prospective study was undertaken to investigate whether a postoperative Tn-I value higher than 35 μg/l is able to predict long-term outcome as it does in early postoperative course, after surgery for congenital heart defects (CHD). Materials and methods: Five hundred and twenty patients (median age 11 months; male 54.7%: 284 patients) undergoing congenital heart defect repair on cardiopulmonary by-pass were prospectively updated in our database including postoperative Tn-I values. Seventy of them (13.4%) (mean age 2.6 ± 5.8 months) (70/520) experienced low output syndrome in the early postoperative period. According to the complexity of their malformations, we have arbitrarily divided these patients into two groups: group A included atrial and ventricular septal defects (13 patients), while group B included hypoplastic left heart syndrome, atrio-ventricular canal, transposition of great vessels, tetralogy of Fallot, double outlet right ventricle, truncus arteriosus, total anomalous venous return, and other combined diseases (57 patients). These patients are the object of our study. We reviewed clinical, laboratory, and echocardiographic data performed in the immediate postoperative course (within 24 h) and in the follow-up. Results: In this study, 13 patients died (13/70 patients; 18.5%), 12 in group B and 1 in group A. In deceased patients, mean Tn-I value was 130 ± 175 μg/l (CK-MB 570 ± 280 μg/l). Conversely, survivors showed a lower mean Tn-I value (25.5 ± 28.9 μg/l; CK-MB 76 ± 86 μg/l). Overall, Tn-I peak value was higher than 35 μg/l in 19 patients (19/70; 27.2%); among these, 9 died (median Tn-I was 163 ± 186 μg/l), whereas in survivors it was 73.4 ± 37 μg/l (p = 0.37). The remaining four patients who died had a median Tn-I value of 21 μg/l. When Tn-I exceeded 35 μg/l (>100 μg/l in two cases), at echocardiogram a severely depressed cardiac function was evident. Nevertheless, at long-term follow-up (12 ± 6 months), the echocardiogram showed an enhanced cardiac performance with an ejection fraction of 70 ± 8.5% in all; none of these patients presented with worsened ventricular function. Conclusion: Cardiac Tn-I is a specific and sensitive marker of myocardial injury after cardiac surgery and it may predict early in-hospital outcomes. However, by long-term echocardiographic analysis, cardiac Tn-I value looses its prognostic significance and therefore it is not a predictor of long-term ventricular dysfunction. © 2006 Elsevier B.V. All rights reserved.
Keywords: Congenital heart defects; Echocardiographic follow-up; Prognostic value; Troponin-I

Extracorporeal membrane oxygenation after stage I reconstruction for hypoplastic left heart syndrome - Ravishankar, C.; Dominguez, T.E.; Kreutzer, J.; Wernovsky, G.; Marino, B.S.; Godinez, R.; Priestley, M.A.; Gruber, P.J.; Gaynor, W.J.; Nicolson, S.C.; Spray, T.L.; Tabbutt, S. (Pediatric Critical Care Medicine, 2006)
OBJECTIVE: Although extracorporeal membrane oxygenation (ECMO) is an acceptable strategy for children with refractory cardiac dysfunction after cardiac surgery, its role after stage I reconstruction for hypoplastic left heart syndrome and its variants is controversial. Our objective is to describe the outcome of "nonelective" ECMO after stage I reconstruction. DESIGN: Retrospective case series. SETTING: Pediatric cardiac intensive care unit. PATIENTS: Infants placed on ECMO after stage I reconstruction from January 1998 to May 2005. INTERVENTIONS: None. MEASUREMENTS AND MAIN RESULTS: Of the 382 infants who underwent stage I reconstruction during the study period, 36 (9.4%) required ECMO in the postoperative period. There were 22 infants with hypoplastic left heart syndrome. Indications for ECMO included inability to separate from cardiopulmonary bypass in 14 and cardiac arrest in 22. Fourteen infants (38.8%) survived to hospital discharge. Nonsurvivors had longer cardiopulmonary bypass time (150.1 ± 70.0 mins vs. 103.9 ± 30.0 mins, p =. 01). 9/14 infants (64%) supported with ECMO> than 24 hrs after stage I reconstruction survived while only 5/22 infants (22%) requiring ECMO< 24 hrs of stage I reconstruction survived (p =. 02). Of note, all five infants diagnosed with an acute shunt thrombosis were early survivors. Mean duration of ECMO was 50.1 ± 12.5 hrs for survivors and 125.2 ± 25.0 for nonsurvivors (p =. 01). 7/14 early survivors are alive at a median follow-up of 20 months (2-78 months). CONCLUSIONS: In our experience, ECMO after stage I reconstruction can be life saving in about a third of infants with otherwise fatal conditions. It is particularly useful in potentially reversible conditions such as acute shunt thrombosis and transient depression of ventricular function. Copyright © 2006 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Arrest; Cardiac; Extracorporeal membrane oxygenation; Hypoplastic left heart syndrome; Infant; Outcome

Wall shear stress is the primary mechanism of energy loss in the Fontan connection - Moyle, K.R.; Mallinson, G.D.; Occleshaw, C.J.; Cowan, B.R.; Gentles, T.L. (Pediatric Cardiology, 2006)
Long-term outcome following the Fontan operation may be affected by the amount of energy lost as blood flows through the anastomosis geometry. A method for detailed quantification of energy loss is applied to computational simulations of the flow in an atriopulmonary and a total cavopulmonary model. Five types of flow (near wall, slow recirculation, medium speed vortices, collision, and streamlined flow) are identified and their energy losses quantified. The presence of recirculation regions decreases the efficiency of the atriopulmonary model, and a region of increased energy loss is seen in the collision region in the total cavopulmonary model. However, the most significant energy loss is through wall shear stress, which is maximal in areas where there is rapid, near wall flow. © Springer Science+Business Media, Inc. 2006.
Keywords: Atriopulmonary; Cavopulmonary; Fontan connection; Hemodynamic energy losses

Right-Sided Maze Procedure for Atrial Tachyarrhythmias in Congenital Heart Disease - Stulak, J.M.; Dearani, J.A.; Puga, F.J.; Zehr, K.J.; Schaff, H.V.; Danielson, G.K. (Annals of Thoracic Surgery, 2006)
Background: Congenital heart disease (CHD) that causes right atrial dilatation is commonly associated with atrial flutter and/or fibrillation (AFl/F). To reduce late recurrence of AFl/F in patients undergoing repair of CHD, we utilized a concomitant right-sided maze procedure. Methods: From 1993 to 2003, 99 patients with CHD and associated AFl/F underwent a concomitant right-sided maze procedure at the time of CHD repair. Ages ranged from 9 to 72 years (median, 43 years). Atrial flutter and/or fibrillation was paroxysmal in 81 and chronic in 18; duration ranged from less than 1 month to 39.5 years (median, 2.9 years). Primary cardiac diagnoses were Ebstein anomaly (n = 47), other congenital tricuspid regurgitation (n = 19), univentricular heart (n = 11), isolated atrial septal defect (ASD, n = 8), tetralogy of Fallot (n = 8), and other (n = 6). Results: Other concomitant procedures included tricuspid valve repair or replacement (n = 70), ASD closure (n = 39), and pulmonary valve procedures (n = 18). There were 6 early deaths. At hospital dismissal, 83 patients were free of AFl/F and 63 were in sinus rhythm. Follow-up in 87 of the 93 early survivors extended up to 8 years (mean, 2.7 years). There were 4 late deaths, all from noncardiac causes. Of the 83 known late survivors, 77 (93%) were free of AFl/F. Eighty-two of the 83 survivors were in New York Heart Association class I or II. Conclusions: In patients with AFl/F associated with CHD, a concomitant right-sided maze procedure at the time of intracardiac repair is effective in reducing late recurrent AFl/F. Most patients enjoy an excellent quality of life. © 2006 The Society of Thoracic Surgeons.

Relationship of patient and medical characteristics to health status in children and adolescents after the Fontan procedure - McCrindle, B.W.; Williams, R.V.; Mitchell, P.D.; Hsu, D.T.; Paridon, S.M.; Atz, A.M.; Li, J.S.; Newburger, J.W. (Circulation, 2006)
Background - After the Fontan procedure, patients are at risk for suboptimal health status related to their complex healthcare experience, physiological limitations, medical complications, and guarded long-term prognosis. Methods and Results - In the Pediatric Heart Network cross-sectional study of Fontan survivors 6 to 18 years of age, parents completed the Child Health Questionnaire, and scores were related in multivariable analysis to patient and medical characteristics obtained from medical record review. For 537 patients (mean age at study, 11.9 years; 60% male) with a median age at Fontan of 2.8 years (range, 0.7 to 14.6 years), parent-reported patient morbidities included deficits in vision in 33%, speech in 27%, and hearing in 7%, as well as problems with attention in 46%, learning in 43%, development in 24%, behavior in 23%, anxiety in 17%, and depression in 8%. Child Health Questionnaire summary scores were significantly lower than the US population sample for Physical Functioning (mean Z score, -0.47±1.19; P<0.001) and Psychosocial Functioning (-0.28±1.08; P<0.001). Parent-reported medical conditions and long-term and current medical problems explained the greatest amount of variation in the Physical Functioning scores. Parent-reported patient conditions, including behavior, learning, anxiety, and attention problems and depression, explained the greatest amount of variation in the Psychosocial Functioning scores. Lower family income had a negative impact on both Physical and Psychosocial Functioning. Conclusions - There are deficits in health status in children and adolescents after the Fontan procedure. Strategies to address this problem might emphasize coordinated and effective prevention, detection, and management of noncardiac and psychosocial conditions, as well as specific targeting of patients from low-income households. © 2006 American Heart Association, Inc.
Keywords: Follow-up studies; Fontan procedure; Health status; Heart defects, congenital; Quality of life

Conversion of the failed Fontan circulation - Backer, C.L.; Deal, B.J.; Mavroudis, C.; Franklin, W.H.; Stewart, R.D. (Cardiology in the Young, 2006)
Many patients with a functional univentricular heart were treated in the 1970s and 1980s, using an atriopulmonary connection to create the Fontan circulation. Although this procedure, in many patients, was initially successful, and provided arterial saturations of oxygen close to normal, as these patients were followed over the years, in some cases they developed significant complications. One complication of the atriopulmonary connection is progressive right atrial dilation, which leads to atrial arrhythmias, such as atrial flutter or fibrillation. The combination of these two problems leads to low cardiac output, diminished quality of life, and poor categorization within the classification of the New York Heart Association. This, and other issues, has led most centres to abandon the atriopulmonary connection as a means of creating the Fontan circulation in favour of the lateral tunnel with cavopulmonary connections, or the extracardiac conduit.
Keywords: Arrhythmias; Atrioventricular valvar atresia; Cardiac failure; Double inlet ventricle; Functionally univentricular heart

Current management of late failure after classic Fontan modifications: Fontan conversions - Erek, E.; Yalcinbas, Y.K.; Sarioglu, A.; Sarioglu, T. (Thoracic and Cardiovascular Surgeon, 2006)
Background: Re-establishment of Fontan circulation by eliminating the drawbacks of classic Fontan modifications has been proposed recently to improve the functional class and quality of life of patients with failed Fontan circulation. Methods: Five patients underwent extracardiac and lateral tunnel Fontan conversion due to failure of the Fontan circulation, after classic Fontan modifications. All of the patients were female and mean age was 10.2 ± 2.2 years (range: 8-14 years). Previous Fontan modifications were atriopulmonary anastomosis in 3 and Kawashima operation in 2 patients. Time to re-operation for Fontan conversion was 6 ± 1.5 years (range: 4-8 years). Indications for re-operation were right heart failure, right atrial dilatation, and intractable atrial arrhythmias in patients with previous atriopulmonary anastomosis, progressive hypoxia and exercise intolerance in patients with previous Kawashima operation due to pulmonary arteriovenous fistulas. Previous atriopulmonary anastomoses were converted to intra-atrial or lateral tunnel Fontan operation with modified right atrial Maze procedure. Extracardiac Fontan completion was carried out after previous Kawashima operations by redirection of hepatic veins to the lungs. Results: There was no mortality and no major morbidity. All patients were discharged from the hospital in good condition and in sinus rhythm. No prolonged or recurrent effusions were observed. On follow-up, all patients were in sinus rhythm and had NYHA class I functional capacity. In two Kawashima patients, SpO2 gradually increased from 60% to 90% six months after the operation. Discussion: We suggest that Fontan conversion should be considered in patients with previous atriopulmonary anastomosis, when right atrial dilatation or intractable atrial arrhythmias with deteriorating functional status develops. Redirection of hepatic venous flow to lungs induces regression of pulmonary arteriovenous fistulas and improves arterial saturation in patients with previous Kawashima operation. © Georg Thieme Verlag KG.
Keywords: Atriopulmonary anastomosis; Fontan conversion; Fontan modifications; Kawashima procedure

Impact of cardiac rehabilitation on the exercise function of children with serious congenital heart disease - Rhodes, J.; Curran, T.J.; Camil, L.; Rabideau, N.; Fulton, D.R.; Gauthier, N.S.; Gauvreau, K.; Jenkins, K.J. (Pediatrics, 2005)
Objectives. The exercise capacity of children with congenital heart disease (CHD) is often depressed. This depression is thought to be attributable to (1) residual hemodynamic defects and (2) deconditioning secondary to physical inactivity. We hypothesized that this latter component would be ameliorated by a formal cardiac rehabilitation program designed specifically for children. The objective of this study was to characterize the effect of a cardiac rehabilitation program on the exercise performance of children with CHD and to define the physiologic mechanisms that might account for any improvements that are observed. Methods. Nineteen patients with CHD who were referred for exercise testing and found to have a peak oxygen consumption (VO2) and/or peak work rate <80% of predicted were enrolled in the study. Sixteen patients (11 Fontan patients, 5 with other CHD) completed the program and had postrehabilitation exercise tests, results of which were compared with the prerehabilitation studies. Results. Improvements were found in 15 of 16 patients. Peak VO2 rose from 26.4 ± 9.1 to 30.7 ± 9.2 mL/kg per min; peak work rate from 93 ± 32 to 106 ± 34 W, and the ventilatory anaerobic threshold from 14.2 ± 4.8 to 17.4 ± 4.5 mL/kg per min. The peak heart rate and peak respiratory exchange ratio did not change, suggesting that the improvements were not attributable merely to an increased effort. In contrast, the peak oxygen pulse rose significantly, from 7.6 ± 2.8 to 9.7 ± 4.1 mL/beat, an improvement that can be attributed only to an increase in stroke volume and/or oxygen extraction at peak exercise. No patient experienced rehabilitation-related complications. Conclusion. Cardiac rehabilitation can improve the exercise performance of children with CHD. This improvement is mediated by an increase in stroke volume and/or oxygen extraction during exercise. Routine use of formal cardiac rehabilitation may greatly reduce the morbidity of complex CHD. Copyright © 2005 by the American Academy of Pediatrics.
Keywords: Cardiac rehabilitation; Congenital heart defects; Exercise

Non-invasive assessment of ventricular force-frequency relations in the univentricular circulation by tissue Doppler echocardiography: A novel method of assessing myocardial performance in congenital heart disease - Cheung, M.M.H.; Smallhorn, J.F.; McCrindle, B.W.; Van Arsdell, G.S.; Redington, A.N. (Heart, 2005)
Objective: To describe the first clinical application of a novel tissue Doppler derived index of contractility, isovolumic acceleration (IVA), in the assessment of the ventricular myocardial force-frequency relation (FFR) in the univentricular heart (UVH). Design: Prospective study. Setting: Tertiary referral centre. Interventions: Non-invasive assessment of the myocardial FFR by tissue Doppler echocardiography during atrial pacing. Results: IVA was used to measure the FFR of the systemic ventricle in patients with structurally normal hearts and in patients with UVHs. Basal IVA of the normal hearts (mean (SD) 1.9 (0.3) m/s2) was significantly greater than that of UVHs in patients with a dominant right ventricle (RV) (1.0 (0.3) m/s2) or left ventricle (LV) (0.8 (0.7) m/s2; p < 0.05 for both). Neither the absolute nor percentage change from basal to peak values of IVA with pacing differed between the three groups. Peak force developed by the normal LV was significantly greater than that of the UVH, dominant LV group but not different from that of the UVH, dominant RV group. Conclusion: Contractility at basal heart rate is depressed in patients with UVH compared with the normal LV. Analysis of ventricular FFRs exposes further differences in myocardial contractility. There is no evidence that contractile function of the dominant RV is inferior to that of the dominant LV over a physiological range of heart rates.

Specific issues after extracardiac fontan operation: Ventricular function, growth potential, arrhythmia, and thromboembolism - Chowdhury, U.K.; Airan, B.; Kothari, S.S.; Talwar, S.; Saxena, A.; Singh, R.; Subramaniam, G.K.; Pradeep, K.K.; Patel, C.D.; Venugopal, P. (Annals of Thoracic Surgery, 2005)
Background. The purpose of this study was to define the prevalence of specific sequelae after extracardiac Fontan operation. Methods. Sixty-five consecutive patients undergoing extracardiac Fontan operation were studied for mortality, Fontan failure, systemic ventricular function, supraventricular arrhythmias, thromboembolism, and growth potential. Age was 3 to 31 years (mean ± standard deviation, 9.4 ± 1.8; median, 7 years). The conduits were constructed of polytetrafluoroethylene (n = 50), and "viable" in situ pericardium (n = 15). The patients underwent serial echocardiogram, dynamic radionuclide studies, and cardiac catheterization. Results. Operative mortality was 3%, and the incidence of conduit thrombosis was 4.6%. There was paradoxic filling of the right lung after femoral injection of the radiotracer in all cases of conduit obstruction. Perioperative and late postoperative supraventricular arrhythmias were observed in 9.2% and 4.7% of patients, respectively. Risk factors for supraventricular arrhythmias included systemic ventricular dysfunction (p = 0.000), heterotaxy syndrome (p = 0.008), systemic venous anomalies (p = 0.015), and previous bidirectional Glenn operation (p = 0.017). At a mean follow-up of 77 ± 2 months (range, 8 to 79 months), there were no late deaths (actuarial survival at 79 months, 96.9% ± 0.02%). Serial echocardiograms demonstrated evidence of growth of the viable tunnels. Postoperatively, there was transient depression of ejection fraction in all patients (p = 0.000). Conclusions. Supraventricular arrhythmias after extracardiac Fontan are more common in patients with heterotaxy syndrome, bilateral superior venae cavae, systemic ventricular dysfunction, and those undergoing completion Fontan operation. The viable tunnel may emerge as an optimal alternative by virtue of reduction of supraventricular arrhythmias, elimination of the need for anticoagulation, and addressing the issue of growth potential in selected patients. © 2005 by The Society of Thoracic Surgeons.

Late outcomes in patients with surgically treated congenital heart disease - Schultz, A.H.; Wernovsky, G. (Pediatric Cardiac Surgery Annual, 2005)
Optimizing late outcomes should be the end result of improvements in medical and surgical care for congenital heart disease (CHD). In addition to mortality, significant morbidities after surgery for CHD need to be considered. These include the need for reintervention, cardiovascular complications, exercise limitations, neurocognitive morbidities, effects on pregnancy, difficulty obtaining insurance, need for chronic medications, and impaired functional status and quality of life. Long-term outcome studies are difficult to perform, and their interpretation is complicated by intervening changes in management. Specific discussion of long-term follow-up of tetralogy of Fallot, D-transposition of the great arteries, and hypoplastic left heart syndrome illustrates the myriad management changes over the last three decades, the challenges in predicting outcomes for recent patients, and the need for ongoing initiation of long-term follow-up studies. © 2005 Elsevier Inc. All rights reserved.
Keywords: Congenital; Follow-up studies; Heart defects; Hypoplastic left heart syndrome; Tetralogy of Fallot; Transposition of great vessels

Extracorporeal membrane oxygenation for cardiac disease: No longer a mistaken diagnosis - Di Russo, G.B.; Martin, G.R. (Pediatric Cardiac Surgery Annual, 2005)
Extracorporeal membrane oxygenation (ECMO) has become a valuable adjunct in caring for infants and children with heart disease. Since the initial reports of ECMO support for cardiac failure in children, the number of centers providing cardiac support and the number of cases of cardiac ECMO have steadily increased. The International Registry for Extracorporeal Life Support Organization has reported survival statistics for cardiac cases in neonates, children, and adults ranging from 33% to 43%. These numbers are similar to the survival from recent reports by Morris (39%) and Chaturvedi (49%). Survival is influenced by ability to be weaned from bypass in the operating room and by residual structural disease and multi-organ system failure but not by cardiac arrest and single ventricle physiology. To improve results in the future, we need to focus on better predicting the need for support and avoiding multi-organ system failure before initiating ECMO. Rapid deployment of ECMO may further improve results for patients who deteriorate suddenly in the intensive care unit. © 2005 Elsevier Inc. All rights reserved.
Keywords: Congenital heart disease; Extracorporeal membrane oxygenation (ECMO); Survival

Persistent plastic bronchitis in a child after cardiac surgery - Peleg, U.; Schwartz, S.; Sirota, G.; Hochman, I.; Cohen, D.; Picard, E. (Israel Medical Association Journal, 2005)
Keywords: Bronchoscopy; Children; Fontan procedure; Plastic bronchitis

Food, toys, and love: Pediatric palliative care - Sourkes, B.; Frankel, L.; Brown, M.; Contro, N.; Benitz, W.; Case, C.; Good, J.; Jones, L.; Komejan, J.; Modderman-Marshall, J.; Reichard, W.; Sentivany-Collins, S.; et al. (Current Problems in Pediatric and Adolescent Health Care, 2005)

Utilization and outcomes of neonatal cardiac extracorporeal life support: 1996-2000 - Hintz, S.R.; Benitz, W.E.; Colby, C.E.; Sheehan, A.M.; Rycus, P.; Van Meurs, K.P. (Pediatric Critical Care Medicine, 2005)
Objectives: Extracorporeal life support for neonatal respiratory failure has decreased, but utilization and outcome of cardiac extracorporeal life support are not well characterized. Among neonates born 1996-2000, our objects were to evaluate changes in utilization and outcome of cardiac extracorporeal life support and characterize correlates of survival. Design: Retrospective analysis of Extracorporeal Life Support Organization Registry data. Setting: Intensive care units participating in the ELSO registry. Patients: Patients placed on extracorporeal life support for center-specified "cardiac support" at ≤30 days of age from 1996 to 2000. Patients with hypoplastic left heart syndrome were also analyzed separately. Interventions: None. Measurements and Main Results: Patient characteristics and correlates of survival to discharge or transfer were analyzed by chi-square, Student's t-test, and logistic regression analysis. Neonates placed on cardiac extracorporeal life support increased from 112 in 1996 to 200 in 2000 (total n = 740). Overall survival was 34.2%: 28% for hypoplastic left heart syndrome and 35.4% for nonhypoplastic left heart syndrome. For the overall group, no significant correlations were found between survival and year on extracorporeal life support, multiple runs, or diagnosis of hypoplastic left heart syndrome. Diagnoses of transposition of the great arteries (p = .03) or persistent pulmonary hypertension of the neonate (p = .004) and extracorporeal life support at <3 days (p = .003) were associated with higher survival. Survivors had fewer mean extracorporeal life support hours (125.5 ± 121.4 vs. 159.0 ± 127.6, p = .0006). Logistic regression confirmed significant bivariate findings. A total of 118 hypoplastic left heart syndrome patients were reported from 1996 to 2000. Extracorporeal life support at >15 days was associated with improved survival among hypoplastic left heart syndrome patients (p = .03), and survivors had fewer mean extracorporeal life support hours (89.3 ± 52.3 vs. 147.5 ± 129.7, p = .015). Logistic regression showed that only greater number of hours on extracorporeal life support was independently associated with nonsurvival. Conclusions: Neonatal cardiac extracorporeal life support use increased substantially from 1996 to 2000, with survival to discharge or transfer in more than one third of patients. Hypoplastic left heart syndrome was not associated with nonsurvival. Fewer hours on extracorporeal life support, diagnoses of persistent pulmonary hypertension of the neonate and transposition of the great arteries, and extracorporeal life support at <3 days were associated with survival. Copyright © 2005 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Cardiac; Extracorporeal life support; Extracorporeal membrane oxygenation; Hypoplastic left heart syndrome; Infant; Neonate; Outcome

The role of exercise stress testing in pediatric patients with heart disease - Connuck, D.M. (Progress in Pediatric Cardiology, 2005)
Exercise testing is a valuable tool in the management of pediatric patients with heart disease. It can be used to help determine the need for medical or surgical interventions and can be used to determine the efficacy of these interventions. Common settings in which exercise testing may be helpful include evaluation of exercise tolerance in repaired or unrepaired congenital heart disease, assessment of heart failure symptoms, diagnosis and management of dysrhythmias, determination of cardiac, as opposed to respiratory causes of chest pain and prescription of exercise rehabilitation programs. This manuscript will review the indications, techniques, and uses of exercise stress testing in the pediatric population with an emphasis on the development of the exercise physiology lab as a source of high-quality data that can be used to improve patient outcomes. © 2005 Elsevier Ireland Ltd. All rights reserved.
Keywords: Congenital heart disease; Exercise testing; Outcomes; Pediatrics

Long-term treatment of plastic bronchitis with aerosolized tissue plasminogen activator in a Fontan patient - Wakeham, M.K.; Van Bergen, A.H.; Torero, L.E.; Akhter, J. (Pediatric Critical Care Medicine, 2005)
Objective: To report the successful treatment of plastic bronchitis with aerosolized tissue plasminogen activator. Design: Case report. Patients: A 4-yr-old boy with congenital heart disease, who developed plastic bronchitis 33 months after a Fontan operation Interventions: Long-term treatment with aerosolized tissue plasminogen activator. Measurements and Main Results: We describe the case of a boy who developed recurrent episodes of life-threatening airway obstruction secondary to plastic bronchitis. Following the failure of multiple therapeutic interventions, his condition improved significantly with aerosolized tissue plasminogen activator. Several attempts to wean him off this treatment resulted in clinical deterioration. He has remained on long-term aerosolized tissue plasminogen activator. Conclusion: Treatment of plastic bronchitis with aerosolized tissue plasminogen activator may benefit patients in whom other therapies have failed. Copyright © 2005 by the Society of Critical Care Medicine and the World Federation of Pediatric Intensive and Critical Care Societies.
Keywords: Airway obstruction; Bronchial casts; Congenital heart disease; Fontan operation; Plastic bronchitis; Tissue plasminogen activator

Rescue cardiac transplantation for early failure of the Fontan-type circulation in children - Chaudhari, M.; Sturman, J.; O'Sullivan, J.; Smith, J.; Wrightson, N.; Parry, G.; Bolton, D.; Haynes, S.; Hamilton, L.; Hasan, A. (Journal of Thoracic and Cardiovascular Surgery, 2005)
Early failure of the Fontan-type circulation is a potentially fatal complication. We review our experience with cardiac transplantation in children presenting with end-stage heart failure in this scenario. We performed a retrospective review. Between 1985 and 2003, 6 children aged less than 16 years were referred for cardiac transplantation. The indication for cardiac transplantation was end-stage cardiac failure early after the completion of the Fontan-type operation. All 6 patients listed for transplantation underwent cardiac transplantation; the median interval to transplantation from the operation was 36 days (range, 6-180 days). Four patients had undergone the Fontan procedure, and 2 had one-and-a-half-ventricle repair. All 6 patients were ventilated and inotrope dependant, with varying degrees of multiorgan dysfunction. One patient was bridged to transplantation with extracorporeal membrane oxygenation. The median age at transplantation was 7.1 years (range, 3-12.5 years), and weight was 18.9 kg (range, 11-35 kg). One patient died on the operating table (graft failure and hemorrhage). In 5 survivors the median intensive care unit stay was 10 days (range, 8-61 days). On follow-up of 6 to 81 months, there have been no subsequent deaths, and the quality of life in survivors is good. Rescue cardiac transplantation in the setting of an early failure of the Fontan-type circulation and end-stage cardiac failure is an effective treatment option and can be performed with acceptable early mortality and encouraging short-term to medium-term results. Copyright © 2005 by The American Association for Thoracic Surgery.

Incidence and treatment of diaphragmatic paralysis after cardiac surgery in children - Joho-Arreola, A.L.; Bauersfeld, U.; Stauffer, U.G.; Baenziger, O.; Bernet, V. (European Journal of Cardio-thoracic Surgery, 2005)
Objective: Diaphragmatic paralysis (DP) caused by phrenic nerve injury is potentially life-threatening in infants. Phrenic nerve injury due to thoracic surgery is the most common cause of DP in children. We retrospectively analyzed incidence, surgical details, management and follow-up of our patients with DP after cardiac surgery to develop an algorithm for the management and follow-up. Methods: Retrospective analysis of 43 patients with DP after cardiac surgery performed between 1996 and 2000. Results: Median age at cardiac surgery was 1 month (range 3 days to 9 years). Incidence of DP was 5.4%. A trend towards higher incidences of DP were observed after arterial switch operation (10.8%, P=0.18), Fontan procedure (17.6%, P=0.056) and Blalock-Taussig Shunt (12.8%, P=0.10). Median time from cardiac surgery to surgical plication was 21 days (range 7-210 days). Transthoracic diaphragmatic plication was performed in 29/43 patients, no plication was done in 14/43 patients. Patients in whom diaphragmatic plication was required were younger (median age 2 months, range 21 days to 53 months versus 17.5 months, range 4 days to 110 months; P<0.001). Indications for plication were failure to wean from ventilator (n=22), respiratory distress (n=4), cavopulmonary anastomosis (n=2), and failure to thrive (n=1). All these symptoms resolved after diaphragmatic plication, however, 8/29 patients with plication and 2/14 without plication died. Cause of death was not related to diaphragmatic plication in any patient. Position of plicated diaphragm was normal in 18/21 surviving patients 1 month after plication. In 2/12 surviving patients without plication hemidiaphragm showed a normal position 1 year after surgery. The rate of pulmonary infections was not significantly different during 12-60 months follow-up. Conclusions: DP is an occasional complication of cardiac surgery. High incidences of DP were seen after arterial switch operation, Fontan procedure and Blalock-Taussig shunt (BT). Respiratory insufficiency requires diaphragmatic plication in most infants with DP whereas older children may tolerate DP. Transthoracic diaphragmatic plication is an effective treatment of DP and achieves relief of respiratory insufficiency in most patients. Spontaneous recovery from postsurgical DP is rare. © 2004 Elsevier B.V. All rights reserved.
Keywords: Diaphragmatic plication; Infant; Newborn; Phrenic nerve injury

What is the perceived quality of life of adults with congenital heart disease and does it differ by anomaly? - Simko, L.C.; McGinnis, K.A. (Journal of Cardiovascular Nursing, 2005)
Adults with congenital heart disease (CHD) represent a growing population of patients thanks to the medical and surgical advances which enable at least 85% of children to survive to adulthood. These advances may create quality-of-life (QoL) issues not previously considered. The purpose of this cross-sectional study of 124 adults with CHD was to describe their QoL as a basis for providing appropriate information, counseling, and anticipatory guidance. Thirteen patients had single ventricle physiology (SVP), 43 had cyanotic lesions with 2 ventricle repairs, and 68 had acyanotic CHD. On the basis of Sickness Impact Profile (SIP) scores, individuals with SVP had worse QoL than did those with cyanotic lesions (with 2 ventricle repairs) and acyanotic anomalies (SIP = 9.98 vs 4.61 and 3.76). SIP scores were statistically significantly different between those with SVP and those with acyanotic anomalies (P =.02). For all groups, the areas of life most affected were work and sleep and rest. Participants with SVP saw themselves as having the poorest QoL. © 2005 Lippincott Williams & Wilkins, Inc.
Keywords: Adults with congenital heart disease; Quality of life; Sickness Impact Profile (SIP)

Quality of life in children with pulmonary atresia and intact ventricular septum - Ekman-Joelsson, B.-M.; Berntsson, L.; Sunnegårdh, J. (Cardiology in the Young, 2004)
Objective: To measure quality of life in children with pulmonary atresia and intact ventricular septum, and make comparisons with a healthy group of children from the general Swedish population. An additional aim was to compare quality of life in two subgroups, children undergoing biventricular and univentricular repair, the latter by establishment of the Fontan circulation. Methods: Quality of life was measured using a mailed questionnaire, taking into consideration the three spheres of personal, interpersonal, and external living conditions. In all, 52 children received the questionnaire, and the answers were compared with those of a random sample of 1856 healthy Swedish children. Results: We received responses from 42 children and parents. The overall differences between groups were small, and no difference was found when comparing the children undergoing univentricular as opposed to biventricular surgical repair. In terms of personal quality of life, we found a higher level of psychosomatic complaints, and lower satisfaction with their own and parent-child activities, in those with the congenital anomaly than in their normal peers. In terms of the interpersonal sphere, more time was available for those with malformed hearts, but the experience of support from the relatives was significantly lower. Conclusions: Overall, quality of life was equal between children with pulmonary atresia and intact ventricular septum and the children in the reference group. The personal psychological conditions were less favourable for children with pulmonary atresia and intact ventricular septum. The perceived lack of support from relatives was also higher in these families. No difference was found when comparing the children undergoing univentricular and biventricular surgical repair. © Cambridge University Press.
Keywords: Congenital heart defect; Fontan circulation; Hypoplastic right heart

Elevated cardiac troponin I in a 9-week-old infant - Muñiz, A.E. (Pediatric Emergency Care, 2004)
Myocardial ischemia in children is generally not suspected when they present to an emergency department with congestive heart failure. However, the opposite holds true for an adult patient. Elevated cardiac troponin is a specific biochemical marker for myocardial damage for both adults and children, however, they have not been routinely used in children at risk for myocardial damage. A case is presented of an infant with a complex congenital heart defect with congestive heart failure who was found to have an elevated cardiac troponin. Infants at risk for myocardial damage should have an evaluation of cardiac markers, as infants with elevated levels are prone to dysrhythmias or worsening cardiac function and thus warrant closer observations and therapy.
Keywords: Troponin

Prenatal and postnatal imaging thoracopagus conjoined twins with a shared six-chamber heart - McAdams, R.M.; Milhoan, K.A.; Hall, B.H.; Richardson, R.G. (Pediatric Radiology, 2004)
Management of thoracopagus conjoined twins is predominantly determined by the associated complex cardiovascular abnormalities seen in the majority of these cases. Magnetic resonance imaging (MRI), including three-dimensional contrast-enhanced magnetic resonance angiography (MRA) provides a useful complement to conventional cardiac echocardiography or catheterization for detailed evaluation of the extra-cardiac anatomy. We report a pair of female thoracopagus conjoined twins with a shared six-chambered heart. The MRA findings are highlighted. © Springer-Verlag 2004.
Keywords: Conjoined twins; MR; Thoracopagus

Neuropsychological outcome of infant heart transplant recipients - Baum, M.; Catherin Freier, M.; Freeman, K.; Babikian, T.; Ashwal, S.; Chinnock, R.; Bailey, L. (Journal of Pediatrics, 2004)
To assess long-term neuropsychological outcomes of infant heart transplant recipients.Fifty-five children (mean age, 6.4 years) with a primary diagnosis of hypoplastic left heart syndrome or other cardiac disorders participated in the study. Six areas of risk were assessed (birth; preoperative, intraoperative, and postoperative status; long-term medical complications; and socioeconomic factors). Neuropsychological evaluations included the following: Wechsler Scales of Intelligence, Wechsler Individual Achievement Test, Berry Visual Motor Integration Scale, Comprehensive Evaluation of Language Function, and Achenbach Child Behavioral Checklist.Intellectual functioning scores revealed a mean full-scale IQ of 81 ± 19. Intraoperative and postoperative variables (bypass time, hospital course, and lowest posttransplant pH), long-term medical complications (serious infections and posttransplant surgical procedures), and socioeconomic factors were associated with cognitive functioning. Visual-motor functioning was also related to bypass and total support time.Long-term outcomes reveal low-average neuropsychological functioning and are related to intrasurgical-postsurgical, long-term medical, and socioeconomic factors. The neuropsychological and psychosocial functioning of infant heart transplant recipients will be important to address as they mature during adolescence and adulthood.

Fontan operation for hypoplastic left heart syndrome with absent aortic valve - Hibino, N.; Harada, Y.; Hiramatsu, T.; Yasukochi, S.; Satomi, G. (Journal of Thoracic and Cardiovascular Surgery, 2004)
Keywords: 21

Plastic bronchitis after Fontan operation: Treatment with stent fenestration of the Fontan circuit - Chaudhari, M.; Stumper, O. (Heart, 2004)

Long-term outcome and quality of life in adult patients after the Fontan operation - Van Den Bosch, A.E.; Roos-Hesselink, J.W.; Van Domburg, R.; Bogers, A.J.J.C.; Simoons, M.L.; Meijboom, F.J. (American Journal of Cardiology, 2004)
The first successful Fontan operation was performed in 1971, and this first cohort of Fontan patients is reaching adulthood with unclear outcome of this palliative procedure. We studied the mortality, morbidity, and quality of life in our adult Fontan patients. We examined all patients (n = 36) who underwent a Fontan procedure and were being seen in an adult outpatient clinic by using electrocardiography, exercise testing, and echocardiography. Quality of life was assessed by the Short Form 36 questionnaire. The mean follow-up period was 15 years (range 0 to 23). Of the initial 36 patients, 10 died (28%) at a mean of 10 years (range 0 to 21) after the Fontan operation and 1 patient underwent cardiac transplantation. Reoperations were performed in 21 patients (58%), and the most common reason was revision of the Fontan connection. Sustained supraventricular tachycardia was observed in 20 patients (56%) with an increased incidence of arrhythmias with longer follow-up. Thromboembolic events were detected in 9 patients (25%), 5 of whom had adequate anticoagulant levels at the time of event. The thromboembolic event was fatal for 3 patients. A total of 195 hospital admissions (mean 3.8 ± 2.7, range 1 to 13) was recorded. Quality-of-life assessment showed physical functioning, mental health, and general health perception to be significantly lower for Fontan patients than for the normal Dutch population. Thus, we found high mortality and very high morbidity in adult patients after the Fontan operation. In particular, reoperations, arrhythmias, and thromboembolic events compromised quality of life. © 2004 by Excerpta Medica, Inc.

Neurodevelopmental outcomes in hypoplastic left heart syndrome - Mahle, W.T.; Wernovsky, G. (Pediatric Cardiac Surgery Annual, 2004)
Infants with hypoplastic left heart syndrome (HLHS) are now surviving to school age and early adulthood because of surgical palliation with either staged reconstruction or transplantation. Although in some respects these patients are doing remarkably well, recent investigations have shown that they are at risk for cognitive, neuromotor, and psychosocial problems. This article examines the neurodevelopmental outcome for children and adolescents with HLHS. In addition, hemodynamic and genetic factors unique to this patient population that may impact longer-term outcome are explored. The continued evolution of the pre-, intra- and post-operative care of the patient with HLHS has significantly improved early survival. Concomitant changes in care, such as selective cerebral perfusion and neurologic monitoring, aimed at reducing neurologic insult may also favorably impact later neurodevelopmental status. © 2004 Elsevier Inc. All rights reserved.
Keywords: Hypoplastic left heart syndrome; Neurologic; Outcomes

Cardiac transplantation for hypoplastic left heart syndrome. - Boucek Jr., R.J.; Chrisant, M.R. (Cardiology in the young, 2004)
Future improvements can be expected in cardiac transplantation in children. We continue to advance our understanding of the immune system, and to develop more specific immunosuppressive agents. Ultimately, the future for recipients may be improved by strategies such as induction therapy or donor-derived chimeric destined transfusions, designed to enhance the tolerance of the host to a human leukocyte antigen incompatible graft. Improvements in tolerance of the host would allow for reduction or elimination of many, if not all, of the immunosuppressive agents, and for longevity extending well into the adulthood. Survival, particularly for infants, has improved dramatically in the last decade. The most recent results from the registry of the International Society of Heart and Lung Transplantation/United Network for Organ Sharing show that recipients less than one year old at transplantation, who survive the first year, have greater than a 95% survival to four years (Fig. 1). As late outcomes continue to improve, transplantation will provide a better quality and duration of life for infants with hypoplastic left heart syndrome. It is possible, nonetheless, that some infants will require retransplantation, since the half life of a transplanted heart in children has been about 12 years. The alternative is conventional surgery with multiple palliative operations, and the need for later transplantation as end-stage cardiac function is reached. Efforts to increase potential donors and donor utilization can be supported by innovative schemes, such as ABO incompatible transplants. Additional efforts are made more urgent when the current data indicate excellent outcomes after transplantation, but a high mortality while waiting for transplantation.

Global impairment of cardiac autonomic nervous activity late after the Fontan operation - Davos, C.H.; Francis, D.P.; Leenarts, M.F.E.; Yap, S.-C.; Li, W.; Davlouros, P.A.; Wensel, R.; Coats, A.J.S.; Piepoli, M.; Sreeram, N.; Gatzoulis, M.A. (Circulation, 2003)
Background - Atrial tachyarrhythmia is a common cause of morbidity and mortality in patients with univentricular physiology undergoing the Fontan operation. We examined cardiac autonomic nervous activity, a predictor of arrhythmia and sudden death in other cardiovascular disease, in patients late after the Fontan operation, employing heart rate variability (HRV) and baroreflex sensitivity. Methods and Results - We measured HRV and baroreflex sensitivity in 22 consecutive patients (8 male, age 26±9 years) who had undergone the Fontan operation 13±6 years previously, and 22 age- and sex-matched healthy controls. Fontan patients had significantly lower HRV (P<0.0001). Baroreflex sensitivity was measured by the α-index method (square root of ratio of RR interval spectral power to systolic blood pressure (SBP) spectral power, in the LF and the HF band) and was also significantly depressed in the Fontan group (P<0.0001 for both). Both low frequency (LF) and high frequency (HF) components of HRV were reduced in the Fontan patients (P<0.0001), but there was interindividual variation so that the LF/(LF+HF) ratio may be high, normal, or low, and decreased with increasing right atrial dimensions (r=-0.62, P=0.006). Patients with a history of sustained atrial arrhythmia had a stronger baroreflex than those without (P=0.005). Conclusions - Autonomic nervous control of the heart is markedly deranged in patients late after the Fontan operation, with reduced HRV and baroreflex sensitivity. A relative suppression of the sympathetic-compared with the parasympathetic-system was observed in patients with marked right atrial dilation within the Fontan group. Furthermore, stronger baroreflexes were seen in Fontan patients in association with a higher incidence of sustained atrial tachyarrhythmia, implying that sinus node dysfunction is unlikely to be the dominant mechanism. Additional studies are clearly required to examine the prognostic importance of impaired BRS and HRV in these patients.
Keywords: Arrhythmias; Baroreceptors; Fontan procedure; Heart rate/heart rate variability; Nervous system autonomic

Electrocardiographic ST segment depression and clinical function in children with Fontan circulation - Rydberg, A.; Rask, P.; Teien, D.E.; Hörnsten, R. (Pediatric Cardiology, 2003)
Previous studies noted that Fontan patients have electrocardiographic ST depressions during exercise tests and on 24-hour ambulatory electrocardiographic (ECG) monitoring. This study investigated whether the ST depressions were correlated to clinical function (NYHA Functional Classification). Forty-five children in two groups were examined - 15 patients with Fontan circulation and 30 with a structurally normal heart, matched for sex, height, and weight. Clinical and echocardiographic examinations were performed. The clinical state was defined as NYHA functional classes I-IV. All 45 children underwent 24-hour ECG and an analysis of ST changes was performed, with ST segment depression >0.20 mV at ST 60 regarded as significant. Twelve of 15 patients had significant 24-hour ECG ST depressions; in 9 of 12 patients these occurred on more than one occasion. Comparing 24-hour ECG recordings from patients in NYHA I with patients in NYHA II or III showed a significant difference in depth (p = 0.0023), duration (p = 0.0016), and number of ST depressions (p = 0.0001). None of the matched healthy children showed ST depressions. Repeated ST analysis on 24-hour ECG shows that the ST depressions seem to be correlated to functional status and this may be a useful tool in clinical praxis.
Keywords: Electrocardiographic ST depression; Fontan circulation; NYHA classification

Basal pulmonary vascular resistance and nitric oxide responsiveness late after fontan-type operation - Khambadkone, S.; Li, J.; De Leval, M.R.; Cullen, S.; Deanfield, J.E.; Redington, A.N. (Circulation, 2003)
Background - The pulsatile nature of pulmonary blood flow is important for shear stress-mediated release of endothelium-derived nitric oxide (NO) and lowering pulmonary vascular resistance (PVR) by passive recruitment of capillaries. Normal pulsatile flow is lost or markedly attenuated after Fontan-type operations, but to date, there are no data on basal pulmonary vascular resistance and its responsiveness to exogenous NO at late follow-up in these patients. Methods and Results - We measured indexed PVR (PVRI) using Fick principle to calculate pulmonary blood flow, with respiratory mass spectrometry to measure oxygen consumption, in 15 patients (median age, 12 years; range, 7 to 17 years; 12 male, 3 female) at a median of 9 years after a Fontan-type operation (6 atriopulmonary connections, 7 lateral tunnels, 2 extracardiac conduits). The basal PVRI was 2.11±0.79 Wood unit (WU) times m2 (mean±SD) and showed a significant reduction to 1.61±0.48 (P=0.016) after 20 ppm of NO for 10 minutes. The patients with nonpulsatile group in the pulmonary circulation dropped the PVRI from 2.18±0.34 to 1.82±0.55 (P<0.05) after NO inhalation. Conclusions - PVR falls with exogenous NO late after Fontan-type operation. These data suggest pulmonary endothelial dysfunction, related in some part to lack of pulsatility in the pulmonary circulation because of altered flow characteristics. Therapeutic strategies to enhance pulmonary endothelial NO release may have a role in these patients.
Keywords: Endothelial dysfunction; Fontan procedure; Pulmonary vascular resistance

Myocardial perfusion and coronary flow reserve assessed by positron emission tomography in patients after Fontan-like operations - Hauser, M.; Bengel, F.M.; Kühn, A.; Sauer, U.; Nekolla, S.G.; Eicken, A.; Schwaiger, M.; Hess, J. (Pediatric Cardiology, 2003)
Ventricular dysfunction in patients after Fontan-like operations (FLOs) is a serious complication that might contribute to poor long-term results. Ischemic heart disease will have debilitating consequences on a Fontan heart. Ten patients (15.8 ± 5.01 years) after FLO had transesophageal echocardiography and cardiac catheterization 9.3 ± 4.2 years after surgery. Myocardial perfusion was assessed by NH3-positron emission tomography (rest/adenosine) and compared with that of 10 healthy adults (26.1 ± 6.3 years). Ventricular function was normal in 4 and reduced in 6 patients; end systolic and end diastolic meridional wall stress was significantly elevated in the FLO group. Coronary angiography revealed no stenosis of the coronaries. Compared to normals, myocardial blood flow (MBF) at rest was higher in the FLO group (0.99 ± 0.25 vs 0.77 ± 0.17 ml/g/min, p < 0.05), whereas MBF after vasodilatation (2.12 ± 0.78 vs 3.10 ± 0.85 ml/g/min, p < 0.05) and coronary flow reserve (CFR) was reduced (2.5 ± 0.88 vs 4.1 ± 1.01, p < 0.05), especially in those with impaired ventricular function. Coronary vascular resistance after vasodilatation was elevated in the FLO group (38.2 ± 17.4 vs 24.5 ± 8.3 mmHg/ml/g/min, p < 0.05). Altered MBF, increased meridional wall stress, and impaired CFR are common findings in FLO. Attenuated CFR and reduced ventricular function are significantly correlated and may be risk factors for the long-term outcome.
Keywords: Coronary disease; Fontan procedure; Microcirculation; Positron emission tomography imaging

The modified Fontan procedure: Early and late results in 132 adult patients - Burkhart, H.M.; Dearani, J.A.; Mair, D.D.; Warnes, C.A.; Rowland, C.C.; Schaff, H.V.; Puga, F.J.; Danielson, G.K.; Spray, T.; Drinkwater, D. (Journal of Thoracic and Cardiovascular Surgery, 2003)
Objective: The modified Fontan procedure, usually performed in children, is used for the treatment of anomalies with a single functional ventricle. We reviewed our experience with the modified Fontan procedure performed in the adult patient. Methods: Between October 1973 and May 2001, the modified Fontan procedure was performed on 132 adult patients (74 men, 58 women). Median age was 23 years (range, 18 to 53 years). Diagnoses included tricuspid atresia in 34 patients (26%), double-inlet left ventricle in 48 (36%), and complex lesions in 50 (38%). The majority of patients (89%) had at least one prior palliative procedure; the most common procedures were Blalock-Taussig shunt in 85 patients and Glenn anastomosis in 31. Results: Operations included an atriopulmonary connection in 74 patients, lateral tunnel in 27, intra-atrial conduit in 14, right atrium-to-right ventricle in 9, extracardiac conduit in 3, and other in 5. Overall early mortality was 8.3%. Mortality was 6.5% for operations performed after 1980. This is comparable to the mortality of the modified Fontan procedure performed in children during the same time interval at our institution. All 7 of the early deaths since 1980 occurred in the complex lesion group. Morbidity included prolonged pleural effusion in 36 patients, atrial arrhythmias in 25, reoperation for bleeding in 13, permanent pacemaker in 8, and stroke in 2. Mean follow-up was 9.1 years with a maximum of 21.2 years. Actuarial survival for early survivors was 89% (84,95), 75% (67,84), and 68% (58,79) at 5, 10, and 15 years, respectively. Freedom from late reoperation was 89% (83,95), 85% (78,93), and 80% (70,91) at 5, 10 and 15 years, respectively. The majority (90%) of present survivors were New York Heart Association class I or II at follow-up. Conclusions: In properly selected adult patients with functional single ventricle, the modified Fontan procedure can be performed with early mortality similar to younger patients. Early mortality is more likely with complex lesions. The majority of late survivors have a good quality of life.

Nitric oxide synthase expression by pulmonary arteries: A predictive marker of Fontan procedure outcome? - Lévy, M.; Danel, C.; Laval, A.-M.; Leca, F.; Vouhé, P.R.; Israël-Biet, D. (Journal of Thoracic and Cardiovascular Surgery, 2003)
Objectives: We retrospectively analyzed lung biopsy specimens from patients who underwent the Fontan procedure to identify predictive markers of outcome. Methods: We studied the intra-acinar pulmonary arteries present in lung biopsy specimens from 17 patients undergoing the Fontan procedure. We evaluated both their morphology and their expression of endothelial nitric oxide synthase and endothelin 1. We compared these data with those of 6 patients who died of no pulmonary cause (control group). Results: Eight patients had a good surgical outcome (group 1). Their distal arteries were thin and weakly expressed endothelin 1 and endothelial nitric oxide synthase. The procedure failed in 9 patients (group 2). Their distal arteries displayed muscle extension with an increased wall thickness (P < .01 vs group 1). Their endothelin 1 expression remained low (not significant vs group 1). By contrast, endothelial nitric oxide synthase was markedly overexpressed (P < .001 vs group 1). Conclusion: Distal pulmonary arteries of patients in whom the Fontan procedure failed exhibited a markedly increased wall thickness and a clear endothelial nitric oxide synthase overexpression. In addition to giving clues to the pathogenesis of the procedure's failure, our study might help to define reliable predictive markers of its outcome.

The use of pulse oximetryto detect congenital heart disease - Reich, J.D.; Miller, S.; Brogdon, B.; Casatelli, J.; Gompf, T.C.; Huhta, J.C.; Sullivan, K. (Journal of Pediatrics, 2003)
Objective: To evaluate whether pulse oximetry can be used as a screening test to detect congenital heart disease (CHD) in otherwise well newborns before nursery discharge. Methods: Births at Lakeland Regional Medical Center (LRMC) who met inclusion criteria, had a single pulse oximeter reading before discharge. A normal reading was considered to be >94%. Abnormal readings were repeated on a different extremity and if still abnormal, an echocardiography was performed. The number of children with CHD and the number of echocardiograms were compared with the previous year at LRMC. Results: There were 2114 infants enrolled, 88 echocardiograms (3.8%) were performed, and 43 were abnormal (yield = 48.9%), of which 12 required management (13.6%). The control group consisted of 2851 births, producing 108 echocardiograms (3.8%), 42 of which were abnormal (38.9%), and 13 required management (12.0%). No comparisons were significant. During both years, 3 children with cyanotic CHD were born. Routine pulse oximetry failed to detect a child with total anomalous pulmonary venous return. Not a single, normal echocardiogram was generated by the study. Conclusion: Routine pulse oximetry was nearly 100% specific for detecting cyanotic CHD; as a result there was no increase in the number of echocardiograms. Routine pulse oximetry did detect a child who might not have been detected otherwise but failed to detect one that should have been detected.

Late follow-up of 1095 patients undergoing operation for complex congenital heart disease utilizing pulmonary ventricle to pulmonary artery conduits - Dearani, J.A.; Danielson, G.K.; Puga, F.J.; Schaff, H.V.; Warnes, C.W.; Driscoll, D.J.; Schleck, C.D.; Ilstrup, D.M.; Clarke, D.R.; Brown, J.W. (Annals of Thoracic Surgery, 2003)
Background. Pulmonary ventricle (PV) to pulmonary artery (PA) conduits have made possible the correction of many complex congenital cardiac anomalies. Methods. Between April 1964 and January 2001, 1270 patients underwent operation with conduit placement from the PV to PA. The present study evaluates late outcome of 1095 patients (612 males, 483 females) having an operation before July 1992. Mean age was 9.6 ± 8.2 years old. Diagnoses included pulmonary atresia/tetralogy of Fallot (459), transposition of the great arteries (TGA) (232), truncus arteriosus (193), double outlet right ventricle (DORV) (121), corrected TGA (49), septated univentricular heart (36), and other (5). A porcine-valved Dacron conduit was used in 730, homograft in 239, and non-valved conduit in 126. Results. Early mortality decreased from 23.5% prior to 1980 to 3.7% for the most recent decade. Mean follow-up was 10.9 years (maximum, 29 years). Actuarial survival for early survivors at 10 and 20 years was 77.0% ± 1.5% and 59.5% ± 2.6%. On univariate analysis, clinical and hemodynamic factors associated with late mortality were male gender, older age at operation, higher post-repair PV/systemic ventricle (SV) pressure ratio, higher distal PA pressure, and longer bypass time (p ≤ 0.01 for all). On multivariate analysis, independent risk factors for late mortality were male gender, older age at operation, diagnosis of TGA, corrected TGA, truncus, or univentricular heart, and PV/SV pressure ratio ≥ 0.72 (p ≤ 0.03 for all). Freedom from reoperation for conduit failure at 10 and 20 years was 55.5% ± 2.0% and 31.9% ≤ 2.7%. On multivariate analysis, independent risk factors for conduit failure were homograft conduit, diagnosis of TGA, younger age at operation, and smaller conduit size (p ≤ 0.007 for all). Reoperation for one conduit replacement was performed in 306 patients, two conduit replacements in 55 patients, three in 6 patients, and four in 3 patients. Overall early mortality for conduit replacement in this series was 4.9%; it was 1.7% for patients operated on from 1989 through 1992. At follow-up, 84% of survivors were in NYHA class I or II. Conclusions. Operations that include conduit placement and replacement can be performed with low early mortality. Younger age at operation was associated with improved late survival. The diagnosis of TGA was associated with increased risk for conduit failure, and the durability of the homograft, in this series, was inferior to the porcine-valved Dacron conduit. Quality of life was excellent for most patients despite the need for reoperation. © 2003 by The Society of Thoracic Surgeons.

Plastic bronchitis: An unusual bronchoscopic challenge associated with congenital heart disease repair - Ishman, S.; Book, D.T.; Conley, S.F.; Kerschner, J.E. (International Journal of Pediatric Otorhinolaryngology, 2003)
Plastic bronchitis is a rare disorder characterized by the formation of branching mucoid bronchial casts. Several pathophysiologic conditions are associated with development of these intrabronchial casts, including congenital heart defects. The management of plastic bronchitis presents an unusual and interesting bronchoscopic challenge. We describe a patient who underwent a Fontan procedure for correction of a congenital heart defect and subsequently developed respiratory distress secondary to plastic bronchitis on two occasions. In both cases, endoscopic intervention was required to remove these casts. A review of the literature, including the proposed etiologies, diagnosis, and current medical and surgical management, is also undertaken. © 2003 Elsevier Science Ireland Ltd. All rights reserved.
Keywords: Bronchial casts; Fontan procedure; Plastic bronchitis

Influence of connection geometry and SVC-IVC flow rate ratio on flow structures within the total cavopulmonary connection: A numerical study - Khunatorn, Y.; Mahalingam, S.; DeGroff, C.G.; Shandas, R. (Journal of Biomechanical Engineering, 2002)
The total cavopulmonary connection (TCPC) is a palliative cardiothoracic surgical procedure used in patients with one functioning ventricle that excludes the heart from the systemic venous to pulmonary artery pathway. Blood in the superior and inferior vena cavae (SVC, IVC) is diverted directly to the pulmonary arteries. Since only one ventricle is left in the circulation, minimizing pressure drop by optimizing connection geometry becomes crucial. Although there have been numerical and in-vitro studies documenting the effect of connection geometry on overall pressure drop, there is little published data examining the effect of SVC-IVC flow rate ratio on detailed fluid mechanical structures within the various connection geometries. We present here results from a numerical study of the TCPC connection, configured with various connections and SVC:IVC flow ratios. The role of major flow parameters: shear stress, secondary flow, recirculation regions, flow stagnation regions, and flow separation, was examined. Results show a complex interplay among connection geometry, flow rate ratio and the types and effects of the various flow parameters described above. Significant changes in flow structures affected local distribution of pressure, which in turn changed overall pressure drop. Likewise, changes in local flow structure also produced changes in maximum shear stress values; this may have consequences for platelet activation and thrombus formation in the clinical situation. This study sheds light on the local flow structures created by the various connections and flow configurations and as such, provides an additional step toward understanding the detailed fluid mechanical behavior of the more complex physiological configurations seen clinically.

Delivery of a nonpotassium modified maintenance solution to enhance myocardial protection in stressed neonatal hearts: A new approach - Kronon, M.T.; Allen, B.S.; Halldorsson, A.; Rahman, S.; Barth, M.J.; Ilbawi, M. (Journal of Thoracic and Cardiovascular Surgery, 2002)
Objectives: This study was undertaken to compare conventional cardioplegic strategies with a new approach that uses a modified nonpotassium maintenance solution between cardioplegia doses in stressed neonatal hearts. Methods: Thirty-five neonatal piglets underwent 60 minutes of ventilator hypoxia (inspired oxygen fraction 8%-10%) followed by 20 minutes of ischemia on cardiopulmonary bypass. In 10 animals bypass was discontinued without further ischemia (stress control group). The other 25 received a warm blood cardioplegic induction and were separated into 5 groups. In 5 animals cardiopulmonary bypass was discontinued without further ischemia (cardioplegia control group); the remaining 20 underwent an additional 70 minutes of cold blood cardioplegic arrest. Five received only intermittent cardioplegia every 20 minutes, whereas 15 also received cold blood maintenance infusions between cardioplegic doses (integrated strategy). In 5 of these animals the blood was unmodified, whereas in 10 a modified nonpotassium "cardioplegia-like" solution was delivered either antegradely (n = 5) or retrogradely (n = 5). Myocardial function was assessed by pressure-volume loops (expressed as percentage of control); vascular function was assessed by coronary vascular resistance. Results: All piglets that underwent hypoxic ischemic stress alone (controls) died. Warm induction alone (cardioplegic controls) partially repaired the stress injury. Intermittent cardioplegia preserved the depressed systolic function (end-systolic elastance 40% vs 39%), increased diastolic stiffness (255% vs 239%), reduced adenosine triphosphate (10.6 vs 12.2 μg/g tissue), and elevated coronary vascular resistance at levels identical to warm induction alone; infusing unmodified blood between cardioplegia doses (standard integrated) improved results slightly. In contrast, infusion of a cold modified solution (antegrade or retrograde) between cardioplegia doses (modified integrated) completely restored systolic function (end-systolic elastance 100% and 97%, P < .001 vs intermittent and standard integrated), only minimally increased diastolic stiffness (159% and 156%, P < .001 vs intermittent and standard integrated), restored adenosine triphosphate (18.8 and 16.6 μg/g, P < .001 vs intermittent and standard integrated), and normalized coronary vascular resistance (P < .001 vs intermittent and standard integrated). This strategy was used in 72 consecutive hypoxic patients (21 arterial switch operations, retrograde; 51 Fontan procedures, antegrade) with a 2.8% mortality. Conclusions: Infusion of a cold modified solution between cardioplegic doses (modified integrated protection) significantly improved myocardial protection in the stressed neonatal heart, was effective delivered either antegradely or retrogradely, and was used successfully for hypoxic (stressed) pediatric patients.

Postoperative management in patients with complex congenital heart disease - Tweddell, J.S.; Hoffman, G.M. (Pediatric Cardiac Surgery Annual, 2002)
Life-threatening problems occur in the neonate and infant after cardiac surgery because of the interplay of diminished cardiac output (CO), increased metabolic demand, inflammatory responses to cardiopulmonary bypass, and maladaptive responses to stress. Therefore, the postoperative management of patients with complex congenital heart defects is directed at optimization of oxygen delivery to maintain end-organ function and promote wound healing. Traditionally, assessment of circulation in the postoperative congenital heart patient has depended on indirect assessment of CO using parameters such as blood pressure, pulses, capillary refill, and urine output. Because of the limitations of indirect and observer-dependent assessment of CO, we rely on objective measures of tissue oxygen levels for the complex postoperative patient. We have found that continuous monitoring of the mixed venous saturation (SvO2) allows for identification of acute changes in systemic oxygen delivery and frequently precedes other indicators of decreased CO. The postoperative patient can be expected to have a period of decreasing CO, and the need for intervention should be anticipated because critical low output syndrome will develop in a subset of patients. Strategies for postoperative care are developed based on the diagnosis and procedure, but optimizing SvO2 is a consistent goal. A uniform approach to airway maintenance, vascular access, and drug infusions, all universal concerns during the perioperative period, minimizes the potential for these predictable and necessary interventions to result in morbidity or mortality. Management of the postoperative single ventricle patient targets stabilization of the systemic vascular resistance through the use of vasodilators to improve systemic perfusion and simplify ventilator management. Management of any individual patient should be driven by objective analysis of available data and must include efforts to re-evaluate the treatment plan as well as to identify unanticipated problems. Copyright © 2002 by W.B. Saunders Company.
Keywords: Cardiac output; Congenital; Heart defects; Oxygen delivery; Postoperative management; Systematic vascular resistance

Heart transplantation in children and infants: Short-term outcome and long-term follow-up - Bauer, J.; Thul, J.; Krämer, U.; Hagel, K.J.; Akintürk, H.; Valeske, K.; Schindler, E.; Bohle, R.M.; Schranz, D. (Pediatric Transplantation, 2001)
Since 1988, 82 heart transplants have been performed in 80 infants and children. Diagnoses pretransplant were: hypoplastic left heart syndrome (HLHS) (n = 43); cardiomyopathy (n = 19); endocardial fibroelastosis (n = 6); and other complex congenital heart diseases (n = 12). Age at transplantation was < 1 yr in 61 patients. Overall survival rate was 79% at 1 yr and 73% at 5 and 10 yr. To date, 20 patients have died after transplantation. Causes of death were: rejection (eight patients); right ventricular failure (four patients); transplant coronary artery disease (TCAD) (two patients); and other causes (six patients). In the majority of patients somatic growth is not impaired, and renal function is reduced (but stable) in all patients. Two patients developed post-transplant lymphoproliferative disease, which was treated successfully. Major long-term morbidity is neurologic deficit - severe in three patients and minor in six. TCAD was present or suspected in six surviving patients. We conclude that heart transplantation in infants and children can be performed with good early and late results. Quality of life is excellent in most patients. TCAD, however, will become an increasing problem in the long term.
Keywords: Children; Follow-up; Heart transplantation; Infants; Morbidity

High frequency of arrhythmias after Fontan operation indicates earlier anticoagulant therapy - Sugimoto, S.; Takagi, N.; Hachiro, Y.; Abe, T. (International Journal of Cardiology, 2001)
Background: As patients began to survive for longer periods following modified Fontan operations (conventional atrio-pulmonary connection), the late morbidity after this procedure became increasingly apparent. The purpose of the present study was to evaluate late sequelae of modified Fontan operations in long-term survivors (n=14) at our institute. Methods and results: The cohort consisted of patients who underwent a modified Fontan operation between 1981 and 1990. Thus, all patients were examined at least 10 years postoperatively in this study. Early mortality, within 30 days of the operation, was 17.6% (three of 17 patients died from low output syndrome). Excluding these early deaths, the cumulative survival rate at 5 and 10 years was 100 and 79%, respectively. Arrhythmias including atrial fibrillation or flutter were the main late causes of morbidity. The arrhythmia-free rate at 5 and 10 years was 77 and 50%, respectively. Although the quality of life was considered good because all patients (n=11) who survived for 10 years or more were in class I or II according to the New York Heart Association classification, most of them in fact suffered from potentially life-threatening arrhythmias. Conclusions. Meticulous attention to and utilization of established treatment strategies for arrhythmias including antiarrhythmics, anticoagulants, catheter ablation or re-operation converting the circulation to the total cavopulmonary connection must be considered in long-term survivors following the modified Fontan operation. The fact that no one knows when the thrombogenic arrhythmias occur suggests anticoagulants should be initiated in the early postoperative period. © 2001 Elsevier Science Ireland Ltd.
Keywords: Anticoagulant; Arrhythmias; Atrio-pulmonary connection; Intracardiac thrombus; Late sequelae; Modified Fontan operation

The Fontan procedure for tricuspid atresia: Early and late results of a 25-year experience with 216 patients - Mair, D.D.; Puga, F.J.; Danielson, G.K. (Journal of the American College of Cardiology, 2001)
OBJECTIVES: We assessed the operative and late mortality and the present clinical status of 216 patients with tricuspid atresia who had a nonfenestrated Fontan procedure performed at the Mayo Clinic in the 25-year period 1973 to 1998. BACKGROUND: The Fontan operation eliminates the systemic hypoxemia and ventricular volume overload characteristic of prior forms of palliation. However, it originally did so at the cost of systemic venous and right atrial hypertension, and the long-term effects of this "price" were unknown when the procedure was initially proposed. METHODS: We reviewed the clinical records of the 216 patients retrospectively. These were arbitrarily grouped into early (1973 through 1980), middle (1981 through 1987) and late (1988 through 1997) surgical eras. Patient outcome was also analyzed according to age at surgery. Operative and late mortality rates were determined and present clinical status was ascertained in 167 of 171 surviving patients. RESULTS: Overall survival was 79%. Operative mortality steadily declined and was 2% (one of 58 patients) during the most recent decade. Late survival also continues to improve. Age at operation had no effect on operative mortality, and late mortality was significantly increased only in patients who were operated on at age 18 years or older. Eighty-nine percent of surviving patients are currently in New York Heart Association class I or II. CONCLUSIONS: The initial 25-year experience with the nonfenestrated Fontan procedure for tricuspid atresia has been gratifying, with most survivors now leading lives of good quality into adulthood. These results justify continued application of this procedure for children born with tricuspid atresia. © 2001 by the American College of Cardiology.

Quality of life and perceived health status in surviving adults with univentricular heart - Saliba, Z.; Butera, G.; Bonnet, D.; Bonhoeffer, P.; Villain, E.; Kachaner, J.; Sidi, D.; Iserin, L. (Heart, 2001)
Objective - To evaluate the quality of life in patients with univentricular heart and to determine the impact of sociodemographic and clinical characteristics. Design and setting - Retrospective, cross sectional study conducted in a regional paediatric cardiology centre. Patients - The health records of 89 survivors with univentricular heart (median age 21 years; range 17-49 years) were reviewed. Sixty seven answered the Duke questionnaire. Sociodemographic and clinical variables were similar in the responders and non-responders. The impact of sociodemographic and clinical variables on individual Duke's measures was assessed. Results - The Duke scores of adults with univentricular heart were similar to the normal population. Cyanosis predicted a worse score for physical (p = 0.05) and perceived health measures (p = 0.02). A higher educational level predicted a better score for physical (p = 0.004), mental (p = 0.01), and general health measures (p = 0.02). Orthopaedic problems worsened the social score (p = 0.05). Psychosocial problems worsened the pain score (p = 0.04). In comparison with the other anatomical types, mitral atresia worsened the perceived health score (p = 0.02). Patients younger than 23 years scored better for almost all health and dysfunction measures. Conclusions - Despite repeated interventions and other disease related everyday stresses, a selected group of adults with univentricular heart had a satisfying quality of life.
Keywords: Congenital heart defect; Psychosocial problems; Quality of life; Univentricular heart

Atrial and ventricular electromechanical function in 1-ventricle hearts: Influence of atrial flutter and fontan procedure - Li, W.; Sarubbi, B.; Sutton, R.; Somerville, J.; Gibson, D.; Henein, M.Y. (Journal of the American Society of Echocardiography, 2001)
Objective: Echocardiography was used to study electromechanical atrial and ventricular function in adult patients with a 1-ventricle heart who were in sinus rhythm to better understand the recurrence of atrial flutter in these conditions. Patients who had recent atrial flutter, with and without the Fontan procedure, were compared with those who had no arrhythmia. Methods: This was a prospective study that used M-mode and 2-dimensional Doppler echocardiography and electrocardiography. Conventional measurements were used to evaluate ventricular long-axis function. Basic data were drawn from case notes. The setting was a designated quaternary service for grown-up congenital heart patients (GUCH) in a tertiary referral center for cardiology and cardiac surgery. From January 1997 to February 1998, 26 consecutive adult patients (aged >16 years) with a heart with one functioning ventricle and a history of atrial flutter were studied: group 1, with non-Fontan palliative surgery or no surgery (10 patients), and group 2, with Fontan-type repair (16 patients). Also studied were 20 patients with a 1-ventricle heart but no history of atrial flutter. These 20 patients were divided into 2 groups: control 1, which comprised 14 patients with previous shunts or no surgery, and control 2, which consisted of 6 patients with Fontan repair. Results: P-wave duration on the electrocardiogram was similar in the 4 patient groups, but the amplitude was reduced in group 2 and control 2 (patients with Fontan surgery) (P < .016). Bifid P wave was seen in 5 (50%) of 10 patients in group 1 and in 6 (43%) of 14 patients in control 1, but it was not seen in patients with Fontan (P < .01). Ventricular systolic and diastolic dimensions and fractional shortening were not different between patients and controls. Right atrial transverse dimensions were greater in group 2 patients compared with those in controls. Significant atrioventricular valve regurgitation was seen in 9 of 10 group 1 patients but in none of the others. Right-sided total long-axis excursion and atrial A-wave amplitude were depressed in group 2 patients compared with the values in the others. The onset of right atrial shortening was delayed by 50 ms in group 2 compared with control 2, whereas the left atrial shortening was delayed by 30 ms in group 1 compared with control 1. This particular disturbance remained 6 months after cardioversion. Condition: In 1-ventricle hearts, significant atrioventricular valve regurgitation is commonly associated with atrial flutter in patients who did not undergo the Fontan procedure, and with electromechanical disturbances in those who did. Recognition of disturbances in ventricular long-axis function may thus assist in the identification of patients with a 1-ventricle heart who are prone to atrial flutter. Copyright © 2001 by the American Society of Echocardiography.

Extracardiac conduit Fontan procedure: Early and intermediate results - Haas, G.S.; Hess, H.; Black, M.; Onnasch, J.; Mohr, F.W.; Van Son, J.A.M. (European Journal of Cardio-thoracic Surgery, 2000)
Objective: The extracardiac Fontan procedure, as compared with classic atriopulmonary connections, may have the potential for optimizing ventricular and pulmonary vascular function by maximizing the laminar flow principle, by the avoidance of intra-atrial suture lines and cardiac manipulation, and by minimizing cardiopulmonary bypass time. In this study the clinical results of this procedure are assessed. Methods: From January 1990 until January 1997, 45 patients (33 males and 12 females) with a median age of 4.0 years (range 2.7-38 years) underwent an extracardiac Fontan procedure for univentricular physiology. The underlying diagnoses included tricuspid atresia (n=19), double-inlet left ventricle (n=11), and complex anomalies (n=15). Forty patients (89%) were in sinus rhythm. The median ventricular ejection fraction was 60%. In 37 patients (82%) the procedure was staged. Results: Median cardiopulmonary bypass time was 72 min, with a decrease to a median time of 24 min in the last ten patients. Aortic cross-clamping was avoided in 33 patients (73%). The intraoperative Fontan pressure and transpulmonary gradient were low: 13.6±3.2 and 8.5±3.9 mmHg, respectively. Transient supraventricular tachyarrhythmias were observed in six patients (13%). There was no early or late mortality. At a median follow-up of 64 months (range 26-105 months), 39 patients (87%) were in NYHA class I, four (9%) were in NYHA class II, and two (4%) were in class III. Forty patients (89%) remained in sinus rhythm. The median ventricular ejection fraction was 59%. The median arterial oxygen saturation raised from 82% preoperatively to 97%. Functional class (P=0.02), maintenance of sinus rhythm (P=0.04), and preservation of ventricular function (P=0.05) was superior in patients who were appropriately staged. None of the patients had atrial thrombus, chronic pleural effusions, or protein losing enteropathy. Conclusions: In the majority of patients, the extracardiac Fontan procedure, when performed as a staged procedure, provides excellent early and midterm results in terms of quality of life, maintenance of sinus rhythm, and preservation of ventricular function. Copyright (C) 2000 Elsevier Science B.V.
Keywords: Bidirectional cavopulmonary anastomosis; Fontan operation; Univentricular heart

Survival after listing for cardiac transplantation in children - Morrow, W.R.; Frazier, E.; Naftel, D.C. (Progress in Pediatric Cardiology, 2000)
Despite improvement in surgical and medical management of children with congenital and acquired heart disease, cardiac transplantation remains an important therapeutic option for infants and children with end-stage heart disease. Ultimate survival in patients who are listed for transplantation is a function of both mortality while awaiting transplantation and survival after transplantation. Survival of heart transplantation is affected by the severity of illness before transplantation, the unique pathophysiology of certain defects, and the availability of donor hearts. Outcome following listing for transplantation is best studied with the use of recent modifications in statistical methods of competing outcomes analysis. By this analysis a predicted mortality while waiting among all pediatric patients is 20% at 1 year, with 67% undergoing transplantation, 10% still on the list awaiting transplant, and 3% removed from the list. Among infants, most of them with hypoplastic left heart syndrome, 60% will have transplantation by 6 months after listing, with 27% of patients dying while waiting. In infants the major risk factors for death while waiting are the need for inotropic support at listing, smaller size, and recipient blood type. In older children risk factors for death while waiting are Status 1 at listing and a need for mechanical ventilation. Intermediate-term survival after transplant is excellent in all age groups with 86% alive at 6 months, 84% at 1 year, and 73% at 5 years. Survival after transplant in infants is comparable to survival in older children, although the early mortality after transplantation is greater. Infants who have recently undergone sternotomy or received organs from donors who did not die of closed head trauma are more likely to die early after transplant. Among older children risk factors for death after transplantation include the need for a mechanical support device or a younger age in patients greater than 1 year of age. Death following transplantation is primarily related to early graft failure in infants, whereas rejection, infection, and sudden death account for the majority of deaths in older children. Although improved immunosuppressive agents promise to lead to even better survival rates after transplantation, greater access to donors is essential if overall survival is to be improved. (C) 2000 Elsevier Science Ireland Ltd.
Keywords: Cardiac transplantation; Competing outcomes; Infancy and childhood; Survival analysis

Outcome of patients with cyanotic congenital heart disease undergoing a second systemic-to-pulmonary artery shunt - Aeba, R.; Katogi, T.; Takeuchi, S.; Kawada, S. (Journal of Cardiovascular Surgery, 2000)
Background. Multiple systemic-to-pulmonary artery shunts often represent a deviation from the initial management strategy for cyanotic congenital heart disease. This study analysed the outcome in patients undergoing a second shunt. Methods. Between 1965 and 1998, 80 patients required a second shunt. Patient age ranged from 11 days to 11.2 years at the initial shunt, and 4 months to 25.6 years at the second shunt. The interval between shunts ranged from 11 days to 19.6 years. Results. The patient survival rates at 1, 6, 12, 60 and 120 months following the second shunt were 95.0 ± 2.4%, 92.5 ± 3.0%, 87.4 ± 3.7%. 82.4 ± 4.5% and 74.8 ± 5.8%, respectively. Although excess pulmonary flow was not encountered after the second shunt, mode and incidence of morbidity were otherwise similar to the first one. Between 9 months and 7.5 years after the second shunt, 24 patients underwent successful definitive repair. Multivariable analysis identified pulmonary atresia (p = 0.027) and a short (< 1 year) interval between the two shunts (p = 0.034) as the independent risk factors for long-term shunt failure. Single ventricle physiology (p = 0.002) and a central approach for the second shunt (p = 0.016) were independent risk factors for lack of application, or failure of intracardiac definitive repair. Conclusions. A significant limitation in longevity and quality of life is common in patients requiring a second shunt, especially those associated with pulmonary atresia, the single ventricle physiology heart, or ungraftably hypoplastic contralateral branch pulmonary artery to the first shunt. Since excess pulmonary blood flow leading to congenital heart failure and/or ventricular diastolic dysfunction is unlikely, all patients who preclude definitive repair due to decreased pulmonary blood flow even after the first shunt should be shunted again.
Keywords: Heart defects, congenital surgery; Heart ventricle abnormalities; Tetralogy of Fallot

Neurodevelopmental outcome and lifestyle assessment in school-aged and adolescent children with hypoplastic left heart syndrome - Mahle, W.T.; Clancy, R.R.; Moss, E.M.; Gerdes, M.; Jobes, D.R.; Wernovsky, G. (Pediatrics, 2000)
Objectives. The purposes of this study are to describe the quality of life and cognitive function in school-aged children who have undergone staged palliation for hypoplastic left heart syndrome (HLHS), and to identify factors that are predictive of neurodevelopmental outcome in this population. Methods. School-aged survivors with HLHS who had undergone palliative surgery at our institution were identified and mailed a questionnaire to assess subjectively quality of life, school performance, and incidence of medical complications. A subgroup of local patients underwent standardized testing of cognitive function and neurologic examination. These patients were compared with the larger (remote) group of questionnaire respondents to determine whether results may be generalizable to the entire HLHS population. Potential predictors of neurologic and cognitive outcome were tested for their association with test scores using multivariate regression analysis. Results. Questionnaire results were obtained from 115 of 138 eligible children (83%; mean age: 9.0 ± 2.0 years). Standardized testing was performed in 28 of 34 (82%) eligible local patients (mean age: 8.6 ± 2.1 years). The majority of parents or guardians described their child's health as good (34%) or excellent (45%) and their academic performance as average (42%) or above average (42%). One third of the children, however, were receiving some form of special education. Chronic medication usage was common (64%); the incidence of medical complications was comparable to that previously reported in children with Fontan physiology. Cognitive testing of the local group demonstrated a median full scale IQ of 86 (range: 50-116). Mental retardation (IQ: <70) was noted in 18% of patients. In multivariate analysis, only the occurrence of preoperative seizures predicted lower full scale IQ. Conclusions. Although the majority of school-aged children with HLHS had IQ scores within the normal range, mean performance for this historical cohort of survivors was lower than that in the general population.
Keywords: Hypoplastic left heart syndrome; Neurodevelopmental outcome; Quality of life

Hypoplastic left heart syndrome: Valuing the survival - Williams, D.L.; Gelijns, A.C.; Moskowitz, A.J.; Weinberg, A.D.; Ng, J.H.; Crawford, E.; Hayes, C.J.; Quaegebeur, J.M. (Journal of Thoracic and Cardiovascular Surgery, 2000)
Objective: To examine the survival, developmental status, quality of life, and direct medical costs of children with hypoplastic left heart syndrome who have undergone stage I, II, and III reconstructive surgery. Methods: A total of 106 children underwent staged repair for classic hypoplastic left heart syndrome between February 1990 and March 1999 (stage I: 106; stage II: 49; stage III: 25; 4 converted to heart transplantation). Survival was analyzed by the Kaplan-Meier method. In a cross-sectional study, parents assessed quality of life by completing the Infant/Toddler Child Health Questionnaire or Child Health Questionnaire Parent Format-28; they assessed developmental progress by completing the Ages and Stages Questionnaire. The ratio-of-costs-to-charges method was used to derive hospital costs, and payments were used to capture physician time and wholesale pricing for outpatient medications. Results: Institutional 1-year and 5-year actuarial survivals were 58% and 54%. Birth weight, the need for preoperative inotropic drugs, and surgical experience were predictors of survival. Norwood I patients achieved fewer developmental benchmarks than those who survived to subsequent stages. Child Health Questionnaire Parent Format-28 mean summary scores for physical and psychosocial health were 48.5 ± 6.3 and 42.8 ± 9.9. The median inpatient costs for stage I, II, and III repairs were $51,000, $33,892, and $52,183, respectively. Monthly outpatient and readmission costs were less than 10% of total costs. Conclusion: A prospective, large-scale study of the comprehensive outcomes of staged repair and transplantation is needed. This study will need to address the longer- term developmental and quality-of-life outcomes, as well as the long-term cost effectiveness of these procedures.

Electrocardiographic ST-segment depression in children with Fontan circulation - Rydberg, A.; Teien, D.E.; Rask, P.; Hörnsten, R. (Clinical Physiology, 2000)
Despite successful operation, many patients palliated with a Fontan-type procedure continue to show effort limitation. We previously observed that these children showed electrocardiographic ST depression during exercise tests. The purpose of the study was to investigate whether electrocardiographic ST depression is a common finding in children with Fontan circulation. Forty-two children in two groups were examined: group A consisted of 14 patients who had all undergone a modified Fontan procedure, and group B consisted of 28 children with a structurally normal heart, matched for length, weight and gender to group A. Complete echocardiographic examinations were performed in all patients and controls. All 14 patients and all 28 healthy children underwent standard 24 h ambulatory electrocardiographic monitoring. All the recordings were analysed by a PC-based Holter system where an analysis of ST changes was performed. Seven patients and 14 matched healthy children were exercised on bicycle ergometers. Four patients and eight matched healthy children underwent exercise testing by walking/running a treadmill. Ten of 13 patients analysed had significant ST depressions on ambulatory electrocardiogram (> 0.20 mV). Three of the 10 patients with ST depression were on digoxin. Three patients showed depressions of the ST segment in the electrocardiogram during exercise, with a maximal depression of 0.20-0.35 mV. None of the 28 matched healthy children showed electrocardiographic ST depression on the ambulatory 24 h ECG. These findings indicate that ST depression in daily activity is a common finding in children with Fontan circulation.
Keywords: Children; Electrocardiographic ST depression; Fontan; Univentricular heart

Surgical treatment of coarctation complex in neonates and infants. - Yamauchi, H.; Fujii, M.; Iwaki, H.; Ishii, Y.; Saji, Y.; Maruyama, Y.; Yamashita, H.; Uchikoba, Y.; Fukazawa, R.; Okubo, T.; Ogawa, S.; Tanaka, S. (Journal of Nippon Medical School = Nihon Ika Daigaku zasshi, 2000)
BACKGROUND: There remains controversy regarding the appropriate surgical treatment of coarctation of the aorta associated with intracardiac anomalies in neonates and infants. Furthermore, the relative benefits of one versus two-stage repair, and subclavian flap aortoplasty versus end-to-end anastomosis for some of these lesions, remain controversial. The purpose of this paper is to review our experience with two-stage repair using subclavian flap aortoplasty and to seek an appropriate procedure. METHODS AND RESULT: From June 1996 to November 1999, thirteen patients underwent subclavian flap aortoplasty in our department. The age range was 16 to 101 days (mean 52 days), and the body weight range was 1.9 to 4.5 kg (mean 3.0 kg). Anatomic diagnosis was coarctation with ventricular septal defect (six patients), double outlet right ventricle (two patients), atrioventricular canal defect (one patient), tricuspid atresia (two patients), mitral atresia (one patient), and single atrium and subaortic stenosis (one patient). There was one hospital death in our series due to the progression of pulmonary hypertension 3 months after the operation. The mean follow up for remaining twelve patients was 28 months (range 7 approximately 48 months). There was one reoperation for recurrent coarctation. Three patients underwent pulmonary artery plasty in a second operation because of right pulmonary artery stenosis. We performed the definitive operation for six patients with coarctation with ventricular septal defect and two patients with double outlet right ventricle, and we performed a bidirectional cavopulmonary shunt for four univentricular hearts who are candidates for the Fontan operation. Two patients required Damus-Kaye-Stansel procedure to release restrictive bulboventricular foramen. Three patients underwent a modified Fontan operation after these palliations. In our series, the intraoperative mortality rate for subclavian flap aortoplasty was 0% and the post operative mortality rate was 7.7% (1/13). Ten patients underwent the final operation successfully, and further two patients are considered good candidates for the final operation. The overall mortality was 7.7% (1/13). CONCLUSION: Two-stage repair appears to offer a good prognosis for neonates and infants with a coarctation complex. Subclavian flap aortoplasty showed the lowest rate of restenosis. However, late mortality may be associated with the progression of pulmonary vascular disease and the presence of associated severe cardiac anomalies. Although Fontan candidates need staged operations, if biventricular repair is feasible, one-stage repair would be a reasonable procedure considering the progression of the pulmonary vascular disease and the distortion of the pulmonary artery due to pulmonary artery banding. It would appear to improve the quality of life of those children if a one-stage operation can be performed with reasonable risk and good midterm outcome.

Impact of early ventricular unloading on exercise performance in preadolescents with single ventricle Fontan physiology - Mahle, W.T.; Wernovsky, G.; Bridges, N.D.; Linton, A.B.; Paridon, S.M. (Journal of the American College of Cardiology, 1999)
OBJECTIVES: We sought to determine if early ventricular volume unloading improves aerobic capacity in patients with single ventricle Fontan physiology. BACKGROUND: Surgical strategies for patients with-single ventricle include intermediate staging or early Fontan completion to reduce the adverse affects of prolonged ventricular volume load. The impact of this strategy on exercise performance has not been evaluated. METHODS: Retrospectively, we reviewed the exercise stress test results of all preadolescents with single unloading was ventricle Fontan physiology. 'Volume unloading' was considered to have occurred at the time of bidirectional cavopulmonary anastomosis or at the time of Fontan surgery in those patients who did not undergo intermediate staging. Potential predictors of aerobic capacity were analyzed using multivariate regression. RESULTS: The patients (n = 46) achieved a mean percentage predicted of maximal oxygen consumption (V̇O2(max)) of 76.1% ± 21.1%. The mean age at the time of volume unloading was 2.7 ± 2.4 years, and the mean age at testing was 8.7 ± 2 years. Intermediate staging was performed in 16 of 46 patients (35%). In multivariate analysis, younger age at volume unloading was associated with increased aerobic capacity (p = 0.003). Other variables were not predictive. The subgroup of patients who underwent volume unloading before two years of age achieved a mean percentage predicted V̇O2(max) of 88.6% ± 24.1%. CONCLUSIONS: Preadolescents with single ventricle who undergo volume unloading surgery at an early age demonstrate superior aerobic capacity compared with those whose surgery is delayed until a later age.

Results after Norwood procedure and subsequent cavopulmonary anastomoses for typical hypoplastic left heart syndrome and similar complex cardiovascular malformations - Breymann, T.; Kirchner, G.; Blanz, U.; Cherlet, E.; Knobl, H.; Meyer, H.; Körfer, R.; Thies, W.-R. (European Journal of Cardio-thoracic Surgery, 1999)
Objective: From October 1989 to June 1998, 60 patients have undergone the Norwood procedure (stage I) at our institution. The results of the staged surgical reconstruction and risk factors were analysed. Typical hypoplastic left heart syndrome (HLHS) and complex lesions with aortic hypoplasia were compared with each other. Patients: Typical HLHS: N=48, median age 15 days (5-190 days), median weight 3.6kg (2.6-5.3kg). Complex lesions (dominant left ventricle): N=12, median age 59 days (10-884 days), median weight 3.4kg (2.4-12kg). Results: Typical HLHS: The stage-I hospital survival was 73% (35/48). It improved from 60% (95% confidence interval: 49-71%) during 1989-1994 to 91% (95% CI: 81-100%) during 1997-1998. Seven patients were lost late. The right ventricular end diastolic diameter (P=0.015), shortening fraction (P=0.027), and the presence of an obstructed pulmonary venous return (P=0.0032) were significant risk factors. 23 children underwent stage-II operation with four (17%) deaths. All survivors experienced an improvement of their statomotoric development. Stage-III operation was performed in 13 patients with no hospital death. Follow up after stage-III procedure was 7 months to 7 years. 4 year actuarial survival, including hospital mortality and deaths at subsequent stages, improved from 28% (95% CI: 18-38%) during 1989-1994 to 58% (95% CI: 48-68%) during 1994-1997. No patient had signs of myocardial insufficiency. Complex lesions: Stage-I hospital survival was 83% (10/12) with no late death. Stage-II was performed in 8 and stage-III in 6 patients with no death respectively. Conclusion: In typical HLHS the results have improved over time. Both size and function of the right ventricle determined significantly stage-I survival. An early operation prevents the natural progression of pulmonary blood flow and may weaken all three risk factors. Patients with complex lesions seemed to have better chances of surviving the early postoperative period. The multistage reconstructions have become a realistic option for patients with HLHS and similar lesions, regardless of the morphologic subtype or diminutiveness of the aorta, and lead to an acceptable quality of life. Copyright (C) 1999 Elsevier Science Ireland Ltd.
Keywords: Fontan operation; Hypoplastic left heart syndrome; Norwood procedure; Risk factors; Single ventricle; Total cavopulmonary anastomosis

Sudden cardiac death in infants, children, and adolescents - Berger, S.; Dhala, A.; Friedberg, D.Z. (Pediatric Clinics of North America, 1999)
Although SCD is relatively uncommon, its psychosocial impact is devastating. This article has reviewed the potential causes of SCD in infants, children, and adolescents. Many patients who die from SCD have identifiable cardiac disease and are known to have been at risk; however, the existence of other cardiac abnormalities, such as hypertrophic cardiomyopathy or long QT syndrome, may not be known, and SCD may be the first symptom. The authors' contention is that many of the patients in this latter group (e.g., patients who have hypertrophic cardiomyopathy or LQLTS but who have no symptoms) can be screened with a careful, accurate, and detailed history, including family history and review of systems, and physical examination. Any patient with a positive family history, positive review of systems, or positive physical examination should receive further in-depth evaluation, such as an BCG and echocardiogram. These studies permit the detection of most, if not all, of the entities potentially associated with SCD in the pediatric population.

Managing disagreements in the management of short bowel and hypoplastic left heart syndrome. - Cooper, T.R.; Garcia-Prats, J.A.; Brody, B.A. (Pediatrics, 1999)
BACKGROUND AND OBJECTIVES: When innovative, not yet fully proven therapies are introduced, physicians may have neither experience nor sufficient data in the medical literature to assist in their decision to discuss them with and/or recommend them to patients. Little is known about how physicians deal with this uncertainty. Moreover, when multiple physicians caring for a single patient have reached different conclusions regarding this new therapy, the potential for disagreement exists that could give rise to ethical issues as well as cause confusion to the patient. To explore these topics, we investigated the attitudes of specialists to therapies for two life-threatening diseases: hypoplastic left heart syndrome (HLHS) and short bowel syndrome. METHODS: A forced choice questionnaire was distributed to the heads of neonatology, pediatric cardiology, and pediatric gastroenterology training programs asking about their outcome impressions and treatment recommendations and about the local availability of treatments. In addition, responses from specialists from the same institution were linked in a confidential manner to evaluate the frequency of disagreement within the same institution. Responses were analyzed using chi(2) and Wilcoxon matched pair analysis as appropriate. RESULTS: The overall rate of response was 79%. In institutions that had both neonatology and pediatric gastroenterology training programs, there was a 59% response rate compared with a 73% response rate from institutions that had both neonatology and cardiology programs. Significant differences were noted among specialists as to who would be involved in discussions of therapeutic options with patients in both HLHS and short bowel syndrome. Differences also were noted in the willingness of specialists to discuss and recommend therapies, in the perceived survival and quality of life by various specialists after transplant and palliative surgery, and in the local availability of various options. The neonatologists and gastroenterologists at the same institution disagreed on responses in 34% of the questions with only 1 of the 25 pairs in full agreement. In contrast, the neonatologists and pediatric cardiologists at the same institution disagreed in only 14% of the questions with 7 of the 28 pairs in full agreement. CONCLUSIONS: Substantial disagreement among specialists about new interventions was found. There seem to be fewer differences among specialists when dealing with the more mature therapy, HLHS. Two major ethical issues arise. First, there seems to be no accepted professional standard to which individuals can appeal when determining whether to discuss or recommend new, not-yet-fully-proven technologies. Second, there is the potential for much patient confusion when counseling physicians recommend different options. Colleagues as individuals and specialists as groups should talk to each other before individual discussions with families to ensure that there is a clear understanding of differing beliefs.

Cyanotic congenital heart disease with decreased pulmonary blood flow in children - Waldman, J.D.; Wernly, J.A. (Pediatric Clinics of North America, 1999)
Of the 'five T's' of cyanotic congenital heart disease-tetralogy of Fallot, TGA, TAPVC, truncus, and tricuspid valve abnormalities (tricuspid atresia, stenosis, and displacement)-the first and last are commonly associated with diminished PBF. The four features that comprise tetralogy of Fallot-right ventricular hypertrophy, VSD, overriding aorta, and subpulmonary stenosis-are all secondary to a single morphogenetic defect: failure of expansion of the subpulmonary conus. This also explains the variability in clinical presentation. When neonates need intervention, shunts are usually performed. Coronary arterial anatomy must be defined before repair, which is usually done after these infants are 3 months of age. Although children with repaired tetralogy of Fallot are not completely 'normal,' markedly increased longevity and improvement in quality of life can be achieved. When major associated defects are present, such as atrioventricular canal defect, diminutive pulmonary arteries or collateral vessels, or left heart lesions, the prognosis changes from excellent to merely good. Tetralogy of Fallot with absent pulmonary valve syndrome is physiologically different from other tetralogy of Fallot conditions and characterized primarily by airway obstruction from massive dilatation of the central and perihilar pulmonary arteries; repair with pulmonary artery reduction is necessary. Tricuspid valve abnormalities include atresia, hypoplasia (i.e., pulmonary atresia with intact ventricular septum), and displacement (i.e., Ebstein anomaly). The pathophysiology that dictates these children's clinical condition (and prognosis) relates to three factors: (1) status of the tricuspid valve, (2) presence and size of a VSD, and (3) TGA or normally related great arteries. Virtually all children with tricuspid valve abnormalities can be palliated; reparative options include repair using two-ventricle, one-ventricle, or 1- 1/2 ventricle repair. Children with critical pulmonary stenosis generally have a normal tricuspid valve and right ventricle. Balloon dilation is usually the only therapy necessary.

Advances in the care of children with heart disease - Fedderly, R.T.; Berger, S.; Frommelt, P.C.; Lewis, D.A.; Dhala, A.; Pelech, A.N.; Frommelt, M.A.; Friedberg, D.Z.; Thomas Jr., J.P.; Tweddell, J.S.; Litwin, S.B. (Wisconsin Medical Journal, 1998)
As we enter the next millennium, we are encouraged by the progress that has been made in the care of neonates, infants, and children with heart disease. Surgical repair can be offered at an earlier age with excellent results. Diseases that were uniformly fatal in the past have improved outcomes. Research continues in the area of interventional devices such that surgical repair might be eliminated or delayed. We continue to look forward to advances in the next several years that will allow for future improvement in outcome, better quality-of-life and better long-term results.

Nonmalignant hyperthermia on induction of anesthesia in a pediatric patient undergoing Bi-directional glenn procedure - Leung, W.K.; Jahr, J.S.; Hotz, J.; Pollock, M. (Journal of Clinical Anesthesia, 1998)
We report a case of severe hyperthermia in a 6-month-old boy with a single ventricle, dextrocardia, asplenia, and transposition of the great arteries, during induction of anesthesia on three separate occasions. To our knowledge, this is the first case reported of repeated intraoperative hyperthermia not related to malignant hyperthermia, infection, neuroendocrine tumor, or iatrogenic causes (e.g., anticholinergic blockade or warming devices). The severe hyperthermia may be secondary to the medications given before and during induction and/or the stress of the induction. Among the induction medications given during the three episodes, fentanyl is the most likely contributing drug. Human data indicate that opioids increase the sweating threshold and decrease the vasoconstriction and shivering thresholds. The medications could cause a widening in the thermoregulation interthreshold and the stress could induce nonshivering thermogenesis.
Keywords: Anesthetic technique: general; Complications: nonmaalignant hyperthermia; Glenn procedue; Pediatrics

Outcome after prenatal diagnosis of the hypoplastic left heart syndrome - Allan, L.D.; Apfel, H.D.; Printz, B.F. (Heart, 1998)
Objective - To derive accurate survival figures in the current surgical era for counselling in early pregnancy after the diagnosis of fetal hypoplastic left heart syndrome. Setting - A tertiary referral centre for paediatric cardiology and cardiac surgery. Design - A retrospective study of the outcome in all cases of hypoplastic left heart syndrome presenting in fetal life between mid-1993 and the end of 1996. Patients - The diagnosis was made in 30 fetuses. In four of 12 identified before 24 weeks' gestation the mothers chose to terminate the pregnancy. There was an intention to treat in 24 of the remaining fetuses. Main outcome measure - Survival to six months of postnatal life. Results - Of the 24 infants, five were not offered Norwood stage I because of trisomy 18 (n = 2), unfavourable cardiac anatomy (n = 2), or neurological impairment (n = 1). One further infant did not survive to cardiac surgery after gastrointestinal surgery. Of the remaining 18 patients, eight had features that were considered to increase the risk of surgical repair. Of the 18 patients who underwent Norwood stage 1, there were nine survivors. There was a survival rate of 70% in infants undergoing surgery with no complicating features, a 50% survival of the all surgical candidates, and 37.5% survival from an intention to treat position. Conclusions - At the initial diagnosis of fetal hypoplastic left heart syndrome, the overall survival appears to be less than 40%. Evaluation must include detailed extracardiac and intracardiac assessment to predict the risks of surgical treatment. Prenatal counselling can be modified as pregnancy advances, depending on the detection or exclusion of complicating factors.
Keywords: Congenital heart disease; Fetus; Hypoplastic left heart syndrome

Abnormal dynamic cardiorespiratory responses to exercise in pediatric patients after fonton procudure - Troutman, W.B.; Barstow, T.J.; Galindo, A.J.; Cooper, D.M. (Journal of the American College of Cardiology, 1998)
Objectives. Novel protocols were used to focus on dynamic cardiorespiratory function during submaximal exercise and on the recovery from 1-min pulses of exercise in children who had undergone Fontan corrections for single-ventricle lesions. Background. Particularly in children, maximal oxygen uptake (Vo2max), which is commonly used to assess the functional capability of patients after the Fontan procedure, is highly effort dependent and not physiologic and leads to uncomfortable metabolic and cardiorespiratory stress. Alternative approaches include the measurement of dynamic responses during progressive exercise and recovery after short bursts of exercise. These strategies yield mechanistic insight into cardiorespiratory impairment and can be used to gauge limitations in daily life activity. Methods. Sixteen patients (mean (±SD) age 12.2.± 2.4 years; 9 boys) and 10 age-matched control subjects (mean age 12.2 ± 2.4 years; 6 boys) performed two separate cycle ergometer test in which gas exchange was measured on a breath by basis:1) Progressive exercise was used to determine the dynamic relation among Vo2, carbon dioxide production (VCO2), ventilation (VE), heart rate (HR) and work rate (WR).2) A 1-min constant WR test was used to determine the recovery time for gas exchange and HR. Results. Peak VO2 and anaerobic threshold were reduced in patients who underwent the Fontan procedure compared with control subjects by 57% and 52%, respectively (p < 0.001). Dynamic relations during progressive exercise - ΔVO2/ΔHR and ΔVO2/ΔWR - were decreased (p < 0.001) and ΔE/ΔVCO2 was increased (p < 0.005) in the Fontan group patients. Recovery times for HR VO2 were prolonged in the Fontan group patients by 154% and 69%, respectively (p < 0.01). Conclusions. The results demonstrate that submaximal gas exchange response to progressive exercise and recovery times after brief intensity exercise are abnormal in patients after the Fontan procedure. These observations complement the findings of reduced VO2 max observed here and by others. We speculate that the mechanisms for these responses are related to 1) a pervasive reduction in stroke volume for both low and high intensity exercise, 2) an abnormal linkage of ventilation to tissue carbon dioxide production, and 3) increased dependence on anaerobic metabolism in skeletal muscles. The prolonged recovery of HR and VO2 provides a possible mechanism for reduced physical activity.

Clinical implications of isolated double aortic arch and its complex with intracardiac anomalies - Lee, M.-L.; Wang, J.-K.; Wu, M.-H.; Lue, H.-C.; Ing-Sh Chiu; Chang, C.-I. (International Journal of Cardiology, 1998)
From July 1, 1989 to June 30, 1996, a total of six patients, four male and two female, with double aortic arch (DAA) were registered. They aged 16 days to 6.5 years. There were two patients with isolated DAA, and four complicated with intracardiac anomalies. All six patients presented respiratory distress and feeding problem early in life. However, cyanosis, owing to decreased pulmonary blood flow, predominated the clinical picture in each patient having DAA intricated with tetralogy of Fallot (TOF) and pulmonary stenosis, TOF with absent pulmonary valve syndrome, and type II-A tricuspid atresia. DiGeorge syndrome was documented in one patient with TOF and pulmonary stenosis. Expiratory wheezing was remarkable in the patient with TOF and absent pulmonary valve syndrome. Mild cyanosis and heart failure was noted in one patient with ventricular septal defect (VSD), and bicuspid pulmonary valve with mild valvular stenosis. Barium esophagogram showed indentations on esophagus in five patients. Echocardiography was yielding in three infants. Four patients, two isolated and two complex DAA, survived the surgical division of the smaller left aortic arch. One-stage and two-stage operation was performed in patients having DAA intricated with VSD and TOF, respectively. The other two patients with complex DAA remained in close observation owing to the tolerance of symptoms related to intracardiac anomalies.
Keywords: Absent pulmonary valve syndrome; Bicuspid pulmonary valve; DiGeorge syndrome; Double aortic arch; Tetralogy of Fallot; Tricuspid atresia; Ventricular septal defect

Alterations in pulmonary artery flow patterns and shear stress determined with three-dimensional phase-contrast magnetic resonance imaging in fontan patients - Morgan, V.L.; Graham, T.P., Jr.; Roselli, R.J.; Lorenz, C.H. (Journal of Thoracic and Cardiovascular Surgery, 1998)
Objective: This study compares in vivo pulmonary blood flow patterns and shear stresses in patients with either the direct atrium-pulmonary artery connection or the bicaval tunnel connection of the Fontan procedure to those in normal volunteers. Comparisons were made with the use of three-dimensional phase contrast magnetic resonance imaging. Methods: Three-dimensional velocities, flows, and pulmonary artery cross-sectional areas were measured in both pulmonary arteries of each subject. Axial, circumferential, and radial shear stresses were calculated with the use of velocities and estimates of viscosity. Results: The axial velocities were not significantly different between subject groups. However, the flows and cross-sectional areas were higher in the normal group than in the two patient groups in both pulmonary arteries. The group with the bicaval connection had circular swirling in the cross section of both pulmonary arteries, causing higher shear stresses than in the controls. The disorder caused by the connection of the atrium to the pulmonary artery caused an increase in some shear stresses over the controls, but not higher than those found in the group having a bicaval tunnel. Conclusions: We found that pulmonary flow was equally reduced compared with normal flow in both patient groups. This reduction in flow can be attributed in part to the reduced size of the pulmonary arteries in both patient groups without change in axial velocity. We also found higher shear stress acting on the wall of the vessels in the patients having a bicaval tunnel, which may alter endothelial function and affect the longevity of the repair. © 1998 Mosby, Inc.

Hypoplastic left heart syndrome: Multiprofessional follow-up in the mid-term following palliative procedures - Hagemo, P.S.; Rasmussen, M.; Bryhn, G.; Vandvik, I.H. (Cardiology in the Young, 1997)
Of the 12 children who represent the complete cohort of Norwegian patients surviving the complete palliative operative programme for hypoplastic left heart syndrome, 10 were studied by a pediatric cardiologist, a pediatric neurologist, a neuropsychologist and a child psychiatrist. We found significant morbidity. Hemodynamic function was relatively uncompromised in eight of the patients, but one had significant cyanosis due to use of an operative technique subsequently abandoned and one had obstruction of the flow of blood from the left to the right atrium. Five children had disturbances of rhythm, with one requiring insertion of a pacemaker. One child had epilepsy. Delayed motor development, most often to mild degree, was found in seven children, while six had attention problems. Mental retardation was found in two children and autistic traits in one. Despite these various problems, the parents were seemingly satisfied with their own lives, and the quality of life of their children. © Greenwich Medical Media Ltd.
Keywords: Follow-up; Hypoplastic left heart syndrome; Norwood palliation

The clinical application of pediatric pharmacologic stress echocardiography in evaluating non-ischemic heart disease - Kimball, T.R.; Witt, S.A. (Journal of the American Society of Echocardiography, 1997)
Traditionally, exercise echo has been used to evaluate pediatric heart disease, specifically, obtaining information regarding pressures, gradients, and function during increased cardiac demands. However, its use is limited because of poor acoustic windows and patient age. Pharmacologic stress echo is an attractive alternative in evaluating heart disease other than coronary disease but has not been explored in children. Methods: We performed pharmacologic stress echo in evaluating non-coronary diseases in 9 patients (3 to 19 y.o.). Diagnoses included aortic stenosis in 3 patients; and coarctation, hypertrophic cardiomyopathy, pulmonary stenosis, "healed" myocarditis, dilated cardiomyopathy and single ventricle in 1 each. Test indications were to assess stress gradient in obstructive lesions and stress function in the other diagnoses. Dobutamine (in 8) or isoproterenol (in 1) was given in increasing doses until one or more of the following endpoints: 1) symptoms (sx), 2) severe gradient, 3) decreasing function, and/or 4) maximum dose. Results: In all patients, tests were safe, and echo information was easily obtained. Gradients increased to significant levels in 5 of the 6 patients with obstruction. The remaining studies were normal. In 4 patients, stress results altered patient care: medical treatment in 3 patients and surgery in 1. Conclusions: Pharmacologic stress echo overcomes the limitations of exercise echo, and is safe and feasible in assessing pediatric heart disease other than coronary artery disease. Hemodynamics during stress may be more clinically relevant than resting echo data because they reflect physiology more closely resembling that which occurs during a child's typically active state. This may improve timing of medical and surgical intervention.

Thoracic epidural anesthesia for cholecystectomy in a patient after fontan procedure - Arai, M.; Kanai, A.; Matsuzaki, S.; Takenaka, T.; Kato, S. (Japanese Journal of Anesthesiology, 1997)
A 12 year-old boy who had received modified Fontan procedure was scheduled for cholecystectomy. Anesthesia was maintained with thoracic epidural anesthesia (Th8-9) and 02-N20-sevoflurane under mechanical ventilation through the endotracheal tube. Transeshophageal echo cardiography and mixed venous oxygen saturation (Svoz) were used for hemodynamic monitoring. The combined use of epidural anesthesia and volatile anesthetics decreased central venous pressure, left ventricular end diastolic volume, left ventricular ejection fraction and Sv̄o 2. These hemodynamic problems were easily solved by infusion therapy and a low dose of dopamine. On the other hand, there were also some hemodynamic benefits such as inhibition of tachycardia and suppression of an increase in pulmonary vascular resistance due to surgical stress. Moreover, patient returned to normal spontaneous breathing with complete analgesia during the early phase after surgery. CVP and Sv̄o 2 increased to preoperative values in the recovery room. From these results, we conclude that satisfactory results can be obtained with epidural anesthesia for upper abdominal surgery after Fontan procedure.

Pulmonary atresia with intact septum: Findings on exercise stress sestamibi scan - Fisher, D.J.; Ferency, S.L.; Rosenbaum, D.M.; McCloskey, J.P. (Clinical Nuclear Medicine, 1997)
Right ventricular size in cases of pulmonary atresia is determined by blood flow into and out of the right ventricle. A hypoplastic or enlarged right ventricle can result. In cases of an intact septum, elevated right ventricular pressure results in retrogated flow of blood from a blind-ending right ventricle into the coronary artery circulation via enlarged myocardial sinusoids. In some cases, no connection exists between the coronary arteries and the aorta. Stress sestamibi myocardial perfusion scan is helpful in determining if myocardium is at risk for ischemia or infarction in cases in which coronary circulation is influenced by right ventricular-coronary artery communications.
Keywords: Congenital Heart Defects; Pulmonary Atresia; Technetium Tc-99m Sestamibi

Survival and risk factors for death after cardiac transplantation in infants: A multi-institutional study - Canter, C.; Naftel, D.; Caldwell, R.; Chinnock, R.; Pahl, E.; Frazier, E.; Kirklin, J.; Boucek, M.; Morrow, R. (Circulation, 1997)
Background: Despite the increasing application of cardiac transplantation in infants, reported survival rates vary, and risk factors for death are poorly understood. Methods and Results: To examine early survival and risk factors for death in infants (<1 year of age) undergoing cardiac transplantation, 141 infants (36 < 1 month of age) underwent primary cardiac transplantation between January 1, 1993, and January 1, 1995, at 23 centers in the Pediatric Heart Transplant Study (PHTS). Diagnoses were hypoplastic left heart syndrome (66%), other congenital hearth disease (17%), cardiomyopathy (14%), and other (3%). Actuarial survival after cardiac transplantation was 84% at 1 month, 70% at 1 year, and 69% at 2 years, with the greatest hazard for death within the first 3 months. The principal cause of death was early graft failure in 20 patients (52% of deaths), infection in 10 (26% of deaths), and rejection in 4 (10%). On the basis of multivariate analysis, risk factors for early mortality were history of previous sternotomy (P=.0003), nonidentical blood type donor (P=.01), recipient non- blood group A (P=.02), and donor cause of death other than closed head trauma (P=.04). Diagnosis at listing, waiting time (mean, 1.3 months), graft ischemic time (mean, 228 minutes; range, 68 to 479 minutes), and recipient ventilatory or inotropic support at listing were not predictive for mortality after transplant. Conclusions: The higher mortality rate observed with infant heart tranplantation is due to a higher mortality within the first month after transplantation as a result of early graft failure. Strategies to improve donor heart function at implantation would have the greatest impact on survival after infant cardiac tranplantation.
Keywords: Infants; Risk factors; Survival; Transplantation

Bidirectional cavo-pulmonary anastomosis with an additional flow source to the lungs: Clinical experience in 21 cases - Borini, I.; Marasini, M.; Dalmonte, P.; Bava, G.L.; Lerzo, F.; Cervo, G.; Moretti, R.; Bertolini, A.; Zannini, L. (Vascular, 1997)
The Fontan operation is considered a palliative procedure for the treatment of complex congenital heart diseases with a morbidity and mortality that are not negligible, expecially in high-risk patients. In these cases, a bidirectional cavopulmonary anastomosis with additional source of blood flow to the lungs can represent a valuable surgical option. Between November 1992 and December 1995, 21 patients with univentricular heart physiology were submitted to bidirectional cavopulmonary anastomosis with additional blood flow the additional flow consisted of an aortopulmonary shunt in 13 cases, pulmonary artery banding in seven cases, and pulmonary artery stenosis in one case. Mean age at operation was 35.5 months (range 4 months to 12 years) and mean body weight 10.9 (range 4–24.4) kg. Hospital mortality was zero. Morbidity (pleuropericardial effusions) was significant in one case. There were three late deaths (14%) caused by worsening atrioventricular valve regurgitation: two of these occurred in patients with right isomerism. Late haemodynamic evaluation documented a significant increase in cardiac output (P < 0.01) and oxygen saturation (P < 0.05) during pharmacological stress testing. Angiographic characterization of blood flow distribution to the lungs showed better results when the additional blood flow was represented by an anterograde source (pulmonary artery banding or native pulmonary artery stenosis). In conclusion, bidrectional cavopulmonary anastomosis with additional blood flow is a good alternative to classic or fenestrated Fontan technique in high-risk patients. Secondly, the diagnosis of isomerism could be a contraindication to this type of surgery, because the persistent volume overload could worsen atrioventricular valve regurgitation. Thirdly, the pharmacological stress testing shows a favourable behaviour of cardiac output and arterial oxygen saturation. Fourth, the type of additional blood flow seems to condition both pulsatility and distribution of pulmonary blood flow. © 1997, The International Society for Cardiovascular Surgery. All rights reserved.
Keywords: bidirectional cavopulmonary anastomosis; congenital heart disease; Fontan operation

The optimal fontan connection: A growing extracardiac lateral tunnel with pedicled pericardium - Gundry, S.R.; Razzouk, A.J.; Del Rio, M.J.; Shirali, G.; Bailey, L.L.; Reddy, V.M.; Drinkwater, D.C.; Lamberti, J.; Mayer J.E., Jr. (Journal of Thoracic and Cardiovascular Surgery, 1997)
ObJective: The concept of a lateral tunnel for the Fontan operation is now widely accepted. Most lateral tunnels are constructed intraatrially with the use of aortic crossclamping. Construction of extracardiac lateral tunnels with the use of homografts or other nonviable tubes eliminates aortic crossclamping but lacks growth potential in length or width. The native pericardium, which is 'sealed' posteriorly along the pulmonary artery, atrium, and inferior vena cava, could be turned down onto the right atrium to form a viable extracardiac lateral tunnel. Methods: We designed and successfully constructed extracardiac lateral tunnels using viable autologous pericardium, pedicled on its lateral blood supply, in 19 patients aged 9 months to 5 years. All patients had a previous Glenn shunt; five patients had dextrocardia and a midline inferior vena cava. The patients' inferior vena cava-right atrial connection was opened transversely and the right atrial opening was sutured to its back wall, keeping the eustachian valve in the inferior vena cava. The underside of the right pulmonary artery was opened longitudinally; its inferior edge was sewn to the adjacent pericardial reflection. Any 'pocket' or depressions in the posterior pericardium along the pulmonary veins were closed with running suture. Two incisions were made in the right pericardium down to the phrenic nerve parallel to the inferior vena caval and pulmonary arterial openings. This pedicled pericardium was trimmed and sewn as a roof to the upper edges of the inferior vena cava and pulmonary artery openings and then sewn longitudinally along the unopened right atrial wall, completing the viable extracardiac lateral tunnel. Although no fenestrations were used, these could be made during construction, or more significantly, owing to the lack of thick walled structures, in the catheterization laboratory in the postoperative period. Results: All 19 patients had respiratory/cardiac pulsations in the pulmonary arteries owing to the compressible lateral tunnel. At follow-up of up to 2 1/4 years, all tunnels are growing and no obstructions have occurred. Conclusion: The viable autologous pericardial extracardiac lateral tunnel can be constructed without cardiac ischemia, can be fenestrated in the postoperative period, and forms a compressible, nonthrombogenic conduit capable of growth, which can be constructed early in infancy.

Myocardial dysfunction and depressed fatty acid metabolism in patients with cyanotic congenital heart disease - Kondo, C.; Nakazawa, M.; Kusakabe, K.; Momma, K. (Journal of Nuclear Cardiology, 1996)
Background. Myocardial contractile dysfunction has been frequently observed in adolescents or adults with cyanotic congenital heart disease. Impaired energy metabolism may be present in such dysfunctional myocardium. Methods and Results. To evaluate the findings of myocardial free fatty acid metabolism, and its relations to ventricular wall motion and myocardial perfusion in cyanotic congenital heart disease, we performed a combined study of iodine 123-labeled 15-(p-iodophenyl)3- (R,S)-methylpentadecanoic acid (BMIPP) scintigraphy, thallium scintigraphy, and contrast cineangiography in seven patients with single right or left ventricle. The results showed that wall motion was reduced in 17 of 35 ventricular segments (49%), which were mostly identical in location to decreased BMIPP uptake. The severity of BMIPP uptake deficit correlated positively with the degree of impairment of wall motion. On the other hand, thallium uptake was abnormal only in 5 of 35 segments (14%), and the severity of the perfusion defect did not correlate with the degree of wall motion abnormality. Conclusions. Contractile dysfunction in cyanotic heart disease was primarily linked to impaired free fatty acid metabolism rather than to myocardial scar as represented by perfusion defect on thallium imaging.
Keywords: Congenital; Heart defects; Myocardial metabolism

Diminished venous vascular capacitance in patients with univentricular hearts after the Fontan operation - Kelley, J.R.; Mack, G.W.; Fahey, J.T. (The American Journal of Cardiology, 1995)
Patients who have undergone Fontan's operation are known to have impaired cardiac output response to dynamic exercise. This may be due to either poor cardiac function or a limited ability to mobilize blood from capacitance vessels due to increased resting venous tone. We tested the latter hypothesis by determining venous vascular capacitance at rest and during orthostatic stress produced by lower body negative pressure (LBNP) in 6 subjects who had undergone the Fontan operation and 6 healthy age-, sex-, height-, and weight-matched controls. Resting blood volume was similar for Fontan and control subjects (79 ± 6 vs 70 ± 3 ml/kg body weight, respectively), while central venous pressure (CVP) was elevated in Fontan subjects (18.4 ± 1.0 vs 3.5 ± 0.9 mm Hg, p < 0.05). Forearm venous capacitance at a distending pressure of 40 mm Hg was less in Fontan subjects than in controls (2.6 ±0.1 vs 3.9 ± 0.5 ml/100 ml), while resting plasma norepinephrine level was elevated in Fontan subjects (255 ± 28 vs 144 ± 9 pg/ml, p < 0.05). The increase in calf volume (1.6 ± 0.2 vs 2.3 ± 0.2 ml) and decrease in CVP (-5.0 ± 0.5 vs -6.7 ± 1.1 mm Hg) during -30 mm Hg LBNP were smaller for Fontan than control subjects (p < 0.05). Reduced forearm venous capacitance and diminished pooling of blood into capacitance vessels of the leg during orthostaric stress indicated higher venous tone in Fontan than control subjects. We propose that increased resting venous tone in Fontan subjects may limit their ability to mobilize blood from capacitance vessels during exercise and may contribute to impaired cardiac output response. © 1995 Excerpta Medica, Inc. All rights reserved under the United States, International, and Pan-American Copyright Conventions.

A study in ventricular-ventricular interaction: Single right ventricles compared with systemic right ventricles in a dual-chamber circulation - Fogel, M.A.; Weinberg, P.M.; Fellows, K.E.; Huffman, E.A. (Circulation, 1995)
Background: Ventricular-ventricular interaction is known to occur in the normal human heart. To determine whether it plays a role in the function of single right ventricles, systemic right ventricles were compared with and without a left ventricle mechanically coupled to it. Methods and Results: A noninvasive magnetic resonance tagging technique (spatial modulation of magnetization [SPAMM]) that lays intersecting stripes down on the myocardium was used to examine 18 patients with systemic right ventricles: 7 with a single right ventricle who have undergone the Fontan procedure (age, 38.8±8.9 months) and 11 with transposition of the great arteries who have undergone an atrial inversion operation (age, 16.3±3.9 years). The motion of the intersection points was tracked through systole to determine regional twist and radial shortening. Shortening rates also were evaluated. Finite strain analysis was applied to the grid lines using Delaunay triangulation, and the two-dimensional strain tensor and principal E1 strains were derived for the various anatomic regions. Basal and apical short-axis planes through the ventricular wall were categorized into four distinct regions spaced equally around the circumference of the slice. We observed the following results. (1) Strain was greatest and heterogeneity of strain was least in patients with transposition of the great arteries who were status post atrial inversion operation (six of eight regions). Marked differences were noted in the distribution of strain within a given region, from endocardium to epicardium, and from atrioventricular valve to apical plane between patient subtypes and those with a normal left ventricle. (2) Contrary to the normal subject studied by the use of the same method, for both patient subtypes, there was counterclockwise twist in one region, clockwise twist in the posterior or inferior wall, and a transition zone of no twist at which the two regions of twist met. Normal human adult left ventricles studied in short-axis twist uniformly counterclockwise as viewed from apex to base. (3) Radial inward motion was greatest in the superior wall of both types of systemic right ventricle. The inferior walls of Fontan patients and the posterior (ie, septal) walls of patients with transposition of the great arteries, status post atrial inversion, moved paradoxically in systole. The shortening rate at the atrioventricular valve of patients with transposition of the great arteries, status post atrial inversion, was significantly lower than at the apex or in Fontan patients. Conclusions: Marked differences in regional wall motion and strain were demonstrated in systemic right ventricles, depending on whether a left ventricle was present to augment its function. Ventricular-ventricular interaction appears to play an important role in affecting the biomechanics of systemic right ventricles. These observations were markedly different from those in the normal systemic left ventricle. These techniques demonstrate tools with which we can begin to evaluate surgical outcomes using regional myocardial mechanics and may provide a clue to single right ventricle failure.
Keywords: contraction; Fontan procedure; transposition of the great arteries; ventricles

Treatment options for hypoplastic left heart syndrome: a mother's perspective. - Swanson, L.T. (Critical care nurse, 1995)
The congenital heart defect of HLHS is nearly uniformly fatal without intervention. As surgeons gain experience with the techniques the success rates are improving; more infants with HLHS are being offered hope for survival and quality of life. The critical nature of this diagnosis, the relatively new treatment options, and uncertainty of the surgical outcome impose tremendous stress on the parents. Choice of treatment is difficult and should be made in collaboration with the attending physician. Although the first year of my son's life was difficult, the past 5 years have been wonderful. He continues to thrive and enjoy most of the activities other 6-year-olds enjoy. In retrospect, palliative surgery was a good option for him. As both his mother and a cardiac nurse, I recognize that he may once again require surgical intervention, but I am encouraged that medical and surgical advances are being made for children with HLHS.

Comparison of cardiopulmonary adaptation during exercise in children after the atriopulmonary and total cavopulmonary connection Fontan procedures - Rosenthal, M.; Bush, A.; Deanfield, J.; Redington, A. (Circulation, 1995)
Background: There are several potential physiological differences between the atriopulmonary (AP) and the total cavopulmonary connection (TCPC) Fontan circulations. Studies suggest that the TCPC reduces energy loss due to turbulence and may have more dependence on respiratory movement for pulmonary blood flow. We compared cardiopulmonary physiology during rest and exercise in patients who had undergone the AP Fontan procedure with those who had undergone the TCPC Fontan procedure. Methods and Results: Forty-three children were studied more than 6 months after undergoing a Fontan procedure (23 AP and 20 TCPC); 106 healthy children were also studied as a control group. Measurements of effective pulmonary blood flow, stroke volume, arteriovenous oxygen difference, minute ventilation, heart rate, and oxygen and carbon dioxide consumption were made with an Innovision quadrupole mass spectrometer. Data from the control group allowed calculation of z scores for the Fontan groups matched for age, sex, pubertal stage, and body surface area. Maximal exercise performance was equal in the two Fontan groups, but it was below normal. However, adaptation to exercise was different in the Fontan groups. After 9 minutes of exercise, pulmonary blood flow rose less in the AP group than in the TCPC group (P<.01), and the stroke volume in the AP group also tended to be lower (P=.057) and their arteriovenous oxygen difference was significantly greater (P<.01). Although minute ventilation per unit of carbon dioxide production was similar in the Fontan groups at this level of exercise, children in the TCPC group breathed faster by approximately 10 breaths per minute (P<.005). Conclusions: At submaximal exercise, children who had undergone the TCPC Fontan procedure had pulmonary hemodynamics superior to those of children who had undergone the AP procedure, largely because of respiratory adaptation that permitted blood to be 'sucked' into the lungs. To achieve the same maximal exercise performance, children who had undergone the AP procedure had a superior metabolic adaptation to exercise stress.
Keywords: exercise; pediatrics; spectrometry; surgery

Neurodevelopmental outcome of infants with hypoplastic left heart syndrome - Rogers, B.T.; Msall, M.E.; Buck, G.M.; Lyon, N.R.; Norris, M.K.; Roland, J.-M.A.; Gingell, R.L.; Cleveland, D.C.; Pieroni, D.R. (The Journal of Pediatrics, 1995)
The neurodevelopmental outcome of hypoplastic left heart syndrome in infants remains unclear. All 11 survivors of staged surgical repair of hypoplastic left heart syndrome received standardized neurodevelopmental assessments at one regional children's hospital. Seven children (64%) had major developmental disabilities. Quality-of-life outcomes must be considered when management options for children with hypoplastic left heart syndrome are evaluated. (J PEDIATR 1995;126:496-8). © 1995 Mosby, Inc. All rights reserved.

Determinants of survival in pediatric continuous hemofiltration - Smoyer, W.E.; McAdams, C.; Kaplan, B.S.; Sherbotie, J.R. (Journal of the American Society of Nephrology, 1995)
Continuous hemofiltration (CH) is being used in increasing numbers of pediatric intensive care unit patients. Experience with 114 CH treatments in 98 critically ill children from March 1988 to March 1993 is presented in this study. Ages ranged from 1 day to 23 yr (mean ± SE = 7.1 ± 0.7 yr), and 54% of patients were male. Seventeen percent of all treatments were performed in neonates under 1 month of age. The most common primary diagnoses were sepsis and adult respiratory distress syndrome (11 patients each), liver transplantation and hypoplastic left heart syndrome (10 patients each), and hemolytic uremic syndrome (9 patients). The most frequent indications for CH were fluid overload and acute renal failure (42% each). Choices for CH included: continuous arteriovenous hemofiltration (CAVH, 50%), continuous arteriovenous hemodiafiltration (CAVH-D, 23%), continuous venovenous hemofiltration (CVVH, 18%), and continuous venovenous hemodiafiltration (CVVH-D, 9%). Choices for anticoagulation included: none (47%), regional (49%), and systemic (4%). Treatment duration ranged from 1 to 25 days (mean = 5.3 ± 0.4 days). Mean filter life span for 363 filters was 0.94 ± 0.1 filters/patient per day. Despite an overall survival rate of 43%, survival to discharge varied greatly (0 to 100%) among the 24 diagnostic groups: tumor lysis syndrome and systemic lupus erythematosus (3/3 patients each, 100%) hemolytic uremic syndrome (8/9 patients, 89%). This compares with: bone marrow transplantation (0/16 patients, 0%), hypoplastic left heart syndrome (2/10 patients, 20%), and leukemia (1/4 patients, 25%). Survival to hospital discharge was better in patients who did not receive pressors (P < 0.005) and in patients treated with combined ultrafiltration and dialysis (CAVH-D, CVVH-D) compared with ultrafiltration alone (CAVH, CVVH) (P < 0.005), but was not notably affected by patient age, sex, use of anticoagulation, filter life span, blood pump-assisted versus spontaneous CH, or duration of therapy. Filter life span was not affected by use of anticoagulation, but was remarkably longer in patients with arteriovenous versus venovenous CH (P < 0.004). It was concluded that: (1) empirical anticoagulation of patients treated with CH is not necessary; (2) children with a minority of underlying diseases and those requiring pressor support at initiation of CH appear to have relatively poor survival rates despite the technically effective use of CH; and (3) the addition of countercurrent dialysis to routine CH may enhance patient survival to hospital discharge.
Keywords: Anticoagulation; Dialysis; Filter life span; Ultrafiltration

Regional wall motion and strain analysis across stages of Fontan reconstruction by magnetic resonance tagging - Fogel, M.A.; Gupta, K.B.; Weinberg, P.M.; Hoffman, E.A. (American Journal of Physiology - Heart and Circulatory Physiology, 1995)
To determine whether systolic regional wall deformation and motion, which may be used as an index of mechanical function, change with surgical intervention in patients with a functional single ventricle, a noninvasive magnetic resonance tagging technique was used to examine 33 such patients at all stages of Fontan reconstruction. The systolic motion of the intersection points was tracked to determine regional twist and radial shortening. Finite strain analysis was applied to the grid lines, and principal E1 strains were derived. The results were as follows. 1) Fontan and prebidirectional cavopulmonary anastomosis (hemiFontan) groups had the highest compressive strains, and regional heterogeneity of strain was least in the Fontan group. 2) Fontan patients had endocardial/epicardial strain different from the other surgical subgroups as well as the normal left ventricle, while the pre- and post-hemiFontan groups had basal/apical short-axis strain different from Fontan patients and normal subjects. 3) Functional single left ventricles had a different strain distribution across wall regions and surgical subgroup from functional single right ventricles. 4) Contrary to the normal human adult studied by the same method, which twists uniformly counterclockwise, 31 of 33 single ventricles, regardless of ventricular morphology or surgical subgroup, twisted counterclockwise in one region, clockwise in another, and met at a 'transition zone' of no twist, which had the highest strains of all regions. 5) Radial contraction was greatest in the superior walls and least at the inferior walls of single-ventricle patients regardless of morphology. In the Fontan group, the inferior walls moved paradoxically. In conclusion, markedly different strain characteristics are noted at each stage of Fontan reconstruction, across various wall regions, and between ventricular morphological groups. Differences in regional wall motion were demonstrated in functional single ventricles throughout Fontan reconstruction regardless of morphology, and differences in associated strains and radial contraction were noted across various wall regions and surgical subgroups. These may play an important role in the energetics of the heart and the long-term viability of the single ventricle.
Keywords: congenital heart disease; contraction; magnetic resonance imaging; twist

Oxygen uptake transient kinetics during constant-load exercise in children after operations of ventricular septal defect, tetralogy of Fallot, transposition of the great arteries, or tricuspid valve atresia - Gildein, P.; Mocellin, R.; Kaufmehl, K. (The American Journal of Cardiology, 1994)
Cardiovascular function accounts for endurance performance and, by a rapid increase in oxygen supply at the onset of exercise, contributes to short-lasting intensive exertion prevailing in many kinds of sports activities. This study determined the time for oxygen uptake (V̇O2) to reach one half of its asymptotic level above rest, and the respective oxygen deficit following the onset of a constant-load exercise corresponding to 80% to 90% of the maximal oxygen uptake (V̇O2max) in 35 children after surgical closure of a ventricular septal defect, after corrective surgery for tetralogy of Fallot, or after the Senning, Mustard, or Fontan procedures. In addition, V̇O2max and maximal Mood lactate were determined. The half-time of V̇O2 response and oxygen deficit was lowest in patients after closure of a ventricular septal defect, whereas children had the most unfavorable V̇O2 transient kinetics after Fontan operation or with a transannular patch after correction of tetralogy of Fallot. A negative correlation was evaluated between half-time of V̇O2 response and V̇O2max, whereas maximal blood lactate varied independently of V̇O2max. It is concluded that many children with decreased V̇O2max after cardiac surgery also have unfavorable V̇O2 transient kinetics. In addition to being less qualified for endurance performance, they are also less prepared for short-lasting intensive energy expenditure. Therefore, the primary aim of training in these children is to improve the economy of motion of the respective tasks. © 1994.

Systolic and diastolic function in tricuspid valve atresia before the fontan operation - Sandor, G.G.S.; Patterson, M.W.H.; LeBlanc, J.G. (The American Journal of Cardiology, 1994)
Systolic and diastolic function were assessed at preoperative cardiac catheterization in 6 patients with classic tricuspid atresia and were compared with those in control subjects. All patients had systemic-to-pulmonary shunts. Left ventricular end-systolic and end-diastolic volumes and masses were significantly larger in the patient group; stroke volume and the ratio of volume to mass were also higher, but not significantly. Mean end diastolic, peak systolic and end-systolic pressures were similar. Mean stress at end-systole and peak systole were significantly higher in the patient group. Operant chamber stiffness tended to be lower than normal, but was not statistically significant, and myocardial stiffness was normal for the patient group also. Indexes of systolic function were compared. The rate-corrected mean velocity of fiber shortening in the patient group was tower and its relation with stress at end-systole was variable with 4 abnormal patients. The ratio of stress at end-systole/end-systolic volume was significantly lower in patients. The duration of hospital stay did not correlate with end-diastolic volume or any parameter. Thus, this study found abnormalities of load-dependent and independent indexes of systolic function with normal diastolic function in young preoperative patients with tricuspid atresia. © 1994.

Prediction of quality of life at long-term follow-up after fontan operation by scoring risk factors - Nakazawa, M.; Park, I.; Imai, Y.; Momma, K.; Sawatari, K. (JAPANESE CIRCULATION JOURNAL, 1994)
Many factors will determine the quality of life at long-term follow-up after the Fontan operation. We tried to predict the long-term outcome of modified Fontan operation based on the combined assessment of various preoperative data. The preoperative condition was evaluated by a scoring system in which multilevel scores (from zero to 8 points) were given to a total of 14 morphological and physiological factors according to the contribution of each factor to mortality. The major factors were the association of the extracardiac total anomalous pulmonary venous connection, pulmonary arterial vascular resistance, mean pulmonary arterial pressure, PA index, ejection fraction of the main ventricle, and creatinine clearance. Points for each factor were determined according to surgical mortality, with zero points indicating no increased risk. The total score, i.e., the sum of the points for each item, in each patient was analyzed in relation to the patient's quality of life over a long-term follow-up, as evaluated by questionnaires. Twenty-six of 29 patients with scores of 5 or less showed normal or almost normal life long after the operation, whereas 5 of 10 with higher scores had restricted physical and daily activity. In conclusion, good preoperative condition predicts a good quality of life long after the Fontan operation. In addition, the concept of taking into account all possible risk factors as a comprehensive indicator may be useful in predicting long-term results. © 1994, The Japanese Circulation Society. All rights reserved.
Keywords: Long-term follow-up; Modified Fontan procedure; Quality of life

Infant heart transplantation: A survey of physician beliefs - Higgins, S.S.; Paul, S.M.; Hardy, C.E.; Ternullo-Retta, C.; Affonso, D. (Journal of Heart and Lung Transplantation, 1994)
Heart transplantation in infancy has become the fastest growing area in pediatric heart transplantation. Infant heart transplantation presents a profoundly complex decision-making situation for parents. There is a relationship between physician beliefs and their manner of presenting heart transplantation options to parents. The purpose of this study was (1) to determine the beliefs of physicians about neonatal heart transplantation, (2) to define their perceptions about their role in counseling parents about heart transplantation, and (3) to evaluate the differences of beliefs by physician specialties (pediatric cardiologists, noenatologists, and pediatricians) and practice settings (university, private, health maintenance organization). A questionnaire was designed to survey 117 physicians on their beliefs about heart transplantation. Findings revealed significant differences related to beliefs: (1) infant heart transplantation is still experimental (pediatric cardiologists, 56%; neonatologists, 85%; pediatricians, 63%; p < 0.05), (2) neonatal heart transplantation is acceptable for fatal heart disease (pediatric cardiologists, 86%; neonatologists, 73%; pediatricians, 63%; p < 0.05), (3) newborn heart transplantation should be presented negatively to protect parents from potential negative consequences on their quality of life (pediatric cardiologists, 14%; neonatologists, 33%; pediatricians, 48%; p < 0.05); (university, 25%; private, 18%; health maintenance organization, 61%; p < 0.05), and (4) infants with hypoplastic left heart syndrome should not be treated (university, 28%; private, 23%; health maintenance organization, 55%; p < 0.05). Though it is critical to impart information to parents with a fair representation of infant heart transplantation, we conclude that many physicians surveyed had a knowledge deficit or bias about the current state of the art of infant heart transplantation.

Congenital heart diseases in Bohemia. Epidemiologic data - Samanek, M. (Cor et Vasa, 1994)
The prevalence rate of cardiac malformations (CM) in Bohemia is 6.64/1000 live births and 21/1000 stillbirths. The most common were ventricular and atrial septal defects, pulmonary and aortic stenoses in live-born infants, and ventricular septal defect, hypoplastic left heart syndrome and transposition in stillborns. Seasonal and regional differences of the prevalence were found in the whole cohort and in individual forms of CM. The boys to girls ratio was 1.09:1 in live births and 1.3:1 stillbirths. Boys predominated in double outlet right ventricle, transposition and aortic stenosis and girls in patent ductus arteriosus, Ebstein's anomaly and truncus arteriosus. 35.3% of all CM, i.e., 2.36/1000 of all live births presented with life-threatening symptomatology or died. Of all children born with CM, 78.3% reached the age of 10. The 10-year survival rate was highest in pulmonary stenosis, atrial septal defect, aortic stenosis, ventricular septal defect and patent ductus arteriosus and lowest in hypoplastic left heart, truncus arteriosus and pulmonary atresia. Only 17.7% of suviving children are on medication. Physical activity is normal in 65.4%, slightly reduced in 28.4%, and reduced in 5.9% of long-term survivors.
Keywords: Boys:girls ratio; Cardiac malformation; Children; Critical heart disease; Prevalence; Quality of life; Stillborns; Survival

Bless the babies: One hundred fifteen late survivors of heart transplantation during the first year of life - Bailey, L.L.; Gundry, S.R.; Razzouk, A.J.; Wang, N.; Sciolaro, C.M.; Chiavarelli, M.; Branson, B.; Zorn, E.; Eby, W.; Allard, M.; Applegate, R.; Brauer, S.; et al. (Journal of Thoracic and Cardiovascular Surgery, 1993)
There is a rapid growth of interest in heart transplantation therapy during early infancy. From 10% to 25% of the infants who are listed for transplantation annually have died while awaiting a donor heart. There has been no significant trend in this variable. Since November 1985, 140 consecutive orthotopic transplantation procedures were performed in 139 infants who were from 3 hours to 12 months of age. Indications for transplantation included hypoplastic left heart syndrome (63%), other complex structural anomalies (29%), myopathy (6.5%), and tumors (1.5%). Most recipients had ductus-dependent circulation and received continuous infusion of prostaglandin E1. Heart donors were usually victims of trauma, sudden infant death, or birth asphyxia. A donor-recipient weight ratio of 4.0 or less was found to be acceptable. The amount of time the graft underwent cold ischemia, ranged from 64 to 576 minutes. The procurement process was facilitated by a single dose of cold crystalloid cardioplegic solution and cold immersion transport. Profound hypothermic circulatory arrest was used for graft implantation. One hundred twenty-four (89%) recipients survived transplantation and were discharged from the hospital. There were 9 late deaths, which resulted in an 83% overall survival. The 5-year actuarial survival is 80%. The survival among newborn recipients (n = 60) at 5 years is 84%. Chronic immunomodulation was cyclosporine-based and steroid-free. Surveillance was noninvasive and relied heavily on echocardiography, electrocardiography, and clinical intuition. There was one documented late lethal infection, tumor was not encountered, and coronary occlusive disease was known to exist in only one long-term survivor. We concluded that transplantation results in excellent life quality and is a highly effective and durable therapy when applied during early infancy.

Pediatric cardioplegic techniques. - Drinkwater, D.C.; Laks, H. (Seminars in thoracic and cardiovascular surgery, 1993)
We use warm induction and reperfusion with amino acid enhancement on all neonates and preoperatively stressed patients to induce arrest without contracture and to replete high-energy substrates. Blood cardioplegia is used in all age groups. We then employ hypothermia in the majority of patients (all neonates), ranging from deep (18 degrees C), to moderate (26 degrees to 28 degrees C), with warm or near normothermia used in only simpler anatomic repairs. The clear benefits of hypothermia in conferring additional cardiac and systemic ischemic protection along with the relatively greater ease of cooling and rewarming in the pediatric patient warrant its continued use in the majority of open-heart cases. Calcium levels are maintained in the 0.3 to 0.5 mM/L range during the conduct of the operation and reperfusion phase. Before removal from bypass, calcium is administered through either bolus or continuous drip technique to provide a normocalcemic level of 1 to 1.2 mM/L. This close attention is particularly important in the neonate to avoid contracture injuries and to maximize cardiac function, and is warranted if citrate-phosphate-dextrose (CPD)-containing transfusion or prime components are used. Preoperative evaluation for aortopulmonary collaterals with coil embolization is routinely performed, and is particularly important in single ventricle physiology where preserved myocardial function is so vital to a favorable outcome. The opportunity to perform some surgeries off bypass, such as on the RV outflow tract, may be used whenever it represents a viable alternative in very young or ill patients. Similarly, the majority of Glenn shunts, for example, are performed using a caval-RA shunt without formal cardiopulmonary bypass.(ABSTRACT TRUNCATED AT 250 WORDS)

Case study: infant transplantation: a change of heart. - Feliciano, S.M.; Girard, N.J.; Calhoon, J.H. (Seminars in perioperative nursing, 1992)
The majority of infant heart transplants are for the correction of hypoplastic left heart syndrome (HLHS). This article will describe the preoperative, intraoperative, and postoperative care for perioperative and pediatric intensive care areas implemented for HLHS infant heart transplantation at Medical Center Hospital, San Antonio, TX. The surgical procedure is given. Dimensions of psychosocial care and education of the parents are briefly described.

Bidirectional cavopulmonary anastomosis in congenital heart disease. Functional and clinical outcome - Giannico, S.; Santoro, G.; Marino, B.; Cicini, M.P.; Marcelletti, C. (Herz, 1992)
The bidirectional cavopulmonary anastomosis is a surgical procedure suitable for patients with cyanotic congenital heart disease and univentricular physiology. This operation is able to increase the effective pulmonary blood flow without any additional load on the cardiac work and without any further distortion on the pulmonary artery branches. The cavopulmonary anastomosis can represent the first stage for patients destined for Fontan repair or a definitive palliative operation in high risk Fontan candidates. In order to test the hypothesis of a definitive palliation by cavopulmonary anastomosis in this kind of patients, we evaluated the hemodynamic data before and after this surgical approach and compared these data with their clinical and functional outcome. We evaluated 74 patients submitted to bidirectional cavopulmonary anastomosis by either hemodynamic or functional evaluation. End-diastolic and end-systolic ventricular volumes were significantly reduced by bidirectional cavopulmonary anastomosis (p < 0.0005). Despite these data and a normal ambulatory ECG, spirometry and echocardiographic analysis, the stress test showed discouraging results. In fact, mean work time and peak heart rate were significantly different from normal values showing an impaired functional capacity of these children. In conclusion we think that bidirectional cavopulmonary anastomosis can not be considered an adequate definitive palliation but it represents a very good stage to preserve the pulmonary arteries and to prepare the systemic ventricle towards the Fontan repair.

Ventricular performance before and after fontan repair for univentricular atrioventricular connection: Angiographic and radionuclide assessment - Akagi, T.; Benson, L.N.; Green, M.; Ash, J.; Gilday, D.L.; Williams, W.G.; Freedom, R.M. (Journal of the American College of Cardiology, 1992)
Objectives. This study was designed to evaluate changes in ventricular volume, mass and cardiac function before and after creation of an atrial to pulmonary connection in patients with a univentricular atrioventricular connection. Background. Intact systolic and diastolic performance is critical for successful establishment of an atrial dependent circulation, and few studies are available comparing cardiac performance before and after creation. Methods. With the use of radionuclide blood pool imaging and ventricular cineangiography, 54 patients (mean age 6.4 ± 3.4 years) were studied. Twenty-eight patients were investigated preoperatively and 36 > 1 year after repair and compared with a control population. Results. Before operation, end-diastolic volume and wall mass were significantly increased compared with those of control subjects; however, the mass/volume ratio was normal (1.08 ± 0.31 g/ml for the preoperative group; 0.97 ± 0.19 for control subjects). Although end-diastolic volume returned to normal after the procedure, wall mass remained elevated and contributed to an elevated mass/volume ratio (1.20 ± 0.38 g/ml). After the procedure, systemic vascular resistance index was significantly elevated compared with that before surgery or with that of control subjects (1,199 ± 373,2,120 ± 645, 1,556 ± 275 dynes·s· cm-5 ·m2: pre- and posirepair and control subjects, respectively). Radionuclide studies demonstrated that preoperative ejection fraction (52 ± 9,50 ± 9,60 ± 8%), peak ejection (2.58 ± 0.66, 2.95 ± 0.81, 3.73 ± 0.70 EDV/s) and peak filling rates (2.84 ± 0.75, 2.75 ± 0.79, 3.84 ± 0.51 end-diastolic volumes [EDV/s]) were significantly reduced compared with those of contral subjects and remained so after surgery. Conclusions. These data suggest that systolic and diastolic function is depressed preoperatively in these patients, remains unchanged after the creation of an atrial-dependent circulation and is associated with an increased systemic vascular resistance. Long-term issues addressing preservation of cardiac function need to be prospectively studied. © 1992.

Intermediate term results of infant orthotopic cardiac transplantation from two centers - Backer, C.L.; Zales, V.R.; Harrison, H.L.; Idriss, F.S.; Benson Jr., D.W.; Mavroudis, C. (Journal of Thoracic and Cardiovascular Surgery, 1991)
Orthotopic cardiac transplantation has become established for selected infants with severe forms of congenital heart disease. This study reviews the combined experience and intermediate term results of infants undergoing orthotopic cardiac transplantation from Children's Memorial Hospital, Chicago, and Kosair Children's Hospital, Louisville. From June 1986 through December 1989, 20 orthotopic cardiac transplantations were performed in 19 patients. Sixteen patients had variants of hypoplastic left heart syndrome. One infant had anomalous origin of the left coronary artery with severe ischemic cardiomyopathy. Two infants had aortic stenosis with endocardial fibroelastosis, and one had extracorporeal membrane oxygenation as a bridge to transplantation. Immunosuppression included cyclosporine, azathioprine (Imuran), and corticosteroids with an effort to wean the patients from steroids by 6 months to 2 years. Three early deaths resulted - from technical errors in two patients and from hyperacute rejection in one patient at 3 days. Four late deaths have occurred. Two patients died at 2 and 13 months of acute rejection. One patient died at 15 months of acute rejection after retransplantation. One patient died at 7 months of respiratory syncytial viral pneumonia. The remaining 12 patients are surviving 5 to 47 months (mean 20 months) after orthotopic cardiac transplantation. Rejection surveillance in the first 6 months is by clinical signs supplemented by echocardiography, electrocardiography, and cell cycle analysis; endomyocardial biopsy is used after 6 months of age. For the cumulative series, 24 episodes of suspected rejection have been treated during 277 at-risk patient months with intravenous methylprednisolone (Solu-Medrol) (n = 18) and monoclonal antibody (OKT3) (n = 6), for an incidence of 1.04 episodes of rejection per patient per year. Serious posttransplantation infections including endocarditis, catheter sepsis, meningitis, and colonic perforation were successfully treated in four patients. Subjectively, their quality of life is excellent as shown by normal growth and development milestones and a low hospital readmission rate (1.4 episodes per patient per year). These encouraging intermediate term results warrant continued application of infant orthotopic cardiac transplantation for severe forms of congenital heart disease.

Effect of right ventricular anatomy on the cardiopulmonary response to exercise: Implications for the fontan procedure - Rhodes, J.; Garofano, R.P.; Bowman Jr., F.O.; Grant, G.P.; Bierman, F.Z.; Gersony, W.M. (Circulation, 1990)
Incorporation of the right ventricle (RV) into the pulmonary circulation of patients with tricuspid atresia undergoing a Fontan procedure has been advocated. The consequences of this approach on the exercise function of these patients was studied by examining the effects of progressive and steady-state bicycle exercise tests performed by 11 patients with right atrial (RA)-RV Fontan anastomoses, seven patients with RA-pulmonary artery (PA) Fontan anastomoses, 13 patients after repair of tetralogy of Fallot, and 34 normal control patients. All patients were in New York Heart Association class I. The exercise function of the patients undergoing RA-RV and RA-PA Fontan procedures were similar. They achieved peak work loads 60% and 67% of control and peak oxygen consumptions 60% and 64% of control, respectively. Both groups also displayed excessive ventilation, elevated dead space/tidal volume ratios, and depressed cardiac output during steady-state exercise. In contrast, tetralogy of Fallot patients achieved peak work loads and oxygen consumptions 83% of control and maintained normal cardiac outputs and dead space/tidal volume ratios during steady-state exercise. These results suggest that the presence of an RV within the pulmonary circulation of the Fontan patient does not result in improved exercise function. This may be due to the development of obstructive gradients across the RA-RV conduits during exercise or to the RV's negative effect on left ventricular compliance. Moreover, in contrast with the postoperative tetralogy of Fallot patient, the hypoplastic RV of tricuspid atresia may not have sufficient myocardium to assume the active pumping function required by exercise.
Keywords: Single ventricle; Tetralogy of fallot; Tricuspid atresia

Impact of Fontan operation on left ventricular size and contractility in tricuspid atresia - Gewillig, M.H.; Lundström, U.R.; Deanfield, J.E.; Bull, C.; Franklin, R.C.; Graham Jr., T.P.; Wyse, R.K. (Circulation, 1990)
Left ventricular dimensions and contractility were determined by echocardiography in 33 patients with tricuspid atresia in 1985 and again in 1988. Eight patients remained palliated throughout the 3-year period; neither the left ventricular end-diastolic diameter (153±15% of normal vs. 157±19%, p=NS) nor a load-independent index of contractility (rate-corrected velocity of shortening [VCFc]/end-systolic meridional stress [ESSM]) changed. Eleven patients underwent a Fontan operation during the study and were reevaluated at least 6 months after surgery; left ventricular dimension decreased (130±15% vs. 114±19%, p<0.001), and the contractility index VCFc/ESSM improved (p<0.05). Fourteen patients had undergone a Fontan operation 0.9-9.5 years (mean, 4.2 years) before initial examination in 1985. Over the 3-year period, left ventricular dimensions did not change (121±17% vs. 118±11%, p=NS), but the contractility index showed significant improvement (p<0.01). Eight additional patients were studied just before and after a Fontan operation to examine the early effects of surgery. Left ventricular dimensions decreased from 130±14% to 100±13% by 10 days p<0.001) with no further change at 2 months. An inappropriate degree of ventricular hypertrophy was observed in only the early postoperative period. Successful Fontan repair results in rapid reduction of left ventricular size, followed by regression of hypertrophy to a normal mass-to-volume ratio. Operating at more favorable dimensions and loading conditions results in an early increase in left ventricular contractility, which further improves in the medium term follow-up.
Keywords: Contractility; Fontan procedure; Volume loading

Assessement of ventricular contractile state and function in patients with univentricular heart - Sano, T.; Ogawa, M.; Taniguchi, K.; Matsuda, H.; Nakajima, T.; Arisawa, J.; Shimazaki, Y.; Nakano, S.; Kawashima, Y. (Circulation, 1989)
To elucidate the ventricular contractile state and function in patients with univentricular heart, the ventricular volume, mass, ejection phase index, and wall stress were evaluated with biplane ventriculography and pressure measurement in 41 patients: 18 with left ventricular (LV) type (age, 6.4 ± 6.1 years) and 23 with right ventricular (RV) type (age, 5.7 ± 4.1 years), and data from patients with univentricular heart were compared with data from 19 normal control subjects (age, 7.2 ± 4.3 years). Althought the end-diastolic and end-systolic volumes were significantly greater in both types of univentricular heart than in the normal control group, the volumes for the LV and RV type patients did not differ from each other. The ejection fraction (EF) was depressed in both patient types of univentricular heart and was significantly (p < 0.005) lower in the RV type than in the LV type patients (0.56 ± 0.05 for LV type, 0.50 ± 0.07 for RV type, and 0.64 ± 0.03 for the control group). The ventricular mass was larger in both patient types of univentricular heart than in that of the control group, whereas the ratio of ventricular mass to end-diastolic volume was significantly (p < 0.001) lower in the RV type patients than in the LV type patients and the control group (0.79 ± 0.18 g/ml for LV type, 0.51 ± 0.10 for RV type, and 0.82 ± 0.13 for control group). End-systolic stress was significantly elevated in both types of univentricular heart (241 ± 45 for LV type, 328 ± 52 for RV type, and 205 ± 26 kdynes/cm2 for the control group) and significantly (p < 0.001) greater in the RV type than in the LV type patients. There was a significant inverse correlation (p < 0.001) between end-systolic stress and the ratio of mass to end-diastolic volume in all the patients. In 27 patients (12 patients for LV type, 15 for RV type) the mean normalized systolic ejection rate corrected for heart rate (MNSERc) clearly fell below the 95% confidence limit of the normal end-sysolic stress-MNSERc relation. The end-systolic stress:end-systolic volume ratio was also significantly depressed in both patient types of univentricular heart volume ratio (3.49 ± 1.77 for LV type, 40.7 ± 2.13 for RV type, and 7.20 ± 1.32 for the control group). In these variables, however, there were no significant differences between LV and RV type patients of univentricular heart. Thus, despite the absence of significant difference either in preload or myocardial contractile function between LV and RV type patients, afterload was significantly increased in RV type patients compared with LV type patients. Therefore, impaired ejection performance in RV type compared with that in LV type patients may be responsible for afterload mismatch caused by inadequate ventricular hypertrophy rather than by myocardial contractile dysfunction.

Metabolic response to surgery in children - Bevan, J.C. (Bailliere's Clinical Anaesthesiology, 1989)
A metabolic response to surgery has recently been confirmed in children. It is characterized by hyperglycaemia, suppression of the insulin response and increased catecholamine secretion during surgery. The pattern of hormonal and metabolic derangements is similar to that of the adult response, but changes are more marked and reverse more quickly in the postoperative period. The hormonal changes show considerable variation in the neonate. Premature neonates do not exhibit an insulin response to hyperglycaemia and this is also less predictable in the full-term neonate than in older children. The relationship of the severity of surgery to the degree of hyperglycaemia is less clear than in the adult, partly because of the wide variation in clinical conditions of measurement. A scoring system has been devised to assess the severity of surgery as minor, moderate or severe so that data can be interpreted in a more standardized manner. Observations during cardiac surgery with cardiopulmonary bypass in neonates confirm that severe surgery is associated with exaggerated and prolonged increases in plasma glucose and catecholamine concentrations and insulin suppression. The stress response to surgery can be obtunded by the addition of volatile anaesthetic agents or opiates to general anaesthetic techniques using oxygen, nitrous oxide and muscle relaxants. Local anaesthetic and regional blockade also modify the responses in conscious and unconscious patients. A possible relationship between pain perception and the stress response to surgery may have implications for changes in perioperative management. The possible benefits of inhibiting these stress responses during surgery in children need to be determined by further morbidity and mortality studies. Anaesthesia and surgery initiate metabolic and hormonal responses which result in a clearly defined clinical sequence of reactions in adults (Moore and Ball, 1952; Moore, 1953; Allison et al, 1969; Wright et al 1974; Lacoumenta et al, 1986; Simpson et al, 1987; Diltoer and Camu, 1988; see Chapter 2). Substrate mobilization produces an initial catabolic phase with oliguria, nitrogen loss, sodium retention and potassium excretion, to a degree which is proportional to the severity of the surgical procedure. During normal convalescence this is reversed within 1-2 days. This is followed by an anabolic phase of water diuresis, marked sodium excretion and decreased nitrogen and potassium losses, which restores positive (Anand et al, 1987 a, b). Similarly, Hansen and Hickey (1986) are finding that the mortality of neonates undergoing correction of hypoplastic left heart syndrome, using a high dose fentanyl and pancuronium technique, is improving. Further morbidity and mortality studies are needed to substantiate the merits of the abolition of the stress response to surgery in children. © 1989 Baillière Tindall. All rights reserved.

Fontan Hemodynamics - PASQUE, M.K. (Journal of Cardiac Surgery, 1988)
Right atrial‐pulmonary artery connection places the pulmonary circulation in series with the systemic circulation rather than the single ventricular “parallel” circulatory arrangement that usually is present prior to repair. The accompanying central cardiac shunt and volume overload physiology are eliminated. Favorable changes in ventricular dimension, ventricular wall stress, cardiovascular efficiency, relative systemic perfusion, and arterial oxygen saturation should result. The ongoing myocardial injury associated with the single‐ventricle volume overload is presumably arrested and repair is initiated to a variable degree. Some candidates for right atrial‐pulmonary artery connection may not benefit from repair because of irreversible ventricular injury. More accurate indices of systolic and diastolic ventricular function should be applied to this difficult group of borderline patients to further define potential for myocardial recovery and, therefore, candidacy for Fontan repair. Copyright © 1988, Wiley Blackwell. All rights reserved

Pediatric heart transplantation at St. Christopher's Hospital for Children - Dunn, J.M.; Cavarocchi, N.C.; Balsara, R.K.; Kolff, J.; McClurken, J.; Badellino, M.M.; Vieweg, C.; Donner, R.M. (Journal of Heart Transplantation, 1987)
Heart transplantation has become the standard of care for patients with end-stage heart failure. The efficacy and therapeutic advantages of transplantation in the pediatric population have not been fully determined. Between March 1985 and September 1986, nine pediatric heart transplantations were performed; the ages ranged from 39 day to 19 years; weight ranged from 2.3 to 100 kg. The underlying disease was acquired cardiomyopathy (four patients); cardiomyopathy caused by congenital mitral valve disease (two patients); unresectable fibroma of the left ventricle in a newborn (one patient); hypoplastic left heart syndrome (one patient); and hypertrophic obstructive cardiomyopathy (one patient). Initial immunosuppression therapy consisted of cyclosporine, prednisone, and antithymocyte globulin. Recently, newer protocols have evolved through experience. Seven patients survived the perioperative period and had follow-up from 1 to 19 months, for a total of 41 transplant months. Rejection occurred at a rate of 1.4 episodes per month in children compared with 0.8 episodes per month in our adult patients. There was no statistical difference in the number, severity, or timing of rejection episodes in the pediatric versus adult population. Major complications included cyclosporine-induced seizures in two patients, mild hypertension in two, five infectious episodes (three bacterial and two viral), and three late deaths. All children who survived are in New York Heart Association functional class I with no developmental delays. This series is heavily weighted with children (33% less than age 1 year). Early results demonstrate that pediatric and infant heart transplantation is technically practical. Improved results are to be expected with additional experience and further modification of adult protocols to assure patient growth and minimize the high infection rate.

Analysis of the effects of Blalock-Taussig shunt on ventricular function and the prognosis in patients with single ventricle - Kuroda, O.; Sano, T.; Matsuda, H.; Nakano, S.; Hirose, H.; Shimazaki, Y.; Kato, H.; Taniguchi, K.; Ogawa, M.; Kawashima, Y. (Circulation, 1987)
Twenty-four patients with single ventricle, six with single left (SLV) and 18 with single right (SRV) ventricle, who received a Blalock-Taussig (BT) shunt at an average age of 3.2 years were studied. Ventricular function was assessed angiographically by end-diastolic volume index (EDVI) and ejection fraction (EF), and attempts were made to measure ventricular mass index (VMI) and VM/EDV. In 14 patients, the preoperative and postoperative results (average 2.4 years after placement of BT shunt) were compared in SLV (n = 5) and SRV (n = 9) groups. The SLV group showed significant increases in EDVI, VMI, and VM/EDV without a significant change in EF. The SRV group showed significant increases in EDVI and VMI, while EF decreased and VM/EDV was unchanged. Late death from congestive heart failure occurred in five patients with SRV. Three patients with atrioventricular valve regurgitation suffered late death. Among the patients with SRV, the late death group had significantly lower preoperative EF and VM/EDV compared with the survivors (n = 13). All of those with a preoperative EF of less than 0.50 and a VM/EDV of less than 0.35 g/ml suffered late death. In summary, patients with SRV appear to fail to develop adaptational hypertrophy to volume loading after the BT shunt procedure, with concomitant depression in ventricular pump function. Also, late cardiac failure seems likely to develop when low EF and VM/EDV are present preoperatively.

Palliative Mustard operation: an expanded horizon - Corno, A.F.; Parisi, F.; Marino, B.; Ballerini, L.; Marcelletti, C. (European Journal of Cardio-Thoracic Surgery, 1987)
From March 1982 to December 1983, five patients with a mean age 7 years (4 months-16 years) underwent a palliative Mustard operation for complex cardiac anomalies. The diagnoses were: univentricular heart with pulmonary vascular obstructive disease (PVOD) (2 cases); criss-cross heart with intact atrial septum, ventricular septal defect (VSD), transposition of the great arteries (TGA) and moderate pulmonary stenosis: isolated atrioventricular discordance with VSD; TGA, diminutive right ventricle and multiple VSDs. Cardiac catheterization showed unfavourable direction of flow: the oxygen saturation in the aorta was lower than in pulmonary artery, with a mean difference of 13.5% (range 6% to 30%). In no case was anatomical or physiological repair considered advisable because of the unfavourable intracardiac anatomy or the presence of PVOD. In two patients the atrial rerouting was accompanied by pulmonary artery banding. There were no hospital or late deaths in a mean follow-up of 36 months (range 29 to 50 months). The mean post-operative arterial oxygen saturation was 95.4% (range 92% to 99%). © 1987.
Keywords: Congenital heart disease; Palliative Mustard operation

Left ventricular wall stress and contractile function in childhood: Normal values and comparison of Fontan repair versus palliation only in patients with tricuspid atresia - Graham Jr., T.P.; Franklin, R.C.G.; Wyse, R.K.H.; Gooch, V.; Deanfield, J.E. (Circulation, 1986)
Left ventricular wall stress and contractile function were determined by echocardiographic methods in 23 patients with tricuspid atresia after palliation only (group 1), in 19 patients after Fontan repair (group 2), and in 24 age-matched normal subjects. End-diastolic dimension was increased above normal in both groups with tricuspid atresia (group 1 [mean ± SEM] 141 ± 4%, group 2 129 ± 5% of normal; both p < .001) but were not different from each other. Left ventricular end-diastolic volume and wall mass also were increased above normal in both groups (group 1, 126 ± 9 ml/m2 and 194 ± 19 g/m2, respectively, p < .001 and p < .004; group 2, 80 ± 7 ml/m2 and 128 ± 10 g/m2, p < .02 and p < .001), and group 2 patients showed significantly lower values than group 1 patients (p < .001 and p < .004). Meridional end-systolic stress was increased above normal in both groups with tricuspid atresia but was not different between groups (normal, 43 ± 3 g/cm2; group 1, 56 ± 5 g/cm2, p < .02; group 2, 59 ± 7 g/cm2, p < .001). Contractile function estimated by rate-corrected circumferential fiber shortening velocity was abnormal in nine of 23 (39%) group 1 patients and in five of 19 (26%) group 2 patients (percentages not different from each other by nonparametric testing). Contractile function was depressed in one of 11 group 1 patients under 5 years old and in eight of 12 over 5.3 years old. Fontan repair in patients with tricuspid atresia resulted in less volume overload and hypertrophy than palliation only, but an increased afterload and abnormal contractile function persisted in a significant number of patients. Abnormal function is prevalent in patients older than 5 years with palliation only. Prospective data are needed in an attempt to clarify causes of myocardial dysfunction in patients with tricuspid atresia.

Tricuspid atresia in adolescents and adults: Current state and late complications - Warnes, C.A.; Somerville, J. (Heart, 1986)
Twenty nine patients aged 15-35 years (mean 23) with tricuspid atresia and normally related great arteries were studied; 20 are alive. Ten patients who had had a Fontan operation (group 1) were compared with 10 patients with palliative shunts (9) or no surgery (1) (group 2). Patients were graded according to their ability to lead a normal life (ability index). Patients in group 1 tended to have a better ability index, a greater exercise capacity, and fewer social and extracardiac problems than those in group 2. The mean left ventricular ejection fraction measured by radionuclide angiography was the same in both groups. Arrhythmias were equally common in both groups; they appear to be age related and they occur independently of left ventricular function.

Left ventricular function in tricuspid atresia: A radionuclide study - Hurwitz, R.A.; Caldwell, R.L.; Girod, D.A.; Wellman, H. (Journal of the American College of Cardiology, 1986)
Left ventricular function was evaluated by radionuclide angiocardiography in patients with tricuspid atresia before and after the Fontan operation. Ejection fraction was 0.54 ± 0.13 in 29 patients without the Fontan procedure and 0.56 ± 0.14 in 14 postoperative patients. Group means were not statistically different, but both were less than normal values for the institution (p < 0.001). Function did not correlate significantly with age or aortic oxygen saturation. Serial studies demonstrated little change in eight of nine patients examined over 1 to 3 years preoperatively. From the preoperative group of nine patients with abnormal ejection fraction, three underwent surgery, with two survivors. Although 5 of 14 patients had abnormal systolic function after the Fontan operation, only 1 was symptomatic. Depressed response to isometric exercise was found in two patients with a normal ejection fraction at rest. Group systolic function after Fontan surgery did not correlate significantly with age at surgery but all patients were operated on at more than 5 years of age. Of seven patients studied both preoperatively and postoperatively two had an increase and three a decrease in ejection fraction. The trend in these seven studied serially after surgery was toward early improvement in ejection fraction. This study shows variability in left ventricular performance in patients with tricuspid atresia before and after surgery. Individuals undergoing the Fontan procedure after 5 years of age do not necessarily have an increase in ejection fraction over preoperative values, and may even have a decrease. Serial improvement over early postoperative results may be expected, without significant deterioration, during the next 1 to 3 years. © 1986, American College of Cardiology Foundation. All rights reserved.

Transthoracic Intracardiac Monitoring Lines in Pediatric Surgical Patients: A Ten-Year Experience - Gold, J.P.; Jonas, R.A.; Lang, P.; Elixson, E.M.; Mayer, J.E.; Castaneda, A.R. (Annals of Thoracic Surgery, 1986)
A study of 6,690 transthoracic intracardiac monitoring (TIM) catheters in 5,666 pediatric patients undergoing cardiac surgical procedures during a 10-year period demonstrates the safety of this monitoring method. The utility of TIM catheters in patients undergoing a modified Fontan procedure, those undergoing repair of tetralogy of Fallot, and those with elevated or labile pulmonary resistance is stressed. Right atrial (RA) and left atrial (LA) catheters are particularly safe; they have a low incidence of bleeding complications (RA = 0%, LA = 0.13%) and retention complications (RA = 0.15%, LA = 0.63%). Pulmonary artery (PA) catheters that are introduced through the right ventricular infundibulum have higher complication rates (1.07%); unpredictable hemodynamic compromise occurs in approximately 0.5% of such patients. PA catheters placed through the wall of the atrium have a lower complication rate—approximately equal to that for RA and LA catheters. The benefits of TIM catheters far outweigh the associated risks if care is exercised in placing and removing them, and if complications are rapidly recognized and aggressively managed. The continued use of TIM catheters in pediatric cardiac surgical patients is therefore strongly recommended. © 1986, The Society of Thoracic Surgeons. All rights reserved.

Radionuclide measurement of left ventricular ejection fraction in tricuspid atresia - Baker, E.J.; Jones, O.D.H.; Joseph, M.C.; Maisey, M.N.; Tynan, M.J. (British Heart Journal, 1984)
In 15 patients with tricuspid atresia and one with tricuspid stenosis the left ventricular ejection fraction was measured by equilibrium gated radionuclide angiography and the results compared with those from a control group of 16 patients. The patients with tricuspid atresia had a significantly depressed ejection fraction. Those who had a surgical shunt or who had had pulmonary artery banding had significantly lower ejection fractions than the remainder. There was no significant correlation between the ejection fraction and age, the arterial oxygen saturation, or the haemoglobin concentration. Five patients were also studied during isometric exercise; three had an abnormal response. Volume overload of the ventricle is identified as one cause of the dysfunction, but other factors may be important. Radionuclide angiography offers a non-invasive method of studying ventricular function in this condition.

Cyanotic congenital heart disease with decreased pulmonary blood flow - Uzark, K. (Nursing Clinics of North America, 1984)
In the past two decades, long-term survival of patients with cyanotic congenital heart disease has dramatically improved. After successful intracardiac repair, many patients can anticipate a normal lifestyle. Health care providers must increase their knowledge of the nature and effects of surgical intervention, the presence, type, and extent of the patient's postoperative residua and sequelae, and the patient's psychosocial adjustment. Prompt surgical intervention and comprehensive follow-up with early identification and treatment of problems will further enhance both survival of patients born with cyanotic heart disease and the quality of life they achieve in the future.

CT diagnosis of false aneurysm of the pulmonary artery not demonstrated by angiography - Shin, M.S.; Ceballos, R.; Bini, R.M.; Ho, K.-J. (Journal of Computer Assisted Tomography, 1983)
A 17-year-old patient with tricuspid atresia, palliatively corrected by a right Glenn and a left Potts anastomosis during his early childhood and a banding of the left pulmonary artery 6 years ago, developed a false aneurysm of the left pulmonary artery secondary to the erosion of the band fabric through the vascular wall with subsequent thrombosis, infection, and leakage. The diagnosis was confused by both chest roentgenography and angiography but was accurately made by postcontrast computed tomography (CT). We stress the importance and usefulness of CT in the diagnosis of a false aneurysm, not demonstrated by angiography. © 1983 Raven Press, New York.
Keywords: Computed tomography; Pseudoaneurysm, pulmonary artery; Pulmonary arteries

Managment of tricuspid atresia with orally administered prostaglandin E2 - Coe, J.Y.; Radley-Smithr, R.; Yacoub, M. (The Journal of Pediatrics, 1982)

Ventricular volume characteristics of single ventricle before corrective surgery - Shimazaki, Y.; Kawashima, Y.; Mori, T.; Kitamura, S.; Matsuda, H.; Yokota, K. (The American Journal of Cardiology, 1980)
With use of biplane cineangiocardiograms, ventricular cavity volume measurements were determined in 17 patients with single ventricle, before total correction. There were 4 patients with a single left and 13 with a single right ventricle. Atrioventricular (A-V) valve regurgitation was evident in 6 of 13 patients with a common A-V valve. End-diastolic volume index ranged from 72 to 282 ml/m2 (average 131 ml/m2), and these values ranged from 71 to 206 percent (average 110 percent) of the sum of the normal left and right ventricular end-diastolic volumes. Ejection fraction averaged 0.55. There was no significant difference in ventricular cavity volume characteristics and ventricular function between patients with single left and single right ventricle. The single ventricle ejects blood to both the systemic and the pulmonary circulatory beds. There was a high correlation of end-diastolic volume index with pulmonary to systemic flow ratio (r = +0.89, p < 0.001). This observation indicates that the major factor affecting ventricular cavity volume in single ventricle is pulmonary blood flow and a systemic to pulmonary arterial shunt should increase the ventricular cavity volume. Ventricular function of single ventricle was depressed. The ejection fraction of patients with A-V valve regurgitation averaged 0.49, which was significantly lower than that (0.58) of patients without regurgitation (p < 0.05). A-V valve regurgitation was also a factor that increased ventricular cavity volume, although the ventricular function became more depressed. © 1980.

Association of Atrioventricular Valve Atresia with Single Ventricle, Truncus Arteriosus Communis and Transposition: A Basic Reorientation in the Approach to the Definition of Congenital Heart Defects - Shakibi, J.G.; Aryanpur, I.; Nazarian, I.; Siassi, B. (Japanese Heart Journal, 1978)
A heart specimen is presented which showed a rare combination of atrioventricular valve atresia with single ventricle, truncus arteriosus communis with an anteriorly placed trunk, ie transposition. Because of the problems involved in the classification of this heart, the types of single ventricle are revised with particular attention to the rare cases of atrioventricular valve atresia and single ventricle reported in the literature. Also the rare type of truncus arteriosus communis with trunco-atrioventricular valve discontinuity is excluded from the so-called transposition complexes, and properly classified as a form of truncus. The literal meaning of transposition is stressed and it is urged to approach congenital heart defects in a purely anatomic sense with definition of each segment as accurately as possible. Thus the present confusion in terminology and further plethora of new terms are avoided. © 1978, International Heart Journal Association. All rights reserved.
Keywords: Common ventricle; Congenetal heart disease; Mitral atresia

Tricuspid atresia with dextroversion: a not very rare combination - Cokkinos, D.V.; Plessas, S.T.; Tolis, G.; Voridis, E.M. (Journal of Thoracic and Cardiovascular Surgery, 1974)
A case of tricuspid atresia with pulmonic stenosis, ventricular septal defect, and normally related great vessels with dextroversion was correctly diagnosed. The patient was treated successfully with a Glenn operation. The association of this complex of congenital defects with dextroversion has not been stressed adequately in the literature. It is emphasized that, in cases of dextroversion with cyanosis, tricuspid atresia should always be suspected.

Single ventricle and pulmonary stenosis. Surgical management in a patient over a period of 25 years - Anagnostopoulos, C.E.; Coleman, P.G.; Taussig, H.B.; Resnekov, L.; Cassels, D.E. (The American Journal of Cardiology, 1973)
One of the longest living survivors of the Blalock-Taussig shunt is a patient with a complex form of cyanotic congenital heart disease, including a single ventricle (anatomically right), d-loop, anterior aorta, pulmonary valvular and subvalvular stenosis and anomalous pulmonary venous return to a common atrial chamber. A Blalock shunt was performed at age 21 months, a Potts anastomosis at age 9 years, and an 8 mm Dacron shunt was added between the ascending aorta and the pulmonary artery at age 24 years. The patient's arterial oxygen saturation level of 86 percent and his relative well-being and active life at age 26 years suggest that sequential aortopulmonary shunting with increasing age is desirable in some patients with complicated heart disease and severe polycythemia. © 1973 Dun · Donnelley Publishing Corporation 666 Fifth Avenue, New York, New York 10019 All rights reserved.

Clinical features of single ventricle with congenitally corrected transposition - Morgan, A.D.; Krovetz, L.J.; Bartley, T.D.; Green Jr., J.R.; Shanklin, D.R.; Wheat Jr., M.W.; Schiebler, G.L. (The American Journal of Cardiology, 1966)
Nine patients with a single ventricle and the great vessel arrangement of congenitally corrected transposition are reviewed to emphasize the different clinical pictures which may be seen. Physical findings are not characteristic. Cyanosis is not always clinically detectable. Variable systolic murmurs are always present, but the most striking auscultatory finding, not stressed previously, is a decrescendo diastolic murmur of pulmonary insufficiency. Electrocardiographic features characteristic of congenitally corrected transposition of the great vessels include some type of arrhythmia, abnormal P waves, a Qr or QS pattern in lead aVR, and reversal of the normal precordial QRS pattern with a Q wave in leads V3R or V1 and no Q wave in V6 or V7. These findings, however, do not allow a distinction between cases with a single ventricle and those with other associated cardiac defects. Characteristic roentgenologic features of congenitally corrected transposition include a narrow cardiac base, a straight or slightly convex left upper cardiac border with absence of a definite pulmonary artery segment, an unusually cephalad position of the right pulmonary hilar shadows, a "waterfall" configuration of the dilated and tortuous right pulmonary artery, a huge main pulmonary artery causing an indentation on the left side of the barium filled esophagus, and a prominent shadow in the right superior mediastinum representing the displaced superior vena cava. These findings, although present in the majority of patients in this series, are not different from those found in cases of congenitally corrected transposition and two ventricles and a large ventricular septal defect. Cardiac catheterization and angiocardiography confirm the great vessel arrangement of corrected transposition and a bidirectional shunt in a ventricle whose systolic pressure is at systemic levels. Selective ventricular or subaortic angiocardiography is highly desirable to distinguish patients with a single ventricle in which a subaortic infundibular chamber is present from those with congenitally corrected transposition and two ventricles with a large ventricular septal defect. Although complete surgical correction of a single ventricle is not yet possible, pulmonary artery banding in patients with a large pulmonary blood flow may be a feasible palliative procedure. © 1966.

Gastrostomy. Its inception and evolution - Cunha, F. (The American Journal of Surgery, 1946)
Among the writing craft there exists a motto: "If you steal from one author, it is plagiarism; if you steal from many, it is research.". In the realm of psychology probably lies the explanation of a type of conduct one finds so consistently present in the evolution of some particular surgical technic. So consistently and even persistently does one find it that it cannot by any chance be attributed to mere coincidence. To the non-psychologist, but one having some experience in the detached scrutiny of the ways of human conduct there is only one explanation. A terrifically frustrated ego exists which drives eternally for expression, for a labeling or attachment of self by way of name to something-in medical and surgical parlance-some step in treatment or procedure in surgical technic, that the individual hopes may go down into posterity, thereby perhaps justifying one's having passed through this cosmos called world. This seems to be a part of the makeup of so many men in the field of medicine. How else can one explain the making of an incision a half inch or so to this side or that side and calling it a "new method"; or reversing a suture line, starting at the top or vice versa at the bottom, or the accidental happening upon some procedure, which some less fortunate colleague used years before, and then rushing into print with a grand flourish, "a new method.". One sees this type of thing so much in a search or study of the medical literature of the past that one becomes stonily cynical and rather hard boiled in approach to anything labeled "a new." However, as a matter of historical accuracy it behooves some of us to scan with a degree of honesty, yet critically current contemporary claims to priority in these so-called "new methods" of doing this or that. Medical achievement has been gradual and step by step. This is as it should be. One person here makes an observation and records it. Fortunate indeed that it should be this way. In another place some one tries it, and possibly finds it wanting and strives to improve upon it, adding a little something. Somebody else points out some deficiencies and tries to solve them. Thus by an evolution of ideas final perfection may be reached or approached. Medical historians in later years scan these contributions and give priority where it is due because there exists material evidence and corroboration in the printed word-in the original publication-in which the ideas were set forth for the use of the medical world at large. This is particularly well illustrated in the historical evolution of the procedure of gastrostomy. We know and have proof, documented proof, that a military surgeon named Egeberg, in statements before a medical society in Christiania made the following remarks: "I cannot see why the indications should not be just as great to open the intestinal canal to put nourishment in as to open it to take a foreign body out.". We surmise that Egeberg may have been influenced by reading of the experiences of another military surgeon, Wm. Beaumont with "old fistulous Alexis," illustrating to him that a man could live in health with a permanent opening in his stomach. We surmise this because we are aware that Dr. Beaumont's experience was much publicized in Europe and in addition because there exists a certain co-incidence as to dates and time. From here on we find that process of evolutionary step by step improvement upon the original. A French surgeon, Sédillot in 1846, lifts a cone-shaped segment of the anterior wall of the stomach through an abdominal incision and behold you have the first completed operation of gastrostomy. But for reasons mentioned in the body of this article the patients died. Therefore, although the idea is a good one it must be made to work better. Along in 1888, in 1890 and in 1893, three men, Girard, Von Hacker and Jaboulay proposed that instead of bringing the cone of stomach wall directly to the skin through the abdominal wall, it should be brought through the subcutaneous tissues in such manner that the rectus abdominis muscle shall act in a sphincteric manner as to stop leakage around the attachment. Although this was a minor improvement it did not solve the problem of spillage, skin excoriation, etcetra. So we find more names attached to contributions, one Sabanieff, one Hartmann, and a Frank, in the years from 1890 to 1893. These suggested various and sundry complicated passages of a cone or anterior gastric wall through and between the subcutaneous tissues and muscles. One suggested bringing the cone through the skin between the costal cartilages hoping to utilize the latter for sphincteric action. It is important to realize and emphasize that these men all were using a cone of tissue in view of what is coming later. In 1894 and 1902, two men suggested twisting this cone of tissue so that when fastened to the abdominal wall, the torsion of the tissues would obstruct leakage and spillage. These men were Ullmann and Souligoux.28. We return to France and the French school of surgery for the first milestone in evolution oj the operation, and give credit where credit is due. In 1893, Pénières proposed constructing a valve from gastric mucosa to combat leakage, and proceeded to perform the operation on dogs in his laboratory in Toulouse; whereupon another Frenchman, Fontan, not, however, without giving due credit to his countryman, proceeds to perform the operation on humans, differing in technic from his confrere in that he made his valve using all the layers of stomach wall instead of mucosa alone as did Pénières. The operation now consisted of a canal instead of a cone with a valve arrangement to prevent leakage. That was the operation as proposed by Fontan and Pénières, a completed operation, the principles originated and laid down by them and the basis upon which any subsequent minor changes were laid. To these men should go the credit for the development of the procedure. The operation to many was still one which could be improved upon. Here again crops up that curious conduct on the part of the surgical mind. Where one man would propose placing a catheter through a stab wound into the stomach, then plicating the serosa over it by means of one or two purse-string sutures, one would rush into print with "a new method." The "new" consisted of placing first the stab wound a half inch or so higher or lower than the first proposer or instead of one or two layers of purse-string sutures advocating three or four, as providing greater strength to the finished canal, therefore, greater safety. Then along came the men who courageously departed a bit farther and who may have been honest and upright in their thinking and advocacy of their ideas. These were the men who advocated the substitution of other hollow viscera as tubes between the stomach and skin. Such was the isolated pedicled loop of jejunum as advocated by Roux and Lexer and the isolated segment or pedicled loop of transverse colon advocated by Vuillet in 1911, and Kelling in the same year. Somehow one gets an impression that Roux must have been in his seventh heaven playing with loops of intestines, attaching here and there, the more complicated, the more enthusiastic and delighted he was, much as a child with an erector set, but he used gut, instead of blocks or metal. It is a laborious piece of work to read of the different anastamoses he made and proposed. Then along came the men who proposed the construction of tubed pedicled flaps from the stomach wall. Most prominent of these were Dépage and Janeway and both names were used connectedly to describe a technic and procedure originated by Dépage in 1901; but the story goes that Janeway was using and had originated a similar operation, entirely unaware of Dépage's work, so somewhere the idea got abroad that he should be given credit with Dépage and the operation has since been spoken of as the Dépage-Janeway technic. It is curious that Dépage's article describing his procedure appeared in 1901, and Janeway's in 1913, a considerable discrepancy in time. Here again that curious pattern of conduct: Dépage made his tubed flap with the base at the lesser curvature. Janeway made his with the base at the greater curvature, and insisted that his was the better method because it had a better blood supply, at any rate it was a "new method." Watsudjii combined Von Hacker's and Fontan's operations giving them credit while Spivack combined Fontan's and Dépage's operations and described it an "original"-"new method" without allocating proper credits. Then came the tubed flap made by partial severance of the greater curvature of the stomach with the base at cardia and another with base at the fundus. These were: (i) the operation worked out in the laboratory by Alexis Carrell with Beck and called the Carrell-Beck procedure, and (2) the method of Jianu used successfully by Dr. George Pack. It is quite possible that a more detailed and thorough perusal of available literature on the subject of gastrostomy might have brought to light even more material than is quoted here. 29,30 However, over fifty different technics or plans of operation have been published by various authors and the prédominent part of these had "A New Method" as part of their title. However, in the past thirty-five years nothing new has been added to our technical knowledge concerning gastrostomy and no surgeon of recent times, or contemporary to the day is warranted lifting the work of the men who actually made the contribution and applying bis own name to it. Sufficient documentary proof exists in published articles with names and dates to make any such conduct too easy to refute and make a lie. © 1946.